The distribution of coagulation factors VII and VIII and fibrinogen in adults over 65 years. Results from the Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Fried, L P; Heiss, G; Lee, M H; Polak, J F; Psaty, B M; Savage, P J (Ann Epidemiol, 1992)
The Cardiovascular Health Study (CHS) was designed to examine cardiovascular disease and its risk factors in older adults. We report here the distributions of the coagulation factors fibrinogen, factor VII, and factor VIII in a population-based cohort of men and women 65 years or older. In other studies of middle-aged individuals, these factors were shown to be associated with cardiovascular risk. In the CHS cohort, all three factors were elevated, compared to levels reported in middle-aged individuals, and fibrinogen and factor VIII values were higher in each successive age group; factor VII values, in contrast, declined slightly with age in the CHS cohort. Compared to white subjects, blacks had higher values for fibrinogen and factor VIII and lower values for factor VII. While women had markedly higher values for factor VII and factor VIII than men at all ages in the CHS, mean fibrinogen values were not different between men and women.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Middle Aged; Risk Factors

Echocardiographic design of a multicenter investigation of free-living elderly subjects: the Cardiovascular Health Study. - Gardin, J M; Wong, N D; Bommer, W; Klopfenstein, H S; Smith, V E; Tabatznik, B; Siscovick, D; Lobodzinski, S; Anton-Culver, H; Manolio, T A (J Am Soc Echocardiogr, 1992)
The Framingham study has shown by M-mode echocardiography that left ventricular hypertrophy is a powerful, independent predictor for the development of coronary heart disease and that increased left atrial dimension has been associated with an increased risk of stroke. No previous population-based study has evaluated the risk factor correlates and predictive value for coronary heart disease and stroke of two-dimensional and Doppler, as well as M-mode, echocardiography. The Cardiovascular Health Study is a multi-year prospective epidemiologic study of 5201 men and women older than 65 recruited from four geographic sites in the United States. The main objectives of incorporating echocardiography were to determine whether echocardiographic indices, or changes in these indices, are (1) correlated with traditional risk factors for coronary heart disease and stroke; and (2) independent predictors of morbidity and mortality for coronary heart disease and stroke. Echocardiographic measurements of interest include those related to global and segmental left ventricular systolic and diastolic structure and function and left atrial size. For each subject, a baseline echocardiogram was recorded in super-VHS tape using a standard protocol and equipment. All studies were sent to a reading center where images were digitized and measurements were made using customized computer algorithms. Calculated data and images were stored on optical disks to facilitate retrieval and future comparisons in longitudinal studies. A second echocardiogram is scheduled in year 7, with a goal of determining whether changes in cardiac anatomy or function over a 5-year period are important predictors of morbidity or mortality from coronary heart disease and stroke. Quality control measures included standardized training of echocardiography technicians and readers, technician observation by a trained echocardiographer, periodic blind duplicate readings with reader review sessions, phantom studies, and quality control adults.
Keywords: Allied Health Personnel; Cerebrovascular Disorders; Coronary Disease; Echocardiography; Echocardiography, Doppler; Humans; Prospective Studies; Quality Control; Risk Factors; United States

Eligibility for cholesterol referral in community-dwelling older adults. The Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Wahl, P W; Tracy, R P; Borhani, N O; Gardin, J M; Fried, L P; O'Leary, D H; Kuller, L H (Ann Intern Med, 1992)
OBJECTIVES: To assess the proportion of community-dwelling adults aged 65 years or older who are eligible for referral for lipoprotein analysis and intervention according to the National Cholesterol Education Program (NCEP) guidelines. DESIGN: Cross-sectional study based on examinations and questionnaires collected in 1989 and 1990. SETTING: Four communities in the U.S. in the Cardiovascular Health Study (CHS), a study of risk factors for heart disease and stroke in older adults. PARTICIPANTS: A sample of 4810 men and women ages 65 to 100 randomly selected and recruited from Health Care Financing Administration Medicare eligibility lists for the four communities; not institutionalized, not wheelchair-bound, not currently receiving therapy for cancer, not currently taking lipid-lowering medications, and not having eaten in the preceding 9 hours. MEASUREMENTS: Total cholesterol and lipoprotein analysis measured in all participants. RESULTS: Total cholesterol levels were less than 5.17 mmol/L (200 mg/dL) in 37% of participants, 5.17 to 6.19 mmol/L (200 to 239 mg/dL) in 39%, and 6.20 mmol/L (240 mg/dL) or greater in 24%. Compared with their counterparts, older participants, especially those over 80 years of age, were more likely to have levels below 5.17 mmol/L, as were men, nonwhites, and those with coronary heart disease or two or more coronary heart disease risk factors (P less than 0.008 for all values). Based on this screening measurement, 2174 participants were eligible for lipoprotein analysis, 80% were eligible for dietary or drug therapy using NCEP guidelines. Overall, 46% of CHS participants were eligible for lipoprotein analysis and 36% for intervention by NCEP guidelines, based on a single cholesterol measurement. CONCLUSION: A substantial proportion of older adults in this community sample were eligible for lipoprotein analysis and intervention. Prospective studies of elderly persons are needed to determine the risk for incident coronary heart disease according to NCEP classifications and the benefits of lipid-lowering treatments in persons in this age group so that intervention strategies may best be targeted to an appropriately high-risk group.
Keywords: Age Factors; Aged; Aged, 80 and over; Cerebrovascular Disorders; Cholesterol, LDL; Coronary Disease; Eligibility Determination; Female; Humans; Hypercholesterolemia; Longitudinal Studies; Male; Primary Prevention; Referral and Consultation; Risk Factors; United States

Lipoprotein lipids in older people. Results from the Cardiovascular Health Study. The CHS Collaborative Research Group. - Ettinger, W H; Wahl, P W; Kuller, L H; Bush, T L; Tracy, R P; Manolio, T A; Borhani, N O; Wong, N D; O'Leary, D H (Circulation, 1992)
BACKGROUND: Cardiovascular disease is the leading cause of death and disability in older people. There is little information about the distributions of risk factors in older populations. This article describes the distribution and correlates of lipoprotein lipids in people greater than or equal to 65 years old. METHODS AND RESULTS: Lipoprotein lipid concentrations were measured in 2,106 men (M) and 2,732 women (F) who were participants in the Cardiovascular Health Study, a population-based epidemiological study. Distributions of lipids by age and sex and bivariate and multivariate relations among lipids and other variables were determined in cross-sectional analyses. Mean concentrations of lipids were cholesterol: M, 5.20 +/- 0.93 mmol/l (201 +/- 36 mg/dl) and F, 5.81 +/- 0.98 mmol/l (225 +/- 38 mg/dl); triglyceride (TG): M, 1.58 +/- 0.85 mmol/l (140 +/- 75 mg/dl) and F, 1.57 +/- 0.78 mmol/l (139 +/- 69 mg/dl); high density lipoprotein cholesterol (HDL-C): M, 1.23 +/- 0.33 mmol/l (48 +/- 16 mg/dl), and F, 1.53 +/- 0.41 mmol/l (59 +/- 16 mg/dl); low density lipoprotein cholesterol (LDL-C): M, 3.27 +/- 0.85 mmol/l (127 +/- 33 mg/dl) and F, 3.57 +/- 0.93 mmol/l (138 +/- 36 mg/dl). The total cholesterol to HDL-C ratios were M, 4.49 +/- 1.29 and F, 4.05 +/- 1.22. TG, total cholesterol, and LDL-C concentrations were lower with increasing age, the last more evident in men than in women. TG concentration was positively associated with obesity (in women), central fat patterning, glucose intolerance, use of beta-blockers (in men), and use of estrogens (in women) and negatively associated with age, renal function, alcohol use, and socioeconomic status. In general, HDL-C had opposite relations with these variables, except that estrogen use was associated with higher HDL-C concentrations. LDL-C concentration was associated with far fewer variables than the other lipids but was negatively associated with age in men and women and positively correlated with obesity and central fat patterning and negatively correlated with renal function and estrogen use in women. There were no differences in total cholesterol and LDL-C concentrations among participants with and without prevalent coronary heart disease and stroke, but TG concentration was higher and HDL-C lower in men with both coronary heart disease and stroke and in women with coronary heart disease. CONCLUSIONS: Cholesterol and cholesterol/HDL-C ratio were lower and HDL-C higher than previously reported values in older people, suggesting that lipid risk profiles may be improving in older Americans. TG and HDL-C concentrations, and to a lesser extent LDL-C, were associated with potentially important modifiable factors such as obesity, glucose intolerance, renal function, and medication use.
Keywords: Aged; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol, HDL; Cholesterol, LDL; Cross-Sectional Studies; Female; Health Status; Humans; Lipids; Lipoproteins; Male; Multivariate Analysis; Triglycerides

Major electrocardiographic abnormalities in persons aged 65 years and older (the Cardiovascular Health Study). Cardiovascular Health Study Collaborative Research Group. - Furberg, C D; Manolio, T A; Psaty, B M; Bild, D E; Borhani, N O; Newman, A; Tabatznik, B; Rautaharju, P M (Am J Cardiol, 1992)
Electrocardiographic abnormalities are often found in older patients, but their prevalence in free-living elderly populations is not well-defined. In addition, the clinical significance of many of these abnormalities is uncertain. The prevalence of major electrocardiographic abnormalities was determined in 5,150 adults aged greater than or equal to 65 years from the Cardiovascular Health Study--a study of risk factors for stroke and coronary heart disease in the elderly. Ventricular conduction defects, major Q/QS waves, left ventricular hypertrophy, isolated major ST-T-wave abnormalities, atrial fibrillation and first-degree atrioventricular block were collectively categorized as major electrocardiographic abnormalities. Prevalence of any major electrocardiographic abnormality was 29% in the entire cohort, 19% among 2,413 participants who reported no history of coronary artery disease or systemic hypertension, and 37% among 2,737 participants with a history of coronary artery disease or hypertension. Prevalence of major electrocardiographic abnormalities was higher in men than in women regardless of history, and tended to increase with age. Major Q/QS waves were found in 5.2%, and more than half were in those who did not report a previous myocardial infarction. Major electrocardiographic abnormalities are common in elderly men and women irrespective of the history of heart disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Arrhythmias, Cardiac; Chi-Square Distribution; Electrocardiography; Female; Heart Diseases; Humans; Logistic Models; Male; Prevalence; Risk Factors; Sex Factors; United States

Orthostatic hypotension in older adults. The Cardiovascular Health Study. CHS Collaborative Research Group. - Rutan, G H; Hermanson, B; Bild, D E; Kittner, S J; LaBaw, F; Tell, G S (Hypertension, 1992)
The purpose of the present study was to assess the prevalence of orthostatic hypotension and its associations with demographic characteristics, cardiovascular risk factors and symptomatology, prevalent cardiovascular disease, and selected clinical measurements in the Cardiovascular Health Study, a multicenter, observational, longitudinal study enrolling 5,201 men and women aged 65 years and older at initial examination. Blood pressure measurements were obtained with the subjects in a supine position and after they had been standing for 3 minutes. The prevalence of asymptomatic orthostatic hypotension, defined as 20 mm Hg or greater decrease in systolic or 10 mm Hg or greater decrease in diastolic blood pressure, was 16.2%. This prevalence increased to 18.2% when the definition also included those in whom the procedure was aborted due to dizziness upon standing. The prevalence was higher at successive ages. Orthostatic hypotension was associated significantly with difficulty walking (odds ratio, 1.23; 95% confidence interval, 1.02, 1.46), frequent falls (odds ratio, 1.52; confidence interval, 1.04, 2.22), and histories of myocardial infarction (odds ratio, 1.24; confidence interval, 1.02, 1.50) and transient ischemic attacks (odds ratio, 1.68; confidence interval, 1.12, 2.51). History of stroke, angina pectoris, and diabetes mellitus were not associated significantly with orthostatic hypotension. In addition, orthostatic hypotension was associated with isolated systolic hypertension (odds ratio, 1.35; confidence interval, 1.09, 1.68), major electrocardiographic abnormalities (odds ratio, 1.21; confidence interval, 1.03, 1.42), and the presence of carotid artery stenosis based on ultrasonography (odds ratio, 1.67; confidence interval, 1.23, 2.26). Orthostatic hypotension was negatively associated with weight. We conclude that orthostatic hypotension is common in the elderly and increases with advancing age. It is associated with cardiovascular disease, particularly those manifestations measured objectively, such as carotid stenosis. It is associated also with general neurological symptoms, but this link may not be causal. Differences in prevalence of and associations with orthostatic hypotension in the present study compared with others are largely attributed to differences in population characteristics and methodology.
Keywords: Aged; Aging; Dementia; Demography; Female; Health Status; Humans; Hypotension, Orthostatic; Male; Multivariate Analysis; Nervous System Diseases; Prevalence; Risk Factors

Associations of postmenopausal estrogen use with cardiovascular disease and its risk factors in older women. The CHS Collaborative Research Group. - Manolio, T A; Furberg, C D; Shemanski, L; Psaty, B M; O'Leary, D H; Tracy, R P; Bush, T L (Circulation, 1993)
BACKGROUND: Postmenopausal estrogen replacement therapy has been associated with favorable levels of cardiovascular disease risk factors, but these associations and the relations between estrogen use and subclinical disease have not been examined in large samples of older women. METHODS AND RESULTS: Present and past estrogen use was ascertained in 2955 women > or = 65 years old in the Cardiovascular Health Study, a study of risk factors for coronary heart disease and stroke in the elderly. Present estrogen use was reported by 12% of these women and past use by an additional 26.5%. Estrogen use (past or present) was strongly associated with lower low-density lipoprotein cholesterol, fibrinogen, glucose, insulin, obesity, and age and higher high-density lipoprotein cholesterol and socioeconomic status (all P < .0001). Estrogen users also had lower levels of subclinical disease as measured by carotid intimal-medial thickness, carotid stenosis grade, ECG left ventricular mass, and Doppler mitral peak flow velocities (each P < .02). Relations were similar in younger and older women (65 to 74 versus > or = 75 years) and smokers and nonsmokers and were unchanged after women with poor medication compliance were excluded. After adjustment for other factors, estrogen use was associated with decreased carotid wall thickness, although this association was of borderline significance after further adjustment for lipids. CONCLUSIONS: Postmenopausal estrogen use in this sample of older women was associated with favorable cardiovascular disease risk factor profiles and with lower measures of subclinical disease. These findings suggest that postmenopausal estrogen use may be associated with lower risk of cardiovascular disease in women well into the eighth decade of life.
Keywords: Aged; Aging; Cardiovascular Diseases; Carotid Arteries; Carotid Stenosis; Electrocardiography; Estrogen Replacement Therapy; Female; Heart; Heart Ventricles; Humans; Patient Compliance; Risk Factors; Smoking; Ultrasonography

Epidemiology of low cholesterol levels in older adults. The Cardiovascular Health Study. - Manolio, T A; Ettinger, W H; Tracy, R P; Kuller, L H; Borhani, N O; Lynch, J C; Fried, L P (Circulation, 1993)
BACKGROUND: Low cholesterol levels have been associated with increased mortality from stroke, cancer, and other noncardiovascular diseases, but the reasons for this association remain unclear. One explanation is that persons with low cholesterol levels have early or occult disease that eventually leads to their deaths. METHODS AND RESULTS: This possibility was explored in 2,091 men and 2,714 women 65-100 years old in the Cardiovascular Health Study, a multicenter observational study of risk factors for heart disease and stroke in older adults. Cholesterol levels < or = 160 mg/dL were present in 11.6% of men and 3.7% of women and increased in prevalence with age. After adjustment for age, total cholesterol levels in this range were associated with a twofold increased prevalence of treated diabetes in men and women and with a twofold increased prevalence of cancer diagnosed in the preceding 5 years in women only. Low cholesterol was also associated with lower levels of hemoglobin, albumin, and factor VII, suggesting a link with hepatic synthetic function. On multivariate analysis, factors most strongly associated with low cholesterol levels in men and women were decreased factor VII levels, decreased albumin, and diabetes. CONCLUSIONS: Cross-sectional associations with low cholesterol levels differ by sex and suggest poorer health by some measures. The observed relations with treated diabetes and impaired hepatic synthetic function should be examined for risk of mortality in longitudinal data from this and other observational studies.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol; Female; Health Status; Humans; Longitudinal Studies; Male; Prevalence; Probability; Regression Analysis; Risk Factors

Prevalence of cardiovascular diseases among older adults. The Cardiovascular Health Study. - Mittelmark, M B; Psaty, B M; Rautaharju, P M; Fried, L P; Borhani, N O; Tracy, R P; Gardin, J M; O'Leary, D H (Am J Epidemiol, 1993)
The Cardiovascular Health Study is a population-based longitudinal study of 5,201 adults aged 65 years and older. Prevalences of myocardial infarction, angina pectoris, congestive heart failure, peripheral artery disease, stroke, and transient ischemic attack were ascertained between June 1989 and May 1990 in participants recruited from Forsyth County, North Carolina; Washington County, Maryland; Sacramento County, California; and Pittsburgh, Pennsylvania. A medical history was taken to obtain self-reports of prevalent disease. For all participants, use of nitrates was ascertained to document angina, electrocardiograms were used to document prevalent myocardial infarction, and ankle-arm blood pressure studies were used to document peripheral artery disease. Self-reports of disease that were not confirmed by examination findings were further investigated by examination of medical records. Reported disease that was confirmed by examination findings or by medical records was classified as "definite." Disease that was documented by examination, but not reported by the participant, was classified as "unreported." The prevalence rates of definite myocardial infarction and angina were 11% and 15%, respectively, among men aged 65-69 years, 18% and 17% among men aged 80-84 years, 4% and 8% among women aged 65-69 years, and 3% and 13% among women aged 80-84 years. Twenty-three percent of men and 38% of women with electrocardiographic evidence of myocardial infarction did not report it. These results suggest that prevalent disease estimates based only on self-report may underestimate the prevalence of cardiovascular diseases in older Americans.
Keywords: Age Factors; Aged; Aged, 80 and over; Bias; California; Cardiovascular Diseases; Electrocardiography; Female; Health Surveys; Humans; Longitudinal Studies; Male; Maryland; Mass Screening; North Carolina; Pennsylvania; Population Surveillance; Prevalence; Reproducibility of Results

Recruitment of adults 65 years and older as participants in the Cardiovascular Health Study. - Tell, G S; Fried, L P; Hermanson, B; Manolio, T A; Newman, A B; Borhani, N O (Ann Epidemiol, 1993)
Few large-scale epidemiologic studies have enrolled older adults; hence, little is known about the feasibility of recruiting this group for long-term population-based studies. In this article we present the recruitment experience of the Cardiovascular Health Study (CHS), a population-based, longitudinal study of cardiovascular diseases in adults 65 years and older. Participants were sampled from the Health Care Financing Administration's (HCFA) Medicare eligibility lists in four US communities. Letters were mailed to 11,955 sampled individuals. Persons recruited were required to complete an extensive home interview and then a 4-hour in-clinic examination. Excluded were persons who were expected to be able to complete the baseline examination and who were not expected to return for the 3-year follow-up. Some 3654 participants were recruited from those randomly selected from the Medicare sampling frame. In addition, 1547 other age-eligible persons living in the household with the sampled individuals also participated, yielding a total of 5201 participants. Of those who were contacted, 9.6% were ineligible and 34.9% refused participation. Among those eligible, 38.6% refused and 57.3% were enrolled (the remaining did not refuse but were not enrolled before the recruitment ended). Data from a subsample indicate that compared to those who were ineligible or who refused, enrolled participants were younger, more highly educated, more likely to be married, and less likely to report limitations in activity. Compared to those who were eligible but refused, enrolled participants were less likely to have high blood pressure and stroke and more likely to have quit smoking and to perceive their health status as very good or excellent.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Epidemiologic Methods; Female; Humans; Male

Sonographic evaluation of carotid artery atherosclerosis in the elderly: relationship of disease severity to stroke and transient ischemic attack. - Polak, J F; O'Leary, D H; Kronmal, R A; Wolfson, S K; Bond, M G; Tracy, R P; Gardin, J M; Kittner, S J; Price, T R; Savage, P J (Radiology, 1993)
Doppler and real-time ultrasound (US) were performed to evaluate the extent of atherosclerotic changes in the carotid artery and to assess their relationship to prevalent cerebrovascular disease. Real-time US scans and Doppler measurements of the carotid arteries were analyzed in 5,201 subjects aged 65 years or older. Severity of atherosclerotic lesions was associated with increased frequencies of hyperechoic, irregular, and heterogeneous textured lesions (P < .0001). The severity of internal carotid artery stenosis was associated with thickening of the intima-media layer of the common carotid artery wall (r = .37, P < .0001). A history of stroke and transient ischemic attack (TIA) was more likely when hyperechoic, heterogeneous, and irregular lesions were seen in the carotid artery. Internal carotid artery stenosis correlated better with prevalent stroke and TIA than did sonographic descriptions of plaque texture. However, the prevalence of hyperechoic, heterogeneous, and irregular lesions increased as the degree of internal carotid stenosis increased. On real-time images alone, the average of the internal carotid artery maximal wall thickness is the sonographic measure of atherosclerosis that enables the best prediction of prevalent stroke and TIA.
Keywords: Aged; Arteriosclerosis; Carotid Artery Diseases; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Female; Humans; Ischemic Attack, Transient; Male; Ultrasonography

Temporal patterns of antihypertensive medication use among elderly patients. The Cardiovascular Health Study. - Psaty, B M; Savage, P J; Tell, G S; Polak, J F; Hirsch, C H; Gardin, J M; McDonald, R H (JAMA, 1993)
OBJECTIVES: To estimate the incidence of newly treated hypertension and to describe the patterns of antihypertensive medication use among those aged 65 years and older. DESIGN: Medicare eligibility lists from four US communities (Forsyth County, North Carolina; Washington County, Maryland; Sacramento County, California; and Pittsburgh, Pa) were used to obtain a representative sample of 5201 community-dwelling elderly for the Cardiovascular Health Study, a prospective cohort study of risk factors for coronary heart disease and stroke. Participants were examined at baseline and again 1 year later. The two examinations included standardized questionnaires, blood pressure measurements, and the assessment of medication use by medication inventory. In this cohort analysis, we excluded 231 subjects (4.4%) who did not return for follow-up, 69 (1.3%) who had missing data for medications, and another 495 (9.5%) who were taking "antihypertensive" medications for an indication other than high blood pressure. INTERVENTIONS: None. RESULTS: Among the 4406 participants, 1613 used antihypertensive medications at both visits. Between the two visits, 144 started and 115 stopped antihypertensive therapy. Among nonusers at baseline, the annual incidence of newly treated hypertension was 5.2% in women and 5.6% in men. Due to the number of participants who stopped therapy, the overall prevalence of antihypertensive treatment increased only slightly, from 40.7% to 41.1% in women and from 37.1% to 38.2% in men, during 1 year of follow-up. After adjustment for age, systolic blood pressure, number of antihypertensive drugs, diabetes, and cardiovascular disease, the newly treated hypertensives were about half as likely as the previously treated hypertensives to receive diuretics (odds ratio [OR], 0.59; P = .008) or beta-blockers (OR, 0.52; P = .01); and they were about twice as likely to receive calcium channel blockers (OR, 1.88; P < .004) or angiotensin converting enzyme inhibitors (OR, 2.40; P < .001). A similar pattern of within-person changes over time was apparent among the continuous users. CONCLUSIONS: Between June 1990 and June 1991, physicians were increasingly prescribing angiotensin converting enzyme inhibitors and calcium channel blockers in place of diuretics and beta-blockers for the treatment of hypertension in elderly patients, especially for those just starting therapy.
Keywords: Adrenergic beta-Antagonists; Aged; Analysis of Variance; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cohort Studies; Diuretics; Drug Utilization; Female; Follow-Up Studies; Humans; Hypertension; Linear Models; Logistic Models; Male; Medicare; Practice Patterns, Physicians'; Recurrence; United States; Vasodilator Agents

Cardiac arrhythmias on 24-h ambulatory electrocardiography in older women and men: the Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Rautaharju, P M; Siscovick, D; Newman, A B; Borhani, N O; Gardin, J M; Tabatznik, B (J Am Coll Cardiol, 1994)
OBJECTIVES: This study describes the prevalence and correlates of cardiac arrhythmias in older persons. BACKGROUND: Cardiac arrhythmias are frequent in selected samples of elderly persons, but their prevalence and association with cardiovascular disease and its risk factors have not been examined in a large population-based sample. METHODS: In 1,372 participants in the Cardiovascular Health Study, a population-based study of cardiovascular disease risk factors, 24-h ambulatory electrocardiography was performed. RESULTS: Serious arrhythmias, such as sustained ventricular tachycardia and complete atrioventricular block, were uncommon, but brief episodes of ventricular tachycardia (> or = 3 consecutive ventricular depolarizations) were detected in 4.3% of women and 10.3% of men. Ventricular arrhythmias as a group (excluding ectopic beats < 15/h) were more common in men than in women but were not significantly associated with age. The same patterns were true for bradycardia/conduction blocks. Supraventricular arrhythmias as a group (excluding ectopic beats < 15/h), in contrast, did not differ by gender but were strongly associated with increased age. Multivariate analyses showed associations with arrhythmias to differ by gender, with only one association (increased age and supraventricular arrhythmias) present in both women and men. Ventricular arrhythmias, particularly in men, were associated with a higher prevalence of cardiovascular disease and its risk factors and with subclinical disease, as measured by increased left ventricular mass and impaired left ventricular function. CONCLUSIONS: Arrhythmias are common in the elderly, and their association with cardiovascular disease differs by gender. Although risk related to arrhythmias can only be determined by prospective study, such studies should have adequate power to examine potential gender differences in associations.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Cardiovascular Diseases; Circadian Rhythm; Electrocardiography, Ambulatory; Female; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Sex Factors

Correlates of blood pressure in community-dwelling older adults. The Cardiovascular Health Study. Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Rutan, G H; Kronmal, R A; Bild, D E; Polak, J F; Wong, N D; Borhani, N O (Hypertension, 1994)
Although elevated blood pressure is an important predictor of cardiovascular disease and stroke in the elderly, little information exists on the distribution and risk factor correlates of blood pressure in this group. As part of the Cardiovascular Health Study, a population-based cohort study of 5201 men and women aged 65 to 101 years, we investigated correlates of systolic and diastolic blood pressure. Multiple regression analyses were conducted for all participants and a subgroup of 2482 without coronary heart disease and not on antihypertensive therapy (the "healthier" subgroup). In the total group, independent predictors of diastolic blood pressure included heart rate, aortic root dimension, creatinine, hematocrit, alcohol use, and black race (positive associations) and internal carotid artery wall thickness, mitral early/late peak flow velocity, white blood cell count, cigarette smoking, and age (negative associations). Positive predictors of systolic blood pressure included mitral late peak flow velocity, left ventricular mass, common carotid artery wall thickness, serum albumin, factor VII, diabetes, alcohol use, and age; negative predictors were coronary heart disease, uric acid, height, and smoking. In the healthier subgroup, positive predictors of diastolic blood pressure included heart rate, hematocrit, serum albumin, creatinine, and body weight, whereas mitral early/late peak flow velocity, serum potassium, smoking, and age inversely related to diastolic pressure. For the same group, common carotid artery wall thickness, left ventricular mass, serum albumin, factor VII, high-density lipoprotein cholesterol, and age were directly related to systolic blood pressure, whereas serum potassium was inversely related. Both systolic and diastolic pressures varied considerably by geographic site.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cohort Studies; Coronary Disease; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; United States

Eating patterns of community-dwelling older adults: the Cardiovascular Health Study. - Kumanyika, S; Tell, G S; Shemanski, L; Polak, J; Savage, P J (Ann Epidemiol, 1994)
We analyzed eating patterns of 4643 adults (1988 men and 2655 women) aged 65 years and older at the time of their enrollment in the Cardiovascular Health Study. Diet was assessed with a qualitative, picture-sort food frequency questionnaire along with supplemental questions on other eating pattern variables. Consumption of high fat foods and low fiber foods was more frequent in older participants, men, minorities, and persons with body mass index > or = 30 kg/m2 and less common among persons who reported following self-prescribed or medically prescribed special diets. Few associations of consumption of specific food groups with disease status were identified. Participants with coronary heart disease, diabetes, hypertension, and cardiovascular disease were significantly more likely to report following a special diet and using low-calorie or low-sodium food products, however. Although the percentage of participants with prevalent disease who reported following special diets was relatively low from a clinical perspective, it was sufficiently high to suggest that controlling for dietary modifications may be important when attempting to identify associations of diet with prevalent disease in older populations.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cerebrovascular Disorders; Demography; Diet; Diet Surveys; Diet, Sodium-Restricted; Female; Humans; Male; Minority Groups; Prospective Studies; Risk Factors; Sex Factors

Relation of smoking with carotid artery wall thickness and stenosis in older adults. The Cardiovascular Health Study. The Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Polak, J F; Ward, B J; Kittner, S J; Savage, P J; Robbins, J (Circulation, 1994)
BACKGROUND: Cigarette smoking has been associated with increased risk of atherosclerotic diseases in hospital-based studies and in studies of middle-aged populations but not in population-based studies of older adults with and without clinical cardiovascular disease. METHODS AND RESULTS: We investigated the relation of smoking to carotid artery atherosclerotic disease, expressed as intimal-medial wall thickness and arterial lumen narrowing (stenosis) measured by ultrasound. Subjects were 5116 older adults participating in the baseline examination of the Cardiovascular Health Study, a community-based study of cardiovascular diseases in older age. With increased smoking there was significantly greater internal and common carotid wall thickening and internal carotid stenosis: current smokers > former smokers > never-smokers; for instance, the unadjusted percent stenosis was 24%, 20%, and 16%, respectively (P < .0001). A significant dose-response relation was seen with pack-years of smoking. These findings persisted after adjusting for other cardiovascular risk factors and were also confirmed when analyses were restricted to those without prevalent cardiovascular disease. The difference in internal carotid wall thickness between current smokers and nonsmokers was greater than the difference associated with 10 years of age among never-smoking participants (0.39 mm versus 0.31 mm). Among all participants, the prevalence of clinically significant (> or = 50%) internal carotid stenosis increased from 4.4% in never-smokers to 7.3% in former smokers to 9.5% in current smokers (P < .0001). CONCLUSIONS: These findings extend previous reports of a positive relation between smoking and carotid artery disease to a population-based sample of older adults using several different indicators of atherosclerotic disease.
Keywords: Aged; Aged, 80 and over; Carotid Arteries; Carotid Stenosis; Cohort Studies; Female; Humans; Male; Smoking; Ultrasonography

Black-white differences in subclinical cardiovascular disease among older adults: the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; Psaty, B M; Newman, A B; Haan, M; Powe, N; Tracy, R P; O'Leary, D H (J Clin Epidemiol, 1995)
Cardiovascular and all-cause mortality are higher in black than white Americans, but racial differences in clinical and subclinical cardiovascular disease (CVD) have not been examined in older adults. Clinical and subclinical CVD and its risk factors were compared in 4926 white and 244 black men and women aged 65 years and older. Black participants had lower socioeconomic status and generally higher prevalences of CVD and its risk factors, except for adverse lipid profiles. Common carotid wall thickness was greater in black than white women, and ankle-arm blood pressure ratios were lower in black women and men (p < 0.01). After adjustment for CVD risk factors, common carotid walls were significantly thicker and ankle-arm ratios were lower in blacks than whites of both sexes, while internal carotid walls were significantly thinner in black women. Racial differences in clinical and subclinical CVD in older adults are similar to those reported in younger populations and do not appear to be explained by CVD risk factors.
Keywords: African Continental Ancestry Group; Aged; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Geriatric Assessment; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Sex Factors

Evidence for inflammation as a cause of hypocholesterolemia in older people. - Ettinger, W H; Harris, T; Verdery, R B; Tracy, R; Kouba, E (J Am Geriatr Soc, 1995)
Keywords: Age Factors; Aged; Analysis of Variance; C-Reactive Protein; Case-Control Studies; Cholesterol; Female; Fibrinogen; Humans; Hypolipoproteinemias; Inflammation; Interleukin-1; Interleukin-6; Male

Fibrinogen and factor VIII, but not factor VII, are associated with measures of subclinical cardiovascular disease in the elderly. Results from The Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J (Arterioscler Thromb Vasc Biol, 1995)
No studies have examined the associations of coagulation factor levels with measures of subclinical cardiovascular disease (CVD) in the elderly. The Cardiovascular Health Study (CHS) is a prospective, population-based cohort study of CVD in persons older than 65 years. At the baseline examination, we measured fibrinogen, factor VII, and factor VIII levels in 5024 of the 5201 participants of the CHS and examined the associations of these coagulation factors with measures of subclinical CVD in a cross-sectional analysis. Subclinical CVD measures were based on electrocardiography, carotid ultrasonography, echocardiography, and ankle-arm blood pressure measurements (AAI). For analyses, we used the full cohort as well as two mutually exclusive subgroups: those with prevalent clinical CVD at baseline and those without. Fibrinogen and to a lesser extent factor VIII showed positive associations with a variety of subclinical CVD measures. In age-adjusted analyses, fibrinogen and factor VIII were significantly associated with 8 of 10 measures. In multivariate analyses, fibrinogen was significantly associated with carotid artery stenosis, internal (but not common) carotid artery wall thickness, and AAI. Factor VIII was associated with abnormal wall motion and AAI in the full cohort only. Factor VII was not consistently associated with subclinical disease measures. In bivariate analyses that included data from all three groups, there were 5 positive subclinical disease associations and 5 negative associations for factor VII. In multivariate analyses, there were no significant associations between factor VII and subclinical CVD in the full cohort or in either subgroup. We conclude that in these cross-sectional analyses, fibrinogen and to a lesser extent factor VIII are associated with subclinical CVD in the elderly, even in those without symptoms or a history of clinical CVD. Factor VII, however, was not associated with subclinical CVD in the elderly.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Humans; Multivariate Analysis; Prospective Studies; Regression Analysis; Risk Factors

Laboratory methods and quality assurance in the Cardiovascular Health Study. - Cushman, M; Cornell, E S; Howard, P R; Bovill, E G; Tracy, R P (Clin Chem, 1995)
The Cardiovascular Health Study is an observational cohort study of risk factors for cardiovascular disease in 5201 participants, ages > or = 65 years. We report the methods and quality-assurance results for blood procurement, processing, shipping, storage, and sample analysis used during the first examination period (May 1989-June 1990). The most frequent difficulty in phlebotomy and processing was the requirement of more than one venipuncture (in 2.6% of the participants). The CVs for control materials ranged from 0.93% for glucose to 10.7% for insulin; most were < 4%. In addition to standard quality-assurance methods, we applied two other methods: technical error calculation for replicates, and weighted linear regression to assess time trend in results of control materials. After outliers were excluded, technical error values ranged from 1.7 for uric acid to 18.8 for insulin. Factor VII and factor VIII had slight trends over the 12-month analysis period. Results of quality-assurance analyses used to resolve problems were successful, thereby improving the second laboratory examination.
Keywords: Aged; Blood Glucose; Blood Specimen Collection; Cardiovascular Diseases; Chemistry, Clinical; Factor VII; Factor VIII; Fibrinogen; Humans; Insulin; Quality Control; Regression Analysis; Triglycerides

Subclinical disease as an independent risk factor for cardiovascular disease. - Kuller, L H; Shemanski, L; Psaty, B M; Borhani, N O; Gardin, J; Haan, M N; O'Leary, D H; Savage, P J; Tell, G S; Tracy, R (Circulation, 1995)
BACKGROUND: The primary aim of the present study was to determine the relation between measures of subclinical cardiovascular disease and the incidence of clinical cardiovascular disease among 5201 adults 65 years of age or older who were participating in the Cardiovascular Health Study. METHODS AND RESULTS: A new method of classifying subclinical disease at baseline examination in the Cardiovascular Health Study included measures of ankle-brachial blood pressure, carotid artery stenosis and wall thickness, ECG and echocardiographic abnormalities, and positive response to the Rose Angina and Claudication Questionnaire. Participants were followed for an average of 2.39 years (maximum, 3 years). For participants without evidence of clinical cardiovascular disease at baseline, the presence of subclinical disease compared with no subclinical disease was associated with a significant increased risk of incident total coronary heart disease including CHD deaths and nonfatal MI and angina pectoris for both men and women. For individuals with subclinical disease, the increased risk of total coronary heart disease was 2.0 for men and 2.5 for women, and the increased risk of total mortality was 2.9 for men and 1.7 for women. The increased risk changed little after adjustment for other risk factors, including lipoprotein levels, blood pressure, smoking, and diabetes. CONCLUSIONS: The measurement of subclinical disease provides an approach for identifying high-risk older individuals who may be candidates for more active intervention to prevent clinical disease.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Female; Humans; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Odds Ratio; Reference Values; Risk Factors

Surveillance and ascertainment of cardiovascular events. The Cardiovascular Health Study. - Ives, D G; Fitzpatrick, A L; Bild, D E; Psaty, B M; Kuller, L H; Crowley, P M; Cruise, R G; Theroux, S (Ann Epidemiol, 1995)
While previous prospective multicenter studies have conducted cardiovascular disease surveillance, few have detailed the techniques relating to the ascertainment of and data collection for events. The Cardiovascular Health Study (CHS) is a population-based study of coronary heart disease and stroke in older adults. This article summarizes the CHS events protocol and describes the methods of surveillance and ascertainment of hospitalized and nonhospitalized events, the use of medical records and other support documents, organizational issues at the field center level, and the classification of events through an adjudication process. We present data on incidence and mortality, the classification of adjudicated events, and the agreement between classification by the Events Subcommittee and the medical records diagnostic codes. The CHS techniques are a successful model for complete ascertainment, investigation, and documentation of events in an older cohort.
Keywords: Aged; Cerebrovascular Disorders; Coronary Disease; Epidemiologic Methods; Female; Hospitalization; Humans; Incidence; Longitudinal Studies; Male; Population Surveillance; Quality Control; United States

Association of fibrinogen and coagulation factors VII and VIII with cardiovascular risk factors in the elderly: the Cardiovascular Health Study. Cardiovascular Health Study Investigators. - Cushman, M; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J; Tracy, R P (Am J Epidemiol, 1996)
The cross-sectional correlates of three hemostatic factors--fibrinogen, factor VII, and factor VIII--were examined in the Cardiovascular Health Study, a population-based cohort study of 5,201 subjects over age 65 years. Subjects were recruited in 1989-1990 in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. In multivariate linear regression models, cardiac risk factors significantly associated with fibrinogen were current smoking, race, lipids, and white blood count. In women, alcohol use, obesity, physical activity, and insulin level were also significant, while in men hypertension was correlated. The significant correlates of factor VII were lipids and white blood count in men and estrogen use, alcohol use, race, lipids, insulin level, white blood count, and obesity in women. The independent correlates of factor VIII were insulin, glucose, and race in both sexes; low density lipoprotein cholesterol, white blood count, and diuretic use in men; and alcohol use in women. In multivariate models, factors known to be modifiable risk factors for cardiovascular disease accounted for more of the population variance of these hemostatic factors in women than in men, especially for factor VII. The hemostatic factors may mediate some effects of risk factors on disease, and this should be considered in longitudinal studies.
Keywords: Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Linear Models; Logistic Models; Male; Prevalence; Risk Factors; Sex Distribution; United States

Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking

Compensatory increase in common carotid artery diameter. Relation to blood pressure and artery intima-media thickness in older adults. Cardiovascular Health Study. - Polak, J F; Kronmal, R A; Tell, G S; O'Leary, D H; Savage, P J; Gardin, J M; Rutan, G H; Borhani, N O (Stroke, 1996)
BACKGROUND AND PURPOSE: Common carotid artery (CCA) diameter is thought to increase as a consequence of hypertension and may increase as the thickness of the arterial wall increases. The purpose of this study was to determine CCA dimensions and correlate them with clinical features. METHODS: We performed a cross-sectional, community-based study of adults 65 years of age and older, measuring inner and outer diameter of the CCA in vivo with carotid sonography. Findings were correlated against risk factors for atherosclerosis, CCA intima-media thickness (IMT), and echocardiographically determined left ventricular (LV) mass. RESULTS: Independent variables showing strong positive associations with outer and inner CCA diameter included age, male sex, height, weight, and systolic blood pressure. As an independent variable, LV mass (r = .40 and r = .37, respectively; P < .00001) had a strong positive relation to inner and outer CCA diameters. The relationship between diameter and IMT was different. In a model that controlled for age, sex, and estimated LV mass, an increase of 1 mm in CCA IMT corresponded to a 1.9 mm increase in the outer diameter of the artery (P < .00001) but was not significantly related to the inner diameter (slope = +0.07 mm; P = .26). CONCLUSIONS: Increase in the outer diameter of the CCA is associated with subject size, sex, age, echocardiographically estimated LV mass, and CCA IMT. Increases in internal diameter of the CCA have similar relationships but are not related to IMT. This supports the hypothesis that the human CCA dilates as the thickness of the artery wall increases.
Keywords: Aged; Blood Pressure; Carotid Artery, Common; Cross-Sectional Studies; Echocardiography; Female; Heart Ventricles; Humans; Hypertension; Male; Tunica Intima; Tunica Media

Correlates of thrombin markers in an elderly cohort free of clinical cardiovascular disease. - Cushman, M; Psaty, B M; Macy, E; Bovill, E G; Cornell, E S; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1996)
Studies suggest that thrombosis is important in the progression of atherosclerotic lesions. The biochemical markers prothrombin fragment 1-2 and fibrinopeptide A reflect in vivo thrombin generation and activity, respectively. As such, they are markers that might be associated with cardiovascular risk. From the Cardiovascular Health Study, a cohort study of 5201 persons over 65 years of age, 399 persons free of clinical cardiovascular disease (CVD) at the baseline examination were selected for study of specialized markers of hemostasis. We report the cross-sectional relationships of the thrombin markers to CVD risk factors and measures of subclinical CVD. The range of fragment 1-2 2 was 0.12 to 0.85 nmol/L. The range of fibrinopeptide A was 0.9 to 44.1 micrograms/L. High levels of fragment 1-2 and fibrinopeptide A were associated with age, with levels higher in women than men. Fragment 1-2 was associated with smoking; high levels of triglyceride, creatinine, and C-reactive protein; and low levels of glucose. Fibrinopeptide A was associated with high C-reactive protein and apolipoprotein(a) and lower ankle-brachial index. There were no significant associations of the thrombin markers with race, fibrinogen, alcohol consumption, diabetes, or most measures of subclinical CVD. Study findings support a hypothesis that there are physiological interrelationships between cardiac risk factors, hemostasis, inflammation, and progression of atherosclerosis.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cohort Studies; Female; Hemostasis; Humans; Male; Risk Factors; Thrombin

Current estrogen-progestin and estrogen replacement therapy in elderly women: association with carotid atherosclerosis. CHS Collaborative Research Group. Cardiovascular Health Study. - Jonas, H A; Kronmal, R A; Psaty, B M; Manolio, T A; Meilahn, E N; Tell, G S; Tracy, R P; Robbins, J A; Anton-Culver, H (Ann Epidemiol, 1996)
The cardioprotective effects of combined estrogen/progestin replacement therapy have been questioned. Therefore, we have compared carotid arterial wall thickening and the prevalence of carotid stenosis in elderly women (> or = 65 years old) currently using replacement estrogen/progestins (E + P) with arterial pathology and its prevalence in women using unopposed estrogens (E). This cross-sectional study used baseline data from all 2962 women participating in the Cardiovascular Health Study, a population-based study of coronary heart disease and stroke in elderly adults. Users of hormone replacement therapy (HRT) were categorized as never (n = 1726), past (n = 787), current E (n = 280), or current E + P (n = 73). Maximal intimal-medial thicknesses of the internal and common carotid arteries and stenosis of the internal carotid arteries were measured by ultrasonography. Current E + P users resembled current E users in most respects, although some lifestyle factors were more favorable among E + P users. Current E + P use and current E use (as compared with no use) were associated with smaller internal carotid wall thicknesses (-0.22 mm; P = 0.003; and -0.09 mm; P = 0.05, respectively) and smaller common carotid wall thicknesses (-0.05 mm; P = 0.03; and -0.02 mm; P = 0.1, respectively) and lower odds ratios (OR) for carotid stenosis (> or = 1% vs. 0%); OR = 0.61; 95% confidence interval [CI]: 0.36 to 1.01; and OR = 0.91, 95% CI: 0.67 to 1.24, respectively), after adjustment for current lifestyle and risk factors. When both groups of current HRT users were compared, there were no significant differences in carotid wall thicknesses or prevalence of carotid stenosis. For this sample of elderly women, both current E + P therapy and current E therapy were associated with decreased measures of carotid atherosclerosis. These measures did not differ significantly between the two groups of HRT users.
Keywords: Aged; Arteriosclerosis; Carotid Arteries; Carotid Stenosis; Cohort Studies; Confidence Intervals; Cross-Sectional Studies; Databases, Factual; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Health Status Indicators; Humans; Odds Ratio; Progestins; Reproductive History; Ultrasonography; United States; Women's Health

Lipoprotein levels in elderly patients with asthma. Cardiovascular Health Study Research Group. - Enright, P L; Lasser, E C; Ward, B J; Tracy, R P (J Allergy Clin Immunol, 1996)
Keywords: Aged; Aging; Arteriosclerosis; Asthma; Female; Humans; Lipoproteins; Male; Prospective Studies; Risk Factors; Sex Factors

Picture-sort method for administering a food frequency questionnaire to older adults. - Kumanyika, S; Tell, G S; Fried, L; Martel, J K; Chinchilli, V M (J Am Diet Assoc, 1996)
OBJECTIVE: To assess the validity of a picture-sort approach to administering the National Cancer Institute food frequency questionnaire to older adults. DESIGN: A picture-sort interview was conducted in each respondent's home. After the picture sort, a 24-hour recall interview was administered on the same occasion. Five additional in-home recall interviews were subsequently conducted at approximately 1-month intervals. SUBJECTS/SETTING: Forty-seven female and 49 male volunteers aged 66 to 100 years were recruited from among Cardiovascular Health Study participants from Maryland and North Carolina. MAIN OUTCOME MEASURES: Estimates from the picture sort and the recall for intakes of macronutrients, cholesterol, fiber, and selected vitamins and minerals exclusive of supplements. STATISTICAL ANALYSES: Comparison of means estimated by the two methods and correlation analyses were used. Correlations were adjusted under varied assumptions about the nature of the information contained in the six 24-hour recalls relative to respondents' usual intakes. RESULTS: After correction for attenuation, Pearson correlation coefficients for macronutrients ranged from .41 for protein to .74 for saturated fat and cholesterol. For vitamins and minerals, correlations ranged from .26 for beta carotene to .62 for calcium. APPLICATIONS: Picture-sort estimates of mean nutrient intakes were comparable with estimates based on 24-hour recalls, and correlations with reference data were similar to those reported in the literature for conventionally administered food frequency questionnaires. This dietary assessment method may, therefore, offer a way to simplify or structure responses to improve ease of administration and increase respondents' liking for the interview without loss of data quality.
Keywords: Aged; Aged, 80 and over; Audiovisual Aids; Data Interpretation, Statistical; Diet Records; Eating; Female; Humans; Interviews as Topic; Male; Mental Recall; Surveys and Questionnaires

Thickening of the carotid wall. A marker for atherosclerosis in the elderly? Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Savage, P J; Borhani, N O; Kittner, S J; Tracy, R; Gardin, J M; Price, T R; Furberg, C D (Stroke, 1996)
BACKGROUND AND PURPOSE: We investigated the relationships between prevalent coronary heart disease (CHD), clinically manifest atherosclerotic disease (ASD), and major established risk factors for atherosclerosis and intima-media thickness (IMT) in the common carotid arteries (CCA) and internal carotid arteries (ICA) separately and in combination in older adults. We wished to determine whether a noninvasive measurement can serve as an indicator of clinically manifest atherosclerotic disease and to determine which of the two variables, CCA IMT or ICA IMT, is a better correlate. METHODS: IMT of the CCA and ICA was measured with duplex ultrasound in 5117 of 5201 individuals enrolled in the Cardiovascular Health Study, a study of the risk factors and the natural history of cardiovascular disease in adults aged 65 years or more. Histories of CHD, peripheral arterial disease, and cerebrovascular disease were obtained during baseline examination. Risk factors included cholesterol levels, cigarette smoking, elevated blood pressure, diabetes, age, and sex. Relationships between risk factors and IMT were studied by multiple regression analysis and canonical variate analysis. Prediction of prevalent CHD and ASD by IMT measurements in CCAs and ICAs were made by logistic regression, adjusting for age and sex. RESULTS: IMT measurements of the CCAs and ICAs were greater in persons with CHD and ASD than those without, even after controlling for sex (P < .001). IMT measurements in the ICA were greater than those in the CCA. Risk factors for ASD accounted for 17% and 18% of the variability in IMT in the CCA and ICA, respectively. These same risk factors accounted for 25% of the variability of a composite measurement consisting of the sum of the ICA IMT and CCA IMT. The ability to predict CHD and ASD was greater for ICA IMT (odds ratio [confidence interval]: 1.36 [1.31 to 1.41] and 1.35 [1.25 to 1.44], respectively) than for CCA IMT (1.09 [1.05 to 1.13] and 1.17 [1.09 to 1.25]). CONCLUSIONS: Whereas CCA IMT is associated with major risk factors for atherosclerosis and existing CHD and ASD in older adults, this association is not as strong as that for ICA IMT. The combination of these measures relates more strongly to existing CHD and ASD and cerebrovascular disease risk factors than either taken alone.
Keywords: Adult; Aged; Arteriosclerosis; Blood Pressure; Carotid Artery, Common; Carotid Artery, Internal; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Electrocardiography; Female; Humans; Male; Medical History Taking; Physical Examination; Prospective Studies; Regression Analysis; Risk Factors; Sex Characteristics; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Carrying the burden of cardiovascular risk in old age: associations of weight and weight change with prevalent cardiovascular disease, risk factors, and health status in the Cardiovascular Health Study. - Harris, T B; Savage, P J; Tell, G S; Haan, M; Kumanyika, S; Lynch, J C (Am J Clin Nutr, 1997)
Measured weight in old age, reported weight at age 50 y, and weight change from age 50 y to old age were studied in association with prevalent cardiovascular disease (CVD), CVD risk factors, and health status in a population of 4954 men and women aged > or = 65 y in the Cardiovascular Health Study (CHS). Heavier weight (i.e., generally weight in the fourth quartile for the cohort) at age 50 y was more closely associated with prevalent CVD than was current weight, with these associations stronger in women than in men. Heavier current weight and heavier weight at age 50 y were associated with cardiovascular risk factors, including higher blood pressure, lower high-density-lipoprotein cholesterol, and higher fasting insulin. Heavier weight at both time points was related to mobility problems in both men and women and to lower current physical activity levels; among women, strong associations were also seen with lower education and current income. Remaining within 10% of reported weight at age 50 y was associated with better health status as measured by reported health, mobility difficulty, number of medications, and prevalent CVD in men. Paradoxically, most cardiovascular risk factors were lowest for weight losers despite an association of weight loss with poorer health. In this cohort of persons aged > or = 65 y, heavier weight was associated with CVD and CVD risk factors, suggesting that prevention of overweight may prove beneficial in improving cardiovascular risk in older persons. Weight stability from age 50 y to old age was associated with better health status than was weight gain or loss.
Keywords: Aged; Blood Pressure; Body Constitution; Body Weight; Cardiovascular Diseases; Cholesterol, LDL; Female; Health Status; Humans; Insulin; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prevalence; Risk Factors; Sex Characteristics

Diabetes mellitus and echocardiographic left ventricular function in free-living elderly men and women: The Cardiovascular Health Study. - Lee, M; Gardin, J M; Lynch, J C; Smith, V E; Tracy, R P; Savage, P J; Szklo, M; Ward, B J (Am Heart J, 1997)
This report describes the relation among diabetes, blood pressure, and prevalent cardiovascular disease, and echocardiographically measured left ventricular mass and filling (transmitral valve flow) velocities in the Cardiovascular Health Study, a cohort of 5201 men and women > or = 65 years of age. Ventricular septal and left posterior wall thicknesses were greater in diabetic than in nondiabetic subjects, showing a significant linear trend (p = 0.025 for ventricular septal thickness in both sexes combined, p = 0.002 for posterior wall thickness) with increased duration of diabetes. Increased wall thickness of the ventricular septum or the left posterior wall was not associated with prevalent coronary heart disease (CHD) in the cohort. Increased left ventricular mass was associated with diabetic persons not reporting CHD and with all subjects with CHD regardless of glucose tolerance status. After adjusting for body weight, blood pressure, heart rate, and prevalent coronary or cerebrovascular disease, diabetes (as measured by glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination) remained an independent predictor of increased left ventricular mass among men and women (174.2 gm in diabetic men vs 169.8 gm in normal men, 138.2 gm in diabetic women vs 134.0 gm in normal women, p = 0.043 for both sexes combined). Both early and late diastolic transmitral peak flow velocities were higher with increased duration of diabetes, but the calculated ratio of the early peak flow velocity to the late velocity (E/A ratio) did not differ significantly between subjects with historical diabetes and those with normal fasting glucose (both genders combined, p = 0.190). Glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination were significant independent predictors of the late transmitral peak flow velocity and its integrated flow-velocity curve but not for the integral of the early peak flow velocity or the E/A ratio. Diabetes is associated with abnormal left ventricular structure and function in elderly persons. This association persists after adjustment for body weight, blood pressure, heart rate, and reported coronary or cerebrovascular disease.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Diabetes Mellitus; Echocardiography; Female; Glucose Tolerance Test; Humans; Male; Mitral Valve; Residence Characteristics; Ventricular Function, Left

Dietary assessment using a picture-sort approach. - Kumanyika, S K; Tell, G S; Shemanski, L; Martel, J; Chinchilli, V M (Am J Clin Nutr, 1997)
Food-frequency questionnaires are usually administered as a list of foods to be checked off by the respondent or interviewer. Techniques in which participants sort into categories cards on which names or pictures of foods are printed can also be used to assess food intake. Food-frequency scores were obtained from a five-category picture sort administered to 4643 men and women aged > or = 65 y in the Cardiovascular Health Study (CHS). This one-step (qualitative) assessment yielded significant associations in expected directions between frequency scores and sex, age, race or ethnicity, body mass index, and use of a special diet. In the two-step (semiquantitative) version of this instrument, an interviewer documented specific frequencies and portion-size information for the foods in each sorting category. A substudy of the two-step version with 96 CHS participants indicated relative validity similar to that of conventionally administered food-frequency questionnaires. The one-step version may be broadly applicable to situations in which general food-pattern data can be informative and cost and time limitations are great. When it is feasible, the two-step picture sort may offer certain methodologic advantages because respondents have a chance to change their responses and the format may simplify the cognitive-response task. Sorting or picture-sort procedures deserve systematic attention in research on dietary assessment methods.
Keywords: Aged; Audiovisual Aids; Diet; Female; Food; Humans; Male; Nutrition Assessment; Surveys and Questionnaires

Left ventricular mass in the elderly. The Cardiovascular Health Study. - Gardin, J M; Arnold, A; Gottdiener, J S; Wong, N D; Fried, L P; Klopfenstein, H S; O'Leary, D H; Tracy, R; Kronmal, R (Hypertension, 1997)
Left ventricular (LV) mass, as estimated from M-mode echocardiography (echo), has previously been shown to be an independent predictor of incident cardiovascular disease morbidity and mortality. We evaluated the relationship at baseline of echo LV mass to relevant cardiovascular disease risk factors and other potential covariates in the Cardiovascular Health Study, multicenter study sponsored by the National Heart, Lung, and Blood Institute of 5201 men and women aged 65 years or older (mean, 73). Two-dimensionally directed M-mode echo LV mass measurements could be obtained in 1357 men and 2053 women (66% of this elderly cohort). Stepwise linear regression analyses of the relationship of echo LV mass to demographic and risk factor, physical activity, electrocardiographic, and prevalent disease variables resulted in a model that explained 37% of the variance for the entire cohort. In order of decreasing importance, factors positively associated with echo LV mass were body weight, male sex, systolic pressure, presence of congestive heart failure, present smoking, major and minor electrocardiographic abnormalities, treatment for hypertension, valvular heart disease, aortic regurgitation by color Doppler, and mitral regurgitation by color Doppler (in men) whereas diastolic pressure, bioresistance (a measure of adiposity), and high-density lipoprotein cholesterol were inversely related to echo LV mass. Although height and weight were both related to LV mass, height added nothing once weight was entered in multiple linear regression analyses. Furthermore, in the multiple regression models, diastolic pressure was inversely and systolic BP positively related to LV mass, with similar magnitudes for their coefficients. In consonance with these findings, pulse pressure was positively related to LV mass in bivariate analyses. Multiple linear regression analyses explained less of the variance for ventricular septal thickness (R2 = .13) and LV posterior wall thickness (R2 = .14) than for LV mass (R2 = .37) and LV diastolic dimension (R2 = .27). Intriguing findings in the elderly Cardiovascular Health Study cohort included the presence of pulse pressure as a positive correlate, and high-density lipoprotein cholesterol as an inverse correlate, of LV mass. Longitudinal studies in the Cardiovascular Health Study cohort will help to clarify the importance of demographic, risk factor, and other variables, and changes in these variables, in predicting changes in echo LV mass and its components as well as the prognostic significance of LV mass in the elderly.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Body Weight; Cardiovascular Diseases; Cohort Studies; Echocardiography; Female; Humans; Hypertrophy, Left Ventricular; Male; Prospective Studies; Risk Factors; Ventricular Function, Left

Lifetime smoking exposure affects the association of C-reactive protein with cardiovascular disease risk factors and subclinical disease in healthy elderly subjects. - Tracy, R P; Psaty, B M; Macy, E; Bovill, E G; Cushman, M; Cornell, E S; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Blood levels of C-reactive protein (CRP), a marker of inflammation, are related to cardiovascular disease risk. To determine cross-sectional correlates in the elderly, we measured CRP in 400 men and women older than 65 years and free of clinical cardiovascular disease at baseline as part of the Cardiovascular Health Study. Only 2% of the values were greater than 10 mg/L, the cut-point usually used to identify inflammation. CRP levels appeared tightly regulated, since there were strong bivariate correlations between CRP and the following: inflammation-sensitive proteins such as fibrinogen (r = .52); measures of fibrinolysis such as plasmin-antiplasmin complex (r = .23); pack-years of smoking (r = .30); and body mass index (r = .24; all P values < or = .001). The association with pack-years was independent of the length of time since cessation of smoking. CRP levels were also associated with coagulation factors VIIc, IXc, and Xc; HDL cholesterol (negative) and triglyceride; diabetes status; diuretic use; ECG abnormalities; and level of exercise. Because of effect modification, two multiple linear regression prediction models were developed for CRP, one each for never smokers and ever smokers. An a priori physiologic model was used to guide these analyses, which disallowed the use of other inflammation-sensitive variables such as fibrinogen. In never smokers, the independent predictors were body mass index (+), diabetes status (+), plasmin-antiplasmin complex (+), and the presence of ECG abnormalities (+); this model predicted 15% of the CRP population variance. In ever smokers, the predictors were body mass index (+), plasmin-antiplasmin complex (+), pack-years of smoking (+), HDL cholesterol (-), and ankle-arm blood pressure index (-); this model predicted 42% of the population variance. We conclude that levels of CRP in the healthy elderly are tightly regulated and reflect lifetime exposure to smoking as well as level of obesity, ongoing level of fibrinolysis, diabetes status, and level of subclinical atherothrombotic disease. Moreover, exposure to smoking affects the relation of CRP to these other factors.
Keywords: Aged; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Risk Factors; Smoking

Relationship of C-reactive protein to risk of cardiovascular disease in the elderly. Results from the Cardiovascular Health Study and the Rural Health Promotion Project. - Tracy, R P; Lemaitre, R N; Psaty, B M; Ives, D G; Evans, R W; Cushman, M; Meilahn, E N; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Markers of inflammation, such as C-reactive protein (CRP), are related to risk of cardiovascular disease (CVD) events in those with angina, but little is known about individuals without prevalent clinical CVD. We performed a prospective, nested case-control study in the Cardiovascular Health Study (CHS; 5201 healthy elderly men and women). Case subjects (n = 146 men and women with incident CVD events including angina, myocardial infarction, and death) and control subjects (n = 146) were matched on the basis of sex and the presence or absence of significant subclinical CVD at baseline (average follow-up, 2.4 years). In women but not men, the mean CRP level was higher for case subjects than for control subjects (P < or = .05). In general, CRP was higher in those with subclinical disease. Most of the association of CRP with female case subjects versus control subjects was in the subgroup with subclinical disease; 3.33 versus 1.90 mg/L, P < .05, adjusted for age and time of follow-up. Case-control differences were greatest when the time between baseline and the CVD event was shortest. The strongest associations were with myocardial infarction, and there was an overall odds ratio for incident myocardial infarction for men and women with subclinical disease (upper quartile versus lower three quartiles) of 2.67 (confidence interval [CI] = 1.04 to 6.81), with the relationship being stronger in women (4.50 [CI = 0.97 to 20.8]) than in men (1.75 [CI = 0.51 to 5.98]). We performed a similar study in the Rural Health Promotion Project, in which mean values of CRP were higher for female case subjects than for female control subjects, but no differences were apparent for men. Comparing the upper quintile with the lower four, the odds ratio for CVD case subjects was 2.7 (CI = 1.10 to 6.60). In conclusion, CRP was associated with incident events in the elderly, especially in those with subclinical disease at baseline.
Keywords: Aged; Aging; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Male; Prospective Studies; Sex Factors

Tumor necrosis factor-alpha-angiotensin interactions and regulation of blood pressure. - Ferreri, N R; Zhao, Y; Takizawa, H; McGiff, J C (J Hypertens, 1997)
OBJECTIVES: To compare the levels of tumor necrosis factor-alpha (TNF) produced by medullary thick ascending limb tubules (MTAL) obtained from normotensive and angiotensin II (Ang II)-dependent hypertensive rats and determine whether TNF participates in a mechanism that opposes elevation of blood pressure by Ang II. DESIGN: We have previously demonstrated that in-vitro administration of Ang II increases production of TNF and prostaglandin E2 (PGE2) by the MTAL. We hypothesize that production of TNF and PGE2 by the MTAL is elevated in in-vivo models of Ang II-dependent hypertension and acts to modulate the pressor effects of Ang II. Thus, inhibition of TNF should disclose whether this cytokine acts to modulate Ang II-induced hypertension. METHODS: MTAL tubules obtained from normotensive and Ang II-dependent hypertensive rats were isolated by enzymatic digestion and sieving. Tubules were cultured in the absence of exogenous Ang II. TNF and PGE2 levels were measured by enzyme-linked immunosorbent assay. Anti-TNF antiserum was administered intravenously to normotensive and Ang II-dependent hypertensive rats and their mean arterial pressures were measured. RESULTS: Production of TNF and PGE2 was significantly greater in MTAL tubules isolated from Ang II hypertensive rats than it was in those from normotensive controls. Administration of anti-TNF antiserum exacerbated the Ang II-mediated increase in mean arterial pressure. CONCLUSIONS: The higher levels of production of TNF and PGE2 by MTAL tubules isolated from Ang II hypertensive rats compared with those of normotensive controls are consistent with results of in-vitro experiments showing that administration of Ang II increases production of TNF and PGE2 by the MTAL. TNF and PGE2 participate in a counter-regulatory mechanism that opposes the pressor actions of Ang II.
Keywords: Angiotensin II; Animals; Blood Pressure; Dinoprostone; Drug Interactions; Hypertension; Immune Sera; In Vitro Techniques; Kidney Medulla; Loop of Henle; Male; Rats; Rats, Sprague-Dawley; Reference Values; Tumor Necrosis Factor-alpha

Aspirin use and incident stroke in the cardiovascular health study. CHS Collaborative Research Group. - Kronmal, R A; Hart, R G; Manolio, T A; Talbert, R L; Beauchamp, N J; Newman, A (Stroke, 1998)
BACKGROUND AND PURPOSE: Randomized clinical trials testing aspirin in relatively low-risk, middle-aged people have consistently shown small increases in stroke associated with aspirin use. We analyzed the relationship between the regular use of aspirin and incident ischemic and hemorrhagic stroke among people aged 65 years or older participating in the Cardiovascular Health Study. METHODS: We conducted a multivariate analysis of incident stroke rates in a prospectively assessed, observational cohort of 5011 elderly people followed for a mean of 4.2 years. RESULTS: Participants had a mean age of 72 years, and 58% were women. Twenty-three percent used aspirin frequently, and 17% used aspirin infrequently at study entry. Frequent aspirin use was associated with an increased rate of ischemic stroke compared with nonusers (relative risk= 1.6; 95% confidence interval [CI], 1.2 to 2.2; P=0.001). After adjustment for other stroke risk factors, women who used aspirin frequently or infrequently at study entry had a 1.8-fold (95% CI, 1.2 to 2.8) and 1.6-fold (95% CI, 0.9 to 3.0) increased risk of ischemic stroke, respectively (P<0.01, test for trend), compared with nonusers. In men, aspirin use was not statistically significantly associated with stroke risk. Findings were similar when aspirin use in the years before the incident stroke was used in the modeling. Aspirin use at entry was also associated with a 4-fold (95% CI, 1.6 to 10.0) increase in risk of hemorrhagic stroke for both infrequent and frequent users of aspirin (P=0.003). CONCLUSIONS: Aspirin use was associated with increased risks of ischemic stroke in women and hemorrhagic stroke overall in this elderly cohort, after adjustment for other stroke predictors. The possibility exists of confounding by reasons for aspirin use rather than cause and effect. Whether regular aspirin use increases stroke risk for elderly people without cardiovascular disease can only be determined by randomized clinical trials.
Keywords: Aged; Aspirin; Brain Ischemia; Cardiovascular Diseases; Cerebral Hemorrhage; Cerebrovascular Disorders; Cohort Studies; Cyclooxygenase Inhibitors; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Incidence; Male; Regression Analysis; Risk Factors; Sex Factors; Time Factors

Correlates of antithrombin, protein C, protein S, and TFPI in a healthy elderly cohort. - Sakkinen, P A; Cushman, M; Psaty, B M; Kuller, L H; Bajaj, S P; Sabharwal, A K; Boineau, R; Macy, E; Tracy, R P (Thromb Haemost, 1998)
The majority of fatal acute myocardial infarctions occur in the elderly. Since these events are predominantly thrombotic, we studied the cross-sectional associations of the anticoagulant proteins Antithrombin, Protein C, Protein S. and Tissue Factor Pathway Inhibitor (TFPI) in a subgroup (n = 400) of the Cardiovascular Health Study (a study of healthy men and women > or = 65 years) free of clinical cardiovascular disease (CVD). We did not observe any strong age-associated trends, although Protein C was lower in older women (p < or = 0.001), and TFPI was higher in older men (p < or = 0.01). The inhibitors were highly intercorrelated, and were associated with increased levels of inflammation-sensitive proteins (e.g., fibrinogen. plasminogen), lipids (especially total and LDL-cholesterol), and coagulation factors, such as Factors VIIc, IXc, and Xc. None was associated with the procoagulant markers Prothrombin Fragment F1-2 or Fibrinopeptide A. Only TFPI was associated with subclinical atherosclerosis: ankle-arm index and internal carotid artery stenosis, p trend < or = 0.01; and carotid wall thickness, p trend < or = 0.05. In multivariate analysis the independent predictors of TFPI were levels of fibrinogen; the fibrinolytic marker plasmin-antiplasmin complex; LDL-cholesterol; and carotid wall thickness (R2 for the model = 0.35). In summary, the inhibitors did not appear to increase with age, and were predominantly associated with inflammation markers and lipids. Since markers of thrombin production do increase with age, we hypothesize that an age-related hemostatic imbalance may ensue, with associated increased thrombotic risk. Only TFPI was associated with subclinical CVD, suggesting that it may more closely reflect endothelial damage.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Anticoagulants; Antithrombin III; Biomarkers; Cross-Sectional Studies; Disease Susceptibility; Female; Humans; Lipoproteins; Male; Prevalence; Protein C; Protein S; Reference Values; Risk Factors; Thrombosis

Diabetes in older adults: comparison of 1997 American Diabetes Association classification of diabetes mellitus with 1985 WHO classification. - Wahl, P W; Savage, P J; Psaty, B M; Orchard, T J; Robbins, J A; Tracy, R P (Lancet, 1998)
BACKGROUND: We aimed to compare the prevalence of abnormal glucose tolerance identified by the 1985 WHO and the 1997 American Diabetes Association (ADA) diagnostic categories based on information collected in the Cardiovascular Health Study, an epidemiological study of elderly people. METHODS: We measured glucose concentrations during fasting and 2 h after a 75 g oral glucose-tolerance test in participants aged 65-100 years in the Cardiovascular Health Study. From a 1989 cohort, we analysed the glucose measurements of 4515 individuals without a previous diagnosis of diabetes and of 262 additional measurements from an African-American cohort recruited in 1992-93. FINDINGS: In the 1989 cohort, the prevalence of untreated diabetes with ADA diagnostic fasting criteria was 7.7% versus a prevalence of 14.8% by the WHO criteria. In the African-American cohort, the prevalence of untreated diabetes was 2.7% with ADA criteria and 11.8% with WHO criteria. 3509 (77.7%) of the 4515 participants in the 1989 cohort had normal glucose concentrations according to ADA fasting criteria, compared with 2401 (53.2%) according to WHO criteria. In the African-American cohort, the corresponding numbers were 239 (91.2%) versus 153 (58.4%). All differences in prevalence of abnormal glucose tolerance between ADA and WHO classifications were significant (p<0.0001). INTERPRETATION: Among elderly individuals, there was a significant difference in the prevalence of diabetes identified by the WHO diagnostic criteria based on oral glucose-tolerance test and the ADA fasting criteria. Consequently, many individuals currently classified as non-diabetic according to ADA criteria would previously have had a diagnosis of diabetes according to WHO criteria. Longitudinal studies are needed to assess the value of the criteria in the identification of individuals at increased risk of diabetes-associated chronic complications.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Diabetes Mellitus; Female; Glucose Tolerance Test; Humans; Male; Prevalence; Societies, Medical; World Health Organization

Factor V Leiden is not a risk factor for arterial vascular disease in the elderly: results from the Cardiovascular Health Study. - Cushman, M; Rosendaal, F R; Psaty, B M; Cook, E F; Valliere, J; Kuller, L H; Tracy, R P (Thromb Haemost, 1998)
Coagulation factor V Leiden is a risk marker for venous thrombosis. For arterial thrombosis no large study to date has included population-based elderly patients. The Cardiovascular Health Study is a longitudinal study of 5,201 men and women over age 65. With 3.4-year follow-up, we studied 373 incident cases of myocardial infarction (MI), angina, stroke. or transient ischemic attack (TIA), and 482 controls. The odds ratios for each event with heterozygous factor V Leiden were: MI, 0.46 (95% CI 0.17 to 1.25); angina, 1.0 (95% CI 0.45 to 2.23); stroke, 0.77 (95% CI 0.35 to 1.70): TIA, 1.33 (95% CI 0.5 to 3.55); any outcome, 0.83 (95% CI 0.48 to 1.44). Adjustment for cardiovascular risk factors did not change relationships. In older adults factor V Leiden is not a risk factor for future arterial thrombosis.
Keywords: Adult; Age Factors; Aged; Arteries; Factor V; Female; Humans; Male; Middle Aged; Mutation; Risk Factors; Thrombosis

Relationship between ApoE, MRI findings, and cognitive function in the Cardiovascular Health Study. - Kuller, L H; Shemanski, L; Manolio, T; Haan, M; Fried, L; Bryan, N; Burke, G L; Tracy, R; Bhadelia, R (Stroke, 1998)
BACKGROUND AND PURPOSE: We determined the relationship between apolipoprotein (Apo)E, MRI, and low cognitive scores. METHODS: The relationship between age, education, ApoE genotype, MRI examination of the brain, subclinical and clinical cardiovascular disease, and low (<80) score on the Modified Mini-Mental State Examination (3MSE, as modified by Teng and Chui) was evaluated for 3469 black and white participants in the Cardiovascular Health Study (CHS) in years 5 and 6 of the study. The participants were followed for up to 3 years. RESULTS: The prevalence of scores <80 in years 5 and 6 of the CHS was 8.2% for participants without and 20.4% for those with prior history of stroke. Age, race, and education were important determinants of low 3MSE scores. The prevalence of ApoE-4 (odds ratio [OR], 1.6 [1.1 to 2.1]) was directly related to scores <80, as was high ventricular volume (OR, 1.6 [1.2 to 2.3]), high white matter grade (OR, 1.4 [1.1 to 1.9]), and infarctlike lesions (OR, 1.6 [1.2 to 2.1]) on the MRI in the multivariate analysis. A five-point or greater decline in scores over up to 3 years was more often observed for participants with low 3MSE scores at year 5, at older ages, with lower education, and experiencing incident stroke (OR, 3.6 [1.2 to 10.6]), ApoE-4 genotype (OR, 1.8 [1.4 to 2.3]), and with MRI findings of high ventricular volume (OR, 2.0 [1.5 to 2.7]), and infarctlike lesions (OR, 1.2 [0.9 to 1.5]). CONCLUSIONS: These results demonstrate that vascular changes on MRI, measures of brain atrophy, ApoE-4, and age, education, and race are associated with low cognitive scores among older individuals. The MRI of the brain provides valuable information related to cognitive tests and decline over time. The potential exists for using MRI measurements to identify high-risk individuals for dementia and to test potential interventions to reduce the risk of dementia.
Keywords: African Continental Ancestry Group; Aged; Apolipoproteins E; Brain; Cardiovascular Diseases; Cerebral Infarction; Cognition; Cognition Disorders; European Continental Ancestry Group; Female; Genotype; Health Status; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Polymerase Chain Reaction; Risk Factors; Sex Factors; United States

Relationship between balance and abnormalities in cerebral magnetic resonance imaging in older adults. - Tell, G S; Lefkowitz, D S; Diehr, P; Elster, A D (Arch Neurol, 1998)
BACKGROUND: Falling is a major cause of disability and morbidity among older adults. Because poor balance is a major reason for frequent falls, assessment of balance and its risk factors are important. In this study, we postulated that cerebral changes identified on magnetic resonance (MR) imaging are related to balance, and that older adults with balance problems would have significantly greater prevalence of such brain abnormalities than older adults without balance problems. DESIGN AND MEASUREMENTS: Several measures of balance were examined in more than 700 community-dwelling older men and women, blacks and whites. Balance measures included dynamic posturography, functional reach, Romberg and 1-foot stand tests, tandem stand, and 1-foot stand. Cerebral MR imaging assessments included ventricular size, sulcal widening, white matter disease, and ischemic infarctions. Cardiovascular disease and hypertension were determined and controlled for in the analyses. RESULTS: A summary of the balance measures was significantly related to each of the 4 MR imaging measures, with those with poorer balance having more disease. The strongest associations with balance were seen for white matter disease and ventricular size. All but the ischemic infarction variable remained significantly associated with balance after adjustments for sex, race, age, cardiovascular disease, and hypertension. CONCLUSION: Cerebral changes identified by MR imaging are associated with poorer balance among older adults.
Keywords: Accidental Falls; Aged; Aging; Cerebral Cortex; Female; Humans; Magnetic Resonance Imaging; Male; Postural Balance; Risk Factors

Analytical and biologic variability in measures of hemostasis, fibrinolysis, and inflammation: assessment and implications for epidemiology. - Sakkinen, P A; Macy, E M; Callas, P W; Cornell, E S; Hayes, T E; Kuller, L H; Tracy, R P (Am J Epidemiol, 1999)
An increasing number of cardiovascular epidemiologic studies are measuring non-traditional risk markers of disease, most of which do not have established biovariability characteristics. When biovariability data have been reported, they usually represent a short time period, and, in any case, there is little consensus on how the information should be used. The authors performed a long-term (6-month) repeated measures study on 26 healthy individuals, and, using a nested analysis of variance (ANOVA) approach, report on the analytical (CVA), intraindividual (CVI), and between individual (CVG) variability of 12 procoagulant, fibrinolysis, and inflammation assays, including total cholesterol for comparison. The results suggest acceptable analytical variability (CVA < or = 1/2 CVI) for all assays. However, there was a large range of intraindividual variation as a proportion of total variance (2-78%), and adjusting for intraindividual and between individual variation in bivariate correlations increased the observed correlation by more than 30 percent for three of these assays. Overall, the assays showed a significant increase in intraindividual variation over 6 months (p < 0.05). While these findings suggest that most of these assays have biovariability characteristics similar to cholesterol, there is variation among assays. Some assays may be better suited to epidemiologic studies, and knowledge of an assay's biovariability data may be useful in interpreting simple statistics, and in designing multivariate models.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Cholesterol; Epidemiology; Female; Fibrinolysis; Hemostasis; Humans; Inflammation; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Risk Factors

Fibrinolytic activation markers predict myocardial infarction in the elderly. The Cardiovascular Health Study. - Cushman, M; Lemaitre, R N; Kuller, L H; Psaty, B M; Macy, E M; Sharrett, A R; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Coagulation factor levels predict arterial thrombosis in epidemiological studies, but studies of older persons are needed. We studied 3 plasma antigenic markers of fibrinolysis, viz, plasminogen activator inhibitor-1 (PAI-1), fibrin fragment D-dimer, and plasmin-antiplasmin complex (PAP) for the prediction of arterial thrombosis in healthy elderly persons over age 65. The study was a nested case-control study in the Cardiovascular Health Study cohort of 5201 men and women >/=65 years of age who were enrolled from 1989 to 1990. Cases were 146 participants without baseline clinical vascular disease who developed myocardial infarction, angina, or coronary death during a follow-up of 2.4 years. Controls remained free of cardiovascular events and were matched 1:1 to cases with respect to sex, duration of follow-up, and baseline subclinical vascular disease status. With increasing quartile of D-dimer and PAP levels but not of PAI-1, there was an independent increased risk of myocardial infarction or coronary death, but not of angina. The relative risk for D-dimer above versus below the median value (>/=120 microg/L) was 2.5 (95% confidence interval, 1.1 to 5.9) and for PAP above the median (>/=5.25 nmol/L), 3.1 (1.3 to 7.7). Risks were independent of C-reactive protein and fibrinogen concentrations. There were no differences in risk by sex or presence of baseline subclinical disease. D-dimer and PAP, but not PAI-1, predicted future myocardial infarction in men and women over age 65. Relationships were independent of other risk factors, including inflammation markers. Results indicate a major role for these markers in identifying a high risk of arterial disease in this age group.
Keywords: Age Factors; Aged; Angina Pectoris; Biomarkers; Female; Fibrin Fibrinogen Degradation Products; Fibrinolysin; Fibrinolysis; Follow-Up Studies; Heart Arrest; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

Hormone replacement therapy, inflammation, and hemostasis in elderly women. - Cushman, M; Meilahn, E N; Psaty, B M; Kuller, L H; Dobs, A S; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Lipid-lowering by postmenopausal hormone therapy (HRT) explains only partly the assumed coronary risk reduction associated with therapy. To explore other possible mechanisms, we studied associations of HRT use with inflammation and hemostasis risk markers in women >/=65 years of age. Subjects were selected from 3393 participants in the fourth year examination of the Cardiovascular Health Study, an observational study of vascular disease risk factors. After excluding women with vascular disease, we compared levels of inflammation and hemostasis variables in the 230 women using unopposed estrogen and 60 using estrogen/progestin, with those of 196 nonusers selected as controls. Compared with nonusers, unopposed estrogen use was associated with 59% higher mean C-reactive protein (P<0.001), but with modestly lower levels of other inflammation indicators, fibrinogen, and alpha-1 acid glycoprotein (P<0.001). Factor VIIc was 16% higher among estrogen users (P<0.001), but this was not associated with higher thrombin production (prothrombin fragment 1-2), or increased fibrin breakdown (D-dimer). Concentration of plasminogen activator inhibitor-1 was 50% lower in both using groups (P<0.001) compared with nonusers, and this was associated with higher plasmin-antiplasmin complex: 8% higher in estrogen and 18% higher in estrogen/progestin users (P<0. 05). Relationships between the markers and hormone use were less pronounced in estrogen/progestin users, with no association for C-reactive protein except in women in upper 2 tertiles of body mass index (P for interaction, 0.02). The direction and strength of the associations of HRT use with inflammation markers differed depending on the protein, so it is not clear whether HRT confers coronary risk reduction through an inflammation-sensitive mechanism. Associations with hemostasis markers indicated no association with evidence of procoagulation and a possible association with increased fibrinolytic activity.
Keywords: Aged; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Estrogens; Female; Hemostasis; Hormone Replacement Therapy; Humans; Inflammation; Progestins; Random Allocation; United Kingdom; United States

Increased blood glucose and insulin, body size, and incident colorectal cancer. - Schoen, R E; Tangen, C M; Kuller, L H; Burke, G L; Cushman, M; Tracy, R P; Dobs, A; Savage, P J (J Natl Cancer Inst, 1999)
BACKGROUND: Abdominal obesity--an elevated level of visceral adipose tissue--has been linked to colorectal cancer. Furthermore, elevated levels of visceral adipose tissue have been associated with hyperinsulinemia, and insulin is a growth factor in the colon. We assessed whether waist circumference, a surrogate measure of visceral adipose tissue, and metabolic parameters associated with visceral adipose tissue were related to colorectal cancer. METHODS: In the Cardiovascular Health Study cohort, we examined the relationship of baseline measurements of body size, glucose, insulin, and lipoproteins to incident colorectal cancer. All P values are two-sided. RESULTS: Among 5849 participants, 102 incident cases of colorectal cancer were identified. Individuals in the highest quartile of fasting glucose had a nearly twofold increased risk of colorectal cancer (relative risk [RR] = 1.8; 95% confidence interval [CI] = 1.0-3.1), and the linear trend RR (LT RR = 1.2; 95% CI = 1.0-1.5) for fasting glucose level was statistically significant (P =. 02). Glucose and insulin levels 2 hours after oral glucose challenge also exhibited statistically significant associations with colorectal cancer (2-hour glucose levels: RR = 2.4 [95% CI = 1.2-4. 7]/LT RR = 1.3 [95% CI = 1.0-1.6; P =.02]; 2-hour insulin levels: RR = 2.0 [95% CI = 1.0-3.8]/LT RR = 1.2 [95% CI = 1.0-1.5; P =.04]). Analysis of fasting insulin levels suggested a threshold effect, with values above the median associated with colorectal cancer (RR = 1.6; 95% CI = 1.1-2.4; P =.02). Higher levels of waist circumference were also statistically significantly associated with colorectal cancer (RR = 1.9; 95% CI = 1.1-3.3; P =.02). CONCLUSIONS: These data provide, to our knowledge, the first direct evidence of an association between elevated visceral adipose tissue level, its associated metabolic effects, and colorectal cancer.
Keywords: Adipose Tissue; Aged; Blood Glucose; Body Constitution; Cholesterol, HDL; Colorectal Neoplasms; Female; Humans; Incidence; Insulin; Male; Prospective Studies; Risk; Triglycerides; Viscera

The relationship of fibrinogen and factors VII and VIII to incident cardiovascular disease and death in the elderly: results from the cardiovascular health study. - Tracy, R P; Arnold, A M; Ettinger, W; Fried, L; Meilahn, E; Savage, P (Arterioscler Thromb Vasc Biol, 1999)
Little is known about the prospective associations of fibrinogen, factor VII, or factor VIII with cardiovascular disease (CVD) and mortality in the elderly. At baseline in the Cardiovascular Health Study (5888 white and African American men and women; aged >/=65 years), we measured fibrinogen, factor VIII, and factor VII. We used sex-stratified stepwise Cox survival analysis to determine relative risks (RRs) for CVD events and all-cause mortality (up to 5 years of follow-up), both unadjusted and adjusted for CVD risk factors and subclinical CVD. After adjustment, comparing the fifth quintile to the first, fibrinogen was significantly associated in men with coronary heart disease events (RR=2.1) and stroke or transient ischemic attack (RR=1.3), and also with mortality within 2.5 years of follow-up (RR=5.8) and later (RR=1.7). Factor VIII was significantly associated in men with coronary heart disease events (RR=1.5) and mortality (RR=1.8), and in women with stroke/transient ischemic attack (RR=1.4). For both factors, values were higher in those who died, whether causes were CVD-related or non-CVD-related, but highest in CVD death. Factor VII exhibited associations with incident angina (RR=1.44) in men and with death in women (RR, middle quintile compared with first=0.66). However, in general, factor VII was not consistently associated with CVD events in this population. We conclude that, if confirmed in other studies, the measurement of fibrinogen and/or factor VIII may help identify older individuals at higher risk for CVD events and mortality.
Keywords: Aged; Cardiovascular Diseases; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Multivariate Analysis; Risk Factors

Relationship of plasmin generation to cardiovascular disease risk factors in elderly men and women. - Sakkinen, P A; Cushman, M; Psaty, B M; Rodriguez, B; Boineau, R; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Plasmin-alpha2-antiplasmin complex (PAP) marks plasmin generation and fibrinolytic balance. We recently observed that elevated levels of PAP predict acute myocardial infarction in the elderly, yet little is known about the correlates of PAP. We measured PAP in 800 elderly subjects who were free of clinical cardiovascular disease in 2 cohort studies: the Cardiovascular Health Study and the Honolulu Heart Program. Median PAP levels did not differ between the Cardiovascular Health Study (6.05+/-1.46 nmol/L) and the Honolulu Heart Program (6.11+/-1.44 nmol/L), and correlates of PAP were similar in both cohorts. In CHS, PAP levels increased with age (r=0. 30), procoagulant factors (eg, factor VIIc, r=0.15), thrombin activity (prothrombin fragment F1+2, r=0.29), and inflammation-sensitive proteins (eg, fibrinogen, r=0.44; factor VIIIc, r=0.37). PAP was associated with increased atherosclerosis as measured by the ankle-arm index (AAI) (P for trend, </=0.001). PAP was negatively related to factors associated with the insulin resistance syndrome (IRS) (eg, fasting insulin, r=-0.26; body mass index, r=-0.26), possibly reflecting an association with plasminogen activator inhibitor-1 (r=-0.29). Although our study did not have sufficient power to detect a significant interaction, PAP and AAI appeared to be more weakly associated in subjects with more manifestations of the IRS: PAP appeared more strongly associated with AAI in the subgroup with 0 or 1 metabolic disorders (P</=0.001; slope estimate, -0.14) compared with the subgroup with 2 or more metabolic disorders (P=0.10; slope estimate, -0.08) and in those with non-insulin-dependent diabetes mellitus (P=0.46; slope estimate, -0.04). Although PAP reflects reactive fibrinolysis and is associated with subclinical atherosclerosis, this relationship may be weaker in populations with characteristics of the IRS, possibly reflecting the inhibitory effects of plasminogen activator inhibitor-1 on PAP. Decreased fibrinolysis in the presence of subclinical disease in subjects with hyperinsulinemia or glucose intolerance is consistent with the premise that depressed plasmin generation may enhance the progression of atherosclerosis in these people.
Keywords: Aged; Aged, 80 and over; alpha-2-Antiplasmin; Antifibrinolytic Agents; Asian Continental Ancestry Group; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Fibrinolysin; Fibrinolysis; Humans; Insulin Resistance; Male; Multivariate Analysis; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

The reliability of medication inventory methods compared to serum levels of cardiovascular drugs in the elderly. - Smith, N L; Psaty, B M; Heckbert, S R; Tracy, R P; Cornell, E S (J Clin Epidemiol, 1999)
Medication inventory is more reliable than self-report in assessing prescription drug use in elderly populations. It is not known how strongly medication inventory reflects actual medication use as measured by serum drug levels. In the Cardiovascular Health Study, medication data were collected annually by study interviewers from medication containers brought to the clinic visit. At the fourth clinic visit, venipuncture was performed under 12-hour fasting conditions. Participants were told to take medications as usual. Based on medication inventory results, we randomly selected 55 users and 55 non-users of four cardiovascular drugs: aspirin, propranolol, hydrochlorothiazide, and digoxin. All 110 blood samples for each of the four drugs were analyzed; cut points were based on detectable levels given laboratory limitations. Kappa statistics (K) tested degree of agreement between medication inventory findings and serum detection. Assays were completed on 400 samples (91%). Agreement for aspirin (n=102) was poor: K=0.16 (95% CI: 0.0-0.32). Agreement for propranolol (n = 98) was fair: K=0.43 (95% CI: 0.27-0.59). Agreement for hydrochlorothiazide (n=100) was good: K=0.62 (95% CI: 0.53-0.91). Agreement for digoxin (n=100) was excellent: K=0.94 (95% CI: 0.74-1.0). For four all drugs, lack of agreement was confined primarily to participants who reported use but did not have detectable levels. Excluding aspirin users, only one non-user (0.7%) had drug detected in serum. The medication inventory is a reasonably sensitive and a fairly reliable method for ascertaining non-aspirin cardiovascular drug use in the elderly even though this method may overestimate use as assessed by serum level.
Keywords: Aged; Aspirin; Cardiovascular Agents; Digoxin; Humans; Hydrochlorothiazide; Patient Compliance; Propranolol; Reproducibility of Results

Chlamydia pneumoniae, herpes simplex virus type 1, and cytomegalovirus and incident myocardial infarction and coronary heart disease death in older adults : the Cardiovascular Health Study. - Siscovick, D S; Schwartz, S M; Corey, L; Grayston, J T; Ashley, R; Wang, S P; Psaty, B M; Tracy, R P; Kuller, L H; Kronmal, R A (Circulation, 2000)
BACKGROUND: Whether serological evidence of prior infection with Chlamydia pneumoniae, herpes simplex virus type 1 (HSV-1), and cytomegalovirus (CMV) is associated with myocardial infarction (MI) and coronary heart disease (CHD) death remains a source of controversy. METHODS AND RESULTS: We conducted a nested case-control study among participants in the Cardiovascular Health Study, a cohort study of persons aged >/=65 years. Cases experienced an incident MI and CHD death (n=213). Control subjects were matched to cases by age, sex, clinic, year of enrollment, and month of blood draw (n=405). Serum was analyzed for IgG antibodies to C pneumoniae, HSV-1, and CMV. After adjustment for other risk factors, the risk of MI and CHD death was associated with the presence of IgG antibodies to HSV-1 (odds ratio [OR] 2.0, 95% CI 1.1 to 3.6) but was not associated with the presence of IgG antibodies to either C pneumoniae (OR 1.1, 95% CI 0.7 to 1.8) or CMV (OR 1.2, 95% CI 0.7 to 1.9). Although there was little association with low to moderate C pneumoniae antibody titers (</=1:512), high-titer (1:1024) C pneumoniae antibody was associated with an increased risk (OR 2.2, 95% CI 1.1 to 4.4). CONCLUSIONS: Among older adults, the presence of IgG antibodies to HSV-1 was associated with a 2-fold increase in the risk of incident MI and CHD death. For C pneumoniae, only high-titer IgG antibodies were associated with an increased risk of MI and CHD death. The presence of IgG antibodies to CMV was not associated with risk among the elderly.
Keywords: Adult; Age Factors; Aged; Antibodies, Bacterial; Antibodies, Viral; Case-Control Studies; Chlamydophila pneumoniae; Coronary Disease; Cytomegalovirus; Female; Herpesvirus 1, Human; HIV Antibodies; Humans; Immunoglobulin G; Male; Myocardial Infarction; Risk Factors

Clustering of procoagulation, inflammation, and fibrinolysis variables with metabolic factors in insulin resistance syndrome. - Sakkinen, P A; Wahl, P; Cushman, M; Lewis, M R; Tracy, R P (Am J Epidemiol, 2000)
The known metabolic cardiovascular disease risk factors associated with insulin resistance syndrome (IRS) do not adequately explain the excess cardiovascular disease risk attributed to this syndrome, and abnormalities in hemostatic variables may contribute to this excess risk. Using data from 322 nondiabetic elderly men and women (aged 65-100 years) participating in the Cardiovascular Health Study during 1989-1990, the authors performed factor analysis on 10 metabolic risk factors associated with IRS and 11 procoagulation, inflammation, and fibrinolysis variables to examine the clustering of the metabolic and hemostatic risk markers. Factor analysis of the metabolic variables confirmed four uncorrelated factors: body mass, insulin/glucose, lipids, and blood pressure. Adding the hemostatic variables yielded three new factors interpreted as inflammation, vitamin K-dependent proteins, and procoagulant activity. Plasminogen activator inhibitor-1 clustered with the body mass factor, supporting the hypothesis that obesity is related to impaired fibrinolysis. Fibrinogen clustered with the inflammation summary factor rather than procoagulant activity, supporting the position that fibrinogen principally reflects underlying inflammation rather than procoagulant potential. The authors conclude that should hemostatic variables be shown to contribute to IRS-related cardiovascular disease, apart from plasminogen activator inhibitor-1, they may do so independently of the established metabolic abnormalities.
Keywords: Aged; Aged, 80 and over; Antigens; Blood Coagulation; Cardiovascular Diseases; Cluster Analysis; Factor Analysis, Statistical; Factor VII; Female; Fibrinogen; Fibrinolysis; Humans; Inflammation; Insulin Resistance; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Risk Factors

Depressive symptoms and risks of coronary heart disease and mortality in elderly Americans. Cardiovascular Health Study Collaborative Research Group. - Ariyo, A A; Haan, M; Tangen, C M; Rutledge, J C; Cushman, M; Dobs, A; Furberg, C D (Circulation, 2000)
BACKGROUND: Several epidemiological studies have associated depressive symptoms with cardiovascular disease. We investigated whether depressive symptoms constituted a risk for coronary heart disease (CHD) and total mortality among an apparently healthy elderly cohort. METHODS AND RESULTS: In a prospective cohort of 5888 elderly Americans (>/=65 years) who were enrolled in the Cardiovascular Health Study, 4493 participants who were free of cardiovascular disease at baseline provided annual information on their depressive status, which was assessed using the Depression Scale of the Center for Epidemiological Studies. These 4493 subjects were followed for 6 years for the development of CHD and mortality. The cumulative mean depression score was assessed for each participant up to the time of event (maximum 6-year follow-up). Using time-dependent, proportional-hazards models, the unadjusted hazard ratio associated with every 5-unit increase in mean depression score for the development of CHD was 1.15 (P:=0.006); the ratio for all-cause mortality was 1.29 (P:<0.0001). In multivariate analyses adjusted for age, race, sex, education, diabetes, hypertension, cigarette smoking, total cholesterol, triglyceride level, congestive heart failure, and physical inactivity, the hazard ratio for CHD was 1.15 (P:=0.006) and that for all-cause mortality was 1.16 (P:=0.006). Among participants with the highest cumulative mean depression scores, the risk of CHD increased by 40% and risk of death by 60% compared with those who had the lowest mean scores. CONCLUSIONS: Among elderly Americans, depressive symptoms constitute an independent risk factor for the development of CHD and total mortality.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Depression; Female; Humans; Male; Prospective Studies; Risk Factors; United States

Estrogen use, APOE, and cognitive decline: evidence of gene-environment interaction. - Yaffe, K; Haan, M; Byers, A; Tangen, C; Kuller, L (Neurology, 2000)
OBJECTIVE: APOE-epsilon4 increases the risk of cognitive decline, while elderly women who take estrogen may have less risk of cognitive decline. The authors sought to determine whether estrogen use modifies the association between APOE-epsilon4 and cognitive decline. METHOD: - As part of the Cardiovascular Health Study, 3,393 Medicare-eligible women (> or =65 years) were randomly selected and recruited from Sacramento County, CA; Washington County, MD; Forsyth County, NC; and Pittsburgh, PA. Cognitive testing was administered annually; the authors studied the 2,716 women with cognitive testing on > or =2 visits. They analyzed change in score on the Modified Mini-Mental State Examination (3MS) as a function of estrogen use, APOE genotype, and baseline common and internal carotid artery wall thickening. RESULTS: A total of 297 (11%) women were current estrogen users and 336 (12%) were past estrogen users. Over the 6-year average follow-up, baseline current users declined 1.5 points on the 3MS whereas never users declined 2.7 points (p = 0.023). Compared with epsilon4-negative women, epsilon4-positive women had a greater adjusted hazard ratio of cognitive impairment (3MS < 80), hazard risk [HR] = 1.47; 95% CI, 1.13 to 1.90. There was an interaction between estrogen use and epsilon4 presence (p = 0.037). Among epsilon4-negative women, current estrogen use reduced the risk of adjusted cognitive impairment compared with never users by almost half (HR = 0.59; 95% CI, 0.36 to 0.99), whereas, it did not reduce the risk among epsilon4-positive women (current use, HR = 1.33; 95% CI, 0.74 to 2.42). Compared with never use, current estrogen use was associated with less internal and common carotid wall thickening in epsilon4-negative women but not in epsilon4-positive women (p for interaction < 0.05 for both). Differences remained after adjusting for age, education, race, and stroke. CONCLUSIONS: Estrogen use was associated with less cognitive decline among epsilon4-negative women but not epsilon4-positive women. Potential mechanisms, including carotid atherosclerosis, by which epsilon4 may interact with estrogen and cognition warrant further investigation.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Carotid Stenosis; Estrogen Replacement Therapy; Female; Genotype; Humans; Mental Status Schedule; Neuropsychological Tests; Risk Factors

Evidence of islet cell autoimmunity in elderly patients with type 2 diabetes. - Pietropaolo, M; Barinas-Mitchell, E; Pietropaolo, S L; Kuller, L H; Trucco, M (Diabetes, 2000)
In light of an occurring growth of elderly people affected by type 2 diabetes and recent observations indicating that type 2 diabetes may be a disease of the innate immune system, we evaluated whether signs of islet cell autoimmunity are associated with an abnormal glucose control, the presence of insulin requirement, or an activation of the acute-phase response in older individuals with type 2 diabetes. GAD65 and IA-2 autoantibodies along with the acute-phase response markers fibrinogen and C-reactive protein were tested in 196 serum samples from patients with type 2 diabetes and in 94 nondiabetic control subjects over the age of 65 years from the Pittsburgh cohort of the Cardiovascular Health Study. Of the diabetic patients, 12% (24 of 196) had autoantibodies against GAD65 and/or IA-2, a prevalence significantly higher than that found in nondiabetic individuals (1 of 94, 1.1%; P = 0.001). Type 2 diabetic patients who were positive for GAD65 and/or IA-2 autoantibodies (Ab+), as compared with those negative for these autoantibodies (Ab-), had an abnormal oral glucose tolerance test (OGTT) (P = 0.03) before and a higher frequency of oral hypoglycemic treatment (P = 0.003) at the time of autoantibody testing. No differences were seen in the percentage of insulin requirement in the two groups. Moreover, a statistically significant increase in fibrinogen (P = 0.005) and C-reactive protein levels (P = 0.025) was found in type 2 diabetic patients with high levels of GAD65 and/or IA-2 autoantibodies as compared with Ab-patients and control subjects. In conclusion, in type 2 diabetic subjects > or =65 years old, the presence of islet cell autoimmunity is associated with an impairment of the acute-phase insulin secretion, as revealed by an OGTT. A pronounced activation of the acute-phase response, found to be associated with islet cell autoimmunity, may in part explain this defect in insulin secretion. These findings not only have direct implications for adequate classification and treatment of diabetes in the elderly, but also for understanding the autoimmune/inflammatory mechanisms involved in the pathogenesis of hyperglycemia.
Keywords: Aged; Aged, 80 and over; Aging; Autoantibodies; Autoantigens; Autoimmunity; Blood Glucose; C-Reactive Protein; Diabetes Mellitus, Type 2; Female; Fibrinogen; Glucose Tolerance Test; Glutamate Decarboxylase; Humans; Islets of Langerhans; Male; Membrane Proteins; Protein Tyrosine Phosphatases; Receptor-Like Protein Tyrosine Phosphatases, Class 8

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Association between physical activity and markers of inflammation in a healthy elderly population. - Geffken, D F; Cushman, M; Burke, G L; Polak, J F; Sakkinen, P A; Tracy, R P (Am J Epidemiol, 2001)
Higher levels of physical activity are associated with lower risk of cardiovascular disease. There is growing evidence that the development of the atherosclerotic plaque is associated with inflammation. In this study, the authors investigated the cross-sectional association between physical activity and markers of inflammation in a healthy elderly population. Data obtained in 1989-1990 and 1992-1993 from the Cardiovascular Health Study, a cohort of 5,888 men and women aged >/=65 years, were analyzed. Concentrations of the inflammation markers-C-reactive protein, fibrinogen, Factor VIII activity, white blood cells, and albumin-were compared cross-sectionally by quartile of self-reported physical activity. Compared with persons in the lowest quartile, those in the highest quartile of physical activity had 19%, 6%, 4%, and 3% lower concentrations of C-reactive protein, white blood cells, fibrinogen, and Factor VIII activity, respectively, after adjustment for gender, the presence of cardiovascular disease, age, race, smoking, body mass index, diabetes, and hypertension. Multivariate regression models suggested that the association of higher levels of physical activity with lower levels of inflammation markers may be mediated by body mass index and glucose. There was no association between physical activity and albumin. Higher levels of physical activity were associated with lower concentrations of four out of five inflammation markers in this elderly cohort. These data suggest that increased exercise is associated with reduced inflammation. Prospective studies will be required for verification of these findings.
Keywords: Aged; Analysis of Variance; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Factor VIII; Female; Fibrinogen; Humans; Inflammation; Leukocyte Count; Male; Physical Exertion; Sex Factors; Smoking

Associations of subclinical cardiovascular disease with frailty. - Newman, A B; Gottdiener, J S; McBurnie, M A; Hirsch, C H; Kop, W J; Tracy, R; Walston, J D; Fried, L P (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frail health in old age has been conceptualized as a loss of physiologic reserve associated with loss of lean mass, neuroendocrine dysregulation, and immune dysfunction. Little work has been done to define frailty and describe the underlying pathophysiology. METHODS: Frailty status was defined in participants of the Cardiovascular Health Study (CHS), a cohort of 5,201 community-dwelling older adults, based on the presence of three out of five clinical criteria. The five criteria included self-reported weight loss, low grip strength, low energy, slow gait speed, and low physical activity. We examined the spectrum of clinical and subclinical cardiovascular disease in those who were frail (3/5 criteria) or of intermediate frailty status (1 or 2/5 criteria), compared to those who were not frail (0/5). We hypothesized that the severity of frailty would be related to a higher prevalence of reported cardiovascular disease (CVD), as well as to a greater extent of CVD, measured by noninvasive testing. RESULTS: Of 4,735 eligible participants, 2,289 (48%) were not frail, 299 (6%) were frail, and 2.147 (45%) were of intermediate frailty status. Those who were frail were older (77.2 yrs) compared to those who were not frail (71.5 yrs) or intermediate (73.4 yrs) (p < .001). Frailty status was associated with clinical CVD and most strongly with congestive heart failure (odds ratio [OR] = 7.51 (95% confidence interval [CI] = 4.66-12.12). In those without a history of a CVD event (n = 1.259), frailty was associated with many noninvasive measures of CVD. Those with carotid stenosis >75% (adjusted OR = 3.41), ankle-arm index <0.8 (adjusted OR = 3.17) or 0.8-0.9 (adjusted OR = 2.01), major electrocardiography (ECG) abnormalities (adjusted OR = 1.58), greater left ventricular (LV) mass by echocardiography (adjusted OR = 1.16), and higher degree of infarct-like lesions in the brain (adjusted OR = 1.71), were more likely to be frail compared to those who were not frail. The overall associations of each of these noninvasive measures of CVD with frailty level were significant (all p < .05). CONCLUSIONS: Cardiovascular disease was associated with an increased likelihood of frail health. In those with no history of CVD, the extent of underlying cardiovascular disease measured by carotid ultrasound and ankle-arm index, LV hypertrophy by ECG and echocardiography, was related to frailty. Infarct-like lesions in the brain on magnet resonance imaging were related to frailty as well.
Keywords: Aged; Ankle; Arm; Black or African American; Blood Pressure; Brain; Cardiovascular Diseases; Carotid Artery Diseases; Cerebral Infarction; Cerebrovascular Disorders; Cohort Studies; Echocardiography; Electrocardiography; Frail Elderly; Health Status; Heart Failure; Humans; Magnetic Resonance Imaging; United States; Vascular Diseases

Frailty in older adults: evidence for a phenotype. - Fried, L P; Tangen, C M; Walston, J; Newman, A B; Hirsch, C; Gottdiener, J; Seeman, T; Tracy, R; Kop, W J; Burke, G; McBurnie, M A (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frailty is considered highly prevalent in old age and to confer high risk for falls, disability, hospitalization, and mortality. Frailty has been considered synonymous with disability, comorbidity, and other characteristics, but it is recognized that it may have a biologic basis and be a distinct clinical syndrome. A standardized definition has not yet been established. METHODS: To develop and operationalize a phenotype of frailty in older adults and assess concurrent and predictive validity, the study used data from the Cardiovascular Health Study. Participants were 5,317 men and women 65 years and older (4,735 from an original cohort recruited in 1989-90 and 582 from an African American cohort recruited in 1992-93). Both cohorts received almost identical baseline evaluations and 7 and 4 years of follow-up, respectively, with annual examinations and surveillance for outcomes including incident disease, hospitalization, falls, disability, and mortality. RESULTS: Frailty was defined as a clinical syndrome in which three or more of the following criteria were present: unintentional weight loss (10 lbs in past year), self-reported exhaustion, weakness (grip strength), slow walking speed, and low physical activity. The overall prevalence of frailty in this community-dwelling population was 6.9%; it increased with age and was greater in women than men. Four-year incidence was 7.2%. Frailty was associated with being African American, having lower education and income, poorer health, and having higher rates of comorbid chronic diseases and disability. There was overlap, but not concordance, in the cooccurrence of frailty, comorbidity, and disability. This frailty phenotype was independently predictive (over 3 years) of incident falls, worsening mobility or ADL disability, hospitalization, and death, with hazard ratios ranging from 1.82 to 4.46, unadjusted, and 1.29-2.24, adjusted for a number of health, disease, and social characteristics predictive of 5-year mortality. Intermediate frailty status, as indicated by the presence of one or two criteria, showed intermediate risk of these outcomes as well as increased risk of becoming frail over 3-4 years of follow-up (odds ratios for incident frailty = 4.51 unadjusted and 2.63 adjusted for covariates, compared to those with no frailty criteria at baseline). CONCLUSIONS: This study provides a potential standardized definition for frailty in community-dwelling older adults and offers concurrent and predictive validity for the definition. It also finds that there is an intermediate stage identifying those at high risk of frailty. Finally, it provides evidence that frailty is not synonymous with either comorbidity or disability, but comorbidity is an etiologic risk factor for, and disability is an outcome of, frailty. This provides a potential basis for clinical assessment for those who are frail or at risk, and for future research to develop interventions for frailty based on a standardized ascertainment of frailty.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Fatigue; Female; Frail Elderly; Humans; Incidence; Male; Muscle Weakness; Phenotype; Prevalence; Sex Distribution; United States; Weight Loss

Incidence and predictors of coronary heart disease among older African Americans--the Cardiovascular Health Study. - Jackson, S A; Burke, G L; Thach, C; Cushman, M; Ives, D; Powe, N; Manolio, T A (J Natl Med Assoc, 2001)
Although coronary heart disease (CHD) is the leading cause of death and morbidity in older African Americans, relatively little is known about the incidence and predictors of CHD in this population. This study was undertaken to determine the incidence and predictors of CHD in African-American men and women aged 65 years and older. The participants in this study included a total of 924 African-American men and women aged 65 years of age and older who participated in the Cardiovascular Health Study (CHS). The overall CHD incidence was 26.6 per 1,000 person-years of risk. Rates were higher in men than women (35.3 vs. 21.6) and in those 75 years or older than in those less than 75 years (31.3 vs. 24.5). In multivariate analysis, factors associated with higher risk of incident disease were male gender [relative risk (RR) = 1.8, 95% confidence interval (CI) = 1.1, 2.7], diabetes mellitus (RR = 1.9, 95% CI = 1.2, 2.9), total cholesterol (RR for 40 mg/dL increment = 1.3, 95% CI = 1.0, 1.5), and low (i.e., <0.9) ankle-arm index (RR = 2.1, 95% CI = 1.3, 3.4) after adjusting for age. Within this cohort of older African Americans, male gender, diabetes mellitus, total cholesterol, and low ankle-arm index and were independently predictive of incident events. These results suggest that the ankle-arm index, a measure of advanced atherosclerosis, should be further evaluated for its efficacy in identifying older African Americans at risk for incident clinical events.
Keywords: Age Distribution; Aged; Black or African American; Coronary Disease; Female; Health Status; Humans; Incidence; Male; Predictive Value of Tests

The relation of markers of inflammation to the development of glucose disorders in the elderly: the Cardiovascular Health Study. - Barzilay, J I; Abraham, L; Heckbert, S R; Cushman, M; Kuller, L H; Resnick, H E; Tracy, R P (Diabetes, 2001)
Several studies suggest that inflammation plays a role in the pathogenesis of some glucose disorders in adults. We tested this hypothesis in a longitudinal cohort study of older individuals who had normal fasting glucose (FG) values at baseline. We compared the baseline levels of six inflammatory markers in participants who had developed glucose disorders at follow-up with those of participants whose FG remained normal at follow-up. Participants were members of the Cardiovascular Health Study, a prospective study of risk factors for cardiovascular disease in adults > or =65 years. All 5,888 participants had baseline testing, including FG and markers of inflammation: white blood cell and platelet counts and albumin, fibrinogen, C-reactive protein (CRP), and factor VIIIc levels. At 3-4 years of follow-up, 4,481 (84.5%) of those who were alive had FG levels retested. Participants who developed diabetes (n = 45) had higher median levels of CRP at baseline than those who remained normoglycemic. On multivariate analysis, those with elevated CRP levels (75th percentile [2.86 mg/l] vs. 25th percentile [0.82 mg/l]) were 2.03 times (95% confidence intervals, 1.44-2.86) more likely to have diabetes on follow-up. Adjustment for confounders and other inflammatory markers did not appreciably change this finding. There was no relationship between the development of diabetes and other markers of inflammation. Inflammation, as measured by CRP levels, is associated with the development of diabetes in the elderly. Understanding the role of inflammation in the pathogenesis of glucose disorders in this age-group may lead to better classification and treatment of glucose disorders among them.
Keywords: Aged; Biomarkers; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Humans; Hypoglycemia; Inflammation; Longitudinal Studies; Male; Reference Values; Risk Factors

Angiotensin II type 1 receptor polymorphisms in the cardiovascular health study: relation to blood pressure, ethnicity, and cardiovascular events. - Hindorff, Lucia A; Heckbert, Susan R; Tracy, Russell; Tang, Zhonghua; Psaty, Bruce M; Edwards, Karen L; Siscovick, David S; Kronmal, Richard A; Nazar-Stewart, Valle (Am J Hypertens, 2002)
BACKGROUND: The angiotensin II type 1 receptor A1166C polymorphism has been associated with increased risks of hypertension and myocardial infarction in several small studies. We examined the association between this polymorphism and new-onset hypertension, blood pressure (BP) control, and incident cardiovascular events in a large population-based cohort of older adults. METHODS: Eight hundred self-identified African Americans and 1,371 randomly selected white participants in the Cardiovascular Health Study were genotyped. The median duration of follow-up was 8.1 years. RESULTS: The A1166C polymorphism was not associated with new-onset hypertension, with BP control, or with incident cardiovascular events in the overall population. In white participants, the CC genotype was associated with higher baseline systolic BP and pulse pressure, compared to the AC or AA genotype. In whites with treated hypertension at baseline, compared to the AA genotype, the CC genotype was associated with increased risks of incident congestive heart failure (hazard ratio = 2.5, 95% confidence interval [CI] 1.3-4.9) and incident ischemic stroke (hazard ratio = 2.6, 95% CI 1.1-6.0). These associations were not observed among white participants without treated hypertension, but the interaction of genotype with treated hypertension on ischemic stroke and heart failure was only marginally significant. CONCLUSIONS: On the whole, in this large cohort of older adults, the A1166C polymorphism was not associated with BP control or incident cardiovascular events. The subgroup findings in treated hypertensives need to be confirmed in additional studies.
Keywords: African Continental Ancestry Group; Aged; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Gene Frequency; Humans; Hypertension; Male; Polymorphism, Genetic; Receptor, Angiotensin, Type 1; Receptors, Angiotensin; United States

Anticardiolipin antibodies as a risk factor for venous thromboembolism in a population-based prospective study. - Runchey, Shauna S; Folsom, Aaron R; Tsai, Michael Y; Cushman, Mary; McGovern, Paul D (Br J Haematol, 2002)
Anticardiolipin antibodies, one of the family of 'antiphospholipid' antibodies, increase the risk of venous thromboembolism in the presence of autoimmune disease. Our objective was to determine prospectively whether there is a positive association between anticardiolipin antibodies and venous thromboembolism in ostensibly healthy adults. We conducted a nested case-control study (n = 317 patients and n = 655 control subjects) in a longitudinal study of over 20 000 participants. Baseline (prediagnosis) anticardiolipin IgG and IgM antibodies were assessed by enzyme-linked immunoassays. Venous thromboembolism was validated using standardized criteria for venous thrombosis and pulmonary embolism. There was no association between anticardiolipin antibodies and subsequent venous thromboembolism occurrence, overall or in any subgroup. For example, the multivariate-adjusted relative risk was 0.88 (95% confidence interval, 0.43, 1.78) for greater than versus less than the 95th percentile of anticardiolipin IgG. In conclusion, in this general population sample, an elevated anticardiolipin antibody level was not a risk factor for venous thromboembolism.
Keywords: Aged; Aged, 80 and over; Antibodies, Anticardiolipin; Case-Control Studies; Female; Humans; Immunoglobulin G; Immunoglobulin M; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Reference Values; Risk Factors; Thromboembolism; Venous Thrombosis

Cardiovascular disease risk status in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Kidney Int, 2002)
BACKGROUND: Renal insufficiency has been independently associated with incident cardiovascular disease events in some, but not all, prospective studies. We determined the prevalence of elevated cardiovascular disease risk status among elderly persons with renal insufficiency. METHODS: This study is a cross-sectional analysis using data collected at the baseline visit of the Cardiovascular Health Study, which enrolled 5888 community dwelling adults aged 65 years or older from four clinical centers in the United States. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. The outcomes of this study included prevalent cardiovascular disease [prior coronary heart disease (CHD) or stroke], subclinical cardiovascular disease (abnormal values of ankle-arm index, carotid ultrasound, and echocardiography) and elevated cardiovascular risk based upon a diagnosis of diabetes and the Framingham equations. The association between renal insufficiency and cardiovascular risk status was estimated with and without adjustment for other cardiovascular predictors. RESULTS: Among the 5808 participants with creatinine levels measured at entry, 15.9% of men (N = 394), and 7.6% of women (N = 254) had renal insufficiency. The prevalence of either clinical or subclinical cardiovascular disease was 64% in persons with renal insufficiency compared with 43% in those without it [odds ratio (OR) 2.34; 95% confidence interval (95% CI), 1.96, 2.80]. After adjustment for other cardiovascular risk factors, renal insufficiency remained significantly associated with clinical and subclinical cardiovascular disease (adjusted OR 1.43; 95% CI, 1.18, 1.75), but the magnitude of association was substantially reduced. After combining clinical and subclinical cardiovascular disease, diabetes, and an estimated risk>20% by the Framingham equations, 78% of men and 61% of women with renal insufficiency had elevated cardiovascular risk status. CONCLUSIONS: Renal insufficiency is a marker for elevated cardiovascular disease risk in community dwelling elderly adults.
Keywords: Age Distribution; Aged; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Creatinine; Cross-Sectional Studies; Female; Humans; Kidney Failure, Chronic; Male; Prevalence; Prospective Studies; Risk Factors

Cardiovascular risk factors and venous thromboembolism incidence: the longitudinal investigation of thromboembolism etiology. - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Polak, Joseph F; Folsom, Aaron R (Arch Intern Med, 2002)
BACKGROUND: The association between traditional cardiovascular risk factors and risk of venous thromboembolism (VTE) has not been extensively examined in prospective studies. METHODS: To determine whether atherosclerotic risk factors are also associated with increased incidence of VTE, we conducted a prospective study of 19 293 men and women without previous VTE in 6 US communities between 1987 and 1998. RESULTS: There were 215 validated VTE events (1.45 per 1000 person-years) during a median of 8 years of follow-up. The age-adjusted hazard ratio was 1.4 (95% confidence interval [CI], 1.1-1.9) for men vs women, 1.6 (95% CI, 1.2-2.2) for blacks vs whites, and 1.7 (95% CI, 1.5-2.0) per decade of age. Cigarette smoking, hypertension, dyslipidemia, physical inactivity, and alcohol consumption were not associated with risk of VTE. Age-, race-, and sex-adjusted hazard ratios for body mass index categories (calculated as the weight in kilograms divided by the height in meters squared) of less than 25, 25 to less than 30, 30 to less than 35, 35 to less than 40, and 40 or more were 1.0, 1.5, 2.2, 1.5, and 2.7, respectively (P<.001 for the trend). Diabetes was also associated with an increased risk of VTE (adjusted hazard ratio, 1.5 [95% CI, 1.0-2.1]). CONCLUSIONS: Our data showing no relationship of some arterial risk factors with VTE corroborate the view that the etiology of VTE differs from atherosclerotic cardiovascular disease. In addition, the findings suggest a hypothesis that avoidance of obesity and diabetes or vigilance in prophylaxis in patients with those conditions may prevent some venous thromboses.
Keywords: Aged; Arteriosclerosis; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Pulmonary Embolism; Risk Factors; United States; Venous Thrombosis

Coagulation factors, inflammation markers, and venous thromboembolism: the longitudinal investigation of thromboembolism etiology (LITE). - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Tracy, Russell P; Aleksic, Nena; Folsom, Aaron R (Am J Med, 2002)
PURPOSE: We sought to assess prospectively whether higher levels of blood coagulation factors and inflammation markers are risk factors for venous thromboembolism. SUBJECTS AND METHODS: In two pooled population-based cohort studies, we measured levels of factor VII, factor VIII, von Willebrand factor, fibrinogen, and C-reactive protein, and white blood cell count, in samples obtained from 19,237 adults with no baseline history of venous thromboembolism, cancer, or warfarin use. The endpoint was validated venous thromboembolism during follow-up (median, 7.8 years). RESULTS: A total of 159 venous thromboembolism events occurred. Factor VIII and von Willebrand factor were linearly associated with increased risk of venous thromboembolism (P for trend <0.0001). As compared with those in the lowest quartile, the multivariate-adjusted hazard ratio (HR) of venous thromboembolism was 2.6 (95% confidence interval [CI]: 1.6 to 4.3) for factor VIII levels in the highest quartile and 3.8 (95% CI: 2.0 to 7.2) for the highest fifth percentile. For von Willebrand factor, the hazard ratios in middle-aged subjects were 4.6 (95% CI: 2.2 to 9.2) for the highest quartile and 7.6 (95% CI: 3.1 to 18) for the highest fifth percentile. Factor VII levels above the 95th percentile, as compared with the lowest quartile, also conveyed a higher risk of venous thromboembolism (HR = 2.4; 95% CI: 1.2 to 4.8). In contrast, there was no association of venous thromboembolism with fibrinogen or C-reactive protein levels, or white cell count. CONCLUSIONS: In this prospective study, elevated factor VIII and von Willebrand factor levels were common, independent, and dose-dependent risk factors for venous thromboembolism, and an elevated factor VII level was a possible risk factor. Venous thromboembolism, unlike arterial disease, was not related to inflammatory markers.
Keywords: Aged; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cohort Studies; Confidence Intervals; Factor VII; Female; Fibrinogen; Humans; Inflammation Mediators; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Risk Assessment; Risk Factors; Sensitivity and Specificity; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Frailty and activation of the inflammation and coagulation systems with and without clinical comorbidities: results from the Cardiovascular Health Study. - Walston, Jeremy; McBurnie, Mary Ann; Newman, Anne; Tracy, Russell P; Kop, Willem J; Hirsch, Calvin H; Gottdiener, John; Fried, Linda P (Arch Intern Med, 2002)
BACKGROUND: The biological basis of frailty has been difficult to establish owing to the lack of a standard definition, its complexity, and its frequent coexistence with illness. OBJECTIVE: To establish the biological correlates of frailty in the presence and absence of concurrent cardiovascular disease and diabetes mellitus. METHODS: Participants were 4735 community-dwelling adults 65 years and older. Frail, intermediate, and nonfrail subjects were identified by a validated screening tool and exclusion criteria. Bivariate relationships between frailty level and physiological measures were evaluated by Pearson chi2 tests for categorical variables and analysis of variance F tests for continuous variables. Multinomial logistic regression was performed to evaluate multivariable relationships between frailty status and physiological measures. RESULTS: Of 4735 Cardiovascular Health Study participants, 299 (6.3%) were identified as frail, 2147 (45.3%) as intermediate, and 2289 (48.3%) as not frail. Frail vs nonfrail participants had increased mean +/- SD levels of C-reactive protein (5.5 +/- 9.8 vs 2.7 +/- 4.0 mg/L), factor VIII (13 790 +/- 4480 vs 11 860 +/- 3460 mg/dL), and, in a smaller subset, D dimer (647 +/- 1033 vs 224 +/- 258 ng/mL) (P< or =.001 for all, chi2 test for trend). These differences persisted when individuals with cardiovascular disease and diabetes were excluded and after adjustment for age, sex, and race. CONCLUSIONS: These findings support the hypothesis that there is a specific physiological basis to the geriatric syndrome of frailty that is characterized in part by increased inflammation and elevated markers of blood clotting and that these physiological differences persist when those with diabetes and cardiovascular disease are excluded.
Keywords: Aged; Aged, 80 and over; Blood Coagulation Disorders; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Diabetes Mellitus; Female; Frail Elderly; Geriatric Assessment; Humans; Inflammation; Longitudinal Studies; Male

In the elderly, interleukin-6 plasma levels and the -174G>C polymorphism are associated with the development of cardiovascular disease. - Jenny, Nancy S; Tracy, Russell P; Ogg, Malcolm S; Luong, Le Ahn; Kuller, Lewis H; Arnold, Alice M; Sharrett, A Richey; Humphries, Steve E (Arterioscler Thromb Vasc Biol, 2002)
OBJECTIVE: Interleukin (IL)-6-mediated inflammation is involved in cardiovascular disease (CVD). We assessed IL-6 levels and the -174G>C genotype in a case-control study of men and women (average age 73 years) within the Cardiovascular Health Study. METHODS AND RESULTS: Cases included incident angina, myocardial infarction (MI), and stroke (5-year follow-up), prevalent MI, and MRI-detectable infarcts. A control group and a group free of subclinical CVD were used for comparison. The -174C allele was associated with higher C-reactive protein (11% higher, P=0.02), fibrinogen (3% higher, P=0.02), and IL-6 (5% higher; P=0.16). IL-6 was associated with increased atherosclerosis when the control group was compared with the group free of subclinical CVD. No further association with CVD events was found when case groups were compared with the control group. Compared with its absence, presence of the -174C allele was associated with risk of MRI infarcts (odds ratio 1.5). CONCLUSIONS: IL-6 levels differentiated those with subclinical CVD from those without. Although the -174C allele was not associated with incident events, associations of the genotype with inflammation and MRI infarcts, combined with the plasma IL-6 results, suggest that IL-6 may chronically predispose an individual to develop atherosclerosis.
Keywords: Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Case-Control Studies; Cytosine; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Guanine; Health Surveys; Humans; Inflammation; Interleukin-6; Linear Models; Male; Polymorphism, Genetic; Predictive Value of Tests; Promoter Regions, Genetic

Inflammation and coagulation factors in persons > 65 years of age with symptoms of depression but without evidence of myocardial ischemia. - Kop, Willem J; Gottdiener, John S; Tangen, Catherine M; Fried, Linda P; McBurnie, Mary Ann; Walston, Jeremy; Newman, Anne; Hirsch, Calvin; Tracy, Russell P (Am J Cardiol, 2002)
Depression is associated with increased cardiovascular disease, but the underlying mechanisms are not well understood. This study examines associations of depressive symptoms with inflammation and coagulation factors in persons aged > 65 years. Blood samples were obtained from 4,268 subjects free of cardiovascular disease (age 72.4 +/- 5.5 years, 2,623 women). Inflammation markers were C-reactive protein (CRP), white blood cell (WBC) count, total platelet count, and albumin; coagulation factors included factors VIIc and VIIIc and fibrinogen. Depression was assessed with the Center for Epidemiologic Studies Depression scale, and states of energy depletion with a validated exhaustion index. Statistical adjustments were made for risk factors (age, sex, race, systolic blood pressure, smoking status, diabetes mellitus) and physical measures of frailty (isometric handgrip, timed 15-feet walk test, activity level). Depression was associated with elevated CRP (3.31 +/- 0.10 vs 3.51 +/- 0.21 mg/L), WBC (6.14 +/- 0.03 vs 6.43 +/- 0.11 10(6)/L), fibrinogen (319 +/- 1 vs 326 +/- 3 mg/dl), and factor VIIc (124.6 +/- 0.6% vs 127.2 +/- 1.3%; all p <0.05). Exhaustion also was related to elevated inflammation and coagulation markers (p < 0.05). Exhausted men had markedly elevated CRP levels (6.82 +/- 2.10 mg/L) versus nonexhausted men (3.05 +/- 0.16: p = 0.007). After adjustment for control variables, exhaustion remained associated with albumin (p = 0.033), fibrinogen (p = 0.017), CRP (p = 0.066), and WBC (p = 0.060), whereas associations of depressive symptoms with biochemistry measures lost statistical significance. Thus, depression and exhaustion are associated with low-grade inflammation and elevated coagulation factors in persons aged > 65 years.
Keywords: Aged; Blood Chemical Analysis; Blood Coagulation Factors; Cardiovascular Diseases; Depression; Female; Humans; Inflammation; Male; Risk Factors

Left atrial dimensions determined by M-mode echocardiography in black and white older (> or =65 years) adults (The Cardiovascular Health Study). - Manolio, Teri A; Gottdiener, John S; Tsang, Teresa S M; Gardin, Julius M (Am J Cardiol, 2002)
Stroke and atrial fibrillation are common and serious illnesses in the elderly, the risks of which are substantially increased by left atrial (LA) enlargement. Despite growing recognition of the importance of LA enlargement, the distribution and correlates of LA dimension in the elderly have not been well defined. A total of 3,882 women and men aged >65 years were studied. Increased LA dimension was independently associated with increased weight, mitral annular calcium, regional wall motion abnormalities, mitral early peak inflow velocity, and left ventricular (LV) fractional shortening. Increased LA dimension was negatively associated with aortic leaflet thickening. The relation with LV fractional shortening was curvilinear with a nadir at 35% to 40%. LA dimension in black men was approximately 1.9 mm less than in white men in multivariate analyses. Adjustment for spirometric lung volumes and chest dimensions appeared to diminish the race-LA dimension relation. Thus, LA dimension is strongly associated with weight and with several echocardiographic valvular abnormalities; its relation with LV fractional shortening is U-shaped with a nadir at the borderline of LV functional impairment.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Blood Flow Velocity; Body Weight; Cardiovascular Diseases; Echocardiography; Electrocardiography; European Continental Ancestry Group; Evidence-Based Medicine; Female; Heart Atria; Heart Ventricles; Humans; Male; Multivariate Analysis; Prospective Studies; Risk Factors; Statistics as Topic; Ventricular Function, Left

No association of plasma prothrombin concentration or the G20210A mutation with incident cardiovascular disease: results from the Cardiovascular Health Study. - Smiles, Adam M; Jenny, Nancy S; Tang, Zhonghua; Arnold, Alice; Cushman, Mary; Tracy, Russell P (Thromb Haemost, 2002)
Prothrombin is a key factor in blood clotting, a process intimately involved in thrombotic disease. We assessed prothrombin levels and G20210A genotype in a case-control study within the Cardiovascular Health Study. Cases included angina, myocardial infarction, stroke, and the presence of MRI-detectable infarcts (n approximately 250 each). Population-based controls free of clinical cardiovascular disease (CVD) (n approximately 500) and a subset free of clinical and subclinical CVD (n approximately 250) were used for comparison. The 20210 A allele, frequency 2.9%, was associated with higher mean prothrombin levels: 166.3 vs. 139.5 microg/ml (P <0.001). Significant correlates of prothrombin included gender, plasma lipids, other vitamin K-dependent proteins, and inflammatory markers, but not race, smoking, hypertension, diabetes, measures of subclinical CVD, or markers of procoagulant activity. Compared to controls, neither genotype nor prothrombin level was associated with any CVD case group. We conclude that, in the elderly, neither prothrombin level nor 20210 genotype were associated with either CVD risk factors or events. This is consistent with the lack of association of prothrombin levels with measures of underlying CVD or procoagulant markers.
Keywords: 3' Untranslated Regions; Aged; Aged, 80 and over; Alleles; Angina Pectoris; Blood Proteins; Cardiovascular Diseases; Case-Control Studies; Comorbidity; Diabetes Mellitus; Female; Genetic Predisposition to Disease; Humans; Hyperlipidemias; Hypertension; Male; Mutation; Myocardial Infarction; Obesity; Promoter Regions, Genetic; Prothrombin; Risk Factors; Smoking; Stroke; Vermont

Nuclear magnetic resonance spectroscopy of lipoproteins and risk of coronary heart disease in the cardiovascular health study. - Kuller, Lewis; Arnold, Alice; Tracy, Russell; Otvos, James; Burke, Greg; Psaty, Bruce; Siscovick, David; Freedman, David S; Kronmal, Richard (Arterioscler Thromb Vasc Biol, 2002)
OBJECTIVES: Relationships between incident cardiovascular disease and lipoprotein subclass measurements by nuclear magnetic resonance spectroscopy were evaluated in the Cardiovascular Health Study (CHS) in a nested case-cohort analysis. METHODS AND RESULTS: The case group consisted of 434 participants with incident myocardial infarction (MI) and angina diagnosed after entry to the study (1990 to 1995) and the comparison group, 249 "healthy" participants with no prevalent clinical or subclinical disease. By univariate analysis, the median levels for healthy participants versus participants with incident MI and angina were 0 versus 7 mg% for small low density lipoprotein (LDL), 1501 versus 1680 nmol/L for the number of LDL particles, and 21.6 versus 21.3 for LDL size, and these values were significantly different between "healthy" participants and those with incident MI and angina for women but not men. The levels of less dense LDL, which is most of the total LDL cholesterol among women, was not related to incident MI and angina. For women, large high density lipoprotein cholesterol (HDLc), but not small HDLc, levels were significantly higher for healthy participants compared with levels for participants with MI and angina. For men and women, levels of total and very low density lipoprotein triglycerides were higher for the case group than for the healthy group. In multivariate models for women that included triglycerides and HDLc, the number of LDL particles (but not LDL size) remained significantly related to MI and angina. CONCLUSIONS: Small LDL, the size of LDL particles, and the greater number of LDL particles are related to incident coronary heart disease among older women.
Keywords: Aged; Aging; Cardiovascular System; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Health Status; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Magnetic Resonance Spectroscopy; Male; Nuclear Magnetic Resonance, Biomolecular; Risk Factors; Sex Factors

Prospective study of the G20210A polymorphism in the prothrombin gene, plasma prothrombin concentration, and incidence of venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Aleksic, Nena (Am J Hematol, 2002)
Case-control studies have indicated increased risk of venous thrombosis associated with the prothrombin gene G20210A polymorphism and with elevated plasma prothrombin levels. We sought to confirm these results in a prospective population-based study of 21,690 persons. We measured G20210A and prothrombin antigen on pre-event blood samples of 302 participants who developed venous thromboembolism (VTE) and 626 participants who remained free of VTE. Approximately 4.0% of cases and 2.4% of controls carried the G20210A polymorphism, but only one of 137 African Americans did. The odds ratio in whites was 1.87 (95% CI = 0.85, 4.11)--higher for those who reported a prior history of VTE (OR = 5.44) than those reporting no VTE history (OR = 1.41) and in those with idiopathic VTE (OR = 2.51) than those with secondary VTE (OR = 1.38). There was no association between venous thromboembolism and plasma prothrombin antigen level. We estimated that the G20210A polymorphism may account for approximately 2.5% of venous thromboembolism events in United States whites.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Case-Control Studies; European Continental Ancestry Group; Genotype; Humans; Incidence; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Prospective Studies; Prothrombin; Recurrence; Research Design; Risk Factors; Thromboembolism; United States

A prospective study of venous thromboembolism in relation to factor V Leiden and related factors. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Aleksic, Nena; Heckbert, Susan R; Boland, Lori L; Tsai, Albert W; Yanez, N David; Rosamond, Wayne D (Blood, 2002)
The aim of this study was to examine the occurrence of venous thromboembolism (VTE) in relation to factor V-related risk factors. Using a nested case-control design combining 2 population-based prospective studies, we measured factor V Leiden, HR2 haplotype, activated protein C (APC) resistance, and plasma factor V antigen in 335 participants who developed VTE during 8 years of follow-up and 688 controls. The overall odds ratio (OR) of VTE was 3.67 (95% CI, 2.20-6.12) in participants carrying factor V Leiden compared with noncarriers. APC resistance measured after predilution with factor V-deficient plasma conferred an OR of 2.58 (95% CI, 1.62-4.10). All 3 participants homozygous for the HR2 haplotype had a VTE, and the OR of VTE for homozygosity was estimated to be 5.5 (95% CI, 2.45-12.5). Carriers of the HR2 haplotype otherwise were not at increased risk of VTE overall (OR = 1.05; 95% CI, 0.64-1.72), but double heterozygotes for HR2 and factor V Leiden carried an OR of idiopathic VTE of 16.3 (95% CI, 1.7-159) compared with noncarriers. Factor V antigen also was not associated with VTE overall, but for participants with the combination of high factor V antigen plus factor V Leiden the OR of idiopathic VTE was 11.5 (95% CI, 4.2-31.4). In the general population, APC resistance and factor V Leiden were important VTE risk factors; homozygosity for the HR2 haplotype may be a risk factor but was rare; otherwise, HR2 haplotype and factor V antigen were not risk factors except in carriers of factor V Leiden.
Keywords: Activated Protein C Resistance; Aged; Cohort Studies; Continental Population Groups; Factor V; Genotype; Haplotypes; Humans; Incidence; Longitudinal Studies; Middle Aged; Odds Ratio; Prospective Studies; Risk Factors; Thromboembolism; Venous Thrombosis

The relation of atherosclerotic cardiovascular disease to retinopathy in people with diabetes in the Cardiovascular Health Study. - Klein, Ronald; Marino, Emily K; Kuller, Lewis H; Polak, Joseph F; Tracy, Russell P; Gottdiener, John S; Burke, Gregory L; Hubbard, Larry D; Boineau, Robin (Br J Ophthalmol, 2002)
AIMS: To describe the association of retinopathy with atherosclerosis and atherosclerotic risk factors in people with diabetes. METHODS: 296 of the 558 people classified as having diabetes by the American Diabetes Association criteria, from a population based cohort of adults (ranging in age from 69 to 102 years) living in four United States communities (Allegheny County, Pennsylvania; Forsyth County, North Carolina; Sacramento County, California; and Washington County, Maryland) were studied from 1997 to 1998. Lesions typical of diabetic retinopathy were determined by grading a 45 degrees colour fundus photograph of one eye of each participant, using a modification of the Airlie House classification system. RESULTS: Retinopathy was present in 20% of the diabetic cohort, with the lowest prevalence (16%), in those 80 years of age or older. Retinopathy was detected in 20.3% of the 296 people with diabetes; 2.7% of the 296 had signs of proliferative retinopathy and 2.1% had signs of macular oedema. The prevalence of diabetic retinopathy was higher in black people (35.4%) than white (16.0%). Controlling for age, sex, and blood glucose, retinopathy was more frequent in black people than white (odds ratio (OR) 2.26, 95% confidence interval (CI) 1.01, 5.05), in those with longer duration of diabetes (OR (per 5 years of diabetes) 1.42, 95% CI 1.18, 1.70), in those with subclinical cardiovascular disease (OR 1.49, 95% CI 0.51, 4.31), or coronary heart disease or stroke (OR 3.23, 95% CI 1.09, 9.56) than those without those diseases, in those with higher plasma low density lipoprotein (LDL) cholesterol (OR (per 10 mg/dl of LDL cholesterol) 1.12, 95% CI 1.02, 1.23), and in those with gross proteinuria (OR 4.76, 95% CI 1.53, 14.86). CONCLUSION: Data from this population based study suggest a higher prevalence of retinopathy in black people than white people with diabetes and the association of cardiovascular disease, elevated plasma LDL cholesterol, and gross proteinuria with diabetic retinopathy. However, any conclusions or explanations regarding associations described here must be made with caution because only about one half of those with diabetes mellitus were evaluated.
Keywords: Age of Onset; Aged; Aged, 80 and over; Arteriosclerosis; Black People; Blood Pressure; Cohort Studies; Diabetes Mellitus, Type 2; Diabetic Retinopathy; Female; Humans; Longitudinal Studies; Male; Odds Ratio; Prospective Studies; Regression Analysis; Risk Factors; Time Factors; White People

Retinal microvascular abnormalities and blood pressure in older people: the Cardiovascular Health Study. - Wong, T Y; Hubbard, L D; Klein, R; Marino, E K; Kronmal, R; Sharrett, A R; Siscovick, D S; Burke, G; Tielsch, J M (Br J Ophthalmol, 2002)
AIM: To examine the relation between blood pressure and retinal microvascular abnormalities in older people. METHODS: The Cardiovascular Health Study is a prospective cohort study conducted in four US communities initiated in 1989 to 1990. Blood pressure was measured according to standardised protocols at each examination. During the 1997-8 examination, retinal photographs were taken of 2405 people aged 69-97 years (2056 without diabetes and 349 with diabetes). Signs of focal microvascular abnormalities (focal arteriolar narrowing, arteriovenous nicking, and retinopathy) were evaluated from photographs according to standardised methods. To quantify generalised arteriolar narrowing, the photographs were digitised and diameters of individual arterioles were measured and summarised. RESULTS: In non-diabetic people, elevated concurrent blood pressure taken at the time of retinal photography was strongly associated with presence of all retinal microvascular lesions. The multivariable adjusted odds ratios, comparing the highest to lowest quintile of concurrent systolic blood pressure, were 4.0 (95% confidence intervals (CI): 2.4 to 6.9, p test of trend<0.001) for focal arteriolar narrowing, 2.9 (95% CI: 1.6 to 5.3, p<0.001) for arteriovenous nicking, 2.8 (95% CI: 1.5 to 5.2, p<0.001) for retinopathy, and 2.1 (95% CI: 1.4 to 3.1, p<0.001) for generalised arteriolar narrowing. Generalised arteriolar narrowing and possibly arteriovenous nicking were also significantly associated with past blood pressure measured up to 8 years before retinal photography, even after adjustment for concurrent blood pressure. These associations were somewhat weaker in people with diabetes. CONCLUSIONS: Retinal microvascular abnormalities are related to elevated concurrent blood pressure in older people. Additionally, generalised retinal arteriolar narrowing and possibly arteriovenous nicking are related to previously elevated blood pressure, independent of concurrent blood pressure. These data suggest that retinal microvascular changes reflect severity and duration of hypertension.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cohort Studies; Diabetic Retinopathy; Eye; Female; Humans; Male; Microcirculation; Prospective Studies; Retina; Retinal Diseases

The 6-min walk test: a quick measure of functional status in elderly adults. - Enright, Paul L; McBurnie, Mary Ann; Bittner, Vera; Tracy, Russell P; McNamara, Robert; Arnold, Alice; Newman, Anne B (Chest, 2003)
OBJECTIVES: To determine the correlates of the total 6-min walk distance (6MWD) in a population sample of adults > or = 68 years old. METHODS: The standardized 6-min walk test (6MWT) was administered to the Cardiovascular Health Study cohort during their seventh annual examination. RESULTS: Of the 3,333 participants with a clinic visit, 2,281 subjects (68%) performed the 6MWT. There were no untoward events. The mean 6MWD was 344 m (SD, 88 m). Independent general correlates of a shorter 6MWD in linear regression models in women and men included the following: older age, higher weight, larger waist, weaker grip strength, symptoms of depression, and decreased mental status. Independent disease or risk factor correlates of a shorter 6MWD included the following: a low ankle BP, use of angiotensin-converting enzyme inhibitors, and arthritis in men and women; higher C-reactive protein, diastolic hypertension, and lower FEV(1) in women; and the use of digitalis in men. Approximately 30% of the variance in 6MWD was explained by the linear regression models. Newly described bivariate associations of a shorter 6MWD included impaired activities of daily living; self-reported poor health; less education; nonwhite race; a history of coronary heart disease, transient ischemic attacks, stroke, or diabetes; and higher levels of C-reactive protein, fibrinogen, or WBC count. CONCLUSIONS: Most community-dwelling elderly persons can quickly and safely perform this functional status test in the outpatient clinic setting. The test may be used clinically to measure the impact of multiple comorbidities, including cardiovascular disease, lung disease, arthritis, diabetes, and cognitive dysfunction and depression, on exercise capacity and endurance in older adults. Expected values should be adjusted for the patient's age, gender, height, and weight.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Exercise Test; Female; Humans; Ischemic Attack, Transient; Linear Models; Male; Mass Screening; Sensitivity and Specificity; Stroke; United States; Walking

Beta2-adrenergic receptor polymorphisms and risk of incident cardiovascular events in the elderly. - Heckbert, Susan R; Hindorff, Lucia A; Edwards, Karen L; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Tang, Zhonghua; Durda, J Peter; Kronmal, Richard A; Tracy, Russell P (Circulation, 2003)
BACKGROUND: Genetic polymorphisms at codons 16 and 27 of the beta2-adrenergic receptor have been associated with altered response to sympathetic stimulation. We examined these polymorphisms in relation to cardiovascular event risk in the Cardiovascular Health Study. METHODS AND RESULTS: A total of 808 black and 4441 white participants (mean age, 73 years) were genotyped for the Arg16Gly and Gln27Glu polymorphisms of the beta2-adrenergic receptor. There were 702 incident coronary events, 438 ischemic strokes, and 1136 combined cardiovascular events during 7 to 10 years of follow-up. Allele frequencies differed by race but not by age or hypertension status. Glu27 carriers had a lower risk of coronary events than Gln27 homozygotes (hazard ratio, 0.82; 95% CI, 0.70 to 0.95), and there was a suggestion of decreased risk among Gly16 carriers compared with Arg16 homozygotes (hazard ratio, 0.88; 95% CI, 0.72 to 1.07). There was no association of beta2-adrenergic receptor genotype with ischemic stroke or combined cardiovascular events. CONCLUSIONS: The Glu27 allele of the beta2-adrenergic receptor was associated with a lower risk of incident coronary events in this elderly population.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Cohort Studies; Comorbidity; Coronary Disease; European Continental Ancestry Group; Follow-Up Studies; Gene Frequency; Humans; Incidence; Linkage Disequilibrium; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Assessment; Stroke; United States

Cardiac benefits of fish consumption may depend on the type of fish meal consumed: the Cardiovascular Health Study. - Mozaffarian, Dariush; Lemaitre, Rozenn N; Kuller, Lewis H; Burke, Gregory L; Tracy, Russell P; Siscovick, David S (Circulation, 2003)
BACKGROUND: Few studies have examined associations of fish consumption with ischemic heart disease (IHD) risk among older adults or how different types of fish meals relate to IHD risk. METHODS AND RESULTS: In a population-based prospective cohort study, usual fish consumption was ascertained at baseline among 3910 adults aged > or =65 years and free of known cardiovascular disease in 1989 and 1990. Consumption of tuna and other broiled or baked fish correlated with plasma phospholipid long-chain n-3 fatty acids, whereas consumption of fried fish or fish sandwiches (fish burgers) did not. Over 9.3 years' mean follow-up, there were 247 IHD deaths (including 148 arrhythmic deaths) and 363 incident nonfatal myocardial infarctions (MIs). After adjustment for potential confounders, consumption of tuna or other broiled or baked fish was associated with lower risk of total IHD death (P for trend=0.001) and arrhythmic IHD death (P=0.001) but not nonfatal MI (P=0.44), with 49% lower risk of total IHD death and 58% lower risk of arrhythmic IHD death among persons consuming tuna/other fish 3 or more times per week compared with less than once per month. In similar analyses, fried fish/fish sandwich consumption was not associated with lower risk of total IHD death, arrhythmic IHD death, or nonfatal MI but rather with trends toward higher risk. CONCLUSIONS: Among adults aged > or =65 years, modest consumption of tuna or other broiled or baked fish, but not fried fish or fish sandwiches, is associated with lower risk of IHD death, especially arrhythmic IHD death. Cardiac benefits of fish consumption may vary depending on the type of fish meal consumed.
Keywords: Aged; Animals; Arrhythmias, Cardiac; Diet; Eating; Fatty Acids, Omega-3; Female; Fishes; Humans; Male; Myocardial Infarction; Myocardial Ischemia; Prospective Studies; Risk; Tuna

C-reactive protein, carotid intima-media thickness, and incidence of ischemic stroke in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Thach, Chau; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis H; Chaves, Paulo H M; Polak, Joseph F; Sutton-Tyrrell, Kim; Herrington, David M; Price, Thomas R; Cushman, Mary (Circulation, 2003)
BACKGROUND: Increased carotid artery intima-media thickness (IMT) and elevated C-reactive protein (CRP) are both associated with the occurrence of stroke. We investigated whether elevated CRP is a risk factor for ischemic stroke independent of carotid IMT and studied the interaction between CRP and IMT. METHODS AND RESULTS: We studied 5417 participants aged 65 years or older without preexisting stroke or chronic atrial fibrillation who were participants in the Cardiovascular Health Study. The hazard ratio of incident ischemic stroke was estimated by Cox proportional hazards regression. During 10.2 years of follow-up, 469 incident ischemic strokes occurred. The adjusted hazard ratios for ischemic stroke in the 2nd to 4th quartiles of baseline CRP, relative to the 1st quartile, were 1.19 (95% CI 0.92 to 1.53), 1.05 (95% CI 0.81 to 1.37), and 1.60 (95% CI 1.23 to 2.08), respectively. With additional adjustment for carotid IMT, there was little confounding. The association of CRP with stroke was significantly different depending on IMT (P<0.02), with no association of CRP with stroke among those in the lowest IMT tertile and a significant association among those with higher levels of IMT. CONCLUSIONS: We conclude that elevated CRP is a risk factor for ischemic stroke, independent of atherosclerosis severity as measured by carotid IMT. The association of CRP with stroke is more apparent in the presence of a higher carotid IMT. CRP and carotid IMT may each be independent integrals in determining the risk of ischemic stroke.
Keywords: Aged; Brain Ischemia; C-Reactive Protein; California; Carotid Arteries; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Maryland; North Carolina; Odds Ratio; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke; Tunica Intima; Tunica Media; Ultrasonography

Elevations of inflammatory and procoagulant biomarkers in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Circulation, 2003)
BACKGROUND: Renal insufficiency has been associated with cardiovascular disease events and mortality in several prospective studies, but the mechanisms for the elevated risk are not clear. Little is known about the association of renal insufficiency with inflammatory and procoagulant markers, which are potential mediators for the cardiovascular risk of kidney disease. METHODS AND RESULTS: The cross-sectional association of renal insufficiency with 8 inflammatory and procoagulant factors was evaluated using baseline data from the Cardiovascular Health Study, a population-based cohort study of 5888 subjects aged > or =65 years. C-reactive protein, fibrinogen, factor VIIc, and factor VIIIc levels were measured in nearly all participants; interleukin-6, intercellular adhesion molecule-1, plasmin-antiplasmin complex, and D-dimer levels were measured in nearly half of participants. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. Multivariate linear regression was used to compare adjusted mean levels of each biomarker in persons with and without renal insufficiency after adjustment for other baseline characteristics. Renal insufficiency was present in 647 (11%) of Cardiovascular Health Study participants. After adjustment for baseline differences, levels of C-reactive protein, fibrinogen, interleukin-6, factor VIIc, factor VIIIc, plasmin-antiplasmin complex, and D-dimer were significantly greater among persons with renal insufficiency (P<0.001). In participants with clinical, subclinical, and no cardiovascular disease at baseline, the positive associations of renal insufficiency with these inflammatory and procoagulant markers were similar. CONCLUSION: Renal insufficiency was independently associated with elevations in inflammatory and procoagulant biomarkers. These pathways may be important mediators leading to the increased cardiovascular risk of persons with kidney disease.
Keywords: Aged; alpha-2-Antiplasmin; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Creatinine; Cross-Sectional Studies; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysin; Humans; Inflammation; Interleukin-6; Male; Prospective Studies; Renal Insufficiency; Risk Factors

Fibrin fragment D-dimer and the risk of future venous thrombosis. - Cushman, Mary; Folsom, Aaron R; Wang, Lu; Aleksic, Nena; Rosamond, Wayne D; Tracy, Russell P; Heckbert, Susan R (Blood, 2003)
Plasma D-dimer concentration rises more than 100-fold during acute deep vein thrombosis, but there are no prospective data concerning D-dimer as a risk factor for incident venous thrombosis in a general population. Incident venous thrombosis was ascertained in 2 prospective observational studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Of 21 690 participants enrolled between 1987 and 1993, after 8 years of follow-up, D-dimer was measured using baseline stored plasma of 307 participants who developed venous thrombosis and 616 who did not. Relative to the first quintile of the distribution of D-dimer, the age-adjusted odds ratios for future venous thrombosis for the second to fifth quintiles of D-dimer were 1.6, 2.3, 2.3, and 4.2, respectively (P for trend <.0001). Following added adjustment for sex, race, body mass index, factor V Leiden, prothrombin 20210A, and elevated factor VIII coagulant activity (factor VIII:c), these odds ratios were 1.5, 2.1, 1.9, and 3.0, respectively (P for trend <.0001). Among those with idiopathic thrombosis or secondary thrombosis unrelated to cancer, the adjusted fifth quintile odds ratios were 3.5 and 4.8, respectively. By contrast, D-dimer in the fifth versus first quintile was not related to occurrence of cancer-associated thrombosis (odds ratio, 1.1). Odds ratios for elevated D-dimer were consistently elevated in subgroups defined by age, sex, race, duration of follow-up, and thrombosis type (deep vein thrombosis or pulmonary embolus). D-dimer is strongly and positively related to the occurrence of future venous thrombosis.
Keywords: Aged; Body Mass Index; Cohort Studies; Continental Population Groups; Factor V; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Prothrombin; Risk Factors; Venous Thrombosis

Inflammation as a risk factor for atrial fibrillation. - Aviles, Ronnier J; Martin, David O; Apperson-Hansen, Carolyn; Houghtaling, Penny L; Rautaharju, Pentti; Kronmal, Richard A; Tracy, Russell P; Van Wagoner, David R; Psaty, Bruce M; Lauer, Michael S; Chung, Mina K (Circulation, 2003)
BACKGROUND: The presence of systemic inflammation determined by elevations in C-reactive protein (CRP) has been associated with persistence of atrial fibrillation (AF). The relationship between CRP and prediction of AF has not been studied in a large population-based cohort. METHODS AND RESULTS: CRP measurement and cardiovascular assessment were performed at baseline in 5806 subjects enrolled in the Cardiovascular Health Study. Patients were followed up for a mean of 6.9+/-1.6 (median 7.8) years. AF was identified by self-reported history and ECGs at baseline and by ECGs and hospital discharge diagnoses at follow-up. Univariate and multivariate analyses were used to assess CRP as a predictor of baseline and future development of AF. At baseline, 315 subjects (5%) had AF. Compared with subjects in the first CRP quartile (<0.97 mg/L), subjects in the fourth quartile (>3.41 mg/L) had more AF (7.4% versus 3.7%, adjusted OR 1.8, 95% CI 1.2 to 2.5; P=0.002). Of 5491 subjects without AF at baseline, 897 (16%) developed AF during follow-up. Baseline CRP predicted higher risk for developing future AF (fourth versus first quartile adjusted hazard ratio 1.31, 95% CI 1.08 to 1.58; P=0.005). When treated as a continuous variable, elevated CRP predicted increased risk for developing future AF (adjusted hazard ratio for 1-SD increase, 1.24; 95% CI 1.11 to 1.40; P<0.001). CONCLUSIONS: CRP is not only associated with the presence of AF but may also predict patients at increased risk for future development of AF.
Keywords: Aged; Atrial Fibrillation; C-Reactive Protein; Cross-Sectional Studies; Female; Humans; Inflammation; Longitudinal Studies; Male; Risk Factors

Lack of association of the plasminogen activator inhibitor-1 4G/5G promoter polymorphism with cardiovascular disease in the elderly. - Crainich, P; Jenny, N S; Tang, Z; Arnold, A M; Kuller, L H; Manolio, T; Sharrett, A R; Tracy, R P (J Thromb Haemost, 2003)
Elevated circulating plasminogen activator inhibitor-1 (PAI-1) may increase risk of cardiovascular disease (CVD). The 4G allele of the 4G/5G PAI-1 promoter polymorphism is associated with higher levels of PAI-1. We examined the association of PAI-1 4G/5G genotype and CVD events in the elderly participants of the Cardiovascular Health Study (CHS). We measured 4G/5G genotype in a nested case-control study within the CHS. Cases included incident angina, myocardial infarction (MI), and stroke. 4G/5G genotype was not found to be associated with markers of fibrinolysis or CVD risk in the selected elderly cohort. There were no differences in genotype frequencies by case-control status (5G/5G frequency 16-22%; chi2P= 0.07). The 5G allele was not associated with incident CVD events when individuals with at least one 5G allele were compared to 4G/4G homozygotes. The presence of at least one 4G allele was likewise not associated with incident CVD when those with 4G/4G and 4G/5G genotypes were compared to 5G/5G homozygotes. Our results suggest that the PAI-1 4G/5G promoter polymorphism is not associated CVD risk factors or incident CVD events in the elderly.
Keywords: African Continental Ancestry Group; Aged; Alleles; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Risk

Lp(a) lipoprotein, vascular disease, and mortality in the elderly. - Ariyo, Abraham A; Thach, Chau; Tracy, Russell (N Engl J Med, 2003)
BACKGROUND: As compared with what is known about predictors of vascular events in middle-aged persons, less is known about these events in the elderly. Lp(a) lipoprotein, which plays an important part in atherothrombogenesis, has been associated with an increased risk of vascular disease. We investigated this relation among older U.S. adults. METHODS: In a prospective study of 5888 community-dwelling older adults (65 years of age or older) in the United States, 2375 women and 1597 men who were free of vascular disease provided base-line serum samples for analysis for levels of Lp(a) lipoprotein. These 3972 subjects were followed for a median of 7.4 years to evaluate the development of stroke and to track deaths from vascular causes and all causes. The men and women were divided into quintile groups according to the Lp(a) lipoprotein level at base line. RESULTS: Using Cox proportional-hazards models, we determined the risk associated with each quintile level of Lp(a) lipoprotein, with the lowest quintile serving as the reference group. As compared with those in the lowest quintile, men in the highest quintile had three times the unadjusted risk of stroke (relative risk, 3.00; 95 percent confidence interval, 1.59 to 5.65), almost three times the risk of death associated with vascular events (relative risk, 2.54; 95 percent confidence interval, 1.59 to 4.08), and nearly twice the risk of death from all causes (relative risk, 1.76; 95 percent confidence interval, 1.31 to 2.36). Adjustment for age; sex; the levels of total cholesterol, low-density lipoprotein cholesterol, and triglycerides; carotid-wall thickness; smoking status; the presence or absence of diabetes and systolic and diastolic hypertension; body-mass index; and other traditional risk factors had little effect on the final assessments. Similar analyses for women, which also included adjustment for estrogen use or nonuse, revealed no such relation. CONCLUSIONS: Among older adults in the United States, an elevated level of Lp(a) lipoprotein is an independent predictor of stroke, death from vascular disease, and death from any cause in men but not in women. These data support the use of Lp(a) lipoprotein levels in predicting the risk of these events in older men.
Keywords: Aged; Coronary Disease; Female; Humans; Incidence; Lipoprotein(a); Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Stroke; Survival Analysis; United States; Vascular Diseases

n-3 Polyunsaturated fatty acids, fatal ischemic heart disease, and nonfatal myocardial infarction in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; King, Irena B; Mozaffarian, Dariush; Kuller, Lewis H; Tracy, Russell P; Siscovick, David S (Am J Clin Nutr, 2003)
BACKGROUND: Little is known about the relation of the dietary intake of n-3 polyunsaturated fatty acids, ie, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) from fatty fish and alpha-linolenic acid from vegetable oils, with ischemic heart disease among older adults. OBJECTIVE: We investigated the associations of plasma phospholipid concentrations of DHA, EPA, and alpha-linolenic acid as biomarkers of intake with the risk of incident fatal ischemic heart disease and incident nonfatal myocardial infarction in older adults. DESIGN: We conducted a case-control study nested in the Cardiovascular Health Study, a cohort study of adults aged > or = 65 y. Cases experienced incident fatal myocardial infarction and other ischemic heart disease death (n = 54) and incident nonfatal myocardial infarction (n = 125). Matched controls were randomly selected (n = 179). We measured plasma phospholipid concentrations of n-3 polyunsaturated fatty acids in blood samples drawn approximately 2 y before the event. RESULTS: A higher concentration of combined DHA and EPA was associated with a lower risk of fatal ischemic heart disease, and a higher concentration of alpha-linolenic acid with a tendency to lower risk, after adjustment for risk factors [odds ratio: 0.32 (95% CI: 0.13, 0.78; P = 0.01) and 0.52 (0.24, 1.15; P = 0.1), respectively]. In contrast, n-3 polyunsaturated fatty acids were not associated with nonfatal myocardial infarction. CONCLUSIONS: Higher combined dietary intake of DHA and EPA, and possibly alpha-linolenic acid, may lower the risk of fatal ischemic heart disease in older adults. The association of n-3 polyunsaturated fatty acids with fatal ischemic heart disease, but not with nonfatal myocardial infarction, is consistent with possible antiarrhythmic effects of these fatty acids.
Keywords: Aged; alpha-Linolenic Acid; Biomarkers; Case-Control Studies; Cohort Studies; Coronary Disease; Dietary Supplements; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Female; Fish Oils; Humans; Incidence; Male; Myocardial Infarction; Odds Ratio; Phospholipids; Prevalence; Prospective Studies; Risk Factors

The prevalence and risk factors of retinal microvascular abnormalities in older persons: The Cardiovascular Health Study. - Wong, Tien Yin; Klein, Ronald; Sharrett, A Richey; Manolio, Teri A; Hubbard, Larry D; Marino, Emily K; Kuller, Lewis; Burke, Gregory; Tracy, Russell P; Polak, Joseph F; Gottdiener, John S; Siscovick, David S (Ophthalmology, 2003)
PURPOSE: To describe the prevalence of retinal microvascular characteristics and their associations with atherosclerosis in elderly, nondiabetic persons. DESIGN AND PARTICIPANTS: Population-based, cross-sectional study comprising 2050 men and women aged 69 to 97 years without diabetes, living in four communities. METHODS: Participants underwent retinal photography and standardized grading of retinal microvascular characteristics, including retinopathy (e.g., microaneurysms, retinal hemorrhages), focal arteriolar narrowing, and arteriovenous nicking. In addition, calibers of retinal arterioles and venules were measured on digitized photographs to obtain an estimate of generalized arteriolar narrowing. Atherosclerosis and its risk factors were obtained from clinical examination and laboratory investigations. MAIN OUTCOME MEASURES: Prevalence of retinal microvascular abnormalities and their associations with measures of atherosclerosis. RESULTS: The prevalence of retinal microvascular abnormalities was 8.3% for retinopathy, 9.6% for focal arteriolar narrowing, and 7.7% for arteriovenous nicking. All retinal lesions were associated with hypertension (odds ratios [OR] were 1.8 for retinopathy, 2.1 for focal arteriolar narrowing, 1.5 for arteriovenous nicking, and 1.7 for generalized arteriolar narrowing). After controlling for age, gender, race, mean arterial blood pressure, and antihypertensive medication use, retinopathy was associated with prevalent coronary heart disease (OR, 1.7), prevalent myocardial infarction (OR, 1.7), prevalent stroke (OR, 2.0), presence of carotid artery plaque (OR, 1.9), and increased intima-media thickness of the common carotid (OR, 2.3; fourth vs. first quartile) and internal carotid (OR, 1.8; fourth vs. first quartile) arteries. In contrast, focal arteriolar narrowing, arteriovenous nicking, and generalized arteriolar narrowing were not associated with any measures of atherosclerosis. CONCLUSIONS: Retinal microvascular abnormalities are common in older persons without diabetes and are related to hypertension. Retinopathy is associated with prevalent coronary heart disease, stroke, and carotid artery thickening, but focal and generalized arteriolar narrowing and arteriovenous nicking are not related to most measures of atherosclerosis. These data suggest that retinal microvascular abnormalities reflect processes associated with hypertension but distinct from atherosclerosis.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Coronary Artery Disease; Cross-Sectional Studies; Female; Humans; Hypertension; Male; Prevalence; Retinal Diseases; Retinal Vessels; Risk Factors; United States

Prospective study of the A455V polymorphism in the thrombomodulin gene, plasma thrombomodulin, and incidence of venous thromboembolism: the LITE Study. - Aleksic, N; Folsom, A R; Cushman, M; Heckbert, S R; Tsai, M Y; Wu, K K (J Thromb Haemost, 2003)
Plasma thrombomodulin (soluble TM; sTM) is considered to be a marker of endothelial injury, but a recent report indicated that the relationship of sTM with thrombosis is complex. Venous thromboembolic events were identified in adults in two longitudinal cohort studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, totaling 21 690 participants. After 8 years of follow-up, sTM was measured in baseline plasma of 305 participants who developed venous thrombosis and 607 who did not. Thrombomodulin A455V genotype was determined in 302 cases and 626 controls. There was no difference in the prevalence of the three TM genotypes between cases and controls and no difference in age-adjusted mean values of sTM by genotype. There were no associations of age-adjusted sTM or TMA455V genotype with overall venous thromboembolism or with thrombosis in any subtype of venous thromboembolism.
Keywords: Age Factors; Aged; Amino Acid Substitution; Case-Control Studies; Female; Genotype; Humans; Incidence; Male; Polymorphism, Genetic; Prevalence; Prospective Studies; Risk Factors; Thromboembolism; Thrombomodulin; Venous Thrombosis

Serum homocysteine, thermolabile variant of methylene tetrahydrofolate reductase (MTHFR), and venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology (LITE). - Tsai, Albert W; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena; Yanez, N David; Psaty, Bruce M; Folsom, Aaron R (Am J Hematol, 2003)
We sought to examine prospectively the association of serum homocysteine and the methylene tetrahydrofolate reductase (MTHFR) C677T gene polymorphism with risk of venous thromboembolism (VTE). We studied these relationships in a nested case-control study of 303 VTE cases and 635 matched controls from a population-based cohort of 21,680 adults from six U.S. communities. The highest quintile of serum homocysteine carried a non-statistically significant adjusted odds ratio of 1.55 (95% CI, 0.93-2.58) compared to the lowest quintile in the overall cohort but a significant association among adults aged 45-64 years (OR = 2.05, 95% CI, 1.10-3.83) and an inverse association in those > or = 65 years of age. Carriers of the MTHFR C677T polymorphism were not at higher risk for VTE than those with normal genotype (OR = 0.74, 95% CI = 0.56-0.98). Our prospective data showed, at most, a weak relationship between homocysteine and VTE risk, with associations larger among younger participants. MTHFR C677T was not a risk factor for VTE.
Keywords: Aged; Aging; Animals; Case-Control Studies; Cohort Studies; Factor V; Female; Genotype; Homocysteine; Humans; Longitudinal Studies; Male; Methylenetetrahydrofolate Reductase (NADPH2); Middle Aged; Odds Ratio; Oxidoreductases Acting on CH-NH Group Donors; Polymorphism, Genetic; Prospective Studies; Risk Factors; Venous Thrombosis

"Successful aging": effect of subclinical cardiovascular disease. - Newman, Anne B; Arnold, Alice M; Naydeck, Barbara L; Fried, Linda P; Burke, Gregory L; Enright, Paul; Gottdiener, John; Hirsch, Calvin; O'Leary, Daniel; Tracy, Russell (Arch Intern Med, 2003)
BACKGROUND: Cardiovascular diseases are the primary cause of death in older adults. Among those without clinical disease, high levels of subclinical disease are associated with poor survival. The effect of the extent of subclinical cardiovascular disease on the quality of the remaining years has not been defined. METHODS: In a longitudinal cohort study, 2932 men and women aged 65 years and older were followed up for 8 years to determine the likelihood of maintaining intact health and functioning. Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and with intact physical and cognitive functioning. RESULTS: Younger age at study entry and a lower extent of subclinical cardiovascular disease were independently associated with the likelihood of maintaining successful aging. In age-stratified summaries, those with subclinical disease had a trajectory of decline similar to subjects 5 years older without subclinical vascular disease. Regression analyses showed that the decline associated with subclinical disease was equivalent to 6.5 (95% confidence interval, 6.4-6.6) years of aging for women and 5.6 (95% confidence interval, 5.4-5.8) years of aging for men. Individual measures of the extent of cardiovascular disease, diabetes mellitus, smoking, and higher C-reactive protein level were also independently predictive of fewer years of successful aging, but none of these factors substantially attenuated the effect of age itself. CONCLUSIONS: There is a graded relationship between the extent of vascular disease measured noninvasively and the likelihood of maintaining intact health and function. Prevention of subclinical vascular disease may increase the quality and the quantity of years in late life.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Female; Health Status; Humans; Longitudinal Studies; Male; Quality of Life; Regression Analysis; Risk Factors

Alcohol consumption and inflammatory markers in older adults: the Cardiovascular Health Study. - Mukamal, Kenneth J; Cushman, Mary; Mittleman, Murray A; Tracy, Russell P; Siscovick, David S (Atherosclerosis, 2004)
OBJECTIVE: We sought to determine the relation of alcohol intake and systemic inflammation in a population-based sample of older adults. METHODS AND RESULTS: As part of the Cardiovascular Health Study (CHS), 5865 adults aged 65 years and older reported their intake of beer, wine, and liquor. We determined white blood cell count (WBC), factor VIII coagulant activity (factor VIIIc), and levels of C-reactive protein (CRP), fibrinogen, and albumin as markers of systemic inflammation. Among participants without confirmed cardiovascular disease, alcohol consumption was inversely associated with WBC, factor VIIIc, and fibrinogen level, and positively associated with albumin concentration in multivariate analyses. We found no consistent modification of these results by sex, obesity, or beverage type. The relation of alcohol use and CRP levels was significantly modified by apoE genotype (P interaction 0.03), with a positive association among participants with an apoE4 allele (P = 0.05), but a trend toward an inverse association among those without an apoE4 allele (P = 0.15). CONCLUSIONS: Alcohol intake is associated with lower levels of inflammatory markers in older adults free of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Apolipoproteins E; C-Reactive Protein; Coronary Artery Disease; Female; Fibrinogen; Geriatric Assessment; Humans; Inflammation Mediators; Leukocyte Count; Logistic Models; Longitudinal Studies; Male; Probability; Prospective Studies; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index

The association between lipid levels and the risks of incident myocardial infarction, stroke, and total mortality: The Cardiovascular Health Study. - Psaty, Bruce M; Anderson, Melissa; Kronmal, Richard A; Tracy, Russell P; Orchard, Trevor; Fried, Linda P; Lumley, Thomas; Robbins, John; Burke, Greg; Newman, Anne B; Furberg, Curt D (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the association between lipid levels and cardiovascular events in older adults. DESIGN: A prospective population-based study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: A total of 5,201 adults aged 65 and older living in U.S. communities, plus a recruitment of 687 African Americans 3 years later. MEASUREMENTS: Fasting lipid measures included low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, and triglycerides. RESULTS: At baseline, 1,954 men and 2,931 women were at risk for an incident myocardial infarction (MI) or stroke. During an average 7.5-year follow-up, 436 subjects had a coronary event, 332 had an ischemic stroke, 104 a hemorrhagic stroke, and 1,096 died. After adjustment, lipid measures were not major predictors of the outcomes of MI, ischemic stroke, hemorrhagic stroke, and total mortality. For total cholesterol and LDL-C, the associations with MI and ischemic stroke were only marginally significant. HDL-C was inversely associated with MI risk (hazard ratio=0.85 per standard deviation of 15.7 mg/dL, 95% confidence interval=0.76-0.96). For the outcome of ischemic stroke, high levels of HDL-C were associated with a decreased risk in men but not women. Lipid measures were generally only weakly associated with the risks of hemorrhagic stroke or total mortality. CONCLUSION: In this population-based study of older adults, most lipid measures were weakly associated with cardiovascular events. The association between low HDL-C and increased MI risk was nonetheless strong and consistent.
Keywords: African Americans; African Continental Ancestry Group; Aged; Female; Health Surveys; Humans; Incidence; Lipids; Male; Mortality; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk Factors; Stroke; United States

The association of fasting glucose levels with congestive heart failure in diabetic adults > or =65 years: the Cardiovascular Health Study. - Barzilay, Joshua I; Kronmal, Richard A; Gottdiener, John S; Smith, Nicholas L; Burke, Gregory L; Tracy, Russell; Savage, Peter J; Carlson, Michelle (J Am Coll Cardiol, 2004)
OBJECTIVES: The purpose of this study was to determine if fasting glucose levels are an independent risk factor for congestive heart failure (CHF) in elderly individuals with diabetes mellitus (DM) with or without coronary heart disease (CHD). BACKGROUND: Diabetes mellitus and CHF frequently coexist in the elderly. It is not clear whether fasting glucose levels in the setting of DM are a risk factor for incident CHF in the elderly. METHODS: A cohort of 829 diabetic participants, age > or =65 years, without prevalent CHF, was followed for five to eight years. The Cox proportional hazards modeling was used to determine the risk of CHF by fasting glucose levels. The cohort was categorized by the presence or absence of prevalent CHD. RESULTS: For a 1 standard deviation (60.6 mg/dl) increase in fasting glucose, the adjusted hazard ratios for incident CHF among participants without CHD at baseline, with or without an incident myocardial infarction (MI) or CHD event on follow-up, was 1.41 (95% confidence interval 1.24 to 1.61; p < 0.0001). Among those with prevalent CHD at baseline, with or without another incident MI or CHD event on follow-up, the corresponding adjusted hazard ratio was 1.27 (95% confidence interval 1.02 to 1.58; p < 0.05). CONCLUSIONS: Among older adults with DM, elevated fasting glucose levels are a risk factor for incident CHF. The relationship of fasting glucose to CHF differs somewhat by the presence or absence of prevalent CHD.
Keywords: Aged; Biomarkers; Blood Glucose; Blood Pressure; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Fasting; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Proportional Hazards Models; Risk Factors; Statistics as Topic; Stroke Volume; Ventricular Function, Left

Deep vein thrombosis and pulmonary embolism in two cohorts: the longitudinal investigation of thromboembolism etiology. - Cushman, Mary; Tsai, Albert W; White, Richard H; Heckbert, Susan R; Rosamond, Wayne D; Enright, Paul; Folsom, Aaron R (Am J Med, 2004)
PURPOSE: To determine the incidence of deep vein thrombosis and pulmonary embolism in two cohorts representing regions of the United States. METHODS: The sample comprised 21,680 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. Subjects were aged >/=45 years, resided in six communities, and were followed for 7.6 years. All hospitalizations were identified and thromboses were validated by chart review. RESULTS: The age-standardized incidence of first-time venous thromboembolism was 1.92 per 1000 person-years. Rates were higher in men than women, and increased with age in both sexes. There was no antecedent trauma, surgery, immobilization, or diagnosis of cancer for 48% (175/366) of events. The 28-day case-fatality rate was 11% (29/265) after a first venous thromboembolism and 25% (17/67) for cancer-associated thrombosis. The recurrence rate 2 years after a first venous thromboembolism was 7.7% per year (95% confidence interval [CI]: 4.5% to 10.9% per year). Cancer was the only factor independently associated with 28-day fatality (relative risk [RR] = 5.2; 95% CI: 1.4 to 19.9) or recurrent thrombosis (RR = 9.2; 95% CI: 2.0 to 41.7). CONCLUSION: The incidence of venous thromboembolism in this cohort of middle- and older-aged subjects was similar to that observed in more geographically homogeneous samples. Half of cases were idiopathic. Short-term mortality and 2-year recurrence rates were appreciable, especially among subjects with cancer. Based on this study we estimate that 187,000 cases of first-time venous thromboembolism are diagnosed yearly in the United States among those aged 45 years or older.
Keywords: Aged; Case-Control Studies; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasms; Population Surveillance; Pulmonary Embolism; Recurrence; Risk Factors; Survival Rate; Venous Thrombosis

Progressive cognitive impairment after stroke. - Toole, James F; Bhadelia, Rafeeque; Williamson, Jeff D; Veltkamp, Roland (J Stroke Cerebrovasc Dis, 2004)
OBJECTIVE: We examined the putative relationship between stroke and cognitive function in the population-based prospective cohort of the Cardiovascular Health Study (CHS). METHODS: Of the 5888 participants of the CHS aged 65 years or older, there were 5364 with more than one modified mini-mental (3MS) examination between 1992 and 1998. To determine the effect of baseline stroke before first and subsequent (stroke between two consecutive examinations) 3MS examination on cognitive function, linear regression models were computed with potential confounders entered as additional independent variables. Stroke was divided into right and left hemispheres or posterior circulation on the basis of the clinical and/or imaging information by the hospital that treated the event and subsequent adjudication by CHS committee. RESULTS: Participants with baseline stroke had an average 3MS decline of 1.2 (95% confidence interval [CI]: -0.7 - -1.7) points per year more than those without one. Those with a history of subsequent stroke had an average first year 3MS decline of 6.2 (CI -8.7 - -3.7) for left hemisphere, 3.5 (CI -5.3 - -1.8) for right hemisphere, and 1.1 (CI -3.9 - 1.6) for posterior circulation more than those without stroke. The effect of stroke on the rate of cognitive decline appeared to ameliorate after the first year (test for linear trend among those with stroke, P = .003). CONCLUSION: Results from this prospective population-based data study show that stroke in the left hemisphere results in a more pronounced decline in cognition than that in the right hemisphere and that cognitive loss because of stroke appears to attenuate over time, perhaps as a result of relearning.

The relationship of cardiovascular risk factors to microalbuminuria in older adults with or without diabetes mellitus or hypertension: the cardiovascular health study. - Barzilay, Joshua I; Peterson, Do; Cushman, Mary; Heckbert, Susan R; Cao, Jie J; Blaum, Caroline; Tracy, Russell P; Klein, Ronald; Herrington, David M (Am J Kidney Dis, 2004)
BACKGROUND: Microalbuminuria is a risk factor for coronary heart disease (CHD). It occurs most commonly in the settings of diabetes and hypertension. The mechanisms by which it increases CHD risk are uncertain. METHODS: We examined the cross-sectional association of microalbuminuria with a broad range of CHD risk factors in 3 groups of adults aged 65 years or older with and without microalbuminuria: those with (1) no diabetes or hypertension (n = 1,098), (2) hypertension only (n = 1,450), and (3) diabetes with or without hypertension (n = 465). RESULTS: Three factors were related to microalbuminuria in all 3 groups: age, elevated systolic blood pressure, and markers of systemic inflammation. In patients with neither diabetes nor hypertension, increasing C-reactive protein levels were associated with microalbuminuria (odds ratio per 1-mg/L increase, 1.46; 95% confidence interval [CI], 1.15 to 1.84). Among those with diabetes, an increase in white blood cell (WBC) count was associated with microalbuminuria (odds ratio per 1,000-cell/mL increase, 2.57; 95% CI, 1.12 to 5.89). Among those with hypertension, an increase in WBC count (odds ratio per 1,000-cell/mL increase, 1.83; 95% CI, 1.04 to 3.23) and fibrinogen level (odds ratio per 10-mg/dL increase, 1.02; 95% CI, 1.00 to 1.05) were significantly associated with microalbuminuria. In all 3 groups, prevalent CHD was related to an elevated WBC count. In none of the 3 groups was brachial artery reactivity to ischemia, an in vivo marker of endothelial function, related to microalbuminuria. CONCLUSION: Microalbuminuria is associated with age, systolic blood pressure, and markers of inflammation. These associations reflect potential mechanisms by which microalbuminuria is related to CHD risk.
Keywords: Age Distribution; Aged; Aged, 80 and over; Albuminuria; Biomarkers; Brachial Artery; Comorbidity; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Hypertension; Inflammation; Logistic Models; Male; Multivariate Analysis; Odds Ratio; Risk Factors; Smoking; Ultrasonography

The relationship of fasting serum radioimmune insulin levels to incident coronary heart disease in an insulin-treated diabetic cohort. - Kronmal, Richard A; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Orchard, Trevor J; Burke, Gregory L (J Clin Endocrinol Metab, 2004)
It is not known whether insulin levels, in the setting of insulin treatment, are an independent risk factor for coronary heart disease (CHD). We studied a cohort of 116 insulin-treated individuals, 65 yr or older, who were followed for 5.6-9 yr. All were free of CHD at baseline. There were 47 incident CHD events. In Cox proportional hazards modeling, with fasting immune-reactive insulin levels as a continuous variable, the hazard ratio for CHD was statistically significant (P < 0.0001). When insulin levels were divided into intervals, those in the third interval [43-150 microU/ml (258-900 pmol/liter)] had an adjusted 30% increased relative risk (95% confidence interval, 0.57, 2.98) compared with those in the first interval [<20 microU/ml (<120 pmol/liter)]. Those in the fourth interval [151-400 microU/ml (906-2400 pmol/liter)] had an adjusted 5.6-fold increased risk (2.3-13.1; P < 0.0001). Approximately 15% of the cohort had such elevated insulin levels. Immune-reactive insulin levels were strongly correlated with specific insulin, proinsulin, and insulin antibody levels. Markedly elevated fasting immune-reactive insulin levels were an independent risk factor for CHD in this study of insulin-treated older adults. These observational findings should be confirmed through larger prospective studies, given their implications for insulin therapy.
Keywords: Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 1; Fasting; Female; Follow-Up Studies; Humans; Hypoglycemic Agents; Incidence; Insulin; Male; Radioimmunoassay; Risk Factors

Respiratory muscle strength and the risk of incident cardiovascular events. - van der Palen, J; Rea, T D; Manolio, T A; Lumley, T; Newman, A B; Tracy, R P; Enright, P L; Psaty, B M (Thorax, 2004)
BACKGROUND: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. METHODS: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI), and stroke. RESULTS: Subjects in the lowest quintile of MIP had a 1.5-fold increased risk of MI (HR 1.48, 95% CI 1.07 to 2.06) and cardiovascular disease (CVD) death (HR 1.54, 95% CI 1.09 to 2.15) after adjustment for non-pulmonary function covariates. There was a potential inverse relationship with stroke (HR 1.36, 95% CI 0.97 to 1.90), but there was little evidence of an association between MIP and CHF (HR 1.22, 95% CI 0.93 to 1.60). The addition of FVC to models attenuated the HR associated with MIP only modestly; similarly, addition of MIP attenuated the HR associated with FVC only modestly. CONCLUSIONS: A reduced MIP is an independent risk factor for MI and CVD death, and a suggestion of an increased risk for stroke. This association with MIP appeared to be mediated through mechanisms other than inflammation.
Keywords: Cardiovascular Diseases; Female; Follow-Up Studies; Forced Expiratory Volume; Humans; Male; Maximal Voluntary Ventilation; Prospective Studies; Respiratory Muscles; Risk Factors; Vital Capacity

Survival associated with two sets of diagnostic criteria for congestive heart failure. - Schellenbaum, Gina D; Rea, Thomas D; Heckbert, Susan R; Smith, Nicholas L; Lumley, Thomas; Roger, Veronique L; Kitzman, Dalane W; Taylor, Herman A; Levy, Daniel; Psaty, Bruce M (Am J Epidemiol, 2004)
Congestive heart failure (CHF) definitions vary across epidemiologic studies. The Framingham Heart Study criteria include CHF signs and symptoms assessed by a physician panel. In the Cardiovascular Health Study, a committee of physicians adjudicated CHF diagnoses, confirmed by signs, symptoms, clinical tests, and/or medical therapy. The authors used data from the Cardiovascular Health Study, a population-based cohort study of 5,888 elderly US adults, to compare CHF incidence and survival patterns following onset of CHF as defined by Framingham and/or Cardiovascular Health Study criteria. They constructed an inception cohort of nonfatal, hospitalized CHF patients. Of 875 participants who had qualifying CHF hospitalizations between 1989 and 2000, 54% experienced a first CHF event that fulfilled both sets of diagnostic criteria (concordant), 31% fulfilled only the Framingham criteria (Framingham only), and 15% fulfilled only the Cardiovascular Health Study criteria (Cardiovascular Health Study only). No significant survival difference was found between the Framingham-only group (hazard ratio = 0.87, 95% confidence interval: 0.71, 1.07) or the Cardiovascular Health Study-only group (hazard ratio = 0.89, 95% confidence interval: 0.68, 1.15) and the concordant group (referent). Compared with Cardiovascular Health Study central adjudication, Framingham criteria for CHF identified a larger group of participants with incident CHF, but all-cause mortality rates were similar across these diagnostic classifications.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Diagnosis, Differential; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Prognosis; Severity of Illness Index; Survival Analysis

Traditional and novel risk factors in older adults: cardiovascular risk assessment late in life. - Mukamal, Kenneth J; Kronmal, Richard A; Tracy, Russell P; Cushman, Mary; Siscovick, David S (Am J Geriatr Cardiol, 2004)
As a population-based, longitudinal study of nearly 6000 older American adults, the Cardiovascular Health Study provides an excellent opportunity to assess the roles of traditional and novel cardiovascular risk factors in the development of coronary heart disease. Cardiovascular Health Study investigators have analyzed both traditional risk factors, such as diabetes, hypertension, and smoking, and new risk factors, such as hemostatic factors, inflammatory markers, exposure to infectious agents, and genetic determinants. These analyses have led to several important conclusions. First, older adults without previous cardiovascular events have a tremendous burden of subclinical vascular disease, which may change how physicians view risk factor modification in this age group. Second, some traditional cardiovascular risk factors lose importance as predictors of cardiovascular disease among older adults. Third, even modest elevations in fasting blood glucose or systolic blood pressure-below the levels used to define diabetes or hypertension-may have prognostic implications. Fourth, novel cardiovascular risk factors may add further information about cardiovascular disease risk in older adults. Promising potential candidates identified in the Cardiovascular Health Study include markers of hemostatic activation, fibrinogen, factor VIII coagulant activity, C-reactive protein, and exposure to herpes simplex virus-1 and possibly chlamydia. Future Cardiovascular Health Study investigations will help to clarify which combination of traditional and newer risk factors provides the best estimate of cardiovascular risk for older adults.
Keywords: Aged; Blood Coagulation Factors; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Female; Genetic Predisposition to Disease; Humans; Hypertension; Infections; Inflammation; Lipids; Longitudinal Studies; Male; Obesity; Predictive Value of Tests; Risk Factors; Smoking; United States

Benefits of fatty fish on dementia risk are stronger for those without APOE epsilon4. - Huang, T L; Zandi, P P; Tucker, K L; Fitzpatrick, A L; Kuller, L H; Fried, L P; Burke, G L; Carlson, M C (Neurology, 2005)
OBJECTIVE: To compare associations of lean fish vs fatty fish (tuna or other fish) intake with dementia, Alzheimer disease (AD), and vascular dementia (VaD) and in relation to APOE epsilon4 status in the Cardiovascular Health Cognition Study (CHCS). METHODS: Fish intake was assessed by food frequency questionnaires. Incident dementia, AD, and VaD were determined through a series of cognitive tests, physician's assessment, and committee consensus. We used Cox proportional hazards regression to calculate hazard ratios of dementia, AD, and VaD with lean fried fish, fatty fish, or total fish intake, which were then stratified by the presence of APOE epsilon4. RESULTS: Although consumption of lean fried fish had no protective effect, consumption of fatty fish more than twice per week was associated with a reduction in risk of dementia by 28% (95% CI: 0.51 to 1.02), and AD by 41% (95% CI: 0.36 to 0.95) in comparison to those who ate fish less than once per month. Stratification by APOE epsilon4 showed this effect to be selective to those without the epsilon4 allele. Adjustment by education and income attenuated the effect. CONCLUSION: In the Cardiovascular Health Cognition Study, consumption of fatty fish was associated with a reduced risk of dementia and Alzheimer disease for those without the APOE epsilon4 allele.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Cohort Studies; Dementia; Dietary Fats, Unsaturated; Fatty Acids, Omega-3; Feeding Behavior; Female; Fish Oils; Fish Products; Food, Formulated; Genetic Predisposition to Disease; Humans; Incidence; Male; Risk Factors; Socioeconomic Factors; Surveys and Questionnaires

beta(2)-Adrenergic receptor polymorphisms and determinants of cardiovascular risk: the Cardiovascular Health Study. - Hindorff, Lucia A; Heckbert, Susan R; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Herrington, David M; Edwards, Karen L; Tracy, Russell P (Am J Hypertens, 2005)
BACKGROUND: Common Arg16Gly and Gln27Glu polymorphisms of the beta(2)-adrenergic receptor (beta(2)AR) have been associated with hypertension and coronary disease. This analysis of older adults in the Cardiovascular Health Study examined whether these polymorphisms were associated with blood pressure (BP), subclinical atherosclerosis, and, among treated hypertensive individuals, differences in coronary disease risk according to antihypertensive drug class. METHODS: Altogether, 5249 participants (4441 white and 808 African American, median follow-up time 10.2 years) were genotyped for both polymorphisms. Ankle-arm index (AAI), carotid intima-media thickness (IMT), and brachial flow-mediated dilation were measured cross-sectionally. All estimates were adjusted for ethnicity. RESULTS: Relative to Gln27 homozygotes, carrying the Glu27 allele was not associated with new-onset hypertension (hazard ratio [HR] = 1.01, 95% confidence interval [CI] = 0.87 to 1.16), BP control (odds ratio [OR] = 0.97, 95% CI = 0.89 to 1.06), AAI (mean difference 0.0042 +/- 0.0052), carotid IMT (mean difference 0.0044 +/- 0.02 mm), or brachial flow-mediated dilation (mean difference in baseline diameter -0.028 +/- 0.036 mm; the most marked of three measures). Among treated hypertensive individuals, coronary disease risk was similar in Glu27 carriers relative to Gln27 homozygotes in subgroups defined by use of beta-blockers (HR = 1.09, 95% CI = 0.64 to 1.87) or other antihypertensive medications (HR = 1.00, 95% CI = 0.78 to 1.28). Results were similar for the Arg16Gly polymorphism. CONCLUSIONS: The association of beta(2)AR genotype with coronary disease previously reported in this older adult population is not likely to be explained by BP levels, subclinical atherosclerosis, or antihypertensive treatment. Other measures of vascular response, gene-gene or gene-environment interactions, or characteristics developing earlier in life may mediate the association between beta(2)AR genotype and coronary disease and merit further research.
Keywords: African Americans; Antihypertensive Agents; Arteriosclerosis; Coronary Artery Disease; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

C-reactive protein and the 10-year incidence of coronary heart disease in older men and women: the cardiovascular health study. - Cushman, Mary; Arnold, Alice M; Psaty, Bruce M; Manolio, Teri A; Kuller, Lewis H; Burke, Gregory L; Polak, Joseph F; Tracy, Russell P (Circulation, 2005)
BACKGROUND: High C-reactive protein (CRP) is associated with increased coronary heart disease risk. Few long-term data in the elderly are available. METHODS AND RESULTS: Baseline CRP was measured in 3971 men and women > or =65 years of age without prior vascular diseases; 26% had elevated concentrations (>3 mg/L). With 10 years of follow-up, 547 participants developed coronary heart disease (CHD; defined as myocardial infarction or coronary death). With elevated CRP, the 10-year cumulative CHD incidences were 33% in men and 17% in women. The age-, ethnicity-, and sex-adjusted relative risk of CHD for CRP >3 mg/L compared with <1 mg/L was 1.82 (95% CI, 1.46 to 2.28). Adjusting for conventional risk factors reduced the relative risk to 1.45 (95% CI, 1.14 to 1.86). The population-attributable risk of CHD for elevated CRP was 11%. Risk relationships did not differ in subgroups defined by baseline risk factors. We assessed whether CRP improved prediction by the Framingham Risk Score. Among men with a 10-year Framingham-predicted risk of 10% to 20%, the observed CHD incidence was 32% for elevated CRP. Among women, CRP discriminated best among those with a 10-year predicted risk >20%; the incidences were 31% and 10% for elevated and normal CRP levels, respectively. CONCLUSIONS: In older men and women, elevated CRP was associated with increased 10-year risk of CHD, regardless of the presence or absence of cardiac risk factors. A single CRP measurement provided information beyond conventional risk assessment, especially in intermediate-Framingham-risk men and high-Framingham-risk women.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Coronary Disease; Female; Humans; Incidence; Inflammation; Male; Myocardial Infarction; Predictive Value of Tests; Risk Factors

Cystatin-C and inflammatory markers in the ambulatory elderly. - Shlipak, Michael G; Katz, Ronit; Cushman, Mary; Sarnak, Mark J; Stehman-Breen, Catherine; Psaty, Bruce M; Siscovick, David; Tracy, Russell P; Newman, Anne; Fried, Linda (Am J Med, 2005)
PURPOSE: Inflammatory factors are elevated in persons with severe renal dysfunction, but their association across all levels of renal function is unclear. We compared cystatin-C, a novel marker of renal function, with creatinine and estimated glomerular filtration rate (eGFR) as predictors of C-reactive protein and fibrinogen levels. METHODS: This study is a cross-sectional analysis to evaluate cystatin-C, creatinine, and eGFR as predictors of the inflammatory markers C-reactive protein and fibrinogen. Participants included 4637 ambulatory elderly patients from the Cardiovascular Health Study. Multivariate linear regression was used to determine the independent associations of each renal function measurement with the inflammatory marker outcomes. RESULTS: After adjustment for confounding factors, cystatin-C was correlated with both C-reactive protein (coefficient = 0.13; 95% confidence interval: 0.10-1.16, P <.0001) and fibrinogen levels (0.15; 0.13-0.18, P <.0001). Associations were larger than those for creatinine and C-reactive protein (0.05; 0.02-0.07, P = .003) or fibrinogen (0.07; 0.04-0.10, P <.0001). Adjusted levels of C-reactive protein increased incrementally across quintiles of cystatin-C, from a median of 2.2 mg/L in quintile 1 to 3.7 mg/L in quintile 5. In contrast, both C-reactive protein and fibrinogen had U-shaped associations with quintiles of creatinine and eGFR, because the inflammatory markers were equivalently elevated in quintiles 1 and 5. CONCLUSIONS: The finding of a significant linear association of cystatin-C and inflammation markers suggests that even small reductions in renal function may be associated with adverse pathophysiologic consequences.
Keywords: Age Factors; Aged; Biomarkers; C-Reactive Protein; Cross-Sectional Studies; Cystatin C; Cystatins; Female; Fibrinogen; Glomerular Filtration Rate; Humans; Kidney Diseases; Male; Predictive Value of Tests; Sensitivity and Specificity

Vascular events, mortality, and preventive therapy following ischemic stroke in the elderly. - Kaplan, R C; Tirschwell, D L; Longstreth, W T; Manolio, T A; Heckbert, S R; Lefkowitz, D; El-Saed, A; Psaty, B M (Neurology, 2005)
BACKGROUND: The authors studied mortality, vascular events, and preventive therapies following ischemic stroke among adults aged > or =65 years. METHODS: The authors identified 546 subjects with first ischemic stroke during 1989 to 2001 among Cardiovascular Health Study participants. Deaths, recurrent strokes, and coronary heart disease (CHD) events were identified over 3.2 years (median) follow-up. RESULTS: During the first year of follow-up, rates were 105.4/1,000 for recurrent stroke and 59.3/1,000 for CHD. After the first year, the stroke rate was 52.0/1,000 and the CHD rate was 46.5/1,000. Cardioembolic strokes had the highest mortality (185.4/1,000) and recurrence rates (86.6/1,000). Lacunar strokes had the lowest mortality (119.3/1,000) and recurrence rates (43.0/1,000). Age and male sex predicted death and CHD, but not recurrence. Outcomes did not differ by race. Following stroke, 47.8% used aspirin and 13.5% used other antiplatelet agents; 52.6% of patients with atrial fibrillation used warfarin; 31.3% of hyperlipidemic subjects, 57.0% of diabetic patients, and 81.5% of hypertensive patients were drug-treated; and 40.0% of hypertensive patients had blood pressure (BP) <140/90 mm Hg. Older subjects were less likely to use lipid-lowering therapy, women were less likely to have BP <140/90 mm Hg, and low-income subjects were less likely to use diabetes medications. CONCLUSIONS: Recurrent strokes were nearly twice as frequent as coronary heart disease (CHD) events during the first year after initial stroke, but stroke and CHD rates were similar after the first year. Preventive drug therapies were underused, which may reflect clinical uncertainty due to the lack of clinical trials among the elderly. Utilization was lower among the oldest patients, women, and low-income individuals.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Anticoagulants; Antihypertensive Agents; Brain Ischemia; Cohort Studies; Comorbidity; Coronary Artery Disease; Drug Utilization; Female; Humans; Hyperlipidemias; Hypertension; Hypolipidemic Agents; Male; Mortality; Prospective Studies; Recurrence; Sex Factors; Stroke; Treatment Outcome

10-year follow-up of subclinical cardiovascular disease and risk of coronary heart disease in the Cardiovascular Health Study. - Kuller, Lewis H; Arnold, Alice M; Psaty, Bruce M; Robbins, John A; O'Leary, Daniel H; Tracy, Russell P; Burke, Gregory L; Manolio, Teri A; Chaves, Paolo H M (Arch Intern Med, 2006)
BACKGROUND: The incidence of coronary heart disease (CHD) is very high among individuals 65 years or older. METHODS: We evaluated the relationships between measurements of subclinical disease at baseline (1989-1990) and at the third-year follow-up examination (1992-1993) and subsequent incidence of cardiovascular disease and total mortality as of June 2001. Approximately 61% of the participants without clinical cardiovascular disease at baseline had subclinical disease based on our previously described criteria from the Cardiovascular Health Study. RESULTS: The incidence of CHD was substantially increased for participants with subclinical disease compared with those who had no subclinical disease: 30.5 per 1000 person-years with and 16.3 per 1000 person-years without for white individuals, and 31.2 per 1000 person-years with and 12.5 per 1000 person-years without for black individuals. The risk persisted over the entire follow-up period. Incidence rates were higher for men than for women with or without subclinical disease, but there was little difference in rates for black individuals and white individuals. CONCLUSIONS: In multivariable models, subclinical disease at baseline remained a significant predictor of CHD in both men and women; the hazard ratios (95% confidence intervals) of their relative risks were 1.64 (1.30-2.06) and 1.49 (1.21-1.84), respectively. The presence of subclinical disease substantially increased the risk of subsequent CHD for participants with hypertension, diabetes mellitus, or elevated C-reactive protein. In summary, subclinical disease is very prevalent among older individuals, is independently associated with risk of CHD even over a 10-year follow-up period, and substantially increases the risk of CHD among participants with hypertension or diabetes mellitus.
Keywords: African Continental Ancestry Group; Aged; Blood Chemical Analysis; Cardiovascular Diseases; Comorbidity; Coronary Disease; Echocardiography; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Multivariate Analysis; Prevalence; Proportional Hazards Models; Regression Analysis; Risk Factors; Sex Distribution; United States

Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima

The association of race with frailty: the cardiovascular health study. - Hirsch, Calvin; Anderson, Melissa L; Newman, Anne; Kop, Willem; Jackson, Sharon; Gottdiener, John; Tracy, Russell; Fried, Linda P (Ann Epidemiol, 2006)
PURPOSE: Frailty, which has been conceptualized as a state of decreased physiologic reserve contributing to functional decline, has a prevalence among older African Americans that is twice that in older whites. This study assesses the independent contribution of race to frailty. METHODS: We evaluated 786 African-American and 4491 white participants of the Cardiovascular Health Study (CHS). Frailty is defined as meeting three or more of five criteria derived from CHS measures: lowest quintile for grip strength, self-reported exhaustion, unintentional weight loss of 10 lbs or greater in 1 year, slowest quintile for gait speed, and lowest quintile for physical activity. Controlling for age, sex, comorbidity, socioeconomic factors, and race, multinomial logistic regression estimated the odds ratio (OR) of prefrail (one or two criteria) to not frail and frail to not frail. RESULTS: Among African Americans, 8.7% of men and 15.0% of women were frail compared with 4.6% and 6.8% of white men and women, respectively. In adjusted models, nonobese African Americans had a fourfold greater odds of frailty compared with whites. The increased OR of frailty associated with African-American race was less pronounced among those who were obese or disabled. CONCLUSION: African-American race is associated independently with frailty.
Keywords: African Americans; Aged; Asthenia; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Frail Elderly; Health Status; Humans; Male; Middle Aged; Motor Activity; Odds Ratio; United States; Weight Loss

Beta2-adrenergic receptor genetic variants and risk of sudden cardiac death. - Sotoodehnia, Nona; Siscovick, David S; Vatta, Matteo; Psaty, Bruce M; Tracy, Russell P; Towbin, Jeffrey A; Lemaitre, Rozenn N; Rea, Thomas D; Durda, J Peter; Chang, Joel M; Lumley, Thomas S; Kuller, Lewis H; et al. (Circulation, 2006)
BACKGROUND: Sympathetic activation influences the risk of ventricular arrhythmias and sudden cardiac death (SCD), mediated in part by the beta2-adrenergic receptor (B2AR). We investigated whether variation in the B2AR gene is associated with SCD risk. METHODS AND RESULTS: In this study, 4441 white and 808 black Cardiovascular Health Study (CHS) participants were followed up prospectively for SCD and genotyped for B2AR Gly16Arg and Gln27Glu polymorphisms. The study was replicated in 155 case and 144 control white subjects in a population-based case-control study of SCD, the Cardiac Arrest Blood Study (CABS). In CHS, Gly16 and Gln27 allele frequencies were 62.4% and 57.1% among white and 50.1% and 81.4% among black participants. Over a median follow-up of 11.1 years, 156 and 39 SCD events occurred in white and black participants, respectively. The Gln27Glu variant was associated with SCD risk (P=0.008 for general model). SCD risk was higher in Gln27 homozygous participants than in Glu27 carriers (ethnicity-adjusted hazard ratio [HR], 1.56; 95% confidence interval [CI], 1.17 to 2.09; P=0.003). The increased risk did not differ significantly between white (HR, 1.62; 95% CI, 1.18 to 2.23) and black (HR, 1.23; 95% CI, 0.61 to 2.48) participants, although the confidence interval was wide in blacks. In the CABS replication study, Gln27 homozygous participants similarly had higher SCD risk than Glu27 carriers (odds ratio, 1.64; 95% CI, 1.02 to 2.63; P=0.040). Gly16Arg was not associated with SCD risk in either study. CONCLUSIONS: Gln27 homozygous individuals have an increased risk of SCD in 2 study populations. Our findings suggest that B2AR plays a role in SCD in humans. Study of genetic variation within the B2AR gene may help identify those at increased SCD risk.
Keywords: African Continental Ancestry Group; Aged; Case-Control Studies; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Glutamine; Haplotypes; Homozygote; Humans; Male; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Reproducibility of Results

Blood pressure level and outcomes in adults aged 65 and older with prior ischemic stroke. - Kaplan, Robert C; Tirschwell, David L; Longstreth, W T; Manolio, Teri A; Heckbert, Susan R; LeValley, Aaron J; Lefkowitz, David; El-Saed, Aiman; Psaty, Bruce M (J Am Geriatr Soc, 2006)
OBJECTIVES: To examine the association between blood pressure (BP) levels and long-term stroke outcomes in elderly stroke survivors. DESIGN: Observational study. SETTING: The Cardiovascular Health Study (CHS) of 5,888 community-dwelling adults. PARTICIPANTS: Two hundred fifty-four adults aged 65 and older (mean age 78.6) who sustained a nonfatal first ischemic stroke. MEASUREMENTS: BP levels assessed at prestroke and poststroke CHS visits were examined as predictors of stroke recurrence, coronary heart disease (CHD), combined vascular events (CVEs), and mortality. RESULTS: Higher poststroke BP level, assessed 261.6 days (mean) after stroke, was associated with higher risk of stroke recurrence over 5.4 years (mean) of follow-up. The multivariate-adjusted hazard ratio for stroke recurrence was 1.42 (95% confidence interval (CI) = 1.03-1.99) per standard deviation (SD) of systolic BP (P = .04) and 1.39 (95% CI = 1.01-1.91) per SD of diastolic BP (P = .04). Mortality was significantly greater in patients with low or high poststroke BP than in those with intermediate BP. Poststroke BP was not associated with risk of CHD or CVE, although further analyses suggested that high systolic BP predicted CHD and CVE in younger but not older subjects. Prestroke BP did not predict poststroke outcomes. CONCLUSION: In this observational study of adults aged 65 and older assessed approximately 8 months after stroke, low BP was associated with favorable risk of recurrent stroke, although high and low poststroke BP levels were associated with greater mortality. Long-term antihypertensive trials in older stroke survivors would increase knowledge about the benefits of lowering BP in this population.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Brain Ischemia; Female; Follow-Up Studies; Humans; Male; Outcome Assessment, Health Care; Prospective Studies; Recurrence; Stroke; Survival Rate

Congestive heart failure incidence and prognosis: case identification using central adjudication versus hospital discharge diagnoses. - Schellenbaum, Gina D; Heckbert, Susan R; Smith, Nicholas L; Rea, Thomas D; Lumley, Thomas; Kitzman, Dalane W; Roger, Veronique L; Taylor, Herman A; Psaty, Bruce M (Ann Epidemiol, 2006)
PURPOSE: We compared hospitalized congestive heart failure (CHF) incidence and prognosis estimates using hospital discharge diagnoses or central adjudication. METHODS: We used the Cardiovascular Health Study (CHS), a population-based cohort study of 5888 elderly adults. A physician committee adjudicated potential CHF events, confirmed by signs, symptoms, clinical tests, and/or medical therapy. A CHF discharge diagnosis included any of these ICD-9 codes in any position: 428, 425, 398.91, 402.01, 402.11, 402.91, and 997.1. We constructed an inception cohort of 1209 hospitalized, nonfatal, incident CHF cases, identified by discharge diagnosis, adjudication, or both. RESULTS: Incidence rates for hospitalized CHF were 24.6 per 1000 person-years using discharge diagnoses and 17.1 per 1000 person-years using central adjudication. Compared to the group identified as having CHF by both methods, the group with only a discharge diagnosis (hazard ratio=0.77, 95% confidence interval=0.65-0.91) and the group with central adjudication only (hazard ratio=0.72, 95% confidence interval=0.55-0.94) had lower mortality rates. CONCLUSIONS: In the elderly, studies using only discharge diagnoses, as compared to central adjudication, may estimate higher rates of incident hospitalized CHF. Mortality following CHF onset may be similar for these methods and higher if both methods are used together.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Heart Failure; Humans; Incidence; Male; Patient Discharge; Prognosis

Cystatin C and prognosis for cardiovascular and kidney outcomes in elderly persons without chronic kidney disease. - Shlipak, Michael G; Katz, Ronit; Sarnak, Mark J; Fried, Linda F; Newman, Anne B; Stehman-Breen, Catherine; Seliger, Stephen L; Kestenbaum, Brian; Psaty, Bruce; Tracy, Russell P; Siscovick, David S (Ann Intern Med, 2006)
BACKGROUND: Cystatin C is an alternative measure of kidney function that may have prognostic importance among elderly persons who do not meet standard criteria for chronic kidney disease (estimated glomerular filtration rate [GFR] > or =60 mL/min per 1.73 m2). OBJECTIVE: To evaluate cystatin C as a prognostic biomarker for death, cardiovascular disease, and incident chronic kidney disease among elderly persons without chronic kidney disease. DESIGN: Cohort study. SETTING: The Cardiovascular Health Study, a population-based cohort recruited from 4 communities in the United States. PARTICIPANTS: 4663 elderly persons. MEASUREMENTS: Measures of kidney function were creatinine-based estimated GFR by using the Modification of Diet in Renal Disease equation and cystatin C concentration. Outcomes were death, cardiovascular death, noncardiovascular death, heart failure, stroke, myocardial infarction, and incident chronic kidney disease during follow-up (median, 9.3 years). RESULTS: At baseline, 78% of participants did not have chronic kidney disease (estimated GFR > or =60 mL/min per 1.73 m2) and mean cystatin C concentration, creatinine concentration, and estimated GFR were 1.0 mg/L, 79.6 micromol/L (0.9 mg/dL), and 83 mL/min per 1.73 m2, respectively. Cystatin C concentrations (per SD, 0.18 mg/L) had strong associations with death (hazard ratio, 1.33 [95% CI, 1.25 to 1.40]), cardiovascular death (hazard ratio, 1.42 [CI, 1.30 to 1.54]), noncardiovascular death (hazard ratio, 1.26 [CI, 1.17 to 1.36]), incident heart failure (hazard ratio, 1.28 [CI, 1.17 to 1.40]), stroke (hazard ratio, 1.22 [CI, 1.08 to 1.38]), and myocardial infarction (hazard ratio, 1.20 [CI, 1.06 to 1.36]) among these participants. Serum creatinine concentrations had much weaker associations with each outcome and only predicted cardiovascular death. Participants without chronic kidney disease who had elevated cystatin C concentrations (> or =1.0 mg/L) had a 4-fold risk for progressing to chronic kidney disease after 4 years of follow-up compared with those with cystatin C concentrations less than 1.0 mg/L. LIMITATIONS: Because this study did not directly measure GFR or albuminuria, the extent to which cystatin C may be influenced by nonrenal factors was not determined and participants with albuminuria might have been misclassified as having no kidney disease. CONCLUSIONS: Among elderly persons without chronic kidney disease, cystatin C is a prognostic biomarker of risk for death, cardiovascular disease, and chronic kidney disease. In this setting, cystatin C seems to identify a "preclinical" state of kidney dysfunction that is not detected with serum creatinine or estimated GFR.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Cystatins; Glomerular Filtration Rate; Humans; Kidney; Longitudinal Studies; Prognosis; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors

Metabolic syndrome and cardiovascular disease in older people: The cardiovascular health study. - McNeill, Ann Marie; Katz, Ronit; Girman, Cynthia J; Rosamond, Wayne D; Wagenknecht, Lynne E; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Jackson, Sharon A (J Am Geriatr Soc, 2006)
OBJECTIVES: To assess the prospective association between metabolic syndrome (MetS) and cardiovascular disease (CVD) in older people and to evaluate the effect of lowering the threshold for impaired fasting glucose (IFG) on the prevalence of IFG and MetS and the risk of CVD. DESIGN: Prospective cohort study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: Three thousand five hundred eighty-five subjects in the Cardiovascular Health Study free of diabetes mellitus and CVD at baseline (mean age 72, 62% female, 14% black). MEASUREMENTS: Baseline measures of MetS components and adjudicated incident CVD events. MetS (2001) was defined first using the original criteria from the Third Adult Treatment Panel Report of the National Cholesterol Education Program (> or =3 of the following: large waist circumference (women >88 cm, men >102 cm), elevated triglycerides (> or =1.70 mmol/L), low high-density lipoprotein cholesterol (men <1.04 mmol/L, women <1.30 mmol/L), elevated fasting glucose (6.1-6.9 mmol/L), and high blood pressure (> or =130/85 mmHg or self-reported use of medications for hypertension). Subjects were also classified according to the revised definition of the MetS (2005) that applies the lower threshold for fasting glucose (5.6-6.9 mmol/L). RESULTS: During follow-up (median 11 years), 818 coronary heart disease (CHD), 401 stroke, and 554 congestive heart failure (CHF) events occurred. Age- and race-adjusted hazard ratios (HRs) for CHD, stroke, and CHF were 1.30 (95% confidence interval (CI) = 1.07-1.57), 0.94 (95% CI = 0.73-1.21), and 1.40 (95% CI = 1.12-1.76) for women and 1.35 (95% CI = 1.10-1.66), 1.51 (95% CI = 1.08-2.12), and 1.47 (95% CI = 1.14-1.90) for men, respectively. Overall, women and men with MetS (2005) were 20% to 30% more likely to experience any CVD event than subjects without MetS (2005). Using the lower cut-point for IFG resulted in a near tripling in IFG prevalence (16% to 46%) and an additional 9% classified with MetS (2005) but HRs similar to those estimated from the original MetS (2001) criteria. High blood pressure was the component most strongly associated with incident CHD. CONCLUSION: Results from this study of an elderly, population-based cohort provide support for earlier investigations in primarily middle-aged populations that link the presence of MetS with the development of CVD and further underscore the importance of recognizing and treating its individual components, particularly high blood pressure.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Fasting; Female; Humans; Incidence; Male; Metabolic Syndrome; Risk Factors; Sex Factors

Plasma phospholipid trans fatty acids, fatal ischemic heart disease, and sudden cardiac death in older adults: the cardiovascular health study. - Lemaitre, Rozenn N; King, Irena B; Mozaffarian, Dariush; Sotoodehnia, Nona; Rea, Thomas D; Kuller, Lewis H; Tracy, Russel P; Siscovick, David S (Circulation, 2006)
BACKGROUND: Intake of trans fatty acids is associated with increased risk of coronary heart disease. Whether different classes of trans fatty acids show similar associations is unclear. We previously reported an association of sudden cardiac death with red cell membrane trans-18:2 but not trans-18:1 fatty acids. To extend these findings, we investigated the associations of plasma phospholipid trans fatty acids with fatal ischemic heart disease (IHD) and sudden cardiac death. METHODS AND RESULTS: We conducted a case-control study nested in the Cardiovascular Health Study. We identified 214 cases of fatal IHD (fatal myocardial infarction and coronary heart disease death) between 1992 and 1998. We randomly selected 214 controls, matched to cases on demographics, prevalent cardiovascular disease, and timing of blood draw. Plasma phospholipid fatty acids were assessed in blood samples collected earlier. Higher levels of plasma phospholipid trans-18:2 fatty acids were associated with higher risk of fatal IHD (odds ratio [OR] for interquintile range 1.68, 95% confidence interval [CI] 1.21 to 2.33) after adjustment for risk factors and trans-18:1 levels. Trans-18:1 levels above the 20th percentile were associated with lower risk (OR 0.34, 95% CI 0.18 to 0.63). In analyses limited to cases of sudden cardiac death (n=95), higher levels of trans-18:2 fatty acids were associated with higher risk (OR 2.34, 95% CI 1.27 to 4.31) and higher trans-18:1 with lower risk (OR 0.18, 95% CI 0.06 to 0.54). CONCLUSIONS: Higher levels of trans-18:2 and lower levels of trans-18:1 fatty acids are associated with higher risks of fatal IHD and sudden cardiac death. If confirmed, these findings suggest that current efforts at decreasing trans fatty acid intake in foods should take into consideration the trans-18:2 content.
Keywords: Aged; Aged, 80 and over; Biomarkers; Case-Control Studies; Coronary Disease; Death, Sudden, Cardiac; Female; Humans; Male; Myocardial Ischemia; Phospholipids; Trans Fatty Acids; United States

Regression dilution methods for meta-analysis: assessing long-term variability in plasma fibrinogen among 27,247 adults in 15 prospective studies. - Wood, Angela M; White, Ian; Thompson, Simon G; Lewington, Sarah; Danesh, John (Int J Epidemiol, 2006)
BACKGROUND: Within-person variability in measured values of a risk factor can bias its association with disease. The extent of this regression dilution bias for plasma fibrinogen was investigated using repeat measurement data collected at varying time intervals on 27 247 adults in 15 prospective studies. METHODS: Regression dilution ratios (RDRs) were estimated from a linear regression of repeat measurements on baseline values in each study and for each time interval, and pooled allowing for within- and between-study heterogeneity. RDRs were estimated both without and with adjustment for confounders, and factors were investigated that might influence the RDRs. RESULTS: The unadjusted overall RDR was 0.51 (95% CI: 0.47, 0.55), which decreased to 0.46 (95% CI: 0.42, 0.49) after adjustment for age, sex and measured values of other established vascular risk factors. The RDR did not vary materially by assay method, age, sex or smoking status, but decreased at higher levels of baseline fibrinogen. CONCLUSION: It is appropriate to use an RDR of 0.5 to correct approximately for regression dilution bias in plasma fibrinogen values; however, this correction factor may produce somewhat conservative hazard ratios in adjusted analyses, at higher fibrinogen concentrations and in follow-up beyond a decade. More generally, the methods described in this report have widespread applicability to quantifying regression dilution bias in repeatability data from multiple prospective studies.
Keywords: Adult; Age Factors; Bias; Cardiovascular Diseases; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Prospective Studies; Regression Analysis; Risk Factors; Sex Factors; Smoking; Time Factors

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke

Thyroid status, cardiovascular risk, and mortality in older adults. - Cappola, Anne R; Fried, Linda P; Arnold, Alice M; Danese, Mark D; Kuller, Lewis H; Burke, Gregory L; Tracy, Russell P; Ladenson, Paul W (JAMA, 2006)
CONTEXT: Previous studies have suggested that subclinical abnormalities in thyroid-stimulating hormone levels are associated with detrimental effects on the cardiovascular system. OBJECTIVE: To determine the relationship between baseline thyroid status and incident atrial fibrillation, incident cardiovascular disease, and mortality in older men and women not taking thyroid medication. DESIGN, SETTING, AND PARTICIPANTS: A total of 3233 US community-dwelling individuals aged 65 years or older with baseline serum thyroid-stimulating hormone levels were enrolled in 1989-1990 in the Cardiovascular Health Study, a large, prospective cohort study. MAIN OUTCOME MEASURES: Incident atrial fibrillation, coronary heart disease, cerebrovascular disease, cardiovascular death, and all-cause death assessed through June 2002. Analyses are reported for 4 groups defined according to thyroid function test results: subclinical hyperthyroidism, euthyroidism, subclinical hypothyroidism, and overt hypothyroidism. RESULTS: Individuals with overt thyrotoxicosis (n = 4) were excluded because of small numbers. Eighty-two percent of participants (n = 2639) had normal thyroid function, 15% (n = 496) had subclinical hypothyroidism, 1.6% (n = 51) had overt hypothyroidism, and 1.5% (n = 47) had subclinical hyperthyroidism. After exclusion of those with prevalent atrial fibrillation, individuals with subclinical hyperthyroidism had a greater incidence of atrial fibrillation compared with those with normal thyroid function (67 events vs 31 events per 1000 person-years; adjusted hazard ratio, 1.98; 95% confidence interval, 1.29-3.03). No differences were seen between the subclinical hyperthyroidism group and euthyroidism group for incident coronary heart disease, cerebrovascular disease, cardiovascular death, or all-cause death. Likewise, there were no differences between the subclinical hypothyroidism or overt hypothyroidism groups and the euthyroidism group for cardiovascular outcomes or mortality. Specifically, individuals with subclinical hypothyroidism had an adjusted hazard ratio of 1.07 (95% confidence interval, 0.90-1.28) for incident coronary heart disease. CONCLUSION: Our data show an association between subclinical hyperthyroidism and development of atrial fibrillation but do not support the hypothesis that unrecognized subclinical hyperthyroidism or subclinical hypothyroidism is associated with other cardiovascular disorders or mortality.
Keywords: Aged; Atrial Fibrillation; Cardiovascular Diseases; Female; Humans; Hyperthyroidism; Hypothyroidism; Male; Proportional Hazards Models; Risk Factors; Thyroid Gland; Thyrotropin

Transthyretin V122I in African Americans with congestive heart failure. - Buxbaum, Joel; Jacobson, Daniel R; Tagoe, Clement; Alexander, Alice; Kitzman, Dalane W; Greenberg, Barry; Thaneemit-Chen, Surai; Lavori, Philip (J Am Coll Cardiol, 2006)
Keywords: African Americans; Gene Frequency; Heart Failure; Heterozygote; Humans; Isoleucine; Mutation; Prealbumin; Valine

ABO blood group, other risk factors and incidence of venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Ohira, T; Cushman, M; Tsai, M Y; Zhang, Y; Heckbert, S R; Zakai, N A; Rosamond, W D; Folsom, A R (J Thromb Haemost, 2007)
BACKGROUND: Numerous case-control studies have reported higher prevalence of non-O blood type among venous thromboembolism (VTE) patients than controls, but potential mechanisms or effect modifiers for the association are not fully established. PATIENTS/METHODS: Using a nested case-control design combining the Atherosclerosis Risk in Communities and the Cardiovascular Health Study cohort, ABO blood type and other VTE risk factors were measured on pre-event blood samples of 492 participants who subsequently developed VTE and 1008 participants who remained free of VTE. RESULTS: A total of 64.4% of cases and 52.5% of controls had non-O blood type. Among controls, mean values of factor VIIIc (FVIIIc) and von Willebrand factor among the non-O blood type group were higher than among the O group. Compared with O blood type, the age-adjusted odds ratio (OR) of VTE for non-O blood type was 1.64 (95% CI, 1.32-2.05) and was similar for the two parent studies and race groups. Further adjustment for sex, race, body mass index, diabetes mellitus and FVIIIc reduced the OR: 1.31 (95% CI, 1.02-1.68). Factor V Leiden (FV Leiden) appeared to modify the non-O blood type association with VTE in a supra-additive fashion, with an age-, sex- and race-adjusted OR of 6.77 (95% CI, 3.65-12.6) for having both risk factors. CONCLUSIONS: Non-O blood type was independently associated with risk of VTE, and added to the risk associated with FV Leiden.
Keywords: ABO Blood-Group System; Aged; Case-Control Studies; Diabetes Complications; Factor V; Factor VIII; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Acceleration of cerebral ventricular expansion in the Cardiovascular Health Study. - Carmichael, Owen T; Kuller, L H; Lopez, O L; Thompson, P M; Dutton, R A; Lu, A; Lee, S E; Lee, J Y; Aizenstein, H J; Meltzer, C C; Liu, Y; Toga, A W; et al. (Neurobiol Aging, 2007)
Interactions between prevalent late-life medical conditions and expansion of the cerebral ventricles are not well understood. Thirty elderly subjects received three magnetic resonance (MR) scans each, in 1997-1999, 2002-2004, and 2003-2005. A linear expansion model of MR-measured lateral ventricle volume was estimated for each subject by fitting a line to a plot of their 1997-1999 and 2002-2004 volumes as a function of time. Acceleration in ventricular expansion was defined as the deviation between the 2003-2005 volumes measured from MR and the 2003-2005 volumes predicted by the linear expansion model. Ventricular acceleration was analyzed in a multivariate model with age, race, history of heart disease, diabetes, and hypertension as fixed effects. Ventricular acceleration was significantly higher in non-whites, diabetics, and those without heart disease (p<0.05). Ventricular acceleration was higher in subjects with a history of hypertension, but the difference was not statistically significant (p=0.08). Acceleration of ventricular expansion in the elderly may be related to demographic and cardiovascular factors.
Keywords: Aged; Analysis of Variance; Cardiovascular Diseases; Cerebral Ventricles; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Reference Values; Retrospective Studies; Sex Factors; Time Factors

Alcohol consumption and lipoprotein subclasses in older adults. - Mukamal, Kenneth J; Mackey, Rachel H; Kuller, Lewis H; Tracy, Russell P; Kronmal, Richard A; Mittleman, Murray A; Siscovick, David S (J Clin Endocrinol Metab, 2007)
CONTEXT: Limited evidence suggests that alcohol intake may be associated with lipoprotein subclass distribution, which could mediate its relationship with coronary heart disease. OBJECTIVES: The objective was to determine the relationship of alcohol intake with lipoprotein particle subclasses. DESIGN, SETTING, AND PARTICIPANTS: The study included a cross-sectional analysis of 1850 participants of the Cardiovascular Health Study aged 65 yr and older and free of clinical cardiovascular disease. MAIN OUTCOME MEASURE: Lipoprotein subclass distribution was measured with nuclear magnetic resonance spectroscopy, according to self-reported alcohol intake. RESULTS: Alcohol intake was associated with total low-density lipoprotein (LDL) particles in a U-shaped manner. Consumers of one or more drinks per week had the highest number of large LDL particles, whereas consumers of 7-13 drinks per week had the lowest number of small LDL particles. Alcohol intake was strongly positively associated with large- and medium-sized high-density lipoprotein (HDL) particles but had an inverse relationship with concentrations of small HDL particles and small- and medium-sized very-low-density lipoprotein particles. Average particle sizes of all three lipoproteins were positively associated with alcohol intake. Associations were generally stronger among women than men but in similar directions. Beverage type did not consistently modify these findings. CONCLUSIONS: Alcohol intake is associated with less total LDL particles, lower levels of small LDL, HDL, and very-low-density lipoprotein particles, and higher levels of large LDL and medium- and large-sized HDL particles in older adults free of prevalent clinical cardiovascular disease.
Keywords: Aged; Alcohol Drinking; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Cholesterol, VLDL; Coronary Disease; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Spectroscopy; Male; Prevalence; Risk Factors

Alcohol consumption, interleukin-6 and apolipoprotein E genotypes, and concentrations of interleukin-6 and serum amyloid P in older adults. - Mukamal, Kenneth J; Jenny, Nancy S; Tracy, Russell P; Siscovick, David S (Am J Clin Nutr, 2007)
BACKGROUND: Whether alcohol intake is associated with concentrations of interleukin-6 (IL-6) and serum amyloid P (SAP) is uncertain. OBJECTIVE: We determined how alcohol intake and apolipoprotein E (apo E) and IL-6 promoter (IL-6 -174G-->C) polymorphisms interact for concentrations of IL-6 and SAP. DESIGN: In the Cardiovascular Health Study, 2454 older adults reported their intake of beer, wine, and liquor and underwent measurements of circulating IL-6 and SAP. RESULTS: Alcohol intake was not associated with IL-6 concentrations among apo E4-negative or IL-6C-positive participants but was positively associated among both apo E4-positive and IL-6C-negative participants (P for trend = 0.02 for both). The corresponding interactions on SAP were not significant for alcohol overall but were similar for liquor intake. CONCLUSIONS: Among older adults free of clinical cardiovascular disease, specific IL-6 promoter and apo E alleles appeared to confer positive associations of alcohol consumption with IL-6 concentrations. Genetic heterogeneity should be considered in understanding the cardiovascular effects of alcohol intake.
Keywords: Aged; Alcohol Drinking; Apolipoprotein E4; Apolipoproteins E; Blood Glucose; C-Reactive Protein; Cohort Studies; Female; Genotype; Humans; Interleukin-6; Male; Promoter Regions, Genetic; Serum Amyloid P-Component

Apolipoprotein e gene and age-related maculopathy in older individuals: the cardiovascular health study. - Tikellis, Gabriella; Sun, Cong; Gorin, Michael B; Klein, Ronald; Klein, Barbara E K; Larsen, Emily K Marino; Siscovick, David S; Hubbard, Larry D; Wong, Tien Y (Arch Ophthalmol, 2007)
OBJECTIVE: To examine the association between the apolipoprotein E (APOE) gene and age-related maculopathy (ARM) in an older population. METHODS: Two thousand one hundred seventy persons 65 years and older sampled from 4 US communities had ARM signs assessed from retinal photographs using a modified Wisconsin Age-Related Maculopathy Grading System. DNA extracted from blood samples was analyzed for common APOE alleles. RESULTS: After controlling for age, sex, cigarette smoking, and other factors, white participants carrying the epsilon2 allele had an increased risk of late ARM (odds ratio, 2.53 [95% confidence interval, 1.08-5.90]) while carriers of the epsilon4 allele had a lower risk of late ARM (odds ratio, 0.69 [95% confidence interval, 0.19-2.50]). There were too few late ARM cases in African American individuals for analysis. CONCLUSION: APOE polymorphism is associated with late ARM in older white persons 65 years and older. Consistent with previous studies, the APOE epsilon2 allele is associated with a significant increased risk of late ARM development, whereas the epsilon4 allele may confer some protection.
Keywords: African Americans; Aged; Aged, 80 and over; Alleles; Apolipoprotein E2; Apolipoprotein E3; Apolipoprotein E4; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genotype; Humans; Macular Degeneration; Male; Odds Ratio; Polymorphism, Genetic; Risk Factors

Apolipoprotein E gene and retinal microvascular signs in older people: the Cardiovascular Health Study. - Sun, Cong; Tikellis, Gabriella; Liew, Gerald; Klein, Ronald; Larsen, Emily K Marino; Wong, Tien Y (Mol Vis, 2007)
PURPOSE: To examine the association between apolipoprotein E (APOE) gene polymorphism and retinal microvascular signs in an older population. METHODS: Retinal photographs were taken of 2,152 participants (1,831 whites, and 321 African-Americans), aged 69-96 years, who were participating in a population-based study of four United States communities. We used standardized protocols to assess photographs for the presence of retinal microvascular signs (retinopathy, arterio-venous nicking, and focal arteriolar narrowing) and a computer-assisted method to measure retinal vessel diameters. We analyzed DNA extracted from blood samples of participants for common allelic variants of the APOE gene. RESULTS: After adjusting for age, gender, systolic blood pressure, smoking, total serum cholesterol, and other risk factors, we found white participants carrying the epsilon2 and epsilon4 alleles were more likely to have arterio-venous nicking than the epsilon3/epsilon3 homozygotes, with odds ratio (OR) of 1.70 and confidence interval (CI) 95% (1.03-2.83) for the epsilon2 carriers and OR 1.74 (95% CI 1.06-2.84) for the epsilon4 carriers. Among white participants without hypertension, the associations remained significant for the epsilon4 carriers (OR 2.32, 95% CI 1.18-4.57). Whites, normotensive carriers of the epsilon2 allele had significantly narrower retinal arteriolar diameters (adjusted mean arteriolar diameter of 163.5 mum, 95% CI 160.1-167.0, p=0.03) compared to the epsilon3/epsilon3 homozygotes (167.8 mum, 95% CI 166.0-169.6). APOE gene polymorphism was not associated with retinopathy, focal narrowing, or retinal venular diameters in white participants. There were insufficient numbers of African-Americans for separate multivariate analysis. CONCLUSIONS: This study provides little evidence that the APOE gene polymorphism plays a significant role in the pathogenesis of retinal microvascular changes in the general population. In the older white population, APOE epsilon2 and epsilon4 allele carriers were more likely to have arterio-venous nicking. Other retinal signs, however, were not related to APOE gene polymorphism.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; European Continental Ancestry Group; Female; Gene Frequency; Genotype; Heterozygote; Homozygote; Humans; Male; Microcirculation; Polymorphism, Genetic; Retinal Diseases; Retinal Vessels

Are microvascular abnormalities in the retina associated with depression symptoms? The Cardiovascular Health Study. - Sun, Cong; Tikellis, Gabriella; Klein, Ronald; Steffens, David C; Larsen, Emily K Marino; Siscovick, David S; Klein, Barbara E K; Wong, Tien Y (Am J Geriatr Psychiatry, 2007)
OBJECTIVE: Depression has been linked with vascular risk factors and stroke. The authors examined the relationship between retinal microvascular abnormalities and depression symptoms in an elderly population. METHODS: The Cardiovascular Health Study is a population-based study conducted in four U.S. communities initiated in 1989-1990. A total of 2,420 persons aged 65 years and older were included in the current analyses. During the 1997-1998 examination, retinal photographs were performed and assessed for retinal microvascular abnormalities (retinopathy, focal arteriolar narrowing, arteriovenous nicking, generalized retinal arteriolar narrowing, and generalized retinal venular dilation) according to standardized methods. Depression symptoms were assessed by a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale annually from 1989 through 1997-1998 and was defined as a CES-D score of >9. RESULTS: Participants with retinal microvascular abnormalities were not more likely to have depression symptoms, with adjusted odds ratio (OR) (95% confidence intervals) of 1.08 (0.71-1.65) for retinopathy, OR 1.09 (0.71-1.68) for focal arteriolar narrowing, OR 0.85 (0.52-1.40) for arteriovenous nicking, OR 0.97 (0.70-1.34) for generalized arteriolar narrowing, and OR 0.79 (0.56-1.12) for generalized venular dilation. Retinal microvascular abnormalities were not related to depression symptoms in multinomial logistic regression comparing the three top quartiles of the depression CES-D scores with the lowest quartile. CONCLUSIONS: Our study did not find an association between retinal microvascular abnormalities and depression symptoms in older people.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Comorbidity; Cross-Sectional Studies; Depression; Female; Fluorescein Angiography; Humans; Male; Microcirculation; Personality Inventory; Retinal Artery Occlusion; Retinal Diseases; Retinal Vein Occlusion; Risk Factors; Statistics as Topic; United States

The association of alpha-fibrinogen Thr312Ala polymorphism and venous thromboembolism in the LITE study. - Rasmussen-Torvik, Laura J; Cushman, Mary; Tsai, Michael Y; Zhang, Yan; Heckbert, Susan R; Rosamond, Wayne D; Folsom, Aaron R (Thromb Res, 2007)
INTRODUCTION: The alpha-fibrinogen Thr312Ala variant has been shown to influence clot structure through increased factor XIII cross-linking and formation of thicker fibrin fibers. However, the effect of this common variant on risk of venous thromboembolism (VTE) is unclear. This paper reports the association between the Thr312Ala variant and VTE in the LITE study. MATERIALS AND METHODS: 506 cases and 1014 controls frequency matched on age, sex, race, and study were drawn from two prospective studies and included in the analysis. Logistic regression was used to examine the association between Thr312Ala and VTE. RESULTS: In a logistic regression model minimally adjusted for the matching variables, the Thr312Ala TA and AA genotypes were associated with a significantly higher risk of VTE than the TT genotype (TA OR and 95% confidence interval 1.27 [1.01-1.60], AA OR 1.49 [1.00-2.22]). Associations were similar in analyses of PE and DVT considered separately and across racial and study subgroups. The association between alpha-fibrinogen Thr312Ala and VTE was modified by both BMI and the FXIII Val34Leu variant; the combination of elevated BMI or FXIII Val34Leu with alpha-fibrinogen Thr312Ala conveyed lower odds of VTE than would be expected by an additive or multiplicative model of individual risk factors. CONCLUSIONS: These results suggest that alpha-fibrinogen Thr312Ala is involved in the pathogenesis of VTE and that its action may be modified by other VTE risk factors.
Keywords: African Continental Ancestry Group; Aged; Case-Control Studies; European Continental Ancestry Group; Female; Fibrinogen; Genotype; Humans; Logistic Models; Male; Middle Aged; Mutation, Missense; Polymorphism, Genetic; Venous Thromboembolism

Associations of plasma fibrinogen levels with established cardiovascular disease risk factors, inflammatory markers, and other characteristics: individual participant meta-analysis of 154,211 adults in 31 prospective studies: the fibrinogen studies collab - Kaptoge, S; White, I R; Thompson, S G; Wood, A M; Lewington, S; Lowe, G D O; Danesh, J (Am J Epidemiol, 2007)
Long-term increases in plasma fibrinogen levels of 1 g/liter are associated with an approximate doubling of risk of major cardiovascular disease outcomes, but causality remains uncertain. To quantify cross-sectional associations of fibrinogen levels with established risk factors and other characteristics, the investigators combined individual data on 154,211 apparently healthy adults from 31 prospective studies conducted between 1967 and 2003, using a linear mixed model that included random effects at the cohort level. Fibrinogen levels increased with age and showed continuous, approximately linear relations with several risk markers and slightly curvilinear associations with log triglycerides, albumin, and tobacco and alcohol consumption. Female sex, Black ethnicity, lower socioeconomic status, and alcohol abstinence were each associated with modestly higher fibrinogen levels. Approximately one third of the variation in fibrinogen levels was explained by cohort, age, and sex. An additional 7% was explained by established risk factors (notably, positive associations with smoking and body mass index and an inverse association with high density lipoprotein cholesterol), and a further 10% was explained by inflammatory markers (notably, a positive association with C-reactive protein). The association with body mass index was twice as strong in women as in men, whereas the association with smoking was much stronger in men. These findings substantially advance understanding of the correlates and possible determinants of fibrinogen levels.
Keywords: Adult; African Americans; Age Factors; Biomarkers; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Female; Fibrinogen; Humans; Linear Models; Male; Prospective Studies; Risk Factors; Sex Factors; Smoking; Social Class; United States

Cerebral ventricular changes associated with transitions between normal cognitive function, mild cognitive impairment, and dementia. - Carmichael, Owen T; Kuller, Lewis H; Lopez, Oscar L; Thompson, Paul M; Dutton, Rebecca A; Lu, Allen; Lee, Sharon E; Lee, Jessica Y; Aizenstein, Howard J; Meltzer, Carolyn C; Liu, Yanxi; Toga, Arthur W; et al. (Alzheimer Dis Assoc Disord, 2007)
Expansion of the cerebral ventricles may occur at an accelerated rate in subjects with dementia, but the time course of expansion during transitions between normal cognitive function, mild cognitive impairment (MCI), and dementia is not well understood. Furthermore, the effects of cardiovascular risk factors on rate of ventricular expansion are unclear. We used a fully automated segmentation technique to measure change rate in lateral ventricle-to-brain ratio (VBR) on 145 longitudinal pairs of magnetic resonance images of subjects in the Cardiovascular Health Study Cognition Study from the Pittsburgh Center. A multivariate model analyzed VBR change rate, accounting for dementia statuses at both imaging times (normal, MCI, or dementia), age, sex, education, race, magnetic resonance-defined infarcts, Center for Epidemiology Studies Depression Scale, baseline ventricular volume, and cardiovascular risk factors. VBR change was faster in subjects who were demented or transitioned from MCI to dementia, compared with subjects normal at both images and subjects who transitioned from normal to MCI or dementia. Patients with diabetes had faster VBR change. Ventricular expansion may accelerate late in the progression from normal cognitive function to dementia, and may be modulated by diabetes.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cerebral Ventricles; Cognition Disorders; Dementia; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Severity of Illness Index; Time Factors

Collaborative meta-analysis of individual participant data from observational studies of Lp-PLA2 and cardiovascular diseases. - Ballantyne, C; Cushman, M; Psaty, B; Furberg, C; Khaw, K T; Sandhu, M; Oldgren, J; Rossi, G P; Maiolino, G; Cesari, M; Lenzini, L; James, S K; et al. (Eur J Cardiovasc Prev Rehabil, 2007)
BACKGROUND: A large number of observational epidemiological studies have reported generally positive associations between circulating mass and activity levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and the risk of cardiovascular diseases. Few studies have been large enough to provide reliable estimates in different circumstances, such as in different subgroups (e.g., by age group, sex, or smoking status) or at different Lp-PLA2 levels. Moreover, most published studies have related disease risk only to baseline values of Lp-PLA2 markers (which can lead to substantial underestimation of any risk relationships because of within-person variability over time) and have used different approaches to adjustment for possible confounding factors. OBJECTIVES: By combination of data from individual participants from all relevant observational studies in a systematic 'meta-analysis', with correction for regression dilution (using available data on serial measurements of Lp-PLA2), the Lp-PLA2 Studies Collaboration will aim to characterize more precisely than has previously been possible the strength and shape of the age and sex-specific associations of plasma Lp-PLA2 with coronary heart disease (and, where data are sufficient, with other vascular diseases, such as ischaemic stroke). It will also help to determine to what extent such associations are independent of possible confounding factors and to explore potential sources of heterogeneity among studies, such as those related to assay methods and study design. It is anticipated that the present collaboration will serve as a framework to investigate related questions on Lp-PLA2 and cardiovascular outcomes. METHODS: A central database is being established containing data on circulating Lp-PLA2 values, sex and other potential confounding factors, age at baseline Lp-PLA2 measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of Lp-PLA2 and potential confounding factors has been sought to allow adjustment for possible confounding and correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available observational studies of Lp-PLA2 will yield information on a total of about 15 000 cardiovascular disease endpoints.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Cardiovascular Diseases; Humans; Phospholipases A2

Depressive symptoms and age-related macular degeneration in older people: the cardiovascular health study. - Sun, Cong; Tikellis, Gabriella; Klein, Ronald; Steffens, David C; Larsen, Emily K Marino; Wong, Tien Y (Ophthalmic Epidemiol, 2007)
PURPOSE: To examine the association between age-related macular degeneration (AMD) and depressive symptoms. METHODS: Population-based, cross-sectional study. A total of 2,194 persons aged 69-97 years were included in the current analyses. During the 1997-1998 examination, retinal photography from one randomly selected eye was graded for presence of early and late AMD using a modified Wisconsin AMD by Grading System. Depressive symptoms were assessed via a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale annually from 1989 through 1997-1998. Depressive symptoms were defined as a CES-D score of >9 (top quartile of CES-D score) at the 1997-1998 examination. RESULTS: There were 338 (15.6%) individuals with early AMD and 29 (1.3%) with late AMD. Among them, 368 (16.8%) persons had depressive symptoms at the 1997-1998 examination. Depressive symptoms were not associated with early AMD (multivariable adjusted odds ratio [OR]: 0.97; 95% confidence intervals [CI]: 0.69-1.36) or late AMD (OR: 1.15; 95% CI: 0.38-3.46). Including persons using anti-depressive medications did not alter these associations (OR: 0.98; 95% CI: 0.74-1.32 for early AMD and OR: 0.97; 95% CI: 0.35-2.67 for late AMD). There was no association in multinomial logistic regression models of increasing quartiles of the CES-D scores with early or late AMD status. CONCLUSIONS: Our study did not find an association between early AMD and depressive symptoms in older people.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depressive Disorder; Female; Health Surveys; Humans; Intelligence Tests; Macular Degeneration; Male; Photography; United States

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Factor VII coagulant activity, factor VII -670A/C and -402G/A polymorphisms, and risk of venous thromboembolism. - Folsom, A R; Cushman, M; Heckbert, S R; Ohira, T; Rasmussen-Torvik, L; Tsai, M Y (J Thromb Haemost, 2007)
BACKGROUND: Most epidemiological studies have found no association between levels of factor (F) VII:C and venous thromboembolism (VTE). Our Longitudinal Investigation of Thromboembolism Etiology (LITE) had, in contrast, reported an independent, increased risk of VTE after 7.8 years of follow-up for those with high baseline levels of FVII:C. OBJECTIVE: To confirm whether FVII:C is associated with VTE after 12.6 years of follow-up and to examine whether two FVII gene polymorphisms (-670A/C and -402G/A) are related to VTE occurrence. METHODS: In 19 091 LITE participants with no prior history of VTE or cancer, we measured FVII:C at baseline and identified 404 new VTEs. We also performed a nested case-control study to relate the polymorphisms to VTE (n = 490 without exclusion for cancer or prior VTE). RESULTS: FVII:C was not independently associated with VTE occurrence after extended follow-up. Multivariable-adjusted rate ratios for VTE were 1.00, 1.00, 0.94, 1.00, and 1.38 (P-trend = 0.48) for the <25th, 25th-49th, 50th-74th, 75th-94th, and >or=95th percentiles of FVII:C, respectively. The -670C and -402A alleles were in high linkage disequilibrium, and both were associated with greater FVII:C levels. However, neither polymorphism was associated with VTE occurrence. CONCLUSION: After extended follow-up, LITE offers little evidence that a greater FVII level is a risk factor for VTE.
Keywords: Alleles; Antigens; Coagulants; Factor VII; Female; Genotype; Humans; Male; Polymorphism, Genetic; Prospective Studies; Risk Factors; Thromboembolism; Venous Thrombosis

IL-6 gene variation is associated with IL-6 and C-reactive protein levels but not cardiovascular outcomes in the Cardiovascular Health Study. - Walston, Jeremy D; Fallin, M Daniele; Cushman, Mary; Lange, Leslie; Psaty, Bruce; Jenny, Nancy; Browner, Warren; Tracy, Russell; Durda, Peter; Reiner, Alex (Hum Genet, 2007)
Interleukin-6 (IL-6) and C-reactive protein (CRP) levels increase with age and likely play a role in adverse health outcomes in older adults. The relationship between IL-6 gene tag single nucleotide polymorphisms (SNPs) and circulating IL-6 and CRP levels, cardiovascular disease (CVD) outcomes, and mortality in Caucasian (CA) and African American (AA) participants of the Cardiovascular Health Study (CHS) was evaluated using ANCOVA and Cox proportional hazards models. The minor allele of the promoter SNP 1510 and intronic SNP 3572 associates with significantly higher serum IL-6 and CRP levels in CA but not AA. The CRP association persisted after CA and AA populations were combined and after accounting for multiple comparisons. These associations did not carry through to cardiovascular disease outcomes. Decreased risk of stroke was identified in CA, with the minor allele of SNP 1111 (HRR 0.71, 95% CI 0.52, 0.95), P = 0.02, and increased risk of CVD and all-cause mortality (HRR 1.31, 95% CI 1.05-1.64) in AAs heterozygote for SNP 2989. While genetic variation in the IL-6 gene was associated with circulating IL-6 and especially with CRP concentrations in this study, there is little evidence for association between common IL-6 gene variation and adverse health outcomes in this population of older adults.
Keywords: African Americans; Aged; Alleles; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Introns; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic

Inflammation biomarkers and near-term death in older men. - Jenny, Nancy Swords; Yanez, N David; Psaty, Bruce M; Kuller, Lewis H; Hirsch, Calvin H; Tracy, Russell P (Am J Epidemiol, 2007)
Associations of C-reactive protein (CRP) and fibrinogen with death may weaken over time. Combining both markers may improve prediction of death in older adults. In 5,828 Cardiovascular Health Study participants (United States, 1989-2000), 383 deaths (183 cardiovascular disease (CVD)) in years 1-3 (early) and 914 deaths (396 CVD) in years 4-8 (late) occurred. For men, when comparing highest to lowest quartiles, hazard ratios for early death were 4.1 (95% confidence interval (CI): 2.7, 6.3) for CRP and 4.1 (95% CI: 2.7, 6.4) for fibrinogen in models adjusted for CVD risk. For early CVD death, hazard ratios were 4.3 (95% CI: 2.2, 8.4) and 3.4 (95% CI: 1.8, 6.3), respectively. When comparing men in the highest quartiles of both biomarkers with those in the lowest, hazard ratios were 9.6 (95% CI: 4.3, 21.1) for early death and 13.5 (95% CI: 3.2, 56.5) for early CVD death. Associations were weaker for late deaths. For women, CRP (hazard ratio = 2.3, 95% CI: 1.4, 3.9), but not fibrinogen (hazard ratio = 1.3, 95% CI: 0.8, 2.2), was associated with early death. Results were similar for CVD death. Neither was associated with late deaths. CRP and fibrinogen were more strongly associated with death in older men than women and more strongly associated with early than late death. Combining both markers may identify older men at greatest risk of near-term death.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Diabetes Complications; Epidemiologic Studies; Female; Fibrinogen; Follow-Up Studies; Humans; Hypercholesterolemia; Hypertension; Inflammation; Male; Middle Aged; Obesity; Population Surveillance; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Sex Distribution; Smoking; Time Factors; United States

Leukocyte telomere length and cardiovascular disease in the cardiovascular health study. - Fitzpatrick, Annette L; Kronmal, Richard A; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Walston, Jeremy; Kimura, Masyuki; Aviv, Abraham (Am J Epidemiol, 2007)
The telomere length of replicating somatic cells is inversely correlated with age and has been reported to be associated cross-sectionally with cardiovascular disease (CVD). Leukocyte telomere length, as expressed by mean terminal restriction fragment (TRF) length, was measured in 419 randomly selected participants from the Cardiovascular Health Study, comprising a community-dwelling cohort recruited in four US communities. The authors investigated associations between TRF length and selected measures of subclinical CVD/risk factors for CVD (data were collected at the 1992/1993 clinic visit) and incident CVD (ascertained through June 2002). In these participants (average age = 74.2 years (standard deviation, 5.2)), mean TRF length was 6.3 kilobase pairs (standard deviation, 0.62). Significant or borderline inverse associations were found between TRF length and diabetes, glucose, insulin, diastolic blood pressure, carotid intima-media thickness, and interleukin-6. Associations with body size and C-reactive protein were modified by gender and age, occurring only in men and in participants aged 73 years or younger. In younger (but not older) participants, each shortened kilobase pair of TRF corresponded with a threefold increased risk of myocardial infarction (hazard ratio = 3.08, 95% confidence interval: 1.22, 7.73) and stroke (hazard ratio = 3.22, 95% confidence interval: 1.29, 8.02). These results support the hypotheses that telomere attrition may be related to diseases of aging through mechanisms involving oxidative stress, inflammation, and progression to CVD.
Keywords: Aged; Cardiovascular Diseases; DNA; Female; Humans; Inflammation; Leukocytes; Male; Myocardial Infarction; Oxidative Stress; Pilot Projects; Polymorphism, Restriction Fragment Length; Risk; Risk Assessment; Risk Factors; Telomere

Potential interactions between complementary/alternative products and conventional medicines in a Medicare population. - Elmer, Gary W; Lafferty, William E; Tyree, Patrick T; Lind, Bonnie K (Ann Pharmacother, 2007)
BACKGROUND: Despite the high prevalence of complementary and alternative medicine (CAM) product use among the elderly, little is known about the extent of concurrent CAM-conventional medicine use and the potential for adverse reactions. OBJECTIVE: To determine the prevalence of CAM product use concurrent with conventional medications, prescription and nonprescription, in a Medicare population and assess the risk for adverse interactions. METHODS: Retrospective analysis was performed on Cardiovascular Health Study interview data from 1994, 1995, 1997, and 1999. The prevalence of concurrent combinations of CAM products and conventional drugs was tabulated. The adverse interaction risks were categorized as unknown, theoretical, and significant. RESULTS: Of 5052 participants, the median age was 75, 60.2% were female, 16.6% were African American, and 83.4% were white. The percent using CAM products during the 4 time periods was 6.3%, 6.7%, 12.8%, and 15.1%. The percent using both CAM products and conventional drugs was 6.0%, 6.2%, 11.7%, and 14.4%. Of these, 294 (5.8%) individuals took combinations considered to have a significant risk for an adverse interaction. Combinations with risk were observed on 393 separate interviews. Most (379) involved a risk of bleeding due to use of ginkgo, garlic, or ginseng together with aspirin, warfarin, ticlopidine, or pentoxifylline. An additional 786 observations of combinations were considered to have some, albeit theoretical or uncertain, risk for an adverse interaction. CONCLUSIONS: Concurrent use of CAM products and conventional medicines in a Medicare population was found to be common. Research to define the risks of combining ginkgo and garlic supplements with aspirin should be of high priority.
Keywords: Aged; Complementary Therapies; Drug Interactions; Drug-Related Side Effects and Adverse Reactions; Female; Hemorrhage; Herb-Drug Interactions; Humans; Male; Medicare; Pharmaceutical Preparations; Phytotherapy; Plant Extracts; Plant Preparations; Retrospective Studies; Risk Factors; Washington

Serum amyloid P and cardiovascular disease in older men and women: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: Serum amyloid P (SAP), a pentraxin like C-reactive protein (CRP), functions in innate immunity. However, associations of SAP with cardiovascular disease (CVD) are unknown. METHODS AND RESULTS: We examined these associations in the Cardiovascular Health Study using a case-cohort design. Nonexclusive case groups were incident angina (n=523), myocardial infarction (MI; n=308), stroke (n=323), and CVD death (n=288). 786 participants had no events. SAP was correlated with CRP, CVD risk factors (obesity, blood pressure, lipids), common and internal carotid wall thickness, and ankle-brachial index (all P<0.02). In Cox regression models adjusted for age, sex, and ethnicity, a standard deviation increase in SAP (9.8 mg/L) was associated with angina (hazard ratio; 95% confidence interval 1.3; 1.2 to 1.5) and MI (1.3; 1.1 to 1.5), but not stroke (1.1; 0.9 to 1.3) or CVD death (1.1; 0.9 to 1.3). Adding CRP to the models had no significant effect on associations. Adjusting for CVD risk factors slightly attenuated SAP associations with CVD events; however, associations with angina and MI remained significant. CONCLUSIONS: Although both are pentraxins, SAP and CRP may represent different facets of inflammation. The association of SAP with CVD in these older adults further supports the role of innate immunity in atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aging; Angina, Unstable; Atherosclerosis; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Hypertension; Immunity, Innate; Male; Myocardial Infarction; Obesity; Prevalence; Proportional Hazards Models; Risk Factors; Serum Amyloid P-Component

USF1 gene variants, cardiovascular risk, and mortality in European Americans: analysis of two US cohort studies. - Reiner, Alexander P; Carlson, Christopher S; Jenny, Nancy S; Durda, J Peter; Siscovick, David S; Nickerson, Deborah A; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: A common haplotype of the upstream transcription factor 1 gene (USF1) has been associated with decreased susceptibility to familial combined hyperlipidemia (FCHL) and, paradoxically, with increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS AND RESULTS: We assessed associations between USF1 tagSNPs, CVD risk factors, and aging-related phenotypes using data from 2 large population-based cohorts, Coronary Artery Risk Development in Young Adults (CARDIA) and the Cardiovascular Health Study (CHS), comprising younger and older adults, respectively. In CARDIA, each additional copy of the FCHL low-risk allele was associated with 2.4 mg/dL lower levels of LDL cholesterol (P=0.01) and decreased risk of subclinical atherosclerosis as assessed by coronary artery calcium (odds ratio 0.79; 95%CI 0.63 to 0.98). Whereas there was little association between USF1 genotype and metabolic or CVD traits in older adults from CHS, the USF1 low-risk dyslipidemia allele was associated with higher plasma C-reactive protein and interleukin (IL)-6 levels and with increased risk of mortality, particularly attributable to noncardiovascular causes. CONCLUSIONS: There appears to be a complex and possibly age-dependent relationship between USF1 genotype, atherosclerosis phenotypes, and CVD risk. USF1 may influence mortality through pathways distinct from atherosclerosis. Alternatively, linkage disequilibrium with neighboring polymorphisms in other genes such as F11R may be responsible for the observed USF1 genotype-phenotype associations in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Blood Glucose; C-Reactive Protein; Calcium; Cardiovascular Diseases; Carotid Artery, Common; Cohort Studies; Coronary Artery Disease; Coronary Vessels; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Hyperlipidemia, Familial Combined; Insulin; Interleukin-6; Linkage Disequilibrium; Lipids; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Upstream Stimulatory Factors

Ventricular volume and dementia progression in the Cardiovascular Health Study. - Carmichael, Owen T; Kuller, Lewis H; Lopez, Oscar L; Thompson, Paul M; Dutton, Rebecca A; Lu, Allen; Lee, Sharon E; Lee, Jessica Y; Aizenstein, Howard J; Meltzer, Carolyn Cidis; Liu, Yanxi; Toga, Arthur W; et al. (Neurobiol Aging, 2007)
Elevated cerebral ventricular volume may be associated with dementia risk and progression. A fully-automated technique that agreed highly with radiological readings was used to estimate lateral ventricle volume on MR scans done at baseline in 1997-99 of 377 subjects in the Cardiovascular Health Study (CHS) from the Pittsburgh Center. 327 subjects were normal or diagnosed with mild cognitive impairment (MCI) at baseline and were evaluated 4 years later. Baseline ventricular volume was analyzed in multivariate models with age, gender, education level, presence and incidence of cerebral infarcts, and dementia category (normal, MCI, or dementia) at baseline and follow-up as fixed effects. Ventricular volume at baseline was significantly higher among subjects normal at baseline and demented 4 years later. Age, gender, education level, and dementia progression were significant factors affecting ventricular volume. Ventricular volume was higher in dementia compared to MCI, higher in MCI compared to controls, and higher in Possible-Alzheimer's-disease (AD) dementia compared to Probable-AD. Larger ventricles in healthy subjects may indicate susceptibility to, or progression of, dementia-related pathology.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Cross-Sectional Studies; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Lateral Ventricles; Linear Models; Magnetic Resonance Imaging; Male; Predictive Value of Tests; Prospective Studies; Retrospective Studies; Time Factors

Association of gene variants with incident myocardial infarction in the Cardiovascular Health Study. - Shiffman, Dov; O'Meara, Ellen S; Bare, Lance A; Rowland, Charles M; Louie, Judy Z; Arellano, Andre R; Lumley, Thomas; Rice, Kenneth; Iakoubova, Olga; Luke, May M; Young, Bradford A; Malloy, Mary J; et al. (Arterioscler Thromb Vasc Biol, 2008)
OBJECTIVE: We asked whether single nucleotide polymorphisms (SNPs) that had been nominally associated with cardiovascular disease in antecedent studies were also associated with cardiovascular disease in a population-based prospective study of 4522 individuals aged 65 or older. METHODS AND RESULTS: Based on antecedent studies, we prespecified a risk allele and an inheritance model for each of 74 SNPs. We then tested the association of these SNPs with myocardial infarction (MI) in the Cardiovascular Health Study (CHS). The prespecified risk alleles of 8 SNPs were nominally associated (1-sided P<0.05) with increased risk of MI in White CHS participants. The false discovery rate for these 8 was 0.43, suggesting that about 4 of these 8 are likely to be true positives. The 4 of these 8 SNPs that had the strongest evidence for association with cardiovascular disease before testing in CHS (association in 3 antecedent studies) were in KIF6 (CHS HR=1.29; 90%CI 1.1 to 1.52), VAMP8 (HR=1.2; 90%CI 1.02 to 1.41), TAS2R50 (HR=1.13; 90%CI 1 to 1.27), and LPA (HR=1.62; 90%CI 1.09 to 2.42). CONCLUSIONS: Although most of the SNPs investigated were not associated with MI in CHS, evidence from this investigation combined with previous studies suggests that 4 of these SNPs are likely associated with MI.
Keywords: African Americans; Aged; Aged, 80 and over; Coronary Disease; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Biomarkers of Inflammation and MRI-Defined Small Vessel Disease of the Brain: The Cardiovascular Health Study. - Fornage, Myriam; Chiang, Y Aron; O'Meara, Ellen S; Psaty, Bruce M; Reiner, Alexander P; Siscovick, David S; Tracy, Russell P; Longstreth, W T (Stroke, 2008)
BACKGROUND AND PURPOSE: To clarify the role of inflammation in the pathogenesis of small vessel disease of the brain, we investigated the association between common variation in the C-reactive protein (CRP) and interleukin (IL)-6 genes, plasma CRP and IL6 levels, and presence of MRI-defined white matter lesions (WML) and brain infarcts (BI) in elderly participants of the Cardiovascular Health Study. METHODS: Tag single nucleotide polymorphisms (SNPs) in the CRP and IL6 genes were selected from the SeattleSNPs database. In cross-sectional analyses, logistic regression models adjusting for known cardiovascular disease risk factors were constructed to assess the associations of plasma CRP and IL6 levels and common CRP and IL6 gene haplotypes with presence of WML or BI in Blacks (n=532) and Whites (n=2905). RESULTS: Plasma IL6 and CRP levels were associated with presence of WML and BI in both races. In Whites, common haplotypes of the IL6 gene were significantly associated with WML and BI. The common haplotype tagged by the -174G/C promoter polymorphism was associated with an increased risk of WML (OR=1.14; 95% CI: [1.02; 1.28]). The common haplotype tagged by the -572G/C promoter polymorphism was associated with an increased risk of BI (OR=1.57; 95% CI: [1.15; 2.14]). Significant associations were lacking for WML or BI with IL6 gene variation in Blacks, or with CRP gene variation in either race. CONCLUSIONS: This study provides evidence of a genetic basis underlying the relationship between plasma biomarkers of inflammation and small vessel disease of the brain. Further studies to elucidate the specific role of IL6 in disease pathogenesis are warranted.
Keywords: African Continental Ancestry Group; Aged; Biomarkers; Brain Infarction; C-Reactive Protein; Cohort Studies; European Continental Ancestry Group; Female; Haplotypes; Humans; Inflammation; Interleukin-6; Magnetic Resonance Imaging; Male; Polymorphism, Single Nucleotide

Common variants in the CRP gene in relation to longevity and cause-specific mortality in older adults: the Cardiovascular Health Study. - Hindorff, Lucia A; Rice, Kenneth M; Lange, Leslie A; Diehr, Paula; Halder, Indrani; Walston, Jeremy; Kwok, Pui; Ziv, Elad; Nievergelt, Caroline; Cummings, Steven R; Newman, Anne B; Tracy, Russell P; et al. (Atherosclerosis, 2008)
Common polymorphisms in the CRP gene are associated with plasma CRP levels in population-based studies, but associations with age-related events are uncertain. A previous study of CRP haplotypes in older adults was broadened to include longevity and cause-specific mortality (all-cause, noncardiovascular (non-CV), and cardiovascular (CV)). Common haplotypes were inferred from four tagSNPs in 4512 whites and five tagSNPs in 812 blacks from the Cardiovascular Health Study, a longitudinal cohort of adults over age 65. Exploratory analyses addressed early versus late mortality. CRP haplotypes were not associated with all-cause mortality or longevity overall in either population, but associations with all-cause mortality differed during early and late periods. In blacks, the haplotype tagged by 3872A (rs1205) was associated with increased risk of non-CV mortality, relative to other haplotypes (adjusted hazard ratio for each additional copy: 1.42, 95% CI: 1.07, 1.87). Relative to other haplotypes, this haplotype was associated with decreased risk of early but not decreased risk of late CV mortality in blacks; among whites, a haplotype tagged by 2667C (rs1800947) gave similar but nonsignificant findings. If confirmed, CRP genetic variants may be weakly associated with CV and non-CV mortality in older adults, particularly in self-identified blacks.
Keywords: African Americans; Aged; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Linear Models; Longevity; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Cystatin C and aging success. - Sarnak, Mark J; Katz, Ronit; Fried, Linda F; Siscovick, David; Kestenbaum, Brian; Seliger, Stephen; Rifkin, Dena; Tracy, Russell; Newman, Anne B; Shlipak, Michael G (Arch Intern Med, 2008)
BACKGROUND: To our knowledge, the effect of kidney function on successful aging has not been examined. METHODS: We evaluated the relationship between cystatin C and aging success during a 6-year follow-up in the Cardiovascular Health Study, a community-based cohort of older adults (aged >or= 65 years). Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and having intact physical and cognitive functioning. In adjusted analysis, an accelerated failure time model was used to evaluate the percentage reduction in successful years by level of cystatin C. A separate Cox proportional hazards model evaluated whether cystatin C was related to incident physical and cognitive disability. RESULTS: A total of 2140 participants had cystatin C measured and were free of the previously mentioned conditions at baseline. Their mean age was 74 years. The mean cystatin C level, creatinine level, and estimated glomerular filtration rate were 1.06 mg/L, 0.93 mg/dL, and 78 mL/min/1.73 m(2), respectively (to convert cystatin C to nanomoles per liter, multiply by 75; and to convert creatinine to micromoles per liter, multiply by 88.4). A total of 873 participants reached a first event in follow-up, 138 because of cognitive disability, 238 because of physical disability, 34 because of chronic obstructive pulmonary disease, 146 because of cancer, and 317 because of cardiovascular disease. The adjusted percentage reduction in successful life years in the highest vs the lowest quartile of cystatin C was 27% (95% confidence interval, 11%-39%). The highest vs lowest quartile of cystatin C also was independently associated with incident cognitive or physical disability (hazard ratio, 1.39; 95% confidence interval, 1.00-1.98). CONCLUSION: A higher cystatin C level, even within a range of relatively normal kidney function, was associated with unsuccessful aging.
Keywords: Aged; Aging; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney; Male

Diabetes mellitus and gait dysfunction: possible explanatory factors. - Brach, Jennifer S; Talkowski, Jaime B; Strotmeyer, Elsa S; Newman, Anne B (Phys Ther, 2008)
BACKGROUND AND OBJECTIVE: Gait characteristics differ in individuals with diabetes compared with those without diabetes. Limited information regarding potential explanatory factors for this association exists. This study examined the association between diabetes and gait characteristics in older adults and explored potential explanatory factors. DESIGN: A cross-sectional, observational study design was used. METHODS: At the 1998-1999 clinic visit, 558 ambulatory older adults (mean age=79 years) from the Pittsburgh site of the Cardiovascular Health Study had an assessment of their gait characteristics, diabetes, health status, cognition, mood, lower-extremity circulation and sensation, vision, lower-extremity strength (force-producing capacity), physical activity, and body mass index (BMI). A series of linear regression models were developed to examine the association between diabetes and gait characteristics and to examine potential explanatory factors for the associations. RESULTS: Diabetes was related to gait speed (beta=-.06 m/s); however, the association was partially explained by health status variables, cognition, mood, lower-extremity circulation and sensation, visual impairment, lower-extremity strength, physical activity, and BMI. Health status and lower-extremity strength each explained the greatest proportion of the association (beta reduced 66% by each). Diabetes was related to step width (beta=.02 m), and the association could not be explained by the examined factors. CONCLUSIONS: Diabetes was associated with gait alterations in older adults. Slowed gait speed appears to be secondary to the peripheral effect of the disease on other body systems. The effect of diabetes on step width was not explained in the analyses and may be related to peripheral motor nerve function or central influences of the disease, which could not be assessed in this study.
Keywords: Aged; Body Mass Index; Cognition; Cross-Sectional Studies; Diabetes Mellitus; Female; Gait; Geriatric Assessment; Health Status; Humans; Linear Models; Longitudinal Studies; Male; Multicenter Studies as Topic; Muscle Strength

Higher levels of inflammation factors and greater insulin resistance are independently associated with higher heart rate and lower heart rate variability in normoglycemic older individuals: the Cardiovascular Health Study. - Stein, Phyllis K; Barzilay, Joshua I; Chaves, Paulo H M; Traber, Jennifer; Domitrovich, Peter P; Heckbert, Susan R; Gottdiener, John S (J Am Geriatr Soc, 2008)
OBJECTIVES: To explore the relationship between (1) insulin resistance and inflammation factors with (2) higher heart rate (HR) and lower heart rate variability (HRV) in normoglycemic older adults. DESIGN: Cross-sectional population-based study. PARTICIPANTS: Five hundred forty-five adults aged 65 and older with normoglycemia (fasting glucose <100 mg/dL) who participated in the Cardiovascular Health Study. MEASUREMENTS: Serum levels of three inflammation proteins (C-reactive protein (CRP), interleukin 6 (IL-6), and fibrinogen); insulin resistance, quantified according to the homeostasis assessment model (HOMA-IR); HR; and four representative measures of HRV (the standard deviation of normal beat to beat intervals (SDNN), the root mean square of successive differences (rMSSD), very low frequency power (VLF), and the low- to high-frequency power ratio (LF/HF)) derived from 24-hour Holter recordings. RESULTS: High CRP and IL-6 levels were associated with higher HR and lower SDNN and VLF after adjustment for multiple covariates, including HOMA-IR and clinical cardiovascular disease. High IL-6 was also associated with lower LF/HF. Significant univariate inverse relationships between HOMA-IR and HR and HRV were also found, but the strengths of these relationships were attenuated after adjustment for inflammation factors. CONCLUSION: Increased levels of inflammation markers and HOMA-IR are associated with higher HR and lower HRV. These findings suggest that inflammation may contribute to the pathogenesis of cardiovascular autonomic decline in older adults.
Keywords: Aged; C-Reactive Protein; Cardiovascular Diseases; Cross-Sectional Studies; Electrocardiography, Ambulatory; Female; Fibrinogen; Heart Rate; Humans; Inflammation Mediators; Insulin Resistance; Interleukin-6; Male; Risk Factors

Impact of health perception, balance perception, fall history, balance performance, and gait speed on walking activity in older adults. - Talkowski, Jaime B; Brach, Jennifer S; Studenski, Stephanie; Newman, Anne B (Phys Ther, 2008)
BACKGROUND AND PURPOSE: Disagreement currently exists regarding the contributions of various factors to physical activity in older adults. The purpose of this cross-sectional study was to investigate the simultaneous impact of psychological (health perception and balance perception) and physiological (gait speed, fall history, and balance performance) factors on walking activity in older adults. SUBJECTS AND METHODS: This cross-sectional secondary data analysis included 2,269 community-dwelling older adults from the Cardiovascular Health Study. A series of simultaneous linear regression models were constructed to examine the association of walking activity with health and balance perception, gait speed, fall history, and balance performance after controlling for potential confounding factors. RESULTS: Health and balance perception and gait speed were significantly related to walking activity after controlling for potential confounding factors. Participants who perceived both their health and their balance to be good walked more blocks per week than those who reported a discordant perception, who walked more than those who perceived both their health and their balance to be poor. Participants who walked at a normal speed walked more blocks per week than those who walked at a slow speed. DISCUSSION AND CONCLUSION: The measure of physical activity used in this study included only walking, not other low- to moderate-intensity activities that are common in older adults. Health and balance perception and gait speed were associated with walking activity more so than fall history or balance performance after controlling for potential confounding factors.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Attitude to Health; Cross-Sectional Studies; Female; Gait; Geriatric Assessment; Health Status; Humans; Male; Motor Activity; Multivariate Analysis; Perception; Postural Balance; Risk Assessment; Walking

Inflammatory markers and longitudinal lung function decline in the elderly. - Jiang, Rui; Burke, Gregory L; Enright, Paul L; Newman, Anne B; Margolis, Helene G; Cushman, Mary; Tracy, Russell P; Wang, Yuanjia; Kronmal, Richard A; Barr, R Graham (Am J Epidemiol, 2008)
Longitudinal studies examining associations of the inflammatory markers fibrinogen and C-reactive protein (CRP) with lung function decline are sparse. The authors examined whether elevated fibrinogen and CRP levels were associated with greater longitudinal lung function decline in the elderly. The Cardiovascular Health Study measured fibrinogen and CRP in 5,790 Whites and African Americans from four US communities aged 65 years or older in 1989-1990 or 1992-1993. Spirometry was performed in 1989-1990 and 4, 7, and 16 years later. Fibrinogen and CRP were inversely associated with lung function at baseline after adjustment for multiple potential confounders. In mixed models, the rate of decline in forced expiratory volume in 1 second (FEV(1))/forced vital capacity (FVC) ratio with increasing age was faster among those with higher baseline fibrinogen (-0.032%/year per standard deviation higher fibrinogen (95% confidence interval: -0.057, -0.0074)) but not among those with higher CRP (-0.0037%/year per standard deviation higher CRP (95% confidence interval: -0.013, 0.0056)). Longitudinal analyses for FEV(1) and FVC yielded results in the direction opposite of that hypothesized, possibly because of the high mortality rate and strong inverse association of FEV(1) and FVC but not FEV(1)/FVC with mortality. An alternative approach to missing data yielded similar results. In conclusion, higher levels of fibrinogen, but not CRP, independently predicted greater FEV(1)/FVC decline in the elderly.
Keywords: Aged; C-Reactive Protein; Cross-Sectional Studies; Female; Fibrinogen; Forced Expiratory Volume; Geriatric Assessment; Humans; Logistic Models; Longitudinal Studies; Lung Volume Measurements; Male; Multicenter Studies as Topic; Pulmonary Disease, Chronic Obstructive; Spirometry

Plasma amyloid levels and the risk of AD in normal subjects in the Cardiovascular Health Study. - Lopez, O L; Kuller, L H; Mehta, P D; Becker, J T; Gach, H M; Sweet, R A; Chang, Y F; Tracy, R; DeKosky, S T (Neurology, 2008)
OBJECTIVES: To examine the association between incident Alzheimer disease (AD), and plasma A beta 1-40 and A beta 1-42 levels in normal and mild cognitive impairment (MCI) subjects in a subgroup of participants of the Cardiovascular Health Study Cognition Study. METHODS: We determined the plasma A beta 1-40 and A beta 1-42 levels of 274 nondemented subjects (232 normals and 42 with MCI) in 1998-1999 and repeated the measurements in 2002-2003. The mean age of the subjects at baseline was 79.3 +/- 3.6 years. We examined the association between A beta levels and incident AD over the ensuing 4.5 years, controlling for age, cystatin C level (marker of glomerular function), apolipoprotein E-4 allele, Modified-Mini-Mental State Examination scores, and MRI-identified infarcts. RESULTS: In an unadjusted prospective model in normal subjects, both A beta 1-40 and A beta 1-42 levels in 1998-1999 were associated with incident AD (n = 55) in 2002-2003 (longitudinal analysis). In the fully adjusted multivariate model, neither A beta 1-42 nor A beta 1-40 nor their ratio was associated with incident AD. However, adjustment had a very small effect on point estimates for A beta 1-42, from an odds ratio (OR) of 1.61 (p = 0.007) in the unadjusted model to an OR of 1.46 (p = 0.08) in the fully adjusted model. In 2002-2003 (cross-sectional analysis), only the unadjusted models showed that both peptides were associated with AD. CONCLUSIONS: Plasma A beta levels are affected by age and by systemic and CNS vascular risk factors. After controlling for these conditions, A beta-40 and A beta 1-42 are weak predictors of conversion to Alzheimer disease (AD) in normal subjects and are only weakly associated with AD in cross-sectional analysis. Consequently, plasma levels of A beta do not seem to be useful biomarkers for AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Brain; Cerebrovascular Disorders; Comorbidity; Cross-Sectional Studies; Cystatin C; Cystatins; Female; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Models, Statistical; Neuropsychological Tests; Peptide Fragments; Predictive Value of Tests; Prospective Studies; Reference Values; Risk Factors

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

Association between elevated fibrosis markers and heart failure in the elderly: the cardiovascular health study. - Barasch, Eddy; Gottdiener, John S; Aurigemma, Gerard; Kitzman, Dalane W; Han, Jing; Kop, Willem J; Tracy, Russell P (Circ Heart Fail, 2009)
BACKGROUND: Myocardial fibrosis reflects excess collagen deposition in the extracellular left ventricular matrix, which has been associated with heart failure (HF). No studies have addressed the relation between fibrosis biomarkers and HF in the elderly. METHODS AND RESULTS: Serum fibrosis markers were measured in 880 participants of the Cardiovascular Health Study (mean age 77+/-6 years, 48% women). Participants with systolic HF (n=131, left ventricular ejection fraction <55%) and those with diastolic HF (n=179, left ventricular ejection fraction > or =55%) were compared with controls (280 with cardiovascular risk factors, and 279 healthy individuals) using a nested case-control design. Fibrosis markers included carboxyl-terminal peptide of procollagen type I, carboxyl-terminal telopeptide of collagen type I, and amino-terminal peptide of procollagen type III. Echocardiography was used to document systolic and diastolic function parameters. Analysis of variance and logistic regression analysis (per tertile odds ratios [OR]), adjusted by age, gender, race, hypertension, atrial fibrillation, coronary heart disease, baseline serum glucose, serum cystatin C, serum creatinine, C-reactive protein, any angiotensin-converting enzyme inhibitor, spironolactone or any diuretic, NT-proBNP, and total bone mineral density were performed. Systolic HF was associated with significantly elevated carboxyl-terminal telopeptide of collagen type I (OR=2.6; 95% CI=1.2 to 5.7) and amino-terminal peptide of procollagen type III (OR=3.3; 95% CI=1.6 to 5.8), when adjusting for covariates. Associations of diastolic HF were significant for carboxyl-terminal telopeptide of collagen type I (OR=3.9; 95% CI=1.9 to 8.3) and amino-terminal peptide of procollagen type III (OR=2.7; 95% CI=1.4 to 5.4). HF was not associated with elevated carboxyl-terminal peptide of procollagen type I (P>0.10), and fibrosis markers did not significantly differ between HF with diastolic versus those with systolic dysfunction (P>0.10) whereas NT-proBNP mean values were higher in systolic heart failure than in diastolic heart failure (P<0.0001). CONCLUSIONS: Fibrosis markers are significantly elevated in elderly individuals with diastolic or systolic HF. These associations remained significant when adjusting for covariates relevant to the aging process.
Keywords: Aged; Aged, 80 and over; Female; Fibrosis; Heart Failure; Humans; Male; Myocardium; Ultrasonography

Association of genetic variation in serum amyloid-A with cardiovascular disease and interactions with IL6, IL1RN, IL1beta and TNF genes in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Enquobahrie, Daniel A; Jarvik, Gail P; Davis, Scott; Tracy, Russell P; Reiner, Alexander P (J Atheroscler Thromb, 2009)
AIM: Since inflammation is an important contributor to atherosclerosis, gene variants mediating inflammation are of interest. We investigated gene variants in acute phase serum amyloid-A (SAA), a sensitive indicator of inflammatory activity, and their associations with cardiovascular disease (CVD) and HDL cholesterol. Interaction of the SAA genes with genetic variants of their regulators, IL-1, IL-6 and TNF-alpha in influencing CVD was also explored. METHODS: SNPs characterizing common variation in the SAA1 and SAA2 genes were genotyped in European-(EA) and African-American (AA) participants (n=3969 and n=719) of the Cardiovascular Health Study. Using linear and Cox proportional hazards regression, we assessed associations of SNPs with baseline carotid artery intima-media thickness (cIMT) and risk of incident myocardial infarction, ischemic stroke, total CVD events or mortality during 14 years of follow-up. RESULTS: No associations between SAA SNPs and outcomes were observed in EA, with the exception of total CVD events; each rs4638289 minor allele was associated with an increased risk in obese individuals, HR=1.2 (95%CI: 0.981.4; p=0.086) and decreased risk among non-obese, HR=0.9 (95%CI: 0.80.99; p=0.026). In AA, we observed modest associations between SAA SNPs and cIMT, potentially modified by HDL. SAA SNPs were also associated with lower HDL in EA and AA. Suggestive gene-gene interaction findings for cIMT in AA and CVD mortality in EA were not significant in subsequent model selection tests. CONCLUSION: Associations of SAA SNPs with cIMT, HDL and total CVD events were identified, unadjusted for multiple testing. These findings should be regarded as hypothesis-generating until confirmed by other studies.
Keywords: Aged; Cardiovascular Diseases; Cholesterol, HDL; Cytokines; Female; Gene Regulatory Networks; Humans; Inflammation Mediators; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Interleukin-6; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Serum Amyloid A Protein; Tumor Necrosis Factor-alpha; Tunica Intima

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Associations of pentraxin 3 with cardiovascular disease and all-cause death: the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2009)
OBJECTIVE: We examined associations of pentraxin 3 (PTX3), a vascular inflammation marker, with incident cardiovascular disease (CVD) and all-cause death. METHODS AND RESULTS: 1583 Cardiovascular Health Study participants free of prevalent CVD were included. Nonexclusive case groups were angina (n=476), myocardial infarction (MI; n=237), stroke (n=310), CVD death (n=282), and all-cause death (n=772). 535 participants had no events. PTX3 levels were higher in those with subclinical CVD (1.90+/-1.89 ng/mL) than those without (1.71+/-1.88 ng/mL; P=0.001). Using Cox regression adjusted for age, sex, and ethnicity, a standard deviation increase in PTX3 (1.89 ng/mL) was associated with CVD death (hazard ratio 1.11; 95% confidence interval 1.02 to 1.21) and all-cause death (1.08; 1.02 to 1.15). PTX3 was not associated with angina (1.09; 0.98 to 1.20), MI (0.96; 0.81 to 1.12), or stroke (1.06; 0.95 to 1.18). Adding C-reactive protein (CRP) or CVD risk factors to the models had no significant effects on associations. CONCLUSIONS: In these older adults, PTX3 was associated with CVD and all-cause death independent of CRP and CVD risk factors. PTX3 likely reflects different aspects of inflammation than CRP and may provide insight into vascular health in aging and chronic diseases of aging that lead to death.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Health Surveys; Humans; Inflammation Mediators; Linear Models; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Serum Amyloid P-Component; Time Factors; United States; Up-Regulation

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Gene variants associated with ischemic stroke: the cardiovascular health study. - Luke, May M; O'Meara, Ellen S; Rowland, Charles M; Shiffman, Dov; Bare, Lance A; Arellano, Andre R; Longstreth, W T; Lumley, Thomas; Rice, Kenneth; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (Stroke, 2009)
BACKGROUND AND PURPOSE: The purpose of this study was to determine whether 74 single nucleotide polymorphisms (SNPs), which had been associated with coronary heart disease, are associated with incident ischemic stroke. METHODS: Based on antecedent studies of coronary heart disease, we prespecified the risk allele for each of the 74 SNPs. We used Cox proportional hazards models that adjusted for traditional risk factors to estimate the associations of these SNPs with incident ischemic stroke during 14 years of follow-up in a population-based study of older adults: the Cardiovascular Health Study (CHS). RESULTS: In white CHS participants, the prespecified risk alleles of 7 of the 74 SNPs (in HPS1, ITGAE, ABCG2, MYH15, FSTL4, CALM1, and BAT2) were nominally associated with increased risk of stroke (one-sided P<0.05, false discovery rate=0.42). In black participants, the prespecified risk alleles of 5 SNPs (in KRT4, LY6G5B, EDG1, DMXL2, and ABCG2) were nominally associated with stroke (one-sided P<0.05, false discovery rate=0.55). The Val12Met SNP in ABCG2 was associated with stroke in both white (hazard ratio, 1.46; 90% CI, 1.05 to 2.03) and black (hazard ratio, 3.59; 90% CI, 1.11 to 11.6) participants of CHS. Kaplan-Meier estimates of the 10-year cumulative incidence of stroke were greater among Val allele homozygotes than among Met allele carriers in both white (10% versus 6%) and black (12% versus 3%) participants of CHS. CONCLUSIONS: The Val12Met SNP in ABCG2 (encoding a transporter of sterols and xenobiotics) was associated with incident ischemic stroke in white and black participants of CHS.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Coronary Disease; Ethnic Groups; European Continental Ancestry Group; Female; Gene Frequency; Genetic Variation; Humans; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke; United States

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genetic variations in nitric oxide synthase 1 adaptor protein are associated with sudden cardiac death in US white community-based populations. - Kao, W H Linda; Arking, Dan E; Post, Wendy; Rea, Thomas D; Sotoodehnia, Nona; Prineas, Ronald J; Bishe, Bryan; Doan, Betty Q; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Coresh, Josef; et al. (Circulation, 2009)
BACKGROUND: The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wide association study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association with SCD in a combined population of 19 295 black and white adults from the Atherosclerosis Risk In Communities Study and the Cardiovascular Health Study. METHODS AND RESULTS: We examined 19 tagging single-nucleotide polymorphisms in the genomic blocks containing rs10494366 and rs4657139 in NOS1AP. SCD was defined as a sudden pulseless condition of cardiac origin in a previously stable individual. General linear models and Cox proportional hazards regression models were used. Multiple single-nucleotide polymorphisms in NOS1AP, including rs10494366, rs4657139, and rs16847548, were significantly associated with adjusted QT interval in whites (P<0.0001). In whites, after adjustment for age, sex, and study, the relative hazard of SCD associated with each C allele at rs16847548 was 1.31 (95% confidence interval 1.10 to 1.56, P=0.002), assuming an additive model. In addition, a downstream neighboring single-nucleotide polymorphism, rs12567209, which was not correlated with rs16847548 or QT interval, was also independently associated with SCD in whites (relative hazard 0.57, 95% confidence interval 0.39 to 0.83, P=0.003). Adjustment for QT interval and coronary heart disease risk factors attenuated but did not eliminate the association between rs16847548 and SCD, and such adjustment had no effect on the association between rs12567209 and SCD. No significant associations between tagging single-nucleotide polymorphisms in NOS1AP and either QT interval or SCD were observed in blacks. CONCLUSIONS: In a combined analysis of 2 population-based prospective cohort studies, sequence variations in NOS1AP were associated with baseline QT interval and the risk of SCD in white US adults.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Death, Sudden, Cardiac; Electrocardiography; European Continental Ancestry Group; Genotype; Humans; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Genome-wide association study of blood pressure and hypertension. - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nat Genet, 2009)
Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium (n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10(-7). The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium (n = 34,433), four CHARGE loci attained genome-wide significance (P < 5 × 10(-8)) for SBP (ATP2B1, CYP17A1, PLEKHA7, SH2B3), six for DBP (ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4) and one for hypertension (ATP2B1). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.
Keywords: Blood Pressure; Cell Line; Chromosome Mapping; Chromosomes, Human; Diastole; Gene Expression Regulation; Genetic Association Studies; Genome-Wide Association Study; Humans; Hypertension; Liver; Lymphocytes; Meta-Analysis as Topic; Odds Ratio; Phenotype; Prevalence; Risk Assessment; Systole

Inflammation and stress-related candidate genes, plasma interleukin-6 levels, and longevity in older adults. - Walston, Jeremy D; Matteini, Amy M; Nievergelt, Caroline; Lange, Leslie A; Fallin, Dani M; Barzilai, Nir; Ziv, Elad; Pawlikowska, Ludmila; Kwok, Pui; Cummings, Steve R; Kooperberg, Charles; LaCroix, Andrea; et al. (Exp Gerontol, 2009)
Interleukin-6 (IL-6) is an inflammatory cytokine that influences the development of inflammatory and aging-related disorders and ultimately longevity. In order to study the influence of variants in genes that regulate inflammatory response on IL-6 levels and longevity, we screened a panel of 477 tag SNPs across 87 candidate genes in >5000 older participants from the population-based Cardiovascular Health Study (CHS). Baseline plasma IL-6 concentration was first confirmed as a strong predictor of all-cause mortality. Functional alleles of the IL6R and PARP1 genes were significantly associated with 15%-20% higher baseline IL-6 concentration per copy among CHS European-American (EA) participants (all p<10(-4)). In a case/control analysis nested within this EA cohort, the minor allele of PARP1 rs1805415 was nominally associated with decreased longevity (p=0.001), but there was no evidence of association between IL6R genotype and longevity. The PARP1 rs1805415--longevity association was subsequently replicated in one of two independent case/control studies. In a pooled analysis of all three studies, the "risk" of longevity associated with the minor allele of PARP1 rs1805415 was 0.79 (95%CI 0.62-1.02; p=0.07). These findings warrant further study of the potential role of PARP1 genotype in inflammatory and aging-related phenotypes.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Case-Control Studies; Female; Genetic Variation; Genotype; Humans; Inflammation; Interleukin-6; Longevity; Male; Phenotype; Poly (ADP-Ribose) Polymerase-1; Poly(ADP-ribose) Polymerases; Risk Factors

Lack of association of soluble endothelial protein C receptor and PROCR 6936A/G polymorphism with the risk of venous thromboembolism in a prospective study. - Yamagishi, Kazumasa; Cushman, Mary; Heckbert, Susan R; Tsai, Michael Y; Folsom, Aaron R (Br J Haematol, 2009)
Prior case-control studies reported that levels of the soluble form of the endothelial protein C receptor (sEPCR) were strongly controlled by the PROCR 6963A/G polymorphism and higher levels were a risk factor for venous thromboembolism (VTE). We sought to prospectively examine the association of sEPCR and the 6963A/G polymorphism with the incidence of VTE. The Longitudinal Investigation of Thromboembolism Etiology (LITE) pooled data from the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) Study on men and women aged > or =45 years. A nested case-control study of 458 incident VTE and 1038 controls was performed. sEPCR levels were distributed trimodally according to 6963A/G polymorphism. Adjusting for age, sex and race, there was no overall association between sEPCR level and VTE: odds ratio (OR) [95% confidence interval] for highest versus lowest quartile = 1.17[0.86-1.59]. However, higher sEPCR was associated with VTE in non-whites (OR = 1.84[1.05-3.22]) and women (OR = 1.51[1.01-2.26]). The 6963A/G polymorphism was not associated with VTE risk (OR = 0.93[0.70-1.25]). In conclusion, sEPCR levels and the PROCR 6963A/G polymorphism were not associated overall with increased risk of VTE.
Keywords: Antigens, CD; Case-Control Studies; Endothelial Protein C Receptor; Female; Genotype; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Polymorphism, Genetic; Prospective Studies; Receptors, Cell Surface; Risk; Venous Thromboembolism

Lipoprotein(a) concentration and the risk of coronary heart disease, stroke, and nonvascular mortality. - Erqou, Sebhat; Kaptoge, Stephen; Perry, Philip L; Di Angelantonio, Emanuele; Thompson, Alexander; White, Ian R; Marcovina, Santica M; Collins, Rory; Thompson, Simon G; Danesh, John (JAMA, 2009)
CONTEXT: Circulating concentration of lipoprotein(a) (Lp[a]), a large glycoprotein attached to a low-density lipoprotein-like particle, may be associated with risk of coronary heart disease (CHD) and stroke. OBJECTIVE: To assess the relationship of Lp(a) concentration with risk of major vascular and nonvascular outcomes. STUDY SELECTION: Long-term prospective studies that recorded Lp(a) concentration and subsequent major vascular morbidity and/or cause-specific mortality published between January 1970 and March 2009 were identified through electronic searches of MEDLINE and other databases, manual searches of reference lists, and discussion with collaborators. DATA EXTRACTION: Individual records were provided for each of 126,634 participants in 36 prospective studies. During 1.3 million person-years of follow-up, 22,076 first-ever fatal or nonfatal vascular disease outcomes or nonvascular deaths were recorded, including 9336 CHD outcomes, 1903 ischemic strokes, 338 hemorrhagic strokes, 751 unclassified strokes, 1091 other vascular deaths, 8114 nonvascular deaths, and 242 deaths of unknown cause. Within-study regression analyses were adjusted for within-person variation and combined using meta-analysis. Analyses excluded participants with known preexisting CHD or stroke at baseline. DATA SYNTHESIS: Lipoprotein(a) concentration was weakly correlated with several conventional vascular risk factors and it was highly consistent within individuals over several years. Associations of Lp(a) with CHD risk were broadly continuous in shape. In the 24 cohort studies, the rates of CHD in the top and bottom thirds of baseline Lp(a) distributions, respectively, were 5.6 (95% confidence interval [CI], 5.4-5.9) per 1000 person-years and 4.4 (95% CI, 4.2-4.6) per 1000 person-years. The risk ratio for CHD, adjusted for age and sex only, was 1.16 (95% CI, 1.11-1.22) per 3.5-fold higher usual Lp(a) concentration (ie, per 1 SD), and it was 1.13 (95% CI, 1.09-1.18) following further adjustment for lipids and other conventional risk factors. The corresponding adjusted risk ratios were 1.10 (95% CI, 1.02-1.18) for ischemic stroke, 1.01 (95% CI, 0.98-1.05) for the aggregate of nonvascular mortality, 1.00 (95% CI, 0.97-1.04) for cancer deaths, and 1.00 (95% CI, 0.95-1.06) for nonvascular deaths other than cancer. CONCLUSION: Under a wide range of circumstances, there are continuous, independent, and modest associations of Lp(a) concentration with risk of CHD and stroke that appear exclusive to vascular outcomes.
Keywords: Cause of Death; Coronary Disease; Humans; Lipoprotein(a); Risk Factors; Stroke

Lipoprotein-associated phospholipase A(2) and risk of congestive heart failure in older adults: the Cardiovascular Health Study. - Suzuki, Takeki; Solomon, Cam; Jenny, Nancy Swords; Tracy, Russell; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt; Cushman, Mary (Circ Heart Fail, 2009)
BACKGROUND: Inflammation may be a causative factor in congestive heart failure (CHF). Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is an inflammation marker associated with vascular risk. One previous study showed an association of Lp-PLA(2) activity with CHF risk, but there were only 94 CHF cases and Lp-PLA(2) antigen, which is available clinically in the United States, was not measured. METHODS AND RESULTS: We measured baseline Lp-PLA(2) antigen and activity in 3991 men and women without baseline CHF or cardiovascular disease who were participating in the Cardiovascular Health Study, a prospective observational study of adults 65 years or older. Cox proportional hazards models adjusted for age, sex, clinic site, race, low-density and high-density lipoprotein cholesterol, body mass index, systolic and diastolic blood pressure, hypertension, smoking status, pack-years, and diabetes were used to calculate hazard ratios and 95% CIs for incident CHF. Further models adjusted for coronary disease events during follow-up and C-reactive protein. Eight hundred twenty-nine participants developed CHF during 12.1 years. Adjusted hazard ratios for CHF with Lp-PLA(2) in the fourth compared with the first quartile were 1.44 (95% CI, 1.16 to 1.79) for Lp-PLA(2) antigen and 1.06 (95% CI, 0.84 to 1.32) for activity. Adjustment for incident coronary disease attenuated the hazard ratio for Lp-PLA(2) antigen to 1.26 (95% CI, 1.02 to 1.57), adjustment for C-reactive protein had minimal impact. CONCLUSIONS: Lp-PLA(2) antigen was associated with risk of future CHF in older people, independent of CHF and coronary risk factors, and partly mediated by coronary disease events. Further clinical and basic research is needed to better understand the role of Lp-PLA(2) in CHF.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Biomarkers; C-Reactive Protein; Female; Fibrinogen; Heart Failure; Humans; Incidence; Inflammation Mediators; Interleukin-6; Kaplan-Meier Estimate; Male; Population Surveillance; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Prevalence of hearing loss in Black and White elders: results of the Cardiovascular Health Study. - Pratt, Sheila R; Kuller, Lewis; Talbott, Evelyn O; McHugh-Pemu, Kathleen; Buhari, Alhaji M; Xu, Xiaohui (J Speech Lang Hear Res, 2009)
PURPOSE: The goal of this study was to determine the impact of age, gender, and race on the prevalence and severity of hearing loss in elder adults, aged 72-96 years, after accounting for income, education, smoking, and clinical and subclinical cardiovascular disease. Methods Air-conduction thresholds for standard and extended high-frequency pure-tones were obtained from a cohort of 548 (out of 717) elderly adults (ages 72-96 years) who were recruited during the Year 11 clinical visit (1999-2000) of the Cardiovascular Health Study (CHS) at the Pittsburgh, Pennsylvania site. Participant smoking, income, education, and cardiovascular disease histories were obtained from the CHS database and were included as factors. RESULTS: Hearing loss was more common and more severe for the participants in their 80s than for those in their 70s-the men more than the women and the White participants more than the Black participants. The inclusion of education, income, smoking, and cardiovascular disease (clinical and subclinical) histories as factors did not substantively impact the overall results. CONCLUSION: Although the data reported in this article were cross-sectional and a cohort phenomenon might have been operational, they suggested that hearing loss is more substantive in the 8th than the 7th decade of life and that race and gender influence this decline in audition. Given the high prevalence in the aging population and the differences across groups, there is a clear need to understand the nature and causes of hearing loss across various groups in order to improve prevention and develop appropriate interventions.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; Auditory Threshold; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Hearing Loss; Hearing Tests; Humans; Male; Occupations; Prevalence; Sex Characteristics; Smoking; Socioeconomic Factors; United States

Spousal suffering and partner's depression and cardiovascular disease: the Cardiovascular Health Study. - Schulz, Richard; Beach, Scott R; Hebert, Randy S; Martire, Lynn M; Monin, Joan K; Tompkins, Connie A; Albert, Steven M (Am J Geriatr Psychiatry, 2009)
OBJECTIVES: To assess the effects of suffering in a spouse on prevalent and incident psychiatric (depression) and physical morbidity (cardiovascular disease [CVD]) in their partner, controlling for known risk factors for depression and CVD. DESIGN: Descriptive longitudinal study. PARTICIPANTS: A total of 1,330 older married couples enrolled in the Cardiovascular Health Study, a large epidemiologic study of the elderly. MEASUREMENTS: Predictor variables were physical, psychological, and existential/spiritual indicators of suffering. Primary outcomes were prevalent and incident depression and CVD. RESULTS: Controlling for known risk factors for depression, the authors found a dose-response relationship between suffering in a spouse and concurrent depression in their partner as well as a relationship between suffering and the partner's future risk for depression. With respect to CVD, and controlling for subclinical CVD at baseline, husbands whose wives reported high levels of suffering also had higher rates of prevalent CVD, but there were no significant associations between wives suffering and husbands incident CVD. There were no associations between husbands' suffering and wives' prevalent or incident CVD. CONCLUSION: Exposure to spousal suffering is an independent and unique source of distress in married couples that contributes to psychiatric and physical morbidity. More attention should be paid to the interpersonal effects of suffering in married couples and to its role in contributing to morbidity.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Caregivers; Depression; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Socioeconomic Factors; Spouses; Stress, Psychological; Surveys and Questionnaires

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Usefulness of myeloperoxidase levels in healthy elderly subjects to predict risk of developing heart failure. - Tang, W H Wilson; Katz, Ronit; Brennan, Marie-Luise; Aviles, Ronnier J; Tracy, Russell P; Psaty, Bruce M; Hazen, Stanley L (Am J Cardiol, 2009)
Increased systemic myeloperoxidase (MPO) has been associated with both the presence and severity of heart failure (HF). This study tested the hypothesis that increased systemic MPO in apparently healthy elderly subjects may predict increased risk of developing HF. Systemic MPO was measured in all available samples from the 1992 to 1993 visit of the Cardiovascular Health Study (CHS). After excluding subjects without available blood samples or with a history of prevalent HF, myocardial infarction (MI), or stroke, 3,733 subjects were included. A total of 569 subjects developed incident HF during 7.2 +/- 2.3 years of follow-up. Patients in the highest MPO quartile (>432 pmol/L) showed higher risk of developing incident HF after adjusting for MI, age, gender, systolic blood pressure, smoking, low-density lipoprotein cholesterol, diabetes mellitus, and any subclinical cardiovascular disease (hazard ratio 1.34, 95% confidence interval 1.06 to 1.72, p = 0.013). However, the relation was more apparent after censoring subjects with incident MI before incident HF, even when adjusted for C-reactive protein and cystatin C (hazard ratio 1.46, 95% confidence interval 1.08 to 1.97, p = 0.02). Interestingly, stratified analyses showed that the relation between increased MPO and HF risk was stronger in subjects without traditional cardiovascular risk factors (<or=75 years old, systolic blood pressure <or=136 mm Hg, no subclinical cardiovascular disease, and no diabetes mellitus). In conclusion, an independent association between increased MPO and the development of HF in apparently healthy elderly subjects was observed, particularly beyond MI and traditional cardiac risk factors.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Disease Progression; Female; Geriatric Assessment; Heart Failure; Humans; Longitudinal Studies; Male; Peroxidase; Predictive Value of Tests; Probability; Prognosis; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index; Sex Factors

Admixture mapping of ankle-arm index: identification of a candidate locus associated with peripheral arterial disease. - Scherer, M L; Nalls, M A; Pawlikowska, L; Ziv, E; Mitchell, G; Huntsman, S; Hu, D; Sutton-Tyrrell, K; Lakatta, E G; Hsueh, W-C; Newman, A B; Tandon, A; et al. (J Med Genet, 2010)
BACKGROUND: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality, and has a higher prevalence in African Americans than Caucasians. Ankle-arm index (AAI) is the ratio of systolic blood pressure in the leg to that in the arm, and, when low, is a marker of PAD. METHODS: The authors used an admixture mapping approach to search for genetic loci associated with low AAI. Using data from 1040 African American participants in the observational, population based Health, Aging, and Body Composition Study who were genotyped at 1322 single nucleotide polymorphisms (SNPs) that are informative for African versus European ancestry and span the entire genome, we estimated genetic ancestry in each chromosomal region and then tested the association between AAI and genetic ancestry at each locus. RESULTS: The authors found a region of chromosome 11 that reaches its peak between 80 and 82 Mb associated with low AAI (p<0.001 for rs12289502 and rs9665943, both within this region). 753 African American participants in the observational, population based Cardiovascular Health Study were genotyped at rs9665943 to test the reproducibility of this association, and this association was also statistically significant (odds ratio (OR) for homozygous African genotype 1.59, 95% confidence interval (CI) 1.12 to 2.27). Another candidate SNP (rs1042602) in the same genomic region was tested in both populations, and was also found to be significantly associated with low AAI in both populations (OR for homozygous African genotype 1.89, 95% CI 1.29 to 2.76). CONCLUSION: This study identifies a novel region of chromosome 11 representing an area with a potential candidate gene associated with PAD in African Americans.
Keywords: African Americans; Aged; Ankle Brachial Index; Chromosome Mapping; Chromosomes, Human, Pair 11; Female; Genetic Loci; Genotype; Humans; Male; Odds Ratio; Peripheral Vascular Diseases; Polymorphism, Single Nucleotide

Age and cystatin C in healthy adults: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Katz, Ronit; Fried, Linda F; Newman, Anne B; Canada, Robert B; Harris, Tamara; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Nephrol Dial Transplant, 2010)
BACKGROUND: Kidney function declines with age, but a substantial portion of this decline has been attributed to the higher prevalence of risk factors for kidney disease at older ages. The effect of age on kidney function has not been well described in a healthy population across a wide age spectrum. METHODS: The authors pooled individual-level cross-sectional data from 18 253 persons aged 28-100 years in four studies: the Cardiovascular Health Study; the Health, Aging and Body Composition Study; the Multi-Ethnic Study of Atherosclerosis and the Prevention of Renal and Vascular End-Stage Disease cohort. Kidney function was measured by cystatin C. Clinical risk factors for kidney disease included diabetes, hypertension, obesity, smoking, coronary heart disease, cerebrovascular disease, peripheral arterial disease and heart failure. RESULTS: Across the age range, there was a strong, non-linear association of age with cystatin C concentration. This association was substantial, even among participants free of clinical risk factors for kidney disease; mean cystatin C levels were 46% higher in participants 80 and older compared with those <40 years (1.06 versus 0.72 mg/L, P < 0.001). Participants with one or more risk factors had higher cystatin C concentrations for a given age, and the age association was slightly stronger (P < 0.001 for age and risk factor interaction). CONCLUSIONS: There is a strong, non-linear association of age with kidney function, even in healthy individuals. An important area for research will be to investigate the mechanisms that lead to deterioration of kidney function in apparently healthy persons.
Keywords: Adult; Aged; Aged, 80 and over; Cross-Sectional Studies; Cystatin C; Humans; Kidney; Middle Aged; Reference Values

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Autonomic nervous system dysfunction and inflammation contribute to the increased cardiovascular mortality risk associated with depression. - Kop, Willem J; Stein, Phyllis K; Tracy, Russell P; Barzilay, Joshua I; Schulz, Richard; Gottdiener, John S (Psychosom Med, 2010)
OBJECTIVE: To investigate prospectively whether autonomic nervous system (ANS) dysfunction and inflammation play a role in the increased cardiovascular disease (CVD)-related mortality risk associated with depression. METHODS: Participants in the Cardiovascular Health Study (n = 907; mean age, 71.3 ± 4.6 years; 59.1% women) were evaluated for ANS indices derived from heart rate variability (HRV) analysis (frequency and time domain HRV, and nonlinear indices, including detrended fluctuation analysis (DFA(1)) and heart rate turbulence). Inflammation markers included C-reactive protein, interleukin-6, fibrinogen, and white blood cell count). Depressive symptoms were assessed, using the 10-item Centers for Epidemiological Studies Depression scale. Cox proportional hazards models were used to investigate the mortality risk associated with depression, ANS, and inflammation markers, adjusting for demographic and clinical covariates. RESULTS: Depression was associated with ANS dysfunction (DFA(1), p = .018), and increased inflammation markers (white blood cell count, p = .012, fibrinogen p = .043) adjusting for covariates. CVD-related mortality occurred in 121 participants during a median follow-up of 13.3 years. Depression was associated with an increased CVD mortality risk (hazard ratio, 1.88; 95% confidence interval, 1.23-2.86). Multivariable analyses showed that depression was an independent predictor of CVD mortality (hazard ratio, 1.72; 95% confidence interval, 1.05-2.83) when adjusting for independent HRV and inflammation predictors (DFA(1), heart rate turbulence, interleukin-6), attenuating the depression-CVD mortality association by 12.7% (p < .001). CONCLUSION: Autonomic dysfunction and inflammation contribute to the increased cardiovascular mortality risk associated with depression, but a large portion of the predictive value of depression remains unexplained by these neuroimmunological measures.
Keywords: Aged; Autonomic Nervous System Diseases; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Comorbidity; Depressive Disorder; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Inflammation; Interleukin-6; Leukocyte Count; Male; Risk Factors

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Brain structure and obesity. - Raji, Cyrus A; Ho, April J; Parikshak, Neelroop N; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Leow, Alex D; Toga, Arthur W; Thompson, Paul M (Hum Brain Mapp, 2010)
Obesity is associated with increased risk for cardiovascular health problems including diabetes, hypertension, and stroke. These cardiovascular afflictions increase risk for cognitive decline and dementia, but it is unknown whether these factors, specifically obesity and Type II diabetes, are associated with specific patterns of brain atrophy. We used tensor-based morphometry (TBM) to examine gray matter (GM) and white matter (WM) volume differences in 94 elderly subjects who remained cognitively normal for at least 5 years after their scan. Bivariate analyses with corrections for multiple comparisons strongly linked body mass index (BMI), fasting plasma insulin (FPI) levels, and Type II Diabetes Mellitus (DM2) with atrophy in frontal, temporal, and subcortical brain regions. A multiple regression model, also correcting for multiple comparisons, revealed that BMI was still negatively correlated with brain atrophy (FDR <5%), while DM2 and FPI were no longer associated with any volume differences. In an Analysis of Covariance (ANCOVA) model controlling for age, gender, and race, obese subjects with a high BMI (BMI > 30) showed atrophy in the frontal lobes, anterior cingulate gyrus, hippocampus, and thalamus compared with individuals with a normal BMI (18.5-25). Overweight subjects (BMI: 25-30) had atrophy in the basal ganglia and corona radiata of the WM. Overall brain volume did not differ between overweight and obese persons. Higher BMI was associated with lower brain volumes in overweight and obese elderly subjects. Obesity is therefore associated with detectable brain volume deficits in cognitively normal elderly subjects.
Keywords: Age Factors; Aged; Analysis of Variance; Body Mass Index; Brain; Continental Population Groups; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Insulin; Magnetic Resonance Imaging; Male; Nerve Fibers, Myelinated; Nerve Fibers, Unmyelinated; Obesity; Organ Size; Regression Analysis; Sex Factors

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Combined association of lipids and blood pressure in relation to incident cardiovascular disease in the elderly: the cardiovascular health study. - Wong, Nathan D; Lopez, Victor A; Roberts, Craig S; Solomon, Henry A; Burke, Gregory L; Kuller, Lewis; Tracy, Russell; Yanez, David; Psaty, Bruce M (Am J Hypertens, 2010)
BACKGROUND: Hypertension and dyslipidemia are highly prevalent in the elderly. We studied the combined impact of both conditions on cardiovascular disease (CVD) events. METHODS: We studied 4,311 participants aged 65-98 (61.2% female) from the Cardiovascular Health Study (CHS), a longitudinal epidemiologic study, with no prior CVD. We evaluated the relation of low-density lipoprotein (LDL), high-density lipoprotein (HDL), or non-HDL-cholesterol combined with blood pressure (BP) categories to incident CVD-including coronary heart disease (CHD) (angina, myocardial infarction (MI), angioplasty, coronary bypass surgery, or CHD death), stroke, claudication, and CVD death over 15 years. RESULTS: CVD incidence (per 1,000 person years) ranged from 38.4 when BP <120/80 mm Hg and LDL-C <100 mg/dl to 94.8 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl, and from 28.9 when BP <120/80 mm Hg and HDL >60 mg/dl to 87.1 for a BP >or=160/100 and HDL-C <40 mg/dl. Compared with those with BP <120/80 mm Hg with either LDL-C <100 mg/dl or HDL-C >60 mg/dl, hazard ratios (HRs) for CVD events were 2.1 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl and 2.1 when BP >or=160/100 and HDL-C <40 mg/dl (all P < 0.01), with similar results for non-HDL-C. Elevated BP was associated with increased risk across all lipid levels. Increased LDL-C added risk mainly when BP <140/90 mm Hg, but lower HDL-C also predicted CVD in those with higher BP. CONCLUSION: Increased BP confers increased risks for CVD in elderly persons across all lipid levels. Although increased LDL-C added risk mainly when BP <140/90 mm Hg, low HDL-C added risk also in those with hypertension. These results document the importance of combined hypertension and dyslipidemia.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus; Female; Health Surveys; Humans; Likelihood Functions; Lipids; Male; Proportional Hazards Models; Sex Factors; Smoking; Socioeconomic Factors; United States

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

C-reactive protein concentration and risk of coronary heart disease, stroke, and mortality: an individual participant meta-analysis. - Kaptoge, Stephen; Di Angelantonio, Emanuele; Lowe, Gordon; Pepys, Mark B; Thompson, Simon G; Collins, Rory; Danesh, John (Lancet, 2010)
BACKGROUND: Associations of C-reactive protein (CRP) concentration with risk of major diseases can best be assessed by long-term prospective follow-up of large numbers of people. We assessed the associations of CRP concentration with risk of vascular and non-vascular outcomes under different circumstances. METHODS: We meta-analysed individual records of 160 309 people without a history of vascular disease (ie, 1.31 million person-years at risk, 27 769 fatal or non-fatal disease outcomes) from 54 long-term prospective studies. Within-study regression analyses were adjusted for within-person variation in risk factor levels. RESULTS: Log(e) CRP concentration was linearly associated with several conventional risk factors and inflammatory markers, and nearly log-linearly with the risk of ischaemic vascular disease and non-vascular mortality. Risk ratios (RRs) for coronary heart disease per 1-SD higher log(e) CRP concentration (three-fold higher) were 1.63 (95% CI 1.51-1.76) when initially adjusted for age and sex only, and 1.37 (1.27-1.48) when adjusted further for conventional risk factors; 1.44 (1.32-1.57) and 1.27 (1.15-1.40) for ischaemic stroke; 1.71 (1.53-1.91) and 1.55 (1.37-1.76) for vascular mortality; and 1.55 (1.41-1.69) and 1.54 (1.40-1.68) for non-vascular mortality. RRs were largely unchanged after exclusion of smokers or initial follow-up. After further adjustment for fibrinogen, the corresponding RRs were 1.23 (1.07-1.42) for coronary heart disease; 1.32 (1.18-1.49) for ischaemic stroke; 1.34 (1.18-1.52) for vascular mortality; and 1.34 (1.20-1.50) for non-vascular mortality. INTERPRETATION: CRP concentration has continuous associations with the risk of coronary heart disease, ischaemic stroke, vascular mortality, and death from several cancers and lung disease that are each of broadly similar size. The relevance of CRP to such a range of disorders is unclear. Associations with ischaemic vascular disease depend considerably on conventional risk factors and other markers of inflammation. FUNDING: British Heart Foundation, UK Medical Research Council, BUPA Foundation, and GlaxoSmithKline.
Keywords: Alcohol Drinking; Biomarkers; Blood Pressure; Body Mass Index; C-Reactive Protein; Cholesterol; Coronary Disease; Databases, Factual; Diabetes Mellitus; Female; Fibrinogen; Humans; Interleukin-6; Leukocyte Count; Lung Diseases; Male; Middle Aged; Motor Activity; Neoplasms; Regression Analysis; Risk Assessment; Risk Factors; Serum Albumin; Sex Factors; Smoking; Stroke; Triglycerides

CRP gene variation and risk of community-acquired pneumonia. - Mukamal, Kenneth J; Pai, Jennifer K; O'Meara, Ellen S; Tracy, Russell P; Psaty, Bruce M; Kuller, Lewis H; Newman, Anne B; Yende, Sachin; Curhan, Gary C; Siscovick, David S; Rimm, Eric B (Respirology, 2010)
BACKGROUND AND OBJECTIVE: CRP has several potentially antibacterial effects, and variation in the CRP gene is known to influence CRP levels. Whether this variation influences risk of infection, and hence whether CRP has anti-infective activity in humans, is uncertain. METHODS: We evaluated a series of haplotype-tagging single nucleotide polymorphisms among 5374 individuals in the Cardiovascular Health Study, a cohort of older adults from four communities, who were followed for community-acquired pneumonia for 12-13 years. Secondarily, we evaluated whether these polymorphisms varied among men in the Health Professionals Follow-up Study who self-reported pneumonia on biennial questionnaires. RESULTS: There were 581 (507 white and 74 black) Cardiovascular Health Study participants with incident hospitalizations for pneumonia. No single nucleotide polymorphism or haplotypes were associated with risk among white Cardiovascular Health Study participants. Among black participants, the haplotype tagged by A790T was associated with lower risk of incident pneumonia (hazard ratio 0.5; 95% confidence interval: 0.3-0.9) and with higher CRP levels. In Health Professionals Follow-up Study, a separate haplotype was associated with less frequent self-reported pneumonia but not with circulating CRP levels. CONCLUSIONS: Some genetic variants in CRP may be associated with risk of pneumonia, but haplotypes associated with risk are variably associated with baseline CRP levels. If CRP is a relevant component of innate immunity in humans, the inducibility or tissue-specificity of expression may be at least as important as chronic circulating levels.
Keywords: African Americans; Aged; Aged, 80 and over; Body Mass Index; C-Reactive Protein; Cohort Studies; Community-Acquired Infections; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Pneumonia; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Fucosyltransferase 2 (FUT2) non-secretor status is associated with Crohn's disease. - McGovern, Dermot P B; Jones, Michelle R; Taylor, Kent D; Marciante, Kristin; Yan, Xiaofei; Dubinsky, Marla; Ippoliti, Andy; Vasiliauskas, Eric; Berel, Dror; Derkowski, Carrie; Dutridge, Deb; Fleshner, Phil; et al. (Hum Mol Genet, 2010)
Genetic variation in both innate and adaptive immune systems is associated with Crohn's disease (CD) susceptibility, but much of the heritability to CD remains unknown. We performed a genome-wide association study (GWAS) in 896 CD cases and 3204 healthy controls all of Caucasian origin as defined by multidimensional scaling. We found supportive evidence for 21 out of 40 CD loci identified in a recent CD GWAS meta-analysis, including two loci which had only nominally achieved replication (rs4807569, 19p13; rs991804, CCL2/CCL7). In addition, we identified associations with genes involved in tight junctions/epithelial integrity (ASHL, ARPC1A), innate immunity (EXOC2), dendritic cell biology [CADM1 (IGSF4)], macrophage development (MMD2), TGF-beta signaling (MAP3K7IP1) and FUT2 (a physiological trait that regulates gastrointestinal mucosal expression of blood group A and B antigens) (rs602662, P=3.4x10(-5)). Twenty percent of Caucasians are 'non-secretors' who do not express ABO antigens in saliva as a result of the FUT2 W134X allele. We demonstrated replication in an independent cohort of 1174 CD cases and 357 controls between the four primary FUT2 single nucleotide polymorphisms (SNPs) and CD (rs602662, combined P-value 4.90x10(-8)) and also association with FUT2 W143X (P=2.6x10(-5)). Further evidence of the relevance of this locus to CD pathogenesis was demonstrated by the association of the original four SNPs and CD in the recently published CD GWAS meta-analysis (rs602662, P=0.001). These findings strongly implicate this locus in CD susceptibility and highlight the role of the mucus layer in the development of CD.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Cohort Studies; Crohn Disease; Female; Fucosyltransferases; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Genetic predictors of medically refractory ulcerative colitis. - Haritunians, Talin; Taylor, Kent D; Targan, Stephan R; Dubinsky, Marla; Ippoliti, Andrew; Kwon, Soonil; Guo, Xiuqing; Melmed, Gil Y; Berel, Dror; Mengesha, Emebet; Psaty, Bruce M; Glazer, Nicole L; et al. (Inflamm Bowel Dis, 2010)
BACKGROUND: Acute severe ulcerative colitis (UC) remains a significant clinical challenge and the ability to predict, at an early stage, those individuals at risk of colectomy for medically refractory UC (MR-UC) would be a major clinical advance. The aim of this study was to use a genome-wide association study (GWAS) in a well-characterized cohort of UC patients to identify genetic variation that contributes to MR-UC. METHODS: A GWAS comparing 324 MR-UC patients with 537 non-MR-UC patients was analyzed using logistic regression and Cox proportional hazards methods. In addition, the MR-UC patients were compared with 2601 healthy controls. RESULTS: MR-UC was associated with more extensive disease (P = 2.7 × 10(-6)) and a positive family history of UC (P = 0.004). A risk score based on the combination of 46 single nucleotide polymorphisms (SNPs) associated with MR-UC explained 48% of the variance for colectomy risk in our cohort. Risk scores divided into quarters showed the risk of colectomy to be 0%, 17%, 74%, and 100% in the four groups. Comparison of the MR-UC subjects with healthy controls confirmed the contribution of the major histocompatibility complex to severe UC (peak association: rs17207986, P = 1.4 × 10(-16)) and provided genome-wide suggestive association at the TNFSF15 (TL1A) locus (peak association: rs11554257, P = 1.4 × 10(-6)). CONCLUSIONS: A SNP-based risk scoring system, identified here by GWAS analyses, may provide a useful adjunct to clinical parameters for predicting the natural history of UC. Furthermore, discovery of genetic processes underlying disease severity may help to identify pathways for novel therapeutic intervention in severe UC.
Keywords: Acute Disease; Adolescent; Adult; Cohort Studies; Colectomy; Colitis, Ulcerative; Female; Genetic Loci; Genome-Wide Association Study; Humans; Major Histocompatibility Complex; Male; Polymorphism, Single Nucleotide; Risk Factors; Severity of Illness Index; Tumor Necrosis Factor Ligand Superfamily Member 15; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association study identifies GPC5 as a novel genetic locus protective against sudden cardiac arrest. - Arking, Dan E; Reinier, Kyndaron; Post, Wendy; Jui, Jonathan; Hilton, Gina; O'Connor, Ashley; Prineas, Ronald J; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Rea, Thomas; Sotoodehnia, Nona; et al. (PLoS One, 2010)
BACKGROUND: Existing studies indicate a significant genetic component for sudden cardiac arrest (SCA) and genome-wide association studies (GWAS) provide an unbiased approach for identification of novel genes. We performed a GWAS to identify genetic determinants of SCA. METHODOLOGY/PRINCIPAL FINDINGS: We used a case-control design within the ongoing Oregon Sudden Unexpected Death Study (Oregon-SUDS). Cases (n = 424) were SCAs with coronary artery disease (CAD) among residents of Portland, OR (2002-07, population approximately 1,000,000) and controls (n = 226) were residents with CAD, but no history of SCA. All subjects were of White-European ancestry and GWAS was performed using Affymetrix 500K/5.0 and 6.0 arrays. High signal markers were genotyped in SCA cases (n = 521) identified from the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) (combined n = 19,611). No SNPs reached genome-wide significance (p<5x10(-8)). SNPs at 6 loci were prioritized for follow-up primarily based on significance of p<10(-4) and proximity to a known gene (CSMD2, GPR37L1, LIN9, B4GALNT3, GPC5, and ZNF592). The minor allele of GPC5 (GLYPICAN 5, rs3864180) was associated with a lower risk of SCA in Oregon-SUDS, an effect that was also observed in ARIC/CHS whites (p<0.05) and blacks (p<0.04). In a combined Cox proportional hazards model analysis that adjusted for race, the minor allele exhibited a hazard ratio of 0.85 (95% CI 0.74 to 0.98; p<0.01). CONCLUSIONS/SIGNIFICANCE: A novel genetic locus for SCA, GPC5, was identified from Oregon-SUDS and successfully validated in the ARIC and CHS cohorts. Three other members of the Glypican family have been previously implicated in human disease, including cardiac conditions. The mechanism of this specific association requires further study.
Keywords: Aged; Alleles; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Ethnic Groups; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glypicans; Heart Diseases; Humans; Male; Middle Aged; Models, Genetic; Oligonucleotide Array Sequence Analysis; Oregon; Polymorphism, Single Nucleotide

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic

Genome-wide meta-analyses identify multiple loci associated with smoking behavior. (Nat Genet, 2010)
Consistent but indirect evidence has implicated genetic factors in smoking behavior. We report meta-analyses of several smoking phenotypes within cohorts of the Tobacco and Genetics Consortium (n = 74,053). We also partnered with the European Network of Genetic and Genomic Epidemiology (ENGAGE) and Oxford-GlaxoSmithKline (Ox-GSK) consortia to follow up the 15 most significant regions (n > 140,000). We identified three loci associated with number of cigarettes smoked per day. The strongest association was a synonymous 15q25 SNP in the nicotinic receptor gene CHRNA3 (rs1051730[A], beta = 1.03, standard error (s.e.) = 0.053, P = 2.8 x 10(-73)). Two 10q25 SNPs (rs1329650[G], beta = 0.367, s.e. = 0.059, P = 5.7 x 10(-10); and rs1028936[A], beta = 0.446, s.e. = 0.074, P = 1.3 x 10(-9)) and one 9q13 SNP in EGLN2 (rs3733829[G], beta = 0.333, s.e. = 0.058, P = 1.0 x 10(-8)) also exceeded genome-wide significance for cigarettes per day. For smoking initiation, eight SNPs exceeded genome-wide significance, with the strongest association at a nonsynonymous SNP in BDNF on chromosome 11 (rs6265[C], odds ratio (OR) = 1.06, 95% confidence interval (Cl) 1.04-1.08, P = 1.8 x 10(-8)). One SNP located near DBH on chromosome 9 (rs3025343[G], OR = 1.12, 95% Cl 1.08-1.18, P = 3.6 x 10(-8)) was significantly associated with smoking cessation.
Keywords: Age Factors; Alleles; Chromosome Mapping; Female; Genome; Genome-Wide Association Study; Genotype; Humans; Male; Molecular Epidemiology; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci. - Franke, Andre; McGovern, Dermot P B; Barrett, Jeffrey C; Wang, Kai; Radford-Smith, Graham L; Ahmad, Tariq; Lees, Charlie W; Balschun, Tobias; Lee, James; Roberts, Rebecca; Anderson, Carl A; Bis, Joshua C; et al. (Nat Genet, 2010)
We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate genes including SMAD3, ERAP2, IL10, IL2RA, TYK2, FUT2, DNMT3A, DENND1B, BACH2 and TAGAP. Combined with previously confirmed loci, these results identify 71 distinct loci with genome-wide significant evidence for association with Crohn's disease.
Keywords: Computational Biology; Crohn Disease; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Reproducibility of Results

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Interaction between fibrinogen and IL-6 genetic variants and associations with cardiovascular disease risk in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Jarvik, Gail P; Lange, Leslie A; Cushman, Mary; Tracy, Russell P; Reiner, Alexander P (Ann Hum Genet, 2010)
The inflammatory cytokine interleukin-6 (IL-6) is a main regulator of fibrinogen synthesis, though its interaction with fibrinogen genes (FGA, FGB, FGG) and subsequent impact on cardiovascular disease (CVD) risk is not well-studied. We investigated joint associations of fibrinogen and IL6 tagSNPs with fibrinogen concentrations, carotid intima-media thickness, and myocardial infarction or ischemic stroke in 3900 European-American Cardiovascular Health Study participants. To identify combinations of genetic main effects and interactions associated with outcomes, we used logic regression. We also evaluated whether the relationship between fibrinogen SNPs and fibrinogen level varied by IL-6 level using linear regression models with multiplicative interaction terms. Combinations of fibrinogen and IL6 SNPs were significantly associated with fibrinogen level (p < 0.005), but not with other outcomes. Fibrinogen levels were higher in individuals having FGB1437 (rs1800790) and lacking FGA6534 (rs6050) minor alleles; these SNPs interacted with IL6 rs1800796 to influence fibrinogen level. Marginally significant (p= 0.03) interactions between IL-6 level and FGA and FGG promoter SNPs associated with fibrinogen levels were detected. We identified potential gene-gene interactions influencing fibrinogen levels. Although IL-6 responsive binding sites are present in fibrinogen gene promoter regions, we did not find strong evidence of interaction between fibrinogen SNPs and IL6 SNPs or levels influencing CVD.
Keywords: Aged; Cardiovascular Diseases; Carotid Arteries; Female; Fibrinogen; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Male; Models, Biological; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk; Stroke

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Intravenous tissue plasminogen activator and stroke in the elderly. - Longstreth, W T; Katz, Ronit; Tirschwell, David L; Cushman, Mary; Psaty, Bruce M (Am J Emerg Med, 2010)
OBJECTIVE: Since publication in 1995 of the National Institute of Neurological Disorders and Stroke (NINDS) trial of intravenous tissue plasminogen activator (IV tPA) for acute ischemic stroke, the benefit and frequency of use of IV tPA in the elderly have remained uncertain. METHODS: We obtained data from the NINDS trial to summarize outcomes for randomized subjects older than 80 years. We used data from the Cardiovascular Health Study, a cohort study of 5888 elderly participants from 4 US communities followed longitudinally for stroke since 1989 to estimate the use of and hospital outcome after IV tPA in older adults following publication of the trial in 1995. RESULTS: In the NINDS trial, 44 subjects older than 80 years were randomized, and their 3-month functional outcomes were not significantly improved with IV tPA. Of 25 randomized to IV tPA, 4 experienced symptomatic intracranial hemorrhages within 36 hours of treatment. Compared with younger patients, older patients were 2.87 times more likely to experience a symptomatic intracranial hemorrhage within 36 hours of IV tPA (95% confidence interval, 1.04-7.93). Of 227 Cardiovascular Health Study participants hospitalized for ischemic stroke between 1995 and 2002, seven, whose mean age was 84 years, were treated with IV tPA (3.1%; 95% confidence interval 1.2-6.2). Two had symptomatic intracranial hemorrhages, 3 failed to improve, and 2 of the 7 had good outcomes. CONCLUSIONS: These data highlight the need to clarify the risk-benefit profile of IV tPA in ischemic stroke victims who are older than 80 years.
Keywords: Aged, 80 and over; Female; Fibrinolytic Agents; Humans; Longitudinal Studies; Male; Placebos; Randomized Controlled Trials as Topic; Stroke; Tissue Plasminogen Activator; Treatment Outcome; United States

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; European Continental Ancestry Group; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin

Lipoprotein-associated phospholipase A(2) and risk of coronary disease, stroke, and mortality: collaborative analysis of 32 prospective studies. - Thompson, Alexander; Gao, Pei; Orfei, Lia; Watson, Sarah; Di Angelantonio, Emanuele; Kaptoge, Stephen; Ballantyne, Christie; Cannon, Christopher P; Criqui, Michael; Cushman, Mary; Hofman, Albert; Packard, Chris; et al. (Lancet, 2010)
BACKGROUND: Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), an inflammatory enzyme expressed in atherosclerotic plaques, is a therapeutic target being assessed in trials of vascular disease prevention. We investigated associations of circulating Lp-PLA(2) mass and activity with risk of coronary heart disease, stroke, and mortality under different circumstances. METHODS: With use of individual records from 79 036 participants in 32 prospective studies (yielding 17 722 incident fatal or non-fatal outcomes during 474 976 person-years at risk), we did a meta-analysis of within-study regressions to calculate risk ratios (RRs) per 1 SD higher value of Lp-PLA(2) or other risk factor. The primary outcome was coronary heart disease. FINDINGS: Lp-PLA(2) activity and mass were associated with each other (r=0.51, 95% CI 0.47-0.56) and proatherogenic lipids. We noted roughly log-linear associations of Lp-PLA(2) activity and mass with risk of coronary heart disease and vascular death. RRs, adjusted for conventional risk factors, were: 1.10 (95% CI 1.05-1.16) with Lp-PLA(2) activity and 1.11 (1.07-1.16) with Lp-PLA(2) mass for coronary heart disease; 1.08 (0.97-1.20) and 1.14 (1.02-1.27) for ischaemic stroke; 1.16 (1.09-1.24) and 1.13 (1.05-1.22) for vascular mortality; and 1.10 (1.04-1.17) and 1.10 (1.03-1.18) for non-vascular mortality, respectively. RRs with Lp-PLA(2) did not differ significantly in people with and without initial stable vascular disease, apart from for vascular death with Lp-PLA(2) mass. Adjusted RRs for coronary heart disease were 1.10 (1.02-1.18) with non-HDL cholesterol and 1.10 (1.00-1.21) with systolic blood pressure. INTERPRETATION: Lp-PLA(2) activity and mass each show continuous associations with risk of coronary heart disease, similar in magnitude to that with non-HDL cholesterol or systolic blood pressure in this population. Associations of Lp-PLA(2) mass and activity are not exclusive to vascular outcomes, and the vascular associations depend at least partly on lipids. FUNDING: UK Medical Research Council, GlaxoSmithKline, and British Heart Foundation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Blood Pressure; Coronary Disease; Female; Humans; Linear Models; Lipids; Male; Middle Aged; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Systole

Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) and risk of cardiovascular disease in older adults: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Solomon, Cam; Cushman, Mary; Tracy, Russell P; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt D (Atherosclerosis, 2010)
OBJECTIVE: To examine associations between lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) antigen level (mass) and enzymatic activity (activity) and cardiovascular disease (CVD) in older adults. METHODS: We examined associations of Lp-PLA(2) mass and activity with incident myocardial infarction (MI; n=508), stroke (n=565) and CVD death (n=665) using Cox regressions adjusted for age, sex, ethnicity and CVD risk factors in 3949 older adults, aged > or =65 years at baseline, from the Cardiovascular Health Study (CHS). RESULTS: Lp-PLA(2) was associated with incident CVD events in these older adults. Hazard ratios (95% confidence intervals) for highest versus lowest tertiles of Lp-PLA(2) mass were 1.49 (1.19-1.85) for MI, 1.21 (0.98-1.49) for stroke and 1.11 (0.92-1.33) for CVD death. The highest tertile of Lp-PLA(2) activity was associated with MI (1.36; 1.09-1.70) and CVD death (1.23; 1.02-1.50). Combined Lp-PLA(2) tertile 3 and CRP>3mg/l, compared to Lp-PLA(2) tertile 1 and CRP<1mg/l, was associated with MI (2.29; 1.49-3.52) for Lp-PLA(2) mass and MI (1.66; 1.10-2.51) and CVD death (1.57; 1.08-2.26) for activity. For MI, both mass and activity added excess risk to elevated CRP alone ( approximately 20% excess risk) and activity added excess risk for CVD death ( approximately 12%). CONCLUSION: Lp-PLA(2) mass and activity were associated with incident CVD events in older adults in CHS. Lp-PLA(2) and CRP were independent and additive in prediction of events. While associations were modest, these results support further exploration of Lp-PLA(2) to identify older individuals at risk for CVD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk; Stroke

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Obesity is linked with lower brain volume in 700 AD and MCI patients. - Ho, April J; Raji, Cyrus A; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Lee, Suh; Hibar, Derrek; Dinov, Ivo D; Stein, Jason L; Jack, Clifford R; Weiner, Michael W; et al. (Neurobiol Aging, 2010)
Obesity is associated with lower brain volumes in cognitively normal elderly subjects, but no study has yet investigated the effects of obesity on brain structure in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD). To determine if higher body mass index (BMI) is associated with brain volume deficits in cognitively impaired elderly subjects, we analyzed brain magnetic resonance imaging (MRI) scans of 700 MCI or AD patients from 2 different cohorts: the Alzheimer's Disease Neuroimaging Initiative (ADNI) and the Cardiovascular Health Study-Cognition Study (CHS-CS). Tensor-based morphometry (TBM) was used to create 3-dimensional maps of regional tissue excess or deficits in subjects with MCI (ADNI, n = 399; CHS-CS, n = 77) and AD (ADNI, n = 188; CHS, n = 36). In both AD and MCI groups, higher body mass index was associated with brain volume deficits in frontal, temporal, parietal, and occipital lobes; the atrophic pattern was consistent in both ADNI and CHS populations. Cardiovascular risk factors, especially obesity, should be considered as influencing brain structure in those already afflicted by cognitive impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Obesity; Organ Size; Prospective Studies; Risk Factors

Physical activity predicts gray matter volume in late adulthood: the Cardiovascular Health Study. - Erickson, K I; Raji, C A; Lopez, O L; Becker, J T; Rosano, C; Newman, A B; Gach, H M; Thompson, P M; Ho, A J; Kuller, L H (Neurology, 2010)
OBJECTIVES: Physical activity (PA) has been hypothesized to spare gray matter volume in late adulthood, but longitudinal data testing an association has been lacking. Here we tested whether PA would be associated with greater gray matter volume after a 9-year follow-up, a threshold could be identified for the amount of walking necessary to spare gray matter volume, and greater gray matter volume associated with PA would be associated with a reduced risk for cognitive impairment 13 years after the PA evaluation. METHODS: In 299 adults (mean age 78 years) from the Cardiovascular Health Cognition Study, we examined the association between gray matter volume, PA, and cognitive impairment. Physical activity was quantified as the number of blocks walked over 1 week. High-resolution brain scans were acquired 9 years after the PA assessment on cognitively normal adults. White matter hyperintensities, ventricular grade, and other health variables at baseline were used as covariates. Clinical adjudication for cognitive impairment occurred 13 years after baseline. RESULTS: Walking amounts ranged from 0 to 300 blocks (mean 56.3; SD 69.7). Greater PA predicted greater volumes of frontal, occipital, entorhinal, and hippocampal regions 9 years later. Walking 72 blocks was necessary to detect increased gray matter volume but walking more than 72 blocks did not spare additional volume. Greater gray matter volume with PA reduced the risk for cognitive impairment 2-fold. CONCLUSION: Greater amounts of walking are associated with greater gray matter volume, which is in turn associated with a reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Motor Activity; Neuropsychological Tests; Odds Ratio; Predictive Value of Tests; Surveys and Questionnaires

Post hoc Parkinson's disease: identifying an uncommon disease in the Cardiovascular Health Study. - Ton, T G; Jain, S; Boudreau, R; Thacker, E L; Strotmeyer, E S; Newman, A B; Longstreth, W T; Checkoway, H (Neuroepidemiology, 2010)
BACKGROUND: Although ongoing cohort studies offer a unique opportunity to apply existing information collected prospectively to further the scientific understanding of Parkinson's disease (PD), they typically have limited information for clinical diagnosis. METHODS: We used combinations of self-report, International Classification of Diseases - 9th edition codes and antiparkinsonian medications to identify PD in the Cardiovascular Health Study. To determine whether the expected inverse association between smoking and PD is evident using our outcome definitions, we assessed baseline smoking characteristics for various definitions of PD. RESULTS: We identified 60 cases with prevalent PD (1.0%; 95% confidence interval, CI = 0.8-1.3%) and 154 with incident PD by year 14. Clear associations were observed for current smokers (odds ratio, OR = 0.50; 95% CI = 0.26-0.95) and for those who smoked ≥50 pack-years (OR = 0.53; 95% CI = 0.29-0.96). Estimates for smoking were similar when ≥2 data sources were required. Estimates for self-report alone were attenuated towards null. CONCLUSIONS: Using multiple data sources to identify PD represents an alternative method of outcome identification in a cohort that would otherwise not be possible for PD research. Ongoing cohort studies can provide settings in which rapid replication and explorations of new hypotheses for PD are possible.
Keywords: Aged; Aged, 80 and over; Cardiovascular System; Cohort Studies; Female; Health Status; Humans; Incidence; Male; Odds Ratio; Parkinson Disease; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Prevalence, incidence, and persistence of major depressive symptoms in the Cardiovascular Health Study. - Thielke, Stephen M; Diehr, Paula; Unutzer, Jurgen (Aging Ment Health, 2010)
PURPOSE: To explore the association of major depressive symptoms with advancing age, sex, and self-rated health among older adults. DESIGN AND METHODS: We analyzed 10 years of annual assessments in a longitudinal cohort of 5888 Medicare recipients in the Cardiovascular Health Study. Self-rated health was assessed with a single question, and subjects categorized as healthy or sick. Major depressive symptoms were assessed using the Center for Epidemiologic Studies Short Depression Scale, with subjects categorized as nondepressed (score < 10) or depressed (> or =10). Age-, sex-, and health-specific prevalence of depression and the probabilities of transition between depressed and nondepressed states were estimated. RESULTS: The prevalence of a major depressive state was higher in women, and increased with advancing age. The probability of becoming depressed increased with advancing age among the healthy but not the sick. Women showed a greater probability than men of becoming depressed, regardless of health status. Major depressive symptoms persisted over one-year intervals in about 60% of the healthy and 75% of the sick, with little difference between men and women. IMPLICATIONS: Clinically significant depressive symptoms occur commonly in older adults, especially women, increase with advancing age, are associated with poor self-rated health, and are largely intransigent. In order to limit the deleterious consequences of depression among older adults, increased attention to prevention, screening, and treatment is warranted. A self-rated health item could be used in clinical settings to refine the prognosis of late-life depression.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cohort Studies; Depression; Depressive Disorder, Major; Female; Geriatric Assessment; Health Status; Humans; Incidence; Longitudinal Studies; Male; Personality Assessment; Prevalence; Psychiatric Status Rating Scales; Quality of Life; Sex Factors; Surveys and Questionnaires

Prospective study of obstructive sleep apnea and incident coronary heart disease and heart failure: the sleep heart health study. - Gottlieb, Daniel J; Yenokyan, Gayane; Newman, Anne B; O'Connor, George T; Punjabi, Naresh M; Quan, Stuart F; Redline, Susan; Resnick, Helaine E; Tong, Elisa K; Diener-West, Marie; Shahar, Eyal (Circulation, 2010)
BACKGROUND: Clinic-based observational studies in men have reported that obstructive sleep apnea is associated with an increased incidence of coronary heart disease. The objective of this study was to assess the relation of obstructive sleep apnea to incident coronary heart disease and heart failure in a general community sample of adult men and women. METHODS AND RESULTS: A total of 1927 men and 2495 women > or =40 years of age and free of coronary heart disease and heart failure at the time of baseline polysomnography were followed up for a median of 8.7 years in this prospective longitudinal epidemiological study. After adjustment for multiple risk factors, obstructive sleep apnea was a significant predictor of incident coronary heart disease (myocardial infarction, revascularization procedure, or coronary heart disease death) only in men < or =70 years of age (adjusted hazard ratio 1.10 [95% confidence interval 1.00 to 1.21] per 10-unit increase in apnea-hypopnea index [AHI]) but not in older men or in women of any age. Among men 40 to 70 years old, those with AHI > or =30 were 68% more likely to develop coronary heart disease than those with AHI <5. Obstructive sleep apnea predicted incident heart failure in men but not in women (adjusted hazard ratio 1.13 [95% confidence interval 1.02 to 1.26] per 10-unit increase in AHI). Men with AHI > or =30 were 58% more likely to develop heart failure than those with AHI <5. CONCLUSIONS: Obstructive sleep apnea is associated with an increased risk of incident heart failure in community-dwelling middle-aged and older men; its association with incident coronary heart disease in this sample is equivocal.
Keywords: Adult; Aged; Coronary Disease; Female; Heart Failure; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Sleep Apnea, Obstructive; Survival Analysis

Secondhand smoke, vascular disease, and dementia incidence: findings from the cardiovascular health cognition study. - Barnes, Deborah E; Haight, Thaddeus J; Mehta, Kala M; Carlson, Michelle C; Kuller, Lewis H; Tager, Ira B (Am J Epidemiol, 2010)
Recent studies have found that smoking is associated with an increased risk of dementia, but the effects of secondhand smoke (SHS) on dementia risk are not known to have previously been studied. The authors used Cox proportional hazards marginal structural models to examine the association between self-reported lifetime household SHS exposure and risk of incident dementia over 6 years among 970 US participants in the Cardiovascular Health Cognition Study (performed from 1991 to 1999) who were never smokers and were free of clinical cardiovascular disease (CVD), dementia, and mild cognitive impairment at baseline. In addition, because prior studies have found that SHS is associated with increased risk of CVD and that CVD is associated with increased risk of dementia, the authors tested for interactions between SHS and measures of clinical and subclinical CVD on dementia risk. Moderate (16-25 years) and high (>25 years) SHS exposure levels were not independently associated with dementia risk; however, subjects with >25 years of SHS exposure and >25% carotid artery stenosis had a 3-fold increase (hazard ratio = 3.00, 95% confidence interval: 1.03, 9.72) in dementia risk compared with subjects with no/low (0-15 years) SHS exposure and < or =25% carotid artery stenosis. High lifetime SHS exposure may increase the risk of dementia in elderly with undiagnosed CVD.
Keywords: Aged; Dementia; Female; Humans; Incidence; Male; Risk Factors; Tobacco Smoke Pollution; Vascular Diseases

Significance of the amyloidogenic transthyretin Val 122 Ile allele in African Americans in the Arteriosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies. - Buxbaum, Joel; Alexander, Alice; Koziol, James; Tagoe, Clement; Fox, Ervin; Kitzman, Dalane (Am Heart J, 2010)
BACKGROUND: Many African Americans carry an amyloidogenic transthyretin mutation (TTR V122I), with a high risk for cardiac TTR amyloid deposition after the age of 65 years. We wished to determine the allele frequency and its clinical penetrance in community-dwelling African Americans. METHODS: Five thousand consenting African Americans, aged 41 to 93 years, in 2 community studies of cardiovascular risk (CHS and ARIC) were included in the study. The following were performed: genotyping of banked DNA for TTR V122I allele status and review of cardiovascular and demographic parameters in CHS and ARIC databases, with statistical comparisons of the frequency of congestive heart failure, survival, and occurrence of features of cardiac amyloidosis in carriers of the amyloidogenic allele and controls. RESULTS: One hundred nineteen (3.23%) of 3,712 ARIC and 17 (2.12%) of 805 CHS African Americans carried TTR V122I. After the age of 65 years (CHS), the frequencies of congestive heart failure (38% vs 15%, relative risk 2.62, P = .04) and mortality (76% vs 53%, relative risk 1.46, P = .08) were higher in V122I allele carriers than in age-, gender- and ethnically matched controls. In ARIC (all subjects <65 years old), there were no differences between carriers and noncarriers in mortality, frequency of congestive heart failure, or findings consistent with cardiac amyloidosis. CONCLUSIONS: Heterozygosity for the amyloidogenic TTR V122I mutation is relatively common in community-dwelling African Americans. Before the age of 65 years, the allele has no discernible impact on cardiac function or mortality. After the age of 70 years, carriers show a higher frequency of congestive failure and greater mortality with more echocardiographic evidence suggestive of cardiac amyloidosis, findings consistent with age-dependent clinical penetrance of this autosomal dominant gene.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Amyloidosis; Female; Gene Frequency; Heart Diseases; Humans; Isoleucine; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Prealbumin; Ultrasonography; Valine

Study of the relationship between the interleukin-6 gene and obstructive sleep apnea. - Larkin, Emma K; Patel, Sanjay R; Zhu, Xiaofeng; Tracy, Russell P; Jenny, Nancy S; Reiner, Alex P; Walston, Jeremy; Redline, Susan (Clin Transl Sci, 2010)
Keywords: Adult; African Americans; Alleles; Female; Humans; Interleukin-6; Male; Middle Aged; Polymorphism, Single Nucleotide; Sleep Apnea, Obstructive

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Triglyceride-mediated pathways and coronary disease: collaborative analysis of 101 studies. - Sarwar, Nadeem; Sandhu, Manjinder S; Ricketts, Sally L; Butterworth, Adam S; Di Angelantonio, Emanuele; Boekholdt, S Matthijs; Ouwehand, Willem; Watkins, Hugh; Samani, Nilesh J; Saleheen, Danish; Lawlor, Debbie; Reilly, Muredach P; et al. (Lancet, 2010)
BACKGROUND: Whether triglyceride-mediated pathways are causally relevant to coronary heart disease is uncertain. We studied a genetic variant that regulates triglyceride concentration to help judge likelihood of causality. METHODS: We assessed the -1131T>C (rs662799) promoter polymorphism of the apolipoprotein A5 (APOA5) gene in relation to triglyceride concentration, several other risk factors, and risk of coronary heart disease. We compared disease risk for genetically-raised triglyceride concentration (20,842 patients with coronary heart disease, 35,206 controls) with that recorded for equivalent differences in circulating triglyceride concentration in prospective studies (302 430 participants with no history of cardiovascular disease; 12,785 incident cases of coronary heart disease during 2.79 million person-years at risk). We analysed -1131T>C in 1795 people without a history of cardiovascular disease who had information about lipoprotein concentration and diameter obtained by nuclear magnetic resonance spectroscopy. FINDINGS: The minor allele frequency of -1131T>C was 8% (95% CI 7-9). -1131T>C was not significantly associated with several non-lipid risk factors or LDL cholesterol, and it was modestly associated with lower HDL cholesterol (mean difference per C allele 3.5% [95% CI 2.6-4.6]; 0.053 mmol/L [0.039-0.068]), lower apolipoprotein AI (1.3% [0.3-2.3]; 0.023 g/L [0.005-0.041]), and higher apolipoprotein B (3.2% [1.3-5.1]; 0.027 g/L [0.011-0.043]). By contrast, for every C allele inherited, mean triglyceride concentration was 16.0% (95% CI 12.9-18.7), or 0.25 mmol/L (0.20-0.29), higher (p=4.4x10(-24)). The odds ratio for coronary heart disease was 1.18 (95% CI 1.11-1.26; p=2.6x10(-7)) per C allele, which was concordant with the hazard ratio of 1.10 (95% CI 1.08-1.12) per 16% higher triglyceride concentration recorded in prospective studies. -1131T>C was significantly associated with higher VLDL particle concentration (mean difference per C allele 12.2 nmol/L [95% CI 7.7-16.7]; p=9.3x10(-8)) and smaller HDL particle size (0.14 nm [0.08-0.20]; p=7.0x10(-5)), factors that could mediate the effects of triglyceride. INTERPRETATION: These data are consistent with a causal association between triglyceride-mediated pathways and coronary heart disease. FUNDING: British Heart Foundation, UK Medical Research Council, Novartis.
Keywords: Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Coronary Disease; Gene Frequency; Genotype; Humans; Lipids; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Mendelian Randomization Analysis; Particle Size; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Triglycerides

Antihypertensive medication use and change in kidney function in elderly adults: a marginal structural model analysis. - Odden, Michelle C; Tager, Ira B; van der Laan, Mark J; Delaney, Joseph A C; Peralta, Carmen A; Katz, Ronit; Sarnak, Mark J; Psaty, Bruce M; Shlipak, Michael G (Int J Biostat, 2011)
BACKGROUND: The evidence for the effectiveness of antihypertensive medication use for slowing decline in kidney function in older persons is sparse. We addressed this research question by the application of novel methods in a marginal structural model. METHODS: Change in kidney function was measured by two or more measures of cystatin C in 1,576 hypertensive participants in the Cardiovascular Health Study over 7 years of follow-up (1989-1997 in four U.S. communities). The exposure of interest was antihypertensive medication use. We used a novel estimator in a marginal structural model to account for bias due to confounding and informative censoring. RESULTS: The mean annual decline in eGFR was 2.41 ± 4.91 mL/min/1.73 m(2). In unadjusted analysis, antihypertensive medication use was not associated with annual change in kidney function. Traditional multivariable regression did not substantially change these estimates. Based on a marginal structural analysis, persons on antihypertensives had slower declines in kidney function; participants had an estimated 0.88 (0.13, 1.63) ml/min/1.73 m(2) per year slower decline in eGFR compared with persons on no treatment. In a model that also accounted for bias due to informative censoring, the estimate for the treatment effect was 2.23 (-0.13, 4.59) ml/min/1.73 m(2) per year slower decline in eGFR. CONCLUSION: In summary, estimates from a marginal structural model suggested that antihypertensive therapy was associated with preserved kidney function in hypertensive elderly adults. Confirmatory studies may provide power to determine the strength and validity of the findings.
Keywords: Aged; Antihypertensive Agents; Cystatin C; Data Interpretation, Statistical; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney; Longitudinal Studies; Male; Models, Statistical

Association of eGFR-Related Loci Identified by GWAS with Incident CKD and ESRD. - Böger, Carsten A; Gorski, Mathias; Li, Man; Hoffmann, Michael M; Huang, Chunmei; Yang, Qiong; Teumer, Alexander; Krane, Vera; O'Seaghdha, Conall M; Kutalik, Zoltán; Wichmann, H-Erich; Haak, Thomas; et al. (PLoS Genet, 2011)
Family studies suggest a genetic component to the etiology of chronic kidney disease (CKD) and end stage renal disease (ESRD). Previously, we identified 16 loci for eGFR in genome-wide association studies, but the associations of these single nucleotide polymorphisms (SNPs) for incident CKD or ESRD are unknown. We thus investigated the association of these loci with incident CKD in 26,308 individuals of European ancestry free of CKD at baseline drawn from eight population-based cohorts followed for a median of 7.2 years (including 2,122 incident CKD cases defined as eGFR <60ml/min/1.73m(2) at follow-up) and with ESRD in four case-control studies in subjects of European ancestry (3,775 cases, 4,577 controls). SNPs at 11 of the 16 loci (UMOD, PRKAG2, ANXA9, DAB2, SHROOM3, DACH1, STC1, SLC34A1, ALMS1/NAT8, UBE2Q2, and GCKR) were associated with incident CKD; p-values ranged from p = 4.1e-9 in UMOD to p = 0.03 in GCKR. After adjusting for baseline eGFR, six of these loci remained significantly associated with incident CKD (UMOD, PRKAG2, ANXA9, DAB2, DACH1, and STC1). SNPs in UMOD (OR = 0.92, p = 0.04) and GCKR (OR = 0.93, p = 0.03) were nominally associated with ESRD. In summary, the majority of eGFR-related loci are either associated or show a strong trend towards association with incident CKD, but have modest associations with ESRD in individuals of European descent. Additional work is required to characterize the association of genetic determinants of CKD and ESRD at different stages of disease progression.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Chronic Disease; Creatinine; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Association Studies; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptor, Epidermal Growth Factor; Uromodulin

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

Chronic kidney disease in octogenarians. - Shastri, Shani; Tighiouart, Hocine; Katz, Ronit; Rifkin, Dena E; Fried, Linda F; Shlipak, Michael G; Newman, Anne B; Sarnak, Mark J (Clin J Am Soc Nephrol, 2011)
BACKGROUND AND OBJECTIVES: There are limited data on the prevalence of chronic kidney disease (CKD) and its clinical importance in the very old. We examined the prevalence of CKD in octogenarians and its association with cardiovascular disease (CVD). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In a cross-sectional analysis of 1028 participants from the Cardiovascular Health Study All Stars, we evaluated association of prevalent CKD with CVD using multivariable logistic regression. CKD was defined as eGFR of <60 ml/min per 1.73 m(2). GFR was estimated using CKD-Epi creatinine and cystatin C equations that incorporate coefficients for age, gender, and race (eGFR(EPI), eGFR(CYS3var)) and the one-variable cystatin C equation (eGFR(CYS1var)). Prevalent CVD was defined as a composite of coronary heart disease, heart failure, and stroke. RESULTS: Mean age was 86 years, 64% were women, 86% were Caucasians, 14% had diabetes, and 39% had prevalent CVD. Mean eGFR(EPI), eGFR(CYS3var), and eGFR(CYS1var) were 59, 62, and 70 ml/min per 1.73 m(2), and 51%, 46%, and 33% had CKD, respectively. Associations of CKD with CVD varied by equation in adjusted analyses: CKD(EPI) (OR, 1.53; 95% CI, 1.15 to 2.03), CKD(CYS3var) (OR, 1.67; 95% CI, 1.25, 2.23), and CKD(CYS1var) (OR, 2.09; 95% CI, 1.55, 2.83). CONCLUSIONS: Reduced eGFR is highly prevalent in octogenarians, and the eGFR(CYS1var) equation yielded the lowest prevalence of CKD but the strongest association with prevalent CVD. Because there are no validated estimating equations in the elderly, estimation of kidney function on the basis of on any one equation should be interpreted with caution.
Keywords: Age Factors; Aged, 80 and over; Analysis of Variance; Biomarkers; Cardiovascular Diseases; Chi-Square Distribution; Chronic Disease; Creatinine; Cross-Sectional Studies; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Logistic Models; Male; Models, Biological; Prevalence; Risk Assessment; Risk Factors; United States

Comparing costs associated with risk stratification rules for t-year survival. - Cai, Tianxi; Tian, Lu; Lloyd-Jones, Donald M (Biostatistics, 2011)
Accurate risk prediction is an important step in developing optimal strategies for disease prevention and treatment. Based on the predicted risks, patients can be stratified to different risk categories where each category corresponds to a particular clinical intervention. Incorrect or suboptimal interventions are likely to result in unnecessary financial and medical consequences. It is thus essential to account for the costs associated with the clinical interventions when developing and evaluating risk stratification (RS) rules for clinical use. In this article, we propose to quantify the value of an RS rule based on the total expected cost attributed to incorrect assignment of risk groups due to the rule. We have established the relationship between cost parameters and optimal threshold values used in the stratification rule that minimizes the total expected cost over the entire population of interest. Statistical inference procedures are developed for evaluating and comparing given RS rules and examined through simulation studies. The proposed procedures are illustrated with an example from the Cardiovascular Health Study.
Keywords: Biostatistics; Coronary Disease; Cost-Benefit Analysis; Costs and Cost Analysis; Humans; Models, Statistical; Risk Assessment; Risk Factors; Time Factors

The contribution of a 9p21.3 variant, a KIF6 variant, and C-reactive protein to predicting risk of myocardial infarction in a prospective study. - Shiffman, Dov; O'Meara, Ellen S; Rowland, Charles M; Louie, Judy Z; Cushman, Mary; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (BMC Cardiovasc Disord, 2011)
BACKGROUND: Genetic risk factors might improve prediction of coronary events. Several variants at chromosome 9p21.3 have been widely reported to be associated with coronary heart disease (CHD) in prospective and case-control studies. A variant of KIF6 (719Arg) has also been reported to be associated with increased risk of CHD in large prospective studies, but not in case-control studies. We asked whether the addition of genetic information (the 9p21.3 or KIF6 variants) or a well-established non-genetic risk factor (C-reactive protein [CRP]) can improve risk prediction by the Framingham Risk Score (FRS) in the Cardiovascular Health Study (CHS)--a prospective observational study of risk factors for cardiovascular disease among > 5,000 participants aged 65 or older. METHODS: Improvement of risk prediction was assessed by change in the area under the receiver-operator characteristic curve (AUC) and by net reclassification improvement (NRI). RESULTS: Among white participants the FRS was improved by addition of KIF6 719Arg carrier status among men as assessed by the AUC (from 0.581 to 0.596, P = 0.03) but not by NRI (NRI = 0.027, P = 0.32). Adding both CRP and 719Arg carrier status to the FRS improved risk prediction by the AUC (0.608, P = 0.02) and NRI (0.093, P = 0.008) in men, but not women (P ≥ 0.24). CONCLUSIONS: While none of these risk markers individually or in combination improved risk prediction among women, a combination of KIF6 719Arg carrier status and CRP levels modestly improved risk prediction among white men; although this improvement is not significant after multiple-testing correction. These observations should be investigated in other prospective studies.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; C-Reactive Protein; Case-Control Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Variation; Humans; Kinesin; Male; Myocardial Infarction; Predictive Value of Tests; Prospective Studies; Risk Factors

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Diabetes mellitus, fasting glucose, and risk of cause-specific death. - Rao Kondapally Seshasai, Sreenivasa; Kaptoge, Stephen; Thompson, Alexander; Di Angelantonio, Emanuele; Gao, Pei; Sarwar, Nadeem; Whincup, Peter H; Mukamal, Kenneth J; Gillum, Richard F; Holme, Ingar; Njølstad, Inger; Fletcher, Astrid; et al. (N Engl J Med, 2011)
BACKGROUND: The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS: We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS: After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with persons without diabetes were as follows: 1.80 (95% confidence interval [CI], 1.71 to 1.90) for death from any cause, 1.25 (95% CI, 1.19 to 1.31) for death from cancer, 2.32 (95% CI, 2.11 to 2.56) for death from vascular causes, and 1.73 (95% CI, 1.62 to 1.85) for death from other causes. Diabetes (vs. no diabetes) was moderately associated with death from cancers of the liver, pancreas, ovary, colorectum, lung, bladder, and breast. Aside from cancer and vascular disease, diabetes (vs. no diabetes) was also associated with death from renal disease, liver disease, pneumonia and other infectious diseases, mental disorders, nonhepatic digestive diseases, external causes, intentional self-harm, nervous-system disorders, and chronic obstructive pulmonary disease. Hazard ratios were appreciably reduced after further adjustment for glycemia measures, but not after adjustment for systolic blood pressure, lipid levels, inflammation or renal markers. Fasting glucose levels exceeding 100 mg per deciliter (5.6 mmol per liter), but not levels of 70 to 100 mg per deciliter (3.9 to 5.6 mmol per liter), were associated with death. A 50-year-old with diabetes died, on average, 6 years earlier than a counterpart without diabetes, with about 40% of the difference in survival attributable to excess nonvascular deaths. CONCLUSIONS: In addition to vascular disease, diabetes is associated with substantial premature death from several cancers, infectious diseases, external causes, intentional self-harm, and degenerative disorders, independent of several major risk factors. (Funded by the British Heart Foundation and others.).
Keywords: Blood Glucose; Cause of Death; Diabetes Mellitus; Female; Humans; Hyperglycemia; Life Expectancy; Male; Middle Aged; Risk; Survival Analysis

The effects of physical activity, education, and body mass index on the aging brain. - Ho, April J; Raji, Cyrus A; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Dinov, Ivo D; Stein, Jason L; Rosano, Caterina; Toga, Arthur W; Thompson, Paul M (Hum Brain Mapp, 2011)
Normal human aging is accompanied by progressive brain tissue loss and cognitive decline; however, several factors are thought to influence brain aging. We applied tensor-based morphometry to high-resolution brain MRI scans to determine whether educational level or physical activity was associated with brain tissue volumes in the elderly, particularly in regions susceptible to age-related atrophy. We mapped the 3D profile of brain volume differences in 226 healthy elderly subjects (130F/96M; 77.9 ± 3.6 SD years) from the Cardiovascular Health Study-Cognition Study. Statistical maps revealed the 3D profile of brain regions whose volumes were associated with educational level and physical activity (based on leisure-time energy expenditure). After controlling for age, sex, and physical activity, higher educational levels were associated with ~2-3% greater tissue volumes, on average, in the temporal lobe gray matter. After controlling for age, sex, and education, greater physical activity was associated with ~2-2.5% greater average tissue volumes in the white matter of the corona radiata extending into the parietal-occipital junction. Body mass index (BMI) was highly correlated with both education and physical activity, so we examined BMI as a contributing factor by including physical activity, education, and BMI in the same model; only BMI effects remained significant. This is one of the largest MRI studies of factors influencing structural brain aging, and BMI may be a key factor explaining the observed relationship between education, physical activity, and brain structure. Independent contributions to brain structure could not be teased apart as all these factors were highly correlated with one another.
Keywords: Aged; Aged, 80 and over; Aging; Analysis of Variance; Body Mass Index; Brain; Brain Mapping; Educational Status; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Motor Activity; Neuropsychological Tests; Statistics as Topic

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Fasting and post-glucose load measures of insulin resistance and risk of ischemic stroke in older adults. - Thacker, Evan L; Psaty, Bruce M; McKnight, Barbara; Heckbert, Susan R; Longstreth, W T; Mukamal, Kenneth J; Meigs, James B; de Boer, Ian H; Boyko, Edward J; Carnethon, Mercedes R; Kizer, Jorge R; Tracy, Russell P; et al. (Stroke, 2011)
BACKGROUND AND PURPOSE: Few studies have assessed post-glucose load measures of insulin resistance and ischemic stroke risk, and data are sparse for older adults. We investigated whether fasting and post-glucose load measures of insulin resistance were related to incident ischemic stroke in nondiabetic, older adults. METHODS: Participants were men and women in the Cardiovascular Health Study, age 65+ years and without prevalent diabetes or stroke at baseline, followed for 17 years for incident ischemic stroke. The Gutt insulin sensitivity index was calculated from baseline body weight and from fasting and 2-hour postload insulin and glucose; a lower Gutt index indicates higher insulin resistance. RESULTS: Analyses included 3442 participants (42% men) with a mean age of 73 years. Incidence of ischemic stroke was 9.8 strokes per 1000 person-years. The relative risk (RR) for lowest quartile versus highest quartile of Gutt index was 1.64 (95% CI, 1.24-2.16), adjusted for demographics and prevalent cardiovascular and kidney disease. Similarly, the adjusted RR for highest quartile versus lowest quartile of 2-hour glucose was 1.84 (95% CI, 1.39-2.42). In contrast, the adjusted RR for highest quartile versus lowest quartile of fasting insulin was 1.10 (95% CI, 0.84-1.46). CONCLUSIONS: In nondiabetic, older adults, insulin resistance measured by Gutt index or 2-hour glucose, but not by fasting insulin, was associated with risk of incident ischemic stroke.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Brain Ischemia; Fasting; Female; Humans; Incidence; Insulin Resistance; Male; Risk; Stroke

A gene-centric association scan for Coagulation Factor VII levels in European and African Americans: the Candidate Gene Association Resource (CARe) Consortium. - Taylor, Kira C; Lange, Leslie A; Zabaneh, Delilah; Lange, Ethan; Keating, Brendan J; Tang, Weihong; Smith, Nicholas L; Delaney, Joseph A; Kumari, Meena; Hingorani, Aroon; North, Kari E; Kivimaki, Mika; et al. (Hum Mol Genet, 2011)
Polymorphisms in several distinct genomic regions, including the F7 gene, were recently associated with factor VII (FVII) levels in European Americans (EAs). The genetic determinants of FVII in African Americans (AAs) are unknown. We used a 50,000 single nucleotide polymorphism (SNP) gene-centric array having dense coverage of over 2,000 candidate genes for cardiovascular disease (CVD) pathways in a community-based sample of 16,324 EA and 3898 AA participants from the Candidate Gene Association Resource (CARe) consortium. Our aim was the discovery of new genomic loci and more detailed characterization of existing loci associated with FVII levels. In EAs, we identified three new loci associated with FVII, of which APOA5 on chromosome 11q23 and HNF4A on chromosome 20q12-13 were replicated in a sample of 4289 participants from the Whitehall II study. We confirmed four previously reported FVII-associated loci (GCKR, MS4A6A, F7 and PROCR) in CARe EA samples. In AAs, the F7 and PROCR regions were significantly associated with FVII. Several of the FVII-associated regions are known to be associated with lipids and other cardiovascular-related traits. At the F7 locus, there was evidence of at least five independently associated SNPs in EAs and three independent signals in AAs. Though the variance in FVII explained by the existing loci is substantial (20% in EA and 10% in AA), larger sample sizes and investigation of lower frequency variants may be required to identify additional FVII-associated loci in EAs and AAs and further clarify the relationship between FVII and other CVD risk factors.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Factor VII; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Health and function of participants in the Long Life Family Study: A comparison with other cohorts. - Newman, Anne B; Glynn, Nancy W; Taylor, Christopher A; Sebastiani, Paola; Perls, Thomas T; Mayeux, Richard; Christensen, Kaare; Zmuda, Joseph M; Barral, Sandra; Lee, Joseph H; Simonsick, Eleanor M; Walston, Jeremy D; et al. (Aging (Albany NY), 2011)
Individuals from families recruited for the Long Life Family Study (LLFS) (n= 4559) were examined and compared to individuals from other cohorts to determine whether the recruitment targeting longevity resulted in a cohort of individuals with better health and function. Other cohorts with similar data included the Cardiovascular Health Study, the Framingham Heart Study, and the New England Centenarian Study. Diabetes, chronic pulmonary disease and peripheral artery disease tended to be less common in LLFS probands and offspring compared to similar aged persons in the other cohorts. Pulse pressure and triglycerides were lower, high density lipids were higher, and a perceptual speed task and gait speed were better in LLFS. Age-specific comparisons showed differences that would be consistent with a higher peak, later onset of decline or slower rate of change across age in LLFS participants. These findings suggest several priority phenotypes for inclusion in future genetic analysis to identify loci contributing to exceptional survival.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Gait; Humans; Longevity; Male; Middle Aged; Psychomotor Performance; Research Design

High blood pressure accelerates gait slowing in well-functioning older adults over 18-years of follow-up. - Rosano, Caterina; Longstreth, William T; Boudreau, Robert; Taylor, Christopher A; Du, Yan; Kuller, Lewis H; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine whether the association between hypertension and decline in gait speed is significant in well-functioning older adults and whether other health-related factors, such as brain, kidney, and heart function, can explain it. DESIGN: Longitudinal cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Of 2,733 potential participants with a brain magnetic resonance imaging (MRI) scan, measures of mobility and systolic blood pressure (BP), no self-reported disability in 1992 to 1994 (baseline), and with at least 1 follow-up gait speed measurement through 1997 to 1999, 643 (aged 73.6, 57% female, 15% black) who had received a second MRI in 1997 to 1999 and an additional gait speed measure in 2005 to 2006 were included. MEASUREMENTS: Mixed models with random slopes and intercepts were adjusted for age, race, and sex. Main explanatory factors included white matter hyperintensity progression, baseline cystatin-C, and left cardiac ventricular mass. Incidence of stroke and dementia, BP trajectories, and intake of antihypertensive medications during follow-up were tested as other potential explanatory factors. RESULTS: Higher systolic BP was associated with faster rate of gait speed decline in this selected group of 643 participants, and results were similar in the parent cohort (N = 2,733). Participants with high BP (n = 293) had a significantly faster rate of gait speed decline than those with baseline BP less than 140/90 mmHg and no history of hypertension (n = 350). Rates were similar for those with history of hypertension who were uncontrolled (n = 110) or controlled (n = 87) at baseline and for those who were newly diagnosed (n = 96) at baseline. Adjustment for explanatory factors or for other covariates (education, prevalent cardiovascular disease, physical activity, vision, mood, cognition, muscle strength, body mass index, osteoporosis) did not change the results. CONCLUSION: High BP accelerates gait slowing in well-functioning older adults over a long period of time, even for those who control their BP or develop hypertension later in life. Health-related measurements did not explain these associations. Future studies to investigate the mechanisms linking hypertension to slowing gait in older adults are warranted.
Keywords: Aged; Antihypertensive Agents; Comorbidity; Female; Follow-Up Studies; Gait; Geriatric Assessment; Humans; Hypertension; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Statistics, Nonparametric

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Leukocyte telomere length and mortality in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kronmal, Richard A; Kimura, Masayuki; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Hardikar, Sheetal; Aviv, Abraham (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Leukocyte telomere length (LTL) is related to diseases of aging, but studies of mortality have been inconsistent. METHODS: We evaluated LTL in relation to total mortality and specific cause of death in 1,136 participants of the Cardiovascular Health Study who provided blood samples in 1992-1993 and survived through 1997-1998. LTL was measured by Southern blots of the terminal restriction fragments. Cause of death was classified by a committee of physicians reviewing death certificates, medical records, and informant interviews. RESULTS: A total of 468 (41.2%) deaths occurred over 6.1 years of follow-up in participants with mean age of 73.9 years (SD 4.7), 65.4% female, and 14.8% African American. Although increased age and male gender were associated with shorter LTLs, African Americans had significantly longer LTLs independent of age and sex (p < .001). Adjusted for age, sex, and race, persons with the shortest quartile of LTL were 60% more likely to die during follow-up than those within the longest quartile (hazard ratio: 1.61, 95% confidence interval: 1.22-2.12, p = .001). The association remained after adjustment for cardiovascular disease risk factors. Evaluations of cause of death found LTL to be related to deaths due to an infectious disease etiology (hazard ratio: 2.80, 95% confidence interval: 1.32-5.94, p = .007), whereas a borderline association was found for cardiac deaths (hazard ratio: 1.82, 95% confidence interval: 0.95-3.49, p = .07) in adjusted models. Risk estimates for deaths due to cancer, dementia, and ischemic stroke were not significant. CONCLUSION: These data weakly corroborate prior findings of associations between LTL and mortality in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Body Mass Index; Cardiovascular Diseases; Cause of Death; Comorbidity; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Leukocytes; Longitudinal Studies; Male; Prospective Studies; Smoking; Stroke; Telomere

Longer legs are associated with greater risk of incident venous thromboembolism independent of total body height. The Longitudinal Study of Thromboembolism Etiology (LITE). - Lutsey, Pamela L; Cushman, Mary; Heckbert, Susan R; Tang, Weihong; Folsom, Aaron R (Thromb Haemost, 2011)
Several studies have reported that taller individuals are at greater risk of venous thromboembolism (VTE). We hypothesised that longer leg length would be positively associated with incident VTE, and would explain the height association. LITE ascertained VTE in a prospective population-based sample of 21,860 individuals aged 45 and older. Leg length was measured as standing height minus torso length. Cox regression models were adjusted for age, race, sex, waist circumference, diabetes, and factor VIII. To evaluate whether leg length was associated with VTE risk independent of height, we standardised leg length and height per 1 standard deviation (SD), and then included them simultaneously in Cox regression models. A total of 641 incident VTE cases accrued over a median follow-up of 16 years. Participants in the highest quintile of leg length were at 59% (95% CI: 22%-108%) greater risk of VTE, relative to the lowest quintile. For height, risk was 45% (12%-88%) greater for those in the highest quintile, compared to the lowest. When leg length and height were modelled simultaneously leg length remained associated with VTE risk (HR per 1 SD: 1.21 (1.04-1.40) while height was unrelated (HR per 1 SD: 1.00 (0.86-1.16). To conclude, participants with longer legs were at greater risk of incident VTE, and leg length explained the relation of height to VTE. It remains to be established whether this finding is due to greater venous surface area, a larger number of venous valves, or greater hydrostatic pressure among individuals with longer legs.
Keywords: Adult; Aged; Anthropometry; Body Height; Female; Follow-Up Studies; Humans; Leg; Male; Middle Aged; Population Groups; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

Patterns and predictors of recovery from exhaustion in older adults: the cardiovascular health study. - Whitson, Heather E; Thielke, Stephen; Diehr, Paula; O'Hare, Ann M; Chaves, Paulo H M; Zakai, Neil A; Arnold, Alice; Chaudhry, Sarwat; Ives, Diane; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To estimate the likelihood of, and factors associated with, recovery from exhaustion in older adults. DESIGN: Secondary analysis of a cohort study. SETTING: Six annual examinations in four U.S. communities. PARTICIPANTS: Four thousand five hundred eighty-four men and women aged 69 and older. MEASUREMENTS: Exhaustion was considered present when a participant responded "a moderate amount" or "most of the time" to either of two questions: "How often have you had a hard time getting going?" and "How often does everything seem an effort?" RESULTS: Of the 964 participants who originally reported exhaustion, 634 (65.8%) were exhaustion free at least once during follow-up. When data from all time points were considered, 48% of those who reported exhaustion were exhaustion free the following year. After adjustment for age, sex, race, education, and marital status, 1-year recovery was less likely in individuals with worse self-rated health and in those who were taking six or more medications or were obese, depressed, or had musculoskeletal pain or history of stroke. In proportional hazards models, the following risk factors were associated with more persistent exhaustion over 5 years: poor self-rated health, six or more medications, obesity, and depression. Recovery was not less likely in participants with a history of cancer or heart disease. CONCLUSION: Exhaustion is common in old age but is dynamic, even in those with a history of cancer and congestive heart failure. Recovery is especially likely in seniors who have a positive perception of their overall health, take few medications, and are not obese or depressed. These findings support the notion that resiliency is associated with physical and psychological well-being.
Keywords: Aged; Aging; Cardiovascular Physiological Phenomena; Exercise Test; Exercise Tolerance; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Predictive Value of Tests; Recovery of Function; Retrospective Studies; United States

A phenomics-based strategy identifies loci on APOC1, BRAP, and PLCG1 associated with metabolic syndrome phenotype domains. - Avery, Christy L; He, Qianchuan; North, Kari E; Ambite, José L; Boerwinkle, Eric; Fornage, Myriam; Hindorff, Lucia A; Kooperberg, Charles; Meigs, James B; Pankow, James S; Pendergrass, Sarah A; Psaty, Bruce M; et al. (PLoS Genet, 2011)
Despite evidence of the clustering of metabolic syndrome components, current approaches for identifying unifying genetic mechanisms typically evaluate clinical categories that do not provide adequate etiological information. Here, we used data from 19,486 European American and 6,287 African American Candidate Gene Association Resource Consortium participants to identify loci associated with the clustering of metabolic phenotypes. Six phenotype domains (atherogenic dyslipidemia, vascular dysfunction, vascular inflammation, pro-thrombotic state, central obesity, and elevated plasma glucose) encompassing 19 quantitative traits were examined. Principal components analysis was used to reduce the dimension of each domain such that >55% of the trait variance was represented within each domain. We then applied a statistically efficient and computational feasible multivariate approach that related eight principal components from the six domains to 250,000 imputed SNPs using an additive genetic model and including demographic covariates. In European Americans, we identified 606 genome-wide significant SNPs representing 19 loci. Many of these loci were associated with only one trait domain, were consistent with results in African Americans, and overlapped with published findings, for instance central obesity and FTO. However, our approach, which is applicable to any set of interval scale traits that is heritable and exhibits evidence of phenotypic clustering, identified three new loci in or near APOC1, BRAP, and PLCG1, which were associated with multiple phenotype domains. These pleiotropic loci may help characterize metabolic dysregulation and identify targets for intervention.
Keywords: African Americans; Apolipoprotein C-I; Blood Glucose; Dyslipidemias; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Humans; Metabolic Syndrome; Obesity, Abdominal; Phenotype; Phospholipase C gamma; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Ubiquitin-Protein Ligases; Vascular Diseases

The relationship between serum markers of collagen turnover and cardiovascular outcome in the elderly: the Cardiovascular Health Study. - Barasch, Eddy; Gottdiener, John S; Aurigemma, Gerard; Kitzman, Dalane W; Han, Jing; Kop, Willem J; Tracy, Russell P (Circ Heart Fail, 2011)
BACKGROUND: The deposition of collagen fibrils in the myocardial extracellular matrix increases with age and plays a key role in the pathophysiology of heart failure (HF). We sought to determine the predictive value of serum markers of collagen turnover for incident HF and cardiovascular (CV) morbidity, mortality, and all-cause mortality in elderly individuals. METHODS AND RESULTS: In 880 participants in the Cardiovascular Health Study (mean age, 77±6 years; 48% women), serum levels of carboxyl-terminal peptide of procollagen type I (PIP), carboxyl-terminal telopeptide of collagen type I (CITP), and amino-terminal peptide of procollagen type III (PIIINP) were measured in 4 groups: HF with reduced ejection fraction (HFREF; n=146, EF <55%); HF with preserved EF (HFPEF; n=175, EF ≥55%), control subjects with CV risk factors but not HF (CVD; n=280), and healthy control subjects free of CV disease (n=279). Relationships between these serum markers and outcome at follow-up of 12±4 years (range, 3-17 years) was determined in six models including those adjusted for conventional risk factors, renal function, NT-proBNP and agents which interfere with collagen synthesis. For the entire cohort, in unadjusted and adjusted models, both PIIINP and CITP were associated with myocardial infarction, incident HF, hospitalization for HF, cardiovascular and all-cause mortality. In healthy control subjects, CITP and PIIINP were associated with all-cause death. In control subjects with risk factors, CITP was associated with incident HF, and in participants with HFPEF, CITP was associated with hospitalization for HF. No collagen biomarker was associated with outcome in participants with HFREF, and PIP was not associated with outcome in the cohort or its subgroups. CONCLUSIONS: In both healthy and elderly individuals with CV disease at risk of developing HF, CITP and PIIINP are significantly associated with multiple adverse cardiac outcomes including myocardial infarction, HF, and death. Clinical Trial Registration- URL: http://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Collagen; Collagen Type I; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Peptide Fragments; Peptides; Predictive Value of Tests; Procollagen; Prospective Studies; Stroke Volume; Survival Rate

The risk of Parkinson disease associated with urate in a community-based cohort of older adults. - Jain, S; Ton, T G; Boudreau, R M; Yang, M; Thacker, E L; Studenski, S; Longstreth, W T; Strotmeyer, E S; Newman, A B (Neuroepidemiology, 2011)
BACKGROUND/AIMS: Studies suggest an inverse association between urate concentration and the risk of Parkinson disease (PD). We investigated this in the Cardiovascular Health Study in an elderly community-based cohort of adults. METHODS: The association of baseline urate (µmol/l) and incident PD over 14 years was assessed with locally weighted scatterplot smoothing (LOESS) regression from which categories of low (<300 µmol/l), middle (300-500 µmol/l), and high (>500 µmol/l) urate ranges were derived. Multivariate logistic regression models assessed the risk of PD for each urate range. Linear and quadratic terms were tested when modeling the association between urate and the risk of PD. RESULTS: Women had significantly lower urate concentrations than did men [316.8 µmol/l (SD 88.0) vs. 367.4 µmol/l (SD 87.7), p < 0.0001] and in women no associations between urate and PD risk were observed. In men, LOESS curves suggested a U-shaped or threshold effect between urate and PD risk. With the middle range as reference, the risk of developing PD was significantly increased for urate <300 µmol/l (OR 1.69, 95% CI 1.03-2.78) but not for urate >500 µmol/l (OR 1.55, 95% CI 0.72-3.32) in men. A negative linear term was significant for urate <500 µmol/l, and across the entire range a convex quadratic term was significant. CONCLUSIONS: Results suggest a more complex relationship than previously reported between urate levels and the risk of PD in men. Low urate concentrations were associated with a higher PD risk and high urate concentrations were not associated with a further decrease in PD risk.
Keywords: Aged; California; Cohort Studies; Female; Humans; Male; Maryland; North Carolina; Parkinson Disease; Pennsylvania; Prospective Studies; Risk Factors; Sex Distribution; Sex Factors; Uric Acid

Separate and combined associations of body-mass index and abdominal adiposity with cardiovascular disease: collaborative analysis of 58 prospective studies. - Wormser, David; Kaptoge, Stephen; Di Angelantonio, Emanuele; Wood, Angela M; Pennells, Lisa; Thompson, Alex; Sarwar, Nadeem; Kizer, Jorge R; Lawlor, Debbie A; Nordestgaard, Børge G; Ridker, Paul; Salomaa, Veikko; et al. (Lancet, 2011)
BACKGROUND: Guidelines differ about the value of assessment of adiposity measures for cardiovascular disease risk prediction when information is available for other risk factors. We studied the separate and combined associations of body-mass index (BMI), waist circumference, and waist-to-hip ratio with risk of first-onset cardiovascular disease. METHODS: We used individual records from 58 cohorts to calculate hazard ratios (HRs) per 1 SD higher baseline values (4.56 kg/m(2) higher BMI, 12.6 cm higher waist circumference, and 0.083 higher waist-to-hip ratio) and measures of risk discrimination and reclassification. Serial adiposity assessments were used to calculate regression dilution ratios. RESULTS: Individual records were available for 221,934 people in 17 countries (14,297 incident cardiovascular disease outcomes; 1.87 million person-years at risk). Serial adiposity assessments were made in up to 63,821 people (mean interval 5.7 years [SD 3.9]). In people with BMI of 20 kg/m(2) or higher, HRs for cardiovascular disease were 1.23 (95% CI 1.17-1.29) with BMI, 1.27 (1.20-1.33) with waist circumference, and 1.25 (1.19-1.31) with waist-to-hip ratio, after adjustment for age, sex, and smoking status. After further adjustment for baseline systolic blood pressure, history of diabetes, and total and HDL cholesterol, corresponding HRs were 1.07 (1.03-1.11) with BMI, 1.10 (1.05-1.14) with waist circumference, and 1.12 (1.08-1.15) with waist-to-hip ratio. Addition of information on BMI, waist circumference, or waist-to-hip ratio to a cardiovascular disease risk prediction model containing conventional risk factors did not importantly improve risk discrimination (C-index changes of -0.0001, -0.0001, and 0.0008, respectively), nor classification of participants to categories of predicted 10-year risk (net reclassification improvement -0.19%, -0.05%, and -0.05%, respectively). Findings were similar when adiposity measures were considered in combination. Reproducibility was greater for BMI (regression dilution ratio 0.95, 95% CI 0.93-0.97) than for waist circumference (0.86, 0.83-0.89) or waist-to-hip ratio (0.63, 0.57-0.70). INTERPRETATION: BMI, waist circumference, and waist-to-hip ratio, whether assessed singly or in combination, do not importantly improve cardiovascular disease risk prediction in people in developed countries when additional information is available for systolic blood pressure, history of diabetes, and lipids. FUNDING: British Heart Foundation and UK Medical Research Council.
Keywords: Age Factors; Blood Pressure; Body Mass Index; Cardiovascular Diseases; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Middle Aged; Obesity, Abdominal; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Factors; Smoking; Systole; Waist Circumference; Waist-Hip Ratio

Serum 25-hydroxyvitamin D and physical function in older adults: the Cardiovascular Health Study All Stars. - Houston, Denise K; Tooze, Janet A; Davis, Cralen C; Chaves, Paulo H M; Hirsch, Calvin H; Robbins, John A; Arnold, Alice M; Newman, Anne B; Kritchevsky, Stephen B (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine the association between 25-hydroxyvitamin D (25(OH)D) and physical function in adults of advanced age. DESIGN: Cross-sectional and longitudinal analysis of physical function over 3 years of follow-up in the Cardiovascular Health Study All Stars. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Community-dwelling adults aged 77 to 100 (N = 988). MEASUREMENTS: Serum 25-hydroxyvitamin D 25(OH)D), Short Physical Performance Battery (SPPB), and grip and knee extensor strength assessed at baseline. Mobility disability (difficulty walking half a mile or up 10 steps) and activities of daily living (ADLs) disability were assessed at baseline and every 6 months over 3 years of follow-up. RESULTS: Almost one-third (30.8%) of participants were deficient in 25(OH)D (<20 ng/mL). SPPB scores were lower in those with deficient 25(OH)D (mean (standard error) 6.53 (0.24)) than in those with sufficient 25(OH)D (≥30 ng/mL) (7.15 (0.25)) after adjusting for sociodemographic characteristics, season, health behaviors, and chronic conditions (P = .006). Grip strength adjusted for body size was also lower in those with deficient 25(OH)D than in those with sufficient 25(OH)D (24.7 (0.6) kg vs 26.0 (0.6) kg, P = .02). Participants with deficient 25(OH)D were more likely to have prevalent mobility (OR = 1.44, 95% confidence interval (CI)) = 0.96-2.14) and ADL disability (OR = 1.51, 95% CI = 1.01-2.25) at baseline than those with sufficient 25(OH)D. Furthermore, participants with deficient 25(OH)D were at greater risk of incident mobility disability over 3 years of follow-up (hazard ratio = 1.56, 95% CI = 1.06-2.30). CONCLUSION: Vitamin D deficiency was common and was associated with poorer physical performance, lower muscle strength, and prevalent mobility and ADL disability in community-dwelling older adults. Moreover, vitamin D deficiency predicted incident mobility disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Female; Follow-Up Studies; Geriatric Assessment; Health Surveys; Humans; Male; Mobility Limitation; Muscle Strength; Physical Fitness; Proportional Hazards Models; Reference Values; United States; Vitamin D; Vitamin D Deficiency

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Age and association of kidney measures with mortality and end-stage renal disease. - Hallan, Stein I; Matsushita, Kunihiro; Sang, Yingying; Mahmoodi, Bakhtawar K; Black, Corri; Ishani, Areef; Kleefstra, Nanne; Naimark, David; Roderick, Paul; Tonelli, Marcello; Wetzels, Jack F M; Astor, Brad C; et al. (JAMA, 2012)
CONTEXT: Chronic kidney disease (CKD) is prevalent in older individuals, but the risk implications of low estimated glomerular filtration rate (eGFR) and high albuminuria across the full age range are controversial. OBJECTIVE: To evaluate possible effect modification (interaction) by age of the association of eGFR and albuminuria with clinical risk, examining both relative and absolute risks. DESIGN, SETTING, AND PARTICIPANTS: Individual-level meta-analysis including 2,051,244 participants from 33 general population or high-risk (of vascular disease) cohorts and 13 CKD cohorts from Asia, Australasia, Europe, and North/South America, conducted in 1972-2011 with a mean follow-up time of 5.8 years (range, 0-31 years). MAIN OUTCOME MEASURES: Hazard ratios (HRs) of mortality and end-stage renal disease (ESRD) according to eGFR and albuminuria were meta-analyzed across age categories after adjusting for sex, race, cardiovascular disease, diabetes, systolic blood pressure, cholesterol, body mass index, and smoking. Absolute risks were estimated using HRs and average incidence rates. RESULTS: Mortality (112,325 deaths) and ESRD (8411 events) risks were higher at lower eGFR and higher albuminuria in every age category. In general and high-risk cohorts, relative mortality risk for reduced eGFR decreased with increasing age; eg, adjusted HRs at an eGFR of 45 mL/min/1.73 m2 vs 80 mL/min/1.73 m2 were 3.50 (95% CI, 2.55-4.81), 2.21 (95% CI, 2.02-2.41), 1.59 (95% CI, 1.42-1.77), and 1.35 (95% CI, 1.23-1.48) in age categories 18-54, 55-64, 65-74, and ≥75 years, respectively (P <.05 for age interaction). Absolute risk differences for the same comparisons were higher at older age (9.0 [95% CI, 6.0-12.8], 12.2 [95% CI, 10.3-14.3], 13.3 [95% CI, 9.0-18.6], and 27.2 [95% CI, 13.5-45.5] excess deaths per 1000 person-years, respectively). For increased albuminuria, reduction of relative risk with increasing age was less evident, while differences in absolute risk were higher in older age categories (7.5 [95% CI, 4.3-11.9], 12.2 [95% CI, 7.9-17.6], 22.7 [95% CI, 15.3-31.6], and 34.3 [95% CI, 19.5-52.4] excess deaths per 1000 person-years, respectively by age category, at an albumin-creatinine ratio of 300 mg/g vs 10 mg/g). In CKD cohorts, adjusted relative hazards of mortality did not decrease with age. In all cohorts, ESRD relative risks and absolute risk differences at lower eGFR or higher albuminuria were comparable across age categories. CONCLUSIONS: Both low eGFR and high albuminuria were independently associated with mortality and ESRD regardless of age across a wide range of populations. Mortality showed lower relative risk but higher absolute risk differences at older age.
Keywords: Adolescent; Adult; Age Factors; Aged; Albuminuria; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Risk; Young Adult

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis. - Fox, Caroline S; Matsushita, Kunihiro; Woodward, Mark; Bilo, Henk J G; Chalmers, John; Heerspink, Hiddo J Lambers; Lee, Brian J; Perkins, Robert M; Rossing, Peter; Sairenchi, Toshimi; Tonelli, Marcello; Vassalotti, Joseph A; et al. (Lancet, 2012)
BACKGROUND: Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. METHODS: We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-stage renal disease (ESRD) associated with eGFR and albuminuria in individuals with and without diabetes. FINDINGS: We analysed data for 1,024,977 participants (128,505 with diabetes) from 30 general population and high-risk cardiovascular cohorts and 13 chronic kidney disease cohorts. In the combined general population and high-risk cohorts with data for all-cause mortality, 75,306 deaths occurred during a mean follow-up of 8·5 years (SD 5·0). In the 23 studies with data for cardiovascular mortality, 21,237 deaths occurred from cardiovascular disease during a mean follow-up of 9·2 years (SD 4·9). In the general and high-risk cohorts, mortality risks were 1·2-1·9 times higher for participants with diabetes than for those without diabetes across the ranges of eGFR and albumin-to-creatinine ratio (ACR). With fixed eGFR and ACR reference points in the diabetes and no diabetes groups, HR of mortality outcomes according to lower eGFR and higher ACR were much the same in participants with and without diabetes (eg, for all-cause mortality at eGFR 45 mL/min per 1·73 m(2) [vs 95 mL/min per 1·73 m(2)], HR 1·35; 95% CI 1·18-1·55; vs 1·33; 1·19-1·48 and at ACR 30 mg/g [vs 5 mg/g], 1·50; 1·35-1·65 vs 1·52; 1·38-1·67). The overall interactions were not significant. We identified much the same findings for ESRD in the chronic kidney disease cohorts. INTERPRETATION: Despite higher risks for mortality and ESRD in diabetes, the relative risks of these outcomes by eGFR and ACR are much the same irrespective of the presence or absence of diabetes, emphasising the importance of kidney disease as a predictor of clinical outcomes. FUNDING: US National Kidney Foundation.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Cause of Death; Diabetic Nephropathies; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Risk Factors

Associations of total and high-molecular-weight adiponectin with all-cause and cardiovascular mortality in older persons: the Cardiovascular Health Study. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Mantzoros, Christos S; deFilippi, Christopher R; Newman, Anne B; Djoussé, Luc (Circulation, 2012)
BACKGROUND: Adiponectin shows opposite associations with adverse outcomes in healthy middle-aged populations (lower risk) and cohorts with prevalent cardiovascular disease, heart failure, or advanced age (higher risk). METHODS AND RESULTS: In a population-based study of older adults, we examined the relationships of total and high-molecular-weight adiponectin with mortality among subgroups defined by baseline cardiovascular status: No cardiovascular disease, heart failure, or atrial fibrillation (group 1); cardiovascular disease but no heart failure/atrial fibrillation (group 2); and heart failure/atrial fibrillation (group 3). We found significant differences in the associations with all-cause mortality across the groups. The association in group 1 was U-shaped; increasing levels of total adiponectin up to 12.4 mg/L were associated with lower mortality after adjustment for confounders (hazard ratio=0.81 per 1 SD [95% confidence interval, 0.65-0.95]), but above this cut point, higher levels conferred greater risk (hazard ratio=1.19 [95% confidence interval, 1.12-1.27]). Further adjustment for diabetes mellitus or insulin resistance, protection against which has been proposed to mediate the beneficial relationships of adiponectin with outcome, attenuated the association in the lower range. There was no significant association in group 2, but in group 3, total adiponectin showed a direct adjusted association. Additional adjustment for putative metabolic/inflammatory intermediates suggested a direct association for group 2, and magnified the one for group 3 (hazard ratio=1.31 [1.15-1.50]). Results were similar for high-molecular-weight adiponectin and for cardiovascular mortality. CONCLUSIONS: Adiponectin exhibits distinct associations with mortality in elders, which shift from U-shaped to flat to direct with greater baseline cardiovascular dysfunction but become more consistently adverse after accounting for metabolic/inflammatory factors presumed to be favorably regulated by the adipokine. These findings advance understanding of the adiponectin paradox as it relates to older adults.
Keywords: Adiponectin; Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Female; Health Surveys; Humans; Male; Molecular Weight

Cardiovascular physiology in premotor Parkinson's disease: a neuroepidemiologic study. - Jain, Samay; Ton, Thanh G; Perera, Subashan; Zheng, Yan; Stein, Phyllis K; Thacker, Evan; Strotmeyer, Elsa S; Newman, Anne B; Longstreth, Will T (Mov Disord, 2012)
Changes in cardiovascular physiology in Parkinson's disease (PD) are common and may occur prior to diagnostic parkinsonian motor signs. We investigated associations of electrocardiographic (ECG) abnormalities, orthostasis, heart rate variability, and carotid stenosis with the risk of PD diagnosis in the Cardiovascular Health Study, a community-based cohort of older adults. ECG abnormality, orthostasis (symptomatic or asymptomatic), heart rate variability (24-hour Holter monitoring), and any carotid stenosis (≥1%) by ultrasound were modeled as primary predictors of incident PD diagnosis using multivariable logistic regression. Incident PD cases were identified by at least 1 of the following: self-report, antiparkinsonian medication use, and ICD-9. If unadjusted models were significant, they were adjusted or stratified by age, sex, and smoking status, and those in which predictors were still significant (P ≤ .05) were also adjusted for race, diabetes, total cholesterol, low-density lipoprotein, blood pressure, body mass index, physical activity, education level, stroke, and C-reactive protein. Of 5888 participants, 154 incident PD cases were identified over 14 years of follow-up. After adjusting models with all covariates, those with any ECG abnormality (odds ratio [OR], 1.45; 95% CI, 1.02-2.07; P = .04) or any carotid stenosis (OR, 2.40; 95% CI, 1.40-4.09; P = .001) at baseline had a higher risk of incident PD diagnosis. Orthostasis and heart rate variability were not significant predictors. This exploratory study suggests that carotid stenosis and ECG abnormalities occur prior to motor signs in PD, thus serving as potential premotor features or risk factors for PD diagnosis. Replication is needed in a population with more thorough ascertainment of PD onset.
Keywords: Aged; Antiparkinson Agents; Cardiovascular Physiological Phenomena; Carotid Stenosis; Cohort Studies; Data Interpretation, Statistical; Dizziness; Electrocardiography; Female; Heart Rate; Hospitalization; Humans; Longitudinal Studies; Male; Movement Disorders; Neurologic Examination; Parkinson Disease; Risk; Ultrasonography

Carotid intima-media thickness progression to predict cardiovascular events in the general population (the PROG-IMT collaborative project): a meta-analysis of individual participant data. - Lorenz, Matthias W; Polak, Joseph F; Kavousi, Maryam; Mathiesen, Ellisiv B; Völzke, Henry; Tuomainen, Tomi-Pekka; Sander, Dirk; Plichart, Matthieu; Catapano, Alberico L; Robertson, Christine M; Kiechl, Stefan; Rundek, Tatjana; et al. (Lancet, 2012)
BACKGROUND: Carotid intima-media thickness (cIMT) is related to the risk of cardiovascular events in the general population. An association between changes in cIMT and cardiovascular risk is frequently assumed but has rarely been reported. Our aim was to test this association. METHODS: We identified general population studies that assessed cIMT at least twice and followed up participants for myocardial infarction, stroke, or death. The study teams collaborated in an individual participant data meta-analysis. Excluding individuals with previous myocardial infarction or stroke, we assessed the association between cIMT progression and the risk of cardiovascular events (myocardial infarction, stroke, vascular death, or a combination of these) for each study with Cox regression. The log hazard ratios (HRs) per SD difference were pooled by random effects meta-analysis. FINDINGS: Of 21 eligible studies, 16 with 36,984 participants were included. During a mean follow-up of 7·0 years, 1519 myocardial infarctions, 1339 strokes, and 2028 combined endpoints (myocardial infarction, stroke, vascular death) occurred. Yearly cIMT progression was derived from two ultrasound visits 2-7 years (median 4 years) apart. For mean common carotid artery intima-media thickness progression, the overall HR of the combined endpoint was 0·97 (95% CI 0·94-1·00) when adjusted for age, sex, and mean common carotid artery intima-media thickness, and 0·98 (0·95-1·01) when also adjusted for vascular risk factors. Although we detected no associations with cIMT progression in sensitivity analyses, the mean cIMT of the two ultrasound scans was positively and robustly associated with cardiovascular risk (HR for the combined endpoint 1·16, 95% CI 1·10-1·22, adjusted for age, sex, mean common carotid artery intima-media thickness progression, and vascular risk factors). In three studies including 3439 participants who had four ultrasound scans, cIMT progression did not correlate between occassions (reproducibility correlations between r=-0·06 and r=-0·02). INTERPRETATION: The association between cIMT progression assessed from two ultrasound scans and cardiovascular risk in the general population remains unproven. No conclusion can be derived for the use of cIMT progression as a surrogate in clinical trials. FUNDING: Deutsche Forschungsgemeinschaft.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Disease Progression; Follow-Up Studies; Humans; Myocardial Infarction; Prognosis; Risk Assessment; Stroke

Classification algorithms for predicting sleepiness and sleep apnea severity. - Eiseman, Nathaniel A; Westover, M Brandon; Mietus, Joseph E; Thomas, Robert J; Bianchi, Matt T (J Sleep Res, 2012)
Identifying predictors of subjective sleepiness and severity of sleep apnea are important yet challenging goals in sleep medicine. Classification algorithms may provide insights, especially when large data sets are available. We analyzed polysomnography and clinical features available from the Sleep Heart Health Study. The Epworth Sleepiness Scale and the apnea-hypopnea index were the targets of three classifiers: k-nearest neighbor, naive Bayes and support vector machine algorithms. Classification was based on up to 26 features including demographics, polysomnogram, and electrocardiogram (spectrogram). Naive Bayes was best for predicting abnormal Epworth class (0-10 versus 11-24), although prediction was weak: polysomnogram features had 16.7% sensitivity and 88.8% specificity; spectrogram features had 5.3% sensitivity and 96.5% specificity. The support vector machine performed similarly to naive Bayes for predicting sleep apnea class (0-5 versus >5): 59.0% sensitivity and 74.5% specificity using clinical features and 43.4% sensitivity and 83.5% specificity using spectrographic features compared with the naive Bayes classifier, which had 57.5% sensitivity and 73.7% specificity (clinical), and 39.0% sensitivity and 82.7% specificity (spectrogram). Mutual information analysis confirmed the minimal dependency of the Epworth score on any feature, while the apnea-hypopnea index showed modest dependency on body mass index, arousal index, oxygenation and spectrogram features. Apnea classification was modestly accurate, using either clinical or spectrogram features, and showed lower sensitivity and higher specificity than common sleep apnea screening tools. Thus, clinical prediction of sleep apnea may be feasible with easily obtained demographic and electrocardiographic analysis, but the utility of the Epworth is questioned by its minimal relation to clinical, electrocardiographic, or polysomnographic features.
Keywords: Adult; Algorithms; Disorders of Excessive Somnolence; Electrocardiography; Humans; Polysomnography; Prognosis; Psychometrics; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea, Obstructive; Sleep Stages

Common folate gene variant, MTHFR C677T, is associated with brain structure in two independent cohorts of people with mild cognitive impairment. - Rajagopalan, Priya; Jahanshad, Neda; Stein, Jason L; Hua, Xue; Madsen, Sarah K; Kohannim, Omid; Hibar, Derrek P; Toga, Arthur W; Jack, Clifford R; Saykin, Andrew J; Green, Robert C; Weiner, Michael W; et al. (Neuroimage Clin, 2012)
A commonly carried C677T polymorphism in a folate-related gene, MTHFR, is associated with higher plasma homocysteine, a well-known mediator of neuronal damage and brain atrophy. As homocysteine promotes brain atrophy, we set out to discover whether people carrying the C677T MTHFR polymorphism which increases homocysteine, might also show systematic differences in brain structure. Using tensor-based morphometry, we tested this association in 359 elderly Caucasian subjects with mild cognitive impairment (MCI) (mean age: 75 ± 7.1 years) scanned with brain MRI and genotyped as part of Alzheimer's Disease Neuroimaging Initiative. We carried out a replication study in an independent, non-overlapping sample of 51 elderly Caucasian subjects with MCI (mean age: 76 ± 5.5 years), scanned with brain MRI and genotyped for MTHFR, as part of the Cardiovascular Health Study. At each voxel in the brain, we tested to see where regional volume differences were associated with carrying one or more MTHFR 'T' alleles. In ADNI subjects, carriers of the MTHFR risk allele had detectable brain volume deficits, in the white matter, of up to 2-8% per risk T allele locally at baseline and showed accelerated brain atrophy of 0.5-1.5% per T allele at 1 year follow-up, after adjusting for age and sex. We replicated these brain volume deficits of up to 5-12% per MTHFR T allele in the independent cohort of CHS subjects. As expected, the associations weakened after controlling for homocysteine levels, which the risk gene affects. The MTHFR risk variant may thus promote brain atrophy by elevating homocysteine levels. This study aims to investigate the spatially detailed effects of this MTHFR polymorphism on brain structure in 3D, pointing to a causal pathway that may promote homocysteine-mediated brain atrophy in elderly people with MCI.

Comparing years of healthy life, measured in 16 ways, for normal weight and overweight older adults. - Diehr, Paula; Thielke, Stephen; O'Meara, Ellen; Fitzpatrick, Annette L; Newman, Anne (J Obes, 2012)
Introduction. The traditional definitions of overweight and obesity are not age specific, even though the relationship of weight to mortality is different for older adults. Effects of adiposity on aspects of health beside mortality have not been well investigated. Methods. We calculated the number of years of healthy life (YHL) in the 10 years after baseline, for 5,747 older adults. YHL was defined in 16 different ways. We compared Normal and Overweight persons, classified either by body mass index (BMI) or by waist circumference (WC). Findings. YHL for Normal and Overweight persons differed significantly in 25% of the comparisons, of which half favored the Overweight. Measures of physical health favored Normal weight, while measures of mental health and quality of life favored Overweight. Overweight was less favorable when defined by WC than by BMI. Obese persons usually had worse outcomes. Discussion. Overweight older adults averaged as many years of life and years of healthy life as those of Normal weight. There may be no outcome based reason to distinguish Normal from Overweight for older adults. Conclusion. The "Overweight paradox" appears to hold for nonmortality outcomes. New adiposity standards are needed for older adults, possibly different by race and sex.

Comparison of risk prediction using the CKD-EPI equation and the MDRD study equation for estimated glomerular filtration rate. - Matsushita, Kunihiro; Mahmoodi, Bakhtawar K; Woodward, Mark; Emberson, Jonathan R; Jafar, Tazeen H; Jee, Sun Ha; Polkinghorne, Kevan R; Shankar, Anoop; Smith, David H; Tonelli, Marcello; Warnock, David G; Wen, Chi-Pang; et al. (JAMA, 2012)
CONTEXT: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation more accurately estimates glomerular filtration rate (GFR) than the Modification of Diet in Renal Disease (MDRD) Study equation using the same variables, especially at higher GFR, but definitive evidence of its risk implications in diverse settings is lacking. OBJECTIVE: To evaluate risk implications of estimated GFR using the CKD-EPI equation compared with the MDRD Study equation in populations with a broad range of demographic and clinical characteristics. DESIGN, SETTING, AND PARTICIPANTS: A meta-analysis of data from 1.1 million adults (aged ≥ 18 years) from 25 general population cohorts, 7 high-risk cohorts (of vascular disease), and 13 CKD cohorts. Data transfer and analyses were conducted between March 2011 and March 2012. MAIN OUTCOME MEASURES: All-cause mortality (84,482 deaths from 40 cohorts), cardiovascular mortality (22,176 events from 28 cohorts), and end-stage renal disease (ESRD) (7644 events from 21 cohorts) during 9.4 million person-years of follow-up; the median of mean follow-up time across cohorts was 7.4 years (interquartile range, 4.2-10.5 years). RESULTS: Estimated GFR was classified into 6 categories (≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m(2)) by both equations. Compared with the MDRD Study equation, 24.4% and 0.6% of participants from general population cohorts were reclassified to a higher and lower estimated GFR category, respectively, by the CKD-EPI equation, and the prevalence of CKD stages 3 to 5 (estimated GFR <60 mL/min/1.73 m(2)) was reduced from 8.7% to 6.3%. In estimated GFR of 45 to 59 mL/min/1.73 m(2) by the MDRD Study equation, 34.7% of participants were reclassified to estimated GFR of 60 to 89 mL/min/1.73 m(2) by the CKD-EPI equation and had lower incidence rates (per 1000 person-years) for the outcomes of interest (9.9 vs 34.5 for all-cause mortality, 2.7 vs 13.0 for cardiovascular mortality, and 0.5 vs 0.8 for ESRD) compared with those not reclassified. The corresponding adjusted hazard ratios were 0.80 (95% CI, 0.74-0.86) for all-cause mortality, 0.73 (95% CI, 0.65-0.82) for cardiovascular mortality, and 0.49 (95% CI, 0.27-0.88) for ESRD. Similar findings were observed in other estimated GFR categories by the MDRD Study equation. Net reclassification improvement based on estimated GFR categories was significantly positive for all outcomes (range, 0.06-0.13; all P < .001). Net reclassification improvement was similarly positive in most subgroups defined by age (<65 years and ≥65 years), sex, race/ethnicity (white, Asian, and black), and presence or absence of diabetes and hypertension. The results in the high-risk and CKD cohorts were largely consistent with the general population cohorts. CONCLUSION: The CKD-EPI equation classified fewer individuals as having CKD and more accurately categorized the risk for mortality and ESRD than did the MDRD Study equation across a broad range of populations.
Keywords: African Continental Ancestry Group; Aged; Algorithms; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Decision Support Techniques; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Models, Theoretical; Risk Assessment; Sex Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Evolution and functional impact of rare coding variation from deep sequencing of human exomes. - Tennessen, Jacob A; Bigham, Abigail W; O'Connor, Timothy D; Fu, Wenqing; Kenny, Eimear E; Gravel, Simon; McGee, Sean; Do, Ron; Liu, Xiaoming; Jun, Goo; Kang, Hyun Min; Jordan, Daniel; et al. (Science, 2012)
As a first step toward understanding how rare variants contribute to risk for complex diseases, we sequenced 15,585 human protein-coding genes to an average median depth of 111× in 2440 individuals of European (n = 1351) and African (n = 1088) ancestry. We identified over 500,000 single-nucleotide variants (SNVs), the majority of which were rare (86% with a minor allele frequency less than 0.5%), previously unknown (82%), and population-specific (82%). On average, 2.3% of the 13,595 SNVs each person carried were predicted to affect protein function of ~313 genes per genome, and ~95.7% of SNVs predicted to be functionally important were rare. This excess of rare functional variants is due to the combined effects of explosive, recent accelerated population growth and weak purifying selection. Furthermore, we show that large sample sizes will be required to associate rare variants with complex traits.
Keywords: African Americans; Disease; European Continental Ancestry Group; Evolution, Molecular; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Polymorphism, Single Nucleotide; Population Growth; Selection, Genetic

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genetic variants and associations of 25-hydroxyvitamin D concentrations with major clinical outcomes. - Levin, Gregory P; Robinson-Cohen, Cassianne; de Boer, Ian H; Houston, Denise K; Lohman, Kurt; Liu, Yongmei; Kritchevsky, Stephen B; Cauley, Jane A; Tanaka, Toshiko; Ferrucci, Luigi; Bandinelli, Stefania; Patel, Kushang V; et al. (JAMA, 2012)
CONTEXT: Lower serum 25-hydroxyvitamin D concentrations are associated with greater risks of many chronic diseases across large, prospective community-based studies. Substrate 25-hydroxyvitamin D must be converted to 1,25-dihydroxyvitamin D for full biological activity, and complex metabolic pathways suggest that interindividual variability in vitamin D metabolism may alter the clinical consequences of measured serum 25-hydroxyvitamin D. OBJECTIVE: To investigate whether common variation within genes encoding the vitamin D-binding protein, megalin, cubilin, CYP27B1, CYP24A1, and the vitamin D receptor (VDR) modify associations of low 25-hydroxyvitamin D with major clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS: Examination of 141 single-nucleotide polymorphisms in a discovery cohort of 1514 white participants (who were recruited from 4 US regions) from the community-based Cardiovascular Health Study. Participants had serum 25-hydroxyvitamin D measurements in 1992-1993 and were followed up for a median of 11 years (through 2006). Replication meta-analyses were conducted across the independent, community-based US Health, Aging, and Body Composition (n = 922; follow-up: 1998-1999 through 2005), Italian Invecchiare in Chianti (n = 835; follow-up: 1998-2000 through 2006), and Swedish Uppsala Longitudinal Study of Adult Men (n = 970; follow-up: 1991-1995 through 2008) cohort studies. MAIN OUTCOME MEASURE: Composite outcome of incident hip facture, myocardial infarction, cancer, and mortality over long-term follow-up. RESULTS: Interactions between 5 single-nucleotide polymorphisms and low 25-hydroxyvitamin D concentration were identified in the discovery phase and 1 involving a variant in the VDR gene replicated in independent meta-analysis. Among Cardiovascular Health Study participants, low 25-hydroxyvitamin D concentration was associated with hazard ratios for risk of the composite outcome of 1.40 (95% CI, 1.12-1.74) for those who had 1 minor allele at rs7968585 and 1.82 (95% CI, 1.31-2.54) for those with 2 minor alleles at rs7968585. In contrast, there was no evidence of an association (estimated hazard ratio, 0.93 [95% CI, 0.70-1.24]) among participants who had 0 minor alleles at this single-nucleotide polymorphism. CONCLUSION: Known associations of low 25-hydroxyvitamin D with major health outcomes may vary according to common genetic differences in the vitamin D receptor.
Keywords: 25-Hydroxyvitamin D3 1-alpha-Hydroxylase; Aged; Chronic Disease; Cohort Studies; Female; Genetic Variation; Genotype; Hip Fractures; Humans; Low Density Lipoprotein Receptor-Related Protein-2; Male; Meta-Analysis as Topic; Myocardial Infarction; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Calcitriol; Receptors, Cell Surface; Risk; Steroid Hydroxylases; Vitamin D; Vitamin D3 24-Hydroxylase

Genetic variants in Arhgef11 are associated with kidney injury in the Dahl salt-sensitive rat. - Williams, Jan M; Johnson, Ashley C; Stelloh, Cary; Dreisbach, Albert W; Franceschini, Nora; Regner, Kevin R; Townsend, Raymond R; Roman, Richard J; Garrett, Michael R (Hypertension, 2012)
A previous genetic analysis comparing the Dahl salt-sensitive (S) rat with the spontaneously hypertensive rat identified a major locus on chromosome 2 that influences proteinuria in the S rat. In the present study, blood pressure, proteinuria, and renal hemodynamics were evaluated in congenic strains with small segments of the protective spontaneously hypertensive rat genome on the S background. Proteinuria and renal function were significantly improved in the congenic strains compared with the S. The causative locus interval was narrowed to <375 kb on the basis of congenic strains, haplotype data, comparative mapping, and concordance with human genetic studies. Sequencing of the coding region of genes in this region identified 36 single nucleotide polymorphisms (13 nonsynonymous and 23 synonymous). Gene expression profiling indicated that only a few genes exhibited differential expression. Arhgef11, Pear1, and Sh2d2 were identified as important candidate genes that may be linked to kidney injury in the S rat. In particular, Arhgef11 plays an important role in the activation of the Rho-ROCK signaling pathway. Inhibition of this pathway using fasudil resulted in a significant reduction of proteinuria in treated S rats (compared with untreated S). However, no difference was observed between treated or untreated spontaneously hypertensive rat or congenic strains. The homologous region in humans was found to be associated with estimated glomerular filtration rate in the Candidate Gene Association Resource population. In summary, these findings demonstrate that allelic variants in Arhgef11, acting through the Rho-ROCK pathway, could influence kidney injury in the S as well as provide insight into human kidney disease.
Keywords: 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; Animals; Animals, Congenic; Blood Pressure; Blotting, Western; Chromosome Mapping; Gene Expression Profiling; Genetic Predisposition to Disease; Guanine Nucleotide Exchange Factors; Humans; Kidney; Kidney Diseases; Male; Polymorphism, Single Nucleotide; Protein Kinase Inhibitors; Proteinuria; Quantitative Trait Loci; Rats; Rats, Inbred Dahl; Rats, Inbred SHR; Renal Circulation; Reverse Transcriptase Polymerase Chain Reaction; rho-Associated Kinases; rhoA GTP-Binding Protein; Signal Transduction

Genetic variation in F3 (tissue factor) and the risk of incident venous thrombosis: meta-analysis of eight studies. - Smith, N L; Heit, J A; Tang, W; Teichert, M; Chasman, D I; Morange, P-E (J Thromb Haemost, 2012)
Keywords: Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Regression Analysis; Risk Assessment; Risk Factors; Thromboplastin; Venous Thrombosis

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

A genome-wide association study identifies a potential novel gene locus for keratoconus, one of the commonest causes for corneal transplantation in developed countries. - Li, Xiaohui; Bykhovskaya, Yelena; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Hum Mol Genet, 2012)
Keratoconus is a condition in which the cornea progressively thins over time, and is a major cause for cornea transplantation. To identify keratoconus susceptibility regions, we performed a comprehensive genome-wide association study (GWAS) using a discovery and replication design. A discovery panel of 222 keratoconus Caucasian patients and 3324 Caucasian controls was genotyped using Illumina 370K beadchips. Further associated and fine-mapping single nucleotide polymorphisms (SNPs) (n= 4905) were genotyped in an independent replication case-control panel of 304 cases and 518 controls and a family panel of 307 subjects in 70 families. Logistic regression models implemented in PLINK were performed to test associations in case-control samples with and without principal component (PC) adjustments. Generalized estimation equation models accounting for familial correlations implemented in GWAF were used for association testing in families. No genome-wide associations were identified in the discovery GWAS panel. From the initial testing without adjustments for PCs, the top three SNPs located at 3p26 (rs6442925), 2q21.3 (rs4954218) and 19q13.3 (rs1428642) were identified with unadjusted P-values of 6.5 × 10(-8), 2.4 × 10(-7) and 3.1 × 10(-7), respectively. After adjustments for PCs, rs1428642 became the most significant through the genome with a P-value of 1.4 × 10(-6), while rs6442925 and rs4954218 were less significant (P= 1.9 × 10(-5) and 2.6 × 10(-4)). SNP rs4954218 was confirmed in two independent replication panels with P-values of 0.004 and 0.009, respectively. Meta-analysis revealed a highest association at rs4954218 with adjusted P= 1.6 × 10(-7) (unadjusted P= 1.2 × 10(-9)). These findings suggest SNP rs4954218, located near the RAB3GAP1 gene, previously reported to be associated with corneal malformation, is a potential susceptibility locus for keratoconus.
Keywords: Case-Control Studies; Chromosomes, Human, Pair 2; Cohort Studies; Corneal Transplantation; Developed Countries; Genome-Wide Association Study; Humans; Keratoconus; Polymorphism, Single Nucleotide

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Genome-wide meta-analysis points to CTC1 and ZNF676 as genes regulating telomere homeostasis in humans. - Mangino, Massimo; Hwang, Shih-Jen; Spector, Timothy D; Hunt, Steven C; Kimura, Masayuki; Fitzpatrick, Annette L; Christiansen, Lene; Petersen, Inge; Elbers, Clara C; Harris, Tamara; Chen, Wei; Srinivasan, Sathanur R; et al. (Hum Mol Genet, 2012)
Leukocyte telomere length (LTL) is associated with a number of common age-related diseases and is a heritable trait. Previous genome-wide association studies (GWASs) identified two loci on chromosomes 3q26.2 (TERC) and 10q24.33 (OBFC1) that are associated with the inter-individual LTL variation. We performed a meta-analysis of 9190 individuals from six independent GWAS and validated our findings in 2226 individuals from four additional studies. We confirmed previously reported associations with OBFC1 (rs9419958 P = 9.1 × 10(-11)) and with the telomerase RNA component TERC (rs1317082, P = 1.1 × 10(-8)). We also identified two novel genomic regions associated with LTL variation that map near a conserved telomere maintenance complex component 1 (CTC1; rs3027234, P = 3.6 × 10(-8)) on chromosome17p13.1 and zinc finger protein 676 (ZNF676; rs412658, P = 3.3 × 10(-8)) on 19p12. The minor allele of rs3027234 was associated with both shorter LTL and lower expression of CTC1. Our findings are consistent with the recent observations that point mutations in CTC1 cause short telomeres in both Arabidopsis and humans affected by a rare Mendelian syndrome. Overall, our results provide novel insights into the genetic architecture of inter-individual LTL variation in the general population.
Keywords: Genome-Wide Association Study; Humans; Kruppel-Like Transcription Factors; Telomere; Telomere Homeostasis; Telomere-Binding Proteins

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Insulin resistance and incident peripheral artery disease in the Cardiovascular Health Study. - Britton, Kathryn A; Mukamal, Kenneth J; Ix, Joachim H; Siscovick, David S; Newman, Anne B; de Boer, Ian H; Thacker, Evan L; Biggs, Mary L; Gaziano, J Michael; Djoussé, Luc (Vasc Med, 2012)
Type 2 diabetes is a risk factor for peripheral artery disease (PAD), and insulin resistance is a key feature of diabetes and pre-diabetes. No longitudinal epidemiological study has examined the relation between insulin resistance and PAD. Our study analyzed the association of quartiles of the homeostatic model of insulin resistance (HOMA-IR) and the development of PAD defined by two methods. PAD was first defined as the development of an abnormal ankle-brachial index (ABI) (dichotomous outcome) after 6 years of follow-up. PAD was alternatively defined as the development of clinical PAD (time-to-event analysis). The study samples included adults over the age of 65 years who were enrolled in the Cardiovascular Health Study, had fasting measurements of insulin and glucose, had ABI measurements, and were not receiving treatment for diabetes. Multivariable models were adjusted for potential confounders, including age, sex, field center and cohort, body mass index (BMI), smoking status, alcohol use, and exercise intensity. Additional models adjusted for potential mediators, including blood pressure, lipids, kidney function, and prevalent vascular disease. In the ABI analysis (n = 2108), multivariable adjusted models demonstrated a positive relation between HOMA-IR and incident PAD (odds ratio = 1.80 comparing the 4th versus 1st quartile of HOMA-IR, 95% confidence interval [CI] 1.20-2.71). In the clinical PAD analysis (n = 4208), we found a similar relation (hazard ratio = 2.30 comparing the 4th versus 1st quartile of HOMA-IR, 95% CI 1.15-4.58). As expected, further adjustment for potential mediators led to some attenuation of effect estimates. In conclusion, insulin resistance is associated with a higher risk of PAD in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Blood Glucose; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Fasting; Female; Health Surveys; Humans; Incidence; Insulin; Insulin Resistance; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Peripheral Arterial Disease; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Lifetime risks of cardiovascular disease. - Berry, Jarett D; Dyer, Alan; Cai, Xuan; Garside, Daniel B; Ning, Hongyan; Thomas, Avis; Greenland, Philip; Van Horn, Linda; Tracy, Russell P; Lloyd-Jones, Donald M (N Engl J Med, 2012)
BACKGROUND: The lifetime risks of cardiovascular disease have not been reported across the age spectrum in black adults and white adults. METHODS: We conducted a meta-analysis at the individual level using data from 18 cohort studies involving a total of 257,384 black men and women and white men and women whose risk factors for cardiovascular disease were measured at the ages of 45, 55, 65, and 75 years. Blood pressure, cholesterol level, smoking status, and diabetes status were used to stratify participants according to risk factors into five mutually exclusive categories. The remaining lifetime risks of cardiovascular events were estimated for participants in each category at each age, with death free of cardiovascular disease treated as a competing event. RESULTS: We observed marked differences in the lifetime risks of cardiovascular disease across risk-factor strata. Among participants who were 55 years of age, those with an optimal risk-factor profile (total cholesterol level, <180 mg per deciliter [4.7 mmol per liter]; blood pressure, <120 mm Hg systolic and 80 mm Hg diastolic; nonsmoking status; and nondiabetic status) had substantially lower risks of death from cardiovascular disease through the age of 80 years than participants with two or more major risk factors (4.7% vs. 29.6% among men, 6.4% vs. 20.5% among women). Those with an optimal risk-factor profile also had lower lifetime risks of fatal coronary heart disease or nonfatal myocardial infarction (3.6% vs. 37.5% among men, <1% vs. 18.3% among women) and fatal or nonfatal stroke (2.3% vs. 8.3% among men, 5.3% vs. 10.7% among women). Similar trends within risk-factor strata were observed among blacks and whites and across diverse birth cohorts. CONCLUSIONS: Differences in risk-factor burden translate into marked differences in the lifetime risk of cardiovascular disease, and these differences are consistent across race and birth cohorts. (Funded by the National Heart, Lung, and Blood Institute.).
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Effect; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Risk; Risk Assessment; Risk Factors; United States

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Markers of inflammation in prevalent and incident Parkinson's disease in the Cardiovascular Health Study. - Ton, Thanh G N; Jain, Samay; Biggs, Mary L; Thacker, Evan L; Strotmeyer, Elsa S; Boudreau, Robert; Newman, Anne B; Longstreth, W T; Checkoway, Harvey (Parkinsonism Relat Disord, 2012)
BACKGROUND: Studies demonstrate existence of inflammation in prevalent Parkinson's disease (PD). We assessed associations of baseline levels of inflammatory markers with prevalent PD at baseline (1989) and incident PD identified over 13 years of follow-up of the Cardiovascular Health Study. METHODS: Blood samples at baseline were measured for fibrinogen, interleukin-6, tumor necrosis factor-α, C-reactive protein, albumin, and white blood cells. The analysis included 60 prevalent and 154 incident PD cases. RESULTS: Risk of prevalent PD was significantly higher per doubling of IL-6 among women (odds ratio [OR]=1.5, 95% confidence interval [CI]: 1.0, 2.4) and WBC among men (OR: 2.4, 95% CI: 1.2, 4.9) in multivariate models. Risk of incident PD was not associated with higher levels of any biomarker after adjusting for age, smoking, African American race, and history of diabetes. Inverse associations with incident PD were observed per doubling of C-reactive protein (OR=0.9; 95% CI: 0.8, 1.0) and of fibrinogen among women (OR=0.4; 95% CI: 0.2, 0.8). CONCLUSIONS: Although inflammation exists in PD, it may not represent an etiologic factor. Our findings suggest the need for larger studies that measure inflammatory markers before PD onset.
Keywords: Aged; Aged, 80 and over; Albumins; Biomarkers; C-Reactive Protein; Enzyme-Linked Immunosorbent Assay; Female; Fibrinogen; Humans; Incidence; Inflammation; Interleukin-6; Leukocyte Count; Male; Parkinson Disease; Prevalence; Risk Factors; Tumor Necrosis Factor-alpha

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Multi-ethnic analysis of lipid-associated loci: the NHLBI CARe project. - Musunuru, Kiran; Romaine, Simon P R; Lettre, Guillaume; Wilson, James G; Volcik, Kelly A; Tsai, Michael Y; Taylor, Herman A; Schreiner, Pamela J; Rotter, Jerome I; Rich, Stephen S; Redline, Susan; Psaty, Bruce M; et al. (PLoS One, 2012)
BACKGROUND: Whereas it is well established that plasma lipid levels have substantial heritability within populations, it remains unclear how many of the genetic determinants reported in previous studies (largely performed in European American cohorts) are relevant in different ethnicities. METHODOLOGY/PRINCIPAL FINDINGS: We tested a set of ∼50,000 polymorphisms from ∼2,000 candidate genes and genetic loci from genome-wide association studies (GWAS) for association with low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) in 25,000 European Americans and 9,000 African Americans in the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe). We replicated associations for a number of genes in one or both ethnicities and identified a novel lipid-associated variant in a locus harboring ICAM1. We compared the architecture of genetic loci associated with lipids in both African Americans and European Americans and found that the same genes were relevant across ethnic groups but the specific associated variants at each gene often differed. CONCLUSIONS/SIGNIFICANCE: We identify or provide further evidence for a number of genetic determinants of plasma lipid levels through population association studies. In many loci the determinants appear to differ substantially between African Americans and European Americans.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genetic Association Studies; Genetic Loci; Humans; Polymorphism, Single Nucleotide; Triglycerides

Nonesterified fatty acids and risk of sudden cardiac death in older adults. - Djoussé, Luc; Biggs, Mary L; Ix, Joachim H; Kizer, Jorge R; Lemaitre, Rozenn N; Sotoodehnia, Nona; Zieman, Susan J; Mozaffarian, Dariush; Tracy, Russell P; Mukamal, Kenneth J; Siscovick, David S (Circ Arrhythm Electrophysiol, 2012)
BACKGROUND: Although nonesterified fatty acids (NEFA) have been positively associated with coronary heart disease risk factors, limited and inconsistent data are available on the relation between NEFA and sudden cardiac death. METHODS AND RESULTS: Using a prospective design, we studied 4657 older men and women (mean age, 75 years) from the Cardiovascular Health Study (1992-2006) to evaluate the association between plasma NEFA and the risk of sudden cardiac death in older adults. Plasma concentrations of NEFA were measured using established enzymatic methods, and sudden death was adjudicated using medical records, death certificates, proxy interview, and autopsy reports. We used Cox proportional hazard models to estimate multivariable-adjusted relative risks. During a median follow-up of 10.0 years, 221 new cases of sudden cardiac death occurred. In a multivariable model adjusting for age, sex, race, clinic site, alcohol intake, smoking, prevalent coronary heart disease and heart failure, and self-reported health status, relative risks (95% confidence interval) for sudden cardiac death were 1.0 (ref), 1.15 (0.81-1.64), 1.06 (0.72-1.55), and 0.91 (0.60-1.38) across consecutive quartiles of NEFA concentration. In secondary analyses restricted to the first 5 years of follow-up, we also did not observe a statistically significant association between plasma NEFA and sudden cardiac death. CONCLUSIONS: Our data do not provide evidence for an association between plasma NEFA measured late in life and the risk of sudden cardiac death in older adults.
Keywords: Aged; Aged, 80 and over; Biomarkers; Death, Sudden, Cardiac; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Retrospective Studies; Risk Factors

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Persistence and remission of musculoskeletal pain in community-dwelling older adults: results from the cardiovascular health study. - Thielke, Stephen M; Whitson, Heather; Diehr, Paula; O'Hare, Ann; Kearney, Patricia M; Chaudhry, Sarwat I; Zakai, Neil A; Kim, Dae; Sekaran, Nishant; Sale, Joanna E M; Arnold, Alice M; Chaves, Paulo; et al. (J Am Geriatr Soc, 2012)
OBJECTIVES: To characterize longitudinal patterns of musculoskeletal pain in a community sample of older adults over a 6-year period and to identify factors associated with persistence of pain. DESIGN: Secondary analysis of the Cardiovascular Health Study. SETTING: Community-based cohort drawn from four U.S. counties. PARTICIPANTS: Five thousand ninety-three men and women aged 65 and older. MEASUREMENTS: Over a 6-year period, pain was assessed each year using a single question about the presence of pain in any bones or joints during the last year. If affirmative, participants were queried about pain in seven locations (hands, shoulders, neck, back, hips, knees, feet). Participants were categorized according to the percentage of time that pain was present and according to the intermittent or chronic pattern of pain. Factors associated with persistent pain during five remaining years of the study were identified. RESULTS: Over 6 years, 32% of participants reported pain for three or more consecutive years, and 32% reported pain intermittently. Of those who reported pain the first year, 54% were pain free at least once during the follow-up period. Most of the pain at specific body locations was intermittent. Factors associated with remission of pain over 5 years included older age, male sex, better self-rated health, not being obese, taking fewer medications, and having fewer depressive symptoms. Approximately half of those with pain reported fewer pain locations the following year. CONCLUSION: Musculoskeletal pain in older adults, despite high prevalence, is often intermittent. The findings refute the notion that pain is an inevitable, unremitting, or progressive consequence of aging.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Male; Musculoskeletal Pain; Remission Induction; Residence Characteristics

Physical activity, change in biomarkers of myocardial stress and injury, and subsequent heart failure risk in older adults. - deFilippi, Christopher R; de Lemos, James A; Tkaczuk, Andrew T; Christenson, Robert H; Carnethon, Mercedes R; Siscovick, David S; Gottdiener, John S; Seliger, Stephen L (J Am Coll Cardiol, 2012)
OBJECTIVES: The aim of this study was to evaluate the association between physical activity and changes in levels of highly sensitive troponin T (cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP), and the subsequent risk of the development of heart failure (HF) in community-dwelling older adults. BACKGROUND: Higher baseline levels of cTnT and NT-proBNP and increases over time correlate with the risk of HF in older adults. Factors modifying these levels have not been identified. METHODS: NT-proBNP and cTnT were measured at baseline and 2 to 3 years later in adults 65 years of age and older free of HF participating in the Cardiovascular Health Study. Self-reported physical activity and walking pace were combined into a composite score. An increase was prespecified for NT-proBNP as a >25% increment from baseline to ≥190 pg/ml and for cTnT as a >50% increment from baseline in participants with detectable levels (≥3 pg/ml). RESULTS: A total of 2,933 participants free of HF had NT-proBNP and cTnT measured at both time points. The probability of an increase in biomarker concentrations between baseline and follow-up visits was inversely related to the physical activity score. Compared with participants with the lowest score, those with the highest score had an odds ratio of 0.50 (95% confidence interval: 0.33 to 0.77) for an increase in NT-proBNP and an odds ratio of 0.30 (95% confidence interval: 0.16 to 0.55) for an increase in cTnT, after adjusting for comorbidities and baseline levels. A higher activity score associated with a lower long-term incidence of HF. Moreover, at each level of activity, an increase in either biomarker still identified those at higher risk. CONCLUSIONS: These findings suggest that moderate physical activity has protective effects on early heart failure phenotypes, preventing cardiac injury and neurohormonal activation.
Keywords: Aged; Biomarkers; Female; Heart Failure; Humans; Male; Motor Activity; Natriuretic Peptide, Brain; Peptide Fragments; Risk Assessment; Troponin

Plasma fatty acid-binding protein 4, nonesterified fatty acids, and incident diabetes in older adults. - Djoussé, Luc; Khawaja, Owais; Bartz, Traci M; Biggs, Mary L; Ix, Joachim H; Zieman, Susan J; Kizer, Jorge R; Tracy, Russell P; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2012)
OBJECTIVE: To examine the relation of fatty acid-binding protein (FABP)4 and nonesterified fatty acids (NEFAs) to diabetes in older adults. RESEARCH DESIGN AND METHODS: We ascertained incident diabetes among 3,740 Cardiovascular Health Study participants (1992-2007) based on the use of hypoglycemic medications, fasting glucose ≥ 126 mg/dL, or nonfasting glucose ≥ 200 mg/dL. FABP4 and NEFA were measured on specimens collected between 1992 and 1993. RESULTS: Mean age of the 3,740 subjects studied was 74.8 years. For each SD increase in log FABP4, hazard ratios (HRs) for diabetes were 1.35 (95% CI 1.10-1.65) for women and 1.45 (1.13-1.85) for men controlling for age, race, education, physical activity, cystatin C, alcohol intake, smoking, self-reported health status, and estrogen use for women (P for sex-FABP4 interaction 0.10). BMI modified the FABP4-diabetes relation (P = 0.009 overall; 0.02 for women and 0.135 for men), in that statistically significant higher risk of diabetes was mainly seen in men with BMI <25 kg/m(2) (HR per SD: 1.78 [95% CI 1.13-2.81]). There was a modest and nonsignificant association of NEFA with diabetes (P(trend) = 0.21). However, when restricted to the first 5 years of follow-up, multivariable-adjusted HRs for diabetes were 1.0 (ref.), 1.68 (95% CI 1.12-2.53), and 1.63 (1.07-2.50) across consecutive tertiles of NEFA (P(trend) = 0.03). CONCLUSIONS: Plasma FABP4 was positively associated with incident diabetes in older adults, and such association was statistically significant in lean men only. A significant positive association between plasma NEFA and incident diabetes was observed during the first 5 years of follow-up.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Diabetes Mellitus; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Humans; Male; Prospective Studies

Plasma free fatty acids and risk of atrial fibrillation (from the Cardiovascular Health Study). - Khawaja, Owais; Bartz, Traci M; Ix, Joachim H; Heckbert, Susan R; Kizer, Jorge R; Zieman, Susan J; Mukamal, Kenneth J; Tracy, Russell P; Siscovick, David S; Djoussé, Luc (Am J Cardiol, 2012)
Atrial fibrillation (AF) is a highly prevalent cardiac arrhythmia in clinical practice, affecting approximately 2.3 million residents of the United States and 4.5 million residents of the European Union. It is unclear whether plasma free fatty acids (FFAs) influence the risk of AF in older adults. The aim of this study was to prospectively examine the association between plasma FFAs and incident AF in a prospective cohort of 4,175 men and women ≥65 years old from the Cardiovascular Health Study. Plasma concentrations of FFAs were measured 2 times during the 1992 to 1993 examination. Incident AF was ascertained based on study electrocardiographic and hospitalization records during follow-up. We used Cox regression to estimate relative risks of AF. Average age at baseline was 74.6 ± 5.1 years. During a mean follow-up of 10.0 years, 1,041 new cases of AF occurred. Crude incidence rates of AF were 23.7, 23.3, 23.9, and 29.7 cases/1,000 person-years across consecutive quartiles of plasma FFAs. There was a positive association between plasma FFAs and risk of AF. Multivariable adjusted hazard ratios (95% confidence intervals) for incident AF were 1.00 (referent), 1.02 (0.85 to 1.21), 1.05 (0.88 to 1.26), and 1.29 (1.08 to 1.55) from the lowest to highest quartiles of FFAs, respectively. In a secondary analysis restricted to the first 5 years of follow-up, this association persisted. In conclusion, our data show an increased risk of AF with higher plasma FFAs in community-dwelling older adults.
Keywords: Aged; Atrial Fibrillation; C-Reactive Protein; Diabetes Mellitus, Type 2; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Lipoproteins, HDL; Lipoproteins, LDL; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Prospective Studies; Sex Factors; Triglycerides; United States

Probabilistic sleep architecture models in patients with and without sleep apnea. - Bianchi, Matt T; Eiseman, Nathaniel A; Cash, Sydney S; Mietus, Joseph; Peng, Chung-Kang; Thomas, Robert J (J Sleep Res, 2012)
Sleep fragmentation of any cause is disruptive to the rejuvenating value of sleep. However, methods to quantify sleep architecture remain limited. We have previously shown that human sleep-wake stage distributions exhibit multi-exponential dynamics, which are fragmented by obstructive sleep apnea (OSA), suggesting that Markov models may be a useful method to quantify architecture in health and disease. Sleep stage data were obtained from two subsets of the Sleep Heart Health Study database: control subjects with no medications, no OSA, no medical co-morbidities and no sleepiness (n = 374); and subjects with severe OSA (n = 338). Sleep architecture was simplified into three stages: wake after sleep onset (WASO); non-rapid eye movement (NREM) sleep; and rapid eye movement (REM) sleep. The connectivity and transition rates among eight 'generator' states of a first-order continuous-time Markov model were inferred from the observed ('phenotypic') distributions: three exponentials each of NREM sleep and WASO; and two exponentials of REM sleep. Ultradian REM cycling was accomplished by imposing time-variation to REM state entry rates. Fragmentation in subjects with severe OSA involved faster transition probabilities as well as additional state transition paths within the model. The Markov models exhibit two important features of human sleep architecture: multi-exponential stage dynamics (accounting for observed bout distributions); and probabilistic transitions (an inherent source of variability). In addition, the model quantifies the fragmentation associated with severe OSA. Markov sleep models may prove important for quantifying sleep disruption to provide objective metrics to correlate with endpoints ranging from sleepiness to cardiovascular morbidity.
Keywords: Cohort Studies; Computer Simulation; Humans; Models, Theoretical; Polysomnography; Probability; Sleep Apnea Syndromes; Sleep Stages; Sleep, REM; Time Factors

A screening study of drug-drug interactions in cerivastatin users: an adverse effect of clopidogrel. - Floyd, J S; Kaspera, R; Marciante, K D; Weiss, N S; Heckbert, S R; Lumley, T; Wiggins, K L; Tamraz, B; Kwok, P-Y; Totah, R A; Psaty, B M (Clin Pharmacol Ther, 2012)
An analysis of a case-control study of rhabdomyolysis was conducted to screen for previously unrecognized cytochrome P450 enzyme (CYP) 2C8 inhibitors that may cause other clinically important drug-drug interactions. Medication use in cases of rhabdomyolysis using cerivastatin (n = 72) was compared with that in controls using atorvastatin (n = 287) for the period 1998-2001. The use of clopidogrel was strongly associated with rhabdomyolysis (odds ratio (OR) 29.6; 95% confidence interval (CI), 6.1-143). In a replication effort that used the US Food and Drug Administration (FDA) Adverse Event Reporting System (AERS), it was found that clopidogrel was used more commonly in patients with rhabdomyolysis receiving cerivastatin (17%) than in those receiving atorvastatin (0%, OR infinity; 95% CI = 5.2-infinity). Several medications were tested in vitro for their potential to cause drug-drug interactions. Clopidogrel, rosiglitazone, and montelukast were the most potent inhibitors of cerivastatin metabolism. Clopidogrel and its metabolites also inhibited cerivastatin metabolism in human hepatocytes. These epidemiological and in vitro findings suggest that clopidogrel may cause clinically important, dose-dependent drug-drug interactions with other medications metabolized by CYP2C8.
Keywords: Adverse Drug Reaction Reporting Systems; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Cytochrome P-450 CYP3A; Cytochrome P-450 CYP3A Inhibitors; Drug Interactions; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Platelet Aggregation Inhibitors; Pyridines; Rhabdomyolysis; Ticlopidine

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Telomere-associated polymorphisms correlate with cardiovascular disease mortality in Caucasian women: the Cardiovascular Health Study. - Burnett-Hartman, Andrea N; Fitzpatrick, Annette L; Kronmal, Richard A; Psaty, Bruce M; Jenny, Nancy S; Bis, Josh C; Tracy, Russ P; Kimura, Masayuki; Aviv, Abraham (Mech Ageing Dev, 2012)
Leukocyte telomere length (LTL) is linked to cardiovascular disease (CVD); however, it is unclear if LTL has an etiologic role in CVD. To gain insight into the LTL and CVD relationship, a cohort study of CVD mortality and single nucleotide polymorphisms (SNPs) in OBFC1 and TERC, genes related to LTL, was conducted among 3271 Caucasian participants ages ≥65 years enrolled 1989-1990 in the Cardiovascular Health Study. Leukocyte DNA was genotyped for SNPs in OBFC1 (rs4387287 and rs9419958) and TERC (rs3772190) that were previously associated with LTL through genome-wide association studies. Cox regression was used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). The OBFC1 SNPs were in linkage disequilibrium (r(2)=0.99), and both SNPs were similarly associated with CVD mortality in women. For women, there was a decreased risk of CVD death associated with the minor allele (rs4387287), HR=0.7; 95% CI: 0.5-0.9 (CC vs. AC) and HR=0.5; 95% CI: 0.20-1.4 (CC vs. AA) (P-trend <0.01). For men there was no association, HR=1.0; 95% CI: 0.7-1.3 (CC vs. AC) and HR=1.7; 95% CI: 0.8-3.6 (CC vs. AA) (P-trend=0.64). These findings support the hypothesis that telomere biology and associated genes may play a role in CVD-related death, particularly among women.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Humans; Leukocytes; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Risk; RNA; Sex Factors; Telomerase; Telomere

Total and high-molecular-weight adiponectin and risk of incident diabetes in older people. - Kizer, Jorge R; Arnold, Alice M; Benkeser, David; Ix, Joachim H; Djoussé, Luc; Zieman, Susan J; Barzilay, Joshua I; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2012)
OBJECTIVE: To delineate the associations of total adiponectin, high-molecular-weight (HMW) adiponectin, and the HMW-to-total adiponectin ratio with diabetes in older adults. RESEARCH DESIGN AND METHODS: Total and HMW adiponectin were measured in a population-based study of older adults. The relations of total adiponectin, HMW adiponectin, and their ratio with incident diabetes (n = 309) were assessed in 3,802 individuals. RESULTS: Total and HMW adiponectin were highly correlated (r = 0.94). Analysis using cubic splines revealed that the associations between total and HMW adiponectin and new-onset diabetes were not linear. Specifically, after adjustment for confounders, there were similar inverse relationships for total (hazard ratio per SD 0.49 [95% CI 0.39-0.63]) and HMW adiponectin (0.42 [0.32-0.56]) with diabetes up to values of 20 and 10 mg/L, respectively, above which the associations plateaued. These associations persisted after adjustment for potential mediators (blood pressure, lipids, C-reactive protein, and homeostasis model assessment of insulin resistance [HOMA-IR]). There was, however, evidence of interaction by HOMA-IR in the lower range of adiponectin, with stronger inverse associations among insulin-sensitive than insulin-resistant participants. HMW-to-total adiponectin ratio showed a linear adjusted association with outcome, but this was abolished by inclusion of mediating variables. CONCLUSIONS: In this older cohort, increasing concentrations of total and HMW adiponectin were associated with comparably lower risks of diabetes, but these associations leveled off with further increases above concentrations of 20 and 10 mg/L, respectively. The more pronounced risk decreases at the lower range among participants without insulin resistance support a role for adiponectin that is independent of baseline hyperinsulinemia, but this will require further investigation.
Keywords: Adiponectin; Aged; Diabetes Mellitus; Female; Humans; Male; Risk Factors

Transforming growth factor beta-1 and incidence of heart failure in older adults: the Cardiovascular Health Study. - Glazer, Nicole L; Macy, Elizabeth M; Lumley, Thomas; Smith, Nicholas L; Reiner, Alex P; Psaty, Bruce M; King, George L; Tracy, Russell P; Siscovick, David S (Cytokine, 2012)
CONTEXT: Transforming growth factor-beta1 (TGF-B1) is a highly pleiotropic cytokine whose functions include a central role in the induction of fibrosis. OBJECTIVE: To investigate the hypothesis that elevated plasma levels of TGF-B1 are positively associated with incident heart failure (HF). PARTICIPANTS AND METHODS: The hypotheses were tested using a two-phase case-control study design, ancillary to the Cardiovascular Health Study - a longitudinal, population-based cohort study. Cases were defined as having an incident HF event after their 1992-1993 exam and controls were free of HF at follow-up. TGF-B1 was measured using plasma collected in 1992-1993 and data from 89 cases and 128 controls were used for analysis. The association between TGF-B1 and risk of HF was evaluated using the weighted likelihood method, and odds ratios (OR) for risk of HF were calculated for TGF-B1 as a continuous linear variable and across quartiles of TGF-B1. RESULTS: The OR for HF was 1.88 (95% confidence intervals [CI] 1.26-2.81) for each nanogram increase in TGF-B1, and the OR for the highest quartile (compared to the lowest) of TGF-B1 was 5.79 (95% CI 1.65-20.34), after adjustment for age, sex, C-reactive protein, platelet count and digoxin use. Further adjustment with other covariates did not change the results. CONCLUSIONS: Higher levels of plasma TGF-B1 were associated with an increased risk of incident heart failure among older adults. However, further study is needed in larger samples to confirm these findings.
Keywords: Aged; Case-Control Studies; Health; Heart Failure; Humans; Incidence; Transforming Growth Factor beta1; United States

Transitions among Health States Using 12 Measures of Successful Aging in Men and Women: Results from the Cardiovascular Health Study. - Thielke, Stephen; Diehr, Paula (J Aging Res, 2012)
Introduction. Successful aging has many dimensions, which may manifest differently in men and women at different ages. Methods. We characterized one-year transitions among health states in 12 measures of successful aging among adults in the Cardiovascular Health Study. The measures included self-rated health, ADLs, IADLs, depression, cognition, timed walk, number of days spent in bed, number of blocks walked, extremity strength, recent hospitalizations, feelings about life as a whole, and life satisfaction. We dichotomized variables into "healthy" or "sick," states, and estimated the prevalence of the healthy state and the probability of transitioning from one state to another, or dying, during yearly intervals. We compared men and women and three age groups (65-74, 75-84, and 85-94). Findings. Measures of successful aging showed similar results by gender. Most participants remained healthy even into advanced ages, although health declined for all measures. Recuperation, although less common with age, still occurred frequently. Men had a higher death rate than women regardless of health status, and were also more likely to remain in the healthy state. Discussion. The results suggest a qualitatively different experience of successful aging between men and women. Men did not simply "age faster" than women.

Variation in the lysyl oxidase (LOX) gene is associated with keratoconus in family-based and case-control studies. - Bykhovskaya, Yelena; Li, Xiaohui; Epifantseva, Irina; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Taylor, Kent D; Rotter, Jerome I; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2012)
PURPOSE: Keratoconus is a bilateral noninflammatory progressive corneal disorder with complex genetic inheritance and a common cause for cornea transplantation in young adults. A genomewide linkage scan in keratoconus families identified a locus at 5q23.2, overlapping the gene coding for the lysyl oxidase (LOX). LOX encodes an enzyme responsible for collagen cross-linking in a variety of tissues including the cornea. Corneal collagen cross-linking with long-wave ultraviolet light and riboflavin is a promising new treatment for keratoconus. To determine whether LOX is a genetic determinant of the pathogenesis of keratoconus, we analyzed association results of LOX polymorphisms in two independent case-control samples and in keratoconus families. METHODS: Association results were analyzed of single-nucleotide polymorphisms (SNPs) in the LOX gene from a Genome-Wide Association Study (GWAS) investigation in two independent panels of patients with keratoconus and controls and in keratoconus families. RESULTS: Evidence of association was found at SNPs rs10519694 and rs2956540 located in intron 4 of LOX in the GWAS discovery case-control panel with P values of 2.3×10(-3) and 7×10(-3), respectively. The same two SNPs were found to be associated with keratoconus by family-based association testing with P values of 2.7×10(-3) and 7.7×10(-4), respectively. Meta P values of 4.0×10(-5) and 4.0×10(-7) were calculated for SNPs rs10519694 and rs2956540 by analyzing case-control and family samples simultaneously. Sequencing of LOX exons in a subset of keratoconus patients identified two polymorphisms, rs1800449 and rs2288393, located in LOX transcripts I and II, associated with keratoconus in case-control and family samples with a meta P value of 0.02. CONCLUSIONS: Results provided strong genetic evidence that LOX variants lead to increased susceptibility to developing of keratoconus.
Keywords: Case-Control Studies; Cornea; Corneal Topography; DNA; Family; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Polymorphism, Genetic; Protein-Lysine 6-Oxidase

White matter lesions and brain gray matter volume in cognitively normal elders. - Raji, Cyrus A; Lopez, Oscar L; Kuller, Lewis H; Carmichael, Owen T; Longstreth, William T; Gach, H Michael; Boardman, John; Bernick, Charles B; Thompson, Paul M; Becker, James T (Neurobiol Aging, 2012)
Cerebral white matter lesions (WMLs) reflect small vessel disease, are common in elderly individuals, and are associated with cognitive impairment. We sought to determine the relationships between WMLs, age, gray matter (GM) volume, and cognition in the Cardiovascular Health Study (CHS). From the Cardiovascular Health Study we selected 740 cognitively normal controls with a 1.5 T magnetic resonance imaging (MRI) scan of the brain and a detailed diagnostic evaluation. WML severity was determined using a standardized visual rating system. GM volumes were analyzed using voxel-based morphometry implemented in the Statistical Parametric Mapping software. WMLs were inversely correlated with GM volume, with the greatest volume loss in the frontal cortex. Age-related atrophy was observed in the hippocampus and posterior cingulate cortex. Regression analyses revealed links among age, APOE*4 allele, hypertension, WMLs, GM volume, and digit symbol substitution test scores. Both advancing age and hypertension predict higher WML load, which is itself associated with GM atrophy. Longitudinal data are needed to confirm the temporal sequence of events leading to a decline in cognitive function.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Imaging, Three-Dimensional; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Memory Disorders; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Retrospective Studies

Adhesion molecules, endothelin-1 and lung function in seven population-based cohorts. - Oelsner, E C; Pottinger, T D; Burkart, K M; Allison, M; Buxbaum, S G; Hansel, N N; Kumar, R; Larkin, E K; Lange, L A; Loehr, L R; London, S J; O'Connor, G T; et al. (Biomarkers, 2013)
CONTEXT: Endothelial function is abnormal in chronic obstructive pulmonary disease (COPD); whether endothelial dysfunction causes COPD is unknown. OBJECTIVE: Test associations of endothelial biomarkers with FEV1 using instrumental variables. METHODS: Among 26 907 participants with spirometry, ICAM-1, P-selectin, E-selectin and endothelin-1 were measured in subsets. RESULTS: ICAM-1 and P-selectin were inversely associated with FEV1 among European-Americans (-29 mL and -34 mL per standard deviation of log-transformed biomarker, p < 0.001), as was endothelin-1 among African-Americans (-22 mL, p = 0.008). Genetically-estimated ICAM-1 and P-selectin were not significantly associated with FEV1. The instrumental variable for endothelin-1 was non-informative. CONCLUSION: Although ICAM-1, P-selectin and endothelin-1 were inversely associated with FEV1, associations for ICAM-1 and P-selectin do not appear causal.
Keywords: African Continental Ancestry Group; Biomarkers; Cohort Studies; E-Selectin; Endothelin-1; Endothelium, Vascular; European Continental Ancestry Group; Female; Gene Expression; Humans; Intercellular Adhesion Molecule-1; Lung; Male; Middle Aged; P-Selectin; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests; Spirometry

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Association of heat shock proteins with all-cause mortality. - Broer, L; Demerath, E W; Garcia, M E; Homuth, G; Kaplan, R C; Lunetta, K L; Tanaka, T; Tranah, G J; Walter, S; Arnold, A M; Atzmon, G; Harris, T B; et al. (Age (Dordr), 2013)
Experimental mild heat shock is widely known as an intervention that results in extended longevity in various models along the evolutionary lineage. Heat shock proteins (HSPs) are highly upregulated immediately after a heat shock. The elevation in HSP levels was shown to inhibit stress-mediated cell death, and recent experiments indicate a highly versatile role for these proteins as inhibitors of programmed cell death. In this study, we examined common genetic variations in 31 genes encoding all members of the HSP70, small HSP, and heat shock factor (HSF) families for their association with all-cause mortality. Our discovery cohort was the Rotterdam study (RS1) containing 5,974 participants aged 55 years and older (3,174 deaths). We assessed 4,430 single nucleotide polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. After adjusting for multiple testing by permutation analysis, three SNPs showed evidence for association with all-cause mortality in RS1. These findings were followed in eight independent population-based cohorts, leading to a total of 25,007 participants (8,444 deaths). In the replication phase, only HSF2 (rs1416733) remained significantly associated with all-cause mortality. Rs1416733 is a known cis-eQTL for HSF2. Our findings suggest a role of HSF2 in all-cause mortality.
Keywords: Aged, 80 and over; Aging; Cause of Death; Forecasting; Genotype; Heat-Shock Proteins; Humans; Longevity; Promoter Regions, Genetic; Retrospective Studies; Transcription, Genetic; United States

Atrial fibrillation and cognitive decline: a longitudinal cohort study. - Thacker, Evan L; McKnight, Barbara; Psaty, Bruce M; Longstreth, W T; Sitlani, Colleen M; Dublin, Sascha; Arnold, Alice M; Fitzpatrick, Annette L; Gottesman, Rebecca F; Heckbert, Susan R (Neurology, 2013)
OBJECTIVE: We sought to determine whether in the absence of clinical stroke, people with atrial fibrillation experience faster cognitive decline than people without atrial fibrillation. METHODS: We conducted a longitudinal analysis in the Cardiovascular Health Study, a community-based study of 5,888 men and women aged 65 years and older, enrolled in 1989/1990 or 1992/1993. Participants did not have atrial fibrillation or a history of stroke at baseline. Participants were censored when they experienced incident clinical stroke. Incident atrial fibrillation was identified by hospital discharge diagnosis codes and annual study ECGs. The main outcome was rate of decline in mean scores on the 100-point Modified Mini-Mental State Examination (3MSE), administered annually up to 9 times. RESULTS: Analyses included 5,150 participants, of whom 552 (10.7%) developed incident atrial fibrillation during a mean of 7 years of follow-up. Mean 3MSE scores declined faster after incident atrial fibrillation compared with no prior atrial fibrillation. For example, the predicted 5-year decline in mean 3MSE score from age 80 to age 85 was -6.4 points (95% confidence interval [CI]: -7.0, -5.9) for participants without a history of atrial fibrillation, but was -10.3 points (95% CI: -11.8, -8.9) for participants experiencing incident atrial fibrillation at age 80, a 5-year difference of -3.9 points (95% CI: -5.3, -2.5). CONCLUSIONS: In the absence of clinical stroke, people with incident atrial fibrillation are likely to reach thresholds of cognitive impairment or dementia at earlier ages than people with no history of atrial fibrillation.
Keywords: Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cognition Disorders; Comorbidity; Female; Humans; Incidence; Longitudinal Studies; Luria-Nebraska Neuropsychological Battery; Male; Predictive Value of Tests

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Continental Population Groups; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sample Size; Self Report; Sequence Analysis, DNA

Bidirectional relationship between cognitive function and pneumonia. - Shah, Faraaz Ali; Pike, Francis; Alvarez, Karina; Angus, Derek; Newman, Anne B; Lopez, Oscar; Tate, Judith; Kapur, Vishesh; Wilsdon, Anthony; Krishnan, Jerry A; Hansel, Nadia; Au, David; et al. (Am J Respir Crit Care Med, 2013)
RATIONALE: Relationships between chronic health conditions and acute infections remain poorly understood. Preclinical studies suggest crosstalk between nervous and immune systems. OBJECTIVES: To determine bidirectional relationships between cognition and pneumonia. METHODS: We conducted longitudinal analyses of a population-based cohort over 10 years. We determined whether changes in cognition increase risk of pneumonia hospitalization by trajectory analyses and joint modeling. We then determined whether pneumonia hospitalization increased risk of subsequent dementia using a Cox model with pneumonia as a time-varying covariate. MEASUREMENTS AND MAIN RESULTS: Of the 5,888 participants, 639 (10.9%) were hospitalized with pneumonia at least once. Most participants had normal cognition before pneumonia. Three cognition trajectories were identified: no, minimal, and severe rapid decline. A greater proportion of participants hospitalized with pneumonia were on trajectories of minimal or severe decline before occurrence of pneumonia compared with those never hospitalized with pneumonia (proportion with no, minimal, and severe decline were 67.1%, 22.8%, and 10.0% vs. 76.0%, 19.3%, and 4.6% for participants with and without pneumonia, respectively; P < 0.001). Small subclinical changes in cognition increased risk of pneumonia, even in those with normal cognition and physical function before pneumonia (β = -0.02; P < 0.001). Participants with pneumonia were subsequently at an increased risk of dementia (hazard ratio, 2.24 [95% confidence interval, 1.62-3.11]; P = 0.01). Associations were independent of demographics, health behaviors, other chronic conditions, and physical function. Bidirectional relationship did not vary based on severity of disease, and similar associations were noted for those with severe sepsis and other infections. CONCLUSIONS: A bidirectional relationship exists between pneumonia and cognition and may explain how a single episode of infection in well-appearing older individuals accelerates decline in chronic health conditions and loss of functional independence.
Keywords: Aged; Cognition Disorders; Dementia; Female; Hospitalization; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Pneumonia; Proportional Hazards Models; Risk Factors

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Decline in health for older adults: five-year change in 13 key measures of standardized health. - Diehr, Paula H; Thielke, Stephen M; Newman, Anne B; Hirsch, Calvin; Tracy, Russell (J Gerontol A Biol Sci Med Sci, 2013)
BACKGROUND: The health of older adults declines over time, but there are many ways of measuring health. It is unclear whether all health measures decline at the same rate or whether some aspects of health are less sensitive to aging than others. METHODS: We compared the decline in 13 measures of physical, mental, and functional health from the Cardiovascular Health Study: hospitalization, bed days, cognition, extremity strength, feelings about life as a whole, satisfaction with the purpose of life, self-rated health, depression, digit symbol substitution test, grip strength, activities of daily living, instrumental activities of daily living, and gait speed. Each measure was standardized against self-rated health. We compared the 5-year change to see which of the 13 measures declined the fastest and the slowest. RESULTS: The 5-year change in standardized health varied from a decline of 12 points (out of 100) for hospitalization to a decline of 17 points for gait speed. In most comparisons, standardized health from hospitalization and bed days declined the least, whereas health measured by activities of daily living, instrumental activities of daily living, and gait speed declined the most. These rankings were independent of age, sex, mortality patterns, and the method of standardization. CONCLUSIONS: All of the health variables declined, on average, with advancing age, but at significantly different rates. Standardized measures of mental health, cognition, quality of life, and hospital utilization did not decline as fast as gait speed, activities of daily living, and instrumental activities of daily living. Public health interventions to address problems with gait speed, activities of daily living, and instrumental activities of daily living may help older adults to remain healthier in all dimensions.
Keywords: Activities of Daily Living; Aged; Aging; Cohort Studies; Female; Gait; Health Status; Health Status Indicators; Hospitalization; Humans; Longitudinal Studies; Male; Mental Health; Quality of Life; Self Report; United States

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Effects of respiratory and non-respiratory factors on disability among older adults with airway obstruction: the Cardiovascular Health Study. - Locke, Emily; Thielke, Stephen; Diehr, Paula; Wilsdon, Anthony G; Barr, R Graham; Hansel, Nadia; Kapur, Vishesh K; Krishnan, Jerry; Enright, Paul; Heckbert, Susan R; Kronmal, Richard A; Fan, Vincent S (COPD, 2013)
BACKGROUND: High rates of disability associated with chronic airway obstruction may be caused by impaired pulmonary function, pulmonary symptoms, other chronic diseases, or systemic inflammation. METHODS: We analyzed data from the Cardiovascular Health Study, a longitudinal cohort of 5888 older adults. Categories of lung function (normal; restricted; borderline, mild-moderate, and severe obstruction) were delineated by baseline spirometry (without bronchodilator). Disability-free years were calculated as total years alive and without self-report of difficulty performing &γτ;1 Instrumental Activities of Daily Living over 6 years of follow-up. Using linear regression, we compared disability-free years by lung disease category, adjusting for demographic factors, body mass index, smoking, cognition, and other chronic co-morbidities. Among participants with airflow obstruction, we examined the association of respiratory factors (FEV1 and dyspnea) and non-respiratory factors (ischemic heart disease, congestive heart failure, diabetes, muscle weakness, osteoporosis, depression and cognitive impairment) on disability-free years. RESULTS: The average disability free years were 4.0 out of a possible 6 years. Severe obstruction was associated with 1 fewer disability-free year compared to normal spirometry in the adjusted model. For the 1,048 participants with airway obstruction, both respiratory factors (FEV1 and dyspnea) and non-respiratory factors (heart disease, coronary artery disease, diabetes, depression, osteoporosis, cognitive function, and weakness) were associated with decreased disability-free years. CONCLUSIONS: Severe obstruction is associated with greater disability compared to patients with normal spirometery. Both respiratory and non-respiratory factors contribute to disability in older adults with abnormal spirometry.
Keywords: Activities of Daily Living; Aged; Cognition Disorders; Cohort Studies; Comorbidity; Depression; Diabetes Mellitus; Disease Progression; Dyspnea; Female; Heart Failure; Humans; Linear Models; Longitudinal Studies; Male; Muscle Weakness; Myocardial Ischemia; Osteoporosis; Pulmonary Disease, Chronic Obstructive; Severity of Illness Index; Spirometry

Evaluating subject-level incremental values of new markers for risk classification rule. - Cai, T; Tian, L; Lloyd-Jones, D; Wei, L J (Lifetime Data Anal, 2013)
Suppose that we need to classify a population of subjects into several well-defined ordered risk categories for disease prevention or management with their "baseline" risk factors/markers. In this article, we present a systematic approach to identify subjects using their conventional risk factors/markers who would benefit from a new set of risk markers for more accurate classification. Specifically for each subgroup of individuals with the same conventional risk estimate, we present inference procedures for the reclassification and the corresponding correct re-categorization rates with the new markers. We then apply these new tools to analyze the data from the Cardiovascular Health Study sponsored by the US National Heart, Lung, and Blood Institute. We used Framingham risk factors plus the information of baseline anti-hypertensive drug usage to identify adult American women who may benefit from the measurement of a new blood biomarker, CRP, for better risk classification in order to intensify prevention of coronary heart disease for the subsequent 10 years.
Keywords: Aged; Antihypertensive Agents; Biomarkers; Biostatistics; C-Reactive Protein; Confidence Intervals; Coronary Disease; Female; Humans; Risk; Risk Factors; Statistics, Nonparametric; United States

Fatty acid-binding protein 4 and incident heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Bartz, Traci M; Ix, Joachim H; Kochar, Jinesh; Kizer, Jorge R; Gottdiener, John S; Tracy, Russell P; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Zieman, Susan J (Eur J Heart Fail, 2013)
AIM: To examine the association of plasma fatty acid-binding protein 4 (FABP4) with incident heart failure. METHODS AND RESULTS: In a prospective study of 4179 participants from the Cardiovascular Health Study, we measured plasma FABP4 on blood specimens collected between 1992 and 1993. Incident heart failure was adjudicated by an endpoint committee and we used a Cox proportional hazards model to calculate hazard ratios (HRs) of heart failure. The average age at baseline was 75 years. During a median follow-up of 10.7 years, 1182 cases of incident heart failure occurred. We observed a positive association between FABP4 and heart failure in the minimally adjusted models [HR 1.32, 95% confidence interval (CI) 1.25-1.38 per 1 SD higher FABP4] that was attenuated upon adjustment for potential confounders, mostly kidney function and body mass index (corresponding HR 1.09, 95% CI 1.01-1.17). In a subsample of heart failure cases with available data on LV systolic function, FABP4 was not associated with heart failure with or without preserved LV systolic function. Exclusion of people with unintentional weight loss and self-reported fair/poor health status did not alter the conclusion. CONCLUSION: An elevated plasma concentration of FABP4 was associated with a modestly higher risk of heart failure in older adults in the USA after adjustment for confounding factors.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Fatty Acid-Binding Proteins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Ventricular Function, Left

Fetuin-A, type 2 diabetes, and risk of cardiovascular disease in older adults: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Shlipak, Michael; Ix, Joachim H (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A, a hepatic secretory protein that simultaneously inhibits arterial calcification and insulin action, is associated with type 2 diabetes, but its association with cardiovascular disease (CVD) is uncertain. Preliminary studies suggest that the association of fetuin-A with CVD might differ among individuals with or without type 2 diabetes. RESEARCH DESIGN AND METHODS: This was a prospective study of 3,810 community-living individuals older than 65 years (511 with type 2 diabetes) and free of CVD in 1992 when fetuin-A levels were measured. Participants were followed-up for incident CVD through June 2008. RESULTS: Mean age was 75 years, and 61% were women; 1,456 participants had an incident CVD event (248 among individuals with type 2 diabetes). The association of fetuin-A with CVD was modified by type 2 diabetes (P interaction = 0.02). Higher fetuin-A was associated with lower CVD risk among persons without type 2 diabetes [hazard ratio per SD 0.1 g/L higher fetuin-A, 0.93 (95% CI, 0.88-0.99)], whereas a trend in the opposite direction was observed among individuals with type 2 diabetes, although it was not statistically significant [1.07 (0.93-1.22)]. Among individuals without type 2 diabetes, similar effect modification was observed by obesity and insulin resistance. Consistently, higher fetuin-A was associated with lower CVD risk only in the subgroups without obesity or with HOMA-IR below the median [0.91 (0.85-0.97) and 0.87 (0.79-0.95), respectively]. CONCLUSIONS: The association of fetuin-A with risk of CVD differs among elderly individuals with and without insulin resistance or type 2 diabetes.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Fetuins; Humans; Incidence; Longitudinal Studies; Male; Risk Factors

Gene-centric meta-analyses of 108 912 individuals confirm known body mass index loci and reveal three novel signals. - Guo, Yiran; Lanktree, Matthew B; Taylor, Kira C; Hakonarson, Hakon; Lange, Leslie A; Keating, Brendan J (Hum Mol Genet, 2013)
Recent genetic association studies have made progress in uncovering components of the genetic architecture of the body mass index (BMI). We used the ITMAT-Broad-Candidate Gene Association Resource (CARe) (IBC) array comprising up to 49 320 single nucleotide polymorphisms (SNPs) across ~2100 metabolic and cardiovascular-related loci to genotype up to 108 912 individuals of European ancestry (EA), African-Americans, Hispanics and East Asians, from 46 studies, to provide additional insight into SNPs underpinning BMI. We used a five-phase study design: Phase I focused on meta-analysis of EA studies providing individual level genotype data; Phase II performed a replication of cohorts providing summary level EA data; Phase III meta-analyzed results from the first two phases; associated SNPs from Phase III were used for replication in Phase IV; finally in Phase V, a multi-ethnic meta-analysis of all samples from four ethnicities was performed. At an array-wide significance (P < 2.40E-06), we identify novel BMI associations in loci translocase of outer mitochondrial membrane 40 homolog (yeast) - apolipoprotein E - apolipoprotein C-I (TOMM40-APOE-APOC1) (rs2075650, P = 2.95E-10), sterol regulatory element binding transcription factor 2 (SREBF2, rs5996074, P = 9.43E-07) and neurotrophic tyrosine kinase, receptor, type 2 [NTRK2, a brain-derived neurotrophic factor (BDNF) receptor gene, rs1211166, P = 1.04E-06] in the Phase IV meta-analysis. Of 10 loci with previous evidence for BMI association represented on the IBC array, eight were replicated, with the remaining two showing nominal significance. Conditional analyses revealed two independent BMI-associated signals in BDNF and melanocortin 4 receptor (MC4R) regions. Of the 11 array-wide significant SNPs, three are associated with gene expression levels in both primary B-cells and monocytes; with rs4788099 in SH2B adaptor protein 1 (SH2B1) notably being associated with the expression of multiple genes in cis. These multi-ethnic meta-analyses expand our knowledge of BMI genetics.
Keywords: Body Mass Index; Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide

Generalization and dilution of association results from European GWAS in populations of non-European ancestry: the PAGE study. - Carlson, Christopher S; Matise, Tara C; North, Kari E; Haiman, Christopher A; Fesinmeyer, Megan D; Buyske, Steven; Schumacher, Fredrick R; Peters, Ulrike; Franceschini, Nora; Ritchie, Marylyn D; Duggan, David J; Spencer, Kylee L; et al. (PLoS Biol, 2013)
The vast majority of genome-wide association study (GWAS) findings reported to date are from populations with European Ancestry (EA), and it is not yet clear how broadly the genetic associations described will generalize to populations of diverse ancestry. The Population Architecture Using Genomics and Epidemiology (PAGE) study is a consortium of multi-ancestry, population-based studies formed with the objective of refining our understanding of the genetic architecture of common traits emerging from GWAS. In the present analysis of five common diseases and traits, including body mass index, type 2 diabetes, and lipid levels, we compare direction and magnitude of effects for GWAS-identified variants in multiple non-EA populations against EA findings. We demonstrate that, in all populations analyzed, a significant majority of GWAS-identified variants have allelic associations in the same direction as in EA, with none showing a statistically significant effect in the opposite direction, after adjustment for multiple testing. However, 25% of tagSNPs identified in EA GWAS have significantly different effect sizes in at least one non-EA population, and these differential effects were most frequent in African Americans where all differential effects were diluted toward the null. We demonstrate that differential LD between tagSNPs and functional variants within populations contributes significantly to dilute effect sizes in this population. Although most variants identified from GWAS in EA populations generalize to all non-EA populations assessed, genetic models derived from GWAS findings in EA may generate spurious results in non-EA populations due to differential effect sizes. Regardless of the origin of the differential effects, caution should be exercised in applying any genetic risk prediction model based on tagSNPs outside of the ancestry group in which it was derived. Models based directly on functional variation may generalize more robustly, but the identification of functional variants remains challenging.
Keywords: African Americans; Asian Americans; Body Mass Index; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Lipids; Metagenomics; Oceanic Ancestry Group; Polymorphism, Single Nucleotide

Genetic association of COL5A1 variants in keratoconus patients suggests a complex connection between corneal thinning and keratoconus. - Li, Xiaohui; Bykhovskaya, Yelena; Canedo, Ana Laura Caiado; Haritunians, Talin; Siscovick, David; Aldave, Anthony J; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2013)
PURPOSE: Single nucleotide polymorphisms (SNPs) located near or within the COL5A1 gene, at 9q34.2-q34.3 chromosomal region have been reported in association with central corneal thickness (CCT). Using family linkage analysis, we identified a keratoconus susceptibility locus at 9q34. These findings led us to perform an association study between COL5A1 variation and keratoconus susceptibility. METHODS: A Caucasian case-control cohort of 222 keratoconus patients and 3324 controls was selected as the discovery panel. An independent case-control panel of 304 cases and 518 controls and a family panel of 186 subjects were replicated for genotyping and association. Forty-four SNPs (21 for discovery and 23 for fine-mapping) spanning 300 kilobases in and around COL5A1 were genotyped and tested for genetic association. Logistic regression models implemented in PLINK were used to test for association in case controls. Generalized estimating equation models accounting for familial correlations implemented in genome-wide interaction analyses with family data were used for association testing in families. RESULTS: Two CCT associated SNPs (rs1536482 and rs7044529 near and within COL5A1) were identified in the keratoconus discovery cohort (P values of 6.5 × 10(-3) and 7.4 × 10(-3)). SNP rs1536482 was replicated in the second case-control sample (P = 0.02), and SNP rs7044529 was replicated in a keratoconus family panel (P = 0.03). Meta P values of rs1536482 and rs7044529 in the keratoconus cohorts were 1.5 × 10(-4) (odds ratio [OR] = 1.30) and 2.9 × 10(-3) (OR = 1.39). After Bonferroni correction, the association of SNP rs1536482 remained significant (P = 6.5 × 10(-3)). CONCLUSIONS: SNPs in the COL5A1 region, which regulate normal variation in CCT, may play a role in the thinning associated with keratoconus.
Keywords: Adult; Aged; Collagen Type V; Cornea; Corneal Topography; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Male; Microscopy, Acoustic; Middle Aged; Polymorphism, Single Nucleotide; Tomography, Optical Coherence

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

Genome-wide association study of cardiac structure and systolic function in African Americans: the Candidate Gene Association Resource (CARe) study. - Fox, Ervin R; Musani, Solomon K; Barbalic, Maja; Lin, Honghuang; Yu, Bing; Ogunyankin, Kofo O; Smith, Nicholas L; Kutlar, Abdullah; Glazer, Nicole L; Post, Wendy S; Paltoo, Dina N; Dries, Daniel L; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: Using data from 4 community-based cohorts of African Americans, we tested the association between genome-wide markers (single-nucleotide polymorphisms) and cardiac phenotypes in the Candidate-gene Association Resource study. METHODS AND RESULTS: Among 6765 African Americans, we related age, sex, height, and weight-adjusted residuals for 9 cardiac phenotypes (assessed by echocardiogram or magnetic resonance imaging) to 2.5 million single-nucleotide polymorphisms genotyped using Genome-wide Affymetrix Human SNP Array 6.0 (Affy6.0) and the remainder imputed. Within the cohort, genome-wide association analysis was conducted, followed by meta-analysis across cohorts using inverse variance weights (genome-wide significance threshold=4.0 ×10(-7)). Supplementary pathway analysis was performed. We attempted replication in 3 smaller cohorts of African ancestry and tested lookups in 1 consortium of European ancestry (EchoGEN). Across the 9 phenotypes, variants in 4 genetic loci reached genome-wide significance: rs4552931 in UBE2V2 (P=1.43×10(-7)) for left ventricular mass, rs7213314 in WIPI1 (P=1.68×10(-7)) for left ventricular internal diastolic diameter, rs1571099 in PPAPDC1A (P=2.57×10(-8)) for interventricular septal wall thickness, and rs9530176 in KLF5 (P=4.02×10(-7)) for ejection fraction. Associated variants were enriched in 3 signaling pathways involved in cardiac remodeling. None of the 4 loci replicated in cohorts of African ancestry was confirmed in lookups in EchoGEN. CONCLUSIONS: In the largest genome-wide association study of cardiac structure and function to date in African Americans, we identified 4 genetic loci related to left ventricular mass, interventricular septal wall thickness, left ventricular internal diastolic diameter, and ejection fraction, which reached genome-wide significance. Replication results suggest that these loci may be unique to individuals of African ancestry. Additional large-scale studies are warranted for these complex phenotypes.
Keywords: African Americans; Aged; Cohort Studies; Diastole; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Hypertension and low HDL cholesterol were associated with reduced kidney function across the age spectrum: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Fried, Linda F; Newman, Anne B; Katz, Ronit; Satterfield, Suzanne; Harris, Tamara B; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Ann Epidemiol, 2013)
PURPOSE: To determine if the associations among established risk factors and reduced kidney function vary by age. METHODS: We pooled cross-sectional data from 14,788 nondiabetics aged 40 to 100 years in 4 studies: Cardiovascular Health Study, Health, Aging, and Body Composition Study, Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular End-Stage Disease cohort. RESULTS: Hypertension and low high-density lipoprotein (HDL) cholesterol were associated with reduced cystatin C-based estimated glomerular filtration rate (eGFR) across the age spectrum. In adjusted analyses, hypertension was associated with a 2.3 (95% confidence interval [CI], 0.1, 4.4), 5.1 (95% CI, 4.1, 6.1), and 6.9 (95% CI, 3.0, 10.4) mL/min/1.73 m(2) lower eGFR in participants 40 to 59, 60 to 79, and at least 80 years, respectively (P for interaction < .001). The association of low HDL cholesterol with reduced kidney function was also greater in the older age groups: 4.9 (95% CI, 3.5, 6.3), 7.1 (95% CI, 6.0, 8.3), 8.9 (95% CI, 5.4, 11.9) mL/min/1.73 m(2) (P for interaction < .001). Smoking and obesity were associated with reduced kidney function in participants under 80 years. All estimates of the potential population impact of the risk factors were modest. CONCLUSIONS: Hypertension, obesity, smoking, and low HDL cholesterol are modestly associated with reduced kidney function in nondiabetics. The associations of hypertension and HDL cholesterol with reduced kidney function seem to be stronger in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Causality; Cholesterol, LDL; Cohort Studies; Comorbidity; Cross-Sectional Studies; Cystatin C; Female; Humans; Hypertension; Kidney Function Tests; Male; Netherlands; Obesity; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Smoking; United States

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Impact of inflammatory biomarkers on relation of high density lipoprotein-cholesterol with incident coronary heart disease: cardiovascular Health Study. - Tehrani, David M; Gardin, Julius M; Yanez, David; Hirsch, Calvin H; Lloyd-Jones, Donald M; Stein, Phyllis K; Wong, Nathan D (Atherosclerosis, 2013)
BACKGROUND: Inflammatory factors and low HDL-C relate to CHD risk, but whether inflammation attenuates any protective association of high HDL-C is unknown. OBJECTIVE: Investigate inflammatory markers' individual and collective impact on the association of HDL-C with incident coronary heart disease (CHD). METHODS: In 3888 older adults without known cardiovascular disease (CVD), we examined if the inflammatory markers C-reactive protein (CRP), interleukin-6 (IL-6), and lipoprotein-associated phospholipase A2 (Lp-PLA₂) modify the relation of HDL-C with CHD. HDL-C, CRP, IL-6, and Lp-PLA₂ values were grouped as using gender-specific tertiles. Also, an inflammation index of z-score sums for CRP, IL-6, and Lp-PLA₂ was categorized into tertiles. We calculated CHD incidence for each HDL-C/inflammation group and performed Cox regression, adjusted for standard CVD risk factors and triglycerides to examine the relationship of combined HDL-C-inflammation groups with incident events. RESULTS: CHD incidence (per 1000 person years) was higher for higher levels of CRP, IL-6, and the index, and lower for higher levels of HDL-C. Compared to high HDL-C/low-inflammation categories (referent), adjusted HRs for incident CHD were increased for those with high HDL-C and high CRP (HR = 1.50, p < 0.01) or highest IL-6 tertile (HR = 1.40, p < 0.05), but not with highest Lp-PLA₂ tertile. Higher CHD incidence was similarly seen for those with intermediate or low HDL-C accompanied by high CRP, high IL-6, or a high inflammatory index. CONCLUSION: The protective relation of high HDL-C for incident CHD appears to be attenuated by greater inflammation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Inflammation; Interleukin-6; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Insulin resistance and risk of incident heart failure: Cardiovascular Health Study. - Banerjee, Dipanjan; Biggs, Mary L; Mercer, Laina; Mukamal, Kenneth; Kaplan, Robert; Barzilay, Joshua; Kuller, Lewis; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell; Zieman, Susan; Lloyd-Jones, Donald; et al. (Circ Heart Fail, 2013)
BACKGROUND: Patients with heart failure (HF) have higher fasting insulin levels and a higher prevalence of insulin resistance as compared with matched controls. Insulin resistance leads to structural abnormalities in the heart, such as increased left atrial size, left ventricular mass, and alterations in transmitral velocity that can precede the diagnosis of HF. It is not known whether insulin resistance precedes the development of HF or whether the relationship between insulin resistance and HF is present among adults with HF caused by nonischemic heart disease. METHODS AND RESULTS: We examined 4425 participants (60% women) from the Cardiovascular Health Study after excluding those with HF, myocardial infarction, or treated diabetes mellitus at baseline. We used Cox proportional hazards models to estimate the relative risk of incident HF associated with fasting insulin measured at study entry. There were 1216 cases of incident HF (1103 without antecedent myocardial infarction) during a median follow-up of 12 years (maximum, 19 years). Fasting insulin levels were positively associated with the risk of incident HF (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15, per SD change) when adjusted for age, sex, race, field center, physical activity, smoking, alcohol intake, high-density lipoprotein-cholesterol, total cholesterol, systolic blood pressure, and waist circumference. The association between fasting insulin levels and incident HF was similar for HF without antecedent myocardial infarction (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15). Measures of left atrial size, left ventricular mass, and peak A velocity at baseline were associated both with fasting insulin levels and with HF; however, additional statistical adjustment for these parameters did not completely attenuate the insulin-HF estimate (hazard ratio, 1.08; 95% confidence interval, 1.03-1.14 per 1-SD increase in fasting insulin). CONCLUSIONS: Fasting insulin was positively associated with adverse echocardiographic features and risk of subsequent HF in Cardiovascular Health Study participants, including those without an antecedent myocardial infarction. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Female; Heart Atria; Heart Failure; Heart Ventricles; Humans; Incidence; Insulin; Insulin Resistance; Male; Middle Aged; Myocardial Infarction; Organ Size; Proportional Hazards Models; Prospective Studies

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies. - Smith, C E; Ngwa, J; Tanaka, T; Qi, Q; Wojczynski, M K; Lemaitre, R N; Anderson, J S; Manichaikul, A; Mikkilä, V; van Rooij, F J A; Ye, Z; Bandinelli, S; et al. (Int J Obes (Lond), 2013)
OBJECTIVE: Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS: We conducted race/ethnic-specific meta-analyses using data from 14 studies of US and European whites and 4 of African Americans to evaluate associations of dietary fatty acids and LRP1 genotypes with body mass index (BMI), waist circumference and hip circumference, as well as interactions between dietary fatty acids and LRP1 genotypes. Seven single-nucleotide polymorphisms (SNPs) of LRP1 were evaluated in whites (N up to 42 000) and twelve SNPs in African Americans (N up to 5800). RESULTS: After adjustment for age, sex and population substructure if relevant, for each one unit greater intake of percentage of energy from saturated fat (SFA), BMI was 0.104 kg m(-2) greater, waist was 0.305 cm larger and hip was 0.168 cm larger (all P<0.0001). Other fatty acids were not associated with outcomes. The association of SFA with outcomes varied by genotype at rs2306692 (genotyped in four studies of whites), where the magnitude of the association of SFA intake with each outcome was greater per additional copy of the T allele: 0.107 kg m(-2) greater for BMI (interaction P=0.0001), 0.267 cm for waist (interaction P=0.001) and 0.21 cm for hip (interaction P=0.001). No other significant interactions were observed. CONCLUSION: Dietary SFA and LRP1 genotype may interactively influence anthropometric traits. Further exploration of this, and other diet x genotype interactions, may improve understanding of interindividual variability in the relationships of dietary factors with anthropometric traits.
Keywords: Adipose Tissue; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Body Mass Index; Europe; European Continental Ancestry Group; Fatty Acids; Female; Gene Frequency; Gene-Environment Interaction; Genetic Predisposition to Disease; Genotype; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Obesity; Phenotype; Polymorphism, Single Nucleotide; Prevalence; United States

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Plasma Fatty Acid binding protein 4 and risk of sudden cardiac death in older adults. - Djoussé, Luc; Maziarz, Marlena; Biggs, Mary L; Ix, Joachim H; Zieman, Susan J; Kizer, Jorge R; Lemaitre, Rozenn N; Mozaffarian, Dariush; Tracy, Russell P; Mukamal, Kenneth J; Siscovick, David S; Sotoodehnia, Nona (Cardiol Res Pract, 2013)
Although fatty acid binding protein 4 (FABP4) may increase risk of diabetes and exert negative cardiac inotropy, it is unknown whether plasma concentrations of FABP4 are associated with incidence of sudden cardiac death (SCD). We prospectively analyzed data on 4,560 participants of the Cardiovascular Health Study. FABP4 was measured at baseline using ELISA, and SCD events were adjudicated through review of medical records. We used Cox proportional hazards to estimate effect measures. During a median followup of 11.8 years, 146 SCD cases occurred. In a multivariable model adjusting for demographic, lifestyle, and metabolic factors, relative risk of SCD associated with each higher standard deviation (SD) of plasma FABP4 was 1.15 (95% CI: 0.95-1.38), P = 0.15. In a secondary analysis stratified by prevalent diabetes status, FABP4 was associated with higher risk of SCD in nondiabetic participants, (RR per SD higher FABP4: 1.33 (95% CI: 1.07-1.65), P = 0.009) but not in diabetic participants (RR per SD higher FABP4: 0.88 (95% CI: 0.62-1.27), P = 0.50), P for diabetes-FABP4 interaction 0.049. In summary, a single measure of plasma FABP4 obtained later in life was not associated with the risk of SCD in older adults overall. Confirmation of our post-hoc results in nondiabetic people in other studies is warranted.

Plasma free fatty acids and risk of heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Benkeser, David; Arnold, Alice; Kizer, Jorge R; Zieman, Susan J; Lemaitre, Rozenn N; Tracy, Russell P; Gottdiener, John S; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Ix, Joachim H (Circ Heart Fail, 2013)
BACKGROUND: Although plasma free fatty acid (FFA) concentrations have been associated with lipotoxicity, apoptosis, and risk of diabetes mellitus and coronary heart disease, it is unclear whether FFA levels are associated with heart failure (HF). METHODS AND RESULTS: To test the hypothesis that plasma concentration of FFAs is positively associated with incident HF, we prospectively analyzed data on 4248 men and women free of HF at baseline and >65 years old from the Cardiovascular Health Study. FFA concentration was measured in duplicate by the Wako enzymatic method. Incident HF was validated by a centralized Events Committee. We used Cox proportional hazards to estimate the hazard ratio of HF per SD of FFAs. During a median follow-up of 10.5 years, a total of 1286 new cases of HF occurred. In a multivariable model adjusting for clinic site, comorbidity, demographic, anthropometric, and lifestyle factors, each SD (0.2 mEq/L) higher plasma FFA was associated with 12% (95% confidence interval, 6%-19%) higher risk of HF. Controlling for time-varying diabetes mellitus and coronary heart disease did not change the results (hazard ratio per SD, 1.16 [95% confidence interval, 1.09-1.23]). CONCLUSIONS: A single measure of plasma FFA obtained later in life is associated with a higher risk of HF in older adults. Additional studies are needed to explore biological mechanisms by which FFAs may influence the risk of HF and determine whether FFAs could serve as a novel pharmacological target for HF prevention.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Fatty Acids, Nonesterified; Female; Heart Failure; Humans; Incidence; Kaplan-Meier Estimate; Linear Models; Male; Multivariate Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States

Prediction and classification of cardiovascular disease risk in older adults with diabetes. - Mukamal, K J; Kizer, J R; Djoussé, L; Ix, J H; Zieman, S; Siscovick, D S; Sibley, C T; Tracy, R P; Arnold, A M (Diabetologia, 2013)
AIMS/HYPOTHESIS: We sought to derive and validate a cardiovascular disease (CVD) prediction algorithm for older adults with diabetes, and evaluate the incremental benefit of adding novel circulating biomarkers and measures of subclinical atherosclerosis. METHODS: As part of the Cardiovascular Health Study (CHS), a population-based cohort of adults aged ≥65 years, we examined the 10 year risk of myocardial infarction, stroke and cardiovascular death in 782 older adults with diabetes, in whom 265 events occurred. We validated predictive models in 843 adults with diabetes, who were followed for 7 years in a second cohort, the Multi-Ethnic Study of Atherosclerosis (MESA); here 71 events occurred. RESULTS: The best fitting standard model included age, smoking, systolic blood pressure, total and HDL-cholesterol, creatinine and the use of glucose-lowering agents; however, this model had a C statistic of 0.64 and poorly classified risk in men. Novel biomarkers did not improve discrimination or classification. The addition of ankle-brachial index, electrocardiographic left ventricular hypertrophy and internal carotid intima-media thickness modestly improved discrimination (C statistic 0.68; p = 0.002) and classification (net reclassification improvement [NRI] 0.12; p = 0.01), mainly in those remaining free of CVD. Results were qualitatively similar in the MESA, with a change in C statistic from 0.65 to 0.68 and an NRI of 0.09 upon inclusion of subclinical disease measures. CONCLUSIONS/INTERPRETATION: Standard clinical risk factors and novel biomarkers poorly discriminate and classify CVD risk in older adults with diabetes. The inclusion of subclinical atherosclerotic measures modestly improves these features, but to develop more robust risk prediction, a better understanding of the pathophysiology and determinants of CVD in this patient group is needed.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Myocardial Infarction; Regression Analysis; Risk Factors; Stroke

Racial differences in the incidence of and risk factors for atrial fibrillation in older adults: the cardiovascular health study. - Jensen, Paul N; Thacker, Evan L; Dublin, Sascha; Psaty, Bruce M; Heckbert, Susan R (J Am Geriatr Soc, 2013)
This study examined whether different associations between risk factors and atrial fibrillation (AF) according to race could explain the lower incidence of AF in blacks. Baseline risk factor information was obtained from interviews, clinical examinations, and echocardiography in 4,774 white and 911 black Cardiovascular Health Study participants aged 65 and older without a history of AF at baseline in 1989/90 or 1992/93. Incident AF was determined according to hospital discharge diagnosis or annual study electrocardiogram. Cox regression was used to assess associations between risk factors and race and incident AF. During a mean 11.2 years of follow-up, 1,403 whites and 182 blacks had incident AF. Associations between all examined risk factors were similar in both races, except left ventricular posterior wall thickness, which was more strongly associated with AF in blacks (per 0.2 cm, blacks: hazard ratio (HR) = 1.72, 95% confidence interval (CI) = 1.44-2.06; whites: HR = 1.30, 95% CI = 1.18-1.43). Overall, the relative risk of AF was 25% lower in blacks than whites after adjustment for age and sex (HR = 0.75, 95% CI = 0.64-0.87) and 45% lower after adjustment for all considered risk factors (HR = 0.55, 95% CI = 0.35-0.88). Different associations of the considered risk factors and incident AF by race do not explain the lower incidence of AF in blacks.
Keywords: Aged; Atrial Fibrillation; Continental Population Groups; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence; Risk Assessment; Risk Factors; Stroke; United States

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls. - Simone, Benedetto; De Stefano, Valerio; Leoncini, Emanuele; Zacho, Jeppe; Martinelli, Ida; Emmerich, Joseph; Rossi, Elena; Folsom, Aaron R; Almawi, Wassim Y; Scarabin, Pierre Y; den Heijer, Martin; Cushman, Mary; et al. (Eur J Epidemiol, 2013)
Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden, FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95 % confidence intervals [CI]: 0.98-1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR = 4.22; 95 % CI: 3.35-5.32; and OR = 2.79;95 % CI: 2.25-3.46, respectively), in double heterozygotes (OR = 3.42; 95 %CI 1.64-7.13), and in homozygous FVL or PT20210A (OR = 11.45; 95 %CI: 6.79-19.29; and OR: 6.74 (CI 95 % 2.19-20.72), respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤ 45 years (p value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.
Keywords: Case-Control Studies; Factor V; Genetic Predisposition to Disease; Humans; Methylenetetrahydrofolate Reductase (NADPH2); Prothrombin; Risk Factors; Venous Thromboembolism

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Sleep and insulin-like growth factors in the Cardiovascular Health Study. - Shah, Neomi; Rice, Tom; Tracy, Daniel; Rohan, Thomas; Bůzková, Petra; Newman, Anne; Kaplan, Robert C (J Clin Sleep Med, 2013)
STUDY OBJECTIVES: Sleep and sleep disordered breathing (obstructive sleep apnea [OSA]) are known to affect the growth hormone/insulin-like growth factor (GH/IGF) axis. There are few relevant population studies in this area, particularly in the elderly. We conducted this study to investigate the relationship between sleep (architecture and OSA) and circulating IGF-I (insulin-like growth factor-1), IGFBP-1 (insulin-like growth factor binding protein-1), and IGFBP-3 (insulin-like growth factor binding protein-3) levels in an elderly population. DESIGN SETTING: Cross-sectional analysis of participants from the year 9 visit of the Cardiovascular Health Study (CHS) who were enrolled in the Sleep Heart Health Study (SHHS). PATIENTS OR PARTICIPANTS: 1,233 elderly participants from the CHS and SHHS. MEASUREMENTS AND RESULTS: The mean age of males (n = 526) and females (n = 697) was 77 years. The mean value of IGF-I (ng/mL) in males was 112.4 vs. 97.1 in females (p < 0.01). Mean IGFBP-1 and IGFBP-3 levels were higher in females than males (p < 0.01). As expected, slow wave sleep was better preserved in females compared to males (22% total sleep time vs. 9% total sleep time, p < 0.01). Furthermore, as expected, OSA (apneahypopnea index [AHI] ≥ 5/h) was more prevalent in males compared to females (60% vs. 46%, p < 0.01). Multivariable linear regression was used to determine the relationship between objective sleep parameters and circulating IGF-I, IGFBP-1, and IGFBP-3 levels, with adjustment for age, sex, race, BMI, diabetes, estrogen use, progestin use, and physical activity. We did not detect a significant association between slow wave sleep (SWS) (per 5 min) and IGF-I, IGFBP-1, and IGFBP-3 levels (ng/mL). We found no significant linear association between OSA (AHI ≥ 5/h) and IGF-I, IGFBP-1, and IGFBP-3 levels. Gender-stratification of the entire cohort did not alter these findings. Sensitivity analyses excluding diabetics revealed that moderate OSA (AHI ≥ 5 and < 15) is inversely associated with IGFBP-3 levels in women. Conclusions The relationship between SWS and GH/IGF system is not significant in the elderly. Furthermore, OSA does not appear to adversely influence the GH/IGF axis, as reported in younger individuals. Whether our study findings are due to diminished GH/IGF-I axis activity in elderly needs further investigation by replication in other large population based elderly cohorts.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Geriatric Assessment; Health Surveys; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Sex Distribution; Sleep; Sleep Apnea, Obstructive; Somatomedins; United States

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Total and high-molecular-weight adiponectin and risk of coronary heart disease and ischemic stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Djoussé, Luc; Zieman, Susan J; Mukamal, Kenneth J; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Gottdiener, John S; Ix, Joachim H (J Clin Endocrinol Metab, 2013)
CONTEXT: Adiponectin is atheroprotective in the laboratory, but prospective studies have shown opposite associations with cardiovascular disease (CVD) in healthy middle-aged populations (protective) and older cohorts (adverse). Whether this relates to different proportions of high-molecular-weight (HMW) adiponectin is unknown. OBJECTIVE: The aim of the study was to test the hypothesis that total adiponectin is directly associated, but HMW adiponectin is inversely related, with CVD in older adults. DESIGN, SETTING, AND PARTICIPANTS: We evaluated 3290 participants free of prevalent CVD in a longitudinal cohort study of U.S. adults aged 65 yr and older. MAIN OUTCOME MEASURES: We measured incident CVD (n = 1291), comprising coronary heart disease and ischemic stroke. RESULTS: Total and HMW adiponectin were tightly correlated (r = 0.94). Cubic splines adjusted for potential confounders revealed that the associations of total and HMW adiponectin with CVD were U-shaped, with inflection points of 20 and 10 mg/liter, respectively. After controlling for potential confounding, levels of total and HMW adiponectin below these cutpoints tended to be inversely associated with incident CVD, driven by their significant or near-significant relations with coronary heart disease [hazard ratio (HR), 0.85 per sd increase; 95% confidence interval (CI), 0.75-96; and HR, 0.87; 95% CI, 0.75-1.01, respectively]. These associations were abrogated by additional inclusion of putative metabolic intermediates. Above these cutpoints, however, both total and HMW adiponectin were significantly directly associated with CVD after adjustment for confounders and, particularly, mediators (HR, 1.20 per sd increase; 95% CI, 1.06-1.35; and HR, 1.12; 95% CI, 1.02-1.24, respectively). CONCLUSION: In community-living elders, total and HMW adiponectin showed similar U-shaped relationships with CVD. The inverse relation in the lower range, but not the direct association at the higher end, disappeared after inclusion of putative intermediates, suggesting that high levels may reflect adverse processes separate from adiponectin's beneficial glycometabolic properties.
Keywords: Adiponectin; Adult; Aged; Aged, 80 and over; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Male; Molecular Weight; Residence Characteristics; Risk Factors; Stroke

Trans-ethnic fine-mapping of lipid loci identifies population-specific signals and allelic heterogeneity that increases the trait variance explained. - Wu, Ying; Waite, Lindsay L; Jackson, Anne U; Sheu, Wayne H-H; Buyske, Steven; Absher, Devin; Arnett, Donna K; Boerwinkle, Eric; Bonnycastle, Lori L; Carty, Cara L; Cheng, Iona; Cochran, Barbara; et al. (PLoS Genet, 2013)
Genome-wide association studies (GWAS) have identified ~100 loci associated with blood lipid levels, but much of the trait heritability remains unexplained, and at most loci the identities of the trait-influencing variants remain unknown. We conducted a trans-ethnic fine-mapping study at 18, 22, and 18 GWAS loci on the Metabochip for their association with triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), respectively, in individuals of African American (n = 6,832), East Asian (n = 9,449), and European (n = 10,829) ancestry. We aimed to identify the variants with strongest association at each locus, identify additional and population-specific signals, refine association signals, and assess the relative significance of previously described functional variants. Among the 58 loci, 33 exhibited evidence of association at P<1 × 10(-4) in at least one ancestry group. Sequential conditional analyses revealed that ten, nine, and four loci in African Americans, Europeans, and East Asians, respectively, exhibited two or more signals. At these loci, accounting for all signals led to a 1.3- to 1.8-fold increase in the explained phenotypic variance compared to the strongest signals. Distinct signals across ancestry groups were identified at PCSK9 and APOA5. Trans-ethnic analyses narrowed the signals to smaller sets of variants at GCKR, PPP1R3B, ABO, LCAT, and ABCA1. Of 27 variants reported previously to have functional effects, 74% exhibited the strongest association at the respective signal. In conclusion, trans-ethnic high-density genotyping and analysis confirm the presence of allelic heterogeneity, allow the identification of population-specific variants, and limit the number of candidate SNPs for functional studies.
Keywords: African Americans; Apolipoproteins A; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Proprotein Convertases; Serine Endopeptidases; Triglycerides

Advanced glycation/glycoxidation endproduct carboxymethyl-lysine and incidence of coronary heart disease and stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Ix, Joachim H; Mukamal, Kenneth J; Djoussé, Luc; Tracy, Russell P; Siscovick, David S; Psaty, Bruce M; Zieman, Susan J (Atherosclerosis, 2014)
BACKGROUND: Advanced glycation/glycoxidation endproducts (AGEs) accumulate in settings of increased oxidative stress--such as diabetes, chronic kidney disease and aging--where they promote vascular stiffness and atherogenesis, but the prospective association between AGEs and cardiovascular events in elders has not been previously examined. METHODS: To test the hypothesis that circulating levels of N(ɛ)-carboxymethyl-lysine (CML), a major AGE, increase the risk of incident coronary heart disease and stroke in older adults, we measured serum CML by immunoassay in 2111 individuals free of prevalent cardiovascular disease participating in a population-based study of U.S. adults ages 65 and older. RESULTS: During median follow-up of 9.1 years, 625 cardiovascular events occurred. CML was positively associated with incident cardiovascular events after adjustment for age, sex, race, systolic blood pressure, anti-hypertensive treatment, diabetes, smoking status, triglycerides, albumin, and self-reported health status (hazard ratio [HR] per SD [0.99 pmol/l] increase=1.11, 95% confidence interval [CI]=1.03-1.19). This association was not materially attenuated by additional adjustment for C-reactive protein, estimated glomerular filtration rate (eGFR), and urine albumin/creatinine ratio. Findings were similar for the component endpoints of coronary heart disease and stroke. CONCLUSIONS: In this large older cohort, CML was associated with an increased risk of cardiovascular events independent of a wide array of potential confounders and mediators. Although the moderate association limits CML's value for risk prediction, these community-based findings provide support for clinical trials to test AGE-lowering therapies for cardiovascular prevention in this population.
Keywords: Aged; Albumins; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Creatinine; Female; Glomerular Filtration Rate; Glycation End Products, Advanced; Humans; Immunoassay; Incidence; Lysine; Male; Oxidative Stress; Proportional Hazards Models; Stroke; Treatment Outcome

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of a cystatin C gene variant with cystatin C levels, CKD, and risk of incident cardiovascular disease and mortality. - O'Seaghdha, Conall M; Tin, Adrienne; Yang, Qiong; Katz, Ronit; Liu, Yongmei; Harris, Tamara; Astor, Brad; Coresh, Josef; Fox, Caroline S; Kao, W H Linda; Shlipak, Michael G (Am J Kidney Dis, 2014)
BACKGROUND: Carriers of the T allele of the single-nucleotide polymorphism rs13038305 tend to have lower cystatin C levels and higher cystatin C-based estimated glomerular filtration rate (eGFRcys). Adjusting for this genetic effect on cystatin C concentrations may improve GFR estimation, reclassify cases of chronic kidney disease (CKD), and strengthen risk estimates for cardiovascular disease (CVD) and mortality. STUDY DESIGN: Observational. SETTING & POPULATION: 4 population-based cohorts: Atherosclerosis Risk in Communities (ARIC), Cardiovascular Health (CHS), Framingham Heart (FHS), and Health, Aging, and Body Composition (Health ABC) studies. PREDICTORS: We estimated the association of rs13038305 with eGFRcys and serum creatinine-based eGFR (eGFRcr) and performed longitudinal analyses of the associations of eGFRcys with mortality and cardiovascular events following adjustment for rs13038305. OUTCOMES: We assessed reclassification by genotype-adjusted eGFRcys across CKD categories: <45, 45-59, 60-89, and ≥ 90 mL/min/1.73 m(2). We compared mortality and CVD outcomes in those reclassified to a worse eGFRcys category with those unaffected. Results were combined using fixed-effect inverse-variance meta-analysis. RESULTS: In 14,645 participants, each copy of the T allele of rs13038305 (frequency, 21%) was associated with a 6.4% lower cystatin C concentration, 5.5-mL/min/1.73 m(2) higher eGFRcys, and 36% [95% CI, 29%-41%] lower odds of CKD. Associations with CVD (HR, 1.17; 95% CI, 1.14-1.20) and mortality (HR, 1.22; 95% CI, 1.19-1.24) per 10-mL/min/1.73 m(2) lower eGFRcys were similar with or without rs13038305 adjustment. 1,134 (7.7%) participants were reclassified to a worse CKD category following rs13038305 adjustment, and rates of CVD and mortality were higher in individuals who were reclassified. However, the overall net reclassification index was not significant for either outcome, at 0.009 (95% CI, -0.003 to 0.022) for mortality and 0.014 (95% CI, 0.0 to 0.028) for CVD. LIMITATIONS: rs13038305 explains only a small proportion of cystatin C variation. CONCLUSIONS: Statistical adjustment can correct a genetic bias in GFR estimates based on cystatin C in carriers of the T allele of rs13038305 and result in changes in disease classification. However, on a population level, the effects on overall reclassification of CKD status are modest.
Keywords: Aged; Bias; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Genetic Variation; Glomerular Filtration Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Risk Assessment; Risk Factors; Severity of Illness Index; Statistics as Topic; Survival Rate

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Circulating fibrosis biomarkers and risk of atrial fibrillation: The Cardiovascular Health Study (CHS). - Rosenberg, Michael A; Maziarz, Marlena; Tan, Alex Y; Glazer, Nicole L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Djoussé, Luc; Siscovick, David S; Heckbert, Susan R; Mukamal, Kenneth J (Am Heart J, 2014)
BACKGROUND: Cardiac fibrosis is thought to play a central role in the pathogenesis of atrial fibrillation (AF). Retrospective studies have suggested that circulating fibrosis biomarkers are associated with AF, but prospective studies are limited. METHODS: We measured circulating levels of 2 fibrosis biomarkers, procollagen type III, N-terminal propeptide (PIIINP) and transforming growth factor β1 among participants of the CHS, a population-based study of older Americans. We used Cox proportional hazards and competing risks models to examine adjusted risk of incident AF over a median follow-up of 8.8 years. RESULTS: Levels of PIIINP were assessed in 2,935 participants, of whom 767 developed AF. Compared with the median PIIINP level (4.45 μg/L), adjusted hazard ratios (95% CIs) were 0.85 (0.72-1.00) at the 10th percentile, 0.93 (0.88-0.99) at the 25th percentile, 1.04 (0.95-1.04) at the 75th percentile, and 1.07 (0.90-1.26) at the 90th. Transforming growth factor β1 levels, assessed in 1,538 participants with 408 cases of incident AF, were not associated with AF risk. CONCLUSION: In older adults, PIIINP levels were associated with risk of incident AF in a complex manner, with an association that appeared to be positive up to median levels but with little relationship beyond that. Further studies are required to confirm and possibly delineate the mechanism for this relationship.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Cardiomyopathies; Electrocardiography; Enzyme-Linked Immunosorbent Assay; Female; Fibrosis; Follow-Up Studies; Humans; Incidence; Male; Peptide Fragments; Procollagen; Prospective Studies; Risk Factors; Time Factors; Transforming Growth Factor beta1; United States

Circulating levels of carboxy‐methyl‐lysine (CML) are associated with hip fracture risk: the Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Zieman, Susan J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Tracy, Russell P; Siscovick, David S; Cauley, Jane A; Mukamal, Kenneth J (J Bone Miner Res, 2014)
Advanced glycation end products (AGE) in bone tissue are associated with impaired biomechanical properties and increased fracture risk. Here we examine whether serum levels of the AGE carboxy‐methyl‐lysine (CML) are associated with risk of hip fracture.We followed 3373 participants from the Cardiovascular Health Study (age 78 years; range, 68–102 years; 39.8% male) for a median of 9.22 years (range, 0.01–12.07 years). Rates of incident hip fracture were calculated by quartiles of baseline CML levels, and hazard ratios were adjusted for covariates associated with hip fracture risk. A subcohort of 1315 participants had bone mineral density (BMD)measurement. There were 348 hip fractures during follow‐up, with incidence rates of hip fracture by CML quartiles of 0.94, 1.34, 1.18, and 1.69 per 100 participant‐years. The unadjusted hazard ratio of hip fracture increased with each 1 SD increase (189 ng/mL) of CML level (hazard ratio, 1.27; 95% confidence interval [CI], 1.16–1.40]; p<0.001). Sequential adjustment for age, gender, race/ethnicity,body mass index (BMI), smoking, alcohol consumption, prevalent coronary heart disease (CHD), energy expenditure, and estimated glomerular filtration rate (based on cystatin C), moderately attenuated the hazard ratio for fracture (1.17; 95% CI, 1.05–1.31; p=0.006).In the cohort with BMD testing, total hip BMD was not significantly associated with CML levels. We conclude that increasing levels of CML are associated with hip fracture risk in older adults, independent of hip BMD. These results implicate AGE in the pathogenesis of hip fractures.
Keywords: Age Factors; Aged; Female; Follow-Up Studies; Glycation End Products, Advanced; Hip Fractures; Humans; Incidence; Lysine; Male; Prospective Studies; Retrospective Studies; Risk Factors

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Decline in estimated glomerular filtration rate and subsequent risk of end-stage renal disease and mortality. - Coresh, Josef; Turin, Tanvir Chowdhury; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Appel, Lawrence J; Arima, Hisatomi; Chadban, Steven J; Cirillo, Massimo; Djurdjev, Ognjenka; Green, Jamie A; Heine, Gunnar H; et al. (JAMA, 2014)
IMPORTANCE: The established chronic kidney disease (CKD) progression end point of end-stage renal disease (ESRD) or a doubling of serum creatinine concentration (corresponding to a change in estimated glomerular filtration rate [GFR] of −57% or greater) is a late event. OBJECTIVE: To characterize the association of decline in estimated GFR with subsequent progression to ESRD with implications for using lesser declines in estimated GFR as potential alternative end points for CKD progression. Because most people with CKD die before reaching ESRD, mortality risk also was investigated. DATA SOURCES AND STUDY SELECTION: Individual meta-analysis of 1.7 million participants with 12,344 ESRD events and 223,944 deaths from 35 cohorts in the CKD Prognosis Consortium with a repeated measure of serum creatinine concentration over 1 to 3 years and outcome data. DATA EXTRACTION AND SYNTHESIS: Transfer of individual participant data or standardized analysis of outputs for random-effects meta-analysis conducted between July 2012 and September 2013, with baseline estimated GFR values collected from 1975 through 2012. MAIN OUTCOMES AND MEASURES: End-stage renal disease (initiation of dialysis or transplantation) or all-cause mortality risk related to percentage change in estimated GFR over 2 years, adjusted for potential confounders and first estimated GFR. RESULTS: The adjusted hazard ratios (HRs) of ESRD and mortality were higher with larger estimated GFR decline. Among participants with baseline estimated GFR of less than 60 mL/min/1.73 m2, the adjusted HRs for ESRD were 32.1 (95% CI, 22.3-46.3) for changes of −57% in estimated GFR and 5.4 (95% CI, 4.5-6.4) for changes of −30%. However, changes of −30% or greater (6.9% [95% CI, 6.4%-7.4%] of the entire consortium) were more common than changes of −57% (0.79% [95% CI, 0.52%-1.06%]). This association was strong and consistent across the length of the baseline period (1 to 3 years), baseline estimated GFR, age, diabetes status, or albuminuria. Average adjusted 10-year risk of ESRD (in patients with a baseline estimated GFR of 35 mL/min/1.73 m2) was 99% (95% CI, 95%-100%) for estimated GFR change of −57%, was 83% (95% CI, 71%-93%) for estimated GFR change of −40%, and was 64% (95% CI, 52%-77%) for estimated GFR change of −30% vs 18% (95% CI, 15%-22%) for estimated GFR change of 0%. Corresponding mortality risks were 77% (95% CI, 71%-82%), 60% (95% CI, 56%-63%), and 50% (95% CI, 47%-52%) vs 32% (95% CI, 31%-33%), showing a similar but weaker pattern. CONCLUSIONS AND RELEVANCE: Declines in estimated GFR smaller than a doubling of serum creatinine concentration occurred more commonly and were strongly and consistently associated with the risk of ESRD and mortality, supporting consideration of lesser declines in estimated GFR (such as a 30% reduction over 2 years) as an alternative end point for CKD progression.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Creatinine; Disease Progression; Endpoint Determination; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Reference Values; Risk

Disability and recovery of independent function in obstructive lung disease: the cardiovascular health study. - Fan, Vincent S; Locke, Emily R; Diehr, Paula; Wilsdon, Anthony; Enright, Paul; Yende, Sachin; Avdalovic, Mark; Barr, Graham; Kapur, Vishesh K; Thomas, Rachel; Krishnan, Jerry A; Lovasi, Gina; et al. (Respiration, 2014)
BACKGROUND: Chronic obstructive lung disease frequently leads to disability. Older patients may experience transitions between states of disability and independence over time. OBJECTIVE: To identify factors associated with transition between states of disability and independent function in obstructive lung disease. METHODS: We analyzed data on 4,394 participants in the Cardiovascular Health Study who completed prebronchodilator spirometry. We calculated the 1-year probability of developing and resolving impairment in ≥1 instrumental activity of daily living (IADL) or ≥1 activity of daily living (ADL) using transition probability analysis. We identified factors associated with resolving disability using relative risk (RR) regression. RESULTS: The prevalence of IADL impairment was higher with moderate (23.9%) and severe (36.9%) airflow obstruction compared to normal spirometry (22.5%; p < 0.001). Among participants with severe airflow obstruction, 23.5% recovered independence in IADLs and 40.5% recovered independence in ADLs. In the adjusted analyses, airflow obstruction predicted the development of IADL, but not ADL impairment. Participants with severe airflow obstruction were less likely to resolve IADL impairment [RR 0.67 and 95% confidence interval (CI) 0.49-0.94]. Compared to the most active individuals (i.e. who walked ≥28 blocks per week), walking less was associated with a decreased likelihood of resolving IADL impairment (7-27 blocks: RR 0.81 and 95% CI 0.69-0.86 and <7 blocks: RR 0.73 and 95% CI 0.61-0.86). Increased strength (RR 1.16 and 95% CI 1.05-1.29) was associated with resolving IADL impairment. CONCLUSIONS: Disability is common in older people, especially in those with severe airflow obstruction. Increased physical activity and muscle strength are associated with recovery. Research is needed on interventions to improve these factors among patients with obstructive lung disease and disability.
Keywords: Activities of Daily Living; Aged; Cardiac Rehabilitation; Cardiovascular Diseases; Disability Evaluation; Exercise Test; Female; Humans; Independent Living; Longitudinal Studies; Male; Motor Activity; Muscle Strength; Outcome Assessment (Health Care); Pulmonary Disease, Chronic Obstructive; Recovery of Function; Risk Assessment; Severity of Illness Index; Spirometry; United States

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Enhancing case ascertainment of Parkinson's disease using Medicare claims data in a population-based cohort: the Cardiovascular Health Study. - Ton, Thanh G N; Biggs, Mary Lou; Comer, Diane; Curtis, Lesley; Hu, Shu-Ching; Thacker, Evan L; Searles Nielsen, Susan; Delaney, Joseph A; Landsittel, Douglas; Longstreth, William T; Checkoway, Harvey; Jain, Samay (Pharmacoepidemiol Drug Saf, 2014)
PURPOSE: We sought to improve a previous algorithm to ascertain Parkinson's disease (PD) in the Cardiovascular Health Study by incorporating additional data from Medicare outpatient claims. We compared our results to the previous algorithm in terms of baseline prevalence and incidence of PD, as well as associations with baseline smoking characteristics. METHODS: Our original case ascertainment used self-reported diagnosis, antiparkinsonian medication, and hospitalization discharge International Classification of Diseases-Ninth version code. In this study, we incorporated additional data from fee-for-service Medicare claims, extended follow-up time, review of hospitalization records, and adjudicated cause of death. Two movement disorders specialists adjudicated final PD status. We used logistic regression models and controlled for age, sex, African American race, and education. RESULTS: We identified 75 additional cases but reclassified 80 previously identified cases as not having PD. We observed significant inverse association with smoking status (odds ratio = 0.42; 95% confidence interval (CI) = 0.22, 0.79), and inverse linear trends with pack-years (p = 0.005), and cigarettes per day (p = 0.019) with incident PD. All estimates were stronger than those from the previous algorithm. CONCLUSIONS: Our enhanced method did not alter prevalence and incidence estimates compared with our previous algorithm. However, our enhanced method provided stronger estimates of association, potentially due to reduced level of disease misclassification.
Keywords: Aged; Aged, 80 and over; Algorithms; Antiparkinson Agents; Cohort Studies; Databases, Factual; Female; Hospitalization; Humans; Incidence; Logistic Models; Male; Medicare; Parkinson Disease; Prevalence; Prospective Studies; Smoking; Time Factors; United States

Estimated GFR and circulating 24,25-dihydroxyvitamin D3 concentration: a participant-level analysis of 5 cohort studies and clinical trials. - de Boer, Ian H; Sachs, Michael C; Chonchol, Michel; Himmelfarb, Jonathan; Hoofnagle, Andrew N; Ix, Joachim H; Kremsdorf, Robin A; Lin, Yvonne S; Mehrotra, Rajnish; Robinson-Cohen, Cassianne; Siscovick, David S; Steffes, Michael W; et al. (Am J Kidney Dis, 2014)
BACKGROUND: Decreased glomerular filtration rate (GFR) leads to reduced production of 1,25-dihydroxyvitamin D3 from 25-hydroxyvitamin D3 (25[OH]D3). Effects of low GFR on vitamin D catabolism are less well understood. We tested associations of estimated GFR (eGFR) with the circulating concentration of 24,25-dihydroxyvitamin D3 (24,25[OH]2D3), the most abundant product of 25(OH)D3 catabolism, across populations with a wide range of GFRs. STUDY DESIGN: Cross-sectional study. SETTING & PARTICIPANTS: 9,596 participants in 5 cohort studies and clinical trials: the Diabetes Control and Complications Trial (N=1,193), Multi-Ethnic Study of Atherosclerosis (N=6,470), Cardiovascular Health Study (N=932), Seattle Kidney Study (N=289), and Hemodialysis Study (N=712). PREDICTOR: eGFR. OUTCOME: Circulating 24,25(OH)2D3 concentration. MEASUREMENTS: GFR was estimated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration equation. Vitamin D metabolites were measured by mass spectrometry. RESULTS: Circulating 24,25(OH)2D3 concentration was correlated with circulating 25(OH)D3 concentration (Pearson r range, 0.64-0.88). This correlation was weaker with lower eGFRs. Moreover, the increment in 24,25(OH)2D3 concentration associated with higher 25(OH)D3 concentration (slope) was lower with lower eGFRs: 2.06 (95% CI, 2.01-2.10), 1.77 (95% CI, 1.74-1.81), 1.55 (95% CI, 1.48-1.62), 1.17 (95% CI, 1.05-1.29), 0.92 (95% CI, 0.74-1.10), 0.61 (95% CI, 0.22-1.00), and 0.37 (95% CI, 0.35-0.39) ng/mL of 24,25(OH)2D3 per 10 ng/mL of 25(OH)D3 for eGFRs≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m2 and end-stage renal disease treated with hemodialysis, respectively. As a result, at a 25(OH)D3 concentration of 20 ng/mL, mean 24,25(OH)2D3 concentrations were 2.92 (95% CI, 2.87-2.96), 2.68 (95% CI, 2.64-2.72), 2.35 (95% CI, 2.26-2.45), 1.92 (95% CI, 1.74-2.10), 1.69 (95% CI, 1.43-1.95), 1.14 (95% CI, 0.62-1.66), and 1.04 (95% CI,1.02-1.07) ng/mL for each category, respectively. This interaction was independent of other relevant clinical characteristics. Race, diabetes, urine albumin excretion, and circulating parathyroid hormone and fibroblast growth factor 23 concentrations more modestly modified the association of 24,25(OH)2D3 with 25(OH)D3. LIMITATIONS: Lack of direct pharmacokinetic measurements of vitamin D catabolism. CONCLUSIONS: Lower eGFR is associated strongly with reduced vitamin D catabolism, as measured by circulating 24,25(OH)2D3 concentration.
Keywords: 24,25-Dihydroxyvitamin D 3; Adult; Aged; Aged, 80 and over; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Observational Studies as Topic; Randomized Controlled Trials as Topic; Young Adult

Fibrosis-related biomarkers and incident cardiovascular disease in older adults: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Sicovick, David S; Tracy, Russell P; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Fibrotic changes in the heart and arteries have been implicated in a diverse range of cardiovascular diseases (CVD), but whether circulating biomarkers that reflect fibrosis are associated with CVD is unknown. METHODS AND RESULTS: We determined the associations of 2 biomarkers of fibrosis, transforming growth factor- β (TGF-β), and procollagen type III N-terminal propeptide (PIIINP), with incident heart failure, myocardial infarction, and stroke among community-living older adults in the Cardiovascular Health Study. We measured circulating TGF-β (n=1371) and PIIINP (n=2568) from plasma samples collected in 1996 and ascertained events through 2010. Given TGF-β's pleiotropic effects on inflammation and fibrogenesis, we investigated potential effect modification by C-reactive protein in secondary analyses. After adjustment for sociodemographic, clinical, and biochemical risk factors, PIIINP was associated with total CVD (hazard ratio [HR] per SD=1.07; 95% confidence interval [CI], 1.01-1.14) and heart failure (HR per SD=1.08; CI, 1.01-1.16) but not myocardial infarction or stroke. TGF-β was not associated with any CVD outcomes in the full cohort but was associated with total CVD (HR per SD=1.16; CI, 1.02-1.31), heart failure (HR per SD=1.16; CI, 1.01-1.34), and stroke (HR per SD=1.20; CI, 1.01-1.42) among individuals with C-reactive protein above the median, 2.3 mg/L (P interaction <0.05). CONCLUSIONS: Our findings provide large-scale, prospective evidence that circulating biomarkers of fibrosis, measured in community-living individuals late in life, are associated with CVD. Further research on whether TGF-β has a stronger fibrogenic effect in the setting of inflammation is warranted.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Female; Fibrosis; Heart Failure; Humans; Incidence; Male; Myocardial Infarction; Peptide Fragments; Procollagen; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Time Factors; Transforming Growth Factor beta; United States

Fibrosis-related biomarkers and risk of total and cause-specific mortality: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; Tracy, Russell P; et al. (Am J Epidemiol, 2014)
Fibrosis has been implicated in diverse diseases of the liver, kidney, lungs, and heart, but its importance as a risk factor for mortality remains unconfirmed. We determined the prospective associations of 2 complementary biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with total and cause-specific mortality risks among community-living older adults in the Cardiovascular Health Study (1996-2010). We measured circulating TGF-β and PIIINP levels in plasma samples collected in 1996 and ascertained the number of deaths through 2010. Both TGF-β and PIIINP were associated with elevated risks of total and pulmonary mortality after adjustment for sociodemographic, clinical, and biochemical risk factors. For total mortality, the hazard ratios per doubling of TGF-β and PIIINP were 1.09 (95% confidence interval (CI): 1.01, 1.17; P = 0.02) and 1.14 (CI: 1.03, 1.27; P = 0.01), respectively. The corresponding hazard ratios for pulmonary mortality were 1.27 (CI: 1.01, 1.60; P = 0.04) for TGF-β and 1.52 (CI: 1.11, 2.10; P = 0.01) for PIIINP. Associations of TGF-β and PIIINP with total and pulmonary mortality were strongest among individuals with higher C-reactive protein concentrations (P for interaction < 0.05). Our findings provide some of the first large-scale prospective evidence that circulating biomarkers of fibrosis measured late in life are associated with death.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cause of Death; Female; Fibrosis; Follow-Up Studies; Humans; Likelihood Functions; Male; Multivariate Analysis; Peptide Fragments; Procollagen; Proportional Hazards Models; Prospective Studies; Risk Factors; Transforming Growth Factor beta

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gender and telomere length: systematic review and meta-analysis. - Gardner, Michael; Bann, David; Wiley, Laura; Cooper, Rachel; Hardy, Rebecca; Nitsch, Dorothea; Martin-Ruiz, Carmen; Shiels, Paul; Sayer, Avan Aihie; Barbieri, Michelangela; Bekaert, Sofie; Bischoff, Claus; et al. (Exp Gerontol, 2014)
BACKGROUND: It is widely believed that females have longer telomeres than males, although results from studies have been contradictory. METHODS: We carried out a systematic review and meta-analyses to test the hypothesis that in humans, females have longer telomeres than males and that this association becomes stronger with increasing age. Searches were conducted in EMBASE and MEDLINE (by November 2009) and additional datasets were obtained from study investigators. Eligible observational studies measured telomeres for both females and males of any age, had a minimum sample size of 100 and included participants not part of a diseased group. We calculated summary estimates using random-effects meta-analyses. Heterogeneity between studies was investigated using sub-group analysis and meta-regression. RESULTS: Meta-analyses from 36 cohorts (36,230 participants) showed that on average females had longer telomeres than males (standardised difference in telomere length between females and males 0.090, 95% CI 0.015, 0.166; age-adjusted). There was little evidence that these associations varied by age group (p=1.00) or cell type (p=0.29). However, the size of this difference did vary by measurement methods, with only Southern blot but neither real-time PCR nor Flow-FISH showing a significant difference. This difference was not associated with random measurement error. CONCLUSIONS: Telomere length is longer in females than males, although this difference was not universally found in studies that did not use Southern blot methods. Further research on explanations for the methodological differences is required.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Sex Factors; Telomere

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

A genetic association study of D-dimer levels with 50K SNPs from a candidate gene chip in four ethnic groups. - Weng, Lu-Chen; Tang, Weihong; Rich, Stephen S; Smith, Nicholas L; Redline, Susan; O'Donnell, Christopher J; Basu, Saonli; Reiner, Alexander P; Delaney, Joseph A; Tracy, Russell P; Palmer, Cameron D; Young, Taylor; et al. (Thromb Res, 2014)
INTRODUCTION: D-dimer, a fibrin degradation product, is related to risk of cardiovascular disease and venous thromboembolism. Genetic determinants of D-dimer are not well characterized; notably, few data have been reported for African American (AA), Asian, and Hispanic populations. MATERIALS AND METHODS: We conducted a large-scale candidate gene association study to identify variants in genes associated with D-dimer levels in multi-ethnic populations. Four cohorts, comprising 6,848 European Americans (EAs), 2,192 AAs, 670 Asians, and 1,286 Hispanics in the National Heart, Lung, and Blood Institute Candidate Gene Association Resource consortium, were assembled. Approximately 50,000 genotyped single nucleotide polymorphisms (SNPs) in 2,000 cardiovascular disease gene loci were analyzed by linear regression, adjusting for age, sex, study site, and principal components in each cohort and ethnic group. Results across studies were combined within each ethnic group by meta-analysis. RESULTS: Twelve SNPs in coagulation factor V (F5) and 3 SNPs in the fibrinogen alpha chain (FGA) were significantly associated with D-dimer level in EAs with p<2.0×10(-6). The signal for the most associated SNP in F5 (rs6025, factor V Leiden) was replicated in Hispanics (p=0.023), while that for the top functional SNP in FGA (rs6050) was replicated in AAs (p=0.006). No additional SNPs were significantly associated with D-dimer. CONCLUSIONS: Our study replicated previously reported associations of D-dimer with SNPs in F5 and FGA in EAs; we demonstrated replication of the association of D-dimer with FGA rs6050 in AAs and the factor V Leiden variant in Hispanics.
Keywords: Adult; Aged; Cardiovascular Diseases; Ethnic Groups; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

The influence of sex on cardiovascular outcomes associated with diabetes among older black and white adults. - Vimalananda, Varsha G; Biggs, Mary L; Rosenzweig, James L; Carnethon, Mercedes R; Meigs, James B; Thacker, Evan L; Siscovick, David S; Mukamal, Kenneth J (J Diabetes Complications, 2014)
AIMS: It is unknown whether sex differences in the association of diabetes with cardiovascular outcomes vary by race. We examined sex differences in the associations of diabetes with incident congestive heart failure (CHF) and coronary heart disease (CHD) between older black and white adults. METHODS: We analyzed data from the Cardiovascular Health Study (CHS), a prospective cohort study of community-dwelling individuals aged ≥65 from four US counties. We included 4817 participants (476 black women, 279 black men, 2447 white women and 1625 white men). We estimated event rates and multivariate-adjusted hazard ratios for incident CHF, CHD, and all-cause mortality by Cox regression and competing risk analyses. RESULTS: Over a median follow-up of 12.5years, diabetes was more strongly associated with CHF among black women (HR, 2.42 [95% CI, 1.70-3.40]) than black men (1.39 [0.83-2.34]); this finding did not reach statistical significance (P for interaction=0.08). Female sex conferred a higher risk for a composite outcome of CHF and CHD among black participants (2.44 [1.82-3.26]) vs. (1.44 [0.97-2.12]), P for interaction=0.03). There were no significant sex differences in the HRs associated with diabetes for CHF among whites, or for CHD or all-cause mortality among blacks or whites. The three-way interaction between sex, race, and diabetes on risk of cardiovascular outcomes was not significant (P=0.07). CONCLUSIONS: Overall, sex did not modify the cardiovascular risk associated with diabetes among older black or white adults. However, our results suggest that a possible sex interaction among older blacks merits further study.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Diabetes Complications; European Continental Ancestry Group; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Prospective Studies; Regression Analysis; Retrospective Studies; Risk Factors; Sex Factors; Survival Rate

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12. - Kilarski, Laura L; Achterberg, Sefanja; Devan, William J; Traylor, Matthew; Malik, Rainer; Lindgren, Arne; Pare, Guillame; Sharma, Pankaj; Slowik, Agniesczka; Thijs, Vincent; Walters, Matthew; Worrall, Bradford B; et al. (Neurology, 2014)
OBJECTIVES: To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases. METHODS: Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a further 8,480 cases and 56,032 controls in the METASTROKE consortium. A final in silico "look-up" of 2 single nucleotide polymorphisms in 2,522 cases and 1,899 controls was performed. Associations were also examined in 1,088 cases with intracerebral hemorrhage and 1,102 controls. RESULTS: In an overall analysis of 17,970 cases of ischemic stroke and 70,764 controls, we identified a novel association on chromosome 12q24 (rs10744777, odds ratio [OR] 1.10 [1.07-1.13], p = 7.12 × 10(-11)) with ischemic stroke. The association was with all ischemic stroke rather than an individual stroke subtype, with similar effect sizes seen in different stroke subtypes. There was no association with intracerebral hemorrhage (OR 1.03 [0.90-1.17], p = 0.695). CONCLUSION: Our results show, for the first time, a genetic risk locus associated with ischemic stroke as a whole, rather than in a subtype-specific manner. This finding was not associated with intracerebral hemorrhage.
Keywords: Brain Ischemia; Cerebral Hemorrhage; Chromosomes, Human, Pair 12; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Meta-analysis of loci associated with age at natural menopause in African-American women. - Chen, Christina T L; Liu, Ching-Ti; Chen, Gary K; Andrews, Jeanette S; Arnold, Alice M; Dreyfus, Jill; Franceschini, Nora; Garcia, Melissa E; Kerr, Kathleen F; Li, Guo; Lohman, Kurt K; Musani, Solomon K; et al. (Hum Mol Genet, 2014)
Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis in 6510 women with African ancestry derived from 11 studies across the USA. We did not identify any additional loci significantly associated with age at menopause in African Americans. We replicated the associations between six loci and age at menopause (P-value < 0.05): AMHR2, RHBLD2, PRIM1, HK3/UMC1, BRSK1/TMEM150B and MCM8. In addition, associations of 14 loci are directionally consistent with previous reports. We provide evidence that genetic variants influencing reproductive traits identified in European populations are also important in women of African ancestry residing in USA.
Keywords: African Americans; Age Factors; Chromosomes, Human; European Continental Ancestry Group; Female; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Menopause; United States

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Novel gene variants predict serum levels of the cytokines IL-18 and IL-1ra in older adults. - Matteini, A M; Li, J; Lange, E M; Tanaka, T; Lange, L A; Tracy, R P; Wang, Y; Biggs, M L; Arking, D E; Fallin, M D; Chakravarti, A; Psaty, B M; et al. (Cytokine, 2014)
Activation of inflammatory pathways measured by serum inflammatory markers such as interleukin-18 (IL-18) and interleukin-1 receptor antagonist (IL-1ra) is strongly associated with the progression of chronic disease states in older adults. Given that these serum cytokine levels are in part a heritable trait, genetic variation may predict increased serum levels. Using the Cardiovascular Health Study and InCHIANTI cohorts, a genome-wide association study was performed to identify genetic variants that influence IL-18 and IL-1ra serum levels among older adults. Multiple linear regression models characterized the association between each SNP and log-transformed cytokine values. Tests for multiple independent signals within statistically significant loci were performed using haplotype analysis and regression models conditional on lead SNP in each region. Multiple SNPs were associated with these cytokines with genome-wide significance, including SNPs in the IL-18-BCO gene region of chromosome 2 for IL-18 (top SNP rs2250417, P=1.9×10(-32)) and in the IL-1 gene family region of chromosome 2 for IL-1ra (rs6743376, P=2.3×10(-26)). Haplotype tests and conditional linear regression models showed evidence of multiple independent signals in these regions. Serum IL-18 levels were also associated with a region on chromosome 2 containing the NLRC4 gene (rs12989936, P=2.7×10(-19)). These data characterize multiple robust genetic signals that influence IL-18 and IL-1ra cytokine production. In particular, the signal for serum IL-18 located on chromosome two is novel and potentially important in inflammasome triggered chronic activation of inflammation in older adults. Replication in independent cohorts is an important next step, as well as molecular studies to better understand the role of NLRC4.
Keywords: Aged; Aged, 80 and over; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Chromosomes, Human, Pair 2; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Haplotypes; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Male; Polymorphism, Single Nucleotide

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Physical activity, inflammation, and volume of the aging brain. - Braskie, M N; Boyle, C P; Rajagopalan, P; Gutman, B A; Toga, A W; Raji, C A; Tracy, R P; Kuller, L H; Becker, J T; Lopez, O L; Thompson, P M (Neuroscience, 2014)
Physical activity influences inflammation, and both affect brain structure and Alzheimer's disease (AD) risk. We hypothesized that older adults with greater reported physical activity intensity and lower serum levels of the inflammatory marker tumor necrosis factor α (TNFα) would have larger regional brain volumes on subsequent magnetic resonance imaging (MRI) scans. In 43 cognitively intact older adults (79.3±4.8 years) and 39 patients with AD (81.9±5.1 years at the time of MRI) participating in the Cardiovascular Health Study, we examined year-1 reported physical activity intensity, year-5 blood serum TNFα measures, and year-9 volumetric brain MRI scans. We examined how prior physical activity intensity and TNFα related to subsequent total and regional brain volumes. Physical activity intensity was measured using the modified Minnesota Leisure Time Physical Activities questionnaire at year 1 of the study, when all subjects included here were cognitively intact. Stability of measures was established for exercise intensity over 9 years and TNFα over 3 years in a subset of subjects who had these measurements at multiple time points. When considered together, more intense physical activity intensity and lower serum TNFα were both associated with greater total brain volume on follow-up MRI scans. TNFα, but not physical activity, was associated with regional volumes of the inferior parietal lobule, a region previously associated with inflammation in AD patients. Physical activity and TNFα may independently influence brain structure in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Brain; Female; Humans; Inflammation; Longitudinal Studies; Magnetic Resonance Imaging; Male; Motor Activity; Neuroimmunomodulation; Neuropsychological Tests; Organ Size; Parietal Lobe; Surveys and Questionnaires; Tumor Necrosis Factor-alpha

Plasma free fatty acids and risk of stroke in the Cardiovascular Health Study. - Khawaja, Owais; Maziarz, Marlena; Biggs, Mary L; Longstreth, William T; Ix, Joachim H; Kizer, Jorge R; Zieman, Susan; Tracy, Russell P; Mozaffarian, Dariush; Mukamal, Kenneth J; Siscovick, David S; Djoussé, Luc (Int J Stroke, 2014)
BACKGROUND: Although free fatty acids have been positively associated with risk factors for stroke, the role of plasma free fatty acids in the development of stroke has not been elucidated in older adults. AIMS: We sought to examine the association between plasma free fatty acids and incident stroke. METHODS: Prospective cohort of 4369 men and women≥65 years of age in the Cardiovascular Health Study. Plasma levels of free fatty acids were measured at the 1992-1993 examination and stroke events were adjudicated by a committee of experts including neurologists and neuroradiologists. Cox regression was used to estimate the relative risk of stroke associated with free fatty acids concentrations. RESULTS: The average age among participants was 75±5·2 years. During a median follow-up of 11·4 years, 732 incident strokes occurred. The crude incidence rates of stroke were 14·5, 14·9, and 17·6 per 1000 person-years across increasing tertiles of plasma free fatty acids. The adjusted hazard ratio (95% confidence interval) for incident stroke was 1·05 (0·97-1·14) per standard deviation increase in plasma free fatty acids. Restriction to ischemic stroke did not alter the results [hazard ratio (95% confidence interval): 1·04 (0·96-1·14) per standard deviation higher free fatty acids], and there was no effect modification by adiposity (P interaction=0·18) or by diabetes (P interaction=0·15). CONCLUSION: Our data did not show an association of plasma free fatty acids with incident stroke among community dwelling older adults.
Keywords: Aged; Biomarkers; Brain Ischemia; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Male; Prospective Studies; Risk; Stroke

Plasma-free fatty acids, fatty acid-binding protein 4, and mortality in older adults (from the Cardiovascular Health Study). - Miedema, Michael D; Maziarz, Marlena; Biggs, Mary L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Mozaffarian, Dariush; Tracy, Russell P; Psaty, Bruce M; Siscovick, David S; Mukamal, Kenneth J; Djoussé, Luc (Am J Cardiol, 2014)
Plasma-free fatty acids (FFAs) are largely derived from adipose tissue. Elevated levels of FFA and fatty acid-binding protein 4 (FABP4), a key cytoplasmic chaperone of fatty acids, have been associated with adverse cardiovascular outcomes, but limited data are available on the relation of these biomarkers with cardiovascular and total mortality. We studied 4,707 participants with a mean age of 75 years who had plasma FFA and FABP4 measured in 1992 to 1993 as part of the Cardiovascular Health Study, an observational cohort of community-dwelling older adults. Over a median follow-up of 11.8 years, 3,555 participants died. Cox proportional hazard regression was used to determine the association between FFA, FABP4, and mortality. In fully adjusted models, FFA were associated with dose-dependent significantly higher total mortality (hazard ratio [HR] per SD: 1.14, 95% confidence interval [CI] 1.09 to 1.18), but FABP4 levels were not (HR 1.04, 95% CI 0.98 to 1.09). In a cause-specific mortality analysis, higher concentrations of FFA were associated with significantly higher risk of death because of cardiovascular disease, dementia, infection, and respiratory causes but not cancer or trauma. We did not find evidence of an interaction between FFA and FABP4 (p = 0.45), but FABP4 appeared to be associated with total mortality differentially in men and women (HR 1.17, 95% CI 1.08 to 1.26 for men; HR 1.02, 95% CI 0.96 to 1.07 for women, interaction p value <0.001). In conclusion, in a cohort of community-dwelling older subjects, elevated plasma concentrations of FFA, but not FABP4, were associated with cardiovascular and noncardiovascular mortality.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cause of Death; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Health Status; Humans; Male; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors; United States

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Regular fish consumption and age-related brain gray matter loss. - Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Kuller, Lewis H; Gach, H Michael; Thompson, Paul M; Riverol, Mario; Becker, James T (Am J Prev Med, 2014)
BACKGROUND: Brain health may be affected by modifiable lifestyle factors; consuming fish and antioxidative omega-3 fatty acids may reduce brain structural abnormality risk. PURPOSE: To determine whether dietary fish consumption is related to brain structural integrity among cognitively normal elders. METHODS: Data were analyzed from 260 cognitively normal individuals from the Cardiovascular Health Study with information on fish consumption from the National Cancer Institute Food Frequency Questionnaire and brain magnetic resonance imaging (MRI). The relationship between fish consumption data collected in 1989-1990 and brain structural MRI obtained in 1998-1999 was assessed using voxel-based morphometry in multiple regression analyses in 2012. Covariates were age, gender, race, education, white matter lesions, MRI-identified infarcts, waist-hip ratio, and physical activity as assessed by the number of city blocks walked in 1 week. Volumetric changes were further modeled with omega-3 fatty acid estimates to better understand the mechanistic link between fish consumption, brain health, and Alzheimer disease. RESULTS: Weekly consumption of baked or broiled fish was positively associated with gray matter volumes in the hippocampus, precuneus, posterior cingulate, and orbital frontal cortex even after adjusting for covariates. These results did not change when including omega-3 fatty acid estimates in the analysis. CONCLUSIONS: Dietary consumption of baked or broiled fish is related to larger gray matter volumes independent of omega-3 fatty acid content. These findings suggest that a confluence of lifestyle factors influence brain health, adding to the growing body of evidence that prevention strategies for late-life brain health need to begin decades earlier.
Keywords: Aged; Aged, 80 and over; Animals; Brain; Cross-Sectional Studies; Diet; Fatty Acids, Omega-3; Female; Fishes; Gray Matter; Humans; Life Style; Magnetic Resonance Imaging; Male; Regression Analysis; Surveys and Questionnaires

Relations of plasma total and high-molecular-weight adiponectin to new-onset heart failure in adults ≥65 years of age (from the Cardiovascular Health study). - Karas, Maria G; Benkeser, David; Arnold, Alice M; Bartz, Traci M; Djoussé, Luc; Mukamal, Kenneth J; Ix, Joachim H; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Mantzoros, Christos S; Gottdiener, John S; et al. (Am J Cardiol, 2014)
Adiponectin exhibits cardioprotective properties in experimental studies, but elevated levels have been linked to increased mortality in older adults and patients with chronic heart failure (HF). The adipokine's association with new-onset HF remains less well defined. The aim of this study was to investigate the associations of total and high-molecular weight (HMW) adiponectin with incident HF (n = 780) and, in a subset, echocardiographic parameters in a community-based cohort of adults aged ≥65 years. Total and HMW adiponectin were measured in 3,228 subjects without prevalent HF, atrial fibrillation or CVD. The relations of total and HMW adiponectin with HF were nonlinear, with significant associations observed only for concentrations greater than the median (12.4 and 6.2 mg/L, respectively). After adjustment for potential confounders, the hazard ratios per SD increment in total adiponectin were 0.93 (95% confidence interval 0.72 to 1.21) for concentrations less than the median and 1.25 (95% confidence interval 1.14 to 1.38) higher than the median. There was a suggestion of effect modification by body mass index, whereby the association appeared strongest in participants with lower body mass indexes. Consistent with the HF findings, higher adiponectin tended to be associated with left ventricular systolic dysfunction and left atrial enlargement. Results were similar for HMW adiponectin. In conclusion, total and HMW adiponectin showed comparable relations with incident HF in this older cohort, with a threshold effect of increasing risk occurring at their median concentrations. High levels of adiponectin may mark or mediate age-related processes that lead to HF in older adults.
Keywords: Adiponectin; Age of Onset; Aged; Biomarkers; Cross-Sectional Studies; Echocardiography, Doppler; Enzyme-Linked Immunosorbent Assay; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Prognosis; Prospective Studies; Recurrence; Severity of Illness Index; United States; Ventricular Function, Left

A robust method for genome-wide association meta-analysis with the application to circulating insulin-like growth factor I concentrations. - Wang, Tao; Zhou, Baiyu; Guo, Tingwei; Bidlingmaier, Martin; Wallaschofski, Henri; Teumer, Alexander; Vasan, Ramachandran S; Kaplan, Robert C (Genet Epidemiol, 2014)
Genome-wide association studies (GWAS) offer an excellent opportunity to identify the genetic variants underlying complex human diseases. Successful utilization of this approach requires a large sample size to identify single nucleotide polymorphisms (SNPs) with subtle effects. Meta-analysis is a cost-efficient means to achieve large sample size by combining data from multiple independent GWAS; however, results from studies performed on different populations can be variable due to various reasons, including varied linkage equilibrium structures as well as gene-gene and gene-environment interactions. Nevertheless, one should expect effects of the SNP are more similar between similar populations than those between populations with quite different genetic and environmental backgrounds. Prior information on populations of GWAS is often not considered in current meta-analysis methods, rendering such analyses less optimal for the detecting association. This article describes a test that improves meta-analysis to incorporate variable heterogeneity among populations. The proposed method is remarkably simple in computation and hence can be performed in a rapid fashion in the setting of GWAS. Simulation results demonstrate the validity and higher power of the proposed method over conventional methods in the presence of heterogeneity. As a demonstration, we applied the test to real GWAS data to identify SNPs associated with circulating insulin-like growth factor I concentrations.
Keywords: Computer Simulation; Genetic Linkage; Genome; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor I; Meta-Analysis as Topic; Models, Genetic; Polymorphism, Single Nucleotide; Sample Size

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Serum carboxymethyl-lysine, disability, and frailty in older persons: the Cardiovascular Health Study. - Whitson, Heather E; Arnold, Alice M; Yee, Laura M; Mukamal, Kenneth J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Siscovick, David; Tracy, Russell P; Thielke, Stephen M; Hirsch, Calvin; Newman, Anne B; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Advanced glycation endproducts are biologically active compounds that accumulate in disordered metabolism and normal aging. Carboxymethyl-lysine (CML), a ubiquitous human advanced glycation endproduct, has been associated with age-related conditions and mortality. Our objective was to ascertain the relationship between CML and geriatric outcomes (disability and frailty) in a large cohort of older men and women. METHODS: In 1996-1997, serum CML was measured in 3,373 Cardiovascular Health Study participants (mean age 78.1 ± 4.8 years). Disability, defined as difficulty in any of six activities of daily living, was assessed every 6-12 months for 14 years. Frailty was defined according to five standard criteria at the 1996-1997 visit. Cox proportional hazard models estimated the relationship between CML and incident disability (N = 2,643). Logistic regression models estimated the relationship between CML and prevalent frailty. RESULTS: Adjusting for multiple potential confounders, higher CML was associated with incident disability (hazard ratio per standard deviation [225 ng/mL] increase: 1.05, 95% CI 1.01-1.11). In men, odds of frailty increased with higher CML values (odds ratio = 1.30 per standard deviation, 95% CI 1.14-1.48), but the relationship was attenuated by adjustment for cognitive status, kidney function, and arthritis. CML was not associated with frailty in women. CONCLUSIONS: Higher serum CML levels in late life are associated with incident disability and prevalent frailty. Further work is needed to understand CML's value as a risk stratifier, biomarker, or target for interventions that promote healthy aging.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Biomarkers; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Health Status; Humans; Incidence; Lysine; Male; Prevalence; Prognosis; Retrospective Studies; United States

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Simple biologically informed inflammatory index of two serum cytokines predicts 10 year all-cause mortality in older adults. - Varadhan, Ravi; Yao, Wenliang; Matteini, Amy; Beamer, Brock A; Xue, Qian-Li; Yang, Huanle; Manwani, Bhavish; Reiner, Alexander; Jenny, Nancy; Parekh, Neel; Fallin, M Daniele; Newman, Anne; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Individual measurements of inflammation have been utilized to assess adverse outcomes risk in older adults with varying degrees of success. This study was designed to identify biologically informed, aggregate measures of inflammation for optimal risk assessment and to inform further biological study of inflammatory pathways. METHODS: In total, 15 nuclear factor-kappa B-mediated pathway markers of inflammation were first measured in baseline serum samples of 1,155 older participants in the InCHIANTI population. Of these, C-reactive protein, interleukin-1-receptor antagonist, interleukin-6, interleukin-18, and soluble tumor necrosis factor-α receptor-1 were independent predictors of 5-year mortality. These five inflammatory markers were measured in baseline serum samples of 5,600 Cardiovascular Health Study participants. A weighted summary score, the first principal component summary score, and an inflammation index score were developed from these five log-transformed inflammatory markers, and their prediction of 10-year all-cause mortality was evaluated in Cardiovascular Health Study and then validated in InCHIANTI. RESULTS: The inflammation index score that included interleukin-6 and soluble tumor necrosis factor-α receptor-1 was the best predictor of 10-year all-cause mortality in Cardiovascular Health Study, after adjusting for age, sex, education, race, smoking, and body mass index (hazards ratio = 1.62; 95% CI: 1.54, 1.70) compared with all other single and combined measures. The inflammation index score was also the best predictor of mortality in the InCHIANTI validation study (hazards ratio 1.33; 95% CI: 1.17-1.52). Stratification by sex and CVD status further strengthened the association of inflammation index score with mortality. CONCLUSION: A simple additive index of serum interleukin-6 and soluble tumor necrosis factor-α receptor-1 best captures the effect of chronic inflammation on mortality in older adults among the 15 biomarkers measured.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cohort Studies; Female; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Interleukin-6; Longevity; Male; Receptors, Tumor Necrosis Factor, Type I; Risk Factors

Sleep duration does not mediate or modify association of common genetic variants with type 2 diabetes. - Tare, Archana; Lane, Jacqueline M; Cade, Brian E; Grant, Struan F A; Chen, Ting-Hsu; Punjabi, Naresh M; Lauderdale, Diane S; Zee, Phyllis C; Gharib, Sina A; Gottlieb, Daniel J; Scheer, Frank A J L; Redline, Susan; et al. (Diabetologia, 2014)
AIMS/HYPOTHESIS: Short and long sleep duration are associated with increased risk of type 2 diabetes. We aimed to investigate whether genetic variants for fasting glucose or type 2 diabetes associate with short or long sleep duration and whether sleep duration modifies the association of genetic variants with these traits. METHODS: We examined the cross-sectional relationship between self-reported habitual sleep duration and prevalence of type 2 diabetes in individuals of European descent participating in five studies included in the Candidate Gene Association Resource (CARe), totalling 1,474 cases and 8,323 controls. We tested for association of 16 fasting glucose-associated variants, 27 type 2 diabetes-associated variants and aggregate genetic risk scores with continuous and dichotomised (≤5 h or ≥9 h) sleep duration using regression models adjusted for age, sex and BMI. Finally, we tested whether a gene × behaviour interaction of variants with sleep duration had an impact on fasting glucose or type 2 diabetes risk. RESULTS: Short sleep duration was significantly associated with type 2 diabetes in CARe (OR 1.32; 95% CI 1.08, 1.61; p = 0.008). Variants previously associated with fasting glucose or type 2 diabetes and genetic risk scores were not associated with sleep duration. Furthermore, no study-wide significant interaction was observed between sleep duration and these variants on glycaemic traits. Nominal interactions were observed for sleep duration and PPARG rs1801282, CRY2 rs7943320 and HNF1B rs4430796 in influencing risk of type 2 diabetes (p < 0.05). CONCLUSIONS/INTERPRETATION: Our findings suggest that differences in habitual sleep duration do not mediate or modify the relationship between common variants underlying glycaemic traits (including in circadian rhythm genes) and diabetes.
Keywords: Blood Glucose; Body Composition; Body Mass Index; Cross-Sectional Studies; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Fasting; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Glucose Intolerance; Glycated Hemoglobin A; Humans; Insulin Resistance; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sleep; Surveys and Questionnaires; Time Factors; United States

Subclinical hypothyroidism, weight change, and body composition in the elderly: the Cardiovascular Health Study. - Garin, Margaret C; Arnold, Alice M; Lee, Jennifer S; Tracy, Russell P; Cappola, Anne R (J Clin Endocrinol Metab, 2014)
BACKGROUND: Subclinical hypothyroidism is common in the elderly, yet its relationship with weight and body composition is unclear. OBJECTIVE: We examined the relationship between subclinical hypothyroidism and weight change and body composition in older adults. METHODS: A total of 427 subclinically hypothyroid and 2864 euthyroid U.S. individuals ≥65 years old enrolled in the Cardiovascular Health Study and not taking thyroid preparations were included. Analyses of 6-year weight change were performed, compared by thyroid status. A cross-sectional analysis of thyroid status and body composition was performed in a subset of 1276 participants who had dual-energy x-ray absorptiometry scans. Models were risk factor-adjusted and stratified by sex. RESULTS: Overall, participants lost weight during follow-up (-0.38 kg/y in men, -0.37 kg/y in women). Subclinical hypothyroidism, when assessed at a single time point or persisting over 2 years, was not associated with a difference in weight change compared with euthyroidism. Subclinical hypothyroidism was also not associated with differences in lean mass, fat mass, or percent fat compared with euthyroidism. A TSH level 1 mU/L higher within the euthyroid or subclinical hypothyroid range was associated with a 0.51-kg higher baseline weight in women only (P < .001) but not with weight change in either sex. A 1 ng/dL higher free T4 level was associated with lower baseline weight and 0.32 kg/y greater weight loss in women only (P = .003). Baseline weight and weight change did not differ by T3 levels. CONCLUSIONS: Our data do not support a clinically significant impact of subclinical hypothyroidism on weight status in the elderly.
Keywords: Aged; Aged, 80 and over; Asymptomatic Diseases; Body Composition; Body Mass Index; Cohort Studies; Female; Humans; Hypothyroidism; Male; Thyroid Gland; Weight Loss

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

A variant of sparse partial least squares for variable selection and data exploration. - Olson Hunt, Megan J; Weissfeld, Lisa; Boudreau, Robert M; Aizenstein, Howard; Newman, Anne B; Simonsick, Eleanor M; Van Domelen, Dane R; Thomas, Fridtjof; Yaffe, Kristine; Rosano, Caterina (Front Neuroinform, 2014)
When data are sparse and/or predictors multicollinear, current implementation of sparse partial least squares (SPLS) does not give estimates for non-selected predictors nor provide a measure of inference. In response, an approach termed "all-possible" SPLS is proposed, which fits a SPLS model for all tuning parameter values across a set grid. Noted is the percentage of time a given predictor is chosen, as well as the average non-zero parameter estimate. Using a "large" number of multicollinear predictors, simulation confirmed variables not associated with the outcome were least likely to be chosen as sparsity increased across the grid of tuning parameters, while the opposite was true for those strongly associated. Lastly, variables with a weak association were chosen more often than those with no association, but less often than those with a strong relationship to the outcome. Similarly, predictors most strongly related to the outcome had the largest average parameter estimate magnitude, followed by those with a weak relationship, followed by those with no relationship. Across two independent studies regarding the relationship between volumetric MRI measures and a cognitive test score, this method confirmed a priori hypotheses about which brain regions would be selected most often and have the largest average parameter estimates. In conclusion, the percentage of time a predictor is chosen is a useful measure for ordering the strength of the relationship between the independent and dependent variables, serving as a form of inference. The average parameter estimates give further insight regarding the direction and strength of association. As a result, all-possible SPLS gives more information than the dichotomous output of traditional SPLS, making it useful when undertaking data exploration and hypothesis generation for a large number of potential predictors.

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association between left atrial abnormality on ECG and vascular brain injury on MRI in the Cardiovascular Health Study. - Kamel, Hooman; Bartz, Traci M; Longstreth, W T; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Elkind, Mitchell S V; Soliman, Elsayed Z (Stroke, 2015)
BACKGROUND AND PURPOSE: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. RESULTS: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003-0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04-1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08-1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01-1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93-1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. CONCLUSIONS: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Brain; Brain Infarction; Cardiovascular Diseases; Cerebrovascular Trauma; Electrocardiography; Female; Heart Atria; Heart Diseases; Humans; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Regression Analysis; Risk Factors; Treatment Outcome

Association of 25-Hydroxyvitamin D status and genetic variation in the vitamin D metabolic pathway with FEV1 in the Framingham Heart Study. - Hansen, J G; Gao, W; Dupuis, J; O'Connor, G T; Tang, W; Kowgier, M; Sood, A; Gharib, S A; Palmer, L J; Fornage, M; Heckbert, S R; Psaty, B M; et al. (Respir Res, 2015)
BACKGROUND: Vitamin D is associated with lung function in cross-sectional studies, and vitamin D inadequacy is hypothesized to play a role in the pathogenesis of chronic obstructive pulmonary disease. Further data are needed to clarify the relation between vitamin D status, genetic variation in vitamin D metabolic genes, and cross-sectional and longitudinal changes in lung function in healthy adults. METHODS: We estimated the association between serum 25-hydroxyvitamin D [25(OH)D] and cross-sectional forced expiratory volume in the first second (FEV1) in Framingham Heart Study (FHS) Offspring and Third Generation participants and the association between serum 25(OH)D and longitudinal change in FEV1 in Third Generation participants using linear mixed-effects models. Using a gene-based approach, we investigated the association between 241 SNPs in 6 select vitamin D metabolic genes in relation to longitudinal change in FEV1 in Offspring participants and pursued replication of these findings in a meta-analyzed set of 4 independent cohorts. RESULTS: We found a positive cross-sectional association between 25(OH)D and FEV1 in FHS Offspring and Third Generation participants (P=0.004). There was little or no association between 25(OH)D and longitudinal change in FEV1 in Third Generation participants (P=0.97). In Offspring participants, the CYP2R1 gene, hypothesized to influence usual serum 25(OH)D status, was associated with longitudinal change in FEV1 (gene-based P<0.05). The most significantly associated SNP from CYP2R1 had a consistent direction of association with FEV1 in the meta-analyzed set of replication cohorts, but the association did not reach statistical significance thresholds (P=0.09). CONCLUSIONS: Serum 25(OH)D status was associated with cross-sectional FEV1, but not longitudinal change in FEV1. The inconsistent associations may be driven by differences in the groups studied. CYP2R1 demonstrated a gene-based association with longitudinal change in FEV1 and is a promising candidate gene for further studies.
Keywords: Adult; Aged; Cohort Studies; Cross-Sectional Studies; DNA-Binding Proteins; Female; Genetic Variation; Humans; Longitudinal Studies; Male; Massachusetts; Metabolic Networks and Pathways; Middle Aged; Nuclear Proteins; Polymorphism, Single Nucleotide; Vitamin D

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

DCAF4, a novel gene associated with leucocyte telomere length. - Mangino, Massimo; Christiansen, Lene; Stone, Rivka; Hunt, Steven C; Horvath, Kent; Eisenberg, Dan T A; Kimura, Masayuki; Petersen, Inge; Kark, Jeremy D; Herbig, Utz; Reiner, Alex P; Benetos, Athanase; et al. (J Med Genet, 2015)
BACKGROUND: Leucocyte telomere length (LTL), which is fashioned by multiple genes, has been linked to a host of human diseases, including sporadic melanoma. A number of genes associated with LTL have already been identified through genome-wide association studies. The main aim of this study was to establish whether DCAF4 (DDB1 and CUL4-associated factor 4) is associated with LTL. In addition, using ingenuity pathway analysis (IPA), we examined whether LTL-associated genes in the general population might partially explain the inherently longer LTL in patients with sporadic melanoma, the risk for which is increased with ultraviolet radiation (UVR). RESULTS: Genome-wide association (GWA) meta-analysis and de novo genotyping of 20 022 individuals revealed a novel association (p=6.4×10(-10)) between LTL and rs2535913, which lies within DCAF4. Notably, eQTL analysis showed that rs2535913 is associated with decline in DCAF4 expressions in both lymphoblastoid cells and sun-exposed skin (p=4.1×10(-3) and 2×10(-3), respectively). Moreover, IPA revealed that LTL-associated genes, derived from GWA meta-analysis (N=9190), are over-represented among genes engaged in melanoma pathways. Meeting increasingly stringent p value thresholds (p<0.05, <0.01, <0.005, <0.001) in the LTL-GWA meta-analysis, these genes were jointly over-represented for melanoma at p values ranging from 1.97×10(-169) to 3.42×10(-24). CONCLUSIONS: We uncovered a new locus associated with LTL in the general population. We also provided preliminary findings that suggest a link of LTL through genetic mechanisms with UVR and melanoma in the general population.
Keywords: Alleles; Carrier Proteins; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Melanoma; Risk Factors; Telomere; Telomere Homeostasis

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Gene-centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S; Lange, Leslie A; Yang, Qiong; Tracy, Russell P; Tofler, Geoffrey H; Basu, Saonli; Wilson, James G; Keating, Brendan J; Weng, Lu-Chen; et al. (Am J Hematol, 2015)
Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII :C) and VWF antigen (VWF :Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European-American populations. We performed a genetic association study of FVIII :C and VWF:Ag that assessed 50,000 gene-centric single nucleotide polymorphisms (SNPs) in 18,556 European Americans (EAs) and 5,047 African Americans (AAs) from five population-based cohorts. Previously unreported associations for FVIII :C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, Ile581Thr, P = 5.10 × 10(-7) in EAs and P = 3.88 × 10(-3) in AAs) and VWF rs7962217 (Gly2705Arg,P = 6.30 × 10(-9) in EAs and P = 2.98 × 10(-2) in AAs. Significant associations for FVIII :C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10(-10) ), with VWF rs1800380 in AAs (P = 5.62 × 10(-11) ), and with MAT1A rs2236568 in AAs (P51.69 × 10(-6) ). We replicated previously reported associations of FVIII :C and VWF :Ag with the ABO blood group, VWF rs1063856(Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII :C and VWF :Ag in both EAs and AAs.
Keywords: Adult; African Americans; Aged; European Continental Ancestry Group; Factor VIII; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Methionine Adenosyltransferase; Middle Aged; Polymorphism, Single Nucleotide; Venous Thromboembolism; von Willebrand Factor

Gene-Environment Interactions of Circadian-Related Genes for Cardiometabolic Traits. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Garaulet, Marta; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Kiefte-de Jong, Jessica C; Lamon-Fava, Stefania; Scheer, Frank A J L; Bartz, Traci M; et al. (Diabetes Care, 2015)
OBJECTIVE: Common circadian-related gene variants associate with increased risk for metabolic alterations including type 2 diabetes. However, little is known about whether diet and sleep could modify associations between circadian-related variants (CLOCK-rs1801260, CRY2-rs11605924, MTNR1B-rs1387153, MTNR1B-rs10830963, NR1D1-rs2314339) and cardiometabolic traits (fasting glucose [FG], HOMA-insulin resistance, BMI, waist circumference, and HDL-cholesterol) to facilitate personalized recommendations. RESEARCH DESIGN AND METHODS: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations and interactions between dietary intake/sleep duration and selected variants on cardiometabolic traits from 15 cohort studies including up to 28,190 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. RESULTS: We observed significant associations between relative macronutrient intakes and glycemic traits and short sleep duration (<7 h) and higher FG and replicated known MTNR1B associations with glycemic traits. No interactions were evident after accounting for multiple comparisons. However, we observed nominally significant interactions (all P < 0.01) between carbohydrate intake and MTNR1B-rs1387153 for FG with a 0.003 mmol/L higher FG with each additional 1% carbohydrate intake in the presence of the T allele, between sleep duration and CRY2-rs11605924 for HDL-cholesterol with a 0.010 mmol/L higher HDL-cholesterol with each additional hour of sleep in the presence of the A allele, and between long sleep duration (≥9 h) and MTNR1B-rs1387153 for BMI with a 0.60 kg/m(2) higher BMI with long sleep duration in the presence of the T allele relative to normal sleep duration (≥7 to <9 h). CONCLUSIONS: Our results suggest that lower carbohydrate intake and normal sleep duration may ameliorate cardiometabolic abnormalities conferred by common circadian-related genetic variants. Until further mechanistic examination of the nominally significant interactions is conducted, recommendations applicable to the general population regarding diet—specifically higher carbohydrate and lower fat composition—and normal sleep duration should continue to be emphasized among individuals with the investigated circadian-related gene variants.
Keywords: Adult; Alleles; Blood Glucose; Circadian Rhythm Signaling Peptides and Proteins; Cohort Studies; Diabetes Mellitus, Type 2; Diet, Fat-Restricted; European Continental Ancestry Group; Fasting; Female; Gene-Environment Interaction; Humans; Insulin Resistance; Male; Middle Aged; Multicenter Studies as Topic; Observational Studies as Topic; Phenotype; Polymorphism, Single Nucleotide; Sleep; Waist Circumference

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic loci associated with circulating levels of very long-chain saturated fatty acids. - Lemaitre, Rozenn N; King, Irena B; Kabagambe, Edmond K; Wu, Jason H Y; McKnight, Barbara; Manichaikul, Ani; Guan, Weihua; Sun, Qi; Chasman, Daniel I; Foy, Millennia; Wang, Lu; Zhu, Jingwen; et al. (J Lipid Res, 2015)
Very long-chain saturated fatty acids (VLSFAs) are saturated fatty acids with 20 or more carbons. In contrast to the more abundant saturated fatty acids, such as palmitic acid, there is growing evidence that circulating VLSFAs may have beneficial biological properties. Whether genetic factors influence circulating levels of VLSFAs is not known. We investigated the association of common genetic variation with plasma phospholipid/erythrocyte levels of three VLSFAs by performing genome-wide association studies in seven population-based cohorts comprising 10,129 subjects of European ancestry. We observed associations of circulating VLSFA concentrations with common variants in two genes, serine palmitoyl-transferase long-chain base subunit 3 (SPTLC3), a gene involved in the rate-limiting step of de novo sphingolipid synthesis, and ceramide synthase 4 (CERS4). The SPTLC3 variant at rs680379 was associated with higher arachidic acid (20:0 , P = 5.81 × 10(-13)). The CERS4 variant at rs2100944 was associated with higher levels of 20:0 (P = 2.65 × 10(-40)) and in analyses that adjusted for 20:0, with lower levels of behenic acid (P = 4.22 × 10(-26)) and lignoceric acid (P = 3.20 × 10(-21)). These novel associations suggest an inter-relationship of circulating VLSFAs and sphingolipid synthesis.
Keywords: Cohort Studies; Fatty Acids; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

Higher circulating adiponectin levels are associated with increased risk of atrial fibrillation in older adults. - Macheret, Fima; Bartz, Traci M; Djoussé, Luc; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Heckbert, Susan R; Psaty, Bruce M; Kizer, Jorge R (Heart, 2015)
BACKGROUND: Adiponectin has cardioprotective properties, suggesting that lower levels seen in obesity and diabetes could heighten risk of atrial fibrillation (AF). Among older adults, however, higher adiponectin has been linked to greater incidence of adverse outcomes associated with AF, although recent reports have shown this association to be U-shaped. We postulated that higher adiponectin would be linked to increased risk for AF in older adults in a U-shaped manner. METHODS: We examined the associations of total and high-molecular-weight (HMW) adiponectin with incident AF among individuals free of prevalent cardiovascular disease (CVD) participating in a population-based cohort study of older adults (n=3190; age=74±5 years). RESULTS: During median follow-up of 11.4 years, there were 886 incident AF events. Adjusted cubic splines showed a positive and linear association between adiponectin and incident AF. After adjusting for potential confounders, including amino-terminal pro-B-type natriuretic peptide 1-76, the HR (95% CI) for AF per SD increase in total adiponectin was 1.14 (1.05 to 1.24), while that for HMW adiponectin was 1.17 (1.08 to 1.27). Additional adjustment for putative mediators, including subclinical CVD, diabetes, lipids and inflammation, did not significantly affect these estimates. CONCLUSIONS: The present findings demonstrate that higher, not lower, levels of adiponectin are independently associated with increased risk of AF in older adults despite its documented cardiometabolic benefits. Additional work is necessary to determine if adiponectin is a marker of failed counter-regulatory pathways or whether this hormone is directly harmful in the setting of or as a result of advanced age.
Keywords: Adiponectin; Age Factors; Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Biomarkers; Female; Humans; Incidence; Linear Models; Male; Multivariate Analysis; Natriuretic Peptide, Brain; Peptide Fragments; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Intermediate and long-term risk of new-onset heart failure after hospitalization for pneumonia in elderly adults. - Corrales-Medina, Vicente F; Taljaard, Monica; Yende, Sachin; Kronmal, Richard; Dwivedi, Girish; Newman, Anne B; Elkind, Mitchell S V; Lyles, Mary F; Chirinos, Julio A (Am Heart J, 2015)
BACKGROUND: Pneumonia is associated with high risk of heart failure (HF) in the short term (30 days) postinfection. Whether this association persists beyond this period is unknown. METHODS: We studied 5,613 elderly (≥65 years) adults enrolled in the Cardiovascular Health Study between 1989 and 1994 at 4 US communities. Participants had no clinical diagnosis of HF at enrollment, and they were followed up through December 2010. Hospitalizations for pneumonia were identified using validated International Classification of Disease Ninth Revision codes. A centralized committee adjudicated new-onset HF events. Using Cox regression, we estimated adjusted hazard ratios (HRs) of new-onset HF at different time intervals after hospitalization for pneumonia. RESULTS: A total of 652 participants hospitalized for pneumonia during follow-up were still alive and free of clinical diagnosis of HF by day 30 posthospitalization. Relative to the time of their hospitalization, new-onset HF occurred in 22 cases between 31 and 90 days (HR 6.9, 95% CI 4.46-10.63, P < .001), 14 cases between 91 days and 6 months (HR 3.2, 95% CI 1.88-5.50, P < .001), 20 cases between 6 months and 1 year (HR 2.6, 95% CI 1.64-4.04, P < .001), 76 cases between 1 and 5 years (HR 1.7, 95% CI 1.30-2.12, P < .001), and 71 cases after 5 years (HR 2.0, 95% CI 1.56-2.58, P < .001). Results were robust to sensitivity analyses using stringent definitions of pneumonia and extreme assumptions for potential informative censoring. CONCLUSION: Hospitalization for pneumonia is associated with increased risk of new-onset HF in the intermediate and long term. Studies should characterize the mechanisms of this association in order to prevent HF in elderly pneumonia survivors.
Keywords: Aged; Disease Progression; Female; Follow-Up Studies; Forecasting; Heart Failure; Hospitalization; Humans; Incidence; Inpatients; Male; Patient Readmission; Pneumonia; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Risk Factors; Time Factors

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Age, Race, and Sex With Acute Kidney Injury. - Grams, Morgan E; Sang, Yingying; Ballew, Shoshana H; Gansevoort, Ron T; Kimm, Heejin; Kovesdy, Csaba P; Naimark, David; Oien, Cecilia; Smith, David H; Coresh, Josef; Sarnak, Mark J; Stengel, Bénédicte; et al. (Am J Kidney Dis, 2015)
BACKGROUND: Acute kidney injury (AKI) is a serious global public health problem. We aimed to quantify the risk of AKI associated with estimated glomerular filtration rate (eGFR), albuminuria (albumin-creatinine ratio [ACR]), age, sex, and race (African American and white). STUDY DESIGN: Collaborative meta-analysis. SETTING & POPULATION: 8 general-population cohorts (1,285,049 participants) and 5 chronic kidney disease (CKD) cohorts (79,519 participants). SELECTION CRITERIA FOR STUDIES: Available eGFR, ACR, and 50 or more AKI events. PREDICTORS: Age, sex, race, eGFR, urine ACR, and interactions. OUTCOME: Hospitalized with or for AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: 16,480 (1.3%) general-population cohort participants had AKI over a mean follow-up of 4 years; 2,087 (2.6%) CKD participants had AKI over a mean follow-up of 1 year. Lower eGFR and higher ACR were strongly associated with AKI. Compared with eGFR of 80mL/min/1.73m(2), the adjusted HR of AKI at eGFR of 45mL/min/1.73m(2) was 3.35 (95% CI, 2.75-4.07). Compared with ACR of 5mg/g, the risk of AKI at ACR of 300mg/g was 2.73 (95% CI, 2.18-3.43). Older age was associated with higher risk of AKI, but this effect was attenuated with lower eGFR or higher ACR. Male sex was associated with higher risk of AKI, with a slight attenuation in lower eGFR but not in higher ACR. African Americans had higher AKI risk at higher levels of eGFR and most levels of ACR. LIMITATIONS: Only 2 general-population cohorts could contribute to analyses by race; AKI identified by diagnostic code. CONCLUSIONS: Reduced eGFR and increased ACR are consistent strong risk factors for AKI, whereas associations of AKI with age, sex, and race may be weaker in more advanced stages of CKD.
Keywords: Acute Kidney Injury; Adolescent; Adult; African Americans; Age Distribution; Aged; Albuminuria; Continental Population Groups; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Young Adult

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Physical activity, body mass index, and brain atrophy in Alzheimer's disease. - Boyle, Christina P; Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Gach, H Michael; Longstreth, W T; Teverovskiy, Leonid; Kuller, Lewis H; Carmichael, Owen T; Thompson, Paul M (Neurobiol Aging, 2015)
The purpose of this study was to use a novel imaging biomarker to assess associations between physical activity (PA), body mass index (BMI), and brain structure in normal aging, mild cognitive impairment, and Alzheimer's dementia. We studied 963 participants (mean age: 74.1 ± 4.4 years) from the multisite Cardiovascular Health Study including healthy controls (n = 724), Alzheimer's dementia patients (n = 104), and people with mild cognitive impairment (n = 135). Volumetric brain images were processed using tensor-based morphometry to analyze regional brain volumes. We regressed the local brain tissue volume on reported PA and computed BMI, and performed conjunction analyses using both variables. Covariates included age, sex, and study site. PA was independently associated with greater whole brain and regional brain volumes and reduced ventricular dilation. People with higher BMI had lower whole brain and regional brain volumes. A PA-BMI conjunction analysis showed brain preservation with PA and volume loss with increased BMI in overlapping brain regions. In one of the largest voxel-based cross-sectional studies to date, PA and lower BMI may be beneficial to the brain across the spectrum of aging and neurodegeneration.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Atrophy; Biomarkers; Body Mass Index; Brain; Cognitive Dysfunction; Cross-Sectional Studies; Diffusion Magnetic Resonance Imaging; Female; Humans; Magnetic Resonance Imaging; Male; Motor Activity; Neuroimaging

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Positive association of tomato consumption with serum urate: support for tomato consumption as an anecdotal trigger of gout flares. - Flynn, Tanya J; Cadzow, Murray; Dalbeth, Nicola; Jones, Peter B; Stamp, Lisa K; Hindmarsh, Jennie Harré; Todd, Alwyn S; Walker, Robert J; Topless, Ruth; Merriman, Tony R (BMC Musculoskelet Disord, 2015)
BACKGROUND: Gout is a consequence of an innate immune reaction to monosodium urate crystals deposited in joints. Acute gout attacks can be triggered by dietary factors that are themselves associated with serum urate levels. Tomato consumption is an anecdotal trigger of gout flares. This study aimed to measure the frequency of tomato consumption as a self-reported trigger of gout attacks in a large New Zealand sample set, and to test the hypothesis that tomato consumption is associated with serum urate levels. METHODS: Two thousand fifty one New Zealanders (of Māori, Pacific Island, European or other ancestry) with clinically-ascertained gout were asked about gout trigger foods. European individuals from the Atherosclerosis Risk In Communities (ARIC; n = 7517) Study, Cardiovascular Health Study (CHS; n = 2151) and Framingham Heart Study (FHS; n = 3052) were used to test, in multivariate-adjusted analyses, for association between serum urate and tomato intake. RESULTS: Seventy one percent of people with gout reported having ≥1 gout trigger food. Of these 20% specifically mentioned tomatoes, the 4(th) most commonly reported trigger food. There was association between tomato intake and serum urate levels in the ARIC, CHS and FHS combined cohort (β = 0.66 μmolL(-1) increase in serum urate per additional serve per week; P = 0.006) - evident in both sexes (men: β = 0.84 μmolL(-1), P = 0.035; women: β = 0.59 μmolL (-1), P = 0.041). CONCLUSIONS: While our descriptive and observational data are unable to support the claim that tomato consumption is a trigger of gout attacks, the positive association between tomato consumption and serum urate levels suggests that the self-reporting of tomatoes as a dietary trigger by people with gout has a biological basis.
Keywords: Adolescent; Adult; Aged; European Continental Ancestry Group; Female; Gout; Humans; Hyperuricemia; Lycopersicon esculentum; Male; Middle Aged; New Zealand; Oceanic Ancestry Group; Surveys and Questionnaires; Uric Acid; Young Adult

Predicting Future Years of Life, Health, and Functional Ability: A Healthy Life Calculator for Older Adults. - Diehr, Paula; Diehr, Michael; Arnold, Alice; Yee, Laura M; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Psaty, Bruce M; Johnson, W Craig; Kizer Md, Jorge R; Newman, Anne (Gerontol Geriatr Med, 2015)
To create personalized estimates of future health and ability status for older adults.Data came from the Cardiovascular Health Study (CHS), a large longitudinal study. Outcomes included years of life, years of healthy life (based on self-rated health), years of able life (based on activities of daily living), and years of healthy and able life. We developed regression estimates using the demographic and health characteristics that best predicted the four outcomes. Internal and external validity were assessed.A prediction equation based on 11 variables accounted for about 40% of the variability for each outcome. Internal validity was excellent, and external validity was satisfactory. The resulting CHS Healthy Life Calculator (CHSHLC) is available at http://healthylifecalculator.org.CHSHLC provides a well-documented estimate of future years of healthy and able life for older adults, who may use it in planning for the future.

Prospective study of circulating factor XI and incident venous thromboembolism: The Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Tang, Weihong; Roetker, Nicholas S; Heckbert, Susan R; Cushman, Mary; Pankow, James S (Am J Hematol, 2015)
Elevated plasma concentrations of coagulation factor XI may increase risk of venous thromboembolism (VTE), but prospective data are limited. We studied prospectively the associations of plasma factor XI and a key F11 genetic variant with incident VTE in whites and African-Americans. We measured factor XI in 16,299 participants, initially free of VTE, in two prospective population cohorts. We also measured the F11 single nucleotide polymorphism rs4241824, which a genome-wide association study had linked to factor XI concentration. During follow-up, we identified 606 VTEs. The age, race, sex, and study-adjusted hazard ratio of VTE increased across factor XI quintiles (P < 0.001 for trend), and the hazard ratio was 1.51 (95% CI 1.16, 1.97) for the highest versus lowest quintile overall, and was 1.42 (95% CI 1.03, 1.95) in whites and 1.72 (95% CI 1.08, 2.73) in African-Americans. In whites, the F11 variant was associated with both factor XI concentration and VTE incidence (1.15-fold greater incidence of VTE per risk allele). In African-Americans, these associations were absent. In conclusion, this cohort study documented that an elevated plasma factor XI concentration is a risk factor for VTE over extended follow-up, not only in whites but also in African-Americans. In whites, the association of the F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African-Americans.
Keywords: African Americans; Aged; Alleles; European Continental Ancestry Group; Factor XI; Female; Gene Expression; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Rare and Coding Region Genetic Variants Associated With Risk of Ischemic Stroke: The NHLBI Exome Sequence Project. - Auer, Paul L; Nalls, Mike; Meschia, James F; Worrall, Bradford B; Longstreth, W T; Seshadri, Sudha; Kooperberg, Charles; Burger, Kathleen M; Carlson, Christopher S; Carty, Cara L; Chen, Wei-Min; Cupples, L Adrienne; et al. (JAMA Neurol, 2015)
IMPORTANCE: Stroke is the second leading cause of death and the third leading cause of years of life lost. Genetic factors contribute to stroke prevalence, and candidate gene and genome-wide association studies (GWAS) have identified variants associated with ischemic stroke risk. These variants often have small effects without obvious biological significance. Exome sequencing may discover predicted protein-altering variants with a potentially large effect on ischemic stroke risk. OBJECTIVE: To investigate the contribution of rare and common genetic variants to ischemic stroke risk by targeting the protein-coding regions of the human genome. DESIGN, SETTING, AND PARTICIPANTS: The National Heart, Lung, and Blood Institute (NHLBI) Exome Sequencing Project (ESP) analyzed approximately 6000 participants from numerous cohorts of European and African ancestry. For discovery, 365 cases of ischemic stroke (small-vessel and large-vessel subtypes) and 809 European ancestry controls were sequenced; for replication, 47 affected sibpairs concordant for stroke subtype and an African American case-control series were sequenced, with 1672 cases and 4509 European ancestry controls genotyped. The ESP's exome sequencing and genotyping started on January 1, 2010, and continued through June 30, 2012. Analyses were conducted on the full data set between July 12, 2012, and July 13, 2013. MAIN OUTCOMES AND MEASURES: Discovery of new variants or genes contributing to ischemic stroke risk and subtype (primary analysis) and determination of support for protein-coding variants contributing to risk in previously published candidate genes (secondary analysis). RESULTS: We identified 2 novel genes associated with an increased risk of ischemic stroke: a protein-coding variant in PDE4DIP (rs1778155; odds ratio, 2.15; P = 2.63 × 10(-8)) with an intracellular signal transduction mechanism and in ACOT4 (rs35724886; odds ratio, 2.04; P = 1.24 × 10(-7)) with a fatty acid metabolism; confirmation of PDE4DIP was observed in affected sibpair families with large-vessel stroke subtype and in African Americans. Replication of protein-coding variants in candidate genes was observed for 2 previously reported GWAS associations: ZFHX3 (cardioembolic stroke) and ABCA1 (large-vessel stroke). CONCLUSIONS AND RELEVANCE: Exome sequencing discovered 2 novel genes and mechanisms, PDE4DIP and ACOT4, associated with increased risk for ischemic stroke. In addition, ZFHX3 and ABCA1 were discovered to have protein-coding variants associated with ischemic stroke. These results suggest that genetic variation in novel pathways contributes to ischemic stroke risk and serves as a target for prediction, prevention, and therapy.
Keywords: Aged; Brain Ischemia; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Muscle Proteins; National Heart, Lung, and Blood Institute (U.S.); Nuclear Proteins; Open Reading Frames; Palmitoyl-CoA Hydrolase; Stroke; United States

Rare and low-frequency variants and their association with plasma levels of fibrinogen, FVII, FVIII, and vWF. - Huffman, Jennifer E; de Vries, Paul S; Morrison, Alanna C; Sabater-Lleal, Maria; Kacprowski, Tim; Auer, Paul L; Brody, Jennifer A; Chasman, Daniel I; Chen, Ming-Huei; Guo, Xiuqing; Lin, Li-An; Marioni, Riccardo E; et al. (Blood, 2015)
Fibrinogen, coagulation factor VII (FVII), and factor VIII (FVIII) and its carrier von Willebrand factor (vWF) play key roles in hemostasis. Previously identified common variants explain only a small fraction of the trait heritabilities, and additional variations may be explained by associations with rarer variants with larger effects. The aim of this study was to identify low-frequency (minor allele frequency [MAF] ≥0.01 and <0.05) and rare (MAF <0.01) variants that influence plasma concentrations of these 4 hemostatic factors by meta-analyzing exome chip data from up to 76,000 participants of 4 ancestries. We identified 12 novel associations of low-frequency (n = 2) and rare (n = 10) variants across the fibrinogen, FVII, FVIII, and vWF traits that were independent of previously identified associations. Novel loci were found within previously reported genes and had effect sizes much larger than and independent of previously identified common variants. In addition, associations at KCNT1, HID1, and KATNB1 identified new candidate genes related to hemostasis for follow-up replication and functional genomic analysis. Newly identified low-frequency and rare-variant associations accounted for modest amounts of trait variance and therefore are unlikely to increase predicted trait heritability but provide new information for understanding individual variation in hemostasis pathways.
Keywords: Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Gene Frequency; Genetic Association Studies; Genetic Variation; Humans; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels; von Willebrand Factor

Relationship between Systemic and Cerebral Vascular Disease and Brain Structure Integrity in Normal Elderly Individuals. - Riverol, Mario; Becker, James T; Lopez, Oscar L; Raji, Cyrus A; Thompson, Paul M; Carmichael, Owen T; Gach, H Michael; Longstreth, William T; Fried, Linda; Tracy, Russell P; Kuller, Lewis H (J Alzheimers Dis, 2015)
Cerebral white matter lesions (WMLs) are considered a reflection of cerebral and systemic small vessel disease (SVD), and are associated with reductions in brain volume. Like the brain, the kidney is also sensitive to factors that affect vasculature. Glomerular dysfunction due to renal vascular damage can be measured with different biochemical parameters, such as creatinine or cystatin C, although cystatin C is considered to be more accurate than creatinine in the elderly. The purpose of the study was to determine whether manifestations of SVD in the kidney can predict SVD-based damage to the brain. We examined the relationship between glomerular dysfunction as a measure of SVD on WMLs, gray matter (GM) volume, and cognition in 735 cognitively normal participants from the Cardiovascular Health Study Cognition Study. The multivariate analyses controlled for demographic characteristics, hypertension, heart disease, diabetes, Apolipoprotein 4 allele, C reactive protein, lipids, physical activity, smoking, and body mass index (BMI). Elevated cystatin C levels were associated with lower neuropsychological test scores, the presence of MRI-identified brain infarcts, the severity of WMLs, and GM atrophy five years later. In adjusted models, GM volume was significantly associated with cystatin-C only until BMI and severity of WMLs were added to the model, meaning that the effect of SVD on GM volume is mediated by these two variables. These findings suggest that age-related SVD is a process that leads to altered brain structure, and creates a vulnerability state for cognitive decline.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Brain; Cerebrovascular Disorders; Female; Humans; Image Processing, Computer-Assisted; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Peripheral Vascular Diseases; Predictive Value of Tests; Retrospective Studies; White Matter

Sex, Race, and Age Differences in Observed Years of Life, Healthy Life, and Able Life among Older Adults in The Cardiovascular Health Study. - Thielke, Stephen M; Diehr, Paula H; Yee, Laura M; Arnold, Alice M; Quiñones, Ana R; Whitson, Heather E; Jacob, Mini E; Newman, Anne B (J Pers Med, 2015)
OBJECTIVE: Longevity fails to account for health and functional status during aging. We sought to quantify differences in years of total life, years of healthy life, and years of able life among groups defined by age, sex, and race. DESIGN: Primary analysis of a cohort study. SETTING: 18 years of annual evaluations in four U.S. communities. PARTICIPANTS: 5888 men and women aged 65 and older. MEASUREMENTS: Years of life were calculated as the time from enrollment to death or 18 years. Years of total, healthy, and able life were determined from self-report during annual or semi-annual contacts. Cumulative years were summed across each of the age and sex groups. RESULTS: White women had the best outcomes for all three measures, followed by white men, non-white women, and non-white men. For example, at the mean age of 73, a white female participant could expect 12.9 years of life, 8.9 of healthy life and 9.5 of able life, while a non-white female could expect 12.6, 7.0, and 8.0 years, respectively. A white male could expect 11.2, 8.1, and 8.9 years of life, healthy life, and able life, and a non-white male 10.3, 6.2, and 7.9 years. Regardless of starting age, individuals of the same race and sex groups spent similar amounts (not proportions) of time in an unhealthy or unable state. CONCLUSION: Gender had a greater effect on longevity than did race, but race had a greater effect on years spent healthy or able. The mean number of years spent in an unable or sick state was surprisingly independent of the lifespan.

Shared genetic basis for migraine and ischemic stroke: A genome-wide analysis of common variants. - Malik, Rainer; Freilinger, Tobias; Winsvold, Bendik S; Anttila, Verneri; Vander Heiden, Jason; Traylor, Matthew; de Vries, Boukje; Holliday, Elizabeth G; Terwindt, Gisela M; Sturm, Jonathan; Bis, Joshua C; Hopewell, Jemma C; et al. (Neurology, 2015)
OBJECTIVE: To quantify genetic overlap between migraine and ischemic stroke (IS) with respect to common genetic variation. METHODS: We applied 4 different approaches to large-scale meta-analyses of genome-wide data on migraine (23,285 cases and 95,425 controls) and IS (12,389 cases and 62,004 controls). First, we queried known genome-wide significant loci for both disorders, looking for potential overlap of signals. We then analyzed the overall shared genetic load using polygenic scores and estimated the genetic correlation between disease subtypes using data derived from these models. We further interrogated genomic regions of shared risk using analysis of covariance patterns between the 2 phenotypes using cross-phenotype spatial mapping. RESULTS: We found substantial genetic overlap between migraine and IS using all 4 approaches. Migraine without aura (MO) showed much stronger overlap with IS and its subtypes than migraine with aura (MA). The strongest overlap existed between MO and large artery stroke (LAS; p = 6.4 × 10(-28) for the LAS polygenic score in MO) and between MO and cardioembolic stroke (CE; p = 2.7 × 10(-20) for the CE score in MO). CONCLUSIONS: Our findings indicate shared genetic susceptibility to migraine and IS, with a particularly strong overlap between MO and both LAS and CE pointing towards shared mechanisms. Our observations on MA are consistent with a limited role of common genetic variants in this subtype.
Keywords: Brain Ischemia; Genome-Wide Association Study; Humans; Migraine with Aura; Migraine without Aura; Stroke

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

Urine Collagen Fragments and CKD Progression-The Cardiovascular Health Study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth; Djoussé, Luc; Siscovick, David; Tracy, Russell; Katz, Ronit; Delaney, Joseph A; Chaves, Paulo; Rifkin, Dena E; Hughes-Austin, Jan M; Garimella, Pranav S; et al. (J Am Soc Nephrol, 2015)
Tubulointerstitial fibrosis is common with ageing and strongly prognostic for ESRD but is poorly captured by eGFR or urine albumin to creatinine ratio (ACR). Higher urine levels of procollagen type III N-terminal propeptide (PIIINP) mark the severity of tubulointerstitial fibrosis in biopsy studies, but the association of urine PIIINP with CKD progression is unknown. Among community-living persons aged ≥65 years, we measured PIIINP in spot urine specimens from the 1996 to 1997 Cardiovascular Health Study visit among individuals with CKD progression (30% decline in eGFR over 9 years, n=192) or incident ESRD (n=54) during follow-up, and in 958 randomly selected participants. We evaluated associations of urine PIIINP with CKD progression and incident ESRD. Associations of urine PIIINP with cardiovascular disease, heart failure, and death were evaluated as secondary end points. At baseline, mean age (±SD) was 78±5 years, mean eGFR was 63±18 ml/min per 1.73 m(2), and median urine PIIINP was 2.6 (interquartile range, 1.4-4.2) μg/L. In a case-control study (192 participants, 231 controls), each doubling of urine PIIINP associated with 22% higher odds of CKD progression (adjusted odds ratio, 1.22; 95% confidence interval, 1.00 to 1.49). Higher urine PIIINP level was also associated with incident ESRD, but results were not significant in fully adjusted models. In a prospective study among the 958 randomly selected participants, higher urine PIIINP was significantly associated with death, but not with incident cardiovascular disease or heart failure. These data suggest higher urine PIIINP levels associate with CKD progression independently of eGFR and ACR in older individuals.
Keywords: Aged; Cardiovascular Diseases; Case-Control Studies; Disease Progression; Female; Heart Failure; Humans; Kidney Failure, Chronic; Male; Peptide Fragments; Procollagen; Prospective Studies; Renal Insufficiency, Chronic

Voxel Level Survival Analysis of Grey Matter Volume and Incident Mild Cognitive Impairment or Alzheimer's Disease. - Zeifman, Lubov E; Eddy, William F; Lopez, Oscar L; Kuller, Lewis H; Raji, Cyrus; Thompson, Paul M; Becker, James T (J Alzheimers Dis, 2015)
The purpose of this study was to identify, at the voxel level, brain regions associated with the time to develop mild cognitive impairment (MCI) or Alzheimer's disease (AD) from normal cognition. We analyzed incident MCI (n = 58) or AD (n = 151) in 292 cognitively normal participants in the Cardiovascular Health Study-Cognition Study (mean age = 79.2 ± 3.6 years). We used segmented, modulated grey matter maps from 3D (spoiled gradient echo) MRI scans obtained in 1998/99 (with clinical follow-up through 2012) that were smoothed with a 3-D 4 mm Gaussian filter. We fit approximately 1.92 million voxel-level Cox proportional hazard models to examine the grey matter volume effect on time to event, adjusting for age, sex, and diabetes. We used the significance threshold of p <  0.005 with contiguity threshold of at least 68 voxels (false detection probability <2.5×10 -8). Areas within the mesial temporal lobe (MTL), anterior temporal lobe, hippocampus, and posterior cingulate gyrus were associated with time to MCI or AD. The presence of white matter lesions (a marker of small vessel disease in the brain) was associated with the volumes of the MTL and precuneus; MRI-identified infarcts also predicted MTL volume. These findings are important because we identified critical brain regions that predict a person's increased likelihood of developing MCI or AD over a decade prior to the onset of clinical symptoms; these critical brain regions were themselves affected by the presence of vascular disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Chi-Square Distribution; Disease Progression; Female; Gray Matter; Humans; Incidence; Magnetic Resonance Imaging; Male; Mild Cognitive Impairment; Neuropsychological Tests; Psychiatric Status Rating Scales; Survival Analysis

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease: Pooling Project of 19 Cohort Studies - Del Gobbo, L. C.; Imamura, F.; Aslibekyan, S.; Marklund, M.; Virtanen, J. K.; Wennberg, M.; Yakoob, M. Y.; Chiuve, S. E.; Dela Cruz, L.; Frazier-Wood, A. C.; Fretts, A. M.; Guallar, E.; et al. (JAMA Intern Med, 2016)
-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.\ -3) for incident CHD.\ A global consortium of 19 studies identified by November 2014.\ -3 biomarkers and ascertained CHD.\ -6 levels, and FADS desaturase genes.\ Incident total CHD, fatal CHD, and nonfatal myocardial infarction (MI).\ -3 biomarkers ALA, DPA, and DHA were associated with a lower risk of fatal CHD, with relative risks (RRs) of 0.91 (95% CI, 0.84-0.98) for ALA, 0.90 (95% CI, 0.85-0.96) for DPA, and 0.90 (95% CI, 0.84-0.96) for DHA. Although DPA was associated with a lower risk of total CHD (RR, 0.94; 95% CI, 0.90-0.99), ALA (RR, 1.00; 95% CI, 0.95-1.05), EPA (RR, 0.94; 95% CI, 0.87-1.02), and DHA (RR, 0.95; 95% CI, 0.91-1.00) were not. Significant associations with nonfatal MI were not evident. Associations appeared generally stronger in phospholipids and total plasma. Restricted cubic splines did not identify evidence of nonlinearity in dose responses.\ -3 fatty acids are associated with a modestly lower incidence of fatal CHD.

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

APOL1 Genotype, Kidney and Cardiovascular Disease, and Death in Older Adults. - Mukamal, Kenneth J; Tremaglio, Joseph; Friedman, David J; Ix, Joachim H; Kuller, Lewis H; Tracy, Russell P; Pollak, Martin R (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: We sought to evaluate the cardiovascular impact of coding variants in the apolipoprotein L1 gene APOL1 that protect against trypanosome infection but have been associated with kidney disease among African Americans. APPROACH AND RESULTS: As part of the Cardiovascular Health Study, a population-based cohort of Americans aged ≥65 years, we genotyped APOL1 polymorphisms rs73885319 and rs71785153 and examined kidney function, subclinical atherosclerosis, and incident cardiovascular disease and death over 13 years of follow-up among 91 African Americans with 2 risk alleles, 707 other African Americans, and 4964 white participants. The high-risk genotype with 2 risk alleles was associated with 2-fold higher levels of albuminuria and lower ankle-brachial indices but similar carotid intima-media thickness among African Americans. Median survival among high-risk African Americans was 9.9 years (95% confidence interval [CI], 8.7-11.9), compared with 13.6 years (95% CI, 12.5-14.3) among other African Americans and 13.3 years (95% CI, 13.0-13.6) among whites (P=0.03). The high-risk genotype was also associated with increased risk for incident myocardial infarction (adjusted hazard ratio 1.8; 95% CI, 1.1-3.0) and mortality (adjusted hazard ratio 1.3; 95% CI 1.0-1.7). Albuminuria and risk for myocardial infarction and mortality were nearly identical between African Americans with 0 to 1 risk alleles and whites. CONCLUSIONS: APOL1 genotype is associated with albuminuria, subclinical atherosclerosis, incident myocardial infarction, and mortality in older African Americans. African Americans without 2 risk alleles do not differ significantly in risk of myocardial infarction or mortality from whites. APOL1 trypanolytic variants may account for a substantial proportion of the excess risk of chronic disease in African Americans.
Keywords: African Americans; Age Factors; Aged; Albuminuria; Apolipoproteins; Atherosclerosis; Cardiovascular Diseases; Cause of Death; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Health Status Disparities; Heterozygote; Homozygote; Humans; Incidence; Kaplan-Meier Estimate; Kidney Diseases; Lipoproteins, HDL; Male; Myocardial Infarction; Phenotype; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Associations of insulin resistance, inflammation and liver synthetic function with very low-density lipoprotein: The Cardiovascular Health Study. - Jiang, Z Gordon; de Boer, Ian H; Mackey, Rachel H; Jensen, Majken K; Lai, Michelle; Robson, Simon C; Tracy, Russell; Kuller, Lewis H; Mukamal, Kenneth J (Metabolism, 2016)
INTRODUCTION: Production of very low-density lipoprotein (VLDL) is increased in states of metabolic syndrome, leading to hypertriglyceridemia. However, metabolic syndrome is often associated with non-alcoholic fatty liver disease, which leads to liver fibrosis and inflammation that may decrease VLDL production. In this study, we aim to determine the interactive impact on VLDL profiles from insulin resistance, impairment in liver synthetic function and inflammation. METHODS: We examined cross-sectional associations of insulin sensitivity, inflammation, and liver synthetic function with VLDL particle (VLDL-P) concentration and size among 1,850 older adults in the Cardiovascular Health Study. RESULTS: Indices for high insulin sensitivity and low liver synthetic function were associated with lower concentrations of VLDL-P. In addition, insulin resistance preferentially increased concentration of large VLDL and was associated with mean VLDL size. Indices for inflammation however demonstrated a nonlinear relationship with both VLDL-P concentration and VLDL size. When mutually adjusted, one standard deviation (SD) increment in Matsuda index and C-reactive protein (CRP) were associated with 4.9 nmol/L (-8.2 to -1.5, p=0.005) and 6.3 nmol/L (-11.0 to -1.6, p=0.009) lower VLDL-P concentration respectively. In contrast, one-SD increment in factor VII, a marker for liver synthetic function, was associated with 16.9 nmol/L (12.6-21.2, p<0.001) higher VLDL-P concentration. Furthermore, a one-SD increment in the Matsuda index was associated with 1.1 nm (-2.0 to -0.3, p=0.006) smaller mean VLDL size, whereas CRP and factor VII were not associated with VLDL size. CONCLUSION: Insulin sensitivity, inflammation and markers for liver synthetic function differentially impact VLDL-P concentration and VLDL size. These results underscore the complex effects of insulin resistance and its complications on VLDL production.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Cross-Sectional Studies; Factor VII; Female; Humans; Inflammation; Insulin Resistance; Lipoproteins, VLDL; Liver; Liver Function Tests; Male; Risk Factors; Socioeconomic Factors

Brain natriuretic peptide and insulin resistance in older adults. - Kim, F; Biggs, M L; Kizer, J R; Brutsaert, E F; de Fillipi, C; Newman, A B; Kronmal, R A; Tracy, R P; Gottdiener, J S; Djoussé, L; de Boer, I H; Psaty, B M; et al. (Diabet Med, 2016)
AIMS: Higher levels of brain natriuretic peptide (BNP) have been associated with a decreased risk of diabetes in adults, but whether BNP is related to insulin resistance in older adults has not been established. METHODS: N-Terminal (NT)-proBNP was measured among Cardiovascular Health Study participants at the 1989-1990, 1992-1993 and 1996-1997 examinations. We calculated measures of insulin resistance [homeostatic model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI), Gutt index, Matsuda index] from fasting and 2-h concentrations of glucose and insulin among 3318 individuals with at least one measure of NT-proBNP and free of heart failure, coronary heart disease and chronic kidney disease, and not taking diabetes medication. We used generalized estimating equations to assess the cross-sectional association of NT-proBNP with measures of insulin resistance. Instrumental variable analysis with an allele score derived from nine genetic variants (single nucleotide polymorphisms) within or near the NPPA and NPPB loci was used to estimate an un-confounded association of NT-proBNP levels on insulin resistance. RESULTS: Lower NT-proBNP levels were associated with higher insulin resistance even after adjustment for BMI, waist circumference and other risk factors (P < 0.001 for all four indices). Although the genetic score was strongly related to measured NT-proBNP levels amongst European Americans (F statistic = 71.08), we observed no association of genetically determined NT-proBNP with insulin resistance (P = 0.38; P = 0.01 for comparison with the association of measured levels of NT-proBNP). CONCLUSIONS: In older adults, lower NT-proBNP is associated with higher insulin resistance, even after adjustment for traditional risk factors. Because related genetic variants were not associated with insulin resistance, the causal nature of this association will require future study. This article is protected by copyright. All rights reserved.

Can a Healthy Lifestyle Compress the Disabled Period in Older Adults? - Jacob, Mini E; Yee, Laura M; Diehr, Paula H; Arnold, Alice M; Thielke, Stephen M; Chaves, Paulo H M; Gobbo, Liana Del; Hirsch, Calvin; Siscovick, David; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine whether lifestyle factors, measured late in life, could compress the disabled period toward the end of life. DESIGN: Community-based cohort study of older adults followed from 1989 to 2015. SETTING: Four U.S. communities. PARTICIPANTS: Community-living men and women aged 65 and older (N = 5,248, mean age 72.7 ± 5.5, 57% female, 15.2% minority) who were not wheelchair dependent and were able to give informed consent at baseline. MEASUREMENTS: Multiple lifestyle factors, including smoking, alcohol consumption, physical activity, diet, body mass index (BMI), social networks, and social support, were measured at baseline. Activities of daily living (ADLs) were assessed at baseline and throughout follow-up. Years of life (YoL) was defined as years until death. Years of able life (YAL) was defined as years without any ADL difficulty. YAL/YoL%, the proportion of life lived able, was used to indicate the relative compression or expansion of the disabled period. RESULTS: The average duration of disabled years was 4.5 (out of 15.4 mean YoL) for women and 2.9 (out of 12.4 mean YoL) for men. In a multivariable model, obesity was associated with 7.3 percentage points (95% confidence interval (CI) = 5.4-9.2) lower YAL/YoL% than normal weight. Scores in the lowest quintile of the Alternate Healthy Eating Index were associated with a 3.7% (95% CI = 1.6-5.9) lower YAL/YoL% than scores in the highest quintile. Every 25 blocks walked in a week was associated with 0.5 percentage points (95% CI = 0.3-0.8) higher YAL/YoL%. CONCLUSION: The effects of healthy lifestyle factors on the proportion of future life lived free of disability indicate that the disabled period can be compressed, given the right combination of these factors.

Changes in Depressive Symptoms and Subsequent Risk of Stroke in the Cardiovascular Health Study. - Gilsanz, Paola; Kubzansky, Laura D; Tchetgen Tchetgen, Eric J; Wang, Qianyi; Kawachi, Ichiro; Patton, Kristen K; Fitzpatrick, Annette L; Kop, Willem J; Longstreth, W T; Glymour, M Maria (Stroke, 2016)
BACKGROUND AND PURPOSE: Depression is associated with stroke, but the effects of changes in depressive symptoms on stroke risk are not well understood. This study examined whether depressive symptom changes across 2 successive annual assessments were associated with incident stroke the following year. METHODS: We used visit data from 4319 participants of the Cardiovascular Health Study who were stroke free at baseline to examine whether changes in depressive symptoms classified across 2 consecutive annual assessments predicted incident first stroke during the subsequent year. Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression scale (high versus low at ≥10). Survival models were inverse probability weighted to adjust for demographics, health behaviors, medical conditions, past depressive symptoms, censoring, and survival. RESULTS: During follow-up, 334 strokes occurred. Relative to stable low scores of depressive symptoms, improved depression symptoms were associated with almost no excess risk of stroke (adjusted hazards ratio, 1.02; 95% confidence interval, 0.66-1.58). New-onset symptoms were nonsignificantly associated with elevated stroke risk (adjusted hazards ratio, 1.44; 95% confidence interval, 0.97-2.14), whereas persistently high depressive symptoms were associated with elevated adjusted hazard of all-cause stroke (adjusted hazards ratio, 1.65; 95% confidence interval, 1.06-2.56). No evidence for effect modification by race, age, or sex was found. CONCLUSIONS: Persistently high symptoms of depression predicted elevated hazard of stroke. Participants with improved depressive symptoms had no elevation in stroke risk. Such findings suggest that strategies to reduce depressive symptoms may ameliorate stroke risk.

Common variants in DRD2 are associated with sleep duration: the CARe consortium. - Cade, Brian E; Gottlieb, Daniel J; Lauderdale, Diane S; Bennett, David A; Buchman, Aron S; Buxbaum, Sarah G; De Jager, Philip L; Evans, Daniel S; Fulop, Tibor; Gharib, Sina A; Johnson, W Craig; Kim, Hyun; et al. (Hum Mol Genet, 2016)
Sleep duration is implicated in the etiologies of chronic diseases and premature mortality. However, the genetic basis for sleep duration is poorly defined. We sought to identify novel genetic components influencing sleep duration in a multi-ethnic sample. Meta-analyses were conducted of genetic associations with self-reported, habitual sleep duration from seven Candidate Gene Association Resource (CARe) cohorts of over 25 000 individuals of African, Asian, European and Hispanic American ancestry. All individuals were genotyped for ∼50 000 SNPs from 2000 candidate heart, lung, blood and sleep genes. African-Americans had additional genome-wide genotypes. Four cohorts provided replication. A SNP (rs17601612) in the dopamine D2 receptor gene (DRD2) was significantly associated with sleep duration (P = 9.8 × 10(-7)). Conditional analysis identified a second DRD2 signal with opposite effects on sleep duration. In exploratory analysis, suggestive association was observed for rs17601612 with polysomnographically determined sleep latency (P = 0.002). The lead DRD2 signal was recently identified in a schizophrenia GWAS, and a genetic risk score of 11 additional schizophrenia GWAS loci genotyped on the IBC array was also associated with longer sleep duration (P = 0.03). These findings support a role for DRD2 in influencing sleep duration. Our work motivates future pharmocogenetics research on alerting agents such as caffeine and modafinil that interact with the dopaminergic pathway and further investigation of genetic overlap between sleep and neuro-psychiatric traits.
Keywords: Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide; Polysomnography; Receptors, Dopamine D2; Sleep; Time Factors

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

DNA methylation signatures of chronic low-grade inflammation are associated with complex diseases. - Ligthart, Symen; Marzi, Carola; Aslibekyan, Stella; Mendelson, Michael M; Conneely, Karen N; Tanaka, Toshiko; Colicino, Elena; Waite, Lindsay L; Joehanes, Roby; Guan, Weihua; Brody, Jennifer A; Elks, Cathy; et al. (Genome Biol, 2016)
BACKGROUND: Chronic low-grade inflammation reflects a subclinical immune response implicated in the pathogenesis of complex diseases. Identifying genetic loci where DNA methylation is associated with chronic low-grade inflammation may reveal novel pathways or therapeutic targets for inflammation. RESULTS: We performed a meta-analysis of epigenome-wide association studies (EWAS) of serum C-reactive protein (CRP), which is a sensitive marker of low-grade inflammation, in a large European population (n = 8863) and trans-ethnic replication in African Americans (n = 4111). We found differential methylation at 218 CpG sites to be associated with CRP (P < 1.15 × 10(-7)) in the discovery panel of European ancestry and replicated (P < 2.29 × 10(-4)) 58 CpG sites (45 unique loci) among African Americans. To further characterize the molecular and clinical relevance of the findings, we examined the association with gene expression, genetic sequence variants, and clinical outcomes. DNA methylation at nine (16%) CpG sites was associated with whole blood gene expression in cis (P < 8.47 × 10(-5)), ten (17%) CpG sites were associated with a nearby genetic variant (P < 2.50 × 10(-3)), and 51 (88%) were also associated with at least one related cardiometabolic entity (P < 9.58 × 10(-5)). An additive weighted score of replicated CpG sites accounted for up to 6% inter-individual variation (R2) of age-adjusted and sex-adjusted CRP, independent of known CRP-related genetic variants. CONCLUSION: We have completed an EWAS of chronic low-grade inflammation and identified many novel genetic loci underlying inflammation that may serve as targets for the development of novel therapeutic interventions for inflammation.

Dyspnea in Community-Dwelling Older Persons: A Multifactorial Geriatric Health Condition. - Miner, Brienne; Tinetti, Mary E; Van Ness, Peter H; Han, Ling; Leo-Summers, Linda; Newman, Anne B; Lee, Patty J; Vaz Fragoso, Carlos A (J Am Geriatr Soc, 2016)
OBJECTIVES: To evaluate the associations between a broad array of cardiorespiratory and noncardiorespiratory impairments and dyspnea in older persons. DESIGN: Cross-sectional. SETTING: Cardiovascular Health Study. PARTICIPANTS: Community-dwelling persons (N = 4,413; mean age 72.6, 57.1% female, 4.5% African American, 27.2% <high school education, 54.7% ever-smokers). MEASUREMENTS: Dyspnea severity (moderate to severe defined as American Thoracic Society Grade ≥2) and several impairments, including those established using spirometry (forced expiratory volume in 1 second (FEV1 )), maximal inspiratory pressure (respiratory muscle strength), echocardiography, ankle-brachial index, blood pressure, whole-body muscle mass (bioelectrical impedance), single chair stand (lower extremity function), grip strength, serum hemoglobin and creatinine, Center for Epidemiologic Studies Depression Scale (CES-D), Mini-Mental State Examination, medication use, and body mass index (BMI). RESULTS: In a multivariable logistic regression model, impairments that had strong associations with moderate to severe dyspnea were FEV1 less than the lower limit of normal (adjusted odds ratio (aOR) = 2.88, 95% confidence interval (CI) = 2.37-3.49), left ventricular ejection fraction less than 45% (aOR = 2.12, 95% CI = 1.43, 3.16), unable to perform a single chair stand (aOR = 2.10, 95% CI = 1.61-2.73), depressive symptoms (CES-D score ≥16; aOR = 2.02, 95% CI = 1.26-3.23), and obesity (BMI ≥30; aOR = 2.07, 95% CI = 1.67-2.55). Impairments with modest but still statistically significant associations with moderate to severe dyspnea included respiratory muscle weakness, diastolic cardiac dysfunction, grip weakness, anxiety symptoms, and use of cardiovascular and psychoactive medications (aORs = 1.31-1.71). CONCLUSION: In community-dwelling older persons, several cardiorespiratory and noncardiorespiratory impairments were significantly associated with moderate to severe dyspnea, akin to a multifactorial geriatric health condition.

Effects of Disease Burden and Functional Adaptation on Morbidity and Mortality on Older Adults. - Sanders, Jason L; Arnold, Alice M; Hirsch, Calvin H; Thielke, Stephen M; Kim, Dae; Mukamal, Kenneth J; Kizer, Jorge R; Ix, Joachim H; Kaplan, Robert C; Kritchevsky, Stephen B; Newman, Anne B (J Am Geriatr Soc, 2016)
OBJECTIVES: To ascertain whether older adults with extensive disease but relative vigor (adapters) shorten the period at the end of life in which they live with morbidity (compress morbidity). DESIGN: Prospective, community-based cohort study in four U.S. cities. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older. MEASUREMENTS: Participants were categorized into three groups according to extent of disease (assessed noninvasively), vigor, and frailty (expected agers (n = 3,528, extent of disease similar to vigor and frailty-reference group), adapters (n = 882, higher disease but vigorous), and prematurely frail (n = 855, lower disease but frail)) and compared according to years of able life (YAL), years of self-reported healthy life (YHL), and mortality using multivariable regression and survival analysis. RESULTS: After adjustment, adapters had 0.97 (95% confidence interval (CI) = 0.60-1.33) more YAL and 0.54 (95% CI = 0.19-0.90) more YHL than expected agers, and those who were prematurely frail had -0.99 (95% CI = -1.36 to -0.62) fewer YAL and -0.53 (95% CI = -0.89 to -0.17) fewer YHL than expected agers. Adapters had 0.9 more and prematurely frail had 1.5 fewer years of total life than expected agers (P < .001). Adapters spent 55% of their remaining life able and healthy, those who were prematurely frail spent 37%, and of expected agers spent 47% (P < .001). CONCLUSION: Despite similar levels of disease burden, older adults who were more vigorous appeared to compress morbidity and live longer. Older adults with higher frailty lengthened morbidity and had greater mortality. Adaptive factors may compress morbidity and decrease mortality.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

{Gene-gene Interaction Analyses for Atrial Fibrillation - Lin, H.; Mueller-Nurasyid, M.; Smith, A. V.; Arking, D. E.; Barnard, J.; Bartz, T. M.; Lunetta, K. L.; Lohman, K.; Kleber, M. E.; Lubitz, S. A.; Geelhoed, B.; Trompet, S.; et al. (Sci Rep, 2016)
{Atrial fibrillation (AF) is a heritable disease that affects more than thirty million individuals worldwide. Extensive efforts have been devoted to the study of genetic determinants of AF. The objective of our study is to examine the effect of gene-gene interaction on AF susceptibility. We performed a large-scale association analysis of gene-gene interactions with AF in 8,173 AF cases, and 65,237 AF-free referents collected from 15 studies for discovery. We examined putative interactions between genome-wide SNPs and 17 known AF-related SNPs. The top interactions were then tested for association in an independent cohort for replication, which included more than 2,363 AF cases and 114,746 AF-free referents. One interaction, between rs7164883 at the HCN4 locus and rs4980345 at the SLC28A1 locus, was found to be significantly associated with AF in the discovery cohorts (interaction OR = 1.44, 95% CI: 1.27-1.65

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

A genome-wide association study meta-analysis of clinical fracture in 10,012 African American women. - Taylor, Kira C; Evans, Daniel S; Edwards, Digna R Velez; Edwards, Todd L; Sofer, Tamar; Li, Guo; Liu, Youfang; Franceschini, Nora; Jackson, Rebecca D; Giri, Ayush; Donneyong, Macarius; Psaty, Bruce; et al. (Bone Rep, 2016)
BACKGROUND: Osteoporosis is a major public health problem associated with excess disability and mortality. It is estimated that 50-70% of the variation in osteoporotic fracture risk is attributable to genetic factors. The purpose of this hypothesis-generating study was to identify possible genetic determinants of fracture among African American (AA) women in a GWAS meta-analysis. METHODS: Data on clinical fractures (all fractures except fingers, toes, face, skull or sternum) were analyzed among AA female participants in the Women's Health Initiative (WHI) (N = 8155), Cardiovascular Health Study (CHS) (N = 504), BioVU (N = 704), Health ABC (N = 651), and the Johnston County Osteoarthritis Project (JoCoOA) (N = 291). Affymetrix (WHI) and Illumina (Health ABC, JoCoOA, BioVU, CHS) GWAS panels were used for genotyping, and a 1:1 ratio of YRI:CEU HapMap haplotypes was used as an imputation reference panel. We used Cox proportional hazard models or logistic regression to evaluate the association of ~ 2.5 million SNPs with fracture risk, adjusting for ancestry, age, and geographic region where applicable. We conducted a fixed-effects, inverse variance-weighted meta-analysis. Genome-wide significance was set at P < 5 × 10- 8. RESULTS: One SNP, rs12775980 in an intron of SVIL on chromosome 10p11.2, reached genome-wide significance (P = 4.0 × 10- 8). Although this SNP has a low minor allele frequency (0.03), there was no evidence for heterogeneity of effects across the studies (I2 = 0). This locus was not reported in any previous osteoporosis-related GWA studies. We also interrogated previously reported GWA-significant loci associated with fracture or bone mineral density in our data. One locus (SMOC1) generalized, but overall there was not substantial evidence of generalization. Possible reasons for the lack of generalization are discussed. CONCLUSION: This GWAS meta-analysis of fractures in African American women identified a potentially novel locus in the supervillin gene, which encodes a platelet-associated factor and was previously associated with platelet thrombus formation in African Americans. If validated in other populations of African descent, these findings suggest potential new mechanisms involved in fracture that may be particularly important among African Americans.

Genome-Wide Association Study of the Modified Stumvoll Insulin Sensitivity Index Identifies BCL2 and FAM19A2 as Novel Insulin Sensitivity Loci. - Walford, Geoffrey A; Gustafsson, Stefan; Rybin, Denis; Stančáková, Alena; Chen, Han; Liu, Ching-Ti; Hong, Jaeyoung; Jensen, Richard A; Rice, Ken; Morris, Andrew P; Mägi, Reedik; Tönjes, Anke; et al. (Diabetes, 2016)
Genome-wide association studies (GWAS) have found few common variants that influence fasting measures of insulin sensitivity. We hypothesized that a GWAS of an integrated assessment of fasting and dynamic measures of insulin sensitivity would detect novel common variants. We performed a GWAS of the modified Stumvoll Insulin Sensitivity Index (ISI) within the Meta-Analyses of Glucose and Insulin-Related Traits Consortium. Discovery for genetic association was performed in 16,753 individuals, and replication was attempted for the 23 most significant novel loci in 13,354 independent individuals. Association with ISI was tested in models adjusted for age, sex, and BMI and in a model analyzing the combined influence of the genotype effect adjusted for BMI and the interaction effect between the genotype and BMI on ISI (model 3). In model 3, three variants reached genome-wide significance: rs13422522 (NYAP2; P = 8.87 × 10(-11)), rs12454712 (BCL2; P = 2.7 × 10(-8)), and rs10506418 (FAM19A2; P = 1.9 × 10(-8)). The association at NYAP2 was eliminated by conditioning on the known IRS1 insulin sensitivity locus; the BCL2 and FAM19A2 associations were independent of known cardiometabolic loci. In conclusion, we identified two novel loci and replicated known variants associated with insulin sensitivity. Further studies are needed to clarify the causal variant and function at the BCL2 and FAM19A2 loci.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

Global Electric Heterogeneity Risk Score for Prediction of Sudden Cardiac Death in the General Population: The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies. - Waks, Jonathan W; Sitlani, Colleen M; Soliman, Elsayed Z; Kabir, Muammar; Ghafoori, Elyar; Biggs, Mary L; Henrikson, Charles A; Sotoodehnia, Nona; Biering-Sørensen, Tor; Agarwal, Sunil K; Siscovick, David S; Post, Wendy S; et al. (Circulation, 2016)
BACKGROUND: Asymptomatic individuals account for the majority of sudden cardiac deaths (SCDs). Development of effective, low-cost, and noninvasive SCD risk stratification tools is necessary. METHODS AND RESULTS: Participants from the Atherosclerosis Risk in Communities study and Cardiovascular Health Study (n=20 177; age, 59.3±10.1 years; age range, 44-100 years; 56% female; 77% white) were followed up for 14.0 years (median). Five ECG markers of global electric heterogeneity (GEH; sum absolute QRST integral, spatial QRST angle, spatial ventricular gradient [SVG] magnitude, SVG elevation, and SVG azimuth) were measured on standard 12-lead ECGs. Cox proportional hazards and competing risks models evaluated associations between GEH electrocardiographic parameters and SCD. An SCD competing risks score was derived from demographics, comorbidities, and GEH parameters. SCD incidence was 1.86 per 1000 person-years. After multivariable adjustment, baseline GEH parameters and large increases in GEH parameters over time were independently associated with SCD. Final SCD risk scores included age, sex, race, diabetes mellitus, hypertension, coronary heart disease, stroke, and GEH parameters as continuous variables. When GEH parameters were added to clinical/demographic factors, the C statistic increased from 0.777 to 0.790 (P=0.008), the risk score classified 10-year SCD risk as high (>5%) in 7.2% of participants, 10% of SCD victims were appropriately reclassified into a high-risk category, and only 1.4% of SCD victims were inappropriately reclassified from high to intermediate risk. The net reclassification index was 18.3%. CONCLUSIONS: Abnormal electrophysiological substrate quantified by GEH parameters is independently associated with SCD in the general population. The addition of GEH parameters to clinical characteristics improves SCD risk prediction.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Incident Atrial Fibrillation and Disability-Free Survival in the Cardiovascular Health Study. - Wallace, Erin R; Siscovick, David S; Sitlani, Colleen M; Dublin, Sascha; Mitchell, Pamela H; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Heckbert, Susan R (J Am Geriatr Soc, 2016)
OBJECTIVES: To assess the associations between incident atrial fibrillation (AF) and disability-free survival and risk of disability. DESIGN: Prospective cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older and enrolled in fee-for-service Medicare followed between 1991 and 2009 (MN = 4,046). Individuals with prevalent AF, activity of daily living (ADL) disability, or a history of stroke or heart failure at baseline were excluded. MEASUREMENTS: Incident AF was identified according to annual study electrocardiogram, hospital discharge diagnosis, or Medicare claims. Disability-free survival was defined as survival free of ADL disability (any difficulty or inability in bathing, dressing, eating, using the toilet, walking around the home, or getting out of a bed or chair). ADLs were assessed at annual study visits or in a telephone interview. Association between incident AF and disability-free survival or risk of disability was estimated using Cox proportional hazards models. RESULTS: Over an average of 7.0 years of follow-up, 660 individuals (16.3%) developed incident AF, and 3,112 (77%) became disabled or died. Incident AF was associated with shorter disability-free survival (hazard ratio (HR) for death or ADL disability = 1.71, 95% confidence interval (CI) = 1.55-1.90) and a higher risk of ADL disability (HR = 1.36, 95% CI = 1.18-1.58) than in individuals with no history of AF. This association persisted after adjustment for interim stroke and heart failure. CONCLUSION: These results suggest that AF is a risk factor for shorter functional longevity in older adults, independent of other risk factors and comorbid conditions.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Atrial Fibrillation; Disability Evaluation; Electrocardiography; Female; Geriatric Assessment; Humans; Incidence; Longevity; Longitudinal Studies; Male; Medicare; Prevalence; Prospective Studies; Survival Rate; United States

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

Interaction of methylation-related genetic variants with circulating fatty acids on plasma lipids: a meta-analysis of 7 studies and methylation analysis of 3 studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Ma, Yiyi; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Manichaikul, Ani W; Chu, Audrey Y; Samieri, Cecilia; Zhou, Xia; Guan, Weihua; Wang, Lu; Biggs, Mary L; Chen, Yii-der I; et al. (Am J Clin Nutr, 2016)
BACKGROUND: DNA methylation is influenced by diet and single nucleotide polymorphisms (SNPs), and methylation modulates gene expression. OBJECTIVE: We aimed to explore whether the gene-by-diet interactions on blood lipids act through DNA methylation. DESIGN: We selected 7 SNPs on the basis of predicted relations in fatty acids, methylation, and lipids. We conducted a meta-analysis and a methylation and mediation analysis with the use of data from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium and the ENCODE (Encyclopedia of DNA Elements) consortium. RESULTS: On the basis of the meta-analysis of 7 cohorts in the CHARGE consortium, higher plasma HDL cholesterol was associated with fewer C alleles at ATP-binding cassette subfamily A member 1 (ABCA1) rs2246293 (β = -0.6 mg/dL, P = 0.015) and higher circulating eicosapentaenoic acid (EPA) (β = 3.87 mg/dL, P = 5.62 × 10(21)). The difference in HDL cholesterol associated with higher circulating EPA was dependent on genotypes at rs2246293, and it was greater for each additional C allele (β = 1.69 mg/dL, P = 0.006). In the GOLDN (Genetics of Lipid Lowering Drugs and Diet Network) study, higher ABCA1 promoter cg14019050 methylation was associated with more C alleles at rs2246293 (β = 8.84%, P = 3.51 × 10(18)) and lower circulating EPA (β = -1.46%, P = 0.009), and the mean difference in methylation of cg14019050 that was associated with higher EPA was smaller with each additional C allele of rs2246293 (β = -2.83%, P = 0.007). Higher ABCA1 cg14019050 methylation was correlated with lower ABCA1 expression (r = -0.61, P = 0.009) in the ENCODE consortium and lower plasma HDL cholesterol in the GOLDN study (r = -0.12, P = 0.0002). An additional mediation analysis was meta-analyzed across the GOLDN study, Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. Compared with the model without the adjustment of cg14019050 methylation, the model with such adjustment provided smaller estimates of the mean plasma HDL cholesterol concentration in association with both the rs2246293 C allele and EPA and a smaller difference by rs2246293 genotypes in the EPA-associated HDL cholesterol. However, the differences between 2 nested models were NS (P > 0.05). CONCLUSION: We obtained little evidence that the gene-by-fatty acid interactions on blood lipids act through DNA methylation.
Keywords: Apolipoproteins E; ATP Binding Cassette Transporter 1; Cholesterol, HDL; Cohort Studies; Diet; DNA Methylation; Eicosapentaenoic Acid; Epigenesis, Genetic; Fatty Acids; Gene Expression Regulation; Humans; Lipids; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Triglycerides

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Large-scale pharmacogenomic study of sulfonylureas and the QT, JT and QRS intervals: CHARGE Pharmacogenomics Working Group. - Floyd, J S; Sitlani, C M; Avery, C L; Noordam, R; Li, X; Smith, A V; Gogarten, S M; Li, J; Broer, L; Evans, D S; Trompet, S; Brody, J A; et al. (Pharmacogenomics J, 2016)
Sulfonylureas, a commonly used class of medication used to treat type 2 diabetes, have been associated with an increased risk of cardiovascular disease. Their effects on QT interval duration and related electrocardiographic phenotypes are potential mechanisms for this adverse effect. In 11 ethnically diverse cohorts that included 71 857 European, African-American and Hispanic/Latino ancestry individuals with repeated measures of medication use and electrocardiogram (ECG) measurements, we conducted a pharmacogenomic genome-wide association study of sulfonylurea use and three ECG phenotypes: QT, JT and QRS intervals. In ancestry-specific meta-analyses, eight novel pharmacogenomic loci met the threshold for genome-wide significance (P<5 × 10(-8)), and a pharmacokinetic variant in CYP2C9 (rs1057910) that has been associated with sulfonylurea-related treatment effects and other adverse drug reactions in previous studies was replicated. Additional research is needed to replicate the novel findings and to understand their biological basis.The Pharmacogenomics Journal advance online publication, 13 December 2016; doi:10.1038/tpj.2016.90.

Longitudinal assessment of N-terminal pro-B-type natriuretic peptide and risk of diabetes in older adults: The cardiovascular health study. - Brutsaert, Erika F; Biggs, Mary L; Delaney, Joseph A; Djoussé, Luc; Gottdiener, John S; Ix, Joachim H; Kim, Francis; Mukamal, Kenneth J; Siscovick, David S; Tracy, Russell P; de Boer, Ian H; deFilippi, Christopher R; et al. (Metabolism, 2016)
INTRODUCTION: Natriuretic peptides have a well-recognized role in cardiovascular homeostasis. Recently, higher levels of B-type natriuretic peptide (BNP) have also been associated with decreased risk of diabetes in middle-aged adults. Whether this association persists into older age, where the pathophysiology of diabetes changes, has not been established, nor has its intermediate pathways. METHODS: We investigated the relationship between N-terminal (NT)-proBNP and incident diabetes in 2359 older adults free of cardiovascular disease or chronic kidney disease in the Cardiovascular Health Study. RESULTS: We documented 348 incident cases of diabetes over 12.6years of median follow-up. After adjusting for age, sex, race, body mass index, systolic blood pressure, anti-hypertensive treatment, smoking, alcohol use, and LDL, each doubling of NT-proBNP was associated with a 9% lower risk of incident diabetes (HR=0.91 [95% CI: 0.84-0.99]). Additional adjustment for waist circumference, physical activity, estimated glomerular filtration rate or C-reactive protein did not influence the association. Among putative mediators, HDL and triglycerides, adiponectin, and especially homeostasis model assessment of insulin resistance, all appeared to account for a portion of the lower risk associated with NT-proBNP. CONCLUSION: In older adults without prevalent cardiovascular or kidney disease, higher NT-proBNP is associated with decreased risk of incident diabetes even after adjustment for traditional risk factors. These findings suggest that the metabolic effects of natriuretic peptides persist late in life and offer a potential therapeutic target for prevention of diabetes in older people.

Longitudinal Relationship Between Loneliness and Social Isolation in Older Adults: Results From the Cardiovascular Health Study. - Petersen, Johanna; Kaye, Jeffrey; Jacobs, Peter G; Quinones, Ana; Dodge, Hiroko; Arnold, Alice; Thielke, Stephen (J Aging Health, 2016)
OBJECTIVE: To understand the longitudinal relationship between loneliness and isolation. METHOD: Participants included 5,870 adults 65 years and older (M = 72.89 ± 5.59 years) from the first 5 years of the Cardiovascular Health Study. Loneliness was assessed using a dichotomized loneliness question. Social isolation was assessed using six items from the Lubben Social Network Scale. Yearly life events were included to assess abrupt social network changes. Mixed effects logistic regression was employed to analyze the relationship between isolation and loneliness. RESULTS: Higher levels of social isolation were associated with higher odds of loneliness, as was an increase (from median) in level of social isolation. Life events such as a friend dying were also associated with increased odds of loneliness. DISCUSSION: These results suggest that average level of isolation and increases in the level of isolation are closely tied to loneliness, which has implications for future assessment or monitoring of loneliness in older adult populations.

Longitudinal Relationships between Caloric Expenditure and Gray Matter in the Cardiovascular Health Study. - Raji, Cyrus A; Merrill, David A; Eyre, Harris; Mallam, Sravya; Torosyan, Nare; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Carmichael, Owen T; Gach, H Michael; Thompson, Paul M; Longstreth, W T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity (PA) can be neuroprotective and reduce the risk for Alzheimer's disease (AD). In assessing physical activity, caloric expenditure is a proxy marker reflecting the sum total of multiple physical activity types conducted by an individual. OBJECTIVE: To assess caloric expenditure, as a proxy marker of PA, as a predictive measure of gray matter (GM) volumes in the normal and cognitively impaired elderly persons. METHODS: All subjects in this study were recruited from the Institutional Review Board approved Cardiovascular Health Study (CHS), a multisite population-based longitudinal study in persons aged 65 and older. We analyzed a sub-sample of CHS participants 876 subjects (mean age 78.3, 57.5% F, 42.5% M) who had i) energy output assessed as kilocalories (kcal) per week using the standardized Minnesota Leisure-Time Activities questionnaire, ii) cognitive assessments for clinical classification of normal cognition, mild cognitive impairment (MCI), and AD, and iii) volumetric MR imaging of the brain. Voxel-based morphometry modeled the relationship between kcal/week and GM volumes while accounting for standard covariates including head size, age, sex, white matter hyperintensity lesions, MCI or AD status, and site. Multiple comparisons were controlled using a False Discovery Rate of 5 percent. RESULTS: Higher energy output, from a variety of physical activity types, was associated with larger GM volumes in frontal, temporal, and parietal lobes, as well as hippocampus, thalamus, and basal ganglia. High levels of caloric expenditure moderated neurodegeneration-associated volume loss in the precuneus, posterior cingulate, and cerebellar vermis. CONCLUSION: Increasing energy output from a variety of physical activities is related to larger gray matter volumes in the elderly, regardless of cognitive status.

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

Novel Genetic Loci Associated With Retinal Microvascular Diameter. - Jensen, Richard A; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdottir, Johanna; Cheng, Ching-Yu; Brody, Jennifer A; Cotch, Mary Frances; McKnight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. METHODS AND RESULTS: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 (P=3.1×10(-) (11); minor allele frequency=0.43), rs201259422 in TSPAN10 (P=4.4×10(-9); minor allele frequency=0.27), rs5442 in GNB3 (P=7.0×10(-10); minor allele frequency=0.05), and rs1800407 in OCA2 (P=3.4×10(-8); minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent (P=6.5×10(-12)). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic (P=0.001) and diastolic blood pressures (P=8.3×10(-04)). CONCLUSIONS: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease.

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Prospective study of γ' fibrinogen and incident venous thromboembolism: The Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Tang, Weihong; George, Kristen M; Heckbert, Susan R; MacLehose, Richard F; Cushman, Mary; Pankow, James S (Thromb Res, 2016)
INTRODUCTION: Epidemiological studies generally have not found plasma total fibrinogen to be a risk factor for venous thromboembolism (VTE), but several have reported associations between variants in the fibrinogen gamma gene (FGG) and VTE. A case-control study in whites suggested plasma γ' fibrinogen concentration may be associated inversely with VTE, but this was not replicated in African Americans. OBJECTIVE: To examine the prospective association between γ' fibrinogen concentrations and occurrence of VTE. METHODS: We used the Longitudinal Investigation of Thromboembolism Etiology (LITE), involving two pooled population-based cohorts in the United States including 16,234 participants. The cohorts comprised white and African American men and women, aged 50years and older at study onset in the early 1990s. We identified VTEs during follow-up and documented they met standardized diagnostic criteria. RESULTS: During two decades of follow-up, neither γ' fibrinogen nor total fibrinogen nor their ratio was associated with VTE overall (n=521 VTEs), in subgroups defined by race, or in other subgroups. In both race groups, the minor allele of FGG rs2066865 was associated with lower γ' fibrinogen concentrations, but this allele was not associated with VTE. CONCLUSIONS: A lower plasma concentration of γ' fibrinogen in healthy adults does not appear to increase VTE risk.

Relations of Postload and Fasting Glucose With Incident Cardiovascular Disease and Mortality Late in Life: The Cardiovascular Health Study. - Brutsaert, Erika F; Shitole, Sanyog; Biggs, Mary Lou; Mukamal, Kenneth J; deBoer, Ian H; Thacker, Evan L; Barzilay, Joshua I; Djoussé, Luc; Ix, Joachim H; Smith, Nicholas L; Kaplan, Robert C; Siscovick, David S; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Older adults have a high prevalence of postload hyperglycemia. Postload glucose has shown more robust associations with cardiovascular disease (CVD) and death than fasting glucose, but data in the oldest old are sparse. METHODS: Fasting and 2-hour postload glucose were measured in community-dwelling older adults, mean age 78, at the 1996-1997 follow-up visit of the Cardiovascular Health Study. We evaluated their associations with atherosclerotic CVD (ASCVD) and mortality using standard Cox regression and competing-risks analyses and assessed improvement in prediction-model discrimination with the c-statistic. RESULTS: Among 2,394 participants without treated diabetes and available data on glycemic measures, there were 579 ASCVD events and 1,698 deaths during median follow-up of 11.2 years. In fully adjusted models, both fasting and 2-hour glucose were associated with ASCVD (HR per SD, 1.13 [1.03-1.25] and 1.17 [1.07-1.28], respectively) and all-cause mortality (HR 1.12 [1.07-1.18] and 1.14 [1.08-1.20]). After mutual adjustment, however, the associations for fasting glucose with both outcomes were abolished, but those for postload glucose were largely unchanged. Consistent findings were observed for ASCVD in competing-risks models. CONCLUSION: In adults surviving to advanced old age, postload glucose was associated with ASCVD and mortality independently of fasting glucose, but fasting glucose was not associated with these outcomes independently of postload glucose. These findings affirm the robust association of postload glucose with ASCVD and death late in life.
Keywords: Aged; Aging; Blood Glucose; Cardiovascular Diseases; Fasting; Female; Follow-Up Studies; Glucose; Glucose Tolerance Test; Health Surveys; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; United States

Rooted in risk: genetic predisposition for low-density lipoprotein cholesterol level associates with diminished low-density lipoprotein cholesterol response to statin treatment. - Smit, Roelof Aj; Postmus, Iris; Trompet, Stella; Barnes, Michael R; Warren, Helen; Arsenault, Benoit J; Chasman, Daniel I; Cupples, L Adrienne; Hitman, Graham A; Krauss, Ronald M; Li, Xiaohui; Psaty, Bruce M; et al. (Pharmacogenomics, 2016)
AIMS: To utilize previously reported lead SNPs for low-density lipoprotein cholesterol (LDL-c) levels to find additional loci of importance to statin response, and examine whether genetic predisposition to LDL-c levels associates with differential statin response. METHODS: We investigated effects on statin response of 59 LDL-c SNPs, by combining summary level statistics from the Global Lipids Genetics and Genomic Investigation of Statin Therapy consortia. RESULTS: Lead SNPs for APOE, SORT1 and NPC1L1 were associated with a decreased LDL-c response to statin treatment, as was overall genetic predisposition for increased LDL-c levels as quantified with 59 SNPs, with a 5.4% smaller statin response per standard deviation increase in genetically raised LDL-c levels. CONCLUSION: Genetic predisposition for increased LDL-c level may decrease efficacy of statin therapy.
Keywords: Cholesterol, LDL; Genetic Predisposition to Disease; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide; Triglycerides

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

740 adults from 20 prospective cohort studies - Wu, J. H. Y.; Marklund, M.; Imamura, F.; Tintle, N.; Ardisson Korat, A. V.; de Goede, J.; Zhou, X.; Yang, W. S.; de Oliveira Otto, M. C.; ger, J.; Qureshi, W.; Virtanen, J. K.; et al. (Lancet Diabetes Endocrinol, 2017)
The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes.\ We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We analysed data from 20 prospective cohort studies from ten countries (Iceland, the Netherlands, the USA, Taiwan, the UK, Germany, Finland, Australia, Sweden, and France), with biomarkers sampled between 1970 and 2010. Participants included in the analyses were aged 18 years or older and had data available for linoleic acid and arachidonic acid biomarkers at baseline. We excluded participants with type 2 diabetes at baseline. The main outcome was the association between omega-6 PUFA biomarkers and incident type 2 diabetes. We assessed the relative risk of type 2 diabetes prospectively for each cohort and lipid compartment separately using a prespecified analytic plan for exposures, covariates, effect modifiers, and analysis, and the findings were then pooled using inverse-variance weighted meta-analysis.\ 13).\ Findings suggest that linoleic acid has long-term benefits for the prevention of type 2 diabetes and that arachidonic acid is not harmful.\ Funders are shown in the appendix.

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)

Assessing the causal relationship between obesity and venous thromboembolism through a Mendelian Randomization study. - Lindström, Sara; Germain, Marine; Crous-Bou, Marta; Smith, Erin N; Morange, Pierre-Emmanuel; van Hylckama Vlieg, Astrid; de Haan, Hugoline G; Chasman, Daniel; Ridker, Paul; Brody, Jennifer; de Andrade, Mariza; Heit, John A; et al. (Hum Genet, 2017)
Observational studies have shown an association between obesity and venous thromboembolism (VTE) but it is not known if observed associations are causal, due to reverse causation or confounding bias. We conducted a Mendelian Randomization study of body mass index (BMI) and VTE. We identified 95 single nucleotide polymorphisms (SNPs) that have been previously associated with BMI and assessed the association between genetically predicted high BMI and VTE leveraging data from a previously conducted GWAS within the INVENT consortium comprising a total of 7507 VTE cases and 52,632 controls of European ancestry. Five BMI SNPs were associated with VTE at P < 0.05, with the strongest association seen for the FTO SNP rs1558902 (OR 1.07, 95% CI 1.02-1.12, P = 0.005). In addition, we observed a significant association between genetically predicted BMI and VTE (OR = 1.59, 95% CI 1.30-1.93 per standard deviation increase in BMI, P = 5.8 × 10). Our study provides evidence for a causal relationship between high BMI and risk of VTE. Reducing obesity levels will likely result in lower incidence in VTE.
Keywords: Adult; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Incidence; Logistic Models; Male; Mendelian Randomization Analysis; Obesity; Polymorphism, Single Nucleotide; Proportional Hazards Models; Venous Thromboembolism

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Mitochondrial DNA Copy Number With Cardiovascular Disease. - Ashar, Foram N; Zhang, Yiyi; Longchamps, Ryan J; Lane, John; Moes, Anna; Grove, Megan L; Mychaleckyj, Josyf C; Taylor, Kent D; Coresh, Josef; Rotter, Jerome I; Boerwinkle, Eric; Pankratz, Nathan; et al. (JAMA Cardiol, 2017)
Importance: Mitochondrial dysfunction is a core component of the aging process and may play a key role in atherosclerotic cardiovascular disease. Mitochondrial DNA copy number (mtDNA-CN), which represents the number of mitochondria per cell and number of mitochondrial genomes per mitochondrion, is an indirect biomarker of mitochondrial function. Objective: To determine whether mtDNA-CN, measured in an easily accessible tissue (buffy coat/circulating leukocytes), can improve risk classification for cardiovascular disease (CVD) and help guide initiation of statin therapy for primary prevention of CVD. Design, Setting, and Participants: Prospective, population-based cohort analysis including 21 870 participants (20 163 free from CVD at baseline) from 3 studies: Cardiovascular Health Study (CHS), Atherosclerosis Risk in Communities Study (ARIC), and Multiethnic Study of Atherosclerosis (MESA). The mean follow-up was 13.5 years. The study included 11 153 participants from ARIC, 4830 from CHS, and 5887 from MESA. Analysis of the data was conducted from March 10, 2014, to January 29, 2017. Exposures: Mitochondrial DNA-CN measured from buffy coat/circulating leukocytes. Main Outcomes and Measures: Incident CVD, which combines coronary heart disease, defined as the first incident myocardial infarction or death owing to coronary heart disease, and stroke, defined as the first nonfatal stroke or death owing to stroke. Results: Of the 21 870 participants, the mean age was 62.4 years (ARIC, 57.9 years; MESA, 62.4 years; and CHS, 72.5 years), and 54.7% of participants were women. The hazard ratios for incident coronary heart disease, stroke, and CVD associated with a 1-SD decrease in mtDNA-CN were 1.29 (95% CI, 1.24-1.33), 1.11 (95% CI, 1.06-1.16), and 1.23 (95% CI, 1.19-1.26). The associations persisted after adjustment for traditional CVD risk factors. Addition of mtDNA-CN to the 2013 American College of Cardiology/American Heart Association Pooled Cohorts Equations for estimating 10-year hard atherosclerosis CVD risk was associated with improved risk classification (continuous net reclassification index, 0.194; 95% CI, 0.130-0.258; P < .001). Mitochondrial DNA-CN further improved sensitivity and specificity for the 2013 American College of Cardiology/American Heart Association recommendations on initiating statin therapy for primary prevention of ASCVD (net 221 individuals appropriately downclassified and net 15 individuals appropriately upclassified). Conclusions and Relevance: Mitochondrial DNA-CN was independently associated with incident CVD in 3 large prospective studies and may have potential clinical utility in improving CVD risk classification.

Bivariate Genome-Wide Association Study of Depressive Symptoms with Type 2 Diabetes and Quantitative Glycemic Traits. - Haljas, Kadri; Amare, Azmeraw T; Alizadeh, Behrooz Z; Hsu, Yi-Hsiang; Mosley, Thomas; Newman, Anne; Murabito, Joanne; Tiemeier, Henning; Tanaka, Toshiko; van Duijn, Cornelia; Ding, Jingzhong; Llewellyn, David J; et al. (Psychosom Med, 2017)
OBJECTIVE: Shared genetic background may explain phenotypic associations between depression and Type-2-Diabetes (T2D). We aimed to study, on a genome-wide level, if genetic correlation and pleiotropic loci exist between depressive symptoms and T2D or glycemic traits. METHODS: We estimated SNP-based heritability and analyzed genetic correlation between depressive symptoms and T2D and glycemic traits with the LD Score Regression (LDSC) by combining summary statistics of previously conducted meta-analyses for depressive symptoms by CHARGE consortium (N = 51,258), T2D by Diagram consortium (N = 34,840 patients and 114,981 controls), fasting glucose, fasting insulin, HOMA-β, and HOMA-IR by MAGIC consortium (N = 58,074). Finally, we investigated pleiotropic loci using a bivariate GWAS approach with summary statistics from GWAS meta-analyses and reported loci with genome-wide significant bivariate association p-value (p < 5x10). Biological annotation and function of significant pleiotropic SNPs were assessed in several databases. RESULTS: The SNP-based heritability ranged from 0.04 to 0.10 in each individual trait. In the LDSC analyses, depressive symptoms showed no significant genetic correlation with T2D or glycemic traits (p > 0.37). Yet, we identified pleiotropic genetic variations for depressive symptoms and T2D (in the IGF2BP2, CDKAL1, CDKN2B-AS, and PLEKHA1 genes), and fasting glucose (in the MADD, CDKN2B-AS, PEX16, and MTNR1B genes). CONCLUSIONS: We found no significant overall genetic correlations between depressive symptoms, T2D or glycemic traits suggesting major differences in underlying biology of these traits. Yet, several potential pleiotropic loci were identified between depressive symptoms, T2D and fasting glucose suggesting that previously established phenotypic associations may be partly explained by genetic variation in these specific loci.

Comparison of HapMap and 1000 Genomes Reference Panels in a Large-Scale Genome-Wide Association Study. - de Vries, Paul S; Sabater-Lleal, Maria; Chasman, Daniel I; Trompet, Stella; Ahluwalia, Tarunveer S; Teumer, Alexander; Kleber, Marcus E; Chen, Ming-Huei; Wang, Jie Jin; Attia, John R; Marioni, Riccardo E; Steri, Maristella; et al. (PLoS One, 2017)
An increasing number of genome-wide association (GWA) studies are now using the higher resolution 1000 Genomes Project reference panel (1000G) for imputation, with the expectation that 1000G imputation will lead to the discovery of additional associated loci when compared to HapMap imputation. In order to assess the improvement of 1000G over HapMap imputation in identifying associated loci, we compared the results of GWA studies of circulating fibrinogen based on the two reference panels. Using both HapMap and 1000G imputation we performed a meta-analysis of 22 studies comprising the same 91,953 individuals. We identified six additional signals using 1000G imputation, while 29 loci were associated using both HapMap and 1000G imputation. One locus identified using HapMap imputation was not significant using 1000G imputation. The genome-wide significance threshold of 5×10-8 is based on the number of independent statistical tests using HapMap imputation, and 1000G imputation may lead to further independent tests that should be corrected for. When using a stricter Bonferroni correction for the 1000G GWA study (P-value < 2.5×10-8), the number of loci significant only using HapMap imputation increased to 4 while the number of loci significant only using 1000G decreased to 5. In conclusion, 1000G imputation enabled the identification of 20% more loci than HapMap imputation, although the advantage of 1000G imputation became less clear when a stricter Bonferroni correction was used. More generally, our results provide insights that are applicable to the implementation of other dense reference panels that are under development.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Coronary Artery Bypass Graft Surgery and Dementia Risk in the Cardiovascular Health Study. - Kuźma, Elżbieta; Airdrie, Jac; Littlejohns, Thomas J; Lourida, Ilianna; Thompson-Coon, Jo; Lang, Iain A; Scrobotovici, Monica; Thacker, Evan L; Fitzpatrick, Annette; Kuller, Lewis H; Lopez, Oscar L; Longstreth, William T; et al. (Alzheimer Dis Assoc Disord, 2017)
INTRODUCTION: The association between history of coronary artery bypass graft surgery (CABG) and dementia risk remains unclear. METHODS: We conducted a prospective cohort analysis using data on 3155 elderly adults free from prevalent dementia from the US population-based Cardiovascular Health Study (CHS) with adjudicated incident all-cause dementia, Alzheimer disease (AD), vascular dementia (VaD), and mixed dementia. RESULTS: In the CHS, the hazard ratio (HR) for all-cause dementia was 1.93 [95% confidence interval (CI), 1.36-2.74] for those with CABG history compared with those with no CABG history after adjustment for potential confounders. Similar HRs were observed for AD (HR=1.71; 95% CI, 0.98-2.98), VaD (HR=1.42; 95% CI, 0.56-3.65), and mixed dementia (HR=2.73; 95% CI, 1.55-4.80). The same pattern of results was observed when these CHS findings were pooled with a prior prospective study, the pooled HRs were 1.96 (95% CI, 1.42-2.69) for all-cause dementia, 1.71 (95% CI, 1.04-2.79) for AD and 2.20 (95% CI, 0.78-6.19) for VaD. DISCUSSION: Our results suggest CABG history is associated with long-term dementia risk. Further investigation is warranted to examine the causal mechanisms which may explain this relationship or whether the association reflects differences in coronary artery disease severity.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal. http://creativecommons.org/licenses/by-nc-nd/4.0/.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery and fine-mapping of loci associated with monounsaturated fatty acids through trans-ethnic meta-analysis in Chinese and European populations. - Hu, Yao; Tanaka, Toshiko; Zhu, Jingwen; Guan, Weihua; Wu, Jason H Y; Psaty, Bruce M; McKnight, Barbara; King, Irena B; Sun, Qi; Richard, Melissa; Manichaikul, Ani; Frazier-Wood, Alexis C; et al. (J Lipid Res, 2017)
Monounsaturated fatty acids (MUFAs) are unsaturated fatty acids with one double bond and are derived from endogenous synthesis and dietary intake. Accumulating evidence has suggested that plasma and erythrocyte MUFA levels were associated with cardiometabolic disorders including cardiovascular disease (CVD), type 2 diabetes (T2D) and metabolic syndrome (MS). Previous genome-wide association studies (GWAS) have identified seven loci for plasma and erythrocyte palmitoleic acid and oleic acid levels in populations of European origin. To identify additional MUFA-associated loci and the potential causal variant at each locus, we performed ethnic-specific GWAS meta-analyses and trans-ethnic meta-analyses in over 15,000 participants of Chinese- and European-ancestry. We identified novel genome-wide significant associations for vaccenic acid at FADS1/2 and PKD2L1 [log10(Bayes factor)>=8.07] and for gondoic acid at FADS1/2 and GCKR [log10(Bayes factor)>=61619;6.22], and also observed improved fine-mapping resolutions at FADS1/2 and GCKR loci. The greatest improvement was observed at GCKR, where the number of variants in the 99% credible set was reduced from 16 (covering ~95kb) to five (covering ~20kb, including a missense variant rs1260326) after trans-ethnic meta-analysis. We also confirmed the previously reported associations of PKD2L1, FADS1/2, GCKR and HIF1AN with palmitoleic acid and of FADS1/2 and LPCAT3 with oleic acid in the Chinese-specific GWAS and trans-ethnic meta-analyses. Pathway-based analyses suggested that the identified loci were enriched in unsaturated fatty acids metabolism and signaling pathways. Our findings provided novel insight into the genetic basis relevant to MUFA metabolism and biology.

Discovery and replication of SNP-SNP interactions for quantitative lipid traits in over 60,000 individuals. - Holzinger, Emily R; Verma, Shefali S; Moore, Carrie B; Hall, Molly; De, Rishika; Gilbert-Diamond, Diane; Lanktree, Matthew B; Pankratz, Nathan; Amuzu, Antoinette; Burt, Amber; Dale, Caroline; Dudek, Scott; et al. (BioData Min, 2017)
BACKGROUND: The genetic etiology of human lipid quantitative traits is not fully elucidated, and interactions between variants may play a role. We performed a gene-centric interaction study for four different lipid traits: low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TG). RESULTS: Our analysis consisted of a discovery phase using a merged dataset of five different cohorts (n = 12,853 to n = 16,849 depending on lipid phenotype) and a replication phase with ten independent cohorts totaling up to 36,938 additional samples. Filters are often applied before interaction testing to correct for the burden of testing all pairwise interactions. We used two different filters: 1. A filter that tested only single nucleotide polymorphisms (SNPs) with a main effect of p < 0.001 in a previous association study. 2. A filter that only tested interactions identified by Biofilter 2.0. Pairwise models that reached an interaction significance level of p < 0.001 in the discovery dataset were tested for replication. We identified thirteen SNP-SNP models that were significant in more than one replication cohort after accounting for multiple testing. CONCLUSIONS: These results may reveal novel insights into the genetic etiology of lipid levels. Furthermore, we developed a pipeline to perform a computationally efficient interaction analysis with multi-cohort replication.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Fine mapping of QT interval regions in global populations refines previously identified QT interval loci and identifies signals unique to African and Hispanic descent populations. - Avery, Christy L; Wassel, Christina L; Richard, Melissa A; Highland, Heather M; Bien, Stephanie; Zubair, Niha; Soliman, Elsayed Z; Fornage, Myriam; Bielinski, Suzette J; Tao, Ran; Seyerle, Amanda A; Shah, Sanjiv J; et al. (Heart Rhythm, 2017)
BACKGROUND: The electrocardiographically measured QT interval (QT) is heritable and its prolongation is an established risk factor for several cardiovascular diseases. Yet, most QT genetic studies have been performed in European ancestral populations, possibly reducing their global relevance. OBJECTIVE: To leverage diversity and improve biological insight, we fine mapped 16 of the 35 previously identified QT loci (46%) in populations of African American (n = 12,410) and Hispanic/Latino (n = 14,837) ancestry. METHODS: Racial/ethnic-specific multiple linear regression analyses adjusted for heart rate and clinical covariates were examined separately and in combination after inverse-variance weighted trans-ethnic meta-analysis. RESULTS: The 16 fine-mapped QT loci included on the Illumina Metabochip represented 21 independent signals, of which 16 (76%) were significantly (P-value≤9.1×10(-5)) associated with QT. Through sequential conditional analysis we also identified three trans-ethnic novel SNPs at ATP1B1, SCN5A-SCN10A, and KCNQ1 and three Hispanic/Latino-specific novel SNPs at NOS1AP and SCN5A-SCN10A (two novel SNPs) with evidence of associations with QT independent of previous identified GWAS lead SNPs. Linkage disequilibrium patterns helped to narrow the region likely to contain the functional variants at several loci, including NOS1AP, USP50-TRPM7, and PRKCA, although intervals surrounding SLC35F1-PLN and CNOT1 remained broad in size (>100 kb). Finally, bioinformatics-based functional characterization suggested a regulatory function in cardiac tissues for the majority of independent signals that generalized and the novel SNPs. CONCLUSION: Our findings suggest that a majority of identified SNPs implicate gene regulatory dysfunction in QT prolongation, that the same loci influence variation in QT across global populations, and that additional, novel, population-specific QT signals exist.

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

{Genetic Risk Prediction of Atrial Fibrillation - Lubitz, S. A.; Yin, X.; Lin, H. J.; Kolek, M.; Smith, J. G.; Trompet, S.; Rienstra, M.; Rost, N. S.; Teixeira, P. L.; Almgren, P.; Anderson, C. D.; Chen, L. Y.; et al. (Circulation, 2017)
Atrial fibrillation (AF) has a substantial genetic basis. Identification of individuals at greatest AF risk could minimize the incidence of cardioembolic stroke.\ To determine whether genetic data can stratify risk for development of AF, we examined associations between AF genetic risk scores and incident AF in 5 prospective studies comprising 18 919 individuals of European ancestry. We examined associations between AF genetic risk scores and ischemic stroke in a separate study of 509 ischemic stroke cases (202 cardioembolic [40%]) and 3028 referents. Scores were based on 11 to 719 common variants (≥5%) associated with AF at P values ranging from <1×10-3 to <1×10-8 in a prior independent genetic association study.\ Incident AF occurred in 1032 individuals (5.5%). AF genetic risk scores were associated with new-onset AF after adjustment for clinical risk factors. The pooled hazard ratio for incident AF for the highest versus lowest quartile of genetic risk scores ranged from 1.28 (719 variants; 95% confidence interval, 1.13-1.46; P=1.5×10-4) to 1.67 (25 variants; 95% confidence interval, 1.47-1.90; P=9.3×10-15). Discrimination of combined clinical and genetic risk scores varied across studies and scores (maximum C statistic, 0.629-0.811; maximum ΔC statistic from clinical score alone, 0.009-0.017). AF genetic risk was associated with stroke in age- and sex-adjusted models. For example, individuals in the highest versus lowest quartile of a 127-variant score had a 2.49-fold increased odds of cardioembolic stroke (95% confidence interval, 1.39-4.58; P=2.7×10-3). The effect persisted after the exclusion of individuals (n=70) with known AF (odds ratio, 2.25; 95% confidence interval, 1.20-4.40; P=0.01).\ Comprehensive AF genetic risk scores were associated with incident AF beyond associations for clinical AF risk factors but offered small improvements in discrimination. AF genetic risk was also associated with cardioembolic stroke in age- and sex-adjusted analyses. Efforts are warranted to determine whether AF genetic risk may improve identification of subclinical AF or help distinguish between stroke mechanisms.

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

Genome-Wide Association Study Meta-Analysis of Long-Term Average Blood Pressure in East Asians. - Li, Changwei; Kim, Yun Kyoung; Dorajoo, Rajkumar; Li, Huaixing; Lee, I-Te; Cheng, Ching-Yu; He, Meian; Sheu, Wayne H-H; Guo, Xiuqing; Ganesh, Santhi K; He, Jiang; Lee, Juyoung; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide single marker and gene-based meta-analyses of long-term average (LTA) blood pressure (BP) phenotypes may reveal novel findings for BP. METHODS AND RESULTS: We conducted genome-wide analysis among 18 422 East Asian participants (stage 1) followed by replication study of ≤46 629 participants of European ancestry (stage 2). Significant single-nucleotide polymorphisms and genes were determined by a P<5.0×10-8 and 2.5×10-6, respectively, in joint analyses of stage-1 and stage-2 data. We identified 1 novel ARL3 variant, rs4919669 at 10q24.32, influencing LTA systolic BP (stage-1 P=5.03×10-8, stage-2 P=8.64×10-3, joint P=2.63×10-8) and mean arterial pressure (stage-1 P=3.59×10-9, stage-2 P=2.35×10-2, joint P=2.64×10-8). Three previously reported BP loci (WBP1L, NT5C2, and ATP2B1) were also identified for all BP phenotypes. Gene-based analysis provided the first robust evidence for association of KCNJ11 with LTA systolic BP (stage-1 P=8.55×10-6, stage-2 P=1.62×10-5, joint P=3.28×10-9) and mean arterial pressure (stage-1 P=9.19×10-7, stage-2 P=9.69×10-5, joint P=2.15×10-9) phenotypes. Fourteen genes (TMEM180, ACTR1A, SUFU, ARL3, SFXN2, WBP1L, CYP17A1, C10orf32, C10orf32-ASMT, AS3MT, CNNM2, and NT5C2 at 10q24.32; ATP2B1 at 12q21.33; and NCR3LG1 at 11p15.1) implicated by previous genome-wide association study meta-analyses were also identified. Among the loci identified by the previous genome-wide association study meta-analysis of LTA BP, we transethnically replicated associations of the KCNK3 marker rs1275988 at 2p23.3 with LTA systolic BP and mean arterial pressure phenotypes (P=1.27×10-4 and 3.30×10-4, respectively). CONCLUSIONS: We identified 1 novel variant and 1 novel gene and present the first direct evidence of relevance of the KCNK3 locus for LTA BP among East Asians.
Keywords: Asian Continental Ancestry Group; Blood Pressure; Far East; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Phenotype; Polymorphism, Single Nucleotide

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets. - Lam, Max; Trampush, Joey W; Yu, Jin; Knowles, Emma; Davies, Gail; Liewald, David C; Starr, John M; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; Reinvang, Ivar; et al. (Cell Rep, 2017)
Here, we present a large (n = 107,207) genome-wide association study (GWAS) of general cognitive ability ("g"), further enhanced by combining results with a large-scale GWAS of educational attainment. We identified 70 independent genomic loci associated with general cognitive ability. Results showed significant enrichment for genes causing Mendelian disorders with an intellectual disability phenotype. Competitive pathway analysis implicated the biological processes of neurogenesis and synaptic regulation, as well as the gene targets of two pharmacologic agents: cinnarizine, a T-type calcium channel blocker, and LY97241, a potassium channel inhibitor. Transcriptome-wide and epigenome-wide analysis revealed that the implicated loci were enriched for genes expressed across all brain regions (most strongly in the cerebellum). Enrichment was exclusive to genes expressed in neurons but not oligodendrocytes or astrocytes. Finally, we report genetic correlations between cognitive ability and disparate phenotypes including psychiatric disorders, several autoimmune disorders, longevity, and maternal age at first birth.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness. - Willems, Sara M; Wright, Daniel J; Day, Felix R; Trajanoska, Katerina; Joshi, Peter K; Morris, John A; Matteini, Amy M; Garton, Fleur C; Grarup, Niels; Oskolkov, Nikolay; Thalamuthu, Anbupalam; Mangino, Massimo; et al. (Nat Commun, 2017)
Hand grip strength is a widely used proxy of muscular fitness, a marker of frailty, and predictor of a range of morbidities and all-cause mortality. To investigate the genetic determinants of variation in grip strength, we perform a large-scale genetic discovery analysis in a combined sample of 195,180 individuals and identify 16 loci associated with grip strength (P<5 × 10) in combined analyses. A number of these loci contain genes implicated in structure and function of skeletal muscle fibres (ACTG1), neuronal maintenance and signal transduction (PEX14, TGFA, SYT1), or monogenic syndromes with involvement of psychomotor impairment (PEX14, LRPPRC and KANSL1). Mendelian randomization analyses are consistent with a causal effect of higher genetically predicted grip strength on lower fracture risk. In conclusion, our findings provide new biological insight into the mechanistic underpinnings of grip strength and the causal role of muscular strength in age-related morbidities and mortality.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Physical activity predicts reduced plasma β amyloid in the Cardiovascular Health Study. - Stillman, Chelsea M; Lopez, Oscar L; Becker, James T; Kuller, Lewis H; Mehta, Pankaj D; Tracy, Russell P; Erickson, Kirk I (Ann Clin Transl Neurol, 2017)
OBJECTIVE: Higher levels of physical activity (PA) reduce the risk of cognitive impairment, but the underlying mechanisms are unclear. Using longitudinal data from the Cardiovascular Health Study, we examined whether PA predicted plasma Aβ levels and risk for cognitive decline 9-13 years later. METHODS: Linear and logistic regressions (controlling for APOE status, age, gender, body mass index, cardiovascular disease, brain white matter lesions, and cystatin C levels) tested associations between PA, Aβ, and cognitive impairment in a sample of 149 cognitively normal older adults (mean age 83 years). RESULTS: More PA at baseline predicted lower levels of Aβ 9-13 years later. Higher Aβ levels at year 9 predicted greater risk for cognitive impairment at year 13. Levels of Aβ at year 9 mediated the relationship between PA and cognitive impairment. INTERPRETATION: Greater PA may reduce plasma levels of a neurotoxic peptide at an age when the risk for cognitive impairment is especially high.

Predictors of incident epilepsy in older adults: The Cardiovascular Health Study. - Choi, Hyunmi; Pack, Alison; Elkind, Mitchell S V; Longstreth, W T; Ton, Thanh G N; Onchiri, Frankline (Neurology, 2017)
OBJECTIVE: To determine the prevalence, incidence, and predictors of epilepsy among older adults in the Cardiovascular Health Study (CHS). METHODS: We analyzed data prospectively collected in CHS and merged with data from outpatient Medicare administrative claims. We identified cases with epilepsy using self-report, antiepileptic medication, hospitalization discharge ICD-9 codes, and outpatient Medicare ICD-9 codes. We used Cox proportional hazards regression to identify factors independently associated with incident epilepsy. RESULTS: At baseline, 42% of the 5,888 participants were men and 84% were white. At enrollment, 3.7% (215 of 5,888) met the criteria for prevalent epilepsy. During 14 years of follow-up totaling 48,651 person-years, 120 participants met the criteria for incident epilepsy, yielding an incidence rate of 2.47 per 1,000 person-years. The period prevalence of epilepsy by the end of follow-up was 5.7% (335 of 5,888). Epilepsy incidence rates were significantly higher among blacks than nonblacks: 4.44 vs 2.17 per 1,000 person-years (p < 0.001). In multivariable analyses, risk of incident epilepsy was significantly higher among blacks compared to nonblacks (hazard ratio [HR] 4.04, 95% confidence interval [CI] 1.99-8.17), those 75 to 79 compared to those 65 to 69 years of age (HR 2.07, 95% CI 1.21-3.55), and those with history of stroke (HR 3.49, 95% CI 1.37-8.88). CONCLUSIONS: Epilepsy in older adults in the United States was common. Blacks, the very old, and those with history of stroke have a higher risk of incident epilepsy. The association with race remains unexplained.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Sleep-disordered breathing is associated with higher carboxymethyllysine level in elderly women but not elderly men in the cardiovascular health study. - Ahiawodzi, Peter D; Kerber, Richard A; Taylor, Kira C; Groves, Frank D; O'Brien, Elizabeth; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Robbins, John; et al. (Biomarkers, 2017)
CONTEXT: Carboxymethyl-lysine (CML) results from oxidative stress and has been linked to cardiovascular disease. OBJECTIVE: The objective of this study is to investigate the association between sleep-disordered breathing (SDB) - a source of oxidative stress - and CML. MATERIALS AND METHODS: About 1002 participants in the Cardiovascular Health Study (CHS) were studied. RESULTS: Women with SDB had significantly higher CML concentration compared with those without SDB (OR = 1.63, 95%CI = 1.03-2.58, p = 0.04). The association was not significant among men. DISCUSSION: SDB was associated with CML concentration among elderly women but not men in the Cardiovascular Health Study. CONCLUSION: Accumulation of CML may be an adverse health consequence of SDB.

Taller height as a risk factor for venous thromboembolism: a Mendelian randomization meta-analysis. - Roetker, N S; Armasu, S M; Pankow, J S; Lutsey, P L; Tang, W; Rosenberg, M A; Palmer, T M; MacLehose, R F; Heckbert, S R; Cushman, M; de Andrade, M; Folsom, A R (J Thromb Haemost, 2017)
BACKGROUND: Taller height is associated with greater risk of venous thromboembolism (VTE). OBJECTIVES: We used instrumental variable (IV) techniques (Mendelian randomization) to further explore this relationship METHODS: Participants of European ancestry were included from two cohort studies [Atherosclerosis Risk in Communities (ARIC) study and Cardiovascular Health Study (CHS)] and one case-control study [Mayo Clinic VTE Study (Mayo)]. We created two weighted genetic risk scores (GRS) for height; the full GRS included 668 single nucleotide polymorphisms (SNPs) from a previously published meta-analysis and the restricted GRS included a subset of 362 SNPs not associated with weight independently of height. Standard logistic regression and IV models were used to estimate odds ratios (ORs) for VTE per 10 cm increment in height. ORs were pooled across the three studies using inverse variance weighted random effects meta-analysis RESULTS: Among 9143 ARIC and 3180 CHS participants free of VTE at baseline, there were 367 and 109 incident VTE events. There were 1143 VTE cases and 1292 controls included from Mayo. The pooled ORs from non-IV models and models using the full and restricted GRSs as IVs were 1.27 (95% CI: 1.11, 1.46), 1.34 (95% CI: 1.04, 1.73), and 1.45 (95% CI: 1.04, 2.01) per 10 cm greater height, respectively CONCLUSIONS: Taller height is associated with an increased risk of VTE in adults of European ancestry. Possible explanations for this association, including that taller people may have greater venous surface area, greater number of venous valves, or greater hydrostatic pressure, need to be explored further. This article is protected by copyright. All rights reserved.

Telomeres and the natural lifespan limit in humans. - Steenstrup, Troels; Kark, Jeremy D; Verhulst, Simon; Thinggaard, Mikael; Hjelmborg, Jacob V B; Dalgård, Christine; Kyvik, Kirsten Ohm; Christiansen, Lene; Mangino, Massimo; Spector, Timothy D; Petersen, Inge; Kimura, Masayuki; et al. (Aging (Albany NY), 2017)
An ongoing debate in demography has focused on whether the human lifespan has a maximal natural limit. Taking a mechanistic perspective, and knowing that short telomeres are associated with diminished longevity, we examined whether telomere length dynamics during adult life could set a maximal natural lifespan limit. We define leukocyte telomere length of 5 kb as the 'telomeric brink', which denotes a high risk of imminent death. We show that a subset of adults may reach the telomeric brink within the current life expectancy and more so for a 100-year life expectancy. Thus, secular trends in life expectancy should confront a biological limit due to crossing the telomeric brink.

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Trends in the incidence of dementia: design and methods in the Alzheimer Cohorts Consortium. - Chibnik, Lori B; Wolters, Frank J; Bäckman, Kristoffer; Beiser, Alexa; Berr, Claudine; Bis, Joshua C; Boerwinkle, Eric; Bos, Daniel; Brayne, Carol; Dartigues, Jean-François; Darweesh, Sirwan K L; Debette, Stephanie; et al. (Eur J Epidemiol, 2017)
Several studies have reported a decline in incidence of dementia which may have large implications for the projected burden of disease, and provide important guidance to preventive efforts. However, reports are conflicting or inconclusive with regard to the impact of gender and education with underlying causes of a presumed declining trend remaining largely unidentified. The Alzheimer Cohorts Consortium aggregates data from nine international population-based cohorts to determine changes in the incidence of dementia since 1990. We will employ Poisson regression models to calculate incidence rates in each cohort and Cox proportional hazard regression to compare 5-year cumulative hazards across study-specific epochs. Finally, we will meta-analyse changes per decade across cohorts, and repeat all analysis stratified by sex, education and APOE genotype. In all cohorts combined, there are data on almost 69,000 people at risk of dementia with the range of follow-up years between 2 and 27. The average age at baseline is similar across cohorts ranging between 72 and 77. Uniting a wide range of disease-specific and methodological expertise in research teams, the first analyses within the Alzheimer Cohorts Consortium are underway to tackle outstanding challenges in the assessment of time-trends in dementia occurrence.

Assessment of the genetic and clinical determinants of fracture risk: genome wide association and mendelian randomisation study. - Trajanoska, Katerina; Morris, John A; Oei, Ling; Zheng, Hou-Feng; Evans, David M; Kiel, Douglas P; Ohlsson, Claes; Richards, J Brent; Rivadeneira, Fernando (BMJ, 2018)
OBJECTIVES: To identify the genetic determinants of fracture risk and assess the role of 15 clinical risk factors on osteoporotic fracture risk. DESIGN: Meta-analysis of genome wide association studies (GWAS) and a two-sample mendelian randomisation approach. SETTING: 25 cohorts from Europe, United States, east Asia, and Australia with genome wide genotyping and fracture data. PARTICIPANTS: A discovery set of 37 857 fracture cases and 227 116 controls; with replication in up to 147 200 fracture cases and 150 085 controls. Fracture cases were defined as individuals (>18 years old) who had fractures at any skeletal site confirmed by medical, radiological, or questionnaire reports. Instrumental variable analyses were performed to estimate effects of 15 selected clinical risk factors for fracture in a two-sample mendelian randomisation framework, using the largest previously published GWAS meta-analysis of each risk factor. RESULTS: Of 15 fracture associated loci identified, all were also associated with bone mineral density and mapped to genes clustering in pathways known to be critical to bone biology (eg, , , and ) or novel pathways (, , and ). Mendelian randomisation analyses showed a clear effect of bone mineral density on fracture risk. One standard deviation decrease in genetically determined bone mineral density of the femoral neck was associated with a 55% increase in fracture risk (odds ratio 1.55 (95% confidence interval 1.48 to 1.63; P=1.5×10). Hand grip strength was inversely associated with fracture risk, but this result was not significant after multiple testing correction. The remaining clinical risk factors (including vitamin D levels) showed no evidence for an effect on fracture. CONCLUSIONS: This large scale GWAS meta-analysis for fracture identified 15 genetic determinants of fracture, all of which also influenced bone mineral density. Among the clinical risk factors for fracture assessed, only bone mineral density showed a major causal effect on fracture. Genetic predisposition to lower levels of vitamin D and estimated calcium intake from dairy sources were not associated with fracture risk.

Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. - Segna, D; Bauer, D C; Feller, M; Schneider, C; Fink, H A; Aubert, C E; Collet, T-H; da Costa, B R; Fischer, K; Peeters, R P; Cappola, A R; Blum, M R; et al. (J Intern Med, 2018)
BACKGROUND: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. OBJECTIVE: To investigate the association between subclinical thyroid dysfunction and bone loss. METHODS: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946-2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid-stimulating hormone [TSH] 0.45-4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50-19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X-ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random-effects two-step approach. RESULTS: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person-years of follow-up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = -0.18 (95% CI: -0.34, -0.02; I2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = -0.14 (95% CI: -0.38, 0.10; I2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: -0.30, 0.36; I2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = -0.59; [95% CI: -0.99, -0.19]) and total hip region (%ΔBMD = -0.46 [95% CI: -1.05, -0.13]). In contrast, SHypo was not associated with bone loss at any site. CONCLUSION: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.
Keywords: Aged; Asymptomatic Diseases; Bone Density; Female; Fractures, Bone; Humans; Hyperthyroidism; Hypothyroidism; Male; Risk Factors

Associations of activated coagulation factor VII and factor VIIa-antithrombin levels with genome-wide polymorphisms and cardiovascular disease risk. - Olson, N C; Raffield, L M; Lange, L A; Lange, E M; Longstreth, W T; Chauhan, G; Debette, S; Seshadri, S; Reiner, A P; Tracy, R P (J Thromb Haemost, 2018)
ESSENTIALS: Essentials A fraction of coagulation factor VII circulates in blood as an activated protease (FVIIa). We evaluated FVIIa and FVIIa-antithrombin (FVIIa-AT) levels in the Cardiovascular Health Study. Polymorphisms in the F7 and PROCR loci were associated with FVIIa and FVIIa-AT levels. FVIIa may be an ischemic stroke risk factor in older adults and FVIIa-AT may assess mortality risk. SUMMARY: Background A fraction of coagulation factor (F) VII circulates as an active protease (FVIIa). FVIIa also circulates as an inactivated complex with antithrombin (FVIIa-AT). Objective Evaluate associations of FVIIa and FVIIa-AT with genome-wide single nucleotide polymorphisms (SNPs) and incident coronary heart disease, ischemic stroke and mortality. Patients/Methods We measured FVIIa and FVIIa-AT in 3486 Cardiovascular Health Study (CHS) participants. We performed a genome-wide association scan for FVIIa and FVIIa-AT in European-Americans (n = 2410) and examined associations of FVII phenotypes with incident cardiovascular disease. Results In European-Americans, the most significant SNP for FVIIa and FVIIa-AT was rs1755685 in the F7 promoter region on chromosome 13 (FVIIa, β = -25.9 mU mL-1 per minor allele; FVIIa-AT, β = -26.6 pm per minor allele). Phenotypes were also associated with rs867186 located in PROCR on chromosome 20 (FVIIa, β = 7.8 mU mL-1 per minor allele; FVIIa-AT, β = 9.9 per minor allele). Adjusted for risk factors, a one standard deviation higher FVIIa was associated with increased risk of ischemic stroke (hazard ratio [HR], 1.12; 95% confidence interval [CI], 1.01, 1.23). Higher FVIIa-AT was associated with mortality from all causes (HR, 1.08; 95% CI, 1.03, 1.12). Among European-American CHS participants the rs1755685 minor allele was associated with lower ischemic stroke (HR, 0.69; 95% CI, 0.54, 0.88), but this association was not replicated in a larger multi-cohort analysis. Conclusions The results support the importance of the F7 and PROCR loci in variation in circulating FVIIa and FVIIa-AT. The findings suggest FVIIa is a risk factor for ischemic stroke in older adults, whereas higher FVIIa-AT may reflect mortality risk.

Atrial Cardiopathy and the Risk of Ischemic Stroke in the CHS (Cardiovascular Health Study). - Kamel, Hooman; Bartz, Traci M; Elkind, Mitchell S V; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; deFilippi, Christopher R; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Soliman, Elsayed Z; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: Emerging evidence suggests that an underlying atrial cardiopathy may result in thromboembolism before atrial fibrillation (AF) develops. We examined the association between various markers of atrial cardiopathy and the risk of ischemic stroke. METHODS: The CHS (Cardiovascular Health Study) prospectively enrolled community-dwelling adults ≥65 years of age. For this study, we excluded participants diagnosed with stroke or AF before baseline. Exposures were several markers of atrial cardiopathy: baseline P-wave terminal force in ECG lead V, left atrial dimension on echocardiogram, and N terminal pro B type natriuretic peptide (NT-proBNP), as well as incident AF. Incident AF was ascertained from 12-lead electrocardiograms at annual study visits for the first decade after study enrollment and from inpatient and outpatient Medicare data throughout follow-up. The primary outcome was incident ischemic stroke. We used Cox proportional hazards models that included all 4 atrial cardiopathy markers along with adjustment for demographic characteristics and established vascular risk factors. RESULTS: Among 3723 participants who were free of stroke and AF at baseline and who had data on all atrial cardiopathy markers, 585 participants (15.7%) experienced an incident ischemic stroke during a median 12.9 years of follow-up. When all atrial cardiopathy markers were combined in 1 Cox model, we found significant associations with stroke for P-wave terminal force in ECG lead V (hazard ratio per 1000 μV*ms 1.04; 95% confidence interval, 1.001-1.08), log-transformed NT-proBNP (hazard ratio per doubling of NT-proBNP, 1.09; 95% confidence interval, 1.03-1.16), and incident AF (hazard ratio, 2.04; 95% confidence interval, 1.67-2.48) but not left atrial dimension (hazard ratio per cm, 0.96; 95% confidence interval, 0.84-1.10). CONCLUSIONS: In addition to clinically apparent AF, other evidence of abnormal atrial substrate is associated with subsequent ischemic stroke. This finding is consistent with the hypothesis that thromboembolism from the left atrium may occur in the setting of several different manifestations of atrial disease.

Biochemical Markers of Bone Turnover and Risk of Incident Diabetes in Older Women: The Cardiovascular Health Study. - Massera, Daniele; Biggs, Mary L; Walker, Marcella D; Mukamal, Kenneth J; Ix, Joachim H; Djoussé, Luc; Valderrábano, Rodrigo J; Siscovick, David S; Tracy, Russell P; Xue, XiaoNan; Kizer, Jorge R (Diabetes Care, 2018)
OBJECTIVE: To investigate the relationship of osteocalcin (OC), a marker of bone formation, and C-terminal cross-linked telopeptide of type I collagen (CTX), a marker of bone resorption, with incident diabetes in older women. RESEARCH DESIGN AND METHODS: The analysis included 1,455 female participants from the population-based Cardiovascular Health Study (CHS) (mean [SD] age 74.6 [5.0] years). The cross-sectional association of serum total OC and CTX levels with insulin resistance (HOMA-IR) was examined using multiple linear regression. The longitudinal association of both markers with incident diabetes, defined by follow-up glucose measurements, medications, and ICD-9 codes, was examined using multivariable Cox proportional hazards models. RESULTS: OC and CTX were strongly correlated ( = 0.80). In cross-sectional analyses, significant or near-significant inverse associations with HOMA-IR were observed for continuous levels of OC (β = -0.12 per SD increment; = 0.004) and CTX (β = -0.08 per SD; = 0.051) after full adjustment for demographic, lifestyle, and clinical covariates. During a median follow-up of 11.5 years, 196 cases of incident diabetes occurred. After full adjustment, both biomarkers exhibited inverse associations with incident diabetes (OC: hazard ratio 0.85 per SD [95% CI 0.71-1.02; = 0.075]; CTX: 0.82 per SD [0.69-0.98; = 0.031]), associations that were comparable in magnitude and approached or achieved statistical significance. CONCLUSIONS: In late postmenopausal women, lower OC and CTX levels were associated with similarly increased risks of insulin resistance at baseline and incident diabetes over long-term follow-up. Further research to delineate the mechanisms linking abnormal bone homeostasis and energy metabolism could uncover new approaches for the prevention of these age-related disorders.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

{Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies - Huang, T.; Ding, M.; Bergholdt, H. K. M.; Wang, T.; Heianza, Y.; Sun, D.; Frazier-Wood, A. C.; Aslibekyan, S.; North, K. E.; Voortman, T.; Graff, M.; Smith, C. E.; et al. (Clin Chem, 2018)
Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined.\ We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene (LCT-13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between (a) dairy intake and BMI, (b) rs4988235 and dairy intake, and (c) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies.\ Higher dairy intake was associated with higher BMI (β = 0.03 kg/m2 per serving/day; 95% CI, 0.00-0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14-0.25) serving/day higher dairy intake (P = 3.15 × 10-12) and 0.12 (95% CI, 0.06-0.17) kg/m2 higher BMI (P = 2.11 × 10-5). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m2 per serving/day; 95% CI, 0.27-0.92; P = 3.0 × 10-4).\ The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.

Discovery, fine-mapping, and conditional analyses of genetic variants associated with C-reactive protein in multiethnic populations using the Metabochip in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Kocarnik, Jonathan M; Richard, Melissa; Graff, Misa; Haessler, Jeffrey; Bien, Stephanie; Carlson, Chris; Carty, Cara L; Reiner, Alexander P; Avery, Christy L; Ballantyne, Christie M; LaCroix, Andrea Z; Assimes, Themistocles L; et al. (Hum Mol Genet, 2018)
C-reactive protein (CRP) is a circulating biomarker indicative of systemic inflammation. We aimed to evaluate genetic associations with CRP levels among non-European-ancestry populations through discovery, fine-mapping and conditional analyses. A total of 30 503 non-European-ancestry participants from 6 studies participating in the Population Architecture using Genomics and Epidemiology study had serum high-sensitivity CRP measurements and ∼200 000 single nucleotide polymorphisms (SNPs) genotyped on the Metabochip. We evaluated the association between each SNP and log-transformed CRP levels using multivariate linear regression, with additive genetic models adjusted for age, sex, the first four principal components of genetic ancestry, and study-specific factors. Differential linkage disequilibrium patterns between race/ethnicity groups were used to fine-map regions associated with CRP levels. Conditional analyses evaluated for multiple independent signals within genetic regions. One hundred and sixty-three unique variants in 12 loci in overall or race/ethnicity-stratified Metabochip-wide scans reached a Bonferroni-corrected P-value <2.5E-7. Three loci have no (HACL1, OLFML2B) or only limited (PLA2G6) previous associations with CRP levels. Six loci had different top hits in race/ethnicity-specific versus overall analyses. Fine-mapping refined the signal in six loci, particularly in HNF1A. Conditional analyses provided evidence for secondary signals in LEPR, IL1RN and HNF1A, and for multiple independent signals in CRP and APOE. We identified novel variants and loci associated with CRP levels, generalized known CRP associations to a multiethnic study population, refined association signals at several loci and found evidence for multiple independent signals at several well-known loci. This study demonstrates the benefit of conducting inclusive genetic association studies in large multiethnic populations.

DNA methylation age is associated with an altered hemostatic profile in a multi-ethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Evertt, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases, however much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we used European and African-ancestry participants who were meta-analyzed separately and combined via a random effects meta-analysis. All other measures only included participants of European-ancestry. We found that 1-year higher extrinsic epigenetic age as compared to chronological age was associated with higher fibrinogen (0.004 g/L per year; 95% CI: 0.001, 0.007; P = 0.01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL per year; 95% CI: 0.07, 0.20; P = 6.6x10-5) concentrations as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene (SERPINE1) and the three fibrinogen subunit-encoding genes (FGA, FGG, and FGB), in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of FGG in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a pro-coagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Fatty acid biomarkers of dairy fat consumption and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies. - Imamura, Fumiaki; Fretts, Amanda; Marklund, Matti; Ardisson Korat, Andres V; Yang, Wei-Sin; Lankinen, Maria; Qureshi, Waqas; Helmer, Catherine; Chen, Tzu-An; Wong, Kerry; Bassett, Julie K; Murphy, Rachel; et al. (PLoS Med, 2018)
BACKGROUND: We aimed to investigate prospective associations of circulating or adipose tissue odd-chain fatty acids 15:0 and 17:0 and trans-palmitoleic acid, t16:1n-7, as potential biomarkers of dairy fat intake, with incident type 2 diabetes (T2D). METHODS AND FINDINGS: Sixteen prospective cohorts from 12 countries (7 from the United States, 7 from Europe, 1 from Australia, 1 from Taiwan) performed new harmonised individual-level analysis for the prospective associations according to a standardised plan. In total, 63,682 participants with a broad range of baseline ages and BMIs and 15,180 incident cases of T2D over the average of 9 years of follow-up were evaluated. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Prespecified interactions by age, sex, BMI, and race/ethnicity were explored in each cohort and were meta-analysed. Potential heterogeneity by cohort-specific characteristics (regions, lipid compartments used for fatty acid assays) was assessed with metaregression. After adjustment for potential confounders, including measures of adiposity (BMI, waist circumference) and lipogenesis (levels of palmitate, triglycerides), higher levels of 15:0, 17:0, and t16:1n-7 were associated with lower incidence of T2D. In the most adjusted model, the hazard ratio (95% CI) for incident T2D per cohort-specific 10th to 90th percentile range of 15:0 was 0.80 (0.73-0.87); of 17:0, 0.65 (0.59-0.72); of t16:1n7, 0.82 (0.70-0.96); and of their sum, 0.71 (0.63-0.79). In exploratory analyses, similar associations for 15:0, 17:0, and the sum of all three fatty acids were present in both genders but stronger in women than in men (pinteraction < 0.001). Whereas studying associations with biomarkers has several advantages, as limitations, the biomarkers do not distinguish between different food sources of dairy fat (e.g., cheese, yogurt, milk), and residual confounding by unmeasured or imprecisely measured confounders may exist. CONCLUSIONS: In a large meta-analysis that pooled the findings from 16 prospective cohort studies, higher levels of 15:0, 17:0, and t16:1n-7 were associated with a lower risk of T2D.
Keywords: Aged; Australia; Biomarkers; Dairy Products; Diabetes Mellitus, Type 2; Dietary Fats; Europe; Fatty Acids; Fatty Acids, Monounsaturated; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Sex Factors; Taiwan; United States

Generalization and fine mapping of red blood cell trait genetic associations to multi-ethnic populations: The PAGE Study. - Jo Hodonsky, Chani; Schurmann, Claudia; Schick, Ursula M; Kocarnik, Jonathan; Tao, Ran; van Rooij, Frank Ja; Wassel, Christina; Buyske, Steve; Fornage, Myriam; Hindorff, Lucia A; Floyd, James S; Ganesh, Santhi K; et al. (Am J Hematol, 2018)
Red blood cell (RBC) traits provide insight into a wide range of physiological states and exhibit moderate to high heritability, making them excellent candidates for genetic studies to inform underlying biologic mechanisms. Previous RBC trait genome-wide association studies were performed primarily in European- or Asian-ancestry populations, missing opportunities to inform understanding of RBC genetic architecture in diverse populations and reduce intervals surrounding putative functional SNPs through fine-mapping. Here, we report the first fine-mapping of six correlated (Pearson's r range: |0.04 - 0.92|) RBC traits in up to 19,036 African Americans and 19,562 Hispanic/Latinos participants of the Population Architecture using Genomics and Epidemiology (PAGE) consortium. Trans-ethnic meta-analysis of race/ethnic- and study-specific estimates for approximately 11,000 SNPs flanking 13 previously identified association signals as well as 150,000 additional array-wide SNPs was performed using inverse-variance meta-analysis after adjusting for study and clinical covariates. Approximately half of previously reported index SNP-RBC trait associations generalized to the trans-ethnic study population (p<1.7x10 ); previously unreported independent association signals within the ABO region reinforce the potential for multiple functional variants affecting the same locus. Trans-ethnic fine-mapping did not reveal additional signals at the HFE locus independent of the known functional variants. Finally, we identified a potential novel association in the Hispanic/Latino study population at the HECTD4/RPL6 locus for RBC count (p=1.9x10 ). The identification of a previously unknown association, generalization of a large proportion of known association signals, and refinement of known association signals all exemplify the benefits of genetic studies in diverse populations. This article is protected by copyright. All rights reserved.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genetic Variation in Genes Underlying Diverse Dementias May Explain a Small Proportion of Cases in the Alzheimer's Disease Sequencing Project. - Blue, Elizabeth E; Bis, Joshua C; Dorschner, Michael O; Tsuang, Debby W; Barral, Sandra M; Beecham, Gary; Below, Jennifer E; Bush, William S; Butkiewicz, Mariusz; Cruchaga, Carlos; DeStefano, Anita; Farrer, Lindsay A; et al. (Dement Geriatr Cogn Disord, 2018)
BACKGROUND/AIMS: The Alzheimer's Disease Sequencing Project (ADSP) aims to identify novel genes influencing Alzheimer's disease (AD). Variants within genes known to cause dementias other than AD have previously been associated with AD risk. We describe evidence of co-segregation and associations between variants in dementia genes and clinically diagnosed AD within the ADSP. METHODS: We summarize the properties of known pathogenic variants within dementia genes, describe the co-segregation of variants annotated as "pathogenic" in ClinVar and new candidates observed in ADSP families, and test for associations between rare variants in dementia genes in the ADSP case-control study. The participants were clinically evaluated for AD, and they represent European, Caribbean Hispanic, and isolate Dutch populations. RESULTS/CONCLUSIONS: Pathogenic variants in dementia genes were predominantly rare and conserved coding changes. Pathogenic variants within ARSA, CSF1R, and GRN were observed, and candidate variants in GRN and CHMP2B were nominated in ADSP families. An independent case-control study provided evidence of an association between variants in TREM2, APOE, ARSA, CSF1R, PSEN1, and MAPT and risk of AD. Variants in genes which cause dementing disorders may influence the clinical diagnosis of AD in a small proportion of cases within the ADSP.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

Genome-wide association study and meta-analysis identify loci associated with ventricular and supraventricular ectopy. - Napier, Melanie D; Franceschini, Nora; Gondalia, Rahul; Stewart, James D; Méndez-Giráldez, Rául; Sitlani, Colleen M; Seyerle, Amanda A; Highland, Heather M; Li, Yun; Wilhelmsen, Kirk C; Yan, Song; Duan, Qing; et al. (Sci Rep, 2018)
The genetic basis of supraventricular and ventricular ectopy (SVE, VE) remains largely uncharacterized, despite established genetic mechanisms of arrhythmogenesis. To identify novel genetic variants associated with SVE/VE in ancestrally diverse human populations, we conducted a genome-wide association study of electrocardiographically identified SVE and VE in five cohorts including approximately 43,000 participants of African, European and Hispanic/Latino ancestry. In thirteen ancestry-stratified subgroups, we tested multivariable-adjusted associations of SVE and VE with single nucleotide polymorphism (SNP) dosage. We combined subgroup-specific association estimates in inverse variance-weighted, fixed-effects and Bayesian meta-analyses. We also combined fixed-effects meta-analytic t-test statistics for SVE and VE in multi-trait SNP association analyses. No loci reached genome-wide significance in trans-ethnic meta-analyses. However, we found genome-wide significant SNPs intronic to an apoptosis-enhancing gene previously associated with QRS interval duration (FAF1; lead SNP rs7545860; effect allele frequency = 0.02; P = 2.0 × 10) in multi-trait analysis among European ancestry participants and near a locus encoding calcium-dependent glycoproteins (DSC3; lead SNP rs8086068; effect allele frequency = 0.17) in meta-analysis of SVE (P = 4.0 × 10) and multi-trait analysis (P = 2.9 × 10) among African ancestry participants. The novel findings suggest several mechanisms by which genetic variation may predispose to ectopy in humans and highlight the potential value of leveraging pleiotropy in future studies of ectopy-related phenotypes.

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-Wide Associations of Global Electrical Heterogeneity ECG Phenotype: The ARIC (Atherosclerosis Risk in Communities) Study and CHS (Cardiovascular Health Study). - Tereshchenko, Larisa G; Sotoodehnia, Nona; Sitlani, Colleen M; Ashar, Foram N; Kabir, Muammar; Biggs, Mary L; Morley, Michael P; Waks, Jonathan W; Soliman, Elsayed Z; Buxton, Alfred E; Biering-Sørensen, Tor; Solomon, Scott D; et al. (J Am Heart Assoc, 2018)
BACKGROUND: ECG global electrical heterogeneity (GEH) is associated with sudden cardiac death. We hypothesized that a genome-wide association study would identify genetic loci related to GEH. METHODS AND RESULTS: We tested genotyped and imputed variants in black (N=3057) and white (N=10 769) participants in the ARIC (Atherosclerosis Risk in Communities) study and CHS (Cardiovascular Health Study). GEH (QRS-T angle, sum absolute QRST integral, spatial ventricular gradient magnitude, elevation, azimuth) was measured on 12-lead ECGs. Linear regression models were constructed with each GEH variable as an outcome, adjusted for age, sex, height, body mass index, study site, and principal components to account for ancestry. GWAS identified 10 loci that showed genome-wide significant association with GEH in whites or joint ancestry. The strongest signal (rs7301677, near ) was associated with QRS-T angle (white standardized β+0.16 [95% CI 0.13-0.19]; =1.5×10), spatial ventricular gradient elevation (+0.11 [0.08-0.14]; =2.1×10), and spatial ventricular gradient magnitude (-0.12 [95% CI -0.15 to -0.09]; =5.9×10). Altogether, GEH-SNPs explained 1.1% to 1.6% of GEH variance. Loci on chromosomes 4 (near ), 5 (), 11 (11p11.2 region cluster), and 7 (near ) are novel ECG phenotype-associated loci. Several loci significantly associated with gene expression in the left ventricle ( locus-with ; locus-with ), and atria ( locus-with expression of a long non-coding RNA and ). CONCLUSIONS: We identified 10 genetic loci associated with ECG GEH. Replication of GEH GWAS findings in independent cohorts is warranted. Further studies of GEH-loci may uncover mechanisms of arrhythmogenic remodeling in response to cardiovascular risk factors.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

Large-scale whole-exome sequencing association studies identify rare functional variants influencing serum urate levels. - Tin, Adrienne; Li, Yong; Brody, Jennifer A; Nutile, Teresa; Chu, Audrey Y; Huffman, Jennifer E; Yang, Qiong; Chen, Ming-Huei; Robinson-Cohen, Cassianne; Mace, Aurelien; Liu, Jun; Demirkan, Ayse; et al. (Nat Commun, 2018)
Elevated serum urate levels can cause gout, an excruciating disease with suboptimal treatment. Previous GWAS identified common variants with modest effects on serum urate. Here we report large-scale whole-exome sequencing association studies of serum urate and kidney function among ≤19,517 European ancestry and African-American individuals. We identify aggregate associations of low-frequency damaging variants in the urate transporters SLC22A12 (URAT1; p = 1.3 × 10) and SLC2A9 (p = 4.5 × 10). Gout risk in rare SLC22A12 variant carriers is halved (OR = 0.5, p = 4.9 × 10). Selected rare variants in SLC22A12 are validated in transport studies, confirming three as loss-of-function (R325W, R405C, and T467M) and illustrating the therapeutic potential of the new URAT1-blocker lesinurad. In SLC2A9, mapping of rare variants of large effects onto the predicted protein structure reveals new residues that may affect urate binding. These findings provide new insights into the genetic architecture of serum urate, and highlight molecular targets in SLC22A12 and SLC2A9 for lowering serum urate and preventing gout.
Keywords: Exome; Genetic Predisposition to Disease; Glucose Transport Proteins, Facilitative; Humans; Kidney Function Tests; Meta-Analysis as Topic; Organic Anion Transporters; Organic Cation Transport Proteins; Protein Structure, Secondary; Uric Acid

Leukoaraiosis is independently associated with naming outcome in poststroke aphasia. - Wright, Amy; Tippett, Donna; Saxena, Sadhvi; Sebastian, Rajani; Breining, Bonnie; Faria, Andreia; Hillis, Argye E (Neurology, 2018)
OBJECTIVE: To test the hypothesis that severity of leukoaraiosis in the noninfarcted hemisphere at onset is associated with poorer language outcome after poststroke aphasia independently of volume of infarct, damage to 3 critical language areas (left inferior frontal gyrus, superior longitudinal fasciculus, and superior temporal gyrus), comorbid conditions, and time since stroke. METHODS: In this cross-sectional study, we evaluated naming outcome (>3 months after stroke) in 42 individuals who initially had aphasia after stroke. We rated leukoaraiosis in the right hemisphere 1 to 4 weeks from onset of stroke using the Cardiovascular Health Study rating scale. We evaluated associations between severity of leukoaraiosis and each measure of naming using Spearman correlations and evaluated the independent contributions of leukoaraiosis, lesion volume, months since onset, comorbid conditions, and damage to critical nodes of the language network on language outcomes using logistic regression. We also evaluated associations between dichotomously defined leukoaraiosis and language outcomes using χ tests. RESULTS: Severity of leukoaraiosis at onset correlated with object naming (ρ = -0.56, = 0.0008) and word fluency (ρ = -0.37, = 0.01) outcomes. Severe leukoaraiosis was associated with failure to achieve the highest quartile of object naming and word fluency. Severity of leukoaraiosis was associated with degree of naming outcome with the use of both measures after controlling for lesion volume, months since stroke, comorbid conditions, and damage to specific locations. CONCLUSION: Naming outcome after poststroke aphasia is influenced by the initial severity of right hemisphere leukoaraiosis independently of other variables. Degree of recovery from aphasia may depend on the integrity of the noninfarcted brain tissue.

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Long-Term Cognitive Decline After Newly Diagnosed Heart Failure: Longitudinal Analysis in the CHS (Cardiovascular Health Study). - Hammond, Christa A; Blades, Natalie J; Chaudhry, Sarwat I; Dodson, John A; Longstreth, W T; Heckbert, Susan R; Psaty, Bruce M; Arnold, Alice M; Dublin, Sascha; Sitlani, Colleen M; Gardin, Julius M; Thielke, Stephen M; et al. (Circ Heart Fail, 2018)
BACKGROUND: Heart failure (HF) is associated with cognitive impairment. However, we know little about the time course of cognitive change after HF diagnosis, the importance of comorbid atrial fibrillation, or the role of ejection fraction. We sought to determine the associations of incident HF with rates of cognitive decline and whether these differed by atrial fibrillation status or reduced versus preserved ejection fraction. METHODS AND RESULTS: Participants were 4864 men and women aged ≥65 years without a history of HF and free of clinical stroke in the CHS (Cardiovascular Health Study)-a community-based prospective cohort study in the United States, with cognition assessed annually from 1989/1990 through 1998/1999. We identified 496 participants with incident HF by review of hospital discharge summaries and Medicare claims data, with adjudication according to standard criteria. Global cognitive ability was measured by the Modified Mini-Mental State Examination. In adjusted models, 5-year decline in model-predicted mean Modified Mini-Mental State Examination score was 10.2 points (95% confidence interval, 8.6-11.8) after incident HF diagnosed at 80 years of age, compared with a mean 5-year decline of 5.8 points (95% confidence interval, 5.3-6.2) from 80 to 85 years of age without HF. The association was stronger at older ages than at younger ages, did not vary significantly in the presence versus absence of atrial fibrillation (=0.084), and did not vary significantly by reduced versus preserved ejection fraction (=0.734). CONCLUSIONS: Decline in global cognitive ability tends to be faster after HF diagnosis than without HF. Clinical and public health implications of this finding warrant further attention.

Low thyroid function is not associated with an accelerated deterioration in renal function. - Meuwese, Christiaan L; van Diepen, Merel; Cappola, Anne R; Sarnak, Mark J; Shlipak, Michael G; Bauer, Douglas C; Fried, Linda P; Iacoviello, Massimo; Vaes, Bert; Degryse, Jean; Khaw, Kay-Tee; Luben, Robert N; et al. (Nephrol Dial Transplant, 2018)
Background: Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups. Methods: Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models. Results: A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function. Conclusions: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Metabolic Clusters and Outcomes in Older Adults: The Cardiovascular Health Study. - Mukamal, Kenneth J; Siscovick, David S; de Boer, Ian H; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Fitzpatrick, Annette L; Tracy, Russell P; Boyko, Edward J; Kahn, Steven E; Arnold, Alice M (J Am Geriatr Soc, 2018)
BACKGROUND/OBJECTIVES: Few studies have the requisite phenotypic information to define metabolic patterns that may inform our understanding of the pathophysiology and consequences of diabetes in older adults. We sought to characterize clusters of older adults on the basis of shared metabolic features. DESIGN: Population-based prospective cohort study. SETTING: Four U.S. Cardiovascular Health Study field centers. PARTICIPANTS: Individuals aged 65 and older taking no glucose-lowering agents (N = 2,231). MEASUREMENTS: K-means cluster analysis of 11 metabolic parameters (fasting and postload serum glucose and plasma insulin, fasting C-peptide, body mass index, C-reactive protein (CRP), estimated glomerular filtration rate (eGFR), albuminuria, carboxymethyl lysine (an advanced glycation end-product), procollagen III N-terminal propeptide (a fibrotic marker)) and their associations with incident cardiovascular disease, diabetes, disability, and mortality over 8 to 14.5 years of follow-up and with measures of subclinical cardiovascular disease. RESULTS: A 6-cluster solution provided robust differentiation into distinct, identifiable clusters. Cluster A (n = 739) had the lowest glucose and insulin and highest eGFR and the lowest rates of all outcomes. Cluster B (n = 419) had high glucose and insulin and intermediate rates of most outcomes. Cluster C (n = 118) had the highest insulin. Cluster D (n = 129) had the highest glucose with much lower insulin. Cluster E (n = 314) had the lowest eGFR and highest albuminuria. Cluster F (n = 512) had the highest CRP. Rates of CVD, mortality, and subclinical atherosclerosis were highest in clusters C, D, and E and were similar to rates in participants with treated diabetes. Incidence of disability was highest in Cluster C. CONCLUSION: Clustering according to metabolic parameters identifies distinct phenotypes that are strongly associated with clinical and functional outcomes, even at advanced age.
Keywords: Aged; Aged, 80 and over; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Incidence; Insulin; Longitudinal Studies; Male; Prospective Studies; Risk Factors; United States

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Multiethnic Meta-Analysis Identifies RAI1 as a Possible Obstructive Sleep Apnea-related Quantitative Trait Locus in Men. - Chen, Han; Cade, Brian E; Gleason, Kevin J; Bjonnes, Andrew C; Stilp, Adrienne M; Sofer, Tamar; Conomos, Matthew P; Ancoli-Israel, Sonia; Arens, Raanan; Azarbarzin, Ali; Bell, Graeme I; Below, Jennifer E; et al. (Am J Respir Cell Mol Biol, 2018)
Obstructive sleep apnea (OSA) is a common heritable disorder displaying marked sexual dimorphism in disease prevalence and progression. Previous genetic association studies have identified a few genetic loci associated with OSA and related quantitative traits, but they have only focused on single ethnic groups, and a large proportion of the heritability remains unexplained. The apnea-hypopnea index (AHI) is a commonly used quantitative measure characterizing OSA severity. Because OSA differs by sex, and the pathophysiology of obstructive events differ in rapid eye movement (REM) and non-REM (NREM) sleep, we hypothesized that additional genetic association signals would be identified by analyzing the NREM/REM-specific AHI and by conducting sex-specific analyses in multiethnic samples. We performed genome-wide association tests for up to 19,733 participants of African, Asian, European, and Hispanic/Latino American ancestry in 7 studies. We identified rs12936587 on chromosome 17 as a possible quantitative trait locus for NREM AHI in men (N = 6,737; P = 1.7 × 10) but not in women (P = 0.77). The association with NREM AHI was replicated in a physiological research study (N = 67; P = 0.047). This locus overlapping the RAI1 gene and encompassing genes PEMT1, SREBF1, and RASD1 was previously reported to be associated with coronary artery disease, lipid metabolism, and implicated in Potocki-Lupski syndrome and Smith-Magenis syndrome, which are characterized by abnormal sleep phenotypes. We also identified gene-by-sex interactions in suggestive association regions, suggesting that genetic variants for AHI appear to vary by sex, consistent with the clinical observations of strong sexual dimorphism.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Protein and glycomic plasma markers for early detection of adenoma and colon cancer. - Rho, Jung-Hyun; Ladd, Jon J; Li, Christopher I; Potter, John D; Zhang, Yuzheng; Shelley, David; Shibata, David; Coppola, Domenico; Yamada, Hiroyuki; Toyoda, Hidenori; Tada, Toshifumi; Kumada, Takashi; et al. (Gut, 2018)
OBJECTIVE: To discover and confirm blood-based colon cancer early-detection markers. DESIGN: We created a high-density antibody microarray to detect differences in protein levels in plasma from individuals diagnosed with colon cancer <3 years after blood was drawn (ie, prediagnostic) and cancer-free, matched controls. Potential markers were tested on plasma samples from people diagnosed with adenoma or cancer, compared with controls. Components of an optimal 5-marker panel were tested via immunoblotting using a third sample set, Luminex assay in a large fourth sample set and immunohistochemistry (IHC) on tissue microarrays. RESULTS: In the prediagnostic samples, we found 78 significantly (t-test) increased proteins, 32 of which were confirmed in the diagnostic samples. From these 32, optimal 4-marker panels of BAG family molecular chaperone regulator 4 (BAG4), interleukin-6 receptor subunit beta (IL6ST), von Willebrand factor (VWF) and CD44 or epidermal growth factor receptor (EGFR) were established. Each panel member and the panels also showed increases in the diagnostic adenoma and cancer samples in independent third and fourth sample sets via immunoblot and Luminex, respectively. IHC results showed increased levels of BAG4, IL6ST and CD44 in adenoma and cancer tissues. Inclusion of EGFR and CD44 sialyl Lewis-A and Lewis-X content increased the panel performance. The protein/glycoprotein panel was statistically significantly higher in colon cancer samples, characterised by a range of area under the curves from 0.90 (95% CI 0.82 to 0.98) to 0.86 (95% CI 0.83 to 0.88), for the larger second and fourth sets, respectively. CONCLUSIONS: A panel including BAG4, IL6ST, VWF, EGFR and CD44 protein/glycomics performed well for detection of early stages of colon cancer and should be further examined in larger studies.
Keywords: Adaptor Proteins, Signal Transducing; Adenoma; Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; CA-19-9 Antigen; Case-Control Studies; Colonic Neoplasms; Cytokine Receptor gp130; Early Detection of Cancer; ErbB Receptors; Female; Humans; Hyaluronan Receptors; Lewis X Antigen; Male; Middle Aged; Oligosaccharides; Protein Array Analysis; von Willebrand Factor

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Sugar-sweetened beverage intake associations with fasting glucose and insulin concentrations are not modified by selected genetic variants in a ChREBP-FGF21 pathway: a meta-analysis. - McKeown, Nicola M; Dashti, Hassan S; Ma, Jiantao; Haslam, Danielle E; Kiefte-de Jong, Jessica C; Smith, Caren E; Tanaka, Toshiko; Graff, Mariaelisa; Lemaitre, Rozenn N; Rybin, Denis; Sonestedt, Emily; Frazier-Wood, Alexis C; et al. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Sugar-sweetened beverages (SSBs) are a major dietary contributor to fructose intake. A molecular pathway involving the carbohydrate responsive element-binding protein (ChREBP) and the metabolic hormone fibroblast growth factor 21 (FGF21) may influence sugar metabolism and, thereby, contribute to fructose-induced metabolic disease. We hypothesise that common variants in 11 genes involved in fructose metabolism and the ChREBP-FGF21 pathway may interact with SSB intake to exacerbate positive associations between higher SSB intake and glycaemic traits. METHODS: Data from 11 cohorts (six discovery and five replication) in the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided association and interaction results from 34,748 adults of European descent. SSB intake (soft drinks, fruit punches, lemonades or other fruit drinks) was derived from food-frequency questionnaires and food diaries. In fixed-effects meta-analyses, we quantified: (1) the associations between SSBs and glycaemic traits (fasting glucose and fasting insulin); and (2) the interactions between SSBs and 18 independent SNPs related to the ChREBP-FGF21 pathway. RESULTS: In our combined meta-analyses of discovery and replication cohorts, after adjustment for age, sex, energy intake, BMI and other dietary covariates, each additional serving of SSB intake was associated with higher fasting glucose (β ± SE 0.014 ± 0.004 [mmol/l], p = 1.5 × 10-3) and higher fasting insulin (0.030 ± 0.005 [log e pmol/l], p = 2.0 × 10-10). No significant interactions on glycaemic traits were observed between SSB intake and selected SNPs. While a suggestive interaction was observed in the discovery cohorts with a SNP (rs1542423) in the β-Klotho (KLB) locus on fasting insulin (0.030 ± 0.011 log e pmol/l, uncorrected p = 0.006), results in the replication cohorts and combined meta-analyses were non-significant. CONCLUSIONS/INTERPRETATION: In this large meta-analysis, we observed that SSB intake was associated with higher fasting glucose and insulin. Although a suggestive interaction with a genetic variant in the ChREBP-FGF21 pathway was observed in the discovery cohorts, this observation was not confirmed in the replication analysis. TRIAL REGISTRATION: Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005121 (Framingham Offspring Study), NCT00005487 (Multi-Ethnic Study of Atherosclerosis) and NCT00005152 (Nurses' Health Study).

Systemic inflammation as a predictor of brain aging: Contributions of physical activity, metabolic risk, and genetic risk. - Corlier, Fabian; Hafzalla, George; Faskowitz, Joshua; Kuller, Lewis H; Becker, James T; Lopez, Oscar L; Thompson, Paul M; Braskie, Meredith N (Neuroimage, 2018)
Inflammatory processes may contribute to risk for Alzheimer's disease (AD) and age-related brain degeneration. Metabolic and genetic risk factors, and physical activity may, in turn, influence these inflammatory processes. Some of these risk factors are modifiable, and interact with each other. Understanding how these processes together relate to brain aging will help to inform future interventions to treat or prevent cognitive decline. We used brain magnetic resonance imaging (MRI) to scan 335 older adult humans (mean age 77.3 ± 3.4 years) who remained non-demented for the duration of the 9-year longitudinal study. We used structural equation modeling (SEM) in a subset of 226 adults to evaluate whether measures of baseline peripheral inflammation (serum C-reactive protein levels; CRP), mediated the baseline contributions of genetic and metabolic risk, and physical activity, to regional cortical thickness in AD-relevant brain regions at study year 9. We found that both baseline metabolic risk and AD risk variant apolipoprotein E ε4 (APOE4), modulated baseline serum CRP. Higher baseline CRP levels, in turn, predicted thinner regional cortex at year 9, and mediated an effect between higher metabolic risk and thinner cortex in those regions. A higher polygenic risk score composed of variants in immune-associated AD risk genes (other than APOE) was associated with thinner regional cortex. However, CRP levels did not mediate this effect, suggesting that other mechanisms may be responsible for the elevated AD risk. We found interactions between genetic and environmental factors and structural brain health. Our findings support the role of metabolic risk and peripheral inflammation in age-related brain decline.

Temporal Trends in the Incidence of and Mortality Associated With Heart Failure With Preserved and Reduced Ejection Fraction. - Tsao, Connie W; Lyass, Asya; Enserro, Danielle; Larson, Martin G; Ho, Jennifer E; Kizer, Jorge R; Gottdiener, John S; Psaty, Bruce M; Vasan, Ramachandran S (JACC Heart Fail, 2018)
OBJECTIVES: This study aimed to determine temporal trends in the incidence of and mortality associated with heart failure (HF) and its subtypes (heart failure with reduced ejection fraction [HFrEF] and heart rate with preserved ejection fraction [HFpEF]) in the community. BACKGROUND: Major shifts in cardiovascular disease risk factor prevalence and advances in therapies may have influenced HF incidence and mortality. METHODS: In the FHS (Framingham Heart Study) and CHS (Cardiovascular Health Study), for participants who were ≥60 years of age and free of HF (n = 15,217; 60% women; 2,524 incident HF cases; 115,703 person-years of follow-up), we estimated adjusted incidence rate ratios of HF, HFrEF, and HFpEF from 1990 to 1999 and 2000 to 2009. We compared the cumulative incidence of and mortality associated with HFrEF versus HFpEF within and between decades. RESULTS: Across the 2 decades, HF incidence rate ratio was similar (p = 0.13). The incidence rate ratio of HFrEF declined (p = 0.0029), whereas HFpEF increased (p < 0.001). Although HFrEF incidence declined more in men than in women, men had a higher incidence of HFrEF than women in each decade (p < 0.001). The incidence of HFpEF significantly increased over time in both men and women (p < 0.001 and p = 0.02, respectively). During follow-up after HF, 1,701 individuals died (67.4%; HFrEF, n = 557 [33%]; HFpEF, n = 474 [29%]). There were no significant differences in mortality rates (overall, cardiovascular disease, and noncardiovascular disease) across decades within HF subtypes or between HFrEF and HFpEF within decade. CONCLUSIONS: In several U.S. community-based samples from 1990 to 2009, we observed divergent trends of decreasing HFrEF and increasing HFpEF incidence, with stable overall HF incidence and high risk for mortality. Our findings highlight the need to elucidate factors contributing to these observations.

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Whole genome sequencing of Caribbean Hispanic families with late-onset Alzheimer's disease. - Vardarajan, Badri N; Barral, Sandra; Jaworski, James; Beecham, Gary W; Blue, Elizabeth; Tosto, Giuseppe; Reyes-Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al. (Ann Clin Transl Neurol, 2018)
Objective: To identify rare causal variants underlying known loci that segregate with late-onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case-control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene-based associations with disease within LOAD GWAS loci. Results: A variant in p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07-30.9, = 0.041). In addition, missense mutations in and under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow-up genotyping both were nominally significant ( < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including ( = 0.049), ( = 0.0098) and ( = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.

Whole-exome sequencing in 20,197 persons for rare variants in Alzheimer's disease. - Raghavan, Neha S; Brickman, Adam M; Andrews, Howard; Manly, Jennifer J; Schupf, Nicole; Lantigua, Rafael; Wolock, Charles J; Kamalakaran, Sitharthan; Petrovski, Slave; Tosto, Giuseppe; Vardarajan, Badri N; Goldstein, David B; et al. (Ann Clin Transl Neurol, 2018)
Objective: The genetic bases of Alzheimer's disease remain uncertain. An international effort to fully articulate genetic risks and protective factors is underway with the hope of identifying potential therapeutic targets and preventive strategies. The goal here was to identify and characterize the frequency and impact of rare and ultra-rare variants in Alzheimer's disease, using whole-exome sequencing in 20,197 individuals. Methods: We used a gene-based collapsing analysis of loss-of-function ultra-rare variants in a case-control study design with data from the Washington Heights-Inwood Columbia Aging Project, the Alzheimer's Disease Sequencing Project and unrelated individuals from the Institute of Genomic Medicine at Columbia University. Results: We identified 19 cases carrying extremely rare loss-of-function variants among a collection of 6,965 cases and a single loss-of-function variant among 13,252 controls ( = 2.17 × 10; OR: 36.2 [95% CI: 5.8-1493.0]). Age-at-onset was 7 years earlier for patients with qualifying variant compared with noncarriers. No other gene attained a study-wide level of statistical significance, but multiple top-ranked genes, including , and were among candidates for follow-up studies. Interpretation: This study implicates ultra-rare, loss-of-function variants in as a significant genetic risk factor for Alzheimer's disease and provides a comprehensive dataset comparing the burden of rare variation in nearly all human genes in Alzheimer's disease cases and controls. This is the first investigation to establish a genome-wide statistically significant association between multiple extremely rare loss-of-function variants in and Alzheimer's disease in a large whole-exome study of unrelated cases and controls.

Admixture mapping identifies novel loci for obstructive sleep apnea in Hispanic/Latino Americans. - Wang, Heming; Cade, Brian E; Sofer, Tamar; Sands, Scott A; Chen, Han; Browning, Sharon R; Stilp, Adrienne M; Louie, Tin L; Thornton, Timothy A; Johnson, W Craig; Below, Jennifer E; Conomos, Matthew P; et al. (Hum Mol Genet, 2019)
Obstructive sleep apnea (OSA) is a common disorder associated with increased risk of cardiovascular disease and mortality. Its prevalence and severity vary across ancestral background. Although OSA traits are heritable, few genetic associations have been identified. To identify genetic regions associated with OSA and improve statistical power, we applied admixture mapping on three primary OSA traits [the apnea hypopnea index (AHI), overnight average oxyhemoglobin saturation (SaO2) and percentage time SaO2 < 90%] and a secondary trait (respiratory event duration) in a Hispanic/Latino American population study of 11 575 individuals with significant variation in ancestral background. Linear mixed models were performed using previously inferred African, European and Amerindian local genetic ancestry markers. Global African ancestry was associated with a lower AHI, higher SaO2 and shorter event duration. Admixture mapping analysis of the primary OSA traits identified local African ancestry at the chromosomal region 2q37 as genome-wide significantly associated with AHI (P < 5.7 × 10-5), and European and Amerindian ancestries at 18q21 suggestively associated with both AHI and percentage time SaO2 < 90% (P < 10-3). Follow-up joint ancestry-SNP association analyses identified novel variants in ferrochelatase (FECH), significantly associated with AHI and percentage time SaO2 < 90% after adjusting for multiple tests (P < 8 × 10-6). These signals contributed to the admixture mapping associations and were replicated in independent cohorts. In this first admixture mapping study of OSA, novel associations with variants in the iron/heme metabolism pathway suggest a role for iron in influencing respiratory traits underlying OSA.

Advanced glycation end product carboxymethyl-lysine and risk of incident peripheral artery disease in older adults: The Cardiovascular Health Study. - Garg, Parveen K; Biggs, Mary L; Barzilay, Joshua; Djoussé, Luc; Hirsch, Calvin; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Mukamal, Kenneth J (Diab Vasc Dis Res, 2019)
Carboxymethyl-lysine is an advanced glycation end product that is detectable in the serum. Higher carboxymethyl-lysine levels have been associated with increased risk of coronary heart disease, stroke and cardiovascular mortality. We determined whether high carboxymethyl-lysine levels are also associated with the risk of peripheral artery disease in Cardiovascular Health Study participants who were all aged 65 years and older at baseline. Multivariate Cox proportional hazards models were used to determine the association of baseline carboxymethyl-lysine levels with incident peripheral artery disease in 3267 individuals followed for a median length of 10.0 years. A total of 157 cases of incident peripheral artery disease occurred during follow-up. No significant relationship between carboxymethyl-lysine and risk of peripheral artery disease was found (hazard ratio per standard deviation increment = 1.03; 95% confidence interval = 0.87, 1.23).

Albuminuria, Lung Function Decline, and Risk of Incident Chronic Obstructive Pulmonary Disease. The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Grams, Morgan E; Cassano, Patricia A; Jacobs, David R; Barr, R Graham; Burkart, Kristin M; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura R; O'Connor, George T; Schwartz, Joseph E; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: Chronic lower respiratory diseases (CLRDs), including chronic obstructive pulmonary disease (COPD) and asthma, are the fourth leading cause of death. Prior studies suggest that albuminuria, a biomarker of endothelial injury, is increased in patients with COPD. OBJECTIVES: To test whether albuminuria was associated with lung function decline and incident CLRDs. METHODS: Six U.S. population-based cohorts were harmonized and pooled. Participants with prevalent clinical lung disease were excluded. Albuminuria (urine albumin-to-creatinine ratio) was measured in spot samples. Lung function was assessed by spirometry. Incident CLRD-related hospitalizations and deaths were classified via adjudication and/or administrative criteria. Mixed and proportional hazards models were used to test individual-level associations adjusted for age, height, weight, sex, race/ethnicity, education, birth year, cohort, smoking status, pack-years of smoking, renal function, hypertension, diabetes, and medications. MEASUREMENTS AND MAIN RESULTS: Among 10,961 participants with preserved lung function, mean age at albuminuria measurement was 60 years, 51% were never-smokers, median albuminuria was 5.6 mg/g, and mean FEV decline was 31.5 ml/yr. For each SD increase in log-transformed albuminuria, there was 2.81% greater FEV decline (95% confidence interval [CI], 0.86-4.76%; P = 0.0047), 11.02% greater FEV/FVC decline (95% CI, 4.43-17.62%; P = 0.0011), and 15% increased hazard of incident spirometry-defined moderate-to-severe COPD (95% CI, 2-31%, P = 0.0021). Each SD log-transformed albuminuria increased hazards of incident COPD-related hospitalization/mortality by 26% (95% CI, 18-34%, P < 0.0001) among 14,213 participants followed for events. Asthma events were not significantly associated. Associations persisted in participants without current smoking, diabetes, hypertension, or cardiovascular disease. CONCLUSIONS: Albuminuria was associated with greater lung function decline, incident spirometry-defined COPD, and incident COPD-related events in a U.S. population-based sample.

APOL1 gene variants and kidney disease in whites: the cardiovascular health study. - Drury, Erika R; Friedman, David J; Pollak, Martin R; Ix, Joachim H; Kuller, Lewis H; Tracy, Russell P; Mukamal, Kenneth J (Nephrol Dial Transplant, 2019)

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation: A Mendelian Randomization Study. - Ellervik, Christina; Roselli, Carolina; Christophersen, Ingrid E; Alonso, Alvaro; Pietzner, Maik; Sitlani, Collen M; Trompet, Stella; Arking, Dan E; Geelhoed, Bastiaan; Guo, Xiuqing; Kleber, Marcus E; Lin, Henry J; et al. (JAMA Cardiol, 2019)
Importance: Increased free thyroxine (FT4) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear. Objective: To evaluate the potential direct involvement of thyroid traits on AF. Design, Setting, and Participants: Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry. Exposures: Genomewide significant variants were used as instruments for standardized FT4 and thyrotropin levels within the reference range, standardized triiodothyronine (FT3):FT4 ratio, hypothyroidism, standardized thyroid peroxidase antibody levels, and hyperthyroidism. Mendelian randomization used genetic risk scores in study-level analysis or individual single-nucleotide polymorphisms in 2-sample MR for the summary-level data. Main Outcomes and Measures: Prevalent and incident AF. Results: The study-level analysis included 7679 individuals with AF and 49 233 referents (mean age [standard error], 62 [3] years; 15 859 men [29.7%]). In study-level random-effects meta-analysis, the pooled hazard ratio of FT4 levels (nanograms per deciliter) for incident AF was 1.55 (95% CI, 1.09-2.20; P = .02; I2 = 76%) and the pooled odds ratio (OR) for prevalent AF was 2.80 (95% CI, 1.41-5.54; P = .003; I2 = 64%) in multivariable-adjusted analyses. The FT4 genetic risk score was associated with an increase in FT4 by 0.082 SD (standard error, 0.007; P < .001) but not with incident AF (risk ratio, 0.84; 95% CI, 0.62-1.14; P = .27) or prevalent AF (OR, 1.32; 95% CI, 0.64-2.73; P = .46). Similarly, in summary-level inverse-variance weighted random-effects MR, gene-based FT4 within the reference range was not associated with AF (OR, 1.01; 95% CI, 0.89-1.14; P = .88). However, gene-based increased FT3:FT4 ratio, increased thyrotropin within the reference range, and hypothyroidism were associated with AF with inverse-variance weighted random-effects OR of 1.33 (95% CI, 1.08-1.63; P = .006), 0.88 (95% CI, 0.84-0.92; P < .001), and 0.94 (95% CI, 0.90-0.99; P = .009), respectively, and robust to tests of horizontal pleiotropy. However, the subset of hypothyroidism single-nucleotide polymorphisms involved in autoimmunity and thyroid peroxidase antibodies levels were not associated with AF. Gene-based hyperthyroidism was associated with AF with MR-Egger OR of 1.31 (95% CI, 1.05-1.63; P = .02) with evidence of horizontal pleiotropy (P = .045). Conclusions and Relevance: Genetically increased FT3:FT4 ratio and hyperthyroidism, but not FT4 within the reference range, were associated with increased AF, and increased thyrotropin within the reference range and hypothyroidism were associated with decreased AF, supporting a pathway involving the pituitary-thyroid-cardiac axis.

{Association of dietary folate and vitamin B-12 intake with genome-wide DNA methylation in blood: a large-scale epigenome-wide association analysis in 5841 individuals - Mandaviya, P. R.; Joehanes, R.; Brody, J.; Castillo-Fernandez, J. E.; Dekkers, K. F.; Do, A. N.; Graff, M.; H?nninen, I. K.; Tanaka, T.; de Jonge, E. A. L.; Kiefte-de Jong, J. C.; Absher, D. M.; et al. (Am J Clin Nutr, 2019)
Folate and vitamin B-12 are essential micronutrients involved in the donation of methyl groups in cellular metabolism. However, associations between intake of these nutrients and genome-wide DNA methylation levels have not been studied comprehensively in humans.\ The aim of this study was to assess whether folate and/or vitamin B-12 intake are asssociated with genome-wide changes in DNA methylation in leukocytes.\ A large-scale epigenome-wide association study of folate and vitamin B-12 intake was performed on DNA from 5841 participants from 10 cohorts using Illumina 450k arrays. Folate and vitamin B-12 intakes were calculated from food-frequency questionnaires (FFQs). Continuous and categorical (low compared with high intake) linear regression mixed models were applied per cohort, controlling for confounders. A meta-analysis was performed to identify significant differentially methylated positions (DMPs) and regions (DMRs), and a pathway analysis was performed on the DMR annotated genes.\ The categorical model resulted in 6 DMPs, which are all negatively associated with folate intake, annotated to FAM64A, WRAP73, FRMD8, CUX1, and LCN8 genes, which have a role in cellular processes including centrosome localization, cell proliferation, and tumorigenesis. Regional analysis showed 74 folate-associated DMRs, of which 73 were negatively associated with folate intake. The most significant folate-associated DMR was a 400-base pair (bp) spanning region annotated to the LGALS3BP gene. In the categorical model, vitamin B-12 intake was associated with 29 DMRs annotated to 48 genes, of which the most significant was a 1100-bp spanning region annotated to the calcium-binding tyrosine phosphorylation-regulated gene (CABYR). Vitamin B-12 intake was not associated with DMPs.\ We identified novel epigenetic loci that are associated with folate and vitamin B-12 intake. Interestingly, we found a negative association between folate and DNA methylation. Replication of these methylation loci is necessary in future studies.

Association of variants in HTRA1 and NOTCH3 with MRI-defined extremes of cerebral small vessel disease in older subjects. - Mishra, Aniket; Chauhan, Ganesh; Violleau, Marie-Helene; Vojinovic, Dina; Jian, Xueqiu; Bis, Joshua C; Li, Shuo; Saba, Yasaman; Grenier-Boley, Benjamin; Yang, Qiong; Bartz, Traci M; Hofer, Edith; et al. (Brain, 2019)
We report a composite extreme phenotype design using distribution of white matter hyperintensities and brain infarcts in a population-based cohort of older persons for gene-mapping of cerebral small vessel disease. We demonstrate its application in the 3C-Dijon whole exome sequencing (WES) study (n = 1924, nWESextremes = 512), with both single variant and gene-based association tests. We used other population-based cohort studies participating in the CHARGE consortium for replication, using whole exome sequencing (nWES = 2,868, nWESextremes = 956) and genome-wide genotypes (nGW = 9924, nGWextremes = 3308). We restricted our study to candidate genes known to harbour mutations for Mendelian small vessel disease: NOTCH3, HTRA1, COL4A1, COL4A2 and TREX1. We identified significant associations of a common intronic variant in HTRA1, rs2293871 using single variant association testing (Pdiscovery = 8.21 × 10-5, Preplication = 5.25 × 10-3, Pcombined = 4.72 × 10-5) and of NOTCH3 using gene-based tests (Pdiscovery = 1.61 × 10-2, Preplication = 3.99 × 10-2, Pcombined = 5.31 × 10-3). Follow-up analysis identified significant association of rs2293871 with small vessel ischaemic stroke, and two blood expression quantitative trait loci of HTRA1 in linkage disequilibrium. Additionally, we identified two participants in the 3C-Dijon cohort (0.4%) carrying heterozygote genotypes at known pathogenic variants for familial small vessel disease within NOTCH3 and HTRA1. In conclusion, our proof-of-concept study provides strong evidence that using a novel composite MRI-derived phenotype for extremes of small vessel disease can facilitate the identification of genetic variants underlying small vessel disease, both common variants and those with rare and low frequency. The findings demonstrate shared mechanisms and a continuum between genes underlying Mendelian small vessel disease and those contributing to the common, multifactorial form of the disease.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

{Associations of circulating very-long-chain saturated fatty acids and incident type 2 diabetes: a pooled analysis of prospective cohort studies - Fretts, A. M.; Imamura, F.; Marklund, M.; Micha, R.; Wu, J. H. Y.; Murphy, R. A.; Chien, K. L.; McKnight, B.; Tintle, N.; Forouhi, N. G.; Qureshi, W. T.; Virtanen, J. K.; et al. (Am. J. Clin. Nutr., 2019)
Saturated fatty acids (SFAs) of different chain lengths have unique metabolic and biological effects, and a small number of recent studies suggest that higher circulating concentrations of the very-long-chain SFAs (VLSFAs) arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) are associated with a lower risk of diabetes. Confirmation of these findings in a large and diverse population is needed.\ We investigated the associations of circulating VLSFAs 20:0, 22:0, and 24:0 with incident type 2 diabetes in prospective studies.\ Twelve studies that are part of the Fatty Acids and Outcomes Research Consortium participated in the analysis. Using Cox or logistic regression within studies and an inverse-variance-weighted meta-analysis across studies, we examined the associations of VLSFAs 20:0, 22:0, and 24:0 with incident diabetes among 51,431 participants.\ There were 14,276 cases of incident diabetes across participating studies. Higher circulating concentrations of 20:0, 22:0, and 24:0 were each associated with a lower risk of incident diabetes. Pooling across cohorts, the RR (95% CI) for incident diabetes comparing the 90th percentile to the 10th percentile was 0.78 (0.70, 0.87) for 20:0, 0.84 (0.77, 0.91) for 22:0, and 0.75 (0.69, 0.83) for 24:0 after adjustment for demographic, lifestyle, adiposity, and other health factors. Results were fully attenuated in exploratory models that adjusted for circulating 16:0 and triglycerides.\ Results from this pooled analysis indicate that higher concentrations of circulating VLSFAs 20:0, 22:0, and 24:0 are each associated with a lower risk of diabetes.

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

Biochemical markers of bone turnover and risk of incident hip fracture in older women: the Cardiovascular Health Study. - Massera, D; Xu, S; Walker, M D; Valderrábano, R J; Mukamal, K J; Ix, J H; Siscovick, D S; Tracy, R P; Robbins, J A; Biggs, M L; Xue, X; Kizer, J R (Osteoporos Int, 2019)
The relationships of osteocalcin (OC) and C-telopeptide of type I collagen (CTX) with long-term incidence of hip fracture were examined in 1680 post-menopausal women from a population-based study. CTX, but not OC, levels were associated with incident hip fracture in these participants, a relationship characterized by an inverted U-shape. INTRODUCTION: We sought to investigate the relationships of OC, a marker of bone formation, and CTX, a marker of bone resorption, with long-term incidence of hip fracture in older women. METHODS: We included 1680 women from the population-based Cardiovascular Health Study (mean [SD] age 74.5 [5.0] years). The longitudinal association of both markers with incidence of hip fracture was examined using multivariable Cox models. RESULTS: During a median follow-up of 12.3 years, 288 incident hip fractures occurred. Linear spline analysis did not demonstrate an association between OC levels and incident hip fracture. By contrast, increasing levels of CTX up to the middle-upper range were associated with a significantly greater risk of hip fracture (HR = 1.52 per SD increment, 95% CI = 1.10-2.09), while further increases were associated with a marginally non-significant lower risk (HR = 0.80 per SD increment, 95% CI = 0.63-1.01), after full adjustment for potential confounders. In analyses of quartiles, CTX exhibited a similar inverted U-shaped relationship with incident fracture after adjustment, with a significant association observed only for the comparison of quartile 3 to quartile 1 (HR = 1.63, 95% CI = 1.10-2.43). In a subset with available measures, both OC and CTX were inversely associated with bone mineral density of the hip. CONCLUSION: CTX, but not OC, levels were associated with incident hip fracture in post-menopausal women, a relationship characterized by an inverted U-shape. These findings highlight the complex relationship of bone turnover markers with hip fracture risk.

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Common Genetic Variation in Relation to Brachial Vascular Dimensions and Flow-Mediated Vasodilation. - Dörr, Marcus; Hamburg, Naomi M; Müller, Christian; Smith, Nicholas L; Gustafsson, Stefan; Lehtimäki, Terho; Teumer, Alexander; Zeller, Tanja; Li, Xiaohui; Lind, Lars; Raitakari, Olli T; Völker, Uwe; et al. (Circ Genom Precis Med, 2019)

Discrepancy in Frailty Identification: Move beyond Predictive Validity. - Xue, Qian-Li; Tian, Jing; Walston, Jeremy D; Chaves, Paulo H M; Newman, Anne B; Bandeen-Roche, Karen (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: To evaluate the discordance in frailty classification between the frailty index (FI) and the physical frailty phenotype (PFP) and identify factors discriminating those with discordant frailty classification from each other and from those for whom the assessments agree. METHODS: A prospective observational study of older adults aged 65 and older selected from Medicare eligibility lists in four US communities (n=5,362). The PFP was measured by the Cardiovascular Health Study PFP. Subjects meeting ≥3 of the 5 criteria were deemed frail. The FI was calculated as the proportion of deficits in an a priori selected set of 48 measures and subjects were classified as frail if FI>0.35. RESULTS: The prevalence of frailty was 7.0% by the PFP and 8.3% by the FI. Of the 730 deemed frail by either instrument, only 12% were in agreement; whereas 39% were classified as frail by PFP but not FI; and 48% were classified as frail by FI but not PFP. Participants aged 65-72 or greater disease burden were mostly likely to be characterized as being FI-frail but not PFP-frail. The associations of frailty with age and mortality was stronger when frailty was measured by the PFP rather than the FI. CONCLUSIONS: Despite comparable frailty prevalence between the PFP and the FI, there was substantial discordance in individual-level classification, with highest agreement existing only in the most vulnerable subset. These findings suggest that there are clinically important contexts in which PFP and FI cannot be used interchangeably.

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls - Flannick, J.; Mercader, J. M.; Fuchsberger, C.; Udler, M. S.; Mahajan, A.; Wessel, J.; Teslovich, T. M.; Caulkins, L.; Koesterer, R.; Barajas-Olmos, F.; Blackwell, T. W.; Boerwinkle, E.; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 Ã— 10-3) and candidate genes from knockout mice (P = 5.2 Ã— 10-3). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)
) with at least one obesity or lipid trait. Candidate genes include PRKAR2A, PTH1R, and HDAC9, which have been suggested to play roles in adipocyte differentiation or bone marrow adipose tissue. Taken together, these findings provide further insights into the processes that influence circulating adiponectin levels.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{A genome-wide association study identifies genetic loci associated with specific lobar brain volumes - van der Lee, S. J.; Knol, M. J.; Chauhan, G.; Satizabal, C. L.; Smith, A. V.; Hofer, E.; Bis, J. C.; Hibar, D. P.; Hilal, S.; van den Akker, E. B.; Arfanakis, K.; Bernard, M.; et al. (Commun Biol, 2019)
Brain lobar volumes are heritable but genetic studies are limited. We performed genome-wide association studies of frontal, occipital, parietal and temporal lobe volumes in 16,016 individuals, and replicated our findings in 8,789 individuals. We identified six genetic loci associated with specific lobar volumes independent of intracranial volume. Two loci, associated with occipital (6q22.32) and temporal lobe volume (12q14.3), were previously reported to associate with intracranial and hippocampal volume, respectively. We identified four loci previously unknown to affect brain volumes: 3q24 for parietal lobe volume, and 1q22, 4p16.3 and 14q23.1 for occipital lobe volume. The associated variants were located in regions enriched for histone modifications (DAAM1 and THBS3), or close to genes causing Mendelian brain-related diseases (ZIC4 and FGFRL1). No genetic overlap between lobar volumes and neurological or psychiatric diseases was observed. Our findings reveal part of the complex genetics underlying brain development and suggest a role for regulatory regions in determining brain volumes.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Genome-wide association study of breakfast skipping links clock regulation with food timing. - Dashti, Hassan S; Merino, Jordi; Lane, Jacqueline M; Song, Yanwei; Smith, Caren E; Tanaka, Toshiko; McKeown, Nicola M; Tucker, Chandler; Sun, Dianjianyi; Bartz, Traci M; Li-Gao, Ruifang; Nisa, Hoirun; et al. (Am J Clin Nutr, 2019)
BACKGROUND: Little is known about the contribution of genetic variation to food timing, and breakfast has been determined to exhibit the most heritable meal timing. As breakfast timing and skipping are not routinely measured in large cohort studies, alternative approaches include analyses of correlated traits. OBJECTIVES: The aim of this study was to elucidate breakfast skipping genetic variants through a proxy-phenotype genome-wide association study (GWAS) for breakfast cereal skipping, a commonly assessed correlated trait. METHODS: We leveraged the statistical power of the UK Biobank (n = 193,860) to identify genetic variants related to breakfast cereal skipping as a proxy-phenotype for breakfast skipping and applied several in silico approaches to investigate mechanistic functions and links to traits/diseases. Next, we attempted validation of our approach in smaller breakfast skipping GWAS from the TwinUK (n = 2,006) and the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium (n = 11,963). RESULTS: In the UK Biobank, we identified 6 independent GWAS variants, including those implicated for caffeine (ARID3B/CYP1A1), carbohydrate metabolism (FGF21), schizophrenia (ZNF804A), and encoding enzymes important for N6-methyladenosine RNA transmethylation (METTL4, YWHAB, and YTHDF3), which regulates the pace of the circadian clock. Expression of identified genes was enriched in the cerebellum. Genome-wide correlation analyses indicated positive correlations with anthropometric traits. Through Mendelian randomization (MR), we observed causal links between genetically determined breakfast skipping and higher body mass index, more depressive symptoms, and smoking. In bidirectional MR, we demonstrated a causal link between being an evening person and skipping breakfast, but not vice versa. We observed association of our signals in an independent breakfast skipping GWAS in another British cohort (P = 0.032), TwinUK, but not in a meta-analysis of non-British cohorts from the CHARGE consortium (P = 0.095). CONCLUSIONS: Our proxy-phenotype GWAS identified 6 genetic variants for breakfast skipping, linking clock regulation with food timing and suggesting a possible beneficial role of regular breakfast intake as part of a healthy lifestyle.

{Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels - Sabater-Lleal, M.; Huffman, J. E.; de Vries, P. S.; Marten, J.; Mastrangelo, M. A.; Song, C.; Pankratz, N.; Ward-Caviness, C. K.; Yanek, L. R.; Trompet, S.; Delgado, G. E.; Guo, X.; et al. (Circulation, 2019)
Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF.\ We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events.\ We identified 13 novel genome-wide significant ( P≤2.5×10-8) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk.\ The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of SNP and antihypertensive medication interactions on left ventricular traits in African Americans. - Do, Anh N; Zhao, Wei; Baldridge, Abigail S; Raffield, Laura M; Wiggins, Kerri L; Shah, Sanjiv J; Aslibekyan, Stella; Tiwari, Hemant K; Limdi, Nita; Zhi, Degui; Sitlani, Colleen M; Taylor, Kent D; et al. (Mol Genet Genomic Med, 2019)
BACKGROUND: Left ventricular (LV) hypertrophy affects up to 43% of African Americans (AAs). Antihypertensive treatment reduces LV mass (LVM). However, interindividual variation in LV traits in response to antihypertensive treatments exists. We hypothesized that genetic variants may modify the association of antihypertensive treatment class with LV traits measured by echocardiography. METHODS: We evaluated the main effects of the three most common antihypertensive treatments for AAs as well as the single nucleotide polymorphism (SNP)-by-drug interaction on LVM and relative wall thickness (RWT) in 2,068 participants across five community-based cohorts. Treatments included thiazide diuretics (TDs), angiotensin converting enzyme inhibitors (ACE-Is), and dihydropyridine calcium channel blockers (dCCBs) and were compared in a pairwise manner. We performed fixed effects inverse variance weighted meta-analyses of main effects of drugs and 2.5 million SNP-by-drug interaction estimates. RESULTS: We observed that dCCBs versus TDs were associated with higher LVM after adjusting for covariates (p = 0.001). We report three SNPs at a single locus on chromosome 20 that modified the association between RWT and treatment when comparing dCCBs to ACE-Is with consistent effects across cohorts (smallest p = 4.7 × 10 , minor allele frequency range 0.09-0.12). This locus has been linked to LV hypertrophy in a previous study. A marginally significant locus in BICD1 (rs326641) was validated in an external population. CONCLUSIONS: Our study identified one locus having genome-wide significant SNP-by-drug interaction effect on RWT among dCCB users in comparison to ACE-I users. Upon additional validation in future studies, our findings can enhance the precision of medical approaches in hypertension treatment.
Keywords: African Americans; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Humans; Observational Studies as Topic; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors; Ventricular Dysfunction, Left

Genome-wide meta-analysis of variant-by-diuretic interactions as modulators of lipid traits in persons of European and African ancestry. - de Las Fuentes, L; Sung, Y J; Sitlani, C M; Avery, C L; Bartz, T M; Keyser, C de; Evans, D S; Li, X; Musani, S K; Ruiter, R; Smith, A V; Sun, F; et al. (Pharmacogenomics J, 2019)
Hypertension (HTN) is a significant risk factor for cardiovascular morbidity and mortality. Metabolic abnormalities, including adverse cholesterol and triglycerides (TG) profiles, are frequent comorbid findings with HTN and contribute to cardiovascular disease. Diuretics, which are used to treat HTN and heart failure, have been associated with worsening of fasting lipid concentrations. Genome-wide meta-analyses with 39,710 European-ancestry (EA) individuals and 9925 African-ancestry (AA) individuals were performed to identify genetic variants that modify the effect of loop or thiazide diuretic use on blood lipid concentrations. Both longitudinal and cross sectional data were used to compute cohort-specific interaction results, which were then combined through meta-analysis in each ancestry. These ancestry-specific results were further combined through trans-ancestry meta-analysis. Analysis of EA data identified two genome-wide significant (p < 5 × 10) loci with single nucleotide variant (SNV)-loop diuretic interaction on TG concentrations (including COL11A1). Analysis of AA data identified one genome-wide significant locus adjacent to BMP2 with SNV-loop diuretic interaction on TG concentrations. Trans-ancestry analysis strengthened evidence of association for SNV-loop diuretic interaction at two loci (KIAA1217 and BAALC). There were few significant SNV-thiazide diuretic interaction associations on TG concentrations and for either diuretic on cholesterol concentrations. Several promising loci were identified that may implicate biologic pathways that contribute to adverse metabolic side effects from diuretic therapy.

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Genomics of 1 million parent lifespans implicates novel pathways and common diseases and distinguishes survival chances. - Timmers, Paul Rhj; Mounier, Ninon; Läll, Kristi; Fischer, Krista; Ning, Zheng; Feng, Xiao; Bretherick, Andrew D; Clark, David W; Agbessi, M; Ahsan, H; Alves, I; Andiappan, A; et al. (Elife, 2019)
We use a genome-wide association of 1 million parental lifespans of genotyped subjects and data on mortality risk factors to validate previously unreplicated findings near , , , , , and 13q21.31, and identify and replicate novel findings near , , and . We also validate previous findings near 5q33.3/ and , whilst finding contradictory evidence at other loci. Gene set and cell-specific analyses show that expression in foetal brain cells and adult dorsolateral prefrontal cortex is enriched for lifespan variation, as are gene pathways involving lipid proteins and homeostasis, vesicle-mediated transport, and synaptic function. Individual genetic variants that increase dementia, cardiovascular disease, and lung cancer - but not other cancers - explain the most variance. Resulting polygenic scores show a mean lifespan difference of around five years of life across the deciles. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).

High-dimensional longitudinal classification with the multinomial fused lasso. - Adhikari, Samrachana; Lecci, Fabrizio; Becker, James T; Junker, Brian W; Kuller, Lewis H; Lopez, Oscar L; Tibshirani, Ryan J (Stat Med, 2019)
We study regularized estimation in high-dimensional longitudinal classification problems, using the lasso and fused lasso regularizers. The constructed coefficient estimates are piecewise constant across the time dimension in the longitudinal problem, with adaptively selected change points (break points). We present an efficient algorithm for computing such estimates, based on proximal gradient descent. We apply our proposed technique to a longitudinal data set on Alzheimer's disease from the Cardiovascular Health Study Cognition Study. Using data analysis and a simulation study, we motivate and demonstrate several practical considerations such as the selection of tuning parameters and the assessment of model stability. While race, gender, vascular and heart disease, lack of caregivers, and deterioration of learning and memory are all important predictors of dementia, we also find that these risk factors become more relevant in the later stages of life.

{The impact of APOE genotype on survival: Results of 38,537 participants from six population-based cohorts (E2-CHARGE) - Wolters, F. J.; Yang, Q.; Biggs, M. L.; Jakobsdottir, J.; Li, S.; Evans, D. S.; Bis, J. C.; Harris, T. B.; Vasan, R. S.; Zilhao, N. R.; Ghanbari, M.; Ikram, M. A.; et al. (PLoS One, 2019)
Apolipoprotein E is a glycoprotein best known as a mediator and regulator of lipid transport and uptake. The APOE-Îµ4 allele has long been associated with increased risks of Alzheimer's disease and mortality, but the effect of the less prevalent APOE-Îµ2 allele on diseases in the elderly and survival remains elusive.\ We aggregated data of 38,537 individuals of European ancestry (mean age 65.5 years; 55.6% women) from six population-based cohort studies (Rotterdam Study, AGES-Reykjavik Study, Cardiovascular Health Study, Health-ABC Study, and the family-based Framingham Heart Study and Long Life Family Study) to determine the association of APOE, and in particular APOE-Îµ2, with survival in the population.\ During a mean follow-up of 11.7 years, 17,021 individuals died. Compared with homozygous APOE-Îµ3 carriers, APOE-Îµ2 carriers were at lower risk of death (hazard ratio,95% confidence interval: 0.94,0.90-0.99; P = 1.1*10-2), whereas APOE-Îµ4 carriers were at increased risk of death (HR 1.17,1.12-1.21; P = 2.8*10-16). APOE was associated with mortality risk in a dose-dependent manner, with risk estimates lowest for homozygous APOE-Îµ2 (HR 0.89,0.74-1.08), and highest for homozygous APOE-Îµ4 (HR 1.52,1.37-1.70). After censoring for dementia, effect estimates remained similar for APOE-Îµ2 (HR 0.95,0.90-1.01), but attenuated for APOE-Îµ4 (HR 1.07,1.01-1.12). Results were broadly similar across cohorts, and did not differ by age or sex. APOE genotype was associated with baseline lipid fractions (e.g. mean difference(95%CI) in LDL(mg/dL) for Îµ2 versus Îµ33: -17.1(-18.1-16.0), and Îµ4 versus Îµ33: +5.7(4.8;6.5)), but the association between APOE and mortality was unaltered after adjustment for baseline LDL or cardiovascular disease. Given the European ancestry of the study population, results may not apply to other ethnicities.\ Compared with APOE-Îµ3, APOE-Îµ2 is associated with prolonged survival, whereas mortality risk is increased for APOE-Îµ4 carriers. Further collaborative efforts are needed to unravel the role of APOE and in particular APOE-Îµ2 in health and disease.

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

{Low thyroid function is not associated with an accelerated deterioration in renal function - Meuwese, C. L.; van Diepen, M.; Cappola, A. R.; Sarnak, M. J.; Shlipak, M. G.; Bauer, D. C.; Fried, L. P.; Iacoviello, M.; Vaes, B.; Degryse, J.; Khaw, K. T.; Luben, R. N.; et al. (Nephrol Dial Transplant, 2019)
Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups.\ Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models.\ A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function.\ Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) Îµ4) is associated with lower odds of surviving to the 90th and 99th percentile age, while rs7412 (ApoE Îµ2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{Meta-Analysis of Genomewide Association Studies Reveals Genetic Variants for Hip Bone Geometry - Hsu, Y. H.; Estrada, K.; Evangelou, E.; Ackert-Bicknell, C.; Akesson, K.; Beck, T.; Brown, S. J.; Capellini, T.; Carbone, L.; Cauley, J.; Cheung, C. L.; Cummings, S. R.; et al. (J Bone Miner Res, 2019)
Hip geometry is an important predictor of fracture. We performed a meta-analysis of GWAS studies in adults to identify genetic variants that are associated with proximal femur geometry phenotypes. We analyzed four phenotypes: (i) femoral neck length; (ii) neck-shaft angle; (iii) femoral neck width, and (iv) femoral neck section modulus, estimated from DXA scans using algorithms of hip structure analysis. In the Discovery stage, 10 cohort studies were included in the fixed-effect meta-analysis, with up to 18,719 men and women ages 16 to 93 years. Association analyses were performed with ∼2.5 million polymorphisms under an additive model adjusted for age, body mass index, and height. Replication analyses of meta-GWAS significant loci (at adjusted genomewide significance [GWS], threshold p ≤ 2.6 × 10-8 ) were performed in seven additional cohorts in silico. We looked up SNPs associated in our analysis, for association with height, bone mineral density (BMD), and fracture. In meta-analysis (combined Discovery and Replication stages), GWS associations were found at 5p15 (IRX1 and ADAMTS16); 5q35 near FGFR4; at 12p11 (in CCDC91); 11q13 (near LRP5 and PPP6R3 (rs7102273)). Several hip geometry signals overlapped with BMD, including LRP5 (chr. 11). Chr. 11 SNP rs7102273 was associated with any-type fracture (p = 7.5 × 10-5 ). We used bone transcriptome data and discovered several significant eQTLs, including rs7102273 and PPP6R3 expression (p = 0.0007), and rs6556301 (intergenic, chr.5 near FGFR4) and PDLIM7 expression (p = 0.005). In conclusion, we found associations between several genes and hip geometry measures that explained 12% to 22% of heritability at different sites. The results provide a defined set of genes related to biological pathways relevant to BMD and etiology of bone fragility. © 2019 American Society for Bone and Mineral Research.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Multiethnic Genome-Wide Association Study of Diabetic Retinopathy Using Liability Threshold Modeling of Duration of Diabetes and Glycemic Control. - Pollack, Samuela; Igo, Robert P; Jensen, Richard A; Christiansen, Mark; Li, Xiaohui; Cheng, Ching-Yu; Ng, Maggie C Y; Smith, Albert V; Rossin, Elizabeth J; Segrè, Ayellet V; Davoudi, Samaneh; Tan, Gavin S; et al. (Diabetes, 2019)
To identify genetic variants associated with diabetic retinopathy (DR), we performed a large multiethnic genome-wide association study. Discovery included eight European cohorts ( = 3,246) and seven African American cohorts ( = 2,611). We meta-analyzed across cohorts using inverse-variance weighting, with and without liability threshold modeling of glycemic control and duration of diabetes. Variants with a value <1 × 10 were investigated in replication cohorts that included 18,545 European, 16,453 Asian, and 2,710 Hispanic subjects. After correction for multiple testing, the C allele of rs142293996 in an intron of nuclear VCP-like () was associated with DR in European discovery cohorts ( = 2.1 × 10), but did not reach genome-wide significance after meta-analysis with replication cohorts. We applied the Disease Association Protein-Protein Link Evaluator (DAPPLE) to our discovery results to test for evidence of risk being spread across underlying molecular pathways. One protein-protein interaction network built from genes in regions associated with proliferative DR was found to have significant connectivity ( = 0.0009) and corroborated with gene set enrichment analyses. These findings suggest that genetic variation in as well as variation within a protein-protein interaction network that includes genes implicated in inflammation, may influence risk for DR.

{New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders - Evangelou, E.; Gao, H.; Chu, C.; Ntritsos, G.; Blakeley, P.; Butts, A. R.; Pazoki, R.; Suzuki, H.; Koskeridis, F.; Yiorkas, A. M.; Karaman, I.; Elliott, J.; et al. (Nat Hum Behav, 2019)
Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. Here we conducted a meta-analysis of genome-wide association studies of alcohol consumption (g d-1) from the UK Biobank, the Alcohol Genome-Wide Consortium and the Cohorts for Heart and Aging Research in Genomic Epidemiology Plus consortia, collecting data from 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 new common loci and investigated their potential functional importance using magnetic resonance imaging data and gene expression studies. We identify genetic pathways associated with alcohol consumption and suggest genetic mechanisms that are shared with neuropsychiatric disorders such as schizophrenia.

No causal effects of serum urate levels on the risk of chronic kidney disease: A Mendelian randomization study. - Jordan, Daniel M; Choi, Hyon K; Verbanck, Marie; Topless, Ruth; Won, Hong-Hee; Nadkarni, Girish; Merriman, Tony R; Do, Ron (PLoS Med, 2019)
BACKGROUND: Studies have shown strong positive associations between serum urate (SU) levels and chronic kidney disease (CKD) risk; however, whether the relation is causal remains uncertain. We evaluate whether genetic data are consistent with a causal impact of SU level on the risk of CKD and estimated glomerular filtration rate (eGFR). METHODS AND FINDINGS: We used Mendelian randomization (MR) methods to evaluate the presence of a causal effect. We used aggregated genome-wide association data (N = 110,347 for SU, N = 69,374 for gout, N = 133,413 for eGFR, N = 117,165 for CKD), electronic-medical-record-linked UK Biobank data (N = 335,212), and population-based cohorts (N = 13,425), all in individuals of European ancestry, for SU levels and CKD. Our MR analysis showed that SU has a causal effect on neither eGFR level nor CKD risk across all MR analyses (all P > 0.05). These null associations contrasted with our epidemiological association findings from the 4 population-based cohorts (change in eGFR level per 1-mg/dl [59.48 μmol/l] increase in SU: -1.99 ml/min/1.73 m2; 95% CI -2.86 to -1.11; P = 8.08 × 10(-6); odds ratio [OR] for CKD: 1.48; 95% CI 1.32 to 1.65; P = 1.52 × 10(-11)). In contrast, the same MR approaches showed that SU has a causal effect on the risk of gout (OR estimates ranging from 3.41 to 6.04 per 1-mg/dl increase in SU, all P < 10-3), which served as a positive control of our approach. Overall, our MR analysis had >99% power to detect a causal effect of SU level on the risk of CKD of the same magnitude as the observed epidemiological association between SU and CKD. Limitations of this study include the lifelong effect of a genetic perturbation not being the same as an acute perturbation, the inability to study non-European populations, and some sample overlap between the datasets used in the study. CONCLUSIONS: Evidence from our series of causal inference approaches using genetics does not support a causal effect of SU level on eGFR level or CKD risk. Reducing SU levels is unlikely to reduce the risk of CKD development.
Keywords: Adult; Age Factors; Female; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Male; Mendelian Randomization Analysis; Renal Insufficiency, Chronic; Sex Factors; Uric Acid; Young Adult

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

Pharmacogenomics of statin-related myopathy: Meta-analysis of rare variants from whole-exome sequencing. - Floyd, James S; Bloch, Katarzyna M; Brody, Jennifer A; Maroteau, Cyrielle; Siddiqui, Moneeza K; Gregory, Richard; Carr, Daniel F; Molokhia, Mariam; Liu, Xiaoming; Bis, Joshua C; Ahmed, Ammar; Liu, Xuan; et al. (PLoS One, 2019)
AIMS: Statin-related myopathy (SRM), which includes rhabdomyolysis, is an uncommon but important adverse drug reaction because the number of people prescribed statins world-wide is large. Previous association studies of common genetic variants have had limited success in identifying a genetic basis for this adverse drug reaction. We conducted a multi-site whole-exome sequencing study to investigate whether rare coding variants confer an increased risk of SRM. METHODS AND RESULTS: SRM 3-5 cases (N = 505) and statin treatment-tolerant controls (N = 2047) were recruited from multiple sites in North America and Europe. SRM 3-5 was defined as symptoms consistent with muscle injury and an elevated creatine phosphokinase level >4 times upper limit of normal without another likely cause of muscle injury. Whole-exome sequencing and variant calling was coordinated from two analysis centres, and results of single-variant and gene-based burden tests were meta-analysed. No genome-wide significant associations were identified. Given the large number of cases, we had 80% power to identify a variant with minor allele frequency of 0.01 that increases the risk of SRM 6-fold at genome-wide significance. CONCLUSIONS: In this large whole-exome sequencing study of severe statin-related muscle injury conducted to date, we did not find evidence that rare coding variants are responsible for this adverse drug reaction. Larger sample sizes would be required to identify rare variants with small effects, but it is unclear whether such findings would be clinically actionable.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Serum magnesium and calcium levels in relation to ischemic stroke: Mendelian randomization study. - Larsson, Susanna C; Traylor, Matthew; Burgess, Stephen; Boncoraglio, Giorgio B; Jern, Christina; Michaëlsson, Karl; Markus, Hugh S (Neurology, 2019)
OBJECTIVE: To determine whether serum magnesium and calcium concentrations are causally associated with ischemic stroke or any of its subtypes using the mendelian randomization approach. METHODS: Analyses were conducted using summary statistics data for 13 single-nucleotide polymorphisms robustly associated with serum magnesium (n = 6) or serum calcium (n = 7) concentrations. The corresponding data for ischemic stroke were obtained from the MEGASTROKE consortium (34,217 cases and 404,630 noncases). RESULTS: In standard mendelian randomization analysis, the odds ratios for each 0.1 mmol/L (about 1 SD) increase in genetically predicted serum magnesium concentrations were 0.78 (95% confidence interval [CI] 0.69-0.89; = 1.3 × 10) for all ischemic stroke, 0.63 (95% CI 0.50-0.80; = 1.6 × 10) for cardioembolic stroke, and 0.60 (95% CI 0.44-0.82; = 0.001) for large artery stroke; there was no association with small vessel stroke (odds ratio 0.90, 95% CI 0.67-1.20; = 0.46). Only the association with cardioembolic stroke was robust in sensitivity analyses. There was no association of genetically predicted serum calcium concentrations with all ischemic stroke (per 0.5 mg/dL [about 1 SD] increase in serum calcium: odds ratio 1.03, 95% CI 0.88-1.21) or with any subtype. CONCLUSIONS: This study found that genetically higher serum magnesium concentrations are associated with a reduced risk of cardioembolic stroke but found no significant association of genetically higher serum calcium concentrations with any ischemic stroke subtype.

{Soluble CD14 and CD14 Variants, Other Inflammatory Markers, and Glucose Dysregulation in Older Adults: The Cardiovascular Health Study - Shitole, S. G.; Biggs, M. L.; Reiner, A. P.; Mukamal, K. J.; Djouss?, L.; Ix, J. H.; Barzilay, J. I.; Tracy, R. P.; Siscovick, D.; Kizer, J. R. (Diabetes Care, 2019)
Experimental studies have implicated soluble (s)CD14, an effector of lipopolysaccharide-induced inflammation, in insulin resistance, but its role in human metabolic endotoxemia has not been studied. We evaluated sCD14 in relation to dysglycemia in older adults and how this compares to other markers of inflammation.\ We investigated associations of sCD14, interleukin-6 (IL-6), CRP, and white blood cell (WBC) count with insulin resistance (quantitative insulin-sensitivity check index and HOMA 2 of insulin resistance) and incident type 2 diabetes in a population-based cohort of older adults. We also assessed the causal role of sCD14 in insulin resistance using an instrumental variable approach by Mendelian randomization.\ After adjustment for conventional risk factors, each of the four biomarkers showed positive cross-sectional associations with both insulin resistance measures. These associations persisted after mutual adjustment for all markers except sCD14. Over a median follow-up of 11.6 years, 466 cases of diabetes occurred. All biomarkers except sCD14 were positively associated with diabetes, although only WBC count remained associated (hazard ratio 1.43 per doubling [95% CI 1.07, 1.90]) after mutual adjustment. Instrumental variable analysis did not support a causal role for sCD14 in insulin resistance.\ Among older adults, sCD14 was associated with insulin resistance, but this disappeared after adjustment for other biomarkers, showed no evidence of a causal basis, and was not accompanied by a similar association with diabetes. IL-6, CRP, and WBC count were each associated with insulin resistance and diabetes, WBC count most robustly. These findings do not support a central role for sCD14, but they highlight the preeminence of WBC count as an inflammatory measure of diabetes risk in this population.

Statin-induced LDL cholesterol response and type 2 diabetes: a bidirectional two-sample Mendelian randomization study. - Smit, Roelof A J; Trompet, Stella; Leong, Aaron; Goodarzi, Mark O; Postmus, Iris; Warren, Helen; Theusch, Elizabeth; Barnes, Michael R; Arsenault, Benoit J; Li, Xiaohui; Feng, QiPing; Chasman, Daniel I; et al. (Pharmacogenomics J, 2019)
It remains unclear whether the increased risk of new-onset type 2 diabetes (T2D) seen in statin users is due to low LDL-C concentrations, or due to the statin-induced proportional change in LDL-C. In addition, genetic instruments have not been proposed before to examine whether liability to T2D might cause greater proportional statin-induced LDL-C lowering. Using summary-level statistics from the Genomic Investigation of Statin Therapy (GIST, n = 40,914) and DIAGRAM (n = 159,208) consortia, we found a positive genetic correlation between LDL-C statin response and T2D using LD score regression (r = 0.36, s.e. = 0.13). However, mendelian randomization analyses did not provide support for statin response having a causal effect on T2D risk (OR 1.00 (95% CI: 0.97, 1.03) per 10% increase in statin response), nor that liability to T2D has a causal effect on statin-induced LDL-C response (0.20% increase in response (95% CI: -0.40, 0.80) per doubling of odds of liability to T2D). Although we found no evidence to suggest that proportional statin response influences T2D risk, a definitive assessment should be made in populations comprised exclusively of statin users, as the presence of nonstatin users in the DIAGRAM dataset may have substantially diluted our effect estimate.

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

Trends in Blood Pressure and High-Sensitivity Cardiac Troponin-T with Cardiovascular Disease: The Cardiovascular Health Study. - Tehrani, David M; Fan, Wenjun; Nambi, Vijay; Gardin, Julius; Hirsch, Calvin H; Amsterdam, Ezra; deFilippi, Christopher R; Polonsky, Tamar; Wong, Nathan D (Am J Hypertens, 2019)
BACKGROUND: High-sensitivity cardiac troponin T (hs-cTnT) is individually associated with incident hypertension (HTN) and cardiovascular disease (CVD) events. We hypothesize that the increases in hs-cTnT with increases in blood pressure will be related to higher incidence of CVD. METHODS: The Cardiovascular Health Study is a longitudinal cohort of older adults. Those with hs-cTnT data and CVD risk factors at baseline and follow-up (2-3 years later) were stratified based on systolic blood pressure (SBP) (optimal: <120 mmHg, intermediate: 120-139 mmHg, elevated: ≥140 mmHg) and hs-cTnT (undetectable: <5 ng/L, detectable: 5-13 ng/L, elevated: ≥14 ng/L) categories. SBP and hs-cTnT were classified as increased or decreased if they changed categories between exams, and stable if they did not. Cox regression evaluated incident CVD events over an average 9 year follow-up. RESULTS: Among 2219 adults, 510 (23.0 %) had decreased hs-cTnT, 1,279 (57.6 %) had stable hs-cTnT, and 430 (19.4 %) had increased hs-cTnT. Those with increased hs-cTnT had a higher CVD risk with stable SBP (HR: 1.28 [1.04-1.57], p=0.02) or decreased SBP (HR: 1.57 [1.08-2.28], p=0.02) compared to those within the same SBP group but a stable hs-cTnT. In those with lower SBP at follow-up, there was an inverse relation between DBP and risk of CVD events in those with increased hs-cTnT (HR: 0.44 per 10 mmHg increase, p<0.01). CONCLUSION: An increase in hs-cTnT over time is associated with a higher risk of CVD even when the blood pressure is stable or decreases over time.

{Variants Associated with the Ankle Brachial Index Differ by Hispanic/Latino Ethnic Group: a genome-wide association study in the Hispanic Community Health Study/Study of Latinos - Sofer, T.; Emery, L.; Jain, D.; Ellis, A. M.; Laurie, C. C.; Allison, M. A.; Lee, J.; Kurniansyah, N.; Kerr, K. F.; Gonz?lez, H. M.; Tarraf, W.; Criqui, M. H.; et al. (Sci Rep, 2019)
Lower extremity peripheral artery disease (PAD) burden differs by race/ethnicity. Although familial aggregation and heritability studies suggest a genetic basis, little is known about the genetic susceptibility to PAD, especially in non-European descent populations. Genome-wide association studies (GWAS) of the ankle brachial index (ABI) and PAD (defined as an ABI < 0.90) have not been conducted in Hispanics/Latinos. We performed a GWAS of PAD and the ABI in 7,589 participants aged >45 years from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We also performed GWAS for ABI stratified by Hispanic/Latino ethnic subgroups: Central American, Mexican, and South American (Mainland group), and Cuban, Dominican, and Puerto Rican (Caribbean group). We detected two genome-wide significant associations for the ABI in COMMD10 in Puerto Ricans, and at SYBU in the Caribbean group. The lead SNP rs4466200 in the COMMD10 gene had a replication p = 0.02 for the ABI in Multi-Ethnic Study of Atherosclerosis (MESA) African Americans, but it did not replicate in African Americans from the Cardiovascular Health Study (CHS). In a regional look-up, a nearby SNP rs12520838 had Bonferroni adjusted p = 0.05 (unadjusted p = 7.5 Ã— 10-5) for PAD in MESA Hispanics. Among three suggestive associations (p < 10-7) in subgroup-specific analyses, DMD on chromosome X, identified in Central Americans, replicated in MESA Hispanics (p = 2.2 Ã— 10-4). None of the previously reported ABI and PAD associations in whites generalized to Hispanics/Latinos.

{Androgens In Men Study (AIMS): protocol for meta-analyses of individual participant data investigating associations of androgens with health outcomes in men - Yeap, B. B.; Marriott, R. J.; Adams, R. J.; Antonio, L.; Ballantyne, C. M.; Bhasin, S.; Cawthon, P. M.; Couper, D. J.; Dobs, A. S.; Flicker, L.; Karlsson, M.; Martin, S. A.; et al. (BMJ Open, 2020)
This study aims to clarify the role(s) of endogenous sex hormones to influence health outcomes in men, specifically to define the associations of plasma testosterone with incidence of cardiovascular events, cancer, dementia and mortality risk, and to identify factors predicting testosterone concentrations. Data will be accrued from at least three Australian, two European and four North American population-based cohorts involving approximately 20 000 men.\ Eligible studies include prospective cohort studies with baseline testosterone concentrations measured using mass spectrometry and 5 years of follow-up data on incident cardiovascular events, mortality, cancer diagnoses or deaths, new-onset dementia or decline in cognitive function recorded. Data for men, who were not taking androgens or drugs suppressing testosterone production, metabolism or action; and had no prior orchidectomy, are eligible. Systematic literature searches were conducted from 14 June 2019 to 31 December 2019, with no date range set for searches. Aggregate level data will be sought where individual participant data (IPD) are not available. One-stage IPD random-effects meta-analyses will be performed, using linear mixed models, generalised linear mixed models and either stratified or frailty-augmented Cox regression models. Heterogeneity in estimates from different studies will be quantified and bias investigated using funnel plots. Effect size estimates will be presented in forest plots and non-negligible heterogeneity and bias investigated using subgroup or meta-regression analyses.\ Ethics approvals obtained for each of the participating cohorts state that participants have consented to have their data collected and used for research purposes. The Androgens In Men Study has been assessed as exempt from ethics review by the Human Ethics office at the University of Western Australia (file reference number RA/4/20/5014). Each of the component studies had obtained ethics approvals; please refer to respective component studies for details. Research findings will be disseminated to the scientific and broader community via the publication of four research articles, with each involving a separate set of IPD meta-analyses (articles will investigate different, distinct outcomes), at scientific conferences and meetings of relevant professional societies. Collaborating cohort studies will disseminate findings to study participants and local communities.\ CRD42019139668.

Association Between Blood Pressure and Later-Life Cognition Among Black and White Individuals. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Kabeto, Mohammed U; Hingtgen, Stephanie M; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Manly, Jennifer J; et al. (JAMA Neurol, 2020)
Importance: Black individuals are more likely than white individuals to develop dementia. Whether higher blood pressure (BP) levels in black individuals explain differences between black and white individuals in dementia risk is uncertain. Objective: To determine whether cumulative BP levels explain racial differences in cognitive decline. Design, Setting, and Participants: Individual participant data from 5 cohorts (January 1971 to December 2017) were pooled from the Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. The median (interquartile range) follow-up was 12.4 (5.9-21.0) years. Analysis began September 2018. Main Outcomes and Measures: The primary outcome was change in global cognition, and secondary outcomes were change in memory and executive function. Exposures: Race (black vs white). Results: Among 34 349 participants, 19 378 individuals who were free of stroke and dementia and had longitudinal BP, cognitive, and covariate data were included in the analysis. The mean (SD) age at first cognitive assessment was 59.8 (10.4) years and ranged from 5 to 95 years. Of 19 378 individuals, 10 724 (55.3%) were female and 15 526 (80.1%) were white. Compared with white individuals, black individuals had significantly faster declines in global cognition (-0.03 points per year faster [95% CI, -0.05 to -0.01]; P = .004) and memory (-0.08 points per year faster [95% CI, -0.11 to -0.06]; P < .001) but significantly slower declines in executive function (0.09 points per year slower [95% CI, 0.08-0.10]; P < .001). Time-dependent cumulative mean systolic BP level was associated with significantly faster declines in global cognition (-0.018 points per year faster per each 10-mm Hg increase [95% CI, -0.023 to -0.014]; P < .001), memory (-0.028 points per year faster per each 10-mm Hg increase [95% CI, -0.035 to -0.021]; P < .001), and executive function (-0.01 points per year faster per each 10-mm Hg increase [95% CI, -0.014 to -0.007]; P < .001). After adjusting for cumulative mean systolic BP, differences between black and white individuals in cognitive slopes were attenuated for global cognition (-0.01 points per year [95% CI, -0.03 to 0.01]; P = .56) and memory (-0.06 points per year [95% CI, -0.08 to -0.03]; P < .001) but not executive function (0.10 points per year [95% CI, 0.09-0.11]; P < .001). Conclusions and Relevance: These results suggest that black individuals' higher cumulative BP levels may contribute to racial differences in later-life cognitive decline.

Association of CD14 with incident dementia and markers of brain aging and injury. - Pase, Matthew P; Himali, Jayandra J; Beiser, Alexa S; DeCarli, Charles; McGrath, Emer R; Satizabal, Claudia L; Aparicio, Hugo J; Adams, Hieab H H; Reiner, Alexander P; Longstreth, W T; Fornage, Myriam; Tracy, Russell P; et al. (Neurology, 2020)
OBJECTIVE: To test the hypothesis that the inflammatory marker plasma soluble CD14 (sCD14) associates with incident dementia and related endophenotypes in 2 community-based cohorts. METHODS: Our samples included the prospective community-based Framingham Heart Study (FHS) and Cardiovascular Health Study (CHS) cohorts. Plasma sCD14 was measured at baseline and related to the incidence of dementia, domains of cognitive function, and MRI-defined brain volumes. Follow-up for dementia occurred over a mean of 10 years (SD 4) in the FHS and a mean of 6 years (SD 3) in the CHS. RESULTS: We studied 1,588 participants from the FHS (mean age 69 ± 6 years, 47% male, 131 incident events) and 3,129 participants from the CHS (mean age 72 ± 5 years, 41% male, 724 incident events) for the risk of incident dementia. Meta-analysis across the 2 cohorts showed that each SD unit increase in sCD14 was associated with a 12% increase in the risk of incident dementia (95% confidence interval 1.03-1.23; = 0.01) following adjustments for age, sex, ε4 status, and vascular risk factors. Higher levels of sCD14 were associated with various cognitive and MRI markers of accelerated brain aging in both cohorts and with a greater progression of brain atrophy and a decline in executive function in the FHS. CONCLUSION: sCD14 is an inflammatory marker related to brain atrophy, cognitive decline, and incident dementia.

Association of Genetic Variation With Keratoconus. - McComish, Bennet J; Sahebjada, Srujana; Bykhovskaya, Yelena; Willoughby, Colin E; Richardson, Andrea J; Tenen, Abi; Charlesworth, Jac C; Macgregor, Stuart; Mitchell, Paul; Lucas, Sionne E M; Mills, Richard A; Mackey, David A; et al. (JAMA Ophthalmol, 2020)
Importance: Keratoconus is a condition in which the cornea progressively thins and protrudes in a conical shape, severely affecting refraction and vision. It is a major indication for corneal transplant. To discover new genetic loci associated with keratoconus and better understand the causative mechanism of this disease, we performed a genome-wide association study on patients with keratoconus. Objective: To identify genetic susceptibility regions for keratoconus in the human genome. Design, Setting, and Participants: This study was conducted with data from eye clinics in Australia, the United States, and Northern Ireland. The discovery cohort of individuals with keratoconus and control participants from Australia was genotyped using the Illumina HumanCoreExome single-nucleotide polymorphism array. After quality control and data cleaning, genotypes were imputed against the 1000 Genomes Project reference panel (phase III; version 5), and association analyses were completed using PLINK version 1.90. Single-nucleotide polymorphisms with P < 1.00 × 10-6 were assessed for replication in 3 additional cohorts. Control participants were drawn from the cohorts of the Blue Mountains Eye Study and a previous study of glaucoma. Replication cohorts were from a previous keratoconus genome-wide association study data set from the United States, a cohort of affected and control participants from Australia and Northern Ireland, and a case-control cohort from Victoria, Australia. Data were collected from January 2006 to March 2019. Main Outcomes and Measures: Associations between keratoconus and 6 252 612 genetic variants were estimated using logistic regression after adjusting for ancestry using the first 3 principal components. Results: The discovery cohort included 522 affected individuals and 655 control participants, while the replication cohorts included 818 affected individuals (222 from the United States, 331 from Australia and Northern Ireland, and 265 from Victoria, Australia) and 3858 control participants (2927 from the United States, 229 from Australia and Northern Ireland, and 702 from Victoria, Australia). Two novel loci reached genome-wide significance (defined as P < 5.00 × 10-8), with a P value of 7.46 × 10-9 at rs61876744 in patatin-like phospholipase domain-containing 2 gene (PNPLA2) on chromosome 11 and a P value of 6.35 × 10-12 at rs138380, 2.2 kb upstream of casein kinase I isoform epsilon gene (CSNK1E) on chromosome 22. One additional locus was identified with a P value less than 1.00 × 10-6 in mastermind-like transcriptional coactivator 2 (MAML2) on chromosome 11 (P = 3.91 × 10-7). The novel locus in PNPLA2 reached genome-wide significance in an analysis of all 4 cohorts (P = 2.45 × 10-8). Conclusions and Relevance: In this relatively large keratoconus genome-wide association study, we identified a genome-wide significant locus for keratoconus in the region of PNPLA2 on chromosome 11.
Keywords: Adult; Female; Fuchs' Endothelial Dystrophy; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Keratoconus; Lipase; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide

Brachial Flow-mediated Dilation and Risk of Dementia: The Cardiovascular Health Study. - Garg, Parveen K; Tan, Annabel X; Odden, Michelle C; Gardin, Julius M; Lopez, Oscar L; Newman, Anne B; Rawlings, Andreea M; Mukamal, Kenneth J (Alzheimer Dis Assoc Disord, 2020)
INTRODUCTION: Brachial flow-mediated dilation (FMD) is a physiologic measure of endothelial function. We determined the prospective association of brachial FMD with incident dementia among older adults. METHODS: We included 2777 Cardiovascular Health Study participants who underwent brachial FMD measurement. Incident dementia was ascertained by medication use, International Classification of Diseases-9 codes, requirement for a proxy, and death certificates and calibrated to gold-standard assessments performed in a subset of the cohort. RESULTS: Mean participant age at time of brachial FMD measurement was 77.9 years. We identified 1650 incident dementia cases (median follow-up=10.5 y). After adjusting for age, race, sex, education, clinic site, and baseline arterial diameter, risk of dementia for participants in the highest quartile of percent brachial FMD did not differ from those in lowest quartile (hazard ratio=0.89, 95% confidence interval: 0.77, 1.03). CONCLUSIONS: Brachial FMD, measured late in life, is not associated with an increased risk of incident dementia.

Burden of rare exome sequence variants in PROC gene is associated with venous thromboembolism: a population-based study. - Tang, Weihong; Stimson, Mary Rachel; Basu, Saonli; Heckbert, Susan R; Cushman, Mary; Pankow, James S; Folsom, Aaron R; Pankratz, Nathan (J Thromb Haemost, 2020)
BACKGROUND: Rare coding mutations underlying deficiencies of antithrombin and proteins C and S contribute to familial venous thromboembolism (VTE). It is uncertain whether rare variants play a role in the etiology of VTE in the general population. OBJECTIVES: We conducted a deep whole-exome sequencing (WES) study to investigate the associations between rare coding variants and the risk of VTE in two population-based prospective cohorts. PATIENTS/METHODS: Whole-exome sequencing was performed in the Longitudinal Investigation of Thromboembolism Etiology (LITE), which combines the Atherosclerosis Risk in Communities (ARIC) study (316 incident VTE events among 3159 African Americans [AAs] and 458 incident VTEs among 7772 European Americans [EAs]) and the Cardiovascular Healthy Study (CHS; 60 incident VTEs among 1751 EAs). We performed gene-based tests of rare variants (allele frequency < 1%, exome-wide significance P < 1.47 × 10 ) separately in each study and ancestry group, and meta-analyzed the results for the EAs in ARIC and CHS. RESULTS: In the meta-analysis of EAs, we identified one gene, PROC, in which the burden of rare, coding variants was significantly associated with increased risk of VTE (HR = 5.42 [3.11, 9.42] for carriers versus non-carriers, P = 2.27 × 10 ). In ARIC EAs, carriers of the PROC rare variants had on average 0.75 standard deviation (SD) lower concentrations of plasma protein C and 0.28 SD higher D-dimer (P < .05) than non-carriers. Adjustment for low protein C status did not eliminate the association of PROC burden with VTE. In AAs, rare coding PROC variants were not associated with VTE. CONCLUSIONS: Rare coding variants in PROC contribute to increased VTE risk in EAs in this general population sample.

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

Characterization of cardiac mechanics and incident atrial fibrillation in participants of the Cardiovascular Health Study. - Patel, Ravi B; Delaney, Joseph A; Hu, Mo; Patel, Harnish; Cheng, Jeanette; Gottdiener, John; Kizer, Jorge R; Marcus, Gregory M; Turakhia, Mintu P; Deo, Rajat; Heckbert, Susan R; Psaty, Bruce M; et al. (JCI Insight, 2020)
BACKGROUND: Left atrial (LA) and left ventricular (LV) remodeling are associated with atrial fibrillation (AF). The prospective associations of impairment in cardiac mechanical function, as assessed by speckle-tracking echocardiography, with incident AF are less clear. METHODS: In the Cardiovascular Health Study, a community-based cohort of older adults, participants free of AF with echocardiograms of adequate quality for speckle tracking were included. We evaluated the associations of indices of cardiac mechanics (LA reservoir strain, LV longitudinal strain, and LV early diastolic strain rate) with incident AF. RESULTS: Of 4341 participants with strain imaging, participants with lower LA reservoir strain were older, had more cardiometabolic risk factors, and had lower renal function at baseline. Over a median follow-up of 10 years, 497 (11.4%) participants developed AF. Compared with the highest quartile of LA reservoir strain, the lowest quartile of LA reservoir strain was associated with higher risk of AF after covariate adjustment, including LA volume and LV longitudinal strain (heart rate [HR], 1.80; 95% CI, 1.31-2.45; P < 0.001). The association of LA reservoir strain and AF was stronger in subgroups with higher blood pressure, NT-proBNP, and LA volumes. There were no associations of LV longitudinal strain and LV early diastolic strain rate with incident AF after adjustment for LA reservoir strain. CONCLUSION: Lower LA reservoir strain was associated with incident AF, independent of LV mechanics, and with stronger associations in high-risk subgroups. These findings suggest that LA mechanical dysfunction precedes the development of AF. Therapies targeting LA mechanical dysfunction may prevent progression to AF. FUNDING: This research was supported by contracts HHSN268201200036C, HHSN268200800007C, HHSN268201800001C, N01HC55222, N01HC85079, N01HC85080, N01HC85081, N01HC85082, N01HC85083, and N01HC85086 and grants KL2TR001424, R01HL107577, U01HL080295, and U01HL130114 from the NIH's National Center for Advancing Translational Sciences, and National Heart, Lung, and Blood Institute (NHLBI), with additional contribution from the National Institute of Neurological Disorders and Stroke (NINDS). Additional support was provided by R01AG023629 from the National Institute on Aging (NIA). A full list of principal CHS investigators and institutions can be found at CHS-NHLBI.org.

Cholesterol Variability and Cranial Magnetic Resonance Imaging Findings in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Suchy-Dicey, Astrid; Elkind, Mitchell S V; Psaty, Bruce M; Leung, Lester Y; Rice, Kenneth; Tirschwell, David; Longstreth, W T (Stroke, 2020)
Background and Purpose- Serum cholesterol variability, independent of mean, has been associated with stroke, white matter hyperintensities on cranial magnetic resonance imaging (MRI), and other cardiovascular events. We sought to assess the relationship between total serum cholesterol (TC) variability and cranial MRI findings of subclinical or covert vascular brain injury in a longitudinal, population-based cohort study of older adults. Methods- In the Cardiovascular Health Study, we assessed associations between intraindividual TC mean, trend, and variability over ≈5 years with covert brain infarction (CBI) and white matter grade (WMG) on cranial MRI. Mean TC was calculated for each study participant from 4 annual TC measurements between 2 MRI scans. TC trend was calculated as the slope of the linear regression of the TC measurements, and TC variability was calculated as the SD of the residuals from the linear regression. We evaluated the association of intraindividual TC variability with incident CBI and worsening WMG between 2 MRI scans in primary analyses and with prevalent CBI number and WMG on the follow-up MRI scan in secondary analyses. Results- Among participants who were eligible for the study and free of clinical stroke before the follow-up MRI, 17.9% of 1098 had incident CBI, and 27.8% of 1351 had worsening WMG on the follow-up MRI. Mean, trend, and variability of TC were not associated with these outcomes. TC variability, independent of mean and trend, was significantly associated with the number of CBI (β=0.009 [95% CI, 0.003-0.016] =0.004; N=1604) and was associated with WMG (β, 0.009 [95% CI, -0.0002 to 0.019] =0.055; N=1602) on the follow-up MRI. Conclusions- Among older adults, TC variability was not associated with incident CBI or worsening WMG but was associated with the number of prevalent CBI on cranial MRI. More work is needed to validate and to clarify the mechanisms underlying such associations.

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

Estrogen, brain structure, and cognition in postmenopausal women. - Boyle, Christina P; Raji, Cyrus A; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Gach, H Michael; Kuller, Lewis H; Longstreth, William; Carmichael, Owen T; Riedel, Brandalyn C; Thompson, Paul M (Hum Brain Mapp, 2020)
Declining estrogen levels before, during, and after menopause can affect memory and risk for Alzheimer's disease. Undesirable side effects of hormone variations emphasize a role for hormone therapy (HT) where possible benefits include a delay in the onset of dementia-yet findings are inconsistent. Effects of HT may be mediated by estrogen receptors found throughout the brain. Effects may also depend on lifestyle factors, timing of use, and genetic risk. We studied the impact of self-reported HT use on brain volume in 562 elderly women (71-94 years) with mixed cognitive status while adjusting for aforementioned factors. Covariate-adjusted voxelwise linear regression analyses using a model with 16 predictors showed HT use as positively associated with regional brain volumes, regardless of cognitive status. Examinations of other factors related to menopause, oophorectomy and hysterectomy status independently yielded positive effects on brain volume when added to our model. One interaction term, HTxBMI, out of several examined, revealed significant negative association with overall brain volume, suggesting a greater reduction in brain volume than BMI alone. Our main findings relating HT to regional brain volume were as hypothesized, but some exploratory analyses were not in line with existing hypotheses. Studies suggest lower levels of estrogen resulting from oophorectomy and hysterectomy affect brain volume negatively, and the addition of HT modifies the relation between BMI and brain volume positively. Effects of HT may depend on the age range assessed, motivating studies with a wider age range as well as a randomized design.

{Fatty acids in the de novo lipogenesis pathway and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies - Imamura, F.; Fretts, A. M.; Marklund, M.; Ardisson Korat, A. V.; Yang, W. S.; Lankinen, M.; Qureshi, W.; Helmer, C.; Chen, T. A.; Virtanen, J. K.; Wong, K.; Bassett, J. K.; et al. (PLoS Med, 2020)
De novo lipogenesis (DNL) is the primary metabolic pathway synthesizing fatty acids from carbohydrates, protein, or alcohol. Our aim was to examine associations of in vivo levels of selected fatty acids (16:0, 16:1n7, 18:0, 18:1n9) in DNL with incidence of type 2 diabetes (T2D).\ Seventeen cohorts from 12 countries (7 from Europe, 7 from the United States, 1 from Australia, 1 from Taiwan; baseline years = 1970-1973 to 2006-2010) conducted harmonized individual-level analyses of associations of DNL-related fatty acids with incident T2D. In total, we evaluated 65,225 participants (mean ages = 52.3-75.5 years; % women = 20.4%-62.3% in 12 cohorts recruiting both sexes) and 15,383 incident cases of T2D over the 9-year follow-up on average. Cohort-specific association of each of 16:0, 16:1n7, 18:0, and 18:1n9 with incident T2D was estimated, adjusted for demographic factors, socioeconomic characteristics, alcohol, smoking, physical activity, dyslipidemia, hypertension, menopausal status, and adiposity. Cohort-specific associations were meta-analyzed with an inverse-variance-weighted approach. Each of the 4 fatty acids positively related to incident T2D. Relative risks (RRs) per cohort-specific range between midpoints of the top and bottom quintiles of fatty acid concentrations were 1.53 (1.41-1.66; p < 0.001) for 16:0, 1.40 (1.33-1.48; p < 0.001) for 16:1n-7, 1.14 (1.05-1.22; p = 0.001) for 18:0, and 1.16 (1.07-1.25; p < 0.001) for 18:1n9. Heterogeneity was seen across cohorts (I2 = 51.1%-73.1% for each fatty acid) but not explained by lipid fractions and global geographical regions. Further adjusted for triglycerides (and 16:0 when appropriate) to evaluate associations independent of overall DNL, the associations remained significant for 16:0, 16:1n7, and 18:0 but were attenuated for 18:1n9 (RR = 1.03, 95% confidence interval (CI) = 0.94-1.13). These findings had limitations in potential reverse causation and residual confounding by imprecisely measured or unmeasured factors.\ Concentrations of fatty acids in the DNL were positively associated with T2D incidence. Our findings support further work to investigate a possible role of DNL and individual fatty acids in the development of T2D.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

Genetic loci associated with prevalent and incident myocardial infarction and coronary heart disease in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Hahn, Julie; Fu, Yi-Ping; Brown, Michael R; Bis, Joshua C; de Vries, Paul S; Feitosa, Mary F; Yanek, Lisa R; Weiss, Stefan; Giulianini, Franco; Smith, Albert Vernon; Guo, Xiuqing; Bartz, Traci M; et al. (PLoS One, 2020)
BACKGROUND: Genome-wide association studies have identified multiple genomic loci associated with coronary artery disease, but most are common variants in non-coding regions that provide limited information on causal genes and etiology of the disease. To overcome the limited scope that common variants provide, we focused our investigation on low-frequency and rare sequence variations primarily residing in coding regions of the genome. METHODS AND RESULTS: Using samples of individuals of European ancestry from ten cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, both cross-sectional and prospective analyses were conducted to examine associations between genetic variants and myocardial infarction (MI), coronary heart disease (CHD), and all-cause mortality following these events. For prevalent events, a total of 27,349 participants of European ancestry, including 1831 prevalent MI cases and 2518 prevalent CHD cases were used. For incident cases, a total of 55,736 participants of European ancestry were included (3,031 incident MI cases and 5,425 incident CHD cases). There were 1,860 all-cause deaths among the 3,751 MI and CHD cases from six cohorts that contributed to the analysis of all-cause mortality. Single variant and gene-based analyses were performed separately in each cohort and then meta-analyzed for each outcome. A low-frequency intronic variant (rs988583) in PLCL1 was significantly associated with prevalent MI (OR = 1.80, 95% confidence interval: 1.43, 2.27; P = 7.12 × 10-7). We conducted gene-based burden tests for genes with a cumulative minor allele count (cMAC) ≥ 5 and variants with minor allele frequency (MAF) < 5%. TMPRSS5 and LDLRAD1 were significantly associated with prevalent MI and CHD, respectively, and RC3H2 and ANGPTL4 were significantly associated with incident MI and CHD, respectively. No loci were significantly associated with all-cause mortality following a MI or CHD event. CONCLUSION: This study identified one known locus (ANGPTL4) and four new loci (PLCL1, RC3H2, TMPRSS5, and LDLRAD1) associated with cardiovascular disease risk that warrant further investigation.
Keywords: Aging; Coronary Artery Disease; Cross-Sectional Studies; Europe; European Continental Ancestry Group; Genetic Loci; Genome-Wide Association Study; Humans; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

{Genome-Wide Association Study Meta-Analysis of Stroke in 22 000 Individuals of African Descent Identifies Novel Associations With Stroke - Keene, K. L.; Hyacinth, H. I.; Bis, J. C.; Kittner, S. J.; Mitchell, B. D.; Cheng, Y. C.; Pare, G.; Chong, M.; O'Donnell, M.; Meschia, J. F.; Chen, W. M.; Sale, M. M.; et al. (Stroke, 2020)
Stroke is a complex disease with multiple genetic and environmental risk factors. Blacks endure a nearly 2-fold greater risk of stroke and are 2× to 3× more likely to die from stroke than European Americans.\ The COMPASS (Consortium of Minority Population Genome-Wide Association Studies of Stroke) has conducted a genome-wide association meta-analysis of stroke in >22 000 individuals of African ancestry (3734 cases, 18 317 controls) from 13 cohorts.\ In meta-analyses, we identified one single nucleotide polymorphism (rs55931441) near the HNF1A gene that reached genome-wide significance (P=4.62×10-8) and an additional 29 variants with suggestive evidence of association (P<1×10-6), representing 24 unique loci. For validation, a look-up analysis for a 100 kb region flanking the COMPASS single nucleotide polymorphism was performed in SiGN (Stroke Genetics Network) Europeans, SiGN Hispanics, and METASTROKE (Europeans). Using a stringent Bonferroni correction P value of 2.08×10-3 (0.05/24 unique loci), we were able to validate associations at the HNF1A locus in both SiGN (P=8.18×10-4) and METASTROKE (P=1.72×10-3) European populations. Overall, 16 of 24 loci showed evidence for validation across multiple populations. Previous studies have reported associations between variants in the HNF1A gene and lipids, C-reactive protein, and risk of coronary artery disease and stroke. Suggestive associations with variants in the SFXN4 and TMEM108 genes represent potential novel ischemic stroke loci.\ These findings represent the most thorough investigation of genetic determinants of stroke in individuals of African descent, to date.

Incorporating sampling weights into robust estimation of Cox proportional hazards regression model, with illustration in the Multi-Ethnic Study of Atherosclerosis. - Sitlani, Colleen M; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Olson, Nels C; Doyle, Margaret F; Huber, Sally A; Tracy, Russell P; Psaty, Bruce M; C Delaney, Joseph A (BMC Med Res Methodol, 2020)
BACKGROUND: Cox proportional hazards regression models are used to evaluate associations between exposures of interest and time-to-event outcomes in observational data. When exposures are measured on only a sample of participants, as they are in a case-cohort design, the sampling weights must be incorporated into the regression model to obtain unbiased estimating equations. METHODS: Robust Cox methods have been developed to better estimate associations when there are influential outliers in the exposure of interest, but these robust methods do not incorporate sampling weights. In this paper, we extend these robust methods, which already incorporate influence weights, so that they also accommodate sampling weights. RESULTS: Simulations illustrate that in the presence of influential outliers, the association estimate from the weighted robust method is closer to the true value than the estimate from traditional weighted Cox regression. As expected, in the absence of outliers, the use of robust methods yields a small loss of efficiency. Using data from a case-cohort study that is nested within the Multi-Ethnic Study of Atherosclerosis (MESA) longitudinal cohort study, we illustrate differences between traditional and robust weighted Cox association estimates for the relationships between immune cell traits and risk of stroke. CONCLUSIONS: Robust weighted Cox regression methods are a new tool to analyze time-to-event data with sampling, e.g. case-cohort data, when exposures of interest contain outliers.

{An individual participant data analysis of prospective cohort studies on the association between subclinical thyroid dysfunction and depressive symptoms - Wildisen, L.; Del Giovane, C.; Moutzouri, E.; Beglinger, S.; Syrogiannouli, L.; Collet, T. H.; Cappola, A. R.; ?svold, B. O.; Bakker, S. J. L.; Yeap, B. B.; Almeida, O. P.; Ceresini, G.; et al. (Sci Rep, 2020)
{In subclinical hypothyroidism, the presence of depressive symptoms is often a reason for starting levothyroxine treatment. However, data are conflicting on the association between subclinical thyroid dysfunction and depressive symptoms. We aimed to examine the association between subclinical thyroid dysfunction and depressive symptoms in all prospective cohorts with relevant data available. We performed a systematic review of the literature from Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane Library from inception to 10th May 2019. We included prospective cohorts with data on thyroid status at baseline and depressive symptoms during follow-up. The primary outcome was depressive symptoms measured at first available follow-up, expressed on the Beck's Depression Inventory (BDI) scale (range 0-63, higher values indicate more depressive symptoms, minimal clinically important difference: 5 points). We performed a two-stage individual participant data (IPD) analysis comparing participants with subclinical hypo- or hyperthyroidism versus euthyroidism, adjusting for depressive symptoms at baseline, age, sex, education, and income (PROSPERO CRD42018091627). Six cohorts met the inclusion criteria, with IPD on 23,038 participants. Their mean age was 60 years, 65% were female, 21,025 were euthyroid, 1342 had subclinical hypothyroidism and 671 subclinical hyperthyroidism. At first available follow-up [mean 8.2 (Â± 4.3) years], BDI scores did not differ between participants with subclinical hypothyroidism (mean difference = 0.29, 95% confidence interval = - 0.17 to 0.76

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Innate and adaptive immune cell subsets as risk factors for coronary heart disease in two population-based cohorts. - Olson, Nels C; Sitlani, Colleen M; Doyle, Margaret F; Huber, Sally A; Landay, Alan L; Tracy, Russell P; Psaty, Bruce M; Delaney, Joseph A (Atherosclerosis, 2020)
BACKGROUND AND AIMS: Cell-mediated immunity is implicated in atherosclerosis. We evaluated whether innate and adaptive immune cell subsets in peripheral blood are risk factors for coronary heart disease. METHODS: A nested case-cohort study (n = 2155) was performed within the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). Cases of incident myocardial infarction (MI) and incident angina (n = 880 total cases) were compared with a cohort random sample (n = 1275). Immune cell phenotypes (n = 34, including CD14 monocytes, natural killer cells, γδ T cells, CD4, CD8 and CD19 lymphocyte subsets) were measured from cryopreserved cells by flow cytometry. Cox proportional hazards models with adjustment for cardiovascular disease risk factors were used to evaluate associations of cell phenotypes with incident MI and a composite phenotype of incident MI or incident angina (MI-angina) over a median 9.3 years of follow-up. Th1, Th2, Th17, T regulatory (CD4CD25CD127), naive (CD4CD45RA), memory (CD4CD45RO), and CD4CD28 cells were specified as primary hypotheses. In secondary analyses, 27 additional cell phenotypes were investigated. RESULTS: After correction for multiple testing, there were no statistically significant associations of CD4 naive, memory, CD28, or T helper cell subsets with MI or MI-angina in MESA, CHS, or combined-cohort meta analyses. Null associations were also observed for monocyte subsets, natural killer cells, γδ T cells, CD19 B cell and differentiated CD4 and CD8 cell subsets. CONCLUSIONS: The proportions of peripheral blood monocyte and lymphocyte subsets are not strongly related to the future occurrence of MI or angina in adults free of autoimmune disease.

Long-term cognitive decline and mortality after carotid endarterectomy. - Thirumala, Parthasarathy D; Reddy, Rajiv P; Lopez, Oscar L; Chang, Yue-Fang; Becker, James T; Kuller, Lewis H (Clin Neurol Neurosurg, 2020)
OBJECTIVES: To date no studies have evaluated long term cognitive decline after carotid endarterectomy (CEA). We evaluated whether participants who had CEA were at increased risk of cognitive decline over participants who didn't undergo CEA. PATIENTS AND METHODS: The patients in the study were participants in the Cardiovascular Health Study (CHS), a study of 5201 men and women over the age of 65 who were recruited from four communities (Pittsburgh, Pennsylvania; Sacramento, California; Winston-Salem, North Carolina; Hagerstown, Maryland) in 1988-89. The outcomes measured were 1) Decline in 3MSE and digit symbol substitution test (DSST) scores after CEA compared to before CEA. 2) All-cause mortality in CHS cohort among participants who did and did not have CEA. RESULTS: CEA patients had significantly greater annual decrease in the DSST scores -2.43 (SD 4.21) compared to those who did not have a CEA -1.1 (SD 2.57) (p < 0.001) but this was not seen in the 3MSE scores. CEA patients had increased the risk of decline in DSST (OR 2.41, 95 % CI 1.49, 3.88) and 3MSE (OR 2.17, 95 % CI 1.35, 3.48) scores after adjusting for age, gender, race and educational status. CEA was associated with all-cause mortality in the long term with a HR of 2.72 (95 % CI 2.22, 3.34) after adjusting for covariates. Participants with lower baseline 3MSE scores HR 1.39 (1.27, 1.51), lower DSST scores <34 HR 1.69(1.54, 1.85) were more likely deceased. CONCLUSIONS: CEA patients are at increased risk of lower scores on 3MSE and DSST testing in the long term. Mortality in the CHS cohort was higher in participants who underwent CEA. Further, lower 3MSE and DSST scores increased the risk of mortality.

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Metabolites Associated with Walking Ability Among the Oldest Old from the CHS All Stars Study. - Marron, Megan M; Wendell, Stacy G; Boudreau, Robert M; Clish, Clary B; Santanasto, Adam J; Tseng, George C; Zmuda, Joseph M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Low walking ability is highly prevalent with advancing age and predicts major health outcomes. Metabolomics may help to better characterize differences in walking ability among older adults, providing insight into potentially altered molecular processes underlying age-related decline in functioning. We sought to identify metabolites and metabolic pathways associated with high versus low walking ability among 120 participants ages 79-95 from the CHS All Stars study. METHODS: Using a nested case-control design, 60 randomly selected participants with low walking ability were matched one-to-one on age, gender, race, and fasting time with 60 participants with high walking ability. High versus low walking ability was defined as being in the best versus worst tertiles for both gait speed (≥0.9 vs <0.7 m/s) and the Walking Ability Index (7-9 vs 0-1). Using liquid chromatography-mass spectrometry, 569 metabolites were identified in overnight-fasting plasma. RESULTS: Ninety-six metabolites were associated with walking ability, where 24% were triacylglycerols. Triacylglycerols that were higher among those with high walking ability consisted mostly of polyunsaturated fatty acids, whereas triacylglycerols that were lower among those with high walking ability consisted mostly of saturated or monounsaturated fatty acids. Body composition partly explained associations between some metabolites and walking ability. Proline and arginine metabolism was a top pathway associated with walking ability. CONCLUSION: These results may partly reflect pathways of modifiable risk factors, including excess dietary lipids and lack of physical activity, contributing to obesity and further alterations in metabolic pathways that lead to age-related decline in walking ability in this older adult cohort.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Female; Geriatric Assessment; Humans; Male; Metabolomics; Risk Factors; Walking; Walking Speed

Mitochondrial DNA copy number can influence mortality and cardiovascular disease via methylation of nuclear DNA CpGs. - Castellani, Christina A; Longchamps, Ryan J; Sumpter, Jason A; Newcomb, Charles E; Lane, John A; Grove, Megan L; Bressler, Jan; Brody, Jennifer A; Floyd, James S; Bartz, Traci M; Taylor, Kent D; Wang, Penglong; et al. (Genome Med, 2020)
BACKGROUND: Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. METHODS: To investigate this hypothesis, we assessed the relationship between mtDNA-CN and nDNA methylation in 2507 African American (AA) and European American (EA) participants from the Atherosclerosis Risk in Communities (ARIC) study. To validate our findings, we assayed an additional 2528 participants from the Cardiovascular Health Study (CHS) (N = 533) and Framingham Heart Study (FHS) (N = 1995). We further assessed the effect of experimental modification of mtDNA-CN through knockout of TFAM, a regulator of mtDNA replication, via CRISPR-Cas9. RESULTS: Thirty-four independent CpGs were associated with mtDNA-CN at genome-wide significance (P < 5 × 10). Meta-analysis across all cohorts identified six mtDNA-CN-associated CpGs at genome-wide significance (P < 5 × 10). Additionally, over half of these CpGs were associated with phenotypes known to be associated with mtDNA-CN, including coronary heart disease, cardiovascular disease, and mortality. Experimental modification of mtDNA-CN demonstrated that modulation of mtDNA-CN results in changes in nDNA methylation and gene expression of specific CpGs and nearby transcripts. Strikingly, the "neuroactive ligand receptor interaction" KEGG pathway was found to be highly overrepresented in the ARIC cohort (P = 5.24 × 10), as well as the TFAM knockout methylation (P = 4.41 × 10) and expression (P = 4.30 × 10) studies. CONCLUSIONS: These results demonstrate that changes in mtDNA-CN influence nDNA methylation at specific loci and result in differential expression of specific genes that may impact human health and disease via altered cell signaling.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Non-Esterified Fatty Acids and Risks of Frailty, Disability, and Mobility Limitation in Older Adults: The Cardiovascular Health Study. - Ahiawodzi, Peter; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne; Mukamal, Kenneth J (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: Non-esterified fatty acids (NEFAs) play central roles in the relationship between adiposity and glucose metabolism, and they have been implicated in the pathogenesis of cardiovascular disease, but few studies have assessed their effects on complex geriatric syndromes like frailty that cross multiple organ systems. We sought to determine the relationships between NEFAs and incident frailty, disability, and mobility limitation in a population-based cohort of older persons. METHODS: We analyzed 4,710 Cardiovascular Health Study (CHS) participants who underwent measurement of circulating total fasting NEFAs in 1992-1993 and were assessed for frailty in 1996-1997 and for disability and mobility limitation annually. We used ordinal logistic regression to model incident frailty, linear regression to model components of frailty, and Cox regression to model disability and mobility limitation in relation to baseline NEFAs. To ensure proportional hazards, we truncated follow-up at 9 years for disability and 6.5 years for mobility limitation. RESULTS: A total of 42 participants became frail and 510 became pre-frail over a 4-year period, and we documented 1,720 cases of disability and 1,225 cases of mobility limitation during follow-up. NEFAs were positively associated in a dose-dependent manner with higher risks of incident frailty, disability, and mobility limitation. The adjusted odds ratios for frailty were 1.37 (95% confidence interval [CI] = 1.01-1.86; P = .04) across extreme tertiles and 1.17 (95% CI = 1.03-1.33; P = .01) per standard deviation increment. The corresponding hazard ratios for incident disability were 1.14 (95% CI = 1.01-1.30; P = .04) and 1.11 (95% CI = 1.06-1.17; P < .0001); those for incident mobility limitation were 1.23 (95% CI = 1.06-1.43; P = .006) and 1.15 (95% CI = 1.08-1.22; P < .0001). Results were largely consistent among both men and women. Among individual components of frailty, NEFAs were significantly associated with self-reported exhaustion (β = .07; standard error = .03; P = .02). CONCLUSION: Circulating NEFAs are significantly associated with frailty, disability, and mobility limitation among older adults. These results highlight the broad spectrum of adverse health issues associated with NEFA in older adults.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Putative Cut-Points in Sarcopenia Components and Incident Adverse Health Outcomes: An SDOC Analysis. - Cawthon, Peggy M; Manini, Todd; Patel, Sheena M; Newman, Anne; Travison, Thomas; Kiel, Douglas P; Santanasto, Adam J; Ensrud, Kristine E; Xue, Qian-Li; Shardell, Michelle; Duchowny, Kate; Erlandson, Kristine M; et al. (J Am Geriatr Soc, 2020)
OBJECTIVES: Analyses performed by the Sarcopenia Definitions and Outcomes Consortium (SDOC) identified cut-points in several metrics of grip strength for consideration in a definition of sarcopenia. We describe the associations between the SDOC-identified metrics of low grip strength (absolute or standardized to body size/composition); low dual-energy x-ray absorptiometry (DXA) lean mass as previously defined in the literature (appendicular lean mass [ALM]/ht ); and slowness (walking speed <.8 m/s) with subsequent adverse outcomes (falls, hip fractures, mobility limitation, and mortality). DESIGN: Individual-level, sex-stratified pooled analysis. We calculated odds ratios (ORs) or hazard ratios (HRs) for incident falls, mobility limitation, hip fractures, and mortality. Follow-up time ranged from 1 year for falls to 8.8 ± 2.3 years for mortality. SETTING: Eight prospective observational cohort studies. PARTICIPANTS: A total of 13,421 community-dwelling men and 4,828 community-dwelling women. MEASUREMENTS Grip strength by hand dynamometry, gait speed, and lean mass by DXA. RESULTS: Low grip strength (absolute or standardized to body size/composition) was associated with incident outcomes, usually independently of slowness, in both men and women. ORs and HRs generally ranged from 1.2 to 3.0 for those below vs above the cut-point. DXA lean mass was not consistently associated with these outcomes. When considered together, those who had both muscle weakness by absolute grip strength (<35.5 kg in men and <20 kg in women) and slowness were consistently more likely to have a fall, hip fracture, mobility limitation, or die than those without either slowness or muscle weakness. CONCLUSION: Older men and women with both muscle weakness and slowness have a higher likelihood of adverse health outcomes. These results support the inclusion of grip strength and walking speed as components in a summary definition of sarcopenia. J Am Geriatr Soc 68:1429-1437, 2020.

A systematic review and participant-level meta-analysis found little association of retinal microvascular caliber and reduced kidney function. - Lye, Weng Kit; Paterson, Euan; Patterson, Christopher C; Maxwell, Alexander P; Binte Mohammed Abdul, Riswana Banu; Tai, E Shyong; Cheng, Ching Yu; Kayama, Takamasa; Yamashita, Hidetoshi; Sarnak, Mark; Shlipak, Michael; Matsushita, Kunihiro; et al. (Kidney Int, 2020)
Previously, variation in retinal vascular caliber has been reported in association with chronic kidney disease (CKD) but findings remain inconsistent. To help clarify this we conducted individual participant data meta-analysis and aggregate data meta-analysis on summary estimates to evaluate cross-sectional associations between retinal vascular caliber and CKD. A systematic review was performed using Medline and EMBASE for articles published until October 2018. The aggregate analysis used a two-stage approach combining summary estimates from eleven studies (44,803 patients) while the individual participant analysis used a one-stage approach combining raw data from nine studies (33,222 patients). CKD stages 3-5 was defined as an estimated glomerular filtration rate under 60 mL/min/1.73m. Retinal arteriolar and venular caliber (central retinal arteriolar and venular equivalent) were assessed from retinal photographs using computer-assisted methods. Logistic regression estimated relative risk of CKD stages 3-5 associated with a 20 μm decrease (approximately one standard deviation) in central retinal arteriolar and venular equivalent. Prevalence of CKD stages 3-5 was 11.2 % of 33,222 and 11.3 % of 44,803 patients in the individual participant and aggregate data analysis, respectively. No significant associations were detected in adjusted analyses between central retinal arteriolar and venular equivalent and CKD stages 3-5 in the aggregate analysis for central retinal arteriolar relative risk (0.98, 95% confidence interval 0.94-1.03); venular equivalent (0.99, 0.95- 1.04) or individual participant central retinal arteriolar (0.99, 0.95-1.04) or venular equivalent (1.01, 0.97-1.05). Thus, meta-analysis provided little evidence to suggest that cross sectional direct measurements of retinal vascular caliber was associated with CKD stages 3-5 in the general population. Hence, meta-analyses of longitudinal studies evaluating the association between retinal parameters and CKD stages 3-5 may be warranted.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole Blood DNA Methylation Signatures of Diet Are Associated With Cardiovascular Disease Risk Factors and All-Cause Mortality. - Ma, Jiantao; Rebholz, Casey M; Braun, Kim V E; Reynolds, Lindsay M; Aslibekyan, Stella; Xia, Rui; Biligowda, Niranjan G; Huan, Tianxiao; Liu, Chunyu; Mendelson, Michael M; Joehanes, Roby; Hu, Emily A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: DNA methylation patterns associated with habitual diet have not been well studied. METHODS: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healthy Eating Index score. We conducted ethnicity-specific and trans-ethnic epigenome-wide association analyses for diet quality and leukocyte-derived DNA methylation at over 400 000 CpGs (cytosine-guanine dinucleotides) in 5 population-based cohorts including 6662 European ancestry, 2702 African ancestry, and 360 Hispanic ancestry participants. For diet-associated CpGs identified in epigenome-wide analyses, we conducted Mendelian randomization (MR) analysis to examine their relations to cardiovascular disease risk factors and examined their longitudinal associations with all-cause mortality. RESULTS: We identified 30 CpGs associated with either Mediterranean-style diet score or Alternative Healthy Eating Index, or both, in European ancestry participants. Among these CpGs, 12 CpGs were significantly associated with all-cause mortality (Bonferroni corrected <1.6×10). Hypermethylation of cg18181703 () was associated with higher scores of both Mediterranean-style diet score and Alternative Healthy Eating Index and lower risk for all-cause mortality (=5.7×10). Ten additional diet-associated CpGs were nominally associated with all-cause mortality (<0.05). MR analysis revealed 8 putatively causal associations for 6 CpGs with 4 cardiovascular disease risk factors (body mass index, triglycerides, high-density lipoprotein cholesterol concentrations, and type 2 diabetes mellitus; Bonferroni corrected MR <4.5×10). For example, hypermethylation of cg11250194 () was associated with lower triglyceride concentrations (MR, =1.5×10).and hypermethylation of cg02079413 (; ) was associated with body mass index (corrected MR, =1×10). CONCLUSIONS: Habitual diet quality was associated with differential peripheral leukocyte DNA methylation levels of 30 CpGs, most of which were also associated with multiple health outcomes, in European ancestry individuals. These findings demonstrate that integrative genomic analysis of dietary information may reveal molecular targets for disease prevention and treatment.

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

{Association between ABO haplotypes and the risk of venous thrombosis: impact on disease risk estimation - Goumidi, L.; Thibord, F.; Wiggins, K. L.; Li-Gao, R.; Brown, M. R.; van Hylckama Vlieg, A.; Souto, J. C.; Soria, J. M.; Ibrahim-Kosta, M.; Saut, N.; Daian, D.; Olaso, R.; et al. (Blood, 2021)
10.1182/blood.2020008997Genetic risk score (GRS) analysis is a popular approach to derive individual risk prediction models for complex diseases. In venous thrombosis (VT), such type of analysis shall integrate information at the ABO blood group locus, which is one of the major susceptibility loci. However, there is no consensus about which single nucleotide polymorphisms (SNPs) must be investigated when properly assessing association between ABO locus and VT risk. Using comprehensive haplotype analyses of ABO blood group tagging SNPs in 5425 cases and 8445 controls from 6 studies, we demonstrate that using only rs8176719 (tagging O1) to correctly assess the impact of ABO locus on VT risk is suboptimal, because 5% of rs8176719-delG carriers do not have an increased risk of developing VT. Instead, we recommend the use of 4 SNPs, rs2519093 (tagging A1), rs1053878 (A2), rs8176743 (B), and rs41302905 (O2), when assessing the impact of ABO locus on VT risk to avoid any risk misestimation. Compared with the O1 haplotype, the A2 haplotype is associated with a modest increase in VT risk (odds ratio, ∼1.2), the A1 and B haplotypes are associated with an ∼1.8-fold increased risk, whereas the O2 haplotype tends to be slightly protective (odds ratio, ∼0.80). In addition, although the A1 and B blood groups are associated with increased von Willebrand factor and factor VIII plasma levels, only the A1 blood group is associated with ICAM levels, but in an opposite direction, leaving additional avenues to be explored to fully understand the spectrum of biological effects mediated by ABO locus on cardiovascular traits.

Association Between Myocardial Strain and Frailty in CHS. - Tan, Annabel X; Shah, Sanjiv J; Sanders, Jason L; Psaty, Bruce M; Wu, Chenkai; Gardin, Julius M; Peralta, Carmen A; Newman, Anne B; Odden, Michelle C (Circ Cardiovasc Imaging, 2021)
BACKGROUND: Myocardial strain, measured by speckle-tracking echocardiography, is a novel measure of subclinical cardiovascular disease and may reflect myocardial aging. We evaluated the association between myocardial strain and frailty-a clinical syndrome of lack of physiological reserve. METHODS: Frailty was defined in participants of the CHS (Cardiovascular Health Study) as having ≥3 of the following clinical criteria: weakness, slowness, weight loss, exhaustion, and inactivity. Using speckle-tracking echocardiography data, we examined the cross-sectional (n=3206) and longitudinal (n=1431) associations with frailty among participants who had at least 1 measure of myocardial strain, left ventricular longitudinal strain (LVLS), left ventricular early diastolic strain rate and left atrial reservoir strain, and no history of cardiovascular disease or heart failure at the time of echocardiography. RESULTS: In cross-sectional analyses, lower (worse) LVLS was associated with prevalent frailty; this association was robust to adjustment for left ventricular ejection fraction (adjusted odds ratio, 1.32 [95% CI, 1.07-1.61] per 1-SD lower strain; =0.007) and left ventricular stroke volume (adjusted OR, 1.32 [95% CI, 1.08-1.61] per 1-SD lower strain; =0.007). In longitudinal analyses, adjusted associations of LVLS and left ventricular early diastolic strain with incident frailty were 1.35 ([95% CI, 0.96-1.89] =0.086) and 1.58 ([95% CI, 1.11-2.27] =0.013, respectively). Participants who were frail and had the worst LVLS had a 2.2-fold increased risk of death (hazard ratio, 2.20 [95% CI, 1.81-2.66]; <0.0001). CONCLUSIONS: In community-dwelling older adults without prevalent cardiovascular disease, worse LVLS by speckle-tracking echocardiography, reflective of subclinical myocardial dysfunction, was associated with frailty. Frailty and LVLS have an additive effect on mortality risk.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of mitochondrial DNA copy number with cardiometabolic diseases. - Liu, Xue; Longchamps, Ryan J; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Blackwell, Thomas W; Yao, Jie; Guo, Xiuqing; Kurniansyah, Nuzulul; Thyagarajan, Bharat; et al. (Cell Genom, 2021)
Mitochondrial DNA (mtDNA) is present in multiple copies in human cells. We evaluated cross-sectional associations of whole blood mtDNA copy number (CN) with several cardiometabolic disease traits in 408,361 participants of multiple ancestries in TOPMed and UK Biobank. Age showed a threshold association with mtDNA CN: among younger participants (<65 years of age), each additional 10 years of age was associated with 0.03 standard deviation (s.d.) higher level of mtDNA CN ( = 0.0014) versus a 0.14 s.d. lower level of mtDNA CN ( = 1.82 × 10) among older participants (≥65 years). At lower mtDNA CN levels, we found age-independent associations with increased odds of obesity ( = 5.6 × 10), hypertension ( = 2.8 × 10), diabetes ( = 3.6 × 10), and hyperlipidemia ( = 6.3 × 10). The observed decline in mtDNA CN after 65 years of age may be a key to understanding age-related diseases.

Association of mitochondrial variants and haplogroups identified by whole exome sequencing with Alzheimer's disease. - Zhang, Xiaoling; Farrell, John J; Tong, Tong; Hu, Junming; Zhu, Congcong; Wang, Li-San; Mayeux, Richard; Haines, Jonathan L; Pericak-Vance, Margaret A; Schellenberg, Gerard D; Lunetta, Kathryn L; Farrer, Lindsay A (Alzheimers Dement, 2021)
INTRODUCTION: Findings regarding the association between mitochondrial DNA (mtDNA) variants and Alzheimer's disease (AD) are inconsistent. METHODS: We developed a pipeline for accurate assembly and variant calling in mitochondrial genomes embedded within whole exome sequences (WES) from 10,831 participants from the Alzheimer's Disease Sequencing Project (ADSP). Association of AD risk was evaluated with each mtDNA variant and variants located in 1158 nuclear genes related to mitochondrial function using the SCORE test. Gene-based tests were performed using SKAT-O. RESULTS: Analysis of 4220 mtDNA variants revealed study-wide significant association of AD with a rare MT-ND4L missense variant (rs28709356; minor allele frequency = 0.002; P = 7.3 × 10 ) as well as with MT-ND4L in a gene-based test (P = 6.71 × 10 ). Significant association was also observed with a MT-related nuclear gene, TAMM41, in a gene-based test (P = 2.7 × 10 ). The expression of TAMM41 was lower in AD cases than controls (P = .00046) or mild cognitive impairment cases (P = .03). DISCUSSION: Significant findings in MT-ND4L and TAMM41 provide evidence for a role of mitochondria in AD.

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Cognitive decline in older adults with epilepsy: The Cardiovascular Health Study. - Choi, Hyunmi; Thacker, Evan L; Longstreth, William T; Elkind, Mitchell S V; Boehme, Amelia K (Epilepsia, 2021)
OBJECTIVE: Cognitive decline is a major concern for older adults with epilepsy. Whether and how much faster older adults with epilepsy experience cognitive decline beyond expected age-related cognitive change remain unclear. We sought to estimate and compare rates of cognitive decline in older adults with and without epilepsy. METHODS: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5888 US adults aged 65+. Cognitive function was assessed annually with Modified Mini-Mental State Exam (3MS) and Digit Symbol Substitution Test (DSST). We used linear mixed models to estimate average rates of decline in 3MS and DSST scores by epilepsy status (prevalent, incident, or no epilepsy), adjusted for risk factors associated with cognitive decline. RESULTS: The rate of decline in 3MS was significantly faster in prevalent epilepsy (P < .001) and after incident epilepsy (P = .002) compared with no epilepsy. Prevalent epilepsy and apolipoprotein E gene (APOE) ε4 (ApoE4) had a synergistic interaction, whereby prevalent epilepsy and ApoE4 together were associated with 1.51 points faster annual decline in 3MS than would be expected if prevalent epilepsy and ApoE4 did not interact (P < .001). Older adults with prevalent epilepsy had a significantly lower initial DSST score and faster rate of decline compared to those with no epilepsy (P < .001). SIGNIFICANCE: Faster decline in global cognitive ability seen in this study validates concerns of patients. ApoE4 allele status was an effect modifier of the relationship between cognitive decline and prevalent epilepsy. Further research is warranted to explore biological mechanisms and possible interventions to mitigate cognitive decline.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Egg consumption, overall diet quality, and risk of type 2 diabetes and coronary heart disease: A pooling project of US prospective cohorts. - Djoussé, Luc; Zhou, Guohai; McClelland, Robyn L; Ma, Nanxun; Zhou, Xia; Kabagambe, Edmond K; Talegawkar, Sameera A; Judd, Suzanne E; Biggs, Mary L; Fitzpatrick, Annette L; Clark, Cheryl R; Gagnon, David R; et al. (Clin Nutr, 2021)
BACKGROUND AND AIMS: Data on the relation of egg consumption with risk of type 2 diabetes (T2D) and coronary heart disease (CHD) are limited and inconsistent. Few studies have controlled for overall dietary patterns in egg-T2D or egg-CHD analyses, and it is unclear whether any observed elevated risks of T2D and CHD with frequent egg consumption is real or due to confounding by dietary habits. We tested the hypothesis that frequent egg consumption is associated with a higher risk of T2D and CHD risk after adjustment for overall dietary patterns among adults. DESIGN: We used prospective cohort design to complete time-to-event analyses. METHODS: We pooled de novo, harmonized, individual-level analyses from nine US cohorts (n = 103,811). Cox regression was used to estimate hazard ratios separately in each cohort adjusting for age, ethnicity, body mass index (BMI), exercise, smoking, alcohol intake, and dietary patterns. We pooled cohort-specific results using an inverse-variance weighted method to estimate summary relative risks. RESULTS: Median age ranged from 25 to 72 years. Median egg consumption was 1 egg per week in most of the cohorts. While egg consumption up to one per week was not associated with T2D risk, consumption of ≥2 eggs per week was associated with elevated risk [27% elevated risk of T2D comparing 7+ eggs/week with none (95% CI: 16%-37%)]. There was little evidence for heterogeneity across cohorts and we observed similar conclusions when stratified by BMI. Overall, egg consumption was not associated with the risk of CHD. However, in a sensitivity analysis, there was a 30% higher risk of CHD (95% CI: 3%-56%) restricted to older adults consuming 5-6 eggs/week. CONCLUSIONS: Our data showed an elevated risk of T2D with egg consumption of ≥2 eggs per week but not with <2 eggs/week. While there was no overall association of egg consumption with CHD risk, the elevated CHD observed with consumption of 5-6 eggs/week in older cohorts merits further investigation.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Eggs; Humans; Middle Aged; Prospective Studies; Risk Factors; United States

Epigenetic Age and the Risk of Incident Atrial Fibrillation. - Roberts, Jason D; Vittinghoff, Eric; Lu, Ake T; Alonso, Alvaro; Wang, Biqi; Sitlani, Colleen M; Mohammadi-Shemirani, Pedrum; Fornage, Myriam; Kornej, Jelena; Brody, Jennifer A; Arking, Dan E; Lin, Honghuang; et al. (Circulation, 2021)
BACKGROUND: The most prominent risk factor for atrial fibrillation (AF) is chronological age; however, underlying mechanisms are unexplained. Algorithms using epigenetic modifications to the human genome effectively predict chronological age. Chronological and epigenetic predicted ages may diverge in a phenomenon referred to as epigenetic age acceleration (EAA), which may reflect accelerated biological aging. We sought to evaluate for associations between epigenetic age measures and incident AF. METHODS: Measures for 4 epigenetic clocks (Horvath, Hannum, DNA methylation [DNAm] PhenoAge, and DNAm GrimAge) and an epigenetic predictor of PAI-1 (plasminogen activator inhibitor-1) levels (ie, DNAm PAI-1) were determined for study participants from 3 population-based cohort studies. Cox models evaluated for associations with incident AF and results were combined via random-effects meta-analyses. Two-sample summary-level Mendelian randomization analyses evaluated for associations between genetic instruments of the EAA measures and AF. RESULTS: Among 5600 participants (mean age, 65.5 years; female, 60.1%; Black, 50.7%), there were 905 incident AF cases during a mean follow-up of 12.9 years. Unadjusted analyses revealed all 4 epigenetic clocks and the DNAm PAI-1 predictor were associated with statistically significant higher hazards of incident AF, though the magnitudes of their point estimates were smaller relative to the associations observed for chronological age. The pooled EAA estimates for each epigenetic measure, with the exception of Horvath EAA, were associated with incident AF in models adjusted for chronological age, race, sex, and smoking variables. After multivariable adjustment for additional known AF risk factors that could also potentially function as mediators, pooled EAA measures for 2 clocks remained statistically significant. Five-year increases in EAA measures for DNAm GrimAge and DNAm PhenoAge were associated with 19% (adjusted hazard ratio [HR], 1.19 [95% CI, 1.09-1.31]; <0.01) and 15% (adjusted HR, 1.15 [95% CI, 1.05-1.25]; <0.01) higher hazards of incident AF, respectively. Mendelian randomization analyses for the 5 EAA measures did not reveal statistically significant associations with AF. CONCLUSIONS: Our study identified adjusted associations between EAA measures and incident AF, suggesting that biological aging plays an important role independent of chronological age, though a potential underlying causal relationship remains unclear. These aging processes may be modifiable and not constrained by the immutable factor of time.
Keywords: Aged; Aging; Atrial Fibrillation; DNA Methylation; Epigenesis, Genetic; Epigenomics; Female; Follow-Up Studies; Humans; Incidence; Male; Mendelian Randomization Analysis; Middle Aged; Models, Cardiovascular; Models, Genetic

{Epigenome-wide association meta-analysis of DNA methylation with coffee and tea consumption - Karabegović, I.; Portilla-Fernandez, E.; Li, Y.; Ma, J.; Maas, S. C. E.; Sun, D.; Hu, E. A.; Kühnel, B.; Zhang, Y.; Ambatipudi, S.; Fiorito, G.; Huang, J.; et al. (Nat Commun, 2021)
10.1038/s41467-021-22752-6Coffee and tea are extensively consumed beverages worldwide which have received considerable attention regarding health. Intake of these beverages is consistently linked to, among others, reduced risk of diabetes and liver diseases; however, the mechanisms of action remain elusive. Epigenetics is suggested as a mechanism mediating the effects of dietary and lifestyle factors on disease onset. Here we report the results from epigenome-wide association studies (EWAS) on coffee and tea consumption in 15,789 participants of European and African-American ancestries from 15 cohorts. EWAS meta-analysis of coffee consumption reveals 11 CpGs surpassing the epigenome-wide significance threshold (P-value <1.1×10-7), which annotated to the AHRR, F2RL3, FLJ43663, HDAC4, GFI1 and PHGDH genes. Among them, cg14476101 is significantly associated with expression of the PHGDH and risk of fatty liver disease. Knockdown of PHGDH expression in liver cells shows a correlation with expression levels of genes associated with circulating lipids, suggesting a role of PHGDH in hepatic-lipid metabolism. EWAS meta-analysis on tea consumption reveals no significant association, only two CpGs annotated to CACNA1A and PRDM16 genes show suggestive association (P-value <5.0×10-6). These findings indicate that coffee-associated changes in DNA methylation levels may explain the mechanism of action of coffee consumption in conferring risk of diseases.

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

Estimating Systolic Blood Pressure Intervention Trial Participant Posttrial Survival Using Pooled Epidemiologic Cohort Data. - Bellows, Brandon K; Zhang, Yiyi; Zhang, Zugui; Lloyd-Jones, Donald M; Bress, Adam P; King, Jordan B; Kolm, Paul; Cushman, William C; Johnson, Karen C; Tamariz, Leonardo; Oelsner, Elizabeth C; Shea, Steven; et al. (J Am Heart Assoc, 2021)
Background Intensive systolic blood pressure treatment (<120 mm Hg) in SPRINT (Systolic Blood Pressure Intervention Trial) improved survival compared with standard treatment (<140 mm Hg) over a median follow-up of 3.3 years. We projected life expectancy after observed follow-up in SPRINT using SPRINT-eligible participants in the NHLBI-PCS (National Heart, Lung, and Blood Institute Pooled Cohorts Study). Methods and Results We used propensity scores to weight SPRINT-eligible NHLBI-PCS participants to resemble SPRINT participants. In SPRINT participants, we estimated in-trial survival (<4 years) using a time-based flexible parametric survival model. In SPRINT-eligible NHLBI-PCS participants, we estimated posttrial survival (≥4 years) using an age-based flexible parametric survival model and applied the formula to SPRINT participants to predict posttrial survival. We projected overall life expectancy for each SPRINT participant and compared it to parametric regression (eg, Gompertz) projections based on SPRINT data alone. We included 8584 SPRINT and 10 593 SPRINT-eligible NHLBI-PCS participants. After propensity weighting, mean (SD) age was 67.9 (9.4) and 68.2 (8.8) years, and 35.5% and 37.6% were women in SPRINT and NHLBI-PCS, respectively. Using the NHLBI-PCS-based method, projected mean life expectancy from randomization was 21.0 (7.4) years with intensive and 19.1 (7.2) years with standard treatment. Using the Gompertz regression, life expectancy was 11.2 (2.3) years with intensive and 10.5 (2.2) years with standard treatment. Conclusions Combining SPRINT and NHLBI-PCS observed data likely offers a more realistic estimate of life expectancy than parametrically extrapolating SPRINT data alone. These results offer insight into the potential long-term effectiveness of intensive SBP goals.

FGL1 as a modulator of plasma D-dimer levels: Exome-wide marker analysis of plasma tPA, PAI-1, and D-dimer. - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A T; Chen, Ming-Huei; O'Donnell, Christopher J; Kleber, Marcus E; Delgado, Graciela E; Guo, Xiuqing; Yao, Jie; Taylor, Kent D; Ozel, Ayse Bilge; et al. (J Thromb Haemost, 2021)
BACKGROUND: Use of targeted exome-arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator-inhibitor 1 (PAI-1), tissue plasminogen activator (tPA), and the plasma product D-dimer are important components of the fibrinolytic system. There have been few large-scale genome-wide or exome-wide studies of PAI-1, tPA, and D-dimer. OBJECTIVES: We sought to discover new genetic loci contributing to variation in these traits using an exome-array approach. METHODS: Cohort-level analyses and fixed effects meta-analyses of PAI-1 (n = 15 603), tPA (n = 6876,) and D-dimer (n = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single-variant analyses and gene-based burden testing. RESULTS: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D-dimer levels, achieved genome-wide significance (P < 5 × 10 ). Replication was sought for these 5 variants, as well as 45 well-imputed variants with P < 1 × 10 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen-like-1) with increased plasma D-dimer levels. Additionally, a candidate-gene approach revealed a suggestive association for a coding variant (rs143202684-C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830-A) in SCARB1 associated with increased D-dimer levels. CONCLUSION: This work provides new evidence for a role of FGL1 in hemostasis.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

{Genome-Wide Association Study of Circulating Interleukin 6 Levels Identifies Novel Loci - Ahluwalia, T. S.; Prins, B. P.; Abdollahi, M.; Armstrong, N. J.; Aslibekyan, S.; Bain, L.; Jefferis, B.; Baumert, J.; Beekman, M.; Ben-Shlomo, Y.; Bis, J. C.; Mitchell, B. D.; et al. (Hum Mol Genet, 2021)
Interleukin-6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery, and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed-effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on Chromosome (Chr) 2q14, (pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.

{Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Jones, G.; Trajanoska, K.; Santanasto, A. J.; Stringa, N.; Kuo, C. L.; Atkins, J. L.; Lewis, J. R.; Duong, T.; Hong, S.; Biggs, M. L.; Luan, J.; Sarnowski, C.; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10-17), arthritis (GDF5 p = 4 × 10-13), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.

{The genomics of heart failure: design and rationale of the HERMES consortium - Lumbers, R. T.; Shah, S.; Lin, H.; Czuba, T.; Henry, A.; Swerdlow, D. I.; Malarstig, A.; Andersson, C.; Verweij, N.; Holmes, M. V.; Ärnlöv, J.; Svensson, P.; et al. (ESC Heart Fail, 2021)
The HERMES (HEart failure Molecular Epidemiology for Therapeutic targetS) consortium aims to identify the genomic and molecular basis of heart failure.\ under an additive genetic model.\ HERMES is a global collaboration aiming to (i) identify the genetic determinants of heart failure; (ii) generate insights into the causal pathways leading to heart failure and enable genetic approaches to target prioritization; and (iii) develop genomic tools for disease stratification and risk prediction.

Hemostatic factor levels and cognitive decline in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (J Thromb Haemost, 2021)
BACKGROUND: Hemostasis is a key factor in cerebrovascular disease, but the association of hemostatic factors with cognitive decline is unclear. OBJECTIVE: To prospectively evaluate associations of 20 hemostatic factor levels with changes in cognition during ≥8 years of follow-up in the Cardiovascular Health Study (CHS) of older adults. METHODS: We included participants of an existing CHS cross-sectional substudy (n = 400) with hemostatic factors measured in 1989-1990. Between 1989-1990 and 1998-1999, cognitive function was measured using the Modified Mini-Mental State Examination (3MSE) and Digit Symbol Substitution Tests. Mixed-effects linear regression models estimated change in cognitive function over time, adjusting for sociodemographic and clinical factors and APOE genotype, using Bonferroni adjustment. We also derived principal components to account for the interrelationship among factors. RESULTS: Of 20 factors evaluated individually, only higher levels of plasmin-α -antiplasmin complex (PAP), tissue factor pathway inhibitor (TFPI), and lower factor X (FXc) levels were associated with faster cognitive decline, estimated by annual change in 3MSE points (1 standard deviation PAP β = -0.65, 95% confidence interval [CI]: -1.08 to -0.21; TFPI β = -0.55, 95% CI: -0.90 to -0.19; FXc β = 0.52, 95% CI: 0.21-0.84). One of four principal components, loading positively on D-dimer, prothrombin fragment 1.2 (F1.2), and PAP was significantly associated with change in 3MSE. CONCLUSIONS: Levels of PAP, TPFI, and FXc and a combination of factors driven by PAP, D-dimer, and F1.2 were associated with cognitive decline. Whether these findings can be used to improve dementia prevention or prediction requires further study.

Identification of Functional Genetic Determinants of Cardiac Troponin T and I in a Multiethnic Population and Causal Associations With Atrial Fibrillation. - Yang, Yunju; Bartz, Traci M; Brown, Michael R; Guo, Xiuqing; Zilhão, Nuno R; Trompet, Stella; Weiss, Stefan; Yao, Jie; Brody, Jennifer A; deFilippi, Christopher R; Hoogeveen, Ron C; Lin, Henry J; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Elevated cardiac troponin levels in blood are associated with increased risk of cardiovascular diseases and mortality. Cardiac troponin levels are heritable, but their genetic architecture remains elusive. METHODS: We conducted a transethnic genome-wide association analysis on high-sensitivity cTnT (cardiac troponin T; hs-cTnT) and high-sensitivity cTnI (cardiac troponin I; hs-cTnI) levels in 24 617 and 14 336 participants free of coronary heart disease and heart failure from 6 population-based cohorts, followed by a series of bioinformatic analyses to decipher the genetic architecture of hs-cTnT and hs-cTnI. RESULTS: We identified 4 genome-wide significant loci for hs-cTnT including a novel locus rs3737882 in and 3 previously reported loci at , , and . One known locus at was replicated for hs-cTnI. One copy of C allele for rs3737882 was associated with a 6% increase in hs-cTnT levels (minor allele frequency, 0.18; =2.80×10). We observed pleiotropic loci located at and . The proportions of variances explained by single-nucleotide polymorphisms were 10.15% and 7.74% for hs-cTnT and hs-cTnI, respectively. Single-nucleotide polymorphisms were colocalized with expression in heart tissues and hs-cTnT and with expression in artery, heart tissues, and whole blood and both troponins. Mendelian randomization analyses showed that genetically increased hs-cTnT and hs-cTnI levels were associated with higher odds of atrial fibrillation (odds ratio, 1.38 [95% CI, 1.25-1.54] for hs-cTnT and 1.21 [95% CI, 1.06-1.37] for hs-cTnI). CONCLUSIONS: We identified a novel genetic locus associated with hs-cTnT in a multiethnic population and found that genetically regulated troponin levels were associated with atrial fibrillation.

Identification of novel and rare variants associated with handgrip strength using whole genome sequence data from the NHLBI Trans-Omics in Precision Medicine (TOPMed) Program. - Sarnowski, Chloe; Chen, Han; Biggs, Mary L; Wassertheil-Smoller, Sylvia; Bressler, Jan; Irvin, Marguerite R; Ryan, Kathleen A; Karasik, David; Arnett, Donna K; Cupples, L Adrienne; Fardo, David W; Gogarten, Stephanie M; et al. (PLoS One, 2021)
Handgrip strength is a widely used measure of muscle strength and a predictor of a range of morbidities including cardiovascular diseases and all-cause mortality. Previous genome-wide association studies of handgrip strength have focused on common variants primarily in persons of European descent. We aimed to identify rare and ancestry-specific genetic variants associated with handgrip strength by conducting whole-genome sequence association analyses using 13,552 participants from six studies representing diverse population groups from the Trans-Omics in Precision Medicine (TOPMed) Program. By leveraging multiple handgrip strength measures performed in study participants over time, we increased our effective sample size by 7-12%. Single-variant analyses identified ten handgrip strength loci among African-Americans: four rare variants, five low-frequency variants, and one common variant. One significant and four suggestive genes were identified associated with handgrip strength when aggregating rare and functional variants; all associations were ancestry-specific. We additionally leveraged the different ancestries available in the UK Biobank to further explore the ancestry-specific association signals from the single-variant association analyses. In conclusion, our study identified 11 new loci associated with handgrip strength with rare and/or ancestry-specific genetic variations, highlighting the added value of whole-genome sequencing in diverse samples. Several of the associations identified using single-variant or aggregate analyses lie in genes with a function relevant to the brain or muscle or were reported to be associated with muscle or age-related traits. Further studies in samples with sequence data and diverse ancestries are needed to confirm these findings.

Identification of putative causal loci in whole-genome sequencing data via knockoff statistics. - He, Zihuai; Liu, Linxi; Wang, Chen; Le Guen, Yann; Lee, Justin; Gogarten, Stephanie; Lu, Fred; Montgomery, Stephen; Tang, Hua; Silverman, Edwin K; Cho, Michael H; Greicius, Michael; et al. (Nat Commun, 2021)
The analysis of whole-genome sequencing studies is challenging due to the large number of rare variants in noncoding regions and the lack of natural units for testing. We propose a statistical method to detect and localize rare and common risk variants in whole-genome sequencing studies based on a recently developed knockoff framework. It can (1) prioritize causal variants over associations due to linkage disequilibrium thereby improving interpretability; (2) help distinguish the signal due to rare variants from shadow effects of significant common variants nearby; (3) integrate multiple knockoffs for improved power, stability, and reproducibility; and (4) flexibly incorporate state-of-the-art and future association tests to achieve the benefits proposed here. In applications to whole-genome sequencing data from the Alzheimer's Disease Sequencing Project (ADSP) and COPDGene samples from NHLBI Trans-Omics for Precision Medicine (TOPMed) Program we show that our method compared with conventional association tests can lead to substantially more discoveries.
Keywords: Algorithms; Causality; Computer Simulation; Data Interpretation, Statistical; Datasets as Topic; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Markov Chains; Models, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Whole Genome Sequencing

Individual non-esterified fatty acids and incident atrial fibrillation late in life. - Pellegrini, Cara N; Bůzková, Petra; Lichtenstein, Alice H; Matthan, Nirupa R; Ix, Joachim H; Siscovick, David S; Heckbert, Susan R; Tracy, Russell P; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R (Heart, 2021)
OBJECTIVE: Obesity and dysmetabolism are major risk factors for atrial fibrillation (AF). Expansion of fat depots is associated with increased circulating total non-esterified fatty acids (NEFAs), elevated levels of which are associated with incident AF. We undertook comprehensive serum measurement of individual NEFA to identify specific associations with new-onset AF late in life. METHODS: The present study focused on participants with available serum and free of AF selected from the Cardiovascular Health Study, a community-based longitudinal investigation of older US adults. Thirty-five individual NEFAs were measured by gas chromatography. Cox regression was used to evaluate the association of individual NEFAs with incident AF. RESULTS: The study sample included 1872 participants (age 77.7±4.4). During median follow-up of 11.3 years, 715 cases of incident AF occurred. After concurrent adjustment of all NEFAs and full adjustment for potential confounders, higher serum concentration of nervonic acid (24:1 n-9), a long-chain monounsaturated fatty acid, was associated with higher risk of AF (HR per SD: 1.18, 95% CI 1.08 to 1.29; p<0.001). Conversely, higher serum concentration of gamma-linolenic acid (GLA) (18:3 n-6), a polyunsaturated n-6 fatty acid, was associated with lower risk of AF (HR per SD: 0.81, 95% CI 0.71 to 0.94; p=0.004). None of the remaining NEFAs was significantly associated with AF. CONCLUSIONS: Among older adults, serum levels of non-esterified nervonic acid were positively associated, while serum levels of non-esterified GLA were inversely associated, with incident AF. If confirmed, these results could offer new strategies for AF prevention and early intervention in this segment of the population at highest risk.

Longitudinal Plasma Measures of Trimethylamine N-Oxide and Risk of Atherosclerotic Cardiovascular Disease Events in Community-Based Older Adults. - Lee, Yujin; Nemet, Ina; Wang, Zeneng; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda M; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (J Am Heart Assoc, 2021)
Background Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of dietary choline, L-carnitine, and phosphatidylcholine-rich foods. On the basis of experimental studies and patients with prevalent disease, elevated plasma TMAO may increase risk of atherosclerotic cardiovascular disease (ASCVD). TMAO is also renally cleared and may interact with and causally contribute to renal dysfunction. Yet, how serial TMAO levels relate to incident and recurrent ASCVD in community-based populations and the potential mediating or modifying role of renal function are not established. Methods and Results We investigated associations of serial measures of plasma TMAO, assessed at baseline and 7 years, with incident and recurrent ASCVD in a community-based cohort of 4131 (incident) and 1449 (recurrent) older US adults. TMAO was measured using stable isotope dilution liquid chromatography-tandem mass spectrometry (laboratory coefficient of variation, <6%). Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, sudden cardiac death, or other atherosclerotic death) was centrally adjudicated using medical records. Risk was assessed by multivariable Cox proportional hazards regression, including time-varying demographics, lifestyle factors, medical history, laboratory measures, and dietary habits. Potential mediating effects and interaction by estimated glomerular filtration rate (eGFR) were assessed. During prospective follow-up, 1766 incident and 897 recurrent ASCVD events occurred. After multivariable adjustment, higher levels of TMAO were associated with a higher risk of incident ASCVD, with extreme quintile hazard ratio (HR) compared with the lowest quintile=1.21 (95% CI, 1.02-1.42; -trend=0.029). This relationship appeared mediated or confounded by eGFR (eGFR-adjusted HR, 1.07; 95% CI, 0.90-1.27), as well as modified by eGFR (-interaction <0.001). High levels of TMAO were associated with higher incidence of ASCVD in the presence of impaired renal function (eGFR <60 mL/min per 1.73 m: HR, 1.56 [95% CI, 1.13-2.14]; -trend=0.007), but not normal or mildly reduced renal function (eGFR ≥60 mL/min per 1.73 m: HR, 1.03 [95% CI, 0.85-1.25]; -trend=0.668). Among individuals with prior ASCVD, TMAO associated with higher risk of recurrent ASCVD (HR, 1.25 [95% CI, 1.01-1.56]; -trend=0.009), without significant modification by eGFR. Conclusions In this large community-based cohort of older US adults, serial measures of TMAO were associated with higher risk of incident ASCVD, with apparent modification by presence of impaired renal function and with higher risk of recurrent ASCVD.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Meta-analysis of epigenome-wide association studies of carotid intima-media thickness. - Portilla-Fernández, Eliana; Hwang, Shih-Jen; Wilson, Rory; Maddock, Jane; Hill, W David; Teumer, Alexander; Mishra, Pashupati P; Brody, Jennifer A; Joehanes, Roby; Ligthart, Symen; Ghanbari, Mohsen; Kavousi, Maryam; et al. (Eur J Epidemiol, 2021)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = -0.0264, p value = 3.5 × 10) in the discovery panel and was replicated in replication panel (beta = -0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

{A multi-ethnic epigenome-wide association study of leukocyte DNA methylation and blood lipids - Jhun, M. A.; Mendelson, M.; Wilson, R.; Gondalia, R.; Joehanes, R.; Salfati, E.; Zhao, X.; Braun, K. V. E.; Do, A. N.; Hedman, Å. K.; Zhang, T.; Carnero-Montoro, E.; et al. (Nat Commun, 2021)
10.1038/s41467-021-23899-yHere we examine the association between DNA methylation in circulating leukocytes and blood lipids in a multi-ethnic sample of 16,265 subjects. We identify 148, 35, and 4 novel associations among Europeans, African Americans, and Hispanics, respectively, and an additional 186 novel associations through a trans-ethnic meta-analysis. We observe a high concordance in the direction of effects across racial/ethnic groups, a high correlation of effect sizes between high-density lipoprotein and triglycerides, a modest overlap of associations with epigenome-wide association studies of other cardio-metabolic traits, and a largely non-overlap with lipid loci identified to date through genome-wide association studies. Thirty CpGs reached significance in at least 2 racial/ethnic groups including 7 that showed association with the expression of an annotated gene. CpGs annotated to CPT1A showed evidence of being influenced by triglycerides levels. DNA methylation levels of circulating leukocytes show robust and consistent association with blood lipid levels across multiple racial/ethnic groups.

Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes. - Lu, Yingchang; Dimitrov, Latchezar; Chen, Shyh-Huei; Bielak, Lawrence F; Bis, Joshua C; Feitosa, Mary F; Lu, Lingyi; Kavousi, Maryam; Raffield, Laura M; Smith, Albert V; Wang, Lihua; Weiss, Stefan; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease. Type 2 diabetes (T2D) is an independent cardiovascular disease risk factor that accelerates atherosclerosis. METHODS: We performed meta-analyses of genome-wide association studies in up to 2500 T2D individuals of European ancestry (EA) and 1590 T2D individuals of African ancestry with or without exclusion of prevalent cardiovascular disease, for CAC measured by cardiac computed tomography, and 3608 individuals of EA and 838 individuals of African ancestry with T2D for cIMT measured by ultrasonography within the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium. RESULTS: We replicated 2 loci (rs9369640 and rs9349379 near and rs10757278 near ) for CAC and one locus for cIMT (rs7412 and rs445925 near ) that were previously reported in the general EA populations. We identified one novel CAC locus (rs8000449 near at 13q13.3) at =2.0×10 in EA. No additional loci were identified with the meta-analyses of EA and African ancestry. The expression quantitative trait loci analysis with nearby expressed genes derived from arterial wall and metabolic tissues from the Genotype-Tissue Expression project pinpoints , encoding a matricellular protein involved in bone formation and bone matrix organization, as the potential candidate gene at this locus. In addition, we found significant associations (<3.1×10) for 3 previously reported coronary artery disease loci for these subclinical atherosclerotic phenotypes (rs2891168 near and rs11170820 near for CAC, and rs7412 near for cIMT). CONCLUSIONS: Our results provide potential biological mechanisms that could link CAC and cIMT to increased cardiovascular disease risk in individuals with T2D.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

n-3 Fatty Acid Biomarkers and Incident Type 2 Diabetes: An Individual Participant-Level Pooling Project of 20 Prospective Cohort Studies - Qian, F.; Ardisson Korat, A. V.; Imamura, F.; Marklund, M.; Tintle, N.; Virtanen, J. K.; Zhou, X.; Bassett, J. K.; Lai, H.; Hirakawa, Y.; Chien, K. L.; Wood, A. C.; et al. (Diabetes Care, 2021)
-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with T2D risk through an individual participant-level pooled analysis.\ For our analysis we incorporated data from a global consortium of 20 prospective studies from 14 countries. We included 65,147 participants who had blood measurements of ALA, EPA, DPA, or DHA and were free of diabetes at baseline. De novo harmonized analyses were performed in each cohort following a prespecified protocol, and cohort-specific associations were pooled using inverse variance-weighted meta-analysis.\ 0.001). ALA was not associated with T2D (HR 0.97 [95% CI 0.92, 1.02]) per interquintile range. Associations were robust across prespecified subgroups as well as in sensitivity analyses.\ Higher circulating biomarkers of seafood-derived n-3 fatty acids, including EPA, DPA, DHA, and their sum, were associated with lower risk of T2D in a global consortium of prospective studies. The biomarker of plant-derived ALA was not significantly associated with T2D risk.

Natural killer cells, gamma delta T cells and classical monocytes are associated with systolic blood pressure in the multi-ethnic study of atherosclerosis (MESA). - Delaney, Joseph A C; Olson, Nels C; Sitlani, Colleen M; Fohner, Alison E; Huber, Sally A; Landay, Alan L; Heckbert, Susan R; Tracy, Russell P; Psaty, Bruce M; Feinstein, Matt; Doyle, Margaret F (BMC Cardiovasc Disord, 2021)
BACKGROUND: Hypertension is a major source of cardiovascular morbidity and mortality. Recent evidence from mouse models, genetic, and cross-sectional human studies suggest increased proportions of selected immune cell subsets may be associated with levels of systolic blood pressure (SBP). METHODS: We assayed immune cells from cryopreserved samples collected at the baseline examination (2000-2002) from 1195 participants from the multi-ethnic study of atherosclerosis (MESA). We used linear mixed models, with adjustment for age, sex, race/ethnicity, smoking, exercise, body mass index, education, diabetes, and cytomegalovirus titers, to estimate the associations between 30 immune cell subsets (4 of which were a priori hypotheses) and repeated measures of SBP (baseline and up to four follow-up measures) over 10 years. The analysis provides estimates of the association with blood pressure level. RESULTS: The mean age of the MESA participants at baseline was 64 ± 10 years and 53% were male. A one standard deviation (1-SD) increment in the proportion of γδ T cells was associated with 2.40 mmHg [95% confidence interval (CI) 1.34-3.42] higher average systolic blood pressure; and for natural killer cells, a 1-SD increment was associated with 1.88 mmHg (95% CI 0.82-2.94) higher average level of systolic blood pressure. A 1-SD increment in classical monocytes (CD14CD16) was associated with 2.01 mmHG (95% CI 0.79-3.24) lower average systolic blood pressure. There were no associations of CD4 T helper cell subsets with average systolic blood pressure. CONCLUSION: These findings suggest that the innate immune system plays a role in levels of SBP whereas there were no associations with adaptive immune cells.

Ophthalmic conditions associated with dementia risk: The Cardiovascular Health Study. - Hwang, Phillip H; Longstreth, Will T; Thielke, Stephen M; Francis, Courtney E; Carone, Marco; Kuller, Lewis H; Fitzpatrick, Annette L (Alzheimers Dement, 2021)
INTRODUCTION: Ophthalmic conditions and dementia appear to overlap and may share common pathways, but research has not differentiated dementia subtypes. METHODS: Diagnoses of cataracts, age-related macular degeneration (AMD), diabetic retinopathy (DR), and glaucoma were based on medical histories and International Classification of Diseases, Ninth Revision (ICD-9) codes for 3375 participants from the Cardiovascular Health Study. Dementia, including Alzheimer's disease (AD) and vascular dementia (VaD), was classified using standardized research criteria. RESULTS: Cataracts were associated with AD (hazard ratio [HR] = 1.34; 95% confidence interval [CI] = 1.01-1.80) and VaD/mixed dementia (HR = 1.41; 95% CI = 1.02-1.95). AMD was associated with AD only (HR = 1.87; 95% CI = 1.13-3.09), whereas DR was associated with VaD/mixed dementia only (HR = 2.63; 95% CI = 1.10-6.27). DISCUSSION: Differential associations between specific ophthalmic conditions and dementia subtypes may elucidate pathophysiologic pathways. Lack of association between glaucoma and dementia was most surprising from these analyses.

The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction. - Trompet, Stella; Postmus, Iris; Warren, Helen R; Noordam, Raymond; Smit, Roelof A J; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I; Hitman, Graham A; Munroe, Patricia B; Rotter, Jerome I; et al. (Front Pharmacol, 2021)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been assessed in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigated whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with a fixed-effects model, inverse variance weighted meta-analysis. All SNPs with -values <5.0 × 10 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (eight studies, = 10,769, 4,212 cases), we observed no genome-wide significant results ( < 5.0 × 10). A total of 144 genetic variants were followed-up in the second stage (three studies, = 1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. It does not appear likely that genetic testing for predicting effects of statins on clinical events will become a useful tool in clinical practice.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

Sex Differences in Cognitive Decline Among US Adults. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Hingtgen, Stephanie; Elkind, Mitchell S V; Manly, Jennifer J; Gottesman, Rebecca F; et al. (JAMA Netw Open, 2021)
Importance: Sex differences in dementia risk are unclear, but some studies have found greater risk for women. Objective: To determine associations between sex and cognitive decline in order to better understand sex differences in dementia risk. Design, Setting, and Participants: This cohort study used pooled analysis of individual participant data from 5 cohort studies for years 1971 to 2017: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Linear mixed-effects models were used to estimate changes in each continuous cognitive outcome over time by sex. Data analysis was completed from March 2019 to October 2020. Exposure: Sex. Main Outcomes and Measures: The primary outcome was change in global cognition. Secondary outcomes were change in memory and executive function. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results: Among 34 349 participants, 26 088 who self-reported Black or White race, were free of stroke and dementia, and had covariate data at or before the first cognitive assessment were included for analysis. Median (interquartile range) follow-up was 7.9 (5.3-20.5) years. There were 11 775 (44.7%) men (median [interquartile range] age, 58 [51-66] years at first cognitive assessment; 2229 [18.9%] Black) and 14 313 women (median [interquartile range] age, 58 [51-67] years at first cognitive assessment; 3636 [25.4%] Black). Women had significantly higher baseline performance than men in global cognition (2.20 points higher; 95% CI, 2.04 to 2.35 points; P < .001), executive function (2.13 points higher; 95% CI, 1.98 to 2.29 points; P < .001), and memory (1.89 points higher; 95% CI, 1.72 to 2.06 points; P < .001). Compared with men, women had significantly faster declines in global cognition (-0.07 points/y faster; 95% CI, -0.08 to -0.05 points/y; P < .001) and executive function (-0.06 points/y faster; 95% CI, -0.07 to -0.05 points/y; P < .001). Men and women had similar declines in memory (-0.004 points/y faster; 95% CI, -0.023 to 0.014; P = .61). Conclusions and Relevance: The results of this cohort study suggest that women may have greater cognitive reserve but faster cognitive decline than men, which could contribute to sex differences in late-life dementia.
Keywords: Aged; Cognitive Dysfunction; Cognitive Reserve; Cohort Studies; Executive Function; Humans; Memory; Middle Aged; Risk; Sex Factors; Time Factors; United States

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Sugar-Sweetened Beverage Consumption May Modify Associations Between Genetic Variants in the CHREBP (Carbohydrate Responsive Element Binding Protein) Locus and HDL-C (High-Density Lipoprotein Cholesterol) and Triglyceride Concentrations. - Haslam, Danielle E; Peloso, Gina M; Guirette, Melanie; Imamura, Fumiaki; Bartz, Traci M; Pitsillides, Achilleas N; Wang, Carol A; Li-Gao, Ruifang; Westra, Jason M; Pitkänen, Niina; Young, Kristin L; Graff, Mariaelisa; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: ChREBP (carbohydrate responsive element binding protein) is a transcription factor that responds to sugar consumption. Sugar-sweetened beverage (SSB) consumption and genetic variants in the locus have separately been linked to HDL-C (high-density lipoprotein cholesterol) and triglyceride concentrations. We hypothesized that SSB consumption would modify the association between genetic variants in the locus and dyslipidemia. METHODS: Data from 11 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (N=63 599) and the UK Biobank (N=59 220) were used to quantify associations of SSB consumption, genetic variants, and their interaction on HDL-C and triglyceride concentrations using linear regression models. A total of 1606 single nucleotide polymorphisms within or near were considered. SSB consumption was estimated from validated questionnaires, and participants were grouped by their estimated intake. RESULTS: In a meta-analysis, rs71556729 was significantly associated with higher HDL-C concentrations only among the highest SSB consumers (β, 2.12 [95% CI, 1.16-3.07] mg/dL per allele; <0.0001), but not significantly among the lowest SSB consumers (=0.81; <0.0001). Similar results were observed for 2 additional variants (rs35709627 and rs71556736). For triglyceride, rs55673514 was positively associated with triglyceride concentrations only among the highest SSB consumers (β, 0.06 [95% CI, 0.02-0.09] ln-mg/dL per allele, =0.001) but not the lowest SSB consumers (=0.84; =0.0005). CONCLUSIONS: Our results identified genetic variants in the locus that may protect against SSB-associated reductions in HDL-C and other variants that may exacerbate SSB-associated increases in triglyceride concentrations. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00005133, NCT00005121, NCT00005487, and NCT00000479.

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

What Cut-Point in Gait Speed Best Discriminates Community-Dwelling Older Adults With Mobility Complaints From Those Without? A Pooled Analysis From the Sarcopenia Definitions and Outcomes Consortium. - Cawthon, Peggy M; Patel, Sheena M; Kritchevsky, Stephen B; Newman, Anne B; Santanasto, Adam; Kiel, Douglas P; Travison, Thomas G; Lane, Nancy; Cummings, Steven R; Orwoll, Eric S; Duchowny, Kate A; Kwok, Timothy; et al. (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Cut-points to define slow walking speed have largely been derived from expert opinion. METHODS: Study participants (13 589 men and 5043 women aged ≥65years) had walking speed (m/s) measured over 4-6 m (mean ± SD: 1.20 ± 0.27 m/s in men and 0.94 ± 0.24 m/s in women.) Mobility limitation was defined as any self-reported difficulty with walking approximately 1/4 mile (prevalence: 12.6% men, 26.4% women). Sex-stratified classification and regression tree (CART) models with 10-fold cross-validation identified walking speed cut-points that optimally discriminated those who reported mobility limitation from those who did not. RESULTS: Among 5043 women, CART analysis identified 2 cut-points, classifying 4144 (82.2%) with walking speed ≥0.75 m/s, which we labeled as "fast"; 478 (9.5%) as "intermediate" (walking speed ≥0.62 m/s but <0.75 m/s); and 421 (8.3%) as "slow" (walking speed <0.62 m/s). Among 13 589 men, CART analysis identified 3 cut-points, classifying 10 001 (73.6%) with walking speed ≥1.00 m/s ("very fast"); 2901 (21.3%) as "fast" (walking speed ≥0.74 m/s but <1.00 m/s); 497 (3.7%) as "intermediate" (walking speed ≥0.57 m/s but <0.74 m/s); and 190 (1.4%) as "slow" (walking speed <0.57 m/s). Prevalence of self-reported mobility limitation was lowest in the "fast" or "very fast" (11% for men and 19% for women) and highest in the "slow" (60.5% in men and 71.0% in women). Rounding the 2 slower cut-points to 0.60 m/s and 0.75 m/s reclassified very few participants. CONCLUSIONS: Cut-points in walking speed of approximately 0.60 m/s and 0.75 m/s discriminate those with self-reported mobility limitation from those without.
Keywords: Aged; Female; Gait; Humans; Independent Living; Male; Mobility Limitation; Sarcopenia; Walking; Walking Speed

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

The association of aortic valve sclerosis, aortic annulus increased reflectivity, and mitral annular calcification with subsequent aortic stenosis in older individuals. Findings from the Cardiovascular Health Study. - Barasch, Eddy; Gottdiener, John S; Tressel, William; Bartz, Traci M; Bůzková, Petra; Massera, Daniele; DeFilippi, Christopher; Biggs, Mary L; Psaty, Bruce M; Kizer, Jorge R; Owens, David (J Am Soc Echocardiogr, 2022)
BACKGROUND: While aortic valve sclerosis (AVS) is well-described as preceding aortic stenosis (AS), the association of AS with antecedent mitral aortic annular calcification and aortic annulus increased reflectivity (MAC and AAIR, respectively) has not been characterized. In a population-based prospective study, we evaluated whether MAC, AAIR, and AVS are associated with the risk of incident AS. METHODS: Among participants of the Cardiovascular Health Study (CHS) free of AS at the 1994-1995 visit, the presence of MAC, AAIR, AVS, and the combination of all three were evaluated in 3041 participants. Cox proportional hazards regression was used to assess the association between the presence of calcification and the incidence of moderate/severe AS in three nested models adjusting for factors associated with atherosclerosis and inflammation both relevant to the pathogenesis of AS. RESULTS: Over a median follow-up of 11.5 years (IQR 6.7 to 17.0), 110 cases of incident moderate/severe AS were ascertained. Strong positive associations with incident moderate/severe AS were found for all calcification sites after adjustment for the main model covariates: AAIR (HR=2.90, 95% CI=[1.95, 4.32], p<0.0005), AVS (HR=2.20, 95% CI=[1.44, 3.37], p<0.0005), MAC (HR=1.67, 95% CI=[1.14, 2.45], p=0.008), and the combination of MAC, AAIR, and AVS (HR=2.50, 95% CI=[1.65, 3.78], p<0.0005). In a secondary analysis, the risk of AS increased with the number of sites at which calcification was present. CONCLUSIONS: In a large cohort of community-dwelling elderly individuals, there were strong associations between each of AAIR, AVS, MAC, and the combination of MAC, AAIR, and AVS with incident moderate/severe AS. The novel finding that AAIR had a particularly strong association with incident AS, even after adjusting for other calcification sites, suggests its value in identifying individuals at risk for AS, and potential inclusion in the routine assessment by transthoracic echocardiography.

Association of immune cell subsets with incident heart failure in two population-based cohorts. - Sinha, Arjun; Sitlani, Colleen M; Doyle, Margaret F; Fohner, Alison E; Bůzková, Petra; Floyd, James S; Huber, Sally A; Olson, Nels C; Njoroge, Joyce N; Kizer, Jorge R; Delaney, Joseph A; Shah, Sanjiv S; et al. (ESC Heart Fail, 2022)
AIMS: Circulating inflammatory markers are associated with incident heart failure (HF), but prospective data on associations of immune cell subsets with incident HF are lacking. We determined the associations of immune cell subsets with incident HF as well as HF subtypes [with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF)]. METHODS AND RESULTS: Peripheral blood immune cell subsets were measured in adults from the Multi-Ethnic Study of Atherosclerosis (MESA) and Cardiovascular Health Study (CHS). Cox proportional hazard models adjusted for demographics, HF risk factors, and cytomegalovirus serostatus were used to evaluate the association of the immune cell subsets with incident HF. The average age of the MESA cohort at the time of immune cell measurements was 63.0 ± 10.4 years with 51% women, and in the CHS cohort, it was 79.6 ± 4.4 years with 62% women. In the meta-analysis of CHS and MESA, a higher proportion of CD4+ T helper (Th) 1 cells (per one standard deviation) was associated with a lower risk of incident HF [hazard ratio (HR) 0.91, (95% CI 0.83-0.99), P = 0.03]. Specifically, higher proportion of CD4+ Th1 cells was significantly associated with a lower risk of HFrEF [HR 0.73, (95% CI 0.62-0.85), <0.001] after correction for multiple testing. No association was observed with HFpEF. No other cell subsets were associated with incident HF. CONCLUSIONS: We observed that higher proportions of CD4+ Th1 cells were associated with a lower risk of incident HFrEF in two distinct population-based cohorts, with similar effect sizes in both cohorts demonstrating replicability. Although unexpected, the consistency of this finding across cohorts merits further investigation.

The Association of Measures of Cardiovascular Autonomic Function, Heart Rate, and Orthostatic Hypotension With Incident Glucose Disorders: The Cardiovascular Health Study. - Barzilay, Joshua I; Tressel, William; Biggs, Mary L; Stein, Phyllis K; Kizer, Jorge R; Shitole, Sanyog G; Bene-Alhasan, Yakubu; Mukamal, Kenneth J (Diabetes Care, 2022)
OBJECTIVE: The autonomic nervous system (ANS) innervates pancreatic endocrine cells, muscle, and liver, all of which participate in glucose metabolism. We tested whether measures of cardiovascular ANS function are independently associated with incident diabetes and annual change in fasting glucose (FG) levels as well as with insulin secretion and insulin sensitivity in older adults without diabetes. RESEARCH DESIGN AND METHODS: Heart rate (HR) and measures of HR variability (HRV) were derived from 24-h electrocardiographic monitoring. Blood pressure, seated and standing, was measured. Cox proportional hazards models and linear mixed models were used to analyze the associations between HRV, HR, and orthostatic hypotension (SBP >20 mmHg decline) and incident diabetes or longitudinal FG change. RESULTS: The mean annual unadjusted FG change was 1 mg/dL. Higher detrended fluctuation analyses (DFA) values, averaged over 4-11 (DFA1) or 12-20 beats (DFA2)-reflecting greater versus less organization of beat-to-beat intervals-were associated with less FG increase over time (per 1-SD increment: DFA1: -0.49 mg/dL/year [-0.96, -0.03]; DFA2: -0.55 mg/dL/year [-1.02, -0.09]). In mutually adjusted analyses, higher SD of the N-N interval (SDNN) was associated with less FG increase over time (per 1-SD increment: SDNN: -0.62 mg/dL/year [-1.22, -0.03]). Higher values of DFA1, DFA2, and SDNN were each associated with greater insulin secretion and insulin sensitivity but not with incident diabetes. We observed no association of HR or orthostatic hypotension with diabetes or FG change. CONCLUSIONS: Specific measures of cardiac autonomic function are prospectively related to FG level changes and insulin secretion and action.
Keywords: Aged; Autonomic Nervous System; Blood Glucose; Diabetes Mellitus; Glucose; Heart Rate; Humans; Hypotension, Orthostatic; Insulin Resistance

Association of Serum Neurofilament Light Chain Concentration and MRI Findings in Older Adults: The Cardiovascular Health Study. - Fohner, Alison E; Bartz, Traci M; Tracy, Russell P; Adams, Hieab H H; Bis, Joshua C; Djoussé, Luc; Satizabal, Claudia L; Lopez, Oscar L; Seshadri, Sudha; Mukamal, Kenneth J; Kuller, Lewis H; Psaty, Bruce M; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Neurofilament light chain (NfL) in blood is a sensitive but nonspecific marker of brain injury. This study sought to evaluate associations between NfL concentration and MRI findings of vascular brain injury in older adults. METHODS: A longitudinal cohort study included 2 cranial MRI scans performed about 5 years apart and assessed for white matter hyperintensities (WMH) and infarcts. About 1 year before their second MRI, 1,362 participants (median age 77 years, 61.4% women) without a history of TIA or stroke had measurement of 4 biomarkers: NfL, total tau, glial fibrillary acidic protein (GFAP), and ubiquitin carboxyl-terminal hydrolase L1. Most (n = 1,279) also had the first MRI scan, and some (n = 633) had quantitative measurements of hippocampal and WMH. In primary analyses, we assessed associations of NfL with a 10-point white matter grade (WMG) and prevalent infarcts on second MRI and with worsening WMG and incident infarct comparing the 2 scans. A value <0.0125 (0.05/4) was considered significant for these analyses. We also assessed associations with hippocampal and WMH volume. RESULTS: In fully adjusted models, log(NfL) concentration was associated with WMG (β = 0.27; = 2.3 × 10) and worsening WMG (relative risk [RR] 1.24; = 0.0022), but less strongly with prevalent brain infarcts (RR 1.18; = 0.013) and not with incident brain infarcts (RR 1.18; = 0.18). Associations were also present with WMH volume (β = 2,242.9, = 0.0036). For the other 3 biomarkers, the associations for log (GFAP) concentration with WMG and worsening WMG were significant. DISCUSSION: Among older adults without a history of stroke, higher serum NfL concentration was associated with covert MRI findings of vascular brain injury, especially the burden of WMH and its worsening. Whether these results offer opportunities for the use of NfL as a noninvasive biomarker of WMH or to control vascular risk factors remains to be determined.

Association of Trimethylamine N-Oxide and Metabolites With Mortality in Older Adults. - Fretts, Amanda M; Hazen, Stanley L; Jensen, Paul; Budoff, Matthew; Sitlani, Colleen M; Wang, Meng; de Oliveira Otto, Marcia C; DiDonato, Joseph A; Lee, Yujin; Psaty, Bruce M; Siscovick, David S; Sotoodehnia, Nona; et al. (JAMA Netw Open, 2022)
Importance: Little is known about the association of trimethylamine N-oxide (TMAO), a novel plasma metabolite derived from L-carnitine and phosphatidylcholine, and related metabolites (ie, choline, betaine, carnitine, and butyrobetaine) with risk of death among older adults in the general population. Objective: To investigate the associations of serial measures of plasma TMAO and related metabolites with risk of total and cause-specific death (ie, deaths from cardiovascular diseases [CVDs] and non-CVDs) among older adults in the US. Design, Setting, and Participants: This prospective cohort study involved 5333 participants from the Cardiovascular Health Study-a community-based longitudinal cohort of adults aged 65 years or older-who were followed up from June 1, 1989, to December 31, 2015. Participants were from 4 communities in the US (Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania). Data were analyzed from March 17 to June 23, 2021. Exposures: Plasma TMAO, choline, betaine, carnitine, and butyrobetaine levels were measured using stored samples from baseline (June 1, 1989, to May 31, 1990, or November 1, 1992, to June 31, 1993) and follow-up examination (June 1, 1996, to May 31, 1997). Measurements were performed through stable-isotope dilution liquid chromatography with tandem mass spectrometry using high-performance liquid chromatography with online electrospray ionization tandem mass spectrometry. Main Outcomes and Measures: Deaths (total and cause specific) were adjudicated by a centralized Cardiovascular Health Study events committee based on information from medical records, laboratory and diagnostic reports, death certificates, and/or interviews with next of kin. The associations of each metabolite with mortality were assessed using Cox proportional hazards regression models. Results: Among 5333 participants in the analytic sample, the mean (SD) age was 73 (6) years; 2149 participants (40.3%) were male, 3184 (59.7%) were female, 848 (15.9%) were African American, 4450 (83.4%) were White, and 35 (0.01%) were of other races (12 were American Indian or Alaska Native, 4 were Asian or Pacific Islander, and 19 were of other races or ethnicities). During a median follow-up of 13.2 years (range, 0-26.9 years), 4791 deaths occurred. After adjustment for potential confounders, the hazard ratios for death from any cause (ie, total mortality) comparing extreme quintiles (fifth vs first) of plasma concentrations were 1.30 (95% CI, 1.17-1.44) for TMAO, 1.19 (95% CI, 1.08-1.32) for choline, 1.26 (95% CI, 1.15-1.40) for carnitine, and 1.26 (95% CI, 1.13-1.40) for butyrobetaine. Plasma betaine was not associated with risk of death. The extent of risk estimates was similar for CVD and non-CVD mortality. Conclusions and Relevance: In this cohort study, plasma concentrations of TMAO and related metabolites were positively associated with risk of death. These findings suggest that circulating TMAO is an important novel risk factor associated with death among older adults.
Keywords: Aged; Betaine; Cardiovascular Diseases; Carnitine; Choline; Cohort Studies; Female; Humans; Male; Methylamines; Prospective Studies

The Associations of Individual and Subclasses of Non-Esterified Fatty Acids with Disability, and Mobility Limitation in Older Adults: the Cardiovascular Health Study. - Ahiawodzi, Peter; Bůzková, Petra; Lichtenstein, Alice H; Matthan, Nirupa R; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Arnold, Alice; Newman, Anne B; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (J Gerontol A Biol Sci Med Sci, 2022)
BACKGROUND: We sought to determine the associations between individual non-esterified fatty acids (NEFAs) and disability and mobility limitation. METHODS: We studied 1734 participants in the Cardiovascular Health Study (CHS), an ongoing population-based cohort study of community-living older American adults. We measured 35 individual NEFA species in fasting serum samples obtained at the 1996-1997 clinic visit. Using yearly assessments of activities of daily living and self-reported mobility, we identified participants with incident disability or mobility limitation during 15 years of follow-up. Cox proportional hazards regression models were used to determine the associations between per-SD increment in the individual NEFAs and incident disability and mobility limitations with adjustment for potential confounding factors. RESULTS: Higher concentrations of total and a broad range of individual NEFA species were associated with risk of disability and mobility limitation [disability: HR per SD of total NEFA (SD=174.70) =1.11, 95%CI=1.04-1.18, p=0.001; mobility limitation: HR per SD of total NEFA=1.09, 95%CI=1.02-1.16, p=0.01). Among individual saturated NEFAs (SFAs), myristic (14:0) and palmitic (16:0) acids were significantly associated with higher risk of both disability and mobility limitations, but longer-chain FAs were not. Most individual monounsaturated (MUFA), n-6 polyunsaturated fatty acids (PUFAs), and trans FAs were positively significantly associated with higher risks of both disability and mobility limitation. In contrast, most n-3 PUFA species were not associated with disability or mobility limitation. CONCLUSIONS: Higher risks of disability and mobility limitation were observed for pro-inflammatory intermediate-chain SFAs, MUFAs, n-6 PUFAs, and trans FAs. Our findings indicated no significant association for anti-inflammatory n-3 PUFAs.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

CD133 as a Biomarker for an Autoantibody-to-ImmunoPET Paradigm for the Early Detection of Small Cell Lung Cancer. - Kunihiro, Andrew G; Sarrett, Samantha M; Lastwika, Kristin J; Solan, Joell L; Pisarenko, Tatyana; Keinänen, Outi; Rodriguez, Cindy; Taverne, Lydia R; Fitzpatrick, Annette L; Li, Christopher I; Houghton, A McGarry; Zeglis, Brian M; et al. (J Nucl Med, 2022)
Small cell lung cancer (SCLC) is a deadly neuroendocrine tumor for which there are no screening methods sensitive enough to facilitate early, effective intervention. We propose targeting the neuroendocrine tumor neoantigen CD133 via antibody-based early detection and PET (immunoPET) to facilitate earlier and more accurate detection of SCLC. RNA sequencing datasets, immunohistochemistry, flow cytometry, and Western blots were used to quantify CD133 expression in healthy and SCLC patients. CD133 was imaged using near-infrared fluorescence (NIRF) immunoimaging, and Zr immunoPET. Anti(α)-CD133 autoantibody levels were measured in SCLC patient plasma using antibody microarrays. Across 6 publicly available datasets, CD133 messenger RNA was found to be higher in SCLC tumors than in other tissues, including healthy or normal adjacent lung and non-SCLC samples. Critically, the upregulation of CD133 messenger RNA in SCLC was associated with a significant increase (hazard ratio, 2.62) in death. CD133 protein was expressed in primary human SCLC, in SCLC patient-derived xenografts, and in both SCLC cell lines tested (H82 and H69). Using an H82 xenograft mouse model, we first imaged CD133 expression with NIRF. Both and NIRF clearly showed that a fluorophore-tagged αCD133 homed to lung tumors. Next, we validated the noninvasive visualization of subcutaneous and orthotopic H82 xenografts via immunoPET. An αCD133 antibody labeled with the positron-emitting radiometal Zr demonstrated significant accumulation in tumor tissue while producing minimal uptake in healthy organs. Finally, plasma αCD133 autoantibodies were found in subjects from cohort studies up to 1 year before SCLC diagnosis. In light of these findings, we conclude that the presence of αCD133 autoantibodies in a blood sample followed by CD133-targeted Zr-immunoPET could be an effective early detection screening strategy for SCLC.
Keywords: Animals; Autoantibodies; Biomarkers; Cell Line, Tumor; Disease Models, Animal; Early Detection of Cancer; Humans; Lung Neoplasms; Mice; Mice, Nude; Neuroendocrine Tumors; Positron-Emission Tomography; RNA, Messenger; Small Cell Lung Carcinoma

Circulating Androgen Concentrations and Risk of Incident Heart Failure in Older Men: The Cardiovascular Health Study. - Njoroge, Joyce N; Tressel, William; Biggs, Mary L; Matsumoto, Alvin M; Smith, Nicholas L; Rosenberg, Emily; Hirsch, Calvin H; Gottdiener, John S; Mukamal, Kenneth J; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Circulating androgen concentrations in men decline with age and have been linked to diabetes and atherosclerotic cardiovascular disease (ASCVD). A similar relationship has been reported for low total testosterone and incident heart failure (HF) but remains unstudied for free testosterone or the more potent androgen dihydrotestosterone (DHT). We hypothesized that total/free testosterone are inversely related, sex hormone-binding globulin is positively related, and total/free DHT bear a U-shaped relationship with incident HF. Methods and Results In a sample of men from the CHS (Cardiovascular Health Study) without atherosclerotic cardiovascular disease or HF, serum testosterone and DHT concentrations were measured by liquid chromatography-tandem mass spectrometry, and sex hormone-binding globulin by immunoassay. Free testosterone or DHT was calculated from total testosterone or total DHT, sex hormone-binding globulin, and albumin. We used Cox regression to estimate relative risks of HF after adjustment for potential confounders. In 1061 men (aged 76±5 years) followed for a median of 9.6 years, there were 368 HF events. After adjustment, lower calculated free testosterone was significantly associated with higher risk of HF (hazard ratio [HR], 1.14 [95% CI, 1.01-1.28]). Risk estimates for total testosterone (HR, 1.12 [95% CI, 0.99-1.26]), total DHT (HR, 1.10 [95% CI, 0.97-1.24]), calculated free dihydrotestosterone (HR, 1.09 [95% CI, 0.97-1.23]), and sex hormone-binding globulin (HR, 1.07 [95% CI, 0.95-1.21]) were directionally similar but not statistically significant. Conclusions Calculated free testosterone was inversely associated with incident HF, suggesting a contribution of testosterone deficiency to HF incidence among older men. Additional research is necessary to determine whether testosterone replacement therapy might be an effective strategy to lower HF risk in older men.
Keywords: Aged; Androgens; Cardiovascular Diseases; Dihydrotestosterone; Estradiol; Heart Failure; Humans; Male; Sex Hormone-Binding Globulin; Testosterone

Circulating Soluble CD163, Associations With Cardiovascular Outcomes and Mortality, and Identification of Genetic Variants in Older Individuals: The Cardiovascular Health Study. - Durda, Peter; Raffield, Laura M; Lange, Ethan M; Olson, Nels C; Jenny, Nancy Swords; Cushman, Mary; Deichgraeber, Pia; Grarup, Niels; Jonsson, Anna; Hansen, Torben; Mychaleckyj, Josyf C; Psaty, Bruce M; et al. (J Am Heart Assoc, 2022)
Background Monocytes/macrophages participate in cardiovascular disease. CD163 (cluster of differentiation 163) is a monocyte/macrophage receptor, and the shed sCD163 (soluble CD163) reflects monocyte/macrophage activation. We examined the association of sCD163 with incident cardiovascular disease events and performed a genome-wide association study to identify sCD163-associated variants. Methods and Results We measured plasma sCD163 in 5214 adults (aged ≥65 years, 58.7% women, 16.2% Black) of the CHS (Cardiovascular Health Study). We used Cox regression models (associations of sCD163 with incident events and mortality); median follow-up was 26 years. Genome-wide association study analyses were stratified on race. Adjusted for age, sex, and race and ethnicity, sCD163 levels were associated with all-cause mortality (hazard ratio [HR], 1.08 [95% CI, 1.04-1.12] per SD increase), cardiovascular disease mortality (HR, 1.15 [95% CI, 1.09-1.21]), incident coronary heart disease (HR, 1.10 [95% CI, 1.04-1.16]), and incident heart failure (HR, 1.18 [95% CI, 1.12-1.25]). When further adjusted (eg, cardiovascular disease risk factors), only incident coronary heart disease lost significance. In European American individuals, genome-wide association studies identified 38 variants on chromosome 2 near (top result rs62165726, =3.3×10),19 variants near chromosome 17 gene (rs55714927, =1.5×10), and 18 variants near chromosome 11 gene . These regions replicated in the European ancestry ADDITION-PRO cohort, a longitudinal cohort study nested in the Danish arm of the Anglo-Danish-Dutch study of Intensive Treatment Intensive Treatment In peOple with screeNdetcted Diabetes in Primary Care. In Black individuals, we identified 9 variants on chromosome 6 (rs3129781 =7.1×10) in the region, and 3 variants (rs115391969 =4.3×10) near the chromosome 16 gene Conclusions Monocyte function, as measured by sCD163, may be predictive of overall and cardiovascular-specific mortality and incident heart failure.
Keywords: Aged; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Asialoglycoprotein Receptor; Biomarkers; Cardiovascular Diseases; Female; Genome-Wide Association Study; Heart Failure; Humans; Longitudinal Studies; Male

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

Correlations between complex human phenotypes vary by genetic background, gender, and environment. - Elgart, Michael; Goodman, Matthew O; Isasi, Carmen; Chen, Han; Morrison, Alanna C; de Vries, Paul S; Xu, Huichun; Manichaikul, Ani W; Guo, Xiuqing; Franceschini, Nora; Psaty, Bruce M; Rich, Stephen S; et al. (Cell Rep Med, 2022)
We develop a closed-form Haseman-Elston estimator for genetic and environmental correlation coefficients between complex phenotypes, which we term HEc, that is as precise as GCTA yet ∼20× faster. We estimate genetic and environmental correlations between over 7,000 phenotype pairs in subgroups from the Trans-Omics in Precision Medicine (TOPMed) program. We demonstrate substantial differences in both heritabilities and genetic correlations for multiple phenotypes and phenotype pairs between individuals of self-reported Black, Hispanic/Latino, and White backgrounds. We similarly observe differences in many of the genetic and environmental correlations between genders. To estimate the contribution of genetics to the observed phenotypic correlation, we introduce "fractional genetic correlation" as the fraction of phenotypic correlation explained by genetics. Finally, we quantify the enrichment of correlations between phenotypic domains, each of which is comprised of multiple phenotypes. Altogether, we demonstrate that the observed correlations between complex human phenotypes depend on the genetic background of the individuals, their gender, and their environment.
Keywords: Female; Genetic Background; Humans; Male; Phenotype

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Dietary Meat, Trimethylamine N-Oxide-Related Metabolites, and Incident Cardiovascular Disease Among Older Adults: The Cardiovascular Health Study. - Wang, Meng; Wang, Zeneng; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (Arterioscler Thromb Vasc Biol, 2022)
BACKGROUND: Effects of animal source foods (ASF) on atherosclerotic cardiovascular disease (ASCVD) and underlying mechanisms remain controversial. We investigated prospective associations of different ASF with incident ASCVD and potential mediation by gut microbiota-generated trimethylamine N-oxide, its L-carnitine-derived intermediates γ-butyrobetaine and crotonobetaine, and traditional ASCVD risk pathways. METHODS: Among 3931 participants from a community-based US cohort aged 65+ years, ASF intakes and trimethylamine N-oxide-related metabolites were measured serially over time. Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, other atherosclerotic death) was adjudicated over 12.5 years median follow-up. Cox proportional hazards models with time-varying exposures and covariates examined ASF-ASCVD associations; and additive hazard models, mediation proportions by different risk pathways. RESULTS: After multivariable-adjustment, higher intakes of unprocessed red meat, total meat, and total ASF associated with higher ASCVD risk, with hazard ratios (95% CI) per interquintile range of 1.15 (1.01-1.30), 1.22 (1.07-1.39), and 1.18 (1.03-1.34), respectively. Trimethylamine N-oxide-related metabolites together significantly mediated these associations, with mediation proportions (95% CI) of 10.6% (1.0-114.5), 7.8% (1.0-32.7), and 9.2% (2.2-44.5), respectively. Processed meat intake associated with a nonsignificant trend toward higher ASCVD (1.11 [0.98-1.25]); intakes of fish, poultry, and eggs were not significantly associated. Among other risk pathways, blood glucose, insulin, and C-reactive protein, but not blood pressure or blood cholesterol, each significantly mediated the total meat-ASCVD association. CONCLUSIONS: In this large, community-based cohort, higher meat intake associated with incident ASCVD, partly mediated by microbiota-derived metabolites of L-carnitine, abundant in red meat. These novel findings support biochemical links between dietary meat, gut microbiome pathways, and ASCVD.
Keywords: Animals; Atherosclerosis; Cardiovascular Diseases; Carnitine; Humans; Meat; Methylamines; Risk Factors

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Dysregulated carbohydrate and lipid metabolism and risk of atrial fibrillation in advanced old age. - Pellegrini, Cara N; Bůzková, Petra; Oesterle, Adam; Heckbert, Susan R; Tracy, Russell P; Siscovick, David S; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R (Heart, 2022)
OBJECTIVE: Obesity and dysmetabolism are major risk factors for atrial fibrillation (AF). Fasting and postload levels of glucose and non-esterified fatty acids (NEFAs) reflect different facets of metabolic regulation. We sought to study their respective contributions to AF risk concurrently. METHODS: We assessed levels of fasting and postload glucose and NEFA in the Cardiovascular Health Study to identify associations with AF incidence and, secondarily, with ECG parameters of AF risk available at baseline. Linear and Cox regressions were performed. RESULTS: The study included 1876 participants (age 77.7±4.4). During the median follow-up of 11.4 years, 717 cases of incident AF occurred. After adjustment for potential confounders, postload glucose showed an association with incident AF (HR per SD increment of postload glucose=1.11, 95% CI 1.02 to 1.21, p=0.017). Both glucose measures, but not NEFA, were positively associated with higher P wave terminal force in V1 (PTFV1); the association remained significant only for postload glucose when the two measures were entered together (β per SD increment=138 μV·ms, 95% CI 15 to 260, p=0.028). Exploratory analyses showed significant interaction by sex for fasting NEFA (p=0.044) and postload glucose (p=0.015) relative to AF, with relationships stronger in women. For postload glucose, the association with incident AF was observed among women but not among men. CONCLUSIONS: Among older adults, postload glucose was positively associated with incident AF, with consistent findings for PTFV1. In exploratory analyses, the relationship with AF appeared specific to women. These findings require further study but suggest that interventions to address postprandial dysglycaemia late in life might reduce AF.

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

Epilepsy, Vascular Risk Factors, and Cognitive Decline in Older Adults: The Cardiovascular Health Study. - Choi, Hyunmi; Elkind, Mitchell S V; Longstreth, W T; Boehme, Amelia K; Hafen, Rebekah; Hoyt, Emma J; Thacker, Evan L (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Recent studies have shown that global cognitive ability tends to decline faster over time in older adults (≥65 years) with epilepsy compared with older adults without epilepsy. Scarce data exist about the role of vascular risk factors (VRFs) on cognitive course in epilepsy. We assessed whether the associations of individual VRFs with cognitive trajectory differed depending on the presence of prevalent epilepsy. METHODS: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5,888 US adults aged ≥65 years. Cognitive function was assessed annually with modified Mini-Mental State Examination (3MS; global cognitive ability) and Digit Symbol Substitution Test (DSST; information processing speed). We used linear mixed models to estimate the individual and joint associations of epilepsy and VRFs with cognitive decline by modeling epilepsy × VRF interactions one by one, each adjusted for all other VRFs considered, including demographics, health behaviors, clinical characteristics, and comorbid diagnoses. From these models, we estimated excess mean cognitive decline due to interaction of epilepsy with each VRF. RESULTS: We observed excess mean decline in global cognitive ability (3MS) due to interactions of epilepsy with hypertension (6.6 points greater mean 8-year decline than expected if no interaction; 95% CI 1.3-12.0) and with abstaining from alcohol (5.8 points greater than expected; 95% CI 0.3-11.3). We also observed excess mean decline in information processing speed (DSST) due to interactions of epilepsy with prior stroke (18.1 points greater mean 9-year decline than expected; 95% CI 7.6-28.5), with abstaining from alcohol (6.1 points greater than expected; 95% CI 2.5-9.8), and with higher triglyceride levels (2.4 points greater than expected per SD; 95% CI 0.4-4.3). DISCUSSION: Associations of some VRFs with cognitive decline in older adults are stronger in the presence of epilepsy, suggesting a need for greater attention to vascular protection for preserving brain health in older adults with epilepsy.
Keywords: Aged; Cognition; Cognitive Dysfunction; Epilepsy; Humans; Longitudinal Studies; Neuropsychological Tests; Risk Factors

Fasting and Post-Load Glucose and Non-Esterified Fatty Acids and Risk of Heart Failure and its Subtypes in Older Adults. - Oesterle, Adam; Bůzková, Petra; Pellegrini, Cara; Hirsch, Calvin; Tracy, Russell P; Siscovick, David S; Djoussé, Luc; Mukamal, Ken J; Kizer, Jorge R (J Gerontol A Biol Sci Med Sci, 2022)
BACKGROUND: Glucose and non-esterified fatty acids (NEFA) are myocardial fuels whose fasting and post-prandial levels are under different homeostatic regulation. The relationships of fasting and post-load glucose and NEFA with incident heart failure (HF) remain incompletely defined. METHODS: Serum glucose and NEFA were measured during fasting and 2 hours post oral glucose tolerance test, performed in Cardiovascular Health Study participants not receiving hypoglycemic medication. Participants with prevalent HF or lacking relevant data were excluded. Outcomes were incident HF (primary), and HF with preserved (HFpEF) and reduced (HFrEF) ejection fraction (secondary). RESULTS: Among 2238 participants (age 78±4) with median follow-up of 9.9 years, there were 737 HF events. After adjustment for demographic and lifestyle factors, both fasting (HR=1.11 per SD [95% CI=1.01-1.23], p=0.040) and post-load (HR=1.14 per SD [1.05-1.24], p=0.002) glucose were significantly associated with incident HF. No association was seen for fasting or post-load NEFA. Upon mutual adjustment, only post-load glucose (HR=1.11 [1.003-1.22], p=0.044), but not fasting glucose (HR=1.06 [0.94-1.20], p=0.340), remained associated with HF. Further adjustment for cardiovascular disease and other risk factors in the causal pathway did not affect the association for post-load glucose, but eliminated that for fasting glucose. Associations for fasting and post-load glucose appeared stronger with higher adiposity, and were observed specifically for HFrEF, but not HFpEF. CONCLUSIONS: Fasting and post-load glucose, but not NEFA, were associated with incident HF. The association was especially robust for post-load glucose, suggesting that pathways involved in post-prandial dysglycemia could offer new targets for HF prevention late in life.

Fasting and Postload Nonesterified Fatty Acids and Glucose Dysregulation in Older Adults. - Shitole, Sanyog G; Biggs, Mary L; Ix, Joachim H; Fretts, Amanda M; Tracy, Russell P; Siscovick, David S; Djoussé, Luc; Mukamal, Kenneth J; Kizer, Jorge R (Am J Epidemiol, 2022)
To evaluate the association of nonesterified fatty acids (NEFA) with dysglycemia in older adults, NEFA levels were measured among participants in the Cardiovascular Health Study (United States; enrolled 1989-1993). Associations with insulin sensitivity and pancreatic β-cell function, and with incident type 2 diabetes mellitus (DM), were examined. The sample comprised 2,144 participants (aged 77.9 (standard deviation, 4.5) years). Participant data from the Cardiovascular Health Study visit in 1996-1997 was used with prospective follow-up through 2010. Fasting and postload NEFA showed significant associations with lower insulin sensitivity and pancreatic β-cell function, individually and on concurrent adjustment. Over median follow-up of 9.7 years, 236 cases of DM occurred. Postload NEFA were associated with risk of DM (per standard deviation, hazard ratio = 1.18, 95% confidence interval: 1.08, 1.29), but fasting NEFA were not (hazard ratio = 1.12, 95% confidence interval: 0.97, 1.29). The association for postload NEFA persisted after adjustment for putative intermediates, and after adjustment for fasting NEFA. Sex and body mass index modified these associations, which were stronger for fasting NEFA with DM in men but were accentuated for postload NEFA in women and among leaner individuals. Fasting and postload NEFA were related to lower insulin sensitivity and pancreatic β-cell function, but only postload NEFA were associated with increased DM. Additional study into NEFA metabolism could uncover novel potential targets for diabetes prevention in elders.
Keywords: Aged; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Fatty Acids, Nonesterified; Female; Glucose; Humans; Insulin; Insulin Resistance; Male; Prospective Studies

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

{Gene Set Enrichment Analsyes Identify Pathways Involved in Genetic Risk for Diabetic Retinopathy - Sobrin, L.; Susarla, G.; Stanwyck, L.; Rouhana, J. M.; Li, A.; Pollack, S.; Igo, R. P.; Jensen, R. A.; Li, X.; Ng, M. C. Y.; Smith, A. V.; Kuo, J. Z.; et al. (Am J Ophthalmol, 2022)
{To identify functionally related genes associated with diabetic retinopathy (DR) risk using gene set enrichment analyses applied to genome-wide association study meta-analyses.\ .05.\ .05) in the other method. These pathways were regulation of the lipid catabolic process (2-fold enrichment

{Gene-mapping study of extremes of cerebral small vessel disease reveals TRIM47 as a strong candidate - Mishra, A.; Duplaà, C.; Vojinovic, D.; Suzuki, H.; Sargurupremraj, M.; Zilhao, N. R.; Li, S.; Bartz, T. M.; Jian, X.; Zhao, W.; Hofer, E.; Wittfeld, K.; et al. (Brain, 2022)
Cerebral small vessel disease is a leading cause of stroke and a major contributor to cognitive decline and dementia, but our understanding of specific genes underlying the cause of sporadic cerebral small vessel disease is limited. We report a genome-wide association study and a whole-exome association study on a composite extreme phenotype of cerebral small vessel disease derived from its most common MRI features: white matter hyperintensities and lacunes. Seventeen population-based cohorts of older persons with MRI measurements and genome-wide genotyping (n = 41 326), whole-exome sequencing (n = 15 965), or exome chip (n = 5249) data contributed 13 776 and 7079 extreme small vessel disease samples for the genome-wide association study and whole-exome association study, respectively. The genome-wide association study identified significant association of common variants in 11 loci with extreme small vessel disease, of which the chr12q24.11 locus was not previously reported to be associated with any MRI marker of cerebral small vessel disease. The whole-exome association study identified significant associations of extreme small vessel disease with common variants in the 5' UTR region of EFEMP1 (chr2p16.1) and one probably damaging common missense variant in TRIM47 (chr17q25.1). Mendelian randomization supports the causal association of extensive small vessel disease severity with increased risk of stroke and Alzheimer's disease. Combined evidence from summary-based Mendelian randomization studies and profiling of human loss-of-function allele carriers showed an inverse relation between TRIM47 expression in the brain and blood vessels and extensive small vessel disease severity. We observed significant enrichment of Trim47 in isolated brain vessel preparations compared to total brain fraction in mice, in line with the literature showing Trim47 enrichment in brain endothelial cells at single cell level. Functional evaluation of TRIM47 by small interfering RNAs-mediated knockdown in human brain endothelial cells showed increased endothelial permeability, an important hallmark of cerebral small vessel disease pathology. Overall, our comprehensive gene-mapping study and preliminary functional evaluation suggests a putative role of TRIM47 in the pathophysiology of cerebral small vessel disease, making it an important candidate for extensive in vivo explorations and future translational work.

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome-wide analyses identify as a susceptibility locus for premature atrial contraction frequency. - Thériault, Sébastien; Imboden, Medea; Biggs, Mary L; Austin, Thomas R; Aeschbacher, Stefanie; Schaffner, Emmanuel; Brody, Jennifer A; Bartz, Traci M; Risch, Martin; Grossmann, Kirsten; Lin, Henry J; Soliman, Elsayed Z; et al. (iScience, 2022)
Premature atrial contractions (PACs) are frequently observed on electrocardiograms and are associated with increased risks of atrial fibrillation (AF), stroke, and mortality. In this study, we aimed to identify genetic susceptibility loci for PAC frequency. We performed a genome-wide association study meta-analysis with PAC frequency obtained from ambulatory cardiac monitoring in 4,831 individuals of European ancestry. We identified a genome-wide significant locus at the gene. The lead variant, rs7373862, located in an intron of , was associated with an increase of 0.12 [95% CI 0.08-0.16] standard deviations of the normalized PAC frequency per risk allele. Among genetic variants previously associated with AF, there was a significant enrichment in concordance of effect for PAC frequency (n = 73/106, p = 5.1 × 10). However, several AF risk loci, including , were not associated with PAC frequency. These findings suggest the existence of both shared and distinct genetic mechanisms for PAC frequency and AF.

{Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - Longchamps, R. J.; Yang, S. Y.; Castellani, C. A.; Shi, W.; Lane, J.; Grove, M. L.; Bartz, T. M.; Sarnowski, C.; Liu, C.; Burrows, K.; Guyatt, A. L.; Gaunt, T. R.; et al. (Hum Genet, 2022)
).

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases - Li, Y.; Cheng, Y.; Consolato, F.; Schiano, G.; Chong, M. R.; Pietzner, M.; Nguyen, N. Q. H.; Scherer, N.; Biggs, M. L.; Kleber, M. E.; Haug, S.; Göçmen, B.; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.

Immune cell subpopulations as risk factors for atrial fibrillation: The Cardiovascular Health Study and Multi-Ethnic Study of Atherosclerosis. - Floyd, James S; Sitlani, Colleen M; Doyle, Margaret F; Feinstein, Matthew J; Olson, Nels C; Heckbert, Susan R; Huber, Sally A; Tracy, Russell P; Psaty, Bruce M; Delaney, Joseph A C (Heart Rhythm, 2022)

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Intake and Sources of Dietary Fiber, Inflammation, and Cardiovascular Disease in Older US Adults. - Shivakoti, Rupak; Biggs, Mary L; Djoussé, Luc; Durda, Peter Jon; Kizer, Jorge R; Psaty, Bruce; Reiner, Alex P; Tracy, Russell P; Siscovick, David; Mukamal, Kenneth J (JAMA Netw Open, 2022)
Importance: Higher intake of dietary fiber has been associated with lower inflammation, but whether there are differences in this association by source of dietary fiber (ie, cereal, vegetable, or fruit) has not been studied to date. Objectives: To evaluate the associations of total fiber intake and source (ie, cereal, vegetable, and fruit fiber intake) with inflammation and to evaluate whether inflammation mediates the inverse association between dietary fiber intake and cardiovascular disease (CVD). Design, Setting, and Participants: At the baseline visit (1989-1990) of 4125 adults aged 65 years or older in an ongoing US cohort study, dietary intake was assessed by a food frequency questionnaire among study participants without prevalent CVD (stroke and myocardial infarction) at enrollment. Inflammation was assessed from blood samples collected at baseline with immunoassays for markers of inflammation. Multivariable linear regression models tested the association of dietary fiber intake with inflammation. Also assessed was whether each inflammatory marker and its composite derived from principal component analysis mediated the association of baseline cereal fiber intake with development of CVD (stroke, myocardial infarction, and atherosclerotic cardiovascular death) through June 2015. Data from June 1, 1989, through June 30, 2015, were analyzed. Exposures: Total fiber intake and sources of fiber (cereal, vegetable, and fruit). Main Outcomes and Measures: Systemic markers of inflammation. Cardiovascular disease was the outcome in the mediation analysis. Results: Of 4125 individuals, 0.1% (n = 3) were Asian or Pacific Islander, 4.4% (n = 183) were Black, 0.3% (n = 12) were Native American, 95.0% (n = 3918) were White, and 0.2% (n = 9) were classified as other. Among these 4125 individuals (2473 women [60%]; mean [SD] age, 72.6 [5.5] years; 183 Black individuals [4.4%]; and 3942 individuals of other races and ethnicitites [95.6%] [ie, race and ethnicity other than Black, self-classified by participant]), an increase in total fiber intake of 5 g/d was associated with significantly lower concentrations of C-reactive protein (adjusted mean difference, -0.05 SD; 95% CI, -0.08 to -0.01 SD; P = .007) and interleukin 1 receptor antagonist (adjusted mean difference, -0.04 SD; 95% CI, -0.07 to -0.01 SD; P < .02) but with higher concentrations of soluble CD163 (adjusted mean difference, 0.05 SD; 95% CI, 0.02-0.09 SD; P = .005). Among fiber sources, only cereal fiber was consistently associated with lower inflammation. Similarly, cereal fiber intake was associated with lower CVD incidence (adjusted hazard ratio, 0.90; 95% CI, 0.81-1.00; 1941 incident cases). The proportion of the observed association of cereal fiber with CVD mediated by inflammatory markers ranged from 1.5% for interleukin 18 to 14.2% for C-reactive protein, and 16.1% for their primary principal component. Conclusions and Relevance: Results of this study suggest that cereal fiber intake was associated with lower levels of various inflammatory markers and lower risk of CVD and that inflammation mediated approximately one-sixth of the association between cereal fiber intake and CVD.
Keywords: Adult; Aged; Cardiovascular Diseases; Cohort Studies; Dietary Fiber; Female; Humans; Inflammation; Middle Aged; Risk Factors

Integrative analysis of clinical and epigenetic biomarkers of mortality. - Huan, Tianxiao; Nguyen, Steve; Colicino, Elena; Ochoa-Rosales, Carolina; Hill, W David; Brody, Jennifer A; Soerensen, Mette; Zhang, Yan; Baldassari, Antoine; Elhadad, Mohamed Ahmed; Toshiko, Tanaka; Zheng, Yinan; et al. (Aging Cell, 2022)
DNA methylation (DNAm) has been reported to be associated with many diseases and with mortality. We hypothesized that the integration of DNAm with clinical risk factors would improve mortality prediction. We performed an epigenome-wide association study of whole blood DNAm in relation to mortality in 15 cohorts (n = 15,013). During a mean follow-up of 10 years, there were 4314 deaths from all causes including 1235 cardiovascular disease (CVD) deaths and 868 cancer deaths. Ancestry-stratified meta-analysis of all-cause mortality identified 163 CpGs in European ancestry (EA) and 17 in African ancestry (AA) participants at p < 1 × 10 , of which 41 (EA) and 16 (AA) were also associated with CVD death, and 15 (EA) and 9 (AA) with cancer death. We built DNAm-based prediction models for all-cause mortality that predicted mortality risk after adjusting for clinical risk factors. The mortality prediction model trained by integrating DNAm with clinical risk factors showed an improvement in prediction of cancer death with 5% increase in the C-index in a replication cohort, compared with the model including clinical risk factors alone. Mendelian randomization identified 15 putatively causal CpGs in relation to longevity, CVD, or cancer risk. For example, cg06885782 (in KCNQ4) was positively associated with risk for prostate cancer (Beta = 1.2, P  = 4.1 × 10 ) and negatively associated with longevity (Beta = -1.9, P  = 0.02). Pathway analysis revealed that genes associated with mortality-related CpGs are enriched for immune- and cancer-related pathways. We identified replicable DNAm signatures of mortality and demonstrated the potential utility of CpGs as informative biomarkers for prediction of mortality risk.
Keywords: Biomarkers; Cardiovascular Diseases; DNA Methylation; Epigenesis, Genetic; Epigenomics; Humans; Male; Neoplasms

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Longitudinal Associations of Plasma TMAO and Related Metabolites with Cognitive Impairment and Dementia in Older Adults: The Cardiovascular Health Study. - de Oliveira Otto, Marcia C; Li, Xinmin S; Wang, Zeneng; Siscovick, David; Newman, Anne B; Lai, Heidi Tsz Mung; Nemet, Ina; Lee, Yujin; Wang, Meng; Fretts, Amanda; Lemaitre, Rozenn N; Tang, W H Wilson; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Animal studies suggest that gut microbiome metabolites such as trimethylamine N-oxide (TMAO) may influence cognitive function and dementia risk. However potential health effects of TMAO and related metabolites remain unclear. OBJECTIVE: We examined prospective associations of TMAO, γ-butyrobetaine, crotonobetaine, carnitine, choline, and betaine with risk of cognitive impairment and dementia among older adults aged 65 years and older in the Cardiovascular Health Study (CHS). METHODS: TMAO and metabolites were measured in stored plasma specimens collected at baseline. Incident cognitive impairment was assessed using the 100-point Modified Mini-Mental State Examination administered serially up to 7 times. Clinical dementia was identified using neuropsychological tests adjudicated by CHS Cognition Study investigators, and by ICD-9 codes from linked Medicare data. Associations of each metabolite with cognitive outcomes were assessed using Cox proportional hazards models. RESULTS: Over a median of 13 years of follow-up, 529 cases of cognitive impairment, and 522 of dementia were identified. After multivariable adjustment for relevant risk factors, no associations were seen with TMAO, carnitine, choline, or betaine. In contrast, higher crotonobetaine was associated with 20-32% higher risk of cognitive impairment and dementia per interquintile range (IQR), while γ-butyrobetaine was associated with ∼25% lower risk of the same cognitive outcomes per IQR.∥Conclusion:These findings suggest that γ-butyrobetaine, crotonobetaine, two gut microbe and host metabolites, are associated with risk of cognitive impairment and dementia. Our results indicate a need for mechanistic studies evaluating potential effects of these metabolites, and their interconversion on brain health, especially later in life.

Longitudinal Changes in Hearing and Visual Impairments and Risk of Dementia in Older Adults in the United States. - Hwang, Phillip H; Longstreth, W T; Thielke, Stephen M; Francis, Courtney E; Carone, Marco; Kuller, Lewis H; Fitzpatrick, Annette L (JAMA Netw Open, 2022)
Importance: Hearing and vision problems are individually associated with increased dementia risk, but the impact of having concurrent hearing and vision deficits, ie, dual sensory impairment (DSI), on risk of dementia, including its major subtypes Alzheimer disease (AD) and vascular dementia (VaD), is not well known. Objective: To evaluate whether DSI is associated with incident dementia in older adults. Design, Setting, and Participants: This prospective cohort study from the Cardiovascular Health Study (CHS) was conducted between 1992 and 1999, with as many as 8 years of follow-up. The multicenter, population-based sample was recruited from Medicare eligibility files in 4 US communities with academic medical centers. Of 5888 participants aged 65 years and older in CHS, 3602 underwent cranial magnetic resonance imaging and completed the modified Mini-Mental State Examination in 1992 to 1994 as part of the CHS Cognition Study. A total of 227 participants were excluded due to prevalent dementia, leaving a total of 3375 participants without dementia at study baseline. The study hypothesis was that DSI would be associated with increased risk of dementia compared with no sensory impairment. The association between the duration of DSI with risk of dementia was also evaluated. Data analysis was conducted from November 2019 to February 2020. Exposures: Hearing and vision impairments were collected via self-report at baseline and as many as 5 follow-up visits. Main Outcomes and Measures: All-cause dementia, AD, and VaD, classified by a multidisciplinary committee using standardized criteria. Results: A total of 2927 participants with information on hearing and vision at all available study visits were included in the analysis (mean [SD] age, 74.6 [4.8] years; 1704 [58.2%] women; 455 [15.5%] African American or Black; 2472 [85.5%] White). Compared with no sensory impairment, DSI was associated with increased risk of all-cause dementia (hazard ratio [HR], 2.60; 95% CI, 1.66-2.06; P < .001), AD (HR, 3.67; 95% CI, 2.04-6.60; P < .001) but not VaD (HR, 2.03; 95% CI, 1.00-4.09; P = .05). Conclusions and Relevance: In this cohort study, DSI was associated with increased risk of dementia, particularly AD. Evaluation of hearing and vision in older adults may help to identify those at high risk of developing dementia.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Female; Hearing; Hearing Loss; Humans; Male; Medicare; Prospective Studies; United States; Vision Disorders

Monocyte subsets, T cell activation profiles, and stroke in men and women: The Multi-Ethnic Study of Atherosclerosis and Cardiovascular Health Study. - Feinstein, Matthew J; Bůzková, Petra; Olson, Nels C; Doyle, Margaret F; Sitlani, Colleen M; Fohner, Alison E; Huber, Sally A; Floyd, James; Sinha, Arjun; Thorp, Edward B; Landay, Alan; Freiberg, Matthew S; et al. (Atherosclerosis, 2022)
BACKGROUND AND AIMS: Despite mechanistic data implicating unresolving inflammation in stroke pathogenesis, data regarding circulating immune cell phenotypes - key determinants of inflammation propagation versus resolution - and incident stroke are lacking. Therefore, we aimed to comprehensively define associations of circulating immune phenotypes and activation profiles with incident stroke. METHODS: We investigated circulating leukocyte phenotypes and activation profiles with incident adjudicated stroke in 2104 diverse adults from the Multi-Ethnic Study of Atherosclerosis (MESA) followed over a median of 16.6 years. Cryopreserved cells from the MESA baseline examination were thawed and myeloid and lymphoid lineage cell subsets were measured using polychromatic flow cytometry and intracellular cytokine activation staining. We analyzed multivariable-adjusted associations of cell phenotypes, as a proportion of parent cell subsets, with incident stroke (overall) and ischemic stroke using Cox regression models. RESULTS: We observed associations of intermediate monocytes, early-activated CD4 T cells, and both CD4 and CD8 T cells producing interleukin-4 after cytokine stimulation (T and T, respectively) with higher risk for incident stroke; effect sizes ranged from 35% to 62% relative increases in risk for stroke. Meanwhile, differentiated and memory T cell phenotypes were associated with lower risk for incident stroke. In sex-stratified analyses, positive and negative associations were especially strong among men but null among women. CONCLUSIONS: Circulating IL-4 producing T cells and intermediate monocytes were significantly associated with incident stroke over nearly two decades of follow-up. These associations were stronger among men and not among women. Further translational studies are warranted to define more precise targets for prognosis and intervention.
Keywords: Atherosclerosis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cytokines; Female; Follow-Up Studies; Humans; Incidence; Inflammation; Interleukin-4; Ischemic Stroke; Lymphocyte Activation; Male; Monocytes; Stroke; T-Lymphocyte Subsets

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

Multi-Scalar Data Integration Links Glomerular Angiopoietin-Tie Signaling Pathway Activation With Progression of Diabetic Kidney Disease. - Liu, Jiahao; Nair, Viji; Zhao, Yi-Yang; Chang, Dong-Yuan; Limonte, Christine; Bansal, Nisha; Fermin, Damian; Eichinger, Felix; Tanner, Emily C; Bellovich, Keith A; Steigerwalt, Susan; Bhat, Zeenat; et al. (Diabetes, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease (ESKD). Prognostic biomarkers reflective of underlying molecular mechanisms are critically needed for effective management of DKD. A three-marker panel was derived from a proteomics analysis of plasma samples by an unbiased machine learning approach from participants (N = 58) in the Clinical Phenotyping and Resource Biobank study. In combination with standard clinical parameters, this panel improved prediction of the composite outcome of ESKD or a 40% decline in glomerular filtration rate. The panel was validated in an independent group (N = 68), who also had kidney transcriptomic profiles. One marker, plasma angiopoietin 2 (ANGPT2), was significantly associated with outcomes in cohorts from the Cardiovascular Health Study (N = 3,183) and the Chinese Cohort Study of Chronic Kidney Disease (N = 210). Glomerular transcriptional angiopoietin/Tie (ANG-TIE) pathway scores, derived from the expression of 154 ANG-TIE signaling mediators, correlated positively with plasma ANGPT2 levels and kidney outcomes. Higher receptor expression in glomeruli and higher ANG-TIE pathway scores in endothelial cells corroborated potential functional effects in the kidney from elevated plasma ANGPT2 levels. Our work suggests that ANGPT2 is a promising prognostic endothelial biomarker with likely functional impact on glomerular pathogenesis in DKD.
Keywords: Angiopoietin-1; Angiopoietin-2; Angiopoietins; Biomarkers; Cohort Studies; Diabetes Mellitus; Diabetic Nephropathies; Disease Progression; Endothelial Cells; Humans; Kidney Failure, Chronic; Receptor, TIE-2; Signal Transduction

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Plasma epoxyeicosatrienoic acids and diabetes-related cardiovascular disease: The cardiovascular health study. - Lemaitre, Rozenn N; Jensen, Paul N; Zeigler, Maxwell; Fretts, Amanda M; Umans, Jason G; Howard, Barbara V; Sitlani, Colleen M; McKnight, Barbara; Gharib, Sina A; King, Irena B; Siscovick, David S; Psaty, Bruce M; et al. (EBioMedicine, 2022)
BACKGROUND: Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid that may impact atherosclerosis, and animal experimental studies suggest EETs protect cardiac function. Plasma EETs are mostly esterified to phospholipids and part of an active pool. To address the limited information about EETs and CVD in humans, we conducted a prospective study of total plasma EETs (free + esterified) and diabetes-related CVD in the Cardiovascular Health Study (CHS). METHODS: We measured 4 EET species and their metabolites, dihydroxyepoxyeicosatrienoic acids (DHETs), in plasma samples from 892 CHS participants with type 2 diabetes. We determined the association of EETs and DHETs with incident myocardial infarction (MI) and ischemic stroke using Cox regression. FINDINGS: During follow-up (median 7.5 years), we identified 150 MI and 134 ischemic strokes. In primary, multivariable analyses, elevated levels of each EET species were associated with non-significant lower risk of incident MI (for example, hazard ratio for 1 SD higher 14,15-EET: 0.86, 95% CI: 0.72-1.02; p=0.08). The EETs-MI associations became significant in analyses further adjusted for DHETs (hazard ratio for 1 SD higher 14,15-EET adjusted for 14,15-DHET: 0.76, 95% CI: 0.63-0.91; p=0.004). Elevated EET levels were associated with higher risk of ischemic stroke in primary but not secondary analyses. Three DHET species were associated with higher risk of ischemic stroke in all analyses. INTERPRETATION: Findings from this prospective study complement the extensive studies in animal models showing EETs protect cardiac function and provide new information in humans. Replication is needed to confirm the associations. FUNDING: US National Institutes of Health.
Keywords: Animals; Arachidonic Acids; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Eicosanoids; Humans; Ischemic Stroke; Prospective Studies

Plasma Levels of Advanced Glycation Endproducts and Risk of Cardiovascular Events: Findings From 2 Prospective Cohorts. - Lamprea-Montealegre, Julio A; Arnold, Alice M; McClelland, Robyn L; Mukamal, Kenneth J; Djoussé, Luc; Biggs, Mary L; Siscovick, David S; Tracy, Russell P; Beisswenger, Paul J; Psaty, Bruce M; Ix, Joachim H; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Advanced glycation endproducts (AGEs) have been linked to cardiovascular disease (CVD) in cohorts with and without diabetes. Data are lacking on prospective associations of various α-dicarbonyl-derived AGEs and incident CVD in the general population. We tested the hypothesis that major plasma AGEs are associated with new-onset CVD in 2 population-based cohorts of differing age and comorbidities. Methods and Results Analyses involved a random subcohort (n=466) from the Cardiovascular Health Study and a case-cohort sample (n=1631) from the Multi-Ethnic Study of Atherosclerosis. Five AGEs and 2 oxidative products were measured by liquid chromatography tandem mass spectrometry. Associations with CVD (myocardial infarction and stroke) were evaluated with Cox regression. Participants in the Cardiovascular Health Study were older than the Multi-Ethnic Study of Atherosclerosis, and had more comorbidities, along with higher levels of all AGEs. During median follow-up of 11 years, 439 participants in the Multi-Ethnic Study of Atherosclerosis and 200 in the Cardiovascular Health Study developed CVD. After multivariable adjustment, carboxymethyl-lysine, 3-deoxyglucosone hydroimidazolones and a summary variable of all measured AGEs (principal component 1) were significantly associated with incident CVD in the Cardiovascular Health Study (HRs [95% CI]: 1.20 [1.01, 1.42], 1.45 [1.23, 1.72], and 1.29 [1.06, 1.56], respectively), but not the Multi-Ethnic Study of Atherosclerosis. Oxidative products were not associated with CVD in either cohort. Conclusions We found α-dicarbonyl-derived AGEs to be associated with CVD in an older cohort, but not in a healthier middle-aged/older cohort. Our results suggest that AGEs may exert detrimental cardiovascular effects only under conditions of marked dicarbonyl and oxidative stress. Further investigation of α-dicarbonyl derivatives could lead to potential new strategies for CVD prevention in high-risk older populations.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Glycation End Products, Advanced; Humans; Middle Aged; Risk Factors

Plasma proteomic signature of decline in gait speed and grip strength. - Liu, Xiaojuan; Pan, Stephanie; Xanthakis, Vanessa; Vasan, Ramachandran S; Psaty, Bruce M; Austin, Thomas R; Newman, Anne B; Sanders, Jason L; Wu, Chenkai; Tracy, Russell P; Gerszten, Robert E; Odden, Michelle C (Aging Cell, 2022)
The biological mechanisms underlying decline in physical function with age remain unclear. We examined the plasma proteomic profile associated with longitudinal changes in physical function measured by gait speed and grip strength in community-dwelling adults. We applied an aptamer-based platform to assay 1154 plasma proteins on 2854 participants (60% women, aged 76 years) in the Cardiovascular Health Study (CHS) in 1992-1993 and 1130 participants (55% women, aged 54 years) in the Framingham Offspring Study (FOS) in 1991-1995. Gait speed and grip strength were measured annually for 7 years in CHS and at cycles 7 (1998-2001) and 8 (2005-2008) in FOS. The associations of individual protein levels (log-transformed and standardized) with longitudinal changes in gait speed and grip strength in two populations were examined separately by linear mixed-effects models. Meta-analyses were implemented using random-effects models and corrected for multiple testing. We found that plasma levels of 14 and 18 proteins were associated with changes in gait speed and grip strength, respectively (corrected p < 0.05). The proteins most strongly associated with gait speed decline were GDF-15 (Meta-analytic p = 1.58 × 10 ), pleiotrophin (1.23 × 10 ), and TIMP-1 (5.97 × 10 ). For grip strength decline, the strongest associations were for carbonic anhydrase III (1.09 × 10 ), CDON (2.38 × 10 ), and SMOC1 (7.47 × 10 ). Several statistically significant proteins are involved in the inflammatory responses or antagonism of activin by follistatin pathway. These novel proteomic biomarkers and pathways should be further explored as future mechanisms and targets for age-related functional decline.
Keywords: Adult; Female; Gait; Hand Strength; Humans; Independent Living; Male; Proteomics; Walking Speed

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

{A population-based meta-analysis of circulating GFAP for cognition and dementia risk - Gonzales, M. M.; Wiedner, C.; Wang, C. P.; Liu, Q.; Bis, J. C.; Li, Z.; Himali, J. J.; Ghosh, S.; Thomas, E. A.; Parent, D. M.; Kautz, T. F.; Pase, M. P.; et al. (Ann Clin Transl Neurol, 2022)
Expression of glial fibrillary acidic protein (GFAP), a marker of reactive astrocytosis, colocalizes with neuropathology in the brain. Blood levels of GFAP have been associated with cognitive decline and dementia status. However, further examinations at a population-based level are necessary to broaden generalizability to community settings.\ Circulating GFAP levels were assayed using a Simoa HD-1 analyzer in 4338 adults without prevalent dementia from four longitudinal community-based cohort studies. The associations between GFAP levels with general cognition, total brain volume, and hippocampal volume were evaluated with separate linear regression models in each cohort with adjustment for age, sex, education, race, diabetes, systolic blood pressure, antihypertensive medication, body mass index, apolipoprotein E ε4 status, site, and time between GFAP blood draw and the outcome. Associations with incident all-cause and Alzheimer's disease dementia were evaluated with adjusted Cox proportional hazard models. Meta-analysis was performed on the estimates derived from each cohort using random-effects models.\ 0.05). However, each standard deviation unit increase in log-transformed GFAP levels was significantly associated with a 2.5-fold higher risk of incident all-cause dementia (Hazard Ratio [HR]: 2.47 (95% CI: 1.52-4.01)) and Alzheimer's disease dementia (HR: 2.54 [95% CI: 1.42-4.53]) over up to 15-years of follow-up.\ Results support the potential role of circulating GFAP levels for aiding dementia risk prediction and improving clinical trial stratification in community settings.

Prospective study of breakfast frequency and timing and the risk of incident type 2 diabetes in community-dwelling older adults: The Cardiovascular Health Study. - Carew, Allie S; Mekary, Rania A; Kirkland, Susan; Theou, Olga; Siddiqi, Ferhan; Urquhart, Robin; George, Michelle; Blanchard, Chris; Biggs, Mary L; Djoussé, Luc; Mukamal, Kenneth J; Cahill, Leah E (Am J Clin Nutr, 2022)
BACKGROUND: No evidence-based recommendations regarding optimal breakfast frequency and timing and type 2 diabetes mellitus (T2DM) exist for older adults due to limited studies. OBJECTIVE: We sought to prospectively assess relationships between breakfast frequency and timing and T2DM risk among older adults and determine whether these depended on gender or cardiometabolic risk factors. METHODS: Weekly breakfast frequency and usual daily breakfast time were assessed by questionnaire at baseline in 3,747 older adults (aged ≥65 years) from the Cardiovascular Health Study (CHS) who were free of cancer and T2DM and followed for 17.6 years. Multivariable-adjusted hazard ratios (aHR) with 95% confidence intervals (CI) estimated from Cox proportional hazards models were used to quantify associations with T2DM. RESULTS: Most CHS participants (median age: 74 years; interquartile range: 71, 78) consumed breakfast daily (85.5%), and 73% had their first daily eating occasion between 07:00-09:00 hours, which were associated with higher socioeconomic status, factors that are indicative of a healthier lifestyle, and lower levels of cardiometabolic risk indicators at baseline. During follow-up, 547 T2DM cases were documented. No strong evidence was observed between breakfast frequency and risk of T2DM. Compared to participants whose breakfast timing (first eating occasion of the day) was 07:00-09:00, those who broke fast after 09:00 had an aHR for T2DM of 0.71 (95% CI: 0.51, 0.99). This association was present in participants with impaired fasting glucose at baseline (0.61; 0.39, 0.95) but not in those without (0.83; 0.50, 1.38)). No associations between eating frequency or timing and T2DM were observed within other pre-specified subgroups. CONCLUSIONS: Eating breakfast daily was not associated with either higher or lower risk of T2DM in this cohort of older adults, while a later (after 09:00) daily first eating occasion time was associated with lower T2DM risk in participants with impaired fasting glucose at baseline.

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

PUFA ω-3 and ω-6 biomarkers and sleep: a pooled analysis of cohort studies on behalf of the Fatty Acids and Outcomes Research Consortium (FORCE). - Murphy, Rachel A; Tintle, Nathan; Harris, William S; Darvishian, Maryam; Marklund, Matti; Virtanen, Jyrki K; Hantunen, Sari; de Mello, Vanessa D; Tuomilehto, Jaakko; Lindström, Jaana; Bolt, Matthew A; Brouwer, Ingeborg A; et al. (Am J Clin Nutr, 2022)
BACKGROUND: n-3 and n-6 PUFAs have physiologic roles in sleep processes, but little is known regarding circulating n-3 and n-6 PUFA and sleep parameters. OBJECTIVES: We sought to assess associations between biomarkers of n-3 and n-6 PUFA intake with self-reported sleep duration and difficulty falling sleeping in the Fatty Acids and Outcome Research Consortium. METHODS: Harmonized, de novo, individual-level analyses were performed and pooled across 12 cohorts. Participants were 35-96 y old and from 5 nations. Circulating measures included α-linolenic acid (ALA), EPA, docosapentaenoic acid (DPA), DHA, EPA + DPA + DHA, linoleic acid, and arachidonic acid. Sleep duration (10 cohorts, n = 18,791) was categorized as short (≤6 h), 7-8 h (reference), or long (≥9 h). Difficulty falling asleep (8 cohorts, n = 12,500) was categorized as yes or no. Associations between PUFAs, sleep duration, and difficulty falling sleeping were assessed by cross-sectional multinomial logistic regression using standardized protocols and covariates. Cohort-specific multivariable-adjusted ORs per quintile of PUFAs were pooled with inverse-variance weighted meta-analysis. RESULTS: In pooled analysis adjusted for sociodemographic characteristics and health status, participants with higher very long-chain n-3 PUFAs were less likely to have long sleep duration. In the top compared with the bottom quintiles, the multivariable-adjusted ORs (95% CIs) for long sleep were 0.78 (95% CI: 0.65, 0.95) for DHA and 0.76 (95% CI: 0.63, 0.93) for EPA + DPA + DHA. Significant associations for ALA and n-6 PUFA with short sleep duration or difficulty falling sleeping were not identified. CONCLUSIONS: Participants with higher concentrations of very long-chain n-3 PUFAs were less likely to have long sleep duration. While objective biomarkers reduce recall bias and misclassification, the cross-sectional design limits assessment of the temporal nature of this relation. These novel findings across 12 cohorts highlight the need for experimental and biological assessments of very long-chain n-3 PUFAs and sleep duration.
Keywords: Biomarkers; Cohort Studies; Cross-Sectional Studies; Fatty Acids; Fatty Acids, Omega-3; Humans; Outcome Assessment, Health Care; Sleep

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Sleep problems and risk of cancer incidence and mortality in an older cohort: The Cardiovascular Health Study (CHS). - Sillah, Arthur; Watson, Nathaniel F; Peters, Ulrike; Biggs, Mary L; Nieto, F Javier; Li, Christopher I; Gozal, David; Thornton, Timothy; Barrie, Sonnah; Phipps, Amanda I (Cancer Epidemiol, 2022)
BACKGROUND: Sleep problems (SP) can indicate underlying sleep disorders, such as obstructive sleep apnea, which may adversely impact cancer risk and mortality. METHODS: We assessed the association of baseline and longitudinal sleep apnea and insomnia symptoms with incident cancer (N = 3930) and cancer mortality (N = 4580) in the Cardiovascular Health Study. We used Cox proportional hazards regression to calculate adjusted hazard ratios (HR) and 95% confidence intervals (CI) to evaluate the associations. RESULTS: Overall, 885 incident cancers and 804 cancer deaths were identified over a median follow-up of 12 and 14 years, respectively. Compared to participants who reported no sleep apnea symptoms, the risk of incident cancer was inversely associated [(HR (95%CI)] with snoring [0.84 (0.71, 0.99)]. We noted an elevated prostate cancer incidence for apnea [2.34 (1.32, 4.15)] and snoring [1.69 (1.11, 2.57)]. We also noted an elevated HR for lymphatic or hematopoietic cancers [daytime sleepiness: 1.81 (1.06, 3.08)]. We found an inverse relationship for cancer mortality with respect to snoring [0.73 (0.62, 0.8)] and apnea [(0.69 (0.51, 0.94))]. We noted a significant inverse relationship between difficulty falling asleep and colorectal cancer death [0.32 (0.15, 0.69)] and snoring with lung cancer death [0.56 (0.35, 0.89)]. CONCLUSIONS: The relationship between SP and cancer risk and mortality was heterogeneous. Larger prospective studies addressing more cancer sites, molecular type-specific associations, and better longitudinal SP assessments are needed for improved delineation of SP-cancer risk dyad.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epi-demiologic evidence supporting the importance of genetic factors influencing OSA, but limited data implicating specific genes. METHODS: Leveraging high depth genomic sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the Cleve-land Family Study (CFS) followed by multi-stage gene-based association analyses in independent cohorts to search for rare variants contributing to OSA severity as assessed by the apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. RESULTS: Linkage analysis in CFS identified a suggestive linkage peak on chromosome 7q31 (LOD=2.31). Gene-based analysis identified 21 non-coding rare variants in Caveolin-1 (CAV1) associated with lower AHI after accounting for multiple comparisons (p=7.4×10-8). These non-coding variants together significantly contributed to the linkage evidence (p<10-3). Follow-up anal-ysis revealed significant associations between these variants and increased CAV1 expression, and increased CAV1 expression in peripheral monocytes was associated with lower AHI (p=0.024) and higher minimum overnight oxygen saturation (p=0.007). CONCLUSION: Rare variants in CAV1, a membrane scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher CAV1 gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.

{Trans Fatty Acid Biomarkers and Incident Type 2 Diabetes: Pooled Analysis of 12 Prospective Cohort Studies in the Fatty Acids and Outcomes Research Consortium (FORCE) - Lai, H. T. M.; Imamura, F.; Korat, A. V. A.; Murphy, R. A.; Tintle, N.; Bassett, J. K.; Chen, J.; ger, J.; Chien, K. L.; Senn, M.; Wood, A. C.; Forouhi, N. G.; et al. (Diabetes Care, 2022)
Trans fatty acids (TFAs) have harmful biologic effects that could increase the risk of type 2 diabetes (T2D), but evidence remains uncertain. We aimed to investigate the prospective associations of TFA biomarkers and T2D by conducting an individual participant-level pooled analysis.\ 18 years without prevalent diabetes. Each cohort conducted de novo harmonized analyses using a prespecified protocol, and findings were pooled using inverse-variance weighted meta-analysis. Heterogeneity was explored by prespecified between-study and within-study characteristics.\ 0.1).\ Circulating individual trans-18:2 TFA biomarkers were not associated with risk of T2D, while trans-16:1n-9, total trans-18:1, and total trans-18:2 were inversely associated. Findings may reflect the influence of mixed TFA sources (industrial vs. natural ruminant), a general decline in TFA exposure due to policy changes during this period, or the relatively limited range of TFA levels.

Whole exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Boerwinkle, Eric; Cushman, Mary; Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII, and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium and the National Heart, Lung, and Blood Institute's Exome Sequencing Project (ESP). Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in FGG (with fibrinogen, p = 9.1x10-13), F7 (with factor VII, p = 1.3x10-72; seven novel variants), and VWF (with factor VIII and vWF; p = 3.2x10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; p = 4.2x10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to African Americans (rs3211938) in CD36. This variant has previously been linked to dyslipidemia but not with levels of a hemostatic factor. These efforts represent the largest integration of whole exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldorsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-Exome Sequencing Study Identifies Four Novel Gene Loci Associated with Diabetic Kidney Disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Metcalf, Ginger; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2022)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease (CKD) and diabetes. Our two-stage whole-exome sequencing study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort (CRIC) and Atherosclerosis Risk in Communities (ARIC) studies (stage-1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine (TOPMed) participants (stage-2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex, and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test (SKAT-O) implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds (95% confidence interval: 33.6, 1105) of DKD compared with non-carriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% confidence interval: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.

{Whole-Genome Sequencing Association Analyses of Stroke and Its Subtypes in Ancestrally Diverse Populations From Trans-Omics for Precision Medicine Project - Hu, Y.; Haessler, J. W.; Manansala, R.; Wiggins, K. L.; Moscati, A.; Beiser, A.; Heard-Costa, N. L.; Sarnowski, C.; Raffield, L. M.; Chung, J.; Marini, S.; Anderson, C. D.; et al. (Stroke, 2022)
Stroke is the leading cause of death and long-term disability worldwide. Previous genome-wide association studies identified 51 loci associated with stroke (mostly ischemic) and its subtypes among predominantly European populations. Using whole-genome sequencing in ancestrally diverse populations from the Trans-Omics for Precision Medicine (TOPMed) Program, we aimed to identify novel variants, especially low-frequency or ancestry-specific variants, associated with all stroke, ischemic stroke and its subtypes (large artery, cardioembolic, and small vessel), and hemorrhagic stroke and its subtypes (intracerebral and subarachnoid).\ Whole-genome sequencing data were available for 6833 stroke cases and 27 116 controls, including 22 315 European, 7877 Black, 2616 Hispanic/Latino, 850 Asian, 54 Native American, and 237 other ancestry participants. In TOPMed, we performed single variant association analysis examining 40 million common variants and aggregated association analysis focusing on rare variants. We also combined TOPMed European populations with over 28 000 additional European participants from the UK BioBank genome-wide array data through meta-analysis.\ .\ We represent the first association analysis for stroke and its subtypes using whole-genome sequencing data from ancestrally diverse populations. While our findings suggest the potential benefits of combining whole-genome sequencing data with populations of diverse genetic backgrounds to identify possible low-frequency or ancestry-specific variants, they also highlight the need to increase genome coverage and sample sizes.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.

Association of Immune Cell Subsets with Incident Hip Fracture: The Cardiovascular Health Study. - Elam, Rachel E; Bůzková, Petra; Delaney, Joseph A C; Fink, Howard A; Barzilay, Joshua I; Carbone, Laura D; Saha, Rick; Robbins, John A; Mukamal, Kenneth J; Valderrábano, Rodrigo J; Psaty, Bruce M; Tracy, Russell P; et al. (Calcif Tissue Int, 2023)
In this study, we aimed to evaluate the association of innate and adaptive immune cell subsets in peripheral blood mononuclear cells (PBMCs) with hip fracture. To conduct this study, we used data from the Cardiovascular Health Study (CHS), a U.S. multicenter observational cohort of community-dwelling men and women aged ≥ 65 years. Twenty-five immune cell phenotypes were measured by flow cytometry from cryopreserved PBMCs of CHS participants collected in 1998-1999. The natural killer (NK), γδ T, T helper 17 (Th17), and differentiated/senescent CD4CD28 T cell subsets were pre-specified as primary subsets of interest. Hip fracture incidence was assessed prospectively by review of hospitalization records. Multivariable Cox hazard models evaluated associations of immune cell phenotypes with incident hip fracture in sex-stratified and combined analyses. Among 1928 persons, 259 hip fractures occurred over a median 9.7 years of follow-up. In women, NK cells were inversely associated with hip fracture [hazard ratio (HR) 0.77, 95% confidence interval (CI) 0.60-0.99 per one standard deviation higher value] and Th17 cells were positively associated with hip fracture [HR 1.18, 95% CI 1.01-1.39]. In men, γδ T cells were inversely associated with hip fracture [HR 0.60, 95% CI 0.37-0.98]. None of the measured immune cell phenotypes were significantly associated with hip fracture incidence in combined analyses. In this large prospective cohort of older adults, potentially important sex differences in the associations of immune cell phenotypes and hip fracture were identified. However, immune cell phenotypes had no association with hip fracture in analyses combining men and women.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer's disease (AD) and AD related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from nine diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5 to 20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs. ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed Mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (Beta=0.04; 95% CI 0.02, 0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the US. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Boerwinkle, Eric; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.

Carriers of rare damaging genetic variants are at lower risk of atherosclerotic disease. - Georgakis, Marios K; Malik, Rainer; Hasbani, Natalie R; Shakt, Gabrielle; Morrison, Alanna C; Tsao, Noah L; Judy, Renae; Mitchell, Braxton D; Xu, Huichun; Montasser, May E; Do, Ron; Kenny, Eimear E; et al. (medRxiv, 2023)
BACKGROUND: The CCL2/CCR2 axis governs monocyte trafficking and recruitment to atherosclerotic lesions. Human genetic analyses and population-based studies support an association between circulating CCL2 levels and atherosclerosis. Still, it remains unknown whether pharmacological targeting of CCR2, the main CCL2 receptor, would provide protection against human atherosclerotic disease. METHODS: In whole-exome sequencing data from 454,775 UK Biobank participants (40-69 years), we identified predicted loss-of-function (LoF) or damaging missense (REVEL score >0.5) variants within the gene. We prioritized variants associated with lower monocyte count (p<0.05) and tested associations with vascular risk factors and risk of atherosclerotic disease over a mean follow-up of 14 years. The results were replicated in a pooled cohort of three independent datasets (TOPMed, deCODE and Penn Medicine BioBank; total n=441,445) and the effect of the most frequent damaging variant was experimentally validated. RESULTS: A total of 45 predicted LoF or damaging missense variants were identified in the gene, 4 of which were also significantly associated with lower monocyte count, but not with other white blood cell counts. Heterozygous carriers of these variants were at a lower risk of a combined atherosclerosis outcome, showed a lower burden of atherosclerosis across four vascular beds, and were at a lower lifetime risk of coronary artery disease and myocardial infarction. There was no evidence of association with vascular risk factors including LDL-cholesterol, blood pressure, glycemic status, or C-reactive protein. Using a cAMP assay, we found that cells transfected with the most frequent damaging variant (3:46358273:T:A, M249K, 547 carriers, frequency: 0.14%) show a decrease in signaling in response to CCL2. The associations of the M249K variant with myocardial infarction were consistent across cohorts (OR : 0.62 95%CI: 0.39-0.96; OR : 0.64 95%CI: 0.34-1.19; OR : 0.64 95%CI: 0.45-0.90). In a phenome-wide association study, we found no evidence for higher risk of common infections or mortality among carriers of damaging variants. CONCLUSIONS: Heterozygous carriers of damaging variants have a lower burden of atherosclerosis and lower lifetime risk of myocardial infarction. In conjunction with previous evidence from experimental and epidemiological studies, our findings highlight the translational potential of CCR2-targeting as an atheroprotective approach.

Circulating differentiated and senescent lymphocyte subsets and incident diabetes risk in older adults: The Cardiovascular Health Study. - Olson, Nels C; Doyle, Margaret F; Bůzková, Petra; Huber, Sally A; de Boer, Ian H; Sitlani, Colleen M; Tracy, Russell P; Psaty, Bruce M; Mukamal, Kenneth J; Delaney, Joseph A (Endocrinol Diabetes Metab, 2023)
INTRODUCTION: Cellular senescence is a feature of aging implicated in the pathophysiology of diabetes mellitus (DM). Whether senescent lymphocytes are associated with the future occurrence of DM is uncertain. METHODS: We used cryopreserved peripheral blood mononuclear cells collected from 1860 Cardiovascular Health Study participants (average age 80.2 years) and flow cytometry immunophenotyping to evaluate the longitudinal relationships of naive (CD45RA ), memory (CD45RO ), senescent (CD28 ), and T effector memory RA (TEMRA) (CD28 CD57 CD45RA ) CD4 and CD8 T cells, and memory B cells (CD19 CD27 ), with the risk of incident DM. In exploratory analyses we evaluated the relationships of 13 additional innate lymphocyte and CD4 and CD8 subsets with incident DM risk. RESULTS: Over a median follow-up time of 8.9 years, 155 cases of incident DM occurred. In Cox models adjusted for demographic variables (age, sex, race, study site and flow cytometry analytical batch) or diabetes risk factors (demographic variables plus education, body mass index, smoking status, alcohol use, systolic blood pressure, hypertension medication use and physical activity), no significant associations were observed for any CD4 , CD8 or CD19 cell phenotypes with incident DM. CONCLUSIONS: These results suggest the frequencies of naive, memory and senescent T cells and memory B cells are not strongly associated with incident DM risk in older adults.
Keywords: CD28 Antigens; CD8-Positive T-Lymphocytes; Cellular Senescence; Diabetes Mellitus; Leukocytes, Mononuclear; Lymphocyte Subsets

Circulating Growth Differentiation Factors 11 and 8, Their Antagonists Follistatin and Follistatin-like-3, and Risk of Heart Failure in Elders. - Kizer, Jorge R; Patel, Sheena; Ganz, Peter; Newman, Anne B; Bhasin, Shalender; Lee, Se-Jin; Cawthon, Peggy M; LeBrasseur, Nathan; Shah, Sanjiv J; Psaty, Bruce M; Tracy, Russell P; Cummings, Steven R (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Heterochronic parabiosis has identified growth differentiation factor (GDF)-11 as a potential means of cardiac rejuvenation, but findings have been inconsistent. A major barrier has been lack of assay specificity for GDF-11 and its homolog GDF-8. METHODS: We tested the hypothesis that GDF-11 and GDF-8, and their major antagonists follistatin and follistatin-like (FSTL)-3, are associated with incident heart failure (HF) and its subtypes in elders. Based on validation experiments, we used liquid chromatography tandem mass spectrometry to measure total serum GDF-11 and GDF-8, along with follistatin and follistatin-like (FSTL)-3 by immunoassay, in two longitudinal cohorts of older adults. RESULTS: In 2,599 participants (age 75.2±4.3) followed for 10.8±5.6 years, 721 HF events occurred. After adjustment, neither GDF-11 (HR per doubling: 0.93 [0.67, 1.30]) nor GDF-8 (HR: 1.02 per doubling [0.83, 1.27]) was associated with incident HF or its subtypes. Positive associations with HF were detected for follistatin (HR: 1.15 [1.00, 1.32]) and FLST-3 (HR: 1.38 [1.03, 1.85]), and with HF with preserved ejection fraction for FSTL-3 (HR: 1.77 [1.03, 3.02]). (All HRs per doubling of biomarker.) FSTL-3 associations with HF appeared stronger at higher follistatin levels and vice versa, and also for men, Blacks and lower kidney function. CONCLUSIONS: Among older adults, serum follistatin and FSTL-3, but not GDF-11 or GDF-8, were associated with incident HF. These findings do not support the concept that low serum levels of total GDF-11 or GDF-8 contribute to HF late in life, but do implicate transforming growth factor-βsuperfamily pathways as potential therapeutic targets.

Circulating Omega-3 and Omega-6 Fatty Acids, Cognitive Decline, and Dementia in Older Adults. - de Oliveira Otto, Marcia C; Wu, Jason H Y; Thacker, Evan L; Lai, Heidi Tsz Mung; Lemaitre, Rozenn N; Padhye, Nikhil; Song, Xiaoling; King, Irena B; Lopez, Oscar; Siscovick, David S; Mozaffarian, Dariush (J Alzheimers Dis, 2023)
BACKGROUND: Comprising nearly 35% of brain lipids, polyunsaturated fatty acids (PUFA) are essential for optimal brain function. However, the role of PUFA on cognitive health outcomes later in life is largely unknown. OBJECTIVE: We investigated prospective associations of plasma phospholipid omega-3 (ALA [18 : 3], EPA [20 : 5], DPA [22 : 5], DHA [22 : 6]) and omega-6 (LA [18 : 2], AA [20 : 4]) PUFA with cognitive decline, risk of cognitive impairment and dementia among adults aged≥65 years in the Cardiovascular Health Study. METHODS: Circulating fatty acid concentrations were measured serially at baseline (1992/1993), 6 years, and 13 years later. Cognitive decline and impairment were assessed using the 100-point Modified Mini-Mental State Examination (3MSE) up to 7 times. Clinical dementia was identified using adjudicated neuropsychological tests, and ICD-9 codes. RESULTS: Among 3,564 older adults free of stroke and dementia at baseline, cognitive function declined annually by approximately -0.5 3MSE points; 507 participants developed cognitive impairment and 499 dementia over up to 23 years of follow-up. In multivariable models, higher circulating arachidonic acid (AA) concentrations were associated with slower cognitive decline and lower dementia risk, with associations growing stronger with greater length of follow-up (hazard ratio [HR,95% CI] of dementia per interquintile range, 0.74 [0.56-0.97] at 5 years, and 0.53 [0.37-0.77] at 15 years). Circulating docosapentaenoic (DPA) concentrations were associated with slower cognitive decline and lower risk of cognitive impairment (extreme-quintile HR, 0.72 [95% CI: 0.55, 0.95]). Findings were generally null or inconsistent for other omega-3 or omega-6 PUFA. CONCLUSION: Circulating AA and DPA, but not other PUFA, are associated with slower rate of cognitive decline and lower risk of dementia or cognitive impairment later in life.

Clonal Hematopoiesis of Indeterminate Potential (CHIP) and Incident Type 2 Diabetes Risk. - Tobias, Deirdre K; Manning, Alisa K; Wessel, Jennifer; Raghavan, Sridharan; Westerman, Kenneth E; Bick, Alexander G; DiCorpo, Daniel; Whitsel, Eric A; Collins, Jason; Correa, Adolfo; Cupples, L Adrienne; Dupuis, Josée; et al. (Diabetes Care, 2023)
OBJECTIVE: Clonal hematopoiesis of indeterminate potential (CHIP) is an aging-related accumulation of somatic mutations in hematopoietic stem cells, leading to clonal expansion. CHIP presence has been implicated in atherosclerotic coronary heart disease (CHD) and all-cause mortality, but its association with incident type 2 diabetes (T2D) is unknown. We hypothesized that CHIP is associated with elevated risk of T2D. RESEARCH DESIGN AND METHODS: CHIP was derived from whole-genome sequencing of blood DNA in the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine (TOPMed) prospective cohorts. We performed analysis for 17,637 participants from six cohorts, without prior T2D, cardiovascular disease, or cancer. We evaluated baseline CHIP versus no CHIP prevalence with incident T2D, including associations with DNMT3A, TET2, ASXL1, JAK2, and TP53 variants. We estimated multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) with adjustment for age, sex, BMI, smoking, alcohol, education, self-reported race/ethnicity, and combined cohorts' estimates via fixed-effects meta-analysis. RESULTS: Mean (SD) age was 63.4 (11.5) years, 76% were female, and CHIP prevalence was 6.0% (n = 1,055) at baseline. T2D was diagnosed in n = 2,467 over mean follow-up of 9.8 years. Participants with CHIP had 23% (CI = 1.04, 1.45) higher risk of T2D than those with no CHIP. Specifically, higher risk was for TET2 (HR 1.48; CI = 1.05, 2.08) and ASXL1 (HR 1.76; CI = 1.03, 2.99) mutations; DNMT3A was nonsignificant (HR 1.15; CI = 0.93, 1.43). Statistical power was limited for JAK2 and TP53 analyses. CONCLUSIONS: CHIP was associated with higher incidence of T2D. CHIP mutations located on genes implicated in CHD and mortality were also related to T2D, suggesting shared aging-related pathology.

Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Complexities of cerebral small vessel disease, blood pressure, and dementia relationship: new insights from genetics. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (medRxiv, 2023)
IMPORTANCE: There is increasing recognition that vascular disease, which can be treated, is a key contributor to dementia risk. However, the contribution of specific markers of vascular disease is unclear and, as a consequence, optimal prevention strategies remain unclear. OBJECTIVE: To disentangle the causal relation of several key vascular traits to dementia risk: (i) white matter hyperintensity (WMH) burden, a highly prevalent imaging marker of covert cerebral small vessel disease (cSVD); (ii) clinical stroke; and (iii) blood pressure (BP), the leading risk factor for cSVD and stroke, for which efficient therapies exist. To account for potential epidemiological biases inherent to late-onset conditions like dementia. DESIGN SETTING AND PARTICIPANTS: This study first explored the association of genetically determined WMH, BP levels and stroke risk with AD using summary-level data from large genome-wide association studies (GWASs) in a two-sample Mendelian randomization (MR) framework. Second, leveraging individual-level data from large longitudinal population-based cohorts and biobanks with prospective dementia surveillance, the association of weighted genetic risk scores (wGRSs) for WMH, BP, and stroke with incident all-cause-dementia was explored using Cox-proportional hazard and multi-state models. The data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined levels of WMH volume and BP (systolic, diastolic and pulse blood pressures) and genetic liability to stroke. MAIN OUTCOMES AND MEASURES: The summary-level MR analyses focused on the outcomes from GWAS of clinically diagnosed AD (n-cases=21,982) and GWAS additionally including self-reported parental history of dementia as a proxy for AD diagnosis (AD , n-cases=53,042). For the longitudinal analyses, individual-level data of 157,698 participants with 10,699 incident all-cause-dementia were studied, exploring AD, vascular or mixed dementia in secondary analyses. RESULTS: In the two-sample MR analyses, WMH showed strong evidence for a causal association with increased risk of AD (OR, 1.16; 95%CI:1.05-1.28; P=.003) and AD (OR, 1.28; 95%CI:1.07-1.53; P=.008), after accounting for genetically determined pulse pressure for the latter. Genetically predicted BP traits showed evidence for a protective association with both clinically defined AD and AD , with evidence for confounding by shared genetic instruments. In longitudinal analyses the wGRSs for WMH, but not BP or stroke, showed suggestive association with incident all-cause-dementia (HR, 1.02; 95%CI:1.00-1.04; P=.06). BP and stroke wGRSs were strongly associated with mortality but there was no evidence for selective survival bias during follow-up. In secondary analyses, polygenic scores with more liberal instrument definition showed association of both WMH and stroke with all-cause-dementia, AD, and vascular or mixed dementia; associations of stroke, but not WMH, with dementia outcomes were markedly attenuated after adjusting for interim stroke. CONCLUSION: These findings provide converging evidence that WMH is a leading vascular contributor to dementia risk, which may better capture the brain damage caused by BP (and other etiologies) than BP itself and should be targeted in priority for dementia prevention in the population. KEY POINTS: Do instrumental variable analyses leveraging genetic information provide evidence for a causal association of various vascular traits with Alzheimer's disease (AD) and all-cause-dementia? How do these associations compare for white matter hyperintensity (WMH) burden, a highly prevalent marker of covert cerebral small vessel disease (cSVD), stroke, and blood pressure traits, the strongest known risk factor for cSVD and stroke? Using Mendelian randomization (MR) leveraging large, published genome-wide association studies, this study showed a putative causal association of larger WMH burden with increased AD risk after accounting for pulse pressure effects, and some evidence for association of lower BP with AD risk with possible confounding by shared genetic instruments. Longitudinal analyses on individual-level data also supported association of genetically determined WMH with incident all-cause-dementia and AD, independently of interim stroke. This study using complementary genetic epidemiology approaches, identified increasing WMH burden to be associated with dementia and AD risk, suggesting the association as specific for cSVD and independent of BP and stroke.

The determinants of fasting and post-load non-esterified fatty acids in older adults: The cardiovascular health study. - Bene-Alhasan, Yakubu; Siscovick, David S; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell; Djoussé, Luc; Mukamal, Kenneth J (Metabol Open, 2023)
AIM: Non-esterified fatty acids (NEFA) are potential targets for prevention of key cardiometabolic diseases of aging, but their population-level correlates remain uncertain. We sought to identify modifiable factors associated with fasting and post-load NEFA levels in older adults. METHODS: We used linear regression to determine the cross-sectional associations of demographic, anthropometric, and lifestyle characteristics and medication use with serum fasting and post-load NEFA concentrations amongst community-dwelling older adults enrolled in the Cardiovascular Health Study (n = 1924). RESULTS: Fasting NEFA levels generally demonstrated a broader set of determinants, while post-load NEFA were more consistently associated with metabolic factors. Waist circumference and weight were associated with higher fasting and post-load NEFA. Cigarette smoking and caffeine intake were associated with lower levels of both species, and moderate alcohol intake was associated with higher fasting levels whereas greater consumption was associated with lower post-load levels. Unique factors associated with higher fasting NEFA included female sex, higher age, loop and thiazide diuretic use and calcium intake, while factors associated with lower fasting levels included higher educational attainment, beta-blocker use, and protein intake. Hours spent sleeping during the daytime were associated with higher post-load NEFA, while DASH score was associated with lower levels. CONCLUSION: Fasting and post-load NEFA have both common and unique modifiable risk factors, including sociodemographics, anthropometric, medications, and diet. Post-load NEFA were particularly sensitive to metabolic factors, while a broader range of determinants were associated with fasting levels. These factors warrant study as targets for lowering levels of NEFA in older adults.

Determinants of mosaic chromosomal alteration fitness. - Pershad, Yash; Mack, Taralynn; Poisner, Hannah; Jakubek, Yasminka A; Stilp, Adrienne M; Mitchell, Braxton D; Lewis, Joshua P; Boerwinkle, Eric; Loos, Ruth J; Chami, Nathalie; Wang, Zhe; Barnes, Kathleen; et al. (medRxiv, 2023)
Clonal hematopoiesis (CH) is characterized by the acquisition of a somatic mutation in a hematopoietic stem cell that results in a clonal expansion. These driver mutations can be single nucleotide variants in cancer driver genes or larger structural rearrangements called mosaic chromosomal alterations (mCAs). The factors that influence the variations in mCA fitness and ultimately result in different clonal expansion rates are not well-understood. We used the Passenger-Approximated Clonal Expansion Rate (PACER) method to estimate clonal expansion rate for 6,381 individuals in the NHLBI TOPMed cohort with gain, loss, and copy-neutral loss of heterozygosity mCAs. Our estimates of mCA fitness were correlated (R = 0.49) with an alternative approach that estimated fitness of mCAs in the UK Biobank using a theoretical probability distribution. Individuals with lymphoid-associated mCAs had a significantly higher white blood cell count and faster clonal expansion rate. In a cross-sectional analysis, genome-wide association study of estimates of mCA expansion rate identified , , and locus variants as modulators of mCA clonal expansion rate.

{Early-onset Alzheimer's disease explained by polygenic risk of late-onset disease? - Mantyh, W. G.; Cochran, J. N.; Taylor, J. W.; Broce, I. J.; Geier, E. G.; Bonham, L. W.; Anderson, A. G.; Sirkis, D. W.; Joie, R.; Iaccarino, L.; Chaudhary, K.; Edwards, L.; et al. (Alzheimers Dement (Amst), 2023)
There is a unique genetic architecture of early- versus late-onset Alzheimer's disease (AD).Late-onset AD polygenic risk is not an explanation for early-onset AD.Polygenic risk of late-onset AD does not predict early-onset AD biology.Unique genetic architecture of early- versus late-onset AD parallels AD heterogeneity.

Evaluation of Associations of Growth Differentiation Factor-11, Growth Differentiation Factor-8 and their Binding Proteins Follistatin and Follistatin-like protein-3 with Dementia and Cognition. - Newman, Anne B; Patel, Sheena; Kizer, Jorge; Lee, Se-Jin; Bhasin, Shalinder; Cawthon, Peggy; LeBrasseur, Nathan; Tracy, Russel P; Ganz, Peter; Cummings, Steve (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Studies using heterochronic parabiosis discovered that circulating factors mediate brain aging in animal models. METHODS: We assessed Growth Differentiation Factor (GDF)-11 and GDF-8 using mass spectrometry and inhibitors follistatin and follistatin-like protein-3 (FSTL-3) with ELISA in in the Cardiovascular Health Study (N=1506) and the Health ABC study (N=1237). CLL-11 and Beta 2 microglobulin (B2M) were measured with ELISA in a subset of 400 individuals in Health ABC. Associations were assessed with cognitive function, brain magnetic resonance imaging (MRI) findings (CHS only) and incident dementia using correlations, linear regression and Cox proportional hazards models. RESULTS: In CHS, levels of GDF-11, GDF-8 and follistatin were not correlated cross sectionally with the 3MSE or DSST, brain MRI findings of white matter hyperintensity, atrophy or small infarcts, nor were they associated with incident dementia. FSTL-3 was modestly correlated with poorer cognitive function, greater white matter hyperintensities and atrophy on MRI as well as with incident dementia with an adjusted HR of 1.72 (95% CI=1.13, 2.61) per doubling of FSTL-3. FSTL-3 was not associated with cognition or dementia in Health ABC, but GDF-8 was associated with both. The adjusted HR for incident dementia was 1.50 (95%CI 1.07, 2.10) per doubling of GDF-8. CONCLUSIONS: Total GDF-11 level was not related to cognition or dementia in older adults. Associations of GDF-8 with cognitive outcomes in Health ABC were not expected, but consistent with animal models. Associations of FSTL-3 with cognition, brain abnormalities, and incident dementia in CHS implicates TGF-B superfamily inhibition in the pathogenesis of dementia.

Factors Associated With Circulating Sex Hormones in Men : Individual Participant Data Meta-analyses. - Marriott, Ross J; Murray, Kevin; Adams, Robert J; Antonio, Leen; Ballantyne, Christie M; Bauer, Douglas C; Bhasin, Shalender; Biggs, Mary L; Cawthon, Peggy M; Couper, David J; Dobs, Adrian S; Flicker, Leon; et al. (Ann Intern Med, 2023)
BACKGROUND: Various factors modulate circulating testosterone in men, affecting interpretation of testosterone measurements. PURPOSE: To clarify factors associated with variations in sex hormone concentrations. DATA SOURCES: Systematic literature searches (to July 2019). STUDY SELECTION: Prospective cohort studies of community-dwelling men with total testosterone measured using mass spectrometry. DATA EXTRACTION: Individual participant data (IPD) (9 studies;  = 21 074) and aggregate data (2 studies;  = 4075). Sociodemographic, lifestyle, and health factors and concentrations of total testosterone, sex hormone-binding globulin (SHBG), luteinizing hormone (LH), dihydrotestosterone, and estradiol were extracted. DATA SYNTHESIS: Two-stage random-effects IPD meta-analyses found a nonlinear association of testosterone with age, with negligible change among men aged 17 to 70 years (change per SD increase about the midpoint, -0.27 nmol/L [-7.8 ng/dL] [CI, -0.71 to 0.18 nmol/L {-20.5 to 5.2 ng/dL}]) and decreasing testosterone levels with age for men older than 70 years (-1.55 nmol/L [-44.7 ng/dL] [CI, -2.05 to -1.06 nmol/L {-59.1 to -30.6 ng/dL}]). Testosterone was inversely associated with body mass index (BMI) (change per SD increase, -2.42 nmol/L [-69.7 ng/dL] [CI, -2.70 to -2.13 nmol/L {-77.8 to -61.4 ng/dL}]). Testosterone concentrations were lower for men who were married (mean difference, -0.57 nmol/L [-16.4 ng/dL] [CI, -0.89 to -0.26 nmol/L {-25.6 to -7.5 ng/dL}]); undertook at most 75 minutes of vigorous physical activity per week (-0.51 nmol/L [-14.7 ng/dL] [CI, -0.90 to -0.13 nmol/L {-25.9 to -3.7 ng/dL}]); were former smokers (-0.34 nmol/L [-9.8 ng/dL] [CI, -0.55 to -0.12 nmol/L {-15.9 to -3.5 ng/dL}]); or had hypertension (-0.53 nmol/L [-15.3 ng/dL] [CI, -0.82 to -0.24 nmol/L {-23.6 to -6.9 ng/dL}]), cardiovascular disease (-0.35 nmol/L [-10.1 ng/dL] [CI, -0.55 to -0.15 nmol/L {-15.9 to -4.3 ng/dL}]), cancer (-1.39 nmol/L [-40.1 ng/dL] [CI, -1.79 to -0.99 nmol/L {-51.6 to -28.5 ng/dL}]), or diabetes (-1.43 nmol/L [-41.2 ng/dL] [CI, -1.65 to -1.22 nmol/L {-47.6 to -35.2 ng/dL}]). Sex hormone-binding globulin was directly associated with age and inversely associated with BMI. Luteinizing hormone was directly associated with age in men older than 70 years. LIMITATION: Cross-sectional analysis, heterogeneity between studies and in timing of blood sampling, and imputation for missing data. CONCLUSION: Multiple factors are associated with variation in male testosterone, SHBG, and LH concentrations. Reduced testosterone and increased LH concentrations may indicate impaired testicular function after age 70 years. Interpretation of individual testosterone measurements should account particularly for age older than 70 years, obesity, diabetes, and cancer. PRIMARY FUNDING SOURCE: Medical Research Future Fund, Government of Western Australia, and Lawley Pharmaceuticals. (PROSPERO: CRD42019139668).

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genome-Wide Association Studies and fine-mapping of genomic loci for n-3 and n-6 Polyunsaturated Fatty Acids in Hispanic American and African American Cohorts. - Yang, Chaojie; Veenstra, Jenna; Bartz, Traci; Pahl, Matthew; Hallmark, Brian; Chen, Yii-Der Ida; Westra, Jason; Steffen, Lyn; Brown, Christopher; Siscovick, David; Tsai, Michael; Wood, Alexis; et al. (Res Sq, 2023)
Omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFAs) play critical roles in human health. Prior genome-wide association studies (GWAS) of n-3 and n-6 PUFAs in European Americans from the CHARGE Consortium have documented strong genetic signals in/near the locus on chromosome 11. We performed a GWAS of four n-3 and four n-6 PUFAs in Hispanic American (n = 1454) and African American (n = 2278) participants from three CHARGE cohorts. Applying a genome-wide significance threshold of  < 5 x 10 , we confirmed association of the signal and found evidence of two additional signals (in and ) within 200 kb of the originally reported signal. Outside of the region, we identified novel signals for arachidonic acid (AA) in Hispanic Americans located in/near genes including , , and spanning a > 9 Mb region on chromosome 11 (57.5Mb ~ 67.1Mb). Among these novel signals, we found associations unique to Hispanic Americans, including rs28364240, a missense variant for AA that is common in CHARGE Hispanic Americans but absent in other race/ancestry groups. Our study sheds light on the genetics of PUFAs and the value of investigating complex trait genetics across diverse ancestry populations.

Genome-Wide Interaction Analysis with DASH Diet Score Identified Novel Loci for Systolic Blood Pressure. - Guirette, Melanie; Lan, Jessie; McKeown, Nicola; Brown, Michael R; Chen, Han; de Vries, Paul S; Kim, Hyunju; Rebholz, Casey M; Morrison, Alanna C; Bartz, Traci M; Fretts, Amanda M; Guo, Xiuqing; et al. (medRxiv, 2023)
OBJECTIVE: We examined interactions between genotype and a Dietary Approaches to Stop Hypertension (DASH) diet score in relation to systolic blood pressure (SBP). METHODS: We analyzed up to 9,420,585 biallelic imputed single nucleotide polymorphisms (SNPs) in up to 127,282 individuals of six population groups (91% of European population) from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (CHARGE; n=35,660) and UK Biobank (n=91,622) and performed European population-specific and cross-population meta-analyses. RESULTS: We identified three loci in European-specific analyses and an additional four loci in cross-population analyses at P for interaction < 5e-8. We observed a consistent interaction between rs117878928 at 15q25.1 (minor allele frequency = 0.03) and the DASH diet score (P for interaction = 4e-8; P for heterogeneity = 0.35) in European population, where the interaction effect size was 0.42±0.09 mm Hg (P for interaction = 9.4e-7) and 0.20±0.06 mm Hg (P for interaction = 0.001) in CHARGE and the UK Biobank, respectively. The 1 Mb region surrounding rs117878928 was enriched with -expression quantitative trait loci (eQTL) variants (P = 4e-273) and -DNA methylation quantitative trait loci (mQTL) variants (P = 1e-300). While the closest gene for rs117878928 is , the highest narrow sense heritability accounted by SNPs potentially interacting with the DASH diet score in this locus was for gene at 15q25.1. CONCLUSION: We demonstrated gene-DASH diet score interaction effects on SBP in several loci. Studies with larger diverse populations are needed to validate our findings.

High-risk carotid plaques and incident ischemic stroke in patients with atrial fibrillation in the Cardiovascular Health Study. - Noubiap, Jean Jacques; Thomas, Gijo; Kamtchum-Tatuene, Joseph; Middeldorp, Melissa E; Sanders, Prashanthan (Eur J Neurol, 2023)
BACKGROUND AND PURPOSE: Whether carotid artery disease could improve stroke risk stratification tools in patients with atrial fibrillation (AF) remains uncertain. This study was undertaken to investigate the risk of ischemic stroke associated with occlusive and nonocclusive carotid atherosclerotic disease in patients with AF in the prospective population-based Cardiovascular Health Study. METHODS: We included participants aged ≥65 years with AF. We used multivariable Cox regression analysis to explore the risk of ischemic stroke associated with the percentage of carotid stenosis, plaque irregularity, echogenicity, and vulnerability (markedly irregular, ulcerated, or hypoechoic plaques). RESULTS: A total of 1398 participants were included (55.2% female, 61.7% aged 65-74 years). The maximum carotid stenosis was <50%, 50%-99%, and 100% in 94.5%, 5%, and 0.5% of participants, respectively. High-risk plaques based on echogenicity and plaque irregularity were found in 25.6% and 8.9% of participants, respectively. After a median follow-up of 10.9 years (interquartile range = 7.5-15.6), 298 ischemic strokes were recorded. There was no difference in the incidence of ischemic stroke according to the degree of carotid artery stenosis (p = 0.44), plaque echogenicity (low vs. high risk, p = 0.68), plaque irregularity (low vs. high risk, p = 0.55), and plaque vulnerability (p = 0.86). The CHA₂DS₂-VASc score was associated with an increased risk of ischemic stroke (adjusted hazard ratio = 1.28, 95% confidence interval = 1.18-1.40, p < 0.001). Both maximum grade of stenosis and plaque vulnerability were not associated with incident ischemic stroke (all p > 0.05). CONCLUSIONS: Neither the degree of carotid stenosis nor the presence of vulnerable plaques was associated with incident ischemic stroke in this cohort of individuals with AF. This suggests that carotid disease was probably not a significant contributor to ischemic stroke in this population.
Keywords: Atrial Fibrillation; Carotid Artery Diseases; Carotid Stenosis; Female; Humans; Ischemic Stroke; Male; Plaque, Atherosclerotic; Prospective Studies; Risk Factors; Stroke

Hospital-Acquired Infection at Time of Stroke and Cognitive Decline: The Cardiovascular Health Study. - Cole, Kyril L; Boehme, Amelia K; Thacker, Evan L; Longstreth, W T; Brown, Bruce L; Gale, Shawn D; Hedges, Dawson W; Anderson, Jacqueline K; Elkind, Mitchell S V (Cerebrovasc Dis, 2023)
Introduction Hospital-acquired infections (HAIs) after stroke are associated with additional morbidity and mortality, but whether HAIs increase long-term cognitive decline in stroke patients is unknown. We hypothesized that older adults with incident stroke with HAI experience faster cognitive decline than those having stroke without HAI and those without stroke. Methods We performed a longitudinal analysis in the population-based prospective Cardiovascular Health Study. Medicare-eligible participants aged >65 years with and without incident stroke had cognition assessed annually. HAIs were assessed by hospital discharge codes. Global cognitive function was assessed annually by Modified Mini-Mental State Examination (3MSE) and executive function by Digit Symbol Substitution Test (DSST). We used linear mixed models to estimate the mean decline and 95% confidence intervals (95% CI) for 3MSE and DSST scores by incident stroke and HAI status, adjusted for demographics and vascular risk factors. Results Among 5,443 participants >65 years without previous history of stroke, 393 participants had stroke with HAI (SI), 766 had a stroke only (SO), and 4,284 had no stroke (NS) throughout a maximum 9-year follow-up. For 3MSE, compared with NS participants, SO participants had a similar adjusted mean decline (additional 0.08 points/year, 95%CI -0.15, 0.31), while SI participants had a more rapid decline (additional 0.28 points/year, 95%CI 0.16, 0.40). Adjusted mean decline was 0.20 points/year faster (95%CI -0.05, 0.45) among SI than SO participants. For DSST, compared with NS participants, SO participants had a faster adjusted mean decline (additional 0.17 points/year (95%CI 0.003, 0.33), as did SI participants (additional 0.27 points/year (95%CI 0.19, 0.35). Conclusion Stroke, when accompanied by HAI, leads to a faster long-term decline in cognitive ability than in those without stroke. The clinical and public health implications of the effect of infection on post-stroke cognitive decline warrant further attention.

{Identification of circulating proteins associated with general cognitive function among middle-aged and older adults - Tin, A.; Fohner, A. E.; Yang, Q.; Brody, J. A.; Davies, G.; Yao, J.; Liu, D.; Caro, I.; Lindbohm, J. V.; Duggan, M. R.; Meirelles, O.; Harris, S. E.; et al. (Commun Biol, 2023)
2.0E-4). Proteins implicated as causes or consequences of AD susceptibility may provide new insight into the potential relationship between immunity and AD susceptibility as well as potential therapeutic targets.

loss-of-function variants: Compatible with longevity and associated with resistance to Alzheimer's Disease pathology - Chemparathy, A.; Guen, Y. L.; Chen, S.; Lee, E. G.; Leong, L.; Gorzynski, J.; Xu, G.; Belloy, M.; Kasireddy, N.; Tauber, A. P.; Williams, K.; Stewart, I.; et al. (medRxiv, 2023)
4 or its protein product as a viable therapeutic option.

Machine learning models for blood pressure phenotypes combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchel, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (medRxiv, 2023)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1% to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8% to 5.1% (SBP) and 4.7% to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs.

Mosaic chromosomal alterations in blood across ancestries using whole-genome sequencing. - Jakubek, Yasminka A; Zhou, Ying; Stilp, Adrienne; Bacon, Jason; Wong, Justin W; Ozcan, Zuhal; Arnett, Donna; Barnes, Kathleen; Bis, Joshua C; Boerwinkle, Eric; Brody, Jennifer A; Carson, April P; et al. (Nat Genet, 2023)
Megabase-scale mosaic chromosomal alterations (mCAs) in blood are prognostic markers for a host of human diseases. Here, to gain a better understanding of mCA rates in genetically diverse populations, we analyzed whole-genome sequencing data from 67,390 individuals from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program. We observed higher sensitivity with whole-genome sequencing data, compared with array-based data, in uncovering mCAs at low mutant cell fractions and found that individuals of European ancestry have the highest rates of autosomal mCAs and the lowest rates of chromosome X mCAs, compared with individuals of African or Hispanic ancestry. Although further studies in diverse populations will be needed to replicate our findings, we report three loci associated with loss of chromosome X, associations between autosomal mCAs and rare variants in DCPS, ADM17, PPP1R16B and TET2 and ancestry-specific variants in ATM and MPL with mCAs in cis.
Keywords: Black People; Genome, Human; Genome-Wide Association Study; Hispanic or Latino; Humans; Mosaicism; Precision Medicine

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification. - Kavousi, Maryam; Bos, Maxime M; Barnes, Hanna J; Lino Cardenas, Christian L; Wong, Doris; Lu, Haojie; Hodonsky, Chani J; Landsmeer, Lennart P L; Turner, Adam W; Kho, Minjung; Hasbani, Natalie R; de Vries, Paul S; et al. (Nat Genet, 2023)
Coronary artery calcification (CAC), a measure of subclinical atherosclerosis, predicts future symptomatic coronary artery disease (CAD). Identifying genetic risk factors for CAC may point to new therapeutic avenues for prevention. Currently, there are only four known risk loci for CAC identified from genome-wide association studies (GWAS) in the general population. Here we conducted the largest multi-ancestry GWAS meta-analysis of CAC to date, which comprised 26,909 individuals of European ancestry and 8,867 individuals of African ancestry. We identified 11 independent risk loci, of which eight were new for CAC and five had not been reported for CAD. These new CAC loci are related to bone mineralization, phosphate catabolism and hormone metabolic pathways. Several new loci harbor candidate causal genes supported by multiple lines of functional evidence and are regulators of smooth muscle cell-mediated calcification ex vivo and in vitro. Together, these findings help refine the genetic architecture of CAC and extend our understanding of the biological and potential druggable pathways underlying CAC.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Non-esterified fatty acids and risk of peripheral artery disease in older adults: The cardiovascular health study. - Ahiawodzi, Peter; Solaru, Khendi White; Chaves, Paulo H M; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Newman, Anne; Siscovick, David; Djoussé, Luc; Mukamal, Kenneth J (Atherosclerosis, 2023)
BACKGROUND AND AIMS: Non-esterified fatty acids have been implicated in the pathogenesis of diabetes and cardiovascular disease. No longitudinal study has assessed their effects on peripheral artery disease (PAD). We determined the relationships between NEFAs and incident clinical PAD and abnormal ankle-brachial index (ABI) in a population-based cohort of older persons. METHODS: We evaluated 4575 community living participants aged >65 years who underwent measurement of circulating NEFAs in fasting specimens and ABI in 1992-1993. Participants were assessed annually for clinical PAD until 2015 and underwent repeat ABI in 1998-1999. We used Cox proportional hazards regression to model the associations between NEFAs and risk of clinical PAD and logistic regression to model the associations of NEFAs with incident abnormal ABI. RESULTS: Mean age was 74.8 years, 59% were female, and 17% were Black. NEFAs were associated with higher risk of clinical PAD in unadjusted and adjusted models. The adjusted hazard ratios for incident clinical PAD were 1.51 (95%CI = 1.06-2.13, p = 0.02) across extreme tertiles, and 1.14 (95%CI = 0.99-1.31, p = 0.08) per standard deviation higher NEFA. The corresponding odds ratios for abnormal ABI were 0.95 (95%CI = 0.69-1.32, p = 0.76) across extreme tertiles, and 1.03 (95%CI = 0.89-1.20, p = 0.68) per standard deviation higher NEFA. Relationships appeared similar irrespective of sex, race, or pre-existing cardiovascular disease, but were stronger later than earlier in follow-up. CONCLUSIONS: Higher serum levels of NEFAs are significantly associated with increased likelihood of clinical PAD over long-term follow-up but not with 6-year decline in ABI. NEFAs may offer a potential target for intervention against clinical PAD.

Plasma Proteomic Associations With Incident Ischemic Stroke in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Psaty, Bruce M; Elkind, Mitchell S V; Floyd, James S; Gerszten, Robert E; Shojaie, Ali; Heckbert, Susan R; Bis, Joshua C; Austin, Thomas R; Tirschwell, David L; Delaney, Joseph A C; et al. (Neurology, 2023)
BACKGROUND: Plasma proteomics may elucidate novel insights into the pathophysiology of ischemic stroke (IS), identify biomarkers of IS risk, and guide development of nascent prevention strategies. We evaluated the relationship between the plasma proteome and IS risk in the population-based Cardiovascular Health Study (CHS). METHODS: Eligible CHS participants were free of prevalent stroke and underwent quantification of 1298 plasma proteins using the aptamer-based SOMAScan assay platform from the 1992-1993 study visit. Multivariable Cox proportional hazards regression was used to evaluate associations between a 1-standard deviation increase in the log-2 transformed estimated plasma protein concentrations and incident IS, adjusting for demographics, IS risk factors, and estimated glomerular filtration rate. For proteins independently associated with incident IS, a secondary stratified analysis evaluated associations in subgroups defined by sex and race. Exploratory analyses evaluated plasma proteomic associations with cardioembolic and non-cardioembolic IS as well as proteins associated with IS risk in participants with left atrial dysfunction but without atrial fibrillation. RESULTS: Of 2983 eligible participants, the mean age was 74.3 (± 4.8) years, 61.2% were women, and 15.4% were Black. Over a median follow-up of 12.6 years, 450 participants experienced an incident IS. N-terminal pro-brain natriuretic peptide (NTproBNP, adjusted HR 1.37, 95% CI 1.23-1.53, P=2.08x10) and macrophage metalloelastase (MMP12, adjusted HR 1.30, 95% CI 1.16-1.45, P=4.55x10) were independently associated with IS risk. These two associations were similar in men and women and in Black and non-Black participants. In exploratory analyses, NTproBNP was independently associated with incident cardioembolic IS, E-selectin with incident non-cardioembolic IS, and secreted frizzled-related protein 1 with IS risk in participants with left atrial dysfunction. CONCLUSIONS: In a cohort of older adults, NTproBNP and MMP12 were independently associated with IS risk. We identified plasma proteomic determinants of incident cardioembolic and non-cardioembolic IS and found a novel protein associated with IS risk in those with left atrial dysfunction.

Posttranslational modifications induce autoantibodies with risk prediction capability in patients with small cell lung cancer. - Lastwika, Kristin J; Kunihiro, Andrew; Solan, Joell L; Zhang, Yuzheng; Taverne, Lydia R; Shelley, David; Rho, Jung-Hyun; Randolph, Timothy W; Li, Christopher I; Grogan, Eric L; Massion, Pierre P; Fitzpatrick, Annette L; et al. (Sci Transl Med, 2023)
Small cell lung cancer (SCLC) elicits the generation of autoantibodies that result in unique paraneoplastic neurological syndromes. The mechanistic basis for the formation of such autoantibodies is largely unknown but is key to understanding their etiology. We developed a high-dimensional technique that enables detection of autoantibodies in complex with native antigens directly from patient plasma. Here, we used our platform to screen 1009 human plasma samples for 3600 autoantibody-antigen complexes, finding that plasma from patients with SCLC harbors, on average, fourfold higher disease-specific autoantibody signals compared with plasma from patients with other cancers. Across three independent SCLC cohorts, we identified a set of common but previously unknown autoantibodies that are produced in response to both intracellular and extracellular tumor antigens. We further characterized several disease-specific posttranslational modifications within extracellular proteins targeted by these autoantibodies, including citrullination, isoaspartylation, and cancer-specific glycosylation. Because most patients with SCLC have metastatic disease at diagnosis, we queried whether these autoantibodies could be used for SCLC early detection. We created a risk prediction model using five autoantibodies with an average area under the curve of 0.84 for the three cohorts that improved to 0.96 by incorporating cigarette smoke consumption in pack years. Together, our findings provide an innovative approach to identify circulating autoantibodies in SCLC with mechanistic insight into disease-specific immunogenicity and clinical utility.
Keywords: Autoantibodies; Humans; Lung Neoplasms; Protein Processing, Post-Translational; Small Cell Lung Carcinoma

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Proteomic prediction of incident heart failure and its main subtypes. - Emilsson, Valur; Jonsson, Brynjolfur G; Austin, Thomas R; Gudmundsdottir, Valborg; Axelsson, Gisli T; Frick, Elisabet A; Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Loureiro, Joseph; Brody, Jennifer A; Aspelund, Thor; Launer, Lenore J; et al. (Eur J Heart Fail, 2023)
AIM: To examine the ability of serum proteins in predicting future heart failure (HF) events, including HF with reduced or preserved ejection fraction (HFrEF or HFpEF), in relation to event time, and with or without considering established HF-associated clinical variables. METHODS AND RESULTS: In the prospective population-based Age, Gene/Environment Susceptibility Reykjavik Study (AGES-RS), 440 individuals developed HF after their first visit with a median follow-up of 5.45 years. Among them, 167 were diagnosed with HFrEF and 188 with HFpEF. A least absolute shrinkage and selection operator regression model with nonparametric bootstrap were used to select predictors from an analysis of 4782 serum proteins, and several pre-established clinical parameters linked to HF. A subset of 8-10 distinct or overlapping serum proteins predicted different future HF outcomes, and C-statistics were used to assess discrimination, revealing proteins combined with a C-index of 0.80 for all incident HF, 0.78 and 0.80 for incident HFpEF or HFrEF, respectively. In the AGES-RS, protein panels alone encompassed the risk contained in the clinical information and improved the performance characteristics of prediction models based on NT-proBNP and clinical risk factors. Finally, the protein predictors performed particularly well close to the time of an HF event, an outcome that was replicated in the Cardiovascular Health Study (CHS). CONCLUSION: A small number of circulating proteins accurately predicted future HF in the AGES-RS cohort of older adults, and they alone encompass the risk information found in a collection of clinical data. Incident HF events were predicted up to eight years, with predictor performance significantly improving for events occurring less than one year ahead, a finding replicated in an external cohort study. This article is protected by copyright. All rights reserved.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

{Serum NfL and GFAP are associated with incident dementia and dementia mortality in older adults: The cardiovascular health study - é, H. T.; Liu, X.; Odden, M. C.; Moseholm, K. F.; Seshadri, S.; Satizabal, C. L.; Lopez, O. L.; Bis, J. C.; é, L.; Fohner, A. E.; Psaty, B. M.; Tracy, R. P.; et al. (Alzheimers Dement, 2023)
Circulating neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) have been independently associated with dementia risk. Their additive association, and their associations with dementia-specific mortality, have not been investigated.\ We associated serum NfL, GFAP, total tau ,and ubiquitin carboxyl-terminal hydrolase-L1, measured in 1712 dementia-free adults, with 19-year incident dementia and dementia-specific mortality risk, and with 3-year cognitive decline.\ 2.06 (1.60-2.67) and 9.22 (4.48-18.9). NfL was independently associated with accelerated cognitive decline.\ Circulating NfL and GFAP may, independently and jointly, provide useful clinical insight regarding dementia risk and prognosis.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

{Structural Variation Detection and Association Analysis of Whole-Genome-Sequence Data from 16,905 Alzheimer's Diseases Sequencing Project Subjects - Wang, H.; Dombroski, B. A.; Cheng, P. L.; Tucci, A.; Si, Y. Q.; Farrell, J. J.; Tzeng, J. Y.; Leung, Y. Y.; Malamon, J. S.; Wang, L. S.; Vardarajan, B. N.; Farrer, L. A.; et al. (medRxiv, 2023)
. We also identified 16 SVs associated with AD and 13 SVs associated with AD-related pathological/cognitive endophenotypes. Our findings demonstrate the broad impact of SVs on AD genetics.\ Alzheimer's disease, Structural variation, Copy number variation.

{Structural Variation Detection and Association Analysis of Whole-Genome-Sequence Data from 16,905 Alzheimer's Diseases Sequencing Project Subjects - Lee, W. P.; Wang, H.; Dombroski, B.; Cheng, P. L.; Tucci, A.; Si, Y. Q.; Farrell, J.; Tzeng, J. Y.; Leung, Y. Y.; Malamon, J.; Wang, L. S.; Vardarajan, B.; et al. (Res Sq, 2023)
. We also identified 16 SVs associated with AD and 13 SVs linked to AD-related pathological/cognitive endophenotypes. This study highlights the pivotal role of SVs in shaping our understanding of AD genetics.

Substitution of self-reported measures for objectively assessed grip strength and slow walk in the Physical Frailty Phenotype: ramifications for validity. - Bandeen-Roche, Karen; Tian, Jing; Buta, Brian; Walston, Jeremy; Xue, Qian-Li (BMC Geriatr, 2023)
BACKGROUND: Frailty assessment promises to identify older adults at risk for adverse consequences following stressors and target interventions to improve health outcomes. The Physical Frailty Phenotype (PFP) is a widely-studied, well validated assessment but incorporates performance-based slow walk and grip strength criteria that challenge its use in some clinical settings. Variants replacing performance-based elements with self-reported proxies have been proposed. Our study evaluated whether commonly available disability self-reports could be substituted for the performance-based criteria in the PFP while still identifying as "frail" the same subpopulations of individuals. METHODS: Parallel analyses were conducted in 3393 female and 2495 male Cardiovascular Health Study, Round 2 participants assessed in 1989-90. Candidate self-reported proxies for the phenotype's "slowness" and "weakness" criteria were evaluated for comparable prevalence and agreement by mode of measurement. For best-performing candidates: Frailty status (3 + positive criteria out of 5) was compared for prevalence and agreement between the PFP and mostly self-reported versions. Personal characteristics were compared between those adjudicated as frail by (a) only a self-reported version; (b) only the PFP; (c) both, using bivariable analyses and multinomial logistic regression. RESULTS: Self-reported difficulty walking ½ mile was selected as a proxy for the phenotype's slowness criterion. Two self-reported weakness proxies were examined: difficulty transferring from a bed or chair or gripping with hands, and difficulty as just defined or in lifting a 10-pound bag. Prevalences matched to within 4% between self-reported and performance-based criteria in the whole sample, but in all cases the self-reported prevalence for women exceeded that for men by 11% or more. Cross-modal agreement was moderate, with by-criterion and frailty-wide Kappa statistics of 0.55-0.60 in all cases. Frail subgroups (a), (b), (c) were independently discriminated (p < 0.05) by race, BMI, and depression in women; by age in men; and by self-reported health for both. CONCLUSIONS: Commonly used self-reported disability items cannot be assumed to stand in for performance-based criteria in the PFP. We found subpopulations identified as frail by resultant phenotypes versus the original phenotype to systematically differ. Work to develop self-reported proxies that more closely replicate their objective phenotypic counterparts than standard disability self-reports is needed.
Keywords: Advance Directives; Female; Frailty; Hand Strength; Humans; Male; Phenotype; Self Report

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Heon Kwak, Soo; Chen, Han; Li, Xihao; DiCorpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.

Vaccination Against Pneumonia May Provide Genotype-Specific Protection Against Alzheimer's Disease. - Ukraintseva, Svetlana; Duan, Matt; Simanek, Amanda M; Holmes, Rachel; Bagley, Olivia; Rajendrakumar, Aravind L; Yashkin, Arseniy P; Akushevich, Igor; Tropsha, Alexander; Whitson, Heather; Yashin, Anatoliy; Arbeev, Konstantin (J Alzheimers Dis, 2023)
Vaccine repurposing that considers individual genotype may aid personalized prevention of Alzheimer's disease (AD). In this retrospective cohort study, we used Cardiovascular Health Study data to estimate associations of pneumococcal polysaccharide vaccine and flu shots received between ages 65-75 with AD onset at age 75 or older, taking into account rs6859 polymorphism in NECTIN2 gene (AD risk factor). Pneumococcal vaccine, and total count of vaccinations against pneumonia and flu, were associated with lower odds of AD in carriers of rs6859 A allele, but not in non-carriers. We conclude that pneumococcal polysaccharide vaccine is a promising candidate for genotype-tailored AD prevention.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
Background Risk for venous thromboembolism has a strong genetic component. Whole genome sequencingfrom the Trans-Omics for Precision Medicine program allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. Methods The 3793 cases and 7834 controls (11.6% of cases were Black, Hispanic/Latino, or Asian American) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). Results Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). Conclusions Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.

Whole genome sequence analysis of apparent treatment resistant hypertension status in participants from the Trans-Omics for Precision Medicine program. - Armstrong, Nicole D; Srinivasasainagendra, Vinodh; Ammous, Farah; Assimes, Themistocles L; Beitelshees, Amber L; Brody, Jennifer; Cade, Brian E; Ida Chen, Yii-Der; Chen, Han; de Vries, Paul S; Floyd, James S; Franceschini, Nora; et al. (Front Genet, 2023)
Apparent treatment-resistant hypertension (aTRH) is characterized by the use of four or more antihypertensive (AHT) classes to achieve blood pressure (BP) control. In the current study, we conducted single-variant and gene-based analyses of aTRH among individuals from 12 Trans-Omics for Precision Medicine cohorts with whole-genome sequencing data. Cases were defined as individuals treated for hypertension (HTN) taking three different AHT classes, with average systolic BP ≥ 140 or diastolic BP ≥ 90 mmHg, or four or more medications regardless of BP ( = 1,705). A normotensive control group was defined as individuals with BP < 140/90 mmHg ( = 22,079), not on AHT medication. A second control group comprised individuals who were treatment responsive on one AHT medication with BP < 140/ 90 mmHg ( = 5,424). Logistic regression with kinship adjustment using the Scalable and Accurate Implementation of Generalized mixed models (SAIGE) was performed, adjusting for age, sex, and genetic ancestry. We assessed variants using SKAT-O in rare-variant analyses. Single-variant and gene-based tests were conducted in a pooled multi-ethnicity stratum, as well as self-reported ethnic/racial strata (European and African American). One variant in the known HTN locus, , was a top finding in the multi-ethnic analysis ( = 8.23E-07) for the normotensive control group [rs12476527, odds ratio (95% confidence interval) = 0.80 (0.74-0.88)]. This variant was replicated in the Vanderbilt University Medical Center's DNA repository data. Aggregate gene-based signals included the genes and . Additional work validating these loci in larger, more diverse populations, is warranted to determine whether these regions influence the pathobiology of aTRH.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-Genome Sequencing Analysis of Human Metabolome in Multi-Ethnic Populations. - Feofanova, Elena V; Brown, Michael R; Alkis, Taryn; Manuel, Astrid M; Li, Xihao; Tahir, Usman A; Li, Zilin; Mendez, Kevin M; Kelly, Rachel S; Qi, Qibin; Chen, Han; Larson, Martin G; et al. (Nat Commun, 2023)
Circulating metabolite levels may reflect the state of the human organism in health and disease, however, the genetic architecture of metabolites is not fully understood. We have performed a whole-genome sequencing association analysis of both common and rare variants in up to 11,840 multi-ethnic participants from five studies with up to 1666 circulating metabolites. We have discovered 1985 novel variant-metabolite associations, and validated 761 locus-metabolite associations reported previously. Seventy-nine novel variant-metabolite associations have been replicated, including three genetic loci located on the X chromosome that have demonstrated its involvement in metabolic regulation. Gene-based analysis have provided further support for seven metabolite-replicated loci pairs and their biologically plausible genes. Among those novel replicated variant-metabolite pairs, follow-up analyses have revealed that 26 metabolites have colocalized with 21 tissues, seven metabolite-disease outcome associations have been putatively causal, and 7 metabolites might be regulated by plasma protein levels. Our results have depicted the genetic contribution to circulating metabolite levels, providing additional insights into understanding human disease.
Keywords: Ethnicity; Genome-Wide Association Study; Humans; Metabolome; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Association analysis of mitochondrial DNA heteroplasmic variants: methods and application. - Sun, Xianbang; Bulekova, Katia; Yang, Jian; Lai, Meng; Pitsillides, Achilleas N; Liu, Xue; Zhang, Yuankai; Guo, Xiuqing; Yong, Qian; Raffield, Laura M; Rotter, Jerome I; Rich, Stephen S; et al. (medRxiv, 2024)
We rigorously assessed a comprehensive association testing framework for heteroplasmy, employing both simulated and real-world data. This framework employed a variant allele fraction (VAF) threshold and harnessed multiple gene-based tests for robust identification and association testing of heteroplasmy. Our simulation studies demonstrated that gene-based tests maintained an appropriate type I error rate at α=0.001. Notably, when 5% or more heteroplasmic variants within a target region were linked to an outcome, burden-extension tests (including the adaptive burden test, variable threshold burden test, and z-score weighting burden test) outperformed the sequence kernel association test (SKAT) and the original burden test. Applying this framework, we conducted association analyses on whole-blood derived heteroplasmy in 17,507 individuals of African and European ancestries (31% of African Ancestry, mean age of 62, with 58% women) with whole genome sequencing data. We performed both cohort- and ancestry-specific association analyses, followed by meta-analysis on bothpooled samples and within each ancestry group. Our results suggest that mtDNA-Enco ded genes/regions are likely to exhibit varying rates in somatic aging, with the notably strong associations observed between heteroplasmy in the and genes ( <0.001) and advance aging by the Original Burden test. In contrast, SKAT identified significant associations ( <0.001) between diabetes and the aggregated effects of heteroplasmy in several protein-coding genes. Further research is warranted to validate these findings. In summary, our proposed statistical framework represents a valuable tool for facilitating association testing of heteroplasmy with disease traits in large human populations.

Development and Validation of the American Heart Association's PREVENT Equations. - Khan, Sadiya S; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Surapaneni, Aditya; Blaha, Michael J; Carson, April P; Chang, Alexander R; Ciemins, Elizabeth; Go, Alan S; Gutierrez, Orlando M; et al. (Circulation, 2024)
BACKGROUND: Multivariable equations are recommended by primary prevention guidelines to assess absolute risk of cardiovascular disease (CVD). However, current equations have several limitations. Therefore, we developed and validated the American Heart Association Predicting Risk of CVD EVENTs (PREVENT) equations among US adults 30 to 79 years of age without known CVD. METHODS: The derivation sample included individual-level participant data from 25 data sets (N=3 281 919) between 1992 and 2017. The primary outcome was CVD (atherosclerotic CVD and heart failure). Predictors included traditional risk factors (smoking status, systolic blood pressure, cholesterol, antihypertensive or statin use, and diabetes) and estimated glomerular filtration rate. Models were sex-specific, race-free, developed on the age scale, and adjusted for competing risk of non-CVD death. Analyses were conducted in each data set and meta-analyzed. Discrimination was assessed using the Harrell C-statistic. Calibration was calculated as the slope of the observed versus predicted risk by decile. Additional equations to predict each CVD subtype (atherosclerotic CVD and heart failure) and include optional predictors (urine albumin-to-creatinine ratio and hemoglobin A1c), and social deprivation index were also developed. External validation was performed in 3 330 085 participants from 21 additional data sets. RESULTS: Among 6 612 004 adults included, mean±SD age was 53±12 years, and 56% were women. Over a mean±SD follow-up of 4.8±3.1 years, there were 211 515 incident total CVD events. The median C-statistics in external validation for CVD were 0.794 (interquartile interval, 0.763-0.809) in female and 0.757 (0.727-0.778) in male participants. The calibration slopes were 1.03 (interquartile interval, 0.81-1.16) and 0.94 (0.81-1.13) among female and male participants, respectively. Similar estimates for discrimination and calibration were observed for atherosclerotic CVD- and heart failure-specific models. The improvement in discrimination was small but statistically significant when urine albumin-to-creatinine ratio, hemoglobin A1c, and social deprivation index were added together to the base model to total CVD (ΔC-statistic [interquartile interval] 0.004 [0.004-0.005] and 0.005 [0.004-0.007] among female and male participants, respectively). Calibration improved significantly when the urine albumin-to-creatinine ratio was added to the base model among those with marked albuminuria (>300 mg/g; 1.05 [0.84-1.20] versus 1.39 [1.14-1.65]; =0.01). CONCLUSIONS: PREVENT equations accurately and precisely predicted risk for incident CVD and CVD subtypes in a large, diverse, and contemporary sample of US adults by using routinely available clinical variables.
Keywords: Adult; Aged; Albumins; American Heart Association; Atherosclerosis; Cardiovascular Diseases; Creatinine; Female; Glycated Hemoglobin; Heart Failure; Humans; Male; Middle Aged; Risk Assessment; Risk Factors

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

{Genetic associations with dementia-related proteinopathy: Application of item response theory - Katsumata, Y.; Fardo, D. W.; Shade, L. M. P.; Wu, X.; Karanth, S. D.; Hohman, T. J.; Schneider, J. A.; Bennett, D. A.; Farfel, J. M.; Gauthreaux, K.; Mock, C.; Kukull, W. A.; et al. (Alzheimers Dement, 2024)
Although dementia-related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.\ -synuclein, and TDP-43.\ -synuclein/Lewy bodies. Novel suggestive proteinopathy-linked alleles were also discovered, including several (SDHAF1, TMEM68, and ARHGEF28) with colocalization analyses and/or high degrees of biologic credibility.\ A novel methodology using GPCM enabled insights into gene candidates for driving misfolded proteinopathies.\ Latent factor scores for proteinopathies were estimated using a generalized partial credit model. The three latent continuous scores corresponded well with proteinopathy severity. Novel genes associated with proteinopathies were identified. Several genes had high degrees of biologic credibility for dementia risk factors.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

{Genome-wide association study of preserved ratio impaired spirometry (PRISm) - Higbee, D. H.; Lirio, A.; Hamilton, F.; Granell, R.; Wyss, A. B.; London, S. J.; Bartz, T. M.; Gharib, S. A.; Cho, M. H.; Wan, E.; Silverman, E.; Crapo, J. D.; et al. (Eur Respir J, 2024)
{0.70. PRISm is associated with respiratory symptoms and comorbidities. Our objective was to discover novel genetic signals for PRISm and see if they provide insight into the pathogenesis of PRISm and associated comorbidities.\ We undertook a genome-wide association study (GWAS) of PRISm in UK Biobank participants (Stage 1), and selected single nucleotide polymorphisms (SNPs) reaching genome-wide significance for replication in 13 cohorts (Stage 2). A combined meta-analysis of Stage 1 and Stage 2 was done to determine top SNPs. We used cross-trait linkage disequilibrium score regression to estimate genome-wide genetic correlation between PRISm and pulmonary and extrapulmonary traits. Phenome-wide association studies of top SNPs were performed.\ =0.12

The Gut Microbial Metabolite Trimethylamine N-oxide, Incident CKD, and Kidney Function Decline. - Wang, Meng; Tang, W H Wilson; Li, Xinmin S; de Oliveira Otto, Marcia C; Lee, Yujin; Lemaitre, Rozenn N; Fretts, Amanda; Nemet, Ina; Sotoodehnia, Nona; Sitlani, Colleen M; Budoff, Matthew; DiDonato, Joseph A; et al. (J Am Soc Nephrol, 2024)
BACKGROUND: Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite of dietary phosphatidylcholine and carnitine. Experimentally, TMAO causes kidney injury and tubulointerstitial fibrosis. Little is known about prospective associations between TMAO and kidney outcomes, especially incident CKD. We hypothesized that higher plasma TMAO levels would be associated with higher risk of incident CKD and greater rate of kidney function decline. METHODS: We included 10,564 participants from two community-based, prospective cohorts with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73m2 to assess incident CKD. TMAO was measured using targeted mass spectrometry at baseline and one follow-up visit. Creatinine and Cystatin C were measured up to 4 times during follow-up and used to compute eGFR. Incident CKD was defined as an eGFR decline ≥ 30% from baseline and a resulting eGFR<60 ml/min/1.73 m2. Time-varying Cox models assessed the association of serial TMAO measures with incident CKD, adjusting for sociodemographic, lifestyle, diet, and cardiovascular disease risk factors. Linear mixed models assessed the association with annualized eGFR change in 10,009 participants with at least one follow-up eGFR measure without exclusions for baseline eGFR levels. RESULTS: During a median follow-up of 9.4 years (interquartile range: 9.1-11.6 years), 979 incident CKD events occurred. Higher TMAO levels associated with higher risk of incident CKD (2nd to 5th vs. 1st quintile HR[95%CI]= 1.65 [1.22-2.23], 1.68 [1.26-2.25], 2.28 [1.72-3.02], and 2.24[1.68-2.98], respectively) and greater annualized eGFR decline ( 2nd to 5th vs. 1st quintile annualized eGFR change= -0.21 [-0.32, -0.09], -0.17 [-0.29, -0.05], -0.35 [-0.47, -0.22], and -0.43[-0.56, -0.30], respectively) with monotonic dose-response relationships. These associations were consistent across different racial/ethnic groups examined. The association with eGFR decline was similar to or larger than that seen for established CKD risk factors including diabetes, per 10 mmHg of higher systolic blood pressure, per 10 years of older age, and Black race. CONCLUSIONS: In community-based US adults, higher serial measures of plasma TMAO were associated with higher risk of incident CKD and greater annualized kidney function decline.

Large-scale circulating proteome association study (CPAS) meta-analysis identifies circulating proteins and pathways predicting incident hip fractures. - Austin, Thomas R; Fink, Howard A; Jalal, Diana I; Törnqvist, Anna E; Bůzková, Petra; Barzilay, Joshua I; Lu, Tianyuan; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Hveem, Kristian; Jonasson, Christian; et al. (J Bone Miner Res, 2024)
Hip fractures are associated with significant disability, high cost, and mortality. However, the exact biological mechanisms underlying susceptibility to hip fractures remain incompletely understood. In an exploratory search of the underlying biology as reflected through the circulating proteome, we performed a comprehensive Circulating Proteome Association Study (CPAS) meta-analysis for incident hip fractures. Analyses included 6430 subjects from two prospective cohort studies (Cardiovascular Health Study and Trøndelag Health Study) with circulating proteomics data (aptamer-based 5 K SomaScan version 4.0 assay; 4979 aptamers). Associations between circulating protein levels and incident hip fractures were estimated for each cohort using age and sex-adjusted Cox regression models. Participants experienced 643 incident hip fractures. Compared with the individual studies, inverse-variance weighted meta-analyses yielded more statistically significant associations, identifying 23 aptamers associated with incident hip fractures (conservative Bonferroni correction 0.05/4979, P < 1.0 × 10-5). The aptamers most strongly associated with hip fracture risk corresponded to two proteins of the growth hormone/insulin growth factor system (GHR and IGFBP2), as well as GDF15 and EGFR. High levels of several inflammation-related proteins (CD14, CXCL12, MMP12, ITIH3) were also associated with increased hip fracture risk. Ingenuity pathway analysis identified reduced LXR/RXR activation and increased acute phase response signaling to be overrepresented among those proteins associated with increased hip fracture risk. These analyses identified several circulating proteins and pathways consistently associated with incident hip fractures. These findings underscore the usefulness of the meta-analytic approach for comprehensive CPAS in a similar manner as has previously been observed for large-scale human genetic studies. Future studies should investigate the underlying biology of these potential novel drug targets.

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Nagarajan, Pavithra; Winkler, Thomas W; Bentley, Amy R; Miller, Clint L; Kraja, Aldi T; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael R; Morrison, John L; Giri, Ayush; O'Connell, Jeffrey R; et al. (medRxiv, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to genes involved in neurological, thyroidal, bone metabolism, and hematopoietic pathways. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausibility of distinct influences of both sleep duration extremes in cardiovascular health. With several of our loci reflecting specificity towards population background or sex, our discovery sheds light on the importance of embracing granularity when addressing heterogeneity entangled in gene-environment interactions, and in therapeutic design approaches for blood pressure management.

Large-Scale Proteomics Identifies Novel Biomarkers and Circulating Risk Factors for Aortic Stenosis. - Shelbaya, Khaled; Arthur, Victoria; Yang, Yimin; Dorbala, Pranav; Buckley, Leo; Claggett, Brian; Skali, Hicham; Dufresne, Line; Yang, Ta-Yu; Engert, James C; Thanassoulis, George; Floyd, James; et al. (J Am Coll Cardiol, 2024)
BACKGROUND: Limited data exist regarding risk factors for aortic stenosis (AS). The plasma proteome is a promising phenotype for discovery of novel biomarkers and potentially causative mechanisms. OBJECTIVES: The aim of this study was to discover novel biomarkers with potentially causal associations with AS. METHODS: We measured 4,877 plasma proteins (SomaScan aptamer-affinity assay) among ARIC (Atherosclerosis Risk In Communities) study participants in mid-life (visit 3 [V3]; n = 11,430; age 60 ± 6 years) and in late-life (V5; n = 4,899; age 76 ± 5 years). We identified proteins cross-sectionally associated with aortic valve (AV) peak velocity (AVmax) and dimensionless index by echocardiography at V5 and with incident AV-related hospitalization after V3 with the use of multivariable linear and Cox proportional hazard regression. We assessed associations of candidate proteins with changes in AVmax over 6 years and with AV calcification with the use of cardiac computed tomography, replicated analysis in an independent sample, performed Mendelian randomization, and evaluated gene expression in explanted human AV tissue. RESULTS: Fifty-two proteins cross-sectionally were associated with AVmax and dimensionless index at V5 and with risk of incident AV-related hospitalization after V3. Among 3,413 participants in the Cardiovascular Health Study, 6 of those proteins were significantly associated with adjudicated moderate or severe AS, including matrix metalloproteinase 12 (MMP12), complement C1q tumor necrosis factor-related protein 1 (C1QTNF1), and growth differentiation factor-15. MMP12 was also associated with greater increase in AVmax over 6 years, greater degree of AV calcification, and greater expression in calcific compared with normal or fibrotic AV tissue. C1QTNF1 had consistent potential causal effects on both AS and AVmax according to Mendelian randomization analysis. CONCLUSIONS: These findings identify MMP12 as a potential novel circulating biomarker of AS risk and C1QTNF1 as a new putative target to prevent AS progression.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Calcinosis; Humans; Matrix Metalloproteinase 12; Middle Aged; Proteomics; Risk Factors

Levels of procoagulant factors and peak thrombin generation in relation to dementia risk in older adults: The Cardiovascular Health Study. - Harrington, Laura B; Ehlert, Alexa N; Thacker, Evan L; Jenny, Nancy S; Lopez, Oscar; Cushman, Mary; Olson, Nels C; Fitzpatrick, Annette; Mukamal, Kenneth J; Jensen, Majken K (Thromb Res, 2024)
INTRODUCTION: Markers of hemostasis such as procoagulant factors and peak thrombin generation are associated with cardiovascular outcomes, but their associations with dementia risk are unclear. We aimed to evaluate prospective associations of selected procoagulant factors and peak thrombin generation with dementia risk. METHODS: We measured levels of 7 hemostatic factors (fibrinogen, factor VII coagulant activity [FVIIc], activated factor VII [FVIIa], factor VIIa-antithrombin [FVIIa-AT], factor XI antigen [FXI], peak thrombin generation, and platelet count) among participants in the Cardiovascular Health Study, a cohort of older adults free of dementia in 1992/1993 (n = 3185). Dementia was adjudicated and classified by DSM-IV criteria through 1998/1999. Cox proportional hazards models estimated hazard ratios (HRs) for any dementia associated with 1-standard deviation (SD) differences, adjusting for sociodemographic and clinical factors and APOE genotype. Secondary analyses separately evaluated the risk of vascular dementia, Alzheimer's disease, and mixed dementia. RESULTS: At baseline, participants had a median age of 73 years. Over 5.4 years of follow-up, we identified 448 dementia cases. There was no evidence of linear associations between levels of these hemostatic factors with any dementia risk (HRs per 1-SD difference ranged from 1.0 to 1.1; 95 % confidence intervals included 1.0). Results of secondary analyses by dementia subtype were similar. CONCLUSIONS: In this prospective study, there was no strong evidence of linear associations between levels of fibrinogen, FVIIc, FVIIa, FVIIa-AT, FXI, peak thrombin generation, or platelet count with dementia risk. Despite their associations with cardiovascular disease, higher levels of these biomarkers measured among older adults may not reflect dementia risk.
Keywords: Aged; Anticoagulants; Antithrombin III; Antithrombins; Dementia; Factor VIIa; Fibrinogen; Hemostatics; Humans; Prospective Studies; Thrombin

Methylation patterns associated with C-reactive protein in racially and ethnically diverse populations. - Lundin, Jessica I; Peters, Ulrike; Hu, Yao; Ammous, Farah; Avery, Christy L; Benjamin, Emelia J; Bis, Joshua C; Brody, Jennifer A; Carlson, Chris; Cushman, Mary; Gignoux, Chris; Guo, Xiuqing; et al. (Epigenetics, 2024)
Systemic low-grade inflammation is a feature of chronic disease. C-reactive protein (CRP) is a common biomarker of inflammation and used as an indicator of disease risk; however, the role of inflammation in disease is not completely understood. Methylation is an epigenetic modification in the DNA which plays a pivotal role in gene expression. In this study we evaluated differential DNA methylation patterns associated with blood CRP level to elucidate biological pathways and genetic regulatory mechanisms to improve the understanding of chronic inflammation. The racially and ethnically diverse participants in this study were included as 50% White, 41% Black or African American, 7% Hispanic or Latino/a, and 2% Native Hawaiian, Asian American, American Indian, or Alaska Native (total  = 13,433) individuals. We replicated 113 CpG sites from 87 unique loci, of which five were novel (, , and cg03282312), across a discovery set of 1,150 CpG sites associated with CRP level ( < 1.2E-7). The downstream pathways affected by DNA methylation included the identification of and CpG-gene transcript pairs which contributed to the innate immune response gene enrichment pathway along with , , and . Gene enrichment analysis also identified the nuclear factor-kappaB transcription pathway. Using two-sample Mendelian randomization (MR) we inferred methylation at three CpG sites as causal for CRP levels using both White and Black or African American MR instrument variables. Overall, we identified novel CpG sites and gene transcripts that could be valuable in understanding the specific cellular processes and pathogenic mechanisms involved in inflammation.
Keywords: C-Reactive Protein; CpG Islands; DNA; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Inflammation; Intracellular Signaling Peptides and Proteins

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins